AAV-Delivered Antibody Mediates Significant Protective Effects against SIVmac239 Challenge in the Absence of Neutralizing Activity - Fuchs, Sebastian; Martinez-Navio, Jose M.; Piatak, Michael; Lifson, Jeffrey D.; Gao, Guangping; Desrosiers, Ronald C. (PLoS Pathogens, 2015)
Long-term delivery of potent broadly-neutralizing antibodies is a promising approach for the prevention of HIV-1 infection. We used AAV vector intramuscularly to deliver anti-SIV monoclonal antibodies (mAbs) in IgG1 form to rhesus monkeys. Persisting levels of delivered mAb as high as 270 ?g/ml were achieved. However, host antibody responses to the delivered antibody were observed in 9 of the 12 monkeys and these appeared to limit the concentration of delivered antibody that could be achieved. This is reflected in the wide range of delivered mAb concentrations that were achieved: 1-270 ?g/ml. Following repeated, marginal dose, intravenous challenge with the difficult-to-neutralize SIVmac239, the six monkeys in the AAV-5L7 IgG1 mAb group showed clear protective effects despite the absence of detectable neutralizing activity against the challenge virus. The protective effects included: lowering of viral load at peak height; lowering of viral load at set point; delay in the time to peak viral load from the time of the infectious virus exposure. All of these effects were statistically significant. In addition, the monkey with the highest level of delivered 5L7 mAb completely resisted six successive SIVmac239 i.v. challenges, including a final challenge with a dose of 10 i.v. infectious units. Our results demonstrate the continued promise of this approach for the prevention of HIV-1 infection in people. However, the problem of anti-antibody responses will need to be understood and overcome for the promise of this approach to be effectively realized.
EVALuna2:8298

A Barcoded Flow Cytometric Assay to Explore the Antibody Responses Against SARS-CoV-2 Spike and Its Variants - Vesper, Niklas; Ortiz, Yaneth; Bartels-Burgahn, Frauke; Yang, Jianying; De La Rosa, Kathrin; Tenbusch, Matthias; Schulz, Sebastian; Finzel, Stephanie; Jäck, Hans-Martin; Eibel, Hermann; Voll, Reinhard E.; Reth, Michael (Frontiers in Immunology, 2021)
The SARS-CoV-2 pandemic has spread to all parts of the world and can cause life-threatening pneumonia and other severe disease manifestations known as COVID-19. This health crisis has resulted in a significant effort to stop the spread of this new coronavirus. However, while propagating itself in the human population, the virus accumulates mutations and generates new variants with increased fitness and the ability to escape the human immune response. Here we describe a color-based barcoded spike flow cytometric assay (BSFA) that is particularly useful to evaluate and directly compare the humoral immune response directed against either wild type (WT) or mutant spike (S) proteins or the receptor-binding domains (RBD) of SARS-CoV-2. This assay employs the human B lymphoma cell line Ramos, transfected for stable expression of WT or mutant S proteins or a chimeric RBD-CD8 fusion protein. We find that the alpha and beta mutants are more stably expressed than the WT S protein on the Ramos B cell surface and/or bind with higher affinity to the viral entry receptor ACE2. However, we find a reduce expression of the chimeric RBD-CD8 carrying the point mutation N501Y and E484K characteristic for the alpha and beta variant, respectively. The comparison of the humoral immune response of 12 vaccinated probands with 12 COVID-19 patients shows that after the boost, the S-specific IgG class immune response in the vaccinated group is similar to that of the patient group. However, in comparison to WT the specific IgG serum antibodies bind less well to the alpha variant and only poorly to the beta variant S protein. This is in line with the notion that the beta variant is an immune escape variant of SARS-CoV-2. The IgA class immune response was more variable than the IgG response and higher in the COVID-19 patients than in the vaccinated group. In summary, we think that our BSFA represents a useful tool to evaluate the humoral immunity against emerging variants of SARS-CoV-2 and to analyze new vaccination protocols against these variants.
CRIS-Team Scopus Importer:2021-10-22
Keywords: coronavirus; COVID-19; flow cytometry; humoral immunity; RBD; SARS-CoV-2; spike protein; virus variants

Access to new highly potent antileukemia, antiviral and antimalarial agents via hybridization of natural products (homo)egonol, thymoquinone and artemisinin - Capci Karagöz, Aysun; Reiter, Christoph; Seo, Ean-Jeong; Gruber, Lisa; Hahn, Friedrich; Leidenberger, Maria; Klein, Volker; Hampel, Frank; Friedrich, Oliver; Marschall, Manfred; Kappes, Bärbel; Efferth, Thomas; et al. (Bioorganic & Medicinal Chemistry, 2018)
Hybridization of natural products has high potential to further improve their activities and may produce synergistic effects between linked pharmacophores. Here we report synthesis of nine new hybrids of natural products egonol, homoegonol, thymoquinone and artemisinin and evaluation of their activities against P. falciparum 3D7 parasites, human cytomegalovirus, sensitive and multidrug-resistant human leukemia cells. Most of the new hybrids exceed their parent compounds in antimalarial, antiviral and antileukemia activities and in some cases show higher in vitro efficacy than clinically used reference drugs chloroquine, ganciclovir and doxorubicin. Combined, our findings stress the high potency of these hybrids and encourages further use of the hybridization concept in applied pharmacological research.
EVALuna2:35269

A clinician's plea to test glioma patients for CMV - Goerig, Nicole; Frey, Benjamin; Überla, Klaus; Gaipl, Udo; Fietkau, Rainer (Neuro-Oncology, 2017)
EVALuna2:32871

A conserved Eph family receptor-binding motif on the gH/gL complex of Kaposi's sarcoma-associated herpesvirus and rhesus monkey rhadinovirus - Grosskopf, Anna K.; Enßer, Armin; Neipel, Frank; Jungnickl, Doris; Schlagowski, Sarah; Desrosiers, Ronald C.; Hahn, Alexander S. (PLoS Pathogens, 2018)
Kaposi's sarcoma-associated herpesvirus (KSHV) is a human oncogenic virus associated with Kaposi's sarcoma and two B-cell malignancies. The rhesus monkey rhadinovirus (RRV) is a virus of nonhuman primates that is closely related to KSHV. Eph family receptor tyrosine kinases (Ephs) are cellular receptors for the gH/gL glycoprotein complexes of both KSHV and RRV. Through sequence analysis and mutational screens, we identified conserved residues in the N-terminal domain of KSHV and RRV glycoprotein H that are critical for Eph-binding in vitro. Homology-based structural predictions of the KSHV and RRV gH/gL complexes based on the Epstein-Barr-Virus gH/gL crystal structure located these amino acids in a beta-hairpin on gH, which is likely stabilized by gL and is optimally positioned for protein-protein interactions. Guided by these predictions, we generated recombinant RRV and KSHV strains mutated in the conserved motif as well as an RRV gL null mutant. Inhibition experiments using these mutants confirmed that disruption of the identified Eph-interaction motif or of gL expression resulted in complete detargeting from Ephs. However, all mutants were infectious on all cell types tested, exhibiting normal attachment but a reduction in infectivity of up to one log order of magnitude. While Eph-binding-negative RRV mutants were replication-competent on fibroblasts, their infectivity was comparatively more reduced on endothelial cells with a substantial subpopulation of endothelial cells remaining resistant to infection. Together, this provides evidence for a cell type-specific use of Ephs by RRV. Furthermore, our results demonstrate that gL is dispensable for infection by RRV. Its deletion caused a reduction in infectivity similar to that observed after mutation of Eph-binding residues in gH. Our findings would be compatible with an ability of KSHV and RRV to use other, less efficient entry mediators in lieu of Ephs, although these host factors may not be uniformly expressed by all cells.
EVALuna2:35289

Active monitoring of adverse reactions following COVID-19 and other vaccinations: a feasibility study as part of the CoVaKo project - Zeschick, Nikoletta; Warkentin, Lisette; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Hueber, Susann; Sebastiao, Maria (Pilot and Feasibility Studies, 2022)
Background: The Corona-Vakzin-Konsortium project (CoVaKo) analyses the efficacy and safety of COVID-19 vaccines in a real-world setting, as well as breakthrough infections in Bavaria, Germany. A subproject of CoVaKo aims to identify adverse reactions of the COVID-19 vaccine and compare these to adverse reactions of other vaccines in an online survey. In a preceding feasibility study, the study materials were tested for comprehensibility, visual design, and motivation to participate, as well as for their ability to be implemented and carried out in primary care practices and vaccination centres. Methods: We used a mixed-methods research design. First, three focus groups consisting of general population participants were organised to evaluate the study materials and survey. Second, a test roll-out was conducted in vaccination centres and primary care practices that involved implementing and quantitatively evaluating the online survey. Third, interviews were conducted with participating general practitioners and heads of vaccination centres four weeks after the test roll-out. Results: Parts of the information and registration form proved incomprehensible, specifically regarding the recruitment material and/or online survey. For example, headings were misleading given that, relative to other vaccinations, the COVID-19 vaccination was overemphasised in the title. Participants requested additional information regarding the procedure and completion time. Within 31 days, 2199 participants, who received either a COVID-19 vaccination (99%) or at least one of the control vaccinations (1%), registered for the study. Participants (strongly) agreed that the registration process was easy to understand, that the completion time was reasonable, and that the technical setup was straightforward. Physicians and heads of the vaccination centres perceived the study as easy to integrate into their workflow. The majority expressed willingness to participate in the main study. Conclusions: Our study indicated that identifying and documenting adverse reactions following vaccinations using an online survey is feasible. Testing materials and surveys provided valuable insight, enabling subsequent improvements. Participation from health professionals proved essential in ensuring the practicality of procedures. Lastly, adapting the study’s organisation to external fluctuating structures and requirements confirmed necessary for a successful implementation, especially due to dynamic changes in the nation’s COVID-19 vaccination strategies. Trial registration: The trial was retrospectively registered at the “Deutsches Register Klinischer Studien” (DRKS-ID: DRKS00025881) on Oct 14, 2021.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Adverse reactions; COVID-19; General practitioners; Healthcare staff; Online survey; Vaccination; Vaccination centres

Adenoviral Vector DNA- and SARS-CoV-2 mRNA-Based Covid-19 Vaccines: Possible Integration into the Human Genome - Are Adenoviral Genes Expressed in Vector-based Vaccines? - Doerfler, Walter (Virus Research, 2021)
Vigorous vaccination programs against SARS-CoV-2-causing Covid-19 are the major chance to fight this dreadful pandemic. The currently administered vaccines depend on adenovirus DNA vectors or on SARS-CoV-2 mRNA that might become reverse transcribed into DNA, however infrequently. In some societies, people have become sensitized against the potential short- or long-term side effects of foreign DNA being injected into humans. In my laboratory, the fate of foreign DNA in mammalian (human) cells and organisms has been investigated for many years. In this review, a summary of the results obtained will be presented. This synopsis has been put in the evolutionary context of retrotransposon insertions into pre-human genomes millions of years ago. In addition, studies on adenovirus vector-based DNA, on the fate of food-ingested DNA as well as the long-term persistence of SARS-CoV-2 RNA/DNA will be described. Actual integration of viral DNA molecules and of adenovirus vector DNA will likely be chance events whose frequency and epigenetic consequences cannot with certainty be assessed. The review also addresses problems of remaining adenoviral gene expression in adenoviral-based vectors and their role in side effects of vaccines. Eventually, it will come down to weighing the possible risks of genomic insertions of vaccine-associated foreign DNA and unknown levels of vector-carried adenoviral gene expression versus protection against the dangers of Covid-19. A decision in favor of vaccination against life-threatening disease appears prudent. Informing the public about the complexities of biology will be a reliable guide when having to reach personal decisions about vaccinations.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Adenovirus DNA integration into mammalian genomes; adenovirus vector DNA & RNA-based SARS-CoV-2 vaccines; adenovirus vector DNA integration into human genome; epigenetic consequences of foreign DNA integration; expression of adenoviral genes in vector DNA; retrotranscription of SARS-CoV-2 RNA into DNA

Adenoviruses using the cancer marker EphA2 as a receptor in vitro and in vivo by genetic ligand insertion into different capsid scaffolds - Behr, Michael; Kaufmann, Johanna K.; Ketzer, Patrick; Engelhardt, Sarah; Mueck-Hauesl, Martin; Okun, Pamela M.; Petersen, Gabriele; Neipel, Frank; Hassel, Jessica C.; Ehrhardt, Anja; Enk, Alexander H.; Nettelbeck, Dirk M. (PLoS ONE, 2014)
Adenoviral gene therapy and oncolysis would critically benefit from targeted cell entry by genetically modified capsids. This requires both the ablation of native adenovirus tropism and the identification of ligands that remain functional in virus context. Here, we establish cell type-specific entry of HAdV-5-based vectors by genetic ligand insertion into a chimeric fiber with shaft and knob domains of the short HAdV-41 fiber (Ad5T/41sSK). This fiber format was reported to ablate transduction in vitro and biodistribution to the liver in vivo. We show that the YSA peptide, binding to the pan-cancer marker EphA2, can be inserted into three positions of the chimeric fiber, resulting in strong transduction of EphA2-positive but not EphA2-negative cells of human melanoma biopsies and of tumor xenografts after intratumoral injection. Transduction was blocked by soluble YSA peptide and restored for EphA2-negative cells after recombinant EphA2 expression. The YSA peptide could also be inserted into three positions of a CAR binding-ablated HAdV-5 fiber enabling specific transduction; however, the Ad5T/41sSK format was superior in vivo. In conclusion, we establish an adenovirus capsid facilitating functional insertion of targeting peptides and a novel adenovirus using the tumor marker EphA2 as receptor with high potential for cancer gene therapy and viral oncolysis.
EVALuna2:8240

A DNA Vaccine Encoding the Gn Ectodomain of Rift Valley Fever Virus Protects Mice via a Humoral Response Decreased by DEC205 Targeting - Chrun, Tiphany; Lacote, Sandra; Urien, Celine; Richard, Charles-Adrien; Tenbusch, Matthias; Aubrey, Nicolas; Pulido, Coralie; Lakhdar, Latifa; Marianneau, Philippe; Schwartz-Cornil, Isabelle (Frontiers in Immunology, 2019)
The Rift Valley fever virus (RVFV) is responsible for a serious mosquito-borne viral disease in humans and ruminants. The development of a new and safer vaccine is urgently needed due to the risk of introduction of this arbovirus into RVFV-free continents. We recently showed that a DNA vaccine encoding eGn, the ectodomain of the RVFV Gn glycoprotein, conferred a substantial protection in the sheep natural host and that the anti-eGn IgG levels correlated to protection. Addressing eGn to DEC205 reduced the protective efficacy while decreasing the antibody and increasing the IFN gamma T cell responses in sheep. In order to get further insight into the involved mechanisms, we evaluated our eGn-encoding DNA vaccine strategy in the reference mouse species. A DNA vaccine encoding eGn induced full clinical protection in mice and the passive transfer of immune serum was protective. This further supports that antibodies, although non-neutralizing in vitro, are instrumental in the protection against RVFV. Addressing eGn to DEC205 was also detrimental to protection in mice, and in this species, both the antibody and the IFN gamma T cell responses were strongly decreased. Conversely when using a plasmid encoding a different antigen, i.e., mCherry, DEC205 targeting promoted the antibody response. Altogether our results show that the outcome of targeting antigens to DEC205 depends on the species and on the fused antigen and is not favorable in the case of eGn. In addition, we bring evidences that eGn in itself is a pertinent antigen to be included in a DNA vaccine and that next developments should aim at promoting the anti-eGn antibody response.
CRIS-Team WoS Importer:2019-05-03

A dopaminergic mechanism of antipsychotic drug efficacy, failure, and failure reversal: the role of the dopamine transporter - Amato, Davide; Canneva, Fabio; Cumming, Paul; Maschauer, Simone; Groos, Dominik; Dahlmanns, Jana Katharina; Grömer, Teja W.; Chiofalo, Lisa; Dahlmanns, Marc; Zheng, Fang; Kornhuber, Johannes; Prante, Olaf; et al. (Molecular Psychiatry, 2018)
Antipsychotic drugs are effective interventions in schizophrenia. However, the efficacy of these agents often decreases over time, which leads to treatment failure and symptom recurrence. We report that antipsychotic efficacy in rat models declines in concert with extracellular striatal dopamine levels rather than insufficient dopamine D2 receptor occupancy. Antipsychotic efficacy was associated with a suppression of dopamine transporter activity, which was reversed during failure. Antipsychotic failure coincided with reduced dopamine neuron firing, which was not observed during antipsychotic efficacy. Synaptic field responses in dopamine target areas declined during antipsychotic efficacy and showed potentiation during failure. Antipsychotics blocked synaptic vesicle release during efficacy but enhanced this release during failure. We found that the pharmacological inhibition of the dopamine transporter rescued antipsychotic drug treatment outcomes, supporting the hypothesis that the dopamine transporter is a main target of antipsychotic drugs and predicting that dopamine transporter blockers may be an adjunct treatment to reverse antipsychotic treatment failure.
EVALuna2:35828

Advantages and limitations of integrated flagellin adjuvants for HIV-based nanoparticle B-cell vaccines - Barnowski, Cornelia; Kadzioch, Nicole; Damm, Dominik; Yan, Huimin; Temchura, Vladimir (Pharmaceutics, 2019)
The great advantage of virus-like particle (VLP) nano-vaccines is their structural identity to wild-type viruses, ensuring that antigen-specific B-cells encounter viral proteins in their natural conformation. “Wild-type” viral nanoparticles can be further genetically or biochemically functionalized with biomolecules (antigens and adjuvants). Flagellin is a potent inducer of innate immunity and it has demonstrated adjuvant effectiveness due to its affinity for toll-like receptor 5 (TLR5). In contrast to most TLR ligands, flagellin is a protein and can induce an immune response against itself. To avoid side-effects, we incorporated a less inflammatory and less immunogenic form of flagellin as an adjuvant into HIV-based nanoparticle B-cell-targeting vaccines that display either the HIV-1 envelope protein (Env) or a model antigen, hen egg lysozyme (HEL). While flagellin significantly enhanced HEL-specific IgG responses, anti-Env antibody responses were suppressed. We demonstrated that flagellin did not activate B-cells directly in vitro, but might compete for CD4+ T-cell help in vivo. Therefore, we hypothesize that in the context of VLP-based B-cell nano-vaccines, flagellin serves as an antigen itself and may outcompete a less immunogenic antigen with its antibody response. In contrast, in combination with a strong immunogen, the adjuvant activity of flagellin may dominate over its immunogenicity.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Adjuvant; B-cell targeting; Flagellin; HIV-based VLP; Nano-vaccines

A gB/CD3 bispecific BiTE antibody construct for targeting Human Cytomegalovirus-infected cells - Brey, Charlotte U.; Proff, Julia; Teufert, Natascha; Salzer, Benjamin; Brozy, Johannes; Muenz, Markus; Pendzialek, Jochen; Enßer, Armin; Holter, Wolfgang; Lehner, Manfred (Scientific Reports, 2018)
Bispecific T cell engager (BiTE) antibody constructs are successfully used as cancer therapeutics. We hypothesized that this treatment strategy could also be applicable for therapy of human cytomegalovirus (HCMV) infection, since HCMV-encoded proteins are abundantly expressed on the surface of infected cells. Here we show that a BiTE antibody construct directed against HCMV glycoprotein B (gB) and CD3 efficiently triggers T cells to secrete IFN-gamma and TNF upon co-culture with fibroblasts infected with HCMV strain AD169, Towne or Toledo. Titration of gB expression levels in non-infected cells confirmed that already low levels of gB are sufficient for efficient triggering of T cells in presence of the BiTE antibody construct. Comparison of redirecting T cells with the bispecific antibody versus a chimeric antigen receptor (CAR) based on the same scFv showed a similar sensitivity for gB expression. Although lysis of infected target cells was absent, the BiTE antibody construct inhibited HCMV replication by triggering cytokine production. Notably, even strongly diluted supernatants of the activated T cells efficiently blocked the replication of HCMV in infected primary fibroblasts. In summary, our data prove the functionality of the first BiTE antibody construct targeting an HCMV-encoded glycoprotein for inhibiting HCMV replication in infected cells.
EVALuna2:35260

A Genetically Encoded Dark-to-Bright Biosensor for Visualisation of Granzyme-Mediated Cytotoxicity - Bednar, Christopher; Kübel, Sabrina; Cordsmeier, Arne; Scholz, Brigitte; Menschikowski, Hanna; Enßer, Armin (International Journal of Molecular Sciences, 2023)
Granzyme B (GZMB) is a key enzyme released by cytotoxic T lymphocytes (CTL) and natural killer (NK) cells to induce apoptosis in target cells. We designed a novel fluorogenic biosensor which is able to assess GZMB activity in a specific and sensitive manner. This cleavage-responsive sensor for T cell activity level (CRSTAL) is based on a fluorescent protein that is only activated upon cleavage by GZMB or caspase-8. CRSTAL was tested in stable cell lines and demonstrated a strong and long-lasting fluorescence signal upon induction with GZMB. It can detect GZMB activity not only by overexpression of GZMB in target cells but also following transfer of GZMB and perforin from effector cells during cytotoxicity. This feature has significant implications for cancer immunotherapy, particularly in monitoring the efficacy of chimeric antigen receptor (CAR)-T cells. CAR-T cells are a promising therapy option for various cancer types, but monitoring their activity in vivo is challenging. The development of biosensors like CRSTAL provides a valuable tool for monitoring of CAR-T cell activity. In summary, CRSTAL is a highly sensitive biosensor that can detect GZMB activity in target cells, providing a means for evaluating the cytotoxic activity of immune cells and monitoring T cell activity in real time.
CRIS-Team Scopus Importer:2023-09-22
Keywords: CAR-T cells; fluorogenic biosensor; granzyme B; T cell cytotoxicity

A glutaminyl cyclase-catalyzed α-synuclein modification identified in human synucleinopathies - Hartlage-Rübsamen, Maike; Bluhm, Alexandra; Moceri, Sandra; Machner, Lisa; Köppen, Janett; Schenk, Mathias; Hilbrich, Isabel; Holzer, Max; Weidenfeller, Martin; Richter, Franziska; Coras, Roland; Serrano, Geidy E.; et al. (Acta Neuropathologica, 2021)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder that is neuropathologically characterized by degeneration of dopaminergic neurons of the substantia nigra (SN) and formation of Lewy bodies and Lewy neurites composed of aggregated α-synuclein. Proteolysis of α-synuclein by matrix metalloproteinases was shown to facilitate its aggregation and to affect cell viability. One of the proteolysed fragments, Gln79-α-synuclein, possesses a glutamine residue at its N-terminus. We argue that glutaminyl cyclase (QC) may catalyze the pyroglutamate (pGlu)79-α-synuclein formation and, thereby, contribute to enhanced aggregation and compromised degradation of α-synuclein in human synucleinopathies. Here, the kinetic characteristics of Gln79-α-synuclein conversion into the pGlu-form by QC are shown using enzymatic assays and mass spectrometry. Thioflavin T assays and electron microscopy demonstrated a decreased potential of pGlu79-α-synuclein to form fibrils. However, size exclusion chromatography and cell viability assays revealed an increased propensity of pGlu79-α-synuclein to form oligomeric aggregates with high neurotoxicity. In brains of wild-type mice, QC and α-synuclein were co-expressed by dopaminergic SN neurons. Using a specific antibody against the pGlu-modified neo-epitope of α-synuclein, pGlu79-α-synuclein aggregates were detected in association with QC in brains of two transgenic mouse lines with human α-synuclein overexpression. In human brain samples of PD and dementia with Lewy body subjects, pGlu79-α-synuclein was shown to be present in SN neurons, in a number of Lewy bodies and in dystrophic neurites. Importantly, there was a spatial co-occurrence of pGlu79-α-synuclein with the enzyme QC in the human SN complex and a defined association of QC with neuropathological structures. We conclude that QC catalyzes the formation of oligomer-prone pGlu79-α-synuclein in human synucleinopathies, which may—in analogy to pGlu-Aβ peptides in Alzheimer’s disease—act as a seed for pathogenic protein aggregation.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Animal models; Dementia with Lewy bodies; Glutaminyl cyclase; Parkinson’s disease; Post-translational modification; Substantia nigra; α-Synuclein

A highly potent trimeric derivative of artesunate shows promising treatment profiles in experimental models for congenital HCMV infection in vitro and ex vivo - Jacquet, Chloé; Marschall, Manfred; Andouard, Déborah; El Hamel, Charhazed; Chianea, Thierry; Tsogoeva, Svetlana; Hantz, Sébastien; Alain, Sophie (Antiviral Research, 2020)
CRIS-Team Scopus Importer:2020-02-04

Alcohol-sourced acetate impairs T cell function by promoting cortactin acetylation - Azizov, Vugar; Hübner, Michel; Frech, Michael; Hofmann, Jörg; Kubankova, Marketa; Lapuente, Dennis; Tenbusch, Matthias; Guck, Jochen; Schett, Georg; Zaiss, Mario (iScience, 2023)
Alcohol is among the most widely consumed dietary substances. Excessive alcohol consumption damages the liver, heart, and brain. Alcohol also has strong immunoregulatory properties. Here, we report how alcohol impairs T cell function via acetylation of cortactin, a protein that binds filamentous actin and facilitates branching. Upon alcohol consumption, acetate, the metabolite of alcohol, accumulates in lymphoid organs. T cells exposed to acetate, exhibit increased acetylation of cortactin. Acetylation of cortactin inhibits filamentous actin binding and hence reduces T cell migration, immune synapse formation and activation. While mutated, acetylation-resistant cortactin rescues the acetate-induced inhibition of T cell migration, primary mouse cortactin knockout T cells exhibited impaired migration. Acetate-induced cytoskeletal changes effectively inhibited activation, proliferation, and immune synapse formation in T cells in vitro and in vivo in an influenza infection model in mice. Together these findings reveal cortactin as a possible target for mitigation of T cell driven autoimmune diseases.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Immunology; Molecular biology

Alpha synuclein processing by MMP-3 – implications for synucleinopathies - Bluhm, Alexandra; Schrempel, Sarah; Moceri, Sandra; Stieler, Jens; Feja, Malte; Schilling, Stephan; Schulze, Anja; von Hörsten, Stephan; Hartlage-Rübsamen, Maike; Richter, Franziska; Roßner, Steffen (Behavioural Brain Research, 2022)
α-Synuclein (aSyn) is a protein implicated in physiological functions such as neurotransmitter release at the synapse and the regulation of gene expression in the nucleus. In addition, pathological aSyn assemblies are characteristic for a class of protein aggregation disorders referred to as synucleinopathies, where aSyn aggregates appear as Lewy bodies and Lewy neurites or as glial cytoplasmic inclusions. We recently discovered a novel post-translational pyroglutamate (pGlu) modification at Gln79 of N-truncated aSyn that promotes oligomer formation and neurotoxicity in human synucleinopathies. A priori, the appearance of pGlu79-aSyn in vivo involves a two-step process of free N-terminal Gln79 residue generation and subsequent cyclization of Gln79 into pGlu79. Prime candidate enzymes for these processes are matrix metalloproteinase-3 (MMP-3) and glutaminyl cyclase (QC). Here, we analyzed the expression of aSyn, MMP-3, QC and pGlu79-aSyn in brains of two transgenic mouse models for synucleinopathies (BAC-SNCA and ASO) by triple immunofluorescent labellings and confocal laser scanning microscopy. We report a co-localization of these proteins in brain structures typically affected by aSyn pathology, namely hippocampus in BAC-SNCA mice and substantia nigra in ASO mice. In addition, Western blot analyses revealed a high abundance of QC, MMP-3 and transgenic human aSyn in brain stem and thalamus but lower levels in cortex/hippocampus, whereas endogenous mouse aSyn was found to be most abundant in cortex/hippocampus, followed by thalamus and brain stem. During aging of ASO mice, we observed no differences between controls and transgenic mice in MMP-3 levels but higher QC content in thalamus of 6-month-old transgenic mice. Transgenic human aSyn abundance transiently increased and then showed decrease in oldest ASO mice analyzed. Immunohistochemistry revealed a successive increase in intraneuronal and extracellular formation of pGlu79-aSyn in substantia nigra during aging of ASO mice. Together, our data are supportive for a role of MMP-3 and QC in the generation of pGlu79-aSyn in brains affected by aSyn pathology.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Glutaminyl cyclase; Matrix metalloproteinase-3; Pyroglutamate modification; Substantia nigra; Transgenic mouse models; α-synuclein

Alterations in miRNA expression patterns in whole blood of OSCC patients - Ries, Jutta; Vairaktaris, Eleftherios; Kintopp, Rita; Baran, Christoph; Neukam, Friedrich Wilhelm; Nkenke, Emeka (In Vivo, 2014)
Aberrant microRNA (miRNA) expression in blood of cancer patients is a common finding. The present study aimed at evaluating the differences in miRNA expression in whole blood samples of oral squamous cell carcinoma (OSCC) patients compared to healthy controls.Microarray based miRNA profiling was performed on whole blood samples of 20 OSCC patients and 20 healthy volunteers and the differences in expression patterns between the two groups were evaluated. The results were validated by Reverse Transcription quantitative-Polymerase Chain Reaction (RT-qPCR) in 50 OSCC patients and 35 volunteers.21 miRNAs were identified to be significantly differentially expressed in whole blood of OSCC patients compared to healthy controls. The impact of miR-186 (p=0.002), miR-494 (p=0.001) and miR-3651 (p=0.0001) could be validated by RT-qPCR.The aberrant expressions of miR-186, miR-494 and miR-3651 in whole blood of OSCC patients may serve as the basis for establishing minimally-invasive screening methods for OSCC based on miRNAs as biomarkers.
EVALuna2:24185

Alterations of Immune Cells By Large B Cell Lymphoma Persist Years after Achieving Complete Remission and Correlate with Impaired Adaptive Immunity - Pelzl, Richard; Kübel, Sabrina; Klein, Paulina; Gsottberger, Franziska; Wendland, Kerstin; Petkovic, Srdjan; Brueckl, Valeska; Baur, Rebecca; Völkl, Simon; Mackensen, Andreas; Nganou-Makamdop, Krystelle; Müller, Fabian (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Alternative NF-kappa B Signaling Discriminates Induction of the Tumor Marker Fascin by the Viral Oncoproteins Tax-1 and Tax-2 of Human T-Cell Leukemia Viruses - Heym, Stefanie; Mohr, Caroline; Engelbrecht, Hanna C.; Fleckenstein, Bernhard; Thoma-Kreß, Andrea (Cancers, 2022)
Simple Summary:& nbsp;The actin-bundling protein Fascin is upregulated in many types of cancers, including adult T-cell leukemia/lymphoma, a tumor induced by the oncogenic retrovirus human T-cell leukemia virus type 1 (HTLV-1). Transcriptional regulation of Fascin is heterogeneous between different cell types and tissues, and Fascin is usually expressed at low levels in T-cells. We have previously shown that a single viral oncoprotein, Tax-1 of HTLV-1, is a potent inducer of Fascin in T-cells depending on classical NF-kappa B signaling. In this study, we discovered that transcriptional activation of Fascin by viral oncoproteins depends on activity of both the classical and the alternative NF-kappa B signaling cascade. Comparisons between Tax-1 and Tax-2 from the closely related but non-oncogenic HTLV-2 revealed that alternative NF-kappa B signaling discriminates transcriptional induction of Fascin by the Tax proteins encoded by HTLVs. Together, Tax-1 and Tax-2 proteins are useful tools to study oncogenic signaling in T-cells.& nbsp;Transcriptional regulation of the actin-bundling protein and tumor marker Fascin is highly diverse depending on cell and tumor type. Previously, we discovered that the viral oncoprotein Tax-1 of human T-cell leukemia virus type 1 (HTLV-1) considerably enhances Fascin expression in T-cells, depending on classical NF-kappa B signaling. In this study, we asked if the non-oncogenic Tax-2 of the related HTLV-2 is still able to induce Fascin by using luciferase assays, immunoblot, and qPCR. We found that Tax-2 only slightly induces Fascin expression compared to Tax-1; however, both Tax-1 and Tax-2 comparably activated a 1.6 kb fragment in the human Fascin promoter including Tax-responsive elements. Furthermore, we identified a link between Tax-induced activity of the alternative NF-kappa B pathway and Fascin induction. While treatment with the second mitochondria-derived activator of caspases (SMAC)-mimetic AZD5582, a compound known to robustly activate alternative NF-kappa B signaling, did not induce Fascin, combination of AZD5582 with activation of classical NF-kappa B signaling by Tax-2 significantly induced Fascin expression. In conclusion, our data demonstrate that both classical and alternative NF-kappa B activity are necessary for strong Fascin induction by the viral Tax oncoproteins, thus, shedding new light on the regulation of Fascin in T-cells and during viral transformation.
CRIS-Team WoS Importer:2022-03-11
Keywords: Fascin; tumor virus; HTLV-1; human T-cell leukemia virus type 1; alternative NF-κB; viral oncoprotein; Tax-1; Tax-2

A molecular model for the differential activation of STAT3 and STAT6 by the herpesviral oncoprotein tip - Mazumder, Eman Dey; Jardin, Christophe; Vogel, Benjamin; Heck, Elke; Scholz, Brigitte; Lengenfelder, Doris; Sticht, Heinrich; Enßer, Armin (PLoS ONE, 2012)
Constitutive STAT signaling provides growth promoting signals in many forms of malignancy. We performed molecular modeling and molecular dynamics studies of the interaction between the regulatory Src homology 2 (SH2) domains of STAT3 and 6 with phosphorylated peptides of the herpesviral oncoprotein Tip, which facilitates Src kinase mediated STAT-activation and T cell proliferation. The studies give insight into the ligand binding specificity of the STAT SH2 domains and provide the first model for the differential activation of STAT3 or STAT6 by two distinct regions of the viral Tip protein. The biological relevance of the modeled interactions was then confirmed by activation studies using corresponding recombinant oncoproteins, and finally by respective recombinant viruses. The functional data give experimental validation of the molecular dynamics study, and provide evidence for the involvement of STAT6 in the herpesvirus induced T cell proliferation.
EVALuna2:8146

Amyloid-beta peptides trigger aggregation of alpha-synuclein in vitro - Köppen, Janett; Schulze, Anja; Machner, Lisa; Wermann, Michael; Eichentopf, Rico; Guthardt, Max; Hähnel, Angelika; Klehm, Jessica; Kriegeskorte, Marie Christin; Hartlage-Rübsamen, Maike; Morawski, Markus; von Hörsten, Stephan; et al. (Molecules, 2020)
Alzheimer’s disease (AD) and Parkinson’s disease (PD), including dementia with Lewy bodies (DLB), account for the majority of dementia cases worldwide. Interestingly, a significant number of patients have clinical and neuropathological features of both AD and PD, i.e., the presence of amyloid deposits and Lewy bodies in the neocortex. The identification of α-synuclein peptides in amyloid plaques in DLB brain led to the hypothesis that both peptides mutually interact with each other to facilitate neurodegeneration. In this article, we report the influence of Aβ(1–42) and pGlu-Aβ(3–42) on the aggregation of α-synuclein in vitro. The aggregation of human recombinant α-synuclein was investigated using thioflavin-T fluorescence assay. Fibrils were investigated by means of antibody conjugated immunogold followed by transmission electron microscopy (TEM). Our data demonstrate a significantly increased aggregation propensity of α-synuclein in the presence of minor concentrations of Aβ(1–42) and pGlu-Aβ(3–42) for the first time, but without effect on toxicity on mouse primary neurons. The analysis of the composition of the fibrils by TEM combined with immunogold labeling of the peptides revealed an interaction of α-synuclein and Aβ in vitro, leading to an accelerated fibril formation. The analysis of kinetic data suggests that significantly enhanced nucleus formation accounts for this effect. Additionally, co-occurrence of α-synuclein and Aβ and pGlu-Aβ, respectively, under pathological conditions was confirmed in vivo by double immunofluorescent labelings in brains of aged transgenic mice with amyloid pathology. These observations imply a cross-talk of the amyloid peptides α-synuclein and Aβ species in neurodegeneration. Such effects might be responsible for the co-occurrence of Lewy bodies and plaques in many dementia cases.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Alpha-synuclein (α-synuclein); Alzheimer’s disease; Amyloid-beta (Aβ); Dementia with Lewy bodies; Parkinson’s disease

Analysis of SARS-CoV-2 Spike Protein Variants with Recombinant Reporter Viruses Created from a Bacmid System - Cordsmeier, Arne; Jungnickl, Doris; Herrmann, Alexandra; Korn, Klaus; Enßer, Armin (International Journal of Molecular Sciences, 2023)
SARS-CoV-2, the causative agent of COVID-19, has spread around the world with more than 700 million cases and 6.8 million deaths. Various variants of concern (VoC) have emerged due to mutations and recombination and concurrent selection for increased viral fitness and immune evasion. The viral protein that primarily determines the pathogenicity, infectivity, and transmissibility is the Spike protein. To analyze the specific impact of variant Spike proteins on infection dynamics, we constructed SARS-CoV-2 with a uniform B.1 backbone but with alternative Spike proteins. In addition, ORF6 was replaced by EYFP as a biological safety measure, and for use of this well-established reporter. We show that namely the delta variant Spike proteins cause a distinct phenotype from the wild type (B.1, D614G) and other variants of concern. Furthermore, we demonstrate that the omicron BA.1 Spike results in lower viral loads and a less efficient spread in vitro. Finally, we utilized viruses with the two different reporters EYFP and mCherry to establish a competitive growth assay, demonstrating that most but not all Spike variant viruses were able to outcompete wild type SARS-CoV-2 B.1.
CRIS-Team Scopus Importer:2023-05-26
Keywords: SARS-CoV-2; Spike protein; variants of concern

An antiviral targeting strategy based on the inducible interference with cytomegalovirus nuclear egress complex - Kicuntod, Jintawee; Häge, Sigrun; Lösing, Josephine; Kopar, Serli; Muller, Yves; Marschall, Manfred (Antiviral Research, 2023)
The nucleocytoplasmic capsid egress of herpesviruses like the human cytomegalovirus (HCMV) is based on a uniquely regulated process. The core nuclear egress complex (NEC) of HCMV, represented by the pUL50–pUL53 heterodimer, is able to oligomerize and thus to build hexameric lattices. Recently, we and others validated the NEC as a novel target for antiviral strategies. So far, the experimental targeting approaches included the development of NEC-directed small molecules, cell-penetrating peptides and NEC-directed mutagenesis. Our postulate states that an interference with the hook-into-groove interaction of pUL50–pUL53 prevents NEC formation and strictly limits viral replication efficiency. Here, we provide an experimental proof-of-concept of the antiviral strategy: the inducible intracellular expression of a NLS-Hook-GFP construct exerted a pronounced level of antiviral activity. The data provide evidence for the following points: (i) generation of a primary fibroblast population with inducible NLS-Hook-GFP expression showed nuclear localization of the construct, (ii) interaction between NLS-Hook-GFP and the viral core NEC was found specific for cytomegaloviruses but not for other herpesviruses, (iii) construct overexpression exerted a strong antiviral activity against three strains of HCMV, (iv) confocal imaging demonstrated the interference with NEC nuclear rim formation in HCMV-infected cells, and (v) quantitative nuclear egress assay confirmed the block of viral nucleocytoplasmic transition and, consequently, an inhibitory effect onto viral cytoplasmic virion assembly complex (cVAC). Combined, data confirmed that the specific interference with protein-protein interaction of the HCMV core NEC represents an efficient antiviral targeting strategy.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Antiviral proof-of-concept; Cytomegalovirus infection; Efficient interference with viral replication; Hook-into-groove principle; Inducible NLS-Hook-GFP expression; Major human pathogen; Novel drug targeting options; Nuclear egress-based antiviral strategy

Angiographic C-arm CT visualization of the Woven EndoBridge cerebral aneurysm embolization device (WEB): first experience in an animal aneurysm model - Struffert, Tobias; Lang, Sabine; Adamek, Edyta; Engelhorn, Tobias; Strother, C. M.; Dörfler, Arnd (Clinical Neuroradiology, 2014)
Improvements in the imaging capabilities of angiographic C-arm computed tomography (CT) using flat detector angiographic (FD-CT) systems now provide a means for the in vivo visualization of devices used for the treatment of intracranial aneurysms. One such device, the WEB embolization device, is made of a braided mesh of nitinol wires, the size of which are near to the limits of visualization using conventional x-ray fluoroscopy. Our hypothesis was that the imaging of these implants C-arm CT would provide useful information regarding their positioning and deployment.In five New Zealand white rabbits elastase induced aneurysms were created and subsequently treated using a WEB. Imaging was performed using digital subtraction angiography (DSA), X-ray imaging and two different Angiographic C-arm CT protocols. The images were evaluated by two neuroradiologists using an evaluation scale.The mesh of the WEB was barely visible on the DSA or x-ray fluoroscopy images. Volume rendering technique (VRT) reconstruction and multiplanar reconstruction (MPR) of images done using the C-arm CT protocols clearly delineated the shape and structure of the device. Contrast-enhanced MPR and VRT reconstructions allowed assessment of the status of blood flow in the aneurysms. Beam hardening artifacts caused by platinum markers on the WEB were present.In vivo C-arm CT imaging of the WEB is feasible and allows precise determination of the position and deployment status of the device. On contrast-enhanced images the occlusion status of aneurysms and the positioning of the WEB in relationship to the parent artery can be evaluated. C-arm-CT may serve as a minimal-invasive follow-up imaging modality.
EVALuna2:22996

A Noncanonical Function of Polycomb Repressive Complexes Promotes Human Cytomegalovirus Lytic DNA Replication and Serves as a Novel Cellular Target for Antiviral Intervention - Svrlanska, Adriana; Reichel, Anna; Schilling, Eva-Maria; Scherer, Myriam; Stamminger, Thomas; Reuter, Nina (Journal of Virology, 2019)
Chromatin-based modifications of herpesviral genomes play a crucial role in dictating the outcome of infection. Consistent with this, host cell multiprotein complexes, such as polycomb repressive complexes (PRCs), were proposed to act as epigenetic regulators of herpesviral latency. In particular, PRC2 has recently been shown to contribute to the silencing of human cytomegalovirus (HCMV) genomes. Here, we identify a novel proviral role of PRC1 and PRC2, the two main polycomb repressive complexes, during productive HCMV infection. Western blot analyses revealed strong HCMV-mediated upregulation of RING finger protein 1B (RING1B) and B lymphoma Moloney murine leukemia virus insertion region 1 homolog (BMI1) as well as of enhancer of zeste homolog 2 (EZH2), suppressor of zeste 12 (SUZ12), and embryonic ectoderm development (EED), which constitute the core components of PRC1 and PRC2, respectively. Furthermore, we observed a relocalization of PRC components to viral replication compartments, whereas histone modifications conferred by the respective PRCs were specifically excluded from these sites. Depletion of individual PRC1/PRC2 proteins by RNA interference resulted in a significant reduction of newly synthesized viral genomes and, in consequence, a decreased release of viral particles. Furthermore, accelerated native isolation of protein on nascent DNA (aniPOND) revealed a physical association of EZH2 and BMI1 with nascent HCMV DNA, suggesting a direct contribution of PRC proteins to viral DNA replication. Strikingly, substances solely inhibiting the enzymatic activity of PRC1/2 did not exert antiviral effects, while drugs affecting the abundance of PRC core components strongly compromised HCMV genome synthesis and particle release. Taken together, our data reveal an enzymatically independent, noncanonical function of both PRC1 and PRC2 during HCMV DNA replication, which may serve as a novel cellular target for antiviral therapy.
CRIS-Team WoS Importer:2019-05-03

A novel CDK7 inhibitor of the Pyrazolotriazine class exerts broad-spectrum antiviral activity at nanomolar concentrations - Hutterer, Corina; Eickhoff, Jan; Milbradt, Jens; Korn, Klaus; Zeitträger, Isabel; Bahsi, Hanife; Wagner, Sabrina; Zischinsky, Gunther; Wolf, Alexander; Degenhart, Carsten; Unger, Anke; Baumann, Matthias; et al. (Antimicrobial Agents and Chemotherapy, 2015)
Protein kinases represent central and multifunctional regulators of a balanced virus-host interaction. Cyclin-dependent protein kinase 7 (CDK7) plays crucial regulatory roles in cell cycle and transcription, both connected with the replication of many viruses. Previously, we developed a CDK7 inhibitor, LDC4297, that inhibits CDK7 in vitro in the nano-picomolar range. Novel data from a kinome-wide evaluation (>330 kinases profiled in vitro) demonstrate a kinase selectivity. Importantly, we provide first evidence for the antiviral potential of the CDK7 inhibitor LDC4297, i.e., in exerting a block of the replication of human cytomegalovirus (HCMV) in primary human fibroblasts at nanomolar concentrations (50% effective concentration, 24.5 ± 1.3 nM). As a unique feature compared to approved antiherpesviral drugs, inhibition occurred already at the immediate-early level of HCMV gene expression. The mode of antiviral action was considered multifaceted since CDK7-regulated cellular factors that are supportive of HCMV replication were substantially affected by the inhibitors. An effect of LDC4297 was identified in the interference with HCMV-driven inactivation of retinoblastoma protein (Rb), a regulatory step generally considered a hallmark of herpesviral replication. In line with this finding, a broad inhibitory activity of the drug could be demonstrated against a selection of human and animal herpesviruses and adenoviruses, whereas other viruses only showed intermediate drug sensitivity. Summarized, the CDK7 inhibitor LDC4297 is a promising candidate for further antiviral drug development, possibly offering new options for a comprehensive approach to antiviral therapy.
EVALuna2:8274

A novel positive feedback-loop between the HTLV-1 oncoprotein Tax and NF-κB activity in T-cells - Millen, Sebastian; Meretuk, Lina; Göttlicher, Tim; Schmitt, Sonja; Fleckenstein, Bernhard; Thoma-Kreß, Andrea (Retrovirology, 2020)
BACKGROUND: Human T-cell leukemia virus type 1 (HTLV-1) infects primarily CD4+ T-lymphocytes and evoques severe diseases, predominantly Adult T-Cell Leukemia/ Lymphoma (ATL/L) and HTLV-1-associated Myelopathy/ Tropical Spastic Paraparesis (HAM/TSP). The viral transactivator of the pX region (Tax) is important for initiating malignant transformation, and deregulation of the major signaling pathway nuclear factor of kappa B (NF-κB) by Tax represents a hallmark of HTLV-1 driven cancer. RESULTS: Here we found that Tax mutants which are defective in NF-κB signaling showed diminished protein expression levels compared to Tax wildtype in T-cells, whereas Tax transcript levels were comparable. Strikingly, constant activation of NF-κB signaling by the constitutive active mutant of inhibitor of kappa B kinase (IKK2, IKK-β), IKK2-EE, rescued protein expression of the NF-κB defective Tax mutants M22 and K1-10R and even increased protein levels of Tax wildtype in various T-cell lines while Tax transcript levels were only slightly affected. Using several Tax expression constructs, an increase of Tax protein occurred independent of Tax transcripts and independent of the promoter used. Further, Tax and M22 protein expression were strongly enhanced by 12-O-Tetradecanoylphorbol-13-Acetate [TPA; Phorbol 12-myristate 13-acetate (PMA)]/ ionomycin, inducers of NF-κB and cytokine signaling, but not by tumor necrosis factor alpha (TNF-α). On the other hand, co-expression of Tax with a dominant negative inhibitor of κB, IκBα-DN, or specific inhibition of IKK2 by the compound ACHP, led to a vast decrease in Tax protein levels to some extent independent of Tax transcripts in transiently transfected and Tax-transformed T-cells. Cycloheximide chase experiments revealed that co-expression of IKK2-EE prolongs the half-life of M22, and constant repression of NF-κB signaling by IκBα-DN strongly reduces protein stability of Tax wildtype suggesting that NF-κB activity is required for Tax protein stability. Finally, protein expression of Tax and M22 could be recovered by NH4Cl and PYR-41, inhibitors of the lysosome and the ubiquitin-activating enzyme E1, respectively. CONCLUSIONS: Together, these findings suggest that Tax's capability to induce NF-κB is critical for protein expression and stabilization of Tax itself. Overall, identification of this novel positive feedback loop between Tax and NF-κB in T-cells improves our understanding of Tax-driven transformation.
CRIS-Team Scopus Importer:2020-09-25
Keywords: HTLV-1; IKK2; M22; NF-κB; Protein stability; Tax-1

A novel strain-specific neutralizing epitope on glycoprotein H of human cytomegalovirus - Thomas, Marco; Kropff, Barbara; Schneider, Andrea; Winkler, Thomas; Görzer, Irene; Sticht, Heinrich; Britt, William J.; Mach, Michael; Reuter, Nina (Journal of Virology, 2021)
Human cytomegalovirus (HCMV) is a ubiquitous pathogen that causes severe clinical disease in immunosuppressed patients and congenitally infected newborn infants. Viral envelope glycoproteins represent attractive targets for vaccination or passive immunotherapy. To extend the knowledge of mechanisms of virus neutralization, monoclonal antibodies (MAbs) were generated following immunization of mice with HCMV virions. Hybridoma supernatants were screened for in vitro neutralization activity, yielding three potent MAbs, 6E3, 3C11, and 2B10. MAbs 6E3 and 3C11 blocked infection of all viral strains that were tested, while MAb 2B10 neutralized only 50% of the HCMV strains analyzed. Characterization of the MAbs using indirect immunofluorescence analyses demonstrated their reactivity with recombinantly derived gH. While MAbs 6E3 and 3C11 reacted with gH when expressed alone, 2B10 detected gH only when it was coexpressed with gB and gL. Recognition of gH by 3C11 was dependent on the expression of the entire ectodomain of gH, whereas 6E3 required residues 1 to 629 of gH. The strain-specific determinant for neutralization by Mab 2B10 was identified as a single Met!Ile amino acid polymorphism within gH, located within the central part of the protein. The polymorphism is evenly distributed among described HCMV strains. The 2B10 epitope thus represents a novel strain-specific antibody target site on gH of HCMV. The dependence of the reactivity of 2B10 on the simultaneous presence of gB/gH/gL will be of value in the structural definition of this tripartite complex. The 2B10 epitope may also represent a valuable tool for diagnostics to monitor infections/reinfections with different HCMV strains during pregnancy or after transplantation. IMPORTANCE HCMV infections are life threatening to people with compromised or immature immune systems. Understanding the antiviral antibody repertoire induced during HCMV infection is a necessary prerequisite to define protective antibody responses. Here, we report three novel anti-gH MAbs that potently neutralized HCMV infectivity. One of these MAbs (2B10) targets a novel strain-specific conformational epitope on gH that only becomes accessible upon coexpression of the minimal fusion machinery gB/gH/gL. Strain specificity is dependent on a single amino acid polymorphism within gH. Our data highlight the importance of strain-specific neutralizing antibody responses against HCMV. The 2B10 epitope may also represent a valuable tool for diagnostics to monitor infections/reinfections with different HCMV strains during pregnancy or after transplantation. In addition, the dependence of the reactivity of 2B10 on the simultaneous presence of gB/gH/gL will be of value in the structural definition of this tripartite complex.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Glycoprotein H; Herpesviruses; Human cytomegalovirus; Neutralizing antibodies

A Novel Window into Angiogenesis — Intravital Microscopy in the AV-Loop-Model - Vaghela, Ravikumar; Arkudas, Andreas; Gage, Daniel; Körner, Carolin; von Hörsten, Stephan; Salehi, Sahar; Horch, Raymund E.; Hessenauer, Maximilian (Cells, 2023)
Due to the limitations of current in vivo experimental designs, our comprehensive knowledge of vascular development and its implications for the development of large-scale engineered tissue constructs is very limited. Therefore, the purpose of this study was to develop unique in vivo imaging chambers that allow the live visualization of cellular processes in the arteriovenous (AV) loop model in rats. We have developed two different types of chambers. Chamber A is installed in the skin using the purse sting fixing method, while chamber B is installed subcutaneously under the skin. Both chambers are filled with modified gelatin hydrogel as a matrix. Intravital microscopy (IVM) was performed after the injection of fluorescein isothiocyanate (FITC)-labeled dextran and rhodamine 6G dye. The AV loop was functional for two weeks in chamber A and allowed visualization of the leukocyte trafficking. In chamber B, microvascular development in the AV loop could be examined for 21 days. Quantification of the microvascular outgrowth was performed using Fiji-ImageJ. Overall, by combining these two IVM chambers, we can comprehensively understand vascular development in the AV loop tissue engineering model¯.
CRIS-Team Scopus Importer:2023-02-03
Keywords: arteriovenous loop; GelMA; intravital microscopy; tissue engineering

Antibody Cross-Reactivity between Porcine Cytomegalovirus (PCMV) and Human Herpesvirus-6 (HHV-6) - Fiebig, Uwe; Holzer, Angela; Ivanusic, Daniel; Plotzki, Elena; Hengel, Hartmut; Neipel, Frank; Denner, Joachim (Viruses, 2017)
Porcine cytomegalovirus (PCMV) infection is widely prevalent among pigs, and PCMV is one of the viruses which may be transmitted during xenotransplantation using pig cells, tissues, or organs. While human cytomegalovirus (HCMV) is a major risk factor for allotransplantation, it is still unclear whether PCMV is able to infect human cells or pose a risk for xenotransplantation. Previously, it was shown that transmission of PCMV after pig kidney to non-human primate transplantations resulted in a significantly reduced survival time of the transplanted organ. To detect PCMV, PCR-based and immunological methods were used. Screening of pigs by Western blot analyses using recombinant viral proteins revealed up to 100% of the tested animals to be infected. When the same method was applied to screen human sera for PCMV-reactive antibodies, positive Western blot results were obtained in butchers and workers in the meat industry as well as in normal blood donors. To exclude an infection of humans with PCMV, the sera were further investigated. PCMV is closely related to human herpesvirus-6 (HHV-6) and human herpesvirus-7 (HHV-7), and a sequence alignment of glycoprotein B suggests that the antibodies may cross-react with identical epitope sequences. HCMV is not related with PCMV, and no correlation between antibody reactivity against PCMV and HCMV was detected. These data indicate that antibodies against PCMV found in humans are cross-reactive antibodies against HHV-6.
EVALuna2:33749

Anticancer activities of parthenolide in primary effusion lymphoma preclinical models - Karam, Louna; Abou Staiteieh, Soumaiah; Chaaban, Rady; Hayar, Berthe; Ismail, Bassel; Neipel, Frank; Darwiche, Nadine; Abou Merhi, Raghida (Molecular Carcinogenesis, 2021)
The sesquiterpene lactone parthenolide is a major component of the feverfew medicinal plant, Tanacetum parthenium. Parthenolide has been extensively studied for its anti-inflammatory and anticancer properties in several tumor models. Parthenolide's antitumor activities depend on several mechanisms but it is mainly known as an inhibitor of the nuclear factor-κB (NF-κB) pathway. This pathway is constitutively activated and induces cell survival in primary effusion lymphoma (PEL), a rare aggressive AIDS-related lymphoproliferative disorder that is commonly caused by the human herpesvirus 8 (HHV-8) infection. The aim of this study is to evaluate the targeted effect of Parthenolide both in vitro and in vivo. Herein, parthenolide significantly inhibited cell growth, induced G0/G1 cell cycle arrest, and induced massive apoptosis in PEL cells and ascites. In addition, parthenolide inhibited the NF-ĸB pathway suppressing IĸB phosphorylation and p65 nuclear translocation. It also reduced the expression of the DNA methylase inhibitor (DNMT1). Parthenolide induced HHV-8 lytic gene expression without inhibiting latent viral gene expression. Importantly, DMAPT, the more soluble parthenolide prodrug, promoted delay in ascites development and prolonged the survival of PEL xenograft mice. This study supports the therapeutic use of parthenolide in PEL and encourages its further clinical development.
CRIS-Team Scopus Importer:2021-06-18
Keywords: apoptosis; NF-ĸB; NOD/SCID mice; parthenolide; primary effusion lymphoma

Antigen-dependent modulation of immune responses to antigen-Fc fusion proteins by Fc-effector functions - Richel, Elie; Wagner, Jannik; Klessing, Stephan; Di Vincenzo, Riccardo; Temchura, Vladimir; Überla, Klaus (Frontiers in Immunology, 2023)
Background: Fc-fusion proteins have been successfully developed for therapeutic purposes, but are also a promising platform for the fast generation and purification of immunogens capable of inducing strong humoral immune responses in preclinical immunization studies. As the Fc-portion of immunoglobulins fused to an antigen confers functional properties of the parental antibody, such as dimerization, binding to Fc-receptors and complement activation, several studies reported that Fc-fusion proteins elicit stronger antigen-specific antibody responses than the unfused antigen. However, dimerization or half-life extension of an antigen have also been described to enhance immunogenicity. Methods: To explore the role of Fc-effector functions for the immunogenicity of fusions proteins of viral glycoproteins and Fc fragments, the HIV-1 gp120 and the RBD of SARS-CoV-2 were fused to the wild type muIgG2a Fc fragment or mutants with impaired (LALA-PG) or improved (GASDIE) Fc-effector functions. Results: Immunization of BALB/c mice with DNA vaccines encoding gp120 – Fc LALA-PG induced significantly higher antigen-specific antibody responses than gp120 – Fc WT and GASDIE. In contrast, immunization with DNA vaccines encoding the RBD fused to the same Fc mutants, resulted in comparable anti-RBD antibody levels and similar neutralization activity against several SARS-CoV-2 variants. Conclusion: Depending on the antigen, Fc-effector functions either do not modulate or suppress the immunogenicity of DNA vaccines encoding Fc-antigen fusion proteins.
CRIS-Team Scopus Importer:2023-11-03
Keywords: DNA immunization; Fc-effector functions; Fc-fusion proteins; HIV; mice; SARS-CoV-2

Anti-SARS-CoV-2 Inhibitory Profile of New Quinoline Compounds in Cell Culture-Based Infection Models - Herrmann, Lars; Hahn, Friedrich; Wangen, Christina; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2021)
The presently ongoing pandemic of human SARS-CoV-2 infections (COVID-19) presents an enormous challenge in surveillance, vaccine and antiviral drug development. Here we report the synthesis of new bioactive quinoline-morpholine hybrid compounds and their virological evaluation, which proves pronounced cell culture-based inhibitory profile against SARS-CoV-2. Thus, selected quinoline compounds may suggest specific hit-to-lead development.
CRIS-Team WoS Importer:2022-01-07

Antitumor activity of the synthetic retinoid ST1926 on primary effusion lymphoma in vitro and in vivo models - Karam, Louna; Houshaymi, Bilal; Abdel-Samad, Rana; Jaafar, Mariam; Halloum, Iman; Pisano, Claudio; Neipel, Frank; Darwiche, Nadine; Abou Merhi, Raghida (Oncology Reports, 2018)
Primary effusion lymphoma (PEL) is a rare B-cell neoplasm, associated with Kaposi sarcoma-associated herpes virus/human herpes virus-8 (KSHV/HHV-8), arising as malignant effusions in body cavities. PEL cells do not harbor conventional genetic cancer mutations; however, their oncogenesis is mainly attributed to HHV-8 latent genes. Treatment strategies are inefficient resulting in poor prognosis of PEL patients, stressing the need for new effective therapy. ST1926 is a synthetic retinoid with favorable antitumor properties and no cross-resistance with the natural retinoid, all-trans retinoic acid. ST1926 has shown potent apoptotic activities on a variety of solid tumors and hematologic malignancies in in vitro and in vivo models. In the present study we elucidated the antitumor activities and underlying molecular mechanism of ST1926 using in vitro, ex vivo, and in vivo PEL preclinical models. ST1926, at sub-micromolar concentrations, displayed potent antiproliferative effects on PEL cell lines and malignant ascites. Furthermore, ST1926 treatment of PEL cells and ascites resulted in their accumulation in the sub-G1 region, S phase cell cycle arrest, early DNA damage, PARP cleavage and p53 activation including the upregulation of its target genes p21 and Bax. However, ST1926 did not significantly modulate HHV-8 latent viral transcripts. Importantly, ST1926 delayed formation of ascites and enhanced survival of PEL mice. These results highlight the therapeutic potential of ST1926 in combination with drugs that target HHV-8 in PEL patients.
EVALuna2:35290

Antiviral effects of artesunate on JC polyomavirus replication in COS-7 cells - Sharma, Biswa Nath; Marschall, Manfred; Rinaldo, Christine Hanssen (Antimicrobial Agents and Chemotherapy, 2014)
The human JC polyomavirus (JCPyV) causes the fatal demyelinating disease progressive multifocal leukoencephalopathy (PML). A growing number of patients with induced or acquired immunosuppression are at risk for infection, and no effective antiviral therapy is presently available. The widely used antimalarial drug artesunate has shown broad antiviral activity in vitro but limited clinical success. The aim of this study was to investigate the effect of artesunate on JCPyV replication in vitro. The permissivity for JCPyV MAD-4 was first compared in four cell lines, and the monkey kidney cell line COS-7 was selected. Artesunate caused a concentration-dependent decrease in the extracellular JCPyV DNA load 96 h postinfection, with a 50% effective concentration (EC50) of 2.9 ?M. This effect correlated with a decreased expression of capsid protein VP1 and a reduced release of infectious viral progeny. For concentrations of <20 ?M, transient reductions in cellular DNA replication and proliferation were seen, while for higher concentrations, some cytotoxicity was detected. A selective index of 16.6 was found when cytotoxicity was calculated based on cellular DNA replication in the mock-infected cells, but interestingly, cellular DNA replication in the JCPyV-infected cells was more strongly affected. In conclusion, artesunate is efficacious in inhibiting JCPyV replication at micromolar concentrations, which are achievable in plasma. The inhibition at EC50 probably reflects an effect on cellular proteins and involves transient cytostatic effects. Our results, together with the favorable distribution of the active metabolite dihydroartemisinin to the central nervous system, suggest a potential use for artesunate in patients with PML.
EVALuna2:8233

Antiviral effects of artesunate on polyomavirus BK replication in primary human kidney cells - Sharma, Biswa Nath; Marschall, Manfred; Henriksen, Stian; Rinaldo, Christine Hanssen (Antimicrobial Agents and Chemotherapy, 2014)
Polyomavirus BK (BKV) causes polyomavirus-associated nephropathy (PyVAN) and hemorrhagic cystitis (PyVHC) in renal and bone marrow transplant patients, respectively. Antiviral drugs with targeted activity against BKV are lacking. Since the antimalarial drug artesunate was recently demonstrated to have antiviral activity, the possible effects of artesunate on BKV replication in human primary renal proximal tubular epithelial cells (RPTECs), the host cells in PyVAN, were explored. At 2 h postinfection (hpi), RPTECs were treated with artesunate at concentrations ranging from 0.3 to 80 ?M. After one viral replication cycle (approximately 72 hpi), the loads of extracellular BKV DNA, reflecting viral progeny production, were reduced in a concentration-dependent manner. Artesunate at 10 ?M reduced the extracellular BKV load by 65%; early large T antigen mRNA and protein expression by 30% and 75%, respectively; DNA replication by 73%; and late VP1 mRNA and protein expression by 47% and 64%, respectively. Importantly, the proliferation of RPTECs was also inhibited in a concentration-dependent manner. At 72 hpi, artesunate at 10 ?M reduced cellular DNA replication by 68% and total metabolic activity by 47%. Cell impedance and lactate dehydrogenase measurements indicated a cytostatic but not a cytotoxic mechanism. Flow cytometry and 5-ethynyl-2'-deoxyuridine incorporation revealed a decreased number of cells in S phase and suggested cell cycle arrest in G0 or G2 phase. Both the antiproliferative and antiviral effects of artesunate at 10 ?M were reversible. Thus, artesunate inhibits BKV replication in RPTECs in a concentration-dependent manner by inhibiting BKV gene expression and genome replication. The antiviral mechanism appears to be closely connected to cytostatic effects on the host cell, underscoring the dependence of BKV on host cell proliferative functions.
EVALuna2:8202

Antiviral Strategies Using Natural Source-Derived Sulfated Polysaccharides in the Light of the COVID-19 Pandemic and Major Human Pathogenic Viruses - Ray, Bimalendu; Ali, Imran; Jana, Subrata; Mukherjee, Shuvam; Pal, Saikat; Ray, Sayani; Schütz, Martin; Marschall, Manfred (Viruses, 2022)
Only a mere fraction of the huge variety of human pathogenic viruses can be targeted by the currently available spectrum of antiviral drugs. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has highlighted the urgent need for molecules that can be deployed quickly to treat novel, developing or re-emerging viral infections. Sulfated polysaccharides are found on the surfaces of both the susceptible host cells and the majority of human viruses, and thus can play an important role during viral infection. Such polysaccharides widely occurring in natural sources, specifically those converted into sulfated varieties, have already proved to possess a high level and sometimes also broad-spectrum antiviral activity. This antiviral potency can be determined through multifold molecular pathways, which in many cases have low profiles of cytotoxicity. Consequently, several new polysaccharide-derived drugs are currently being investigated in clinical settings. We reviewed the present status of research on sulfated polysaccharide-based antiviral agents, their structural characteristics, structure–activity relationships, and the potential of clinical application. Furthermore, the molecular mechanisms of sulfated polysaccharides involved in viral infection or in antiviral activity, respectively, are discussed, together with a focus on the emerging methodology contributing to polysaccharide-based drug development.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Antiviral activities and mechanisms; Antiviral efficacy; Drug structure-activity relationship; Emerging viral infections; Heparin mimetics; In vivo studies; Major human pathogenic viruses; Sulfated polysaccharides; Virus entry as a target

Anxiety Is Associated With DPPIV Alterations in Children With Selective Mutism and Social Anxiety Disorder: A Pilot Study - Golub, Yulia; Stonawski, Valeska; Plank, Anne-Christine; Eichler, Anna; Kratz, Oliver; Waltes, Regina; von Hörsten, Stephan; Roessner, Veit; Freitag, Christine M. (Frontiers in Psychiatry, 2021)
Background: Both selective mutism (SM) and social anxiety disorder (SAD) are severe pediatric anxiety disorders with the common trait of behavioral inhibition (BI). The underlying pathophysiology of these disorders remains poorly understood, however converging evidence suggests that alterations in several peripheral molecular pathways might be involved. In a pilot study, we investigated alterations in plasma molecular markers (dipeptidyl peptidase-4 [DPPIV], interleukin-6 [IL-6], tumor necrosis factor-beta [TNF-beta] and neuropeptide-Y [NPY]) in children with SM, SAD, and healthy controls, as well as the correlation of these markers to symptom severity.
CRIS-Team WoS Importer:2021-07-23

A pair of non‐competing neutralizing human monoclonal antibodies protecting from disease in a SARS‐CoV‐2 infection model - Peter, Antonia Sophia; Roth, Edith; Schulz, Sebastian; Fraedrich, Kirsten; Steinmetz, Tobit; Damm, Dominik; Hauke, Manuela; Richel, Elie; Müller-Schmucker, Sandra; Habenicht, Katharina Marie; Eberlein, Valentina; Issmail, Leila; et al. (European Journal of Immunology, 2021)
TRIANNI mice carry an entire set of human immunoglobulin V region gene segments and are a powerful tool to rapidly isolate human monoclonal antibodies. After immunizing these mice with DNA encoding the spike protein of SARS-CoV-2 and boosting with spike protein, we identified 29 hybridoma antibodies that reacted with the SARS-CoV-2 spike protein. Nine antibodies neutralize SARS-CoV-2 infection at IC50 values in the subnanomolar range. ELISA-binding studies and DNA sequence analyses revealed one cluster of three clonally related neutralizing antibodies that target the receptor-binding domain and compete with the cellular receptor hACE2. A second cluster of six clonally related neutralizing antibodies bind to the N-terminal domain of the spike protein without competing with the binding of hACE2 or cluster 1 antibodies. SARS-CoV-2 mutants selected for resistance to an antibody from one cluster are still neutralized by an antibody from the other cluster. Antibodies from both clusters markedly reduced viral spread in mice transgenic for human ACE2 and protected the animals from SARS-CoV-2-induced weight loss. The two clusters of potent non-competing SARS-CoV-2 neutralizing antibodies provide potential candidates for therapy and prophylaxis of COVID-19. The study further supports transgenic animals with a human immunoglobulin gene repertoire as a powerful platform in pandemic preparedness initiatives.

A placental specific miRNA miR-517a-3p exerts anti-human cytomegalovirus activity - Hamilton, Stuart T.; Hahn, Friedrich; Sonntag, Eric; Marschall, Manfred; Rawlinson, William D. (Placenta, 2021)
Human cytomegalovirus congenital infection is the leading non-genetic cause of fetal malformation in developed countries. There are currently no safe antivirals for use during pregnancy. Placental trophoblast cells specifically secrete exosomes containing miRNA from the chromosome 19 miRNA cluster (C19MC) which confer viral resistance to recipient cells. We show the highly expressed C19MC miRNA miR-517a-3p inhibits HCMV replication and viral protein expression in both fibroblast and trophoblast cell cultures (71.6% and 50.4% inhibition of HCMV DNA at 7 days post infection respectively; p < 0.05). This naturally occurring molecule has potential for opening-up antiviral therapeutic strategies for pregnancy.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Antivirals; Congenital infection; Cytomegalovirus; Placenta; Pregnancy

APOBEC3A, APOBEC3B, and APOBEC3H Haplotype 2 Restrict Human T-Lymphotropic Virus Type 1 - Ooms, Marcel; Krikoni, Aikaterini; Kreß, Andrea; Simon, Viviana; Muenk, Carsten (Journal of Virology, 2012)
The human APOBEC3 family consists of seven cytidine deaminases (A3A to A3H), some of which display potent antiretroviral activity against HIV-1 and other retroviruses. Studies that analyzed the effect of A3G on human T-lymphotropic virus type 1 (HTLV-1) infectivity resulted in conflicting findings, and our knowledge of HTLV-1 restriction by other A3 proteins remains limited. Since HTLV-1, much like HIV, targets CD4+ T cells, we hypothesized that A3 proteins other than A3G restrict HTLV-1. All seven human A3 proteins were tested in HTLV-1 reporter and HIV-1 infectivity assays. We show that A3A, A3B, and A3H haplotype 2 (A3H hapII) acted as potent inhibitors of HTLV-1. Wild-type HIV-1, in contrast, was restricted by A3B and A3H hapII, but not by A3A. Catalytic site mutants of A3A, A3B, and A3H hapII showed that A3A and A3B restriction of HTLV-1 required deaminase activity. However, A3H hapII acted in a deaminase-independent manner when restricting HTLV-1, while requiring deaminase activity for HIV-1 restriction. We also analyzed A3 editing of HTLV-1 in five T-cell lines obtained from HTLV-1-infected patients. These cell lines contained extensively edited HTLV-1 sequences with G-to-A mutations in dinucleotide contexts suggestive of APOBEC3 mutagenesis. Comparison of the A3-induced mutations from reporter cells and the patient-derived cell lines indicate that A3G but also other A3 members, possibly A3A and A3B, affect HTLV-1 in vivo. Taken together, our data indicate that HTLV-1 is a likely target for multiple A3 proteins. © 2012, American Society for Microbiology.
Created from Fastlane, Scopus look-up

Application of surface plasmon resonance imaging technique for the detection of single spherical biological submicrometer particles - Shpacovitch, Victoria; Temchura, Vladimir; Matrosovich, Mikhail; Hamacher, Joachim; Skolnik, Julia; Libuschewski, Pascal; Siedhoff, Dominic; Weichert, Frank; Marvvedel, Peter; Mueller, Heinrich; Überla, Klaus; Hergenroeder, Roland; et al. (Analytical Biochemistry, 2015)
Recent proof-of-principle studies demonstrated the suitability of the surface plasmon resonance imaging (SPRi) technique for the detection of individual submicrometer and nanoparticles in solutions. In the current study, we used the SPRi technique for visualization of the binding of round-shaped viruses (inactivated influenza A virus) and virus-like particles (human immunodeficiency virus (HIV)-based virus-like particles) to the functionalized sensor surface. We show the applicability of the SPRi technique for the detection of individual virus-like particles in buffers without serum as well as in buffers containing different concentrations of serum. Furthermore, we prove the specificity of visualized binding events using two different pseudotypes of HIV virus-like particles. We also demonstrate the applicability of the SPRi technique for the determination of relative particle concentrations in solutions. Moreover, we suggest a technical approach, which allows enhancing the magnitude of binding signals. Our studies indicate that the SPRi technique represents an efficient research tool for quantification and characterization of biological submicrometer objects such as viruses or virus-like particles, for example.
EVALuna2:8272

Application of the PAMONO-Sensor for Quantiﬁcation of Microvesicles and Determination of Nano-Particle Size Distribution - Shpacovitch, Victoria; Sidorenko, Irina; Lenssen, Jan Eric; Temchura, Vladimir; Weichert, Frank; Muller, Heinrich; Überla, Klaus; Zybin, Alexander; Schramm, Alexander; Hergenroder, Roland (Sensors, 2017)
The PAMONO-sensor (plasmon assisted microscopy of nano-objects) demonstrated an ability to detect and quantify individual viruses and virus-like particles. However, another group of biological vesicles-microvesicles (100-1000 nm)-also attracts growing interest as biomarkers of different pathologies and needs development of novel techniques for characterization. This work shows the applicability of a PAMONO-sensor for selective detection of microvesicles in aquatic samples. The sensor permits comparison of relative concentrations of microvesicles between samples. We also study a possibility of repeated use of a sensor chip after elution of the microvesicle capturing layer. Moreover, we improve the detection features of the PAMONO-sensor. The detection process utilizes novel machine learning techniques on the sensor image data to estimate particle size distributions of nano-particles in polydisperse samples. Altogether, our ﬁndings expand analytical features and the application ﬁeld of the PAMONO-sensor. They can also serve for a maturation of diagnostic tools based on the PAMONO-sensor platform.
EVALuna2:33770

A quantitative nuclear egress assay to investigate the nucleocytoplasmic capsid release of human cytomegalovirus - Häge, Sigrun; Horsch, Deborah; Stilp, Anne Charlotte; Kicuntod, Jintawee; Müller, Regina; Hamilton, Stuart T.; Egilmezer, Ece; Rawlinson, William D.; Stamminger, Thomas; Sonntag, Eric; Marschall, Manfred (Journal of Virological Methods, 2020)
Nuclear egress is a rate-limiting step of herpesviral replication, restricting the nucleocytoplasmic transport of viral capsids. The process is regulated by two viral nuclear egress proteins (core NEC pUL50-pUL53), which recruit additional cellular and viral proteins. The multicomponent NEC mediates disassembly of the nuclear lamina barrier and the docking of nuclear capsids. The quantitation of nuclear egress has been accomplished by electron microscopic analysis, but is generally hampered by the low number of detectable cytoplasmic capsids. A newly established method for the quantitation of viral nuclear egress improves the characterization of viral mutants, host cell permissiveness and antiviral drug efficacy. In this study, various strains of human cytomegalovirus (HCMV) were used to measure the replication efficiencies in primary human fibroblasts, applying methods of cell fractionation, DNase digestion, sucrose cushions and quantitative PCR. Several stages of optimization led to a reliable quantitative assay that allowed the characterization of viral nuclear egress efficacy. Using this assay, recovery of the nuclear egress of a NEC-defective HCMV mutant was quantitatively assessed by applying an inducible NEC-expressing fibroblast culture for trans-complementation. This novel assay system can be further used to accurately quantitate and characterize the functionality of nuclear egress of HCMV or other herpesviruses.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Capsid-Release; Cytomegalovirus; Fractionation; genome-specific-qPCR; Nuclear egress; Quantitative assay

A recessive form of hyper-IgE syndrome by disruption of ZNF341-dependent STAT3 transcription and activity - Beziat, Vivien; Li, Juan; Lin, Jian-Xin; Ma, Cindy S.; Li, Peng; Bousfiha, Aziz; Pellier, Isabelle; Zoghi, Samaneh; Baris, Safa; Keles, Sevgi; Gray, Paul; Du, Ning; et al. (Science immunology, 2018)
Heterozygosity for human signal transducer and activator of transcription 3 (STAT3) dominant-negative (DN) mutations underlies an autosomal dominant form of hyper-immunoglobulin E syndrome (HIES). We describe patients with an autosomal recessive form of HIES due to loss-of-function mutations of a previously uncharacterized gene, ZNF341. ZNF341 is a transcription factor that resides in the nucleus, where it binds a specific DNA motif present in various genes, including the STAT3 promoter. The patients' cells have low basal levels of STAT3 mRNA and protein. The autoinduction of STAT3 production, activation, and function by STAT3-activating cytokines is strongly impaired. Like patients with STAT3 DN mutations, ZNF341-deficient patients lack T helper 17 (T(H)17) cells, have an excess of T(H)2 cells, and have low memory B cells due to the tight dependence of STAT3 activity on ZNF341 in lymphocytes. Their milder extra-hematopoietic manifestations and stronger inflammatory responses reflect the lower ZNF341 dependence of STAT3 activity in other cell types. Human ZNF341 is essential for the STAT3 transcription-dependent autoinduction and sustained activity of STAT3.
EVALuna2:35276

A role for MALT1 activity in Kaposi's sarcoma-associated herpes virus latency and growth of primary effusion lymphoma - Bonsignore, L.; Passelli, K.; Pelzer, C.; Perroud, M.; Konrad, A.; Thurau, Mathias; Stürzl, Michael; Dai, L.; Trillo-Tinoco, Jimena; Del Valle, L.; Qin, Z.; Thome, Margot (Leukemia, 2017)
Primary effusion lymphoma (PEL) is an incurable malignancy that develops in immunodeficient patients as a consequence of latent infection of B-cells with Kaposi's sarcoma-associated herpes virus (KSHV). Malignant growth of KSHV-infected B cells requires the activity of the transcription factor nuclear factor (NF)-?B, which controls maintenance of viral latency and suppression of the viral lytic program. Here we show that the KSHV proteins K13 and K15 promote NF-?B activation via the protease mucosa-associated lymphoid tissue lymphoma translocation protein-1 (MALT1), a key driver of NF-?B activation in lymphocytes. Inhibition of the MALT1 protease activity induced a switch from the latent to the lytic stage of viral infection, and led to reduced growth and survival of PEL cell lines in vitro and in a xenograft model. These results demonstrate a key role for the proteolytic activity of MALT1 in PEL, and provide a rationale for the pharmacological targeting of MALT1 in PEL therapy.
EVALuna2:15308

A ROLE FOR TRANSGLUTAMINASE 6 IN HD PATHOLOGY - Schulze-Krebs, Anja; Canneva, Fabio; Schnepf, Rebecca; Glossner, Laura; Plank, Anne-Christine; Dobner, Julia; Bates, Gillian P.; Aeschlimann, Daniel; Steffan, Joan S.; von Hörsten, Stephan (2018)
EVALuna2:36094

Artesunate derivative TF27 inhibits replication and pathogenesis of an oncogenic avian alphaherpesvirus - Bertzbach, Luca D.; Conradie, Andelé M.; Hahn, Friedrich; Wild, Markus; Marschall, Manfred; Kaufer, Benedikt B. (Antiviral Research, 2019)
Nucleoside analogues have been the cornerstone of clinical treatment of herpesvirus infections since the 1970s. However, severe side effects and emergence of drug resistant viruses raise the need for alternative treatment options. We recently investigated the broad and strong antiherpesviral activity of the optimized artesunate derivative TF27 in vitro. TF27 efficiently inhibited replication of the highly oncogenic Marek's disease virus (MDV), a virus that infects chickens, causes deadly lymphomas and threatens poultry populations worldwide. In this study, we used this natural virus-host model for herpesvirus-induced cancer by infecting chickens with MDV, and evaluated the protective efficacy of TF27 and the nucleoside analogue valganciclovir (VGCV) on virus replication and tumorigenesis. We could demonstrate that both drugs reduced viral load in the blood and prevented tumor development in a large portion of the animals. Antiviral treatment also had a positive impact on body weight gain, while no negative compound-associated side effects were observed. This research provides the first evidence that the artesunate derivative TF27 and VGCV can be used in avian species and that they inhibit MDV replication and tumorigenesis. In addition, our study paves the way for promising approaches in future antiherpesviral drug development.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Artesunate; Artesunate derivative; Experimental antiviral drug; Herpesviral in vivo models; Indirect host-targeted antivirals; Marek's disease virus; NF-κB signaling inhibition

Artesunate-derived monomeric, dimeric and trimeric experimental drugs - Their unique mechanistic basis and pronounced antiherpesviral activity - Hahn, Friedrich; Fröhlich, Tony; Frank, Theresa; Bertzbach, Luca D.; Kohrt, Stephan; Kaufer, Benedikt B.; Stamminger, Thomas; Tsogoeva, Svetlana; Marschall, Manfred (Antiviral Research, 2018)
Human cytomegalovirus (HCMV) is a major human pathogen and is associated with severe pathology, such as life-threatening courses of infection in immunocompromised individuals and neonates. Currently, antiviral therapy is still hampered by a considerable toxicity of the available drugs and induction of viral resistance. Recently, we and others reported the very potent antiviral activity of the broad antiinfective drug artesunate in vitro and in vivo. Here, we investigated further optimized analogs including monomeric, dimeric and trimeric derivatives belonging to this highly interesting chemical group of experimental drugs (sesquiterpenes/trioxanes) and compared these to the previously identified trimeric artesunate compound TF27. We could demonstrate that (i) seven of the eight investigated monomeric, dimeric and trimeric artesunate derivatives, i.e. TF79, TF85, TF87, TF93.2.4, TF111, TF57a and TF57ab, exerted a strong anti-HCMV activity in primary human fibroblasts, (ii) the EC50 values ranged in the low to sub-micromolar concentrations and indicated a higher antiviral potency than the recently described artesunate analogs, (iii) one trimeric compound, TF79, showed a very promising EC50 of 0.03 +/- 0.00 mu M, which even exceled the antiviral potency of TF27 (EC50 0.04 +/- 0.01 mu M), (iv) levels of cytotoxicity (quantitative measurement of lactate dehydrogenase release) were low in a range between 100 and 30 mu M and thus different from antiviral concentrations, (v) an analysis of protein expression levels indicated a potent block of viral protein expression, and (vi) data from a NF-kappa B reporter cell system strongly suggested that these compounds share the same antiviral mechanism. Taken together, our data on these novel compounds strongly encourages our earlier concept on the oligomerization and hybridization of artesunate analogs, providing an excellent platform for the generation of antiherpesviral drugs.
EVALuna2:35282

Artificial intelligence-based 3D angiography for visualization of complex cerebrovascular pathologies - Lang, Sabine; Hölter, Philip; Schmidt, Manuel; Strother, C.; Kaethner, C.; Kowarschik, M.; Dörfler, Arnd (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: By means of artificial intelligence, 3D angiography is a novel postprocessing method for 3D imaging of cerebral vessels. Because 3D angiography does not require a mask run like the current standard 3D-DSA, it potentially offers a considerable reduction of the patient radiation dose. Our aim was an assessment of the diagnostic value of 3D angiography for visualization of cerebrovascular pathologies. MATERIALS AND METHODS: 3D-DSA data sets of cerebral aneurysms (nCA ¼ 10), AVMs (nAVM ¼ 10), and dural arteriovenous fistulas (dAVFs) (ndAVF ¼ 10) were reconstructed using both conventional and prototype software. Corresponding reconstructions have been analyzed by 2 neuroradiologists in a consensus reading in terms of image quality, injection vessel diameters (vessel diameter [VD] 1/2), vessel geometry index (VGI ¼ VD1/VD2), and specific qualitative/quantitative parameters of AVMs (eg, location, nidus size, feeder, associated aneurysms, drainage, Spetzler-Martin score), dAVFs (eg, fistulous point, main feeder, diameter of the main feeder, drainage), and cerebral aneurysms (location, neck, size). RESULTS: In total, 60 volumes have been successfully reconstructed with equivalent image quality. The specific qualitative/quantitative assessment of 3D angiography revealed nearly complete accordance with 3D-DSA in AVMs (eg, mean nidus size3D angiography/3D-DSA¼ 19.9 [SD, 10.9]/20.2 [SD, 11.2] mm; r ¼ 0.9, P ¼.001), dAVFs (eg, mean diameter of the main feeder3D angiography/3D-DSA¼ 2.04 [SD, 0.65]/2.05 [SD, 0.63] mm; r ¼ 0.9, P ¼.001), and cerebral aneurysms (eg, mean size3D angiography/3D-DSA¼ 5.17 [SD, 3.4]/5.12 [SD, 3.3] mm; r ¼ 0.9, P ¼.001). Assessment of the geometry of the injection vessel in 3D angiography data sets did not differ significantly from that of 3D-DSA (vessel geometry indexAVM: r ¼ 0.84, P ¼.003; vessel geometry indexdAVF: r ¼ 0.82, P ¼.003; vessel geometry indexCA: r ¼ 0.84, P,.001). CONCLUSIONS: In this study, the artificial intelligence-based 3D angiography was a reliable method for visualization of complex cerebrovascular pathologies and showed results comparable with those of 3D-DSA. Thus, 3D angiography is a promising postprocessing method that provides a significant reduction of the patient radiation dose.
CRIS-Team Scopus Importer:2021-11-05

A Sphingosine-1-Phosphate Receptor Modulator Attenuated Secondary Brain Injury and Improved Neurological Functions of Mice after ICH - Bobinger, Tobias; Bäuerle, Tobias; Seyler, L.; von Hörsten, Stephan; Schwab, Stefan; Huttner, Hagen; Manaenko, A. (Oxidative Medicine and Cellular Longevity, 2020)
Background. Stroke activates the immune system and induces brain infiltration by immune cells, aggravating brain injury. Poststroke immunomodulation via (S1P-)receptor modulation is beneficial; however, the S1P-modulator in clinical use (FTY-720) is unspecific, and undesirable side effects have been reported. Previously, we tested effects of a novel selective S1P-receptor modulator, Siponimod, on ICH-induced brain injury in acute stage of the disease. In the current study, we investigated whether protective effects of Siponimod, evaluated in a short-term study, will protect the brain of ICH animals at long term as well. Methods. 134 C57BL/6N mice were divided into sham and ICH-operated groups. Collagenase model of ICH was employed. ICH animals were divided into Siponimod treated and nontreated. Dose- and time-dependent effects of Siponimod were investigated. Contraplay between development of brain injury and the number of lymphocytes infiltrating the brain was investigated by forelimb placing, T-Maze test, brain water content calculation, MRI scanning, and immunostaining. Results. Depending on the therapeutic strategy, Siponimod attenuated the development of brain edema, decreased ICH-induced ventriculomegaly and improved neurological functions of animals after ICH. It was associated with less lymphocytes in the brain of ICH animals. Conclusion. Siponimod is able to decrease the brain injury and improves neurological functions of animals after ICH.
CRIS-Team Scopus Importer:2020-10-09

Assessment of Covalently Binding Warhead Compounds in the Validation of the Cytomegalovirus Nuclear Egress Complex as an Antiviral Target - Tillmanns, Julia; Häge, Sigrun; Borst, Eva Maria; Wardin, Julia; Eickhoff, Jan; Klebl, Bert; Wagner, Sabrina; Wangen, Christina; Hahn, Friedrich; Socher, Eileen; Marschall, Manfred (Cells, 2023)
Herpesviral nuclear egress is a regulated process of viral capsid nucleocytoplasmic release. Due to the large capsid size, a regular transport via the nuclear pores is unfeasible, so that a multistage-regulated export pathway through the nuclear lamina and both leaflets of the nuclear membrane has evolved. This process involves regulatory proteins, which support the local distortion of the nuclear envelope. For human cytomegalovirus (HCMV), the nuclear egress complex (NEC) is determined by the pUL50–pUL53 core that initiates multicomponent assembly with NEC-associated proteins and capsids. The transmembrane NEC protein pUL50 serves as a multi-interacting determinant that recruits regulatory proteins by direct and indirect contacts. The nucleoplasmic core NEC component pUL53 is strictly associated with pUL50 in a structurally defined hook-into-groove complex and is considered as the potential capsid-binding factor. Recently, we validated the concept of blocking the pUL50–pUL53 interaction by small molecules as well as cell-penetrating peptides or an overexpression of hook-like constructs, which can lead to a pronounced degree of antiviral activity. In this study, we extended this strategy by utilizing covalently binding warhead compounds, originally designed as binders of distinct cysteine residues in target proteins, such as regulatory kinases. Here, we addressed the possibility that warheads may likewise target viral NEC proteins, building on our previous crystallization-based structural analyses that revealed distinct cysteine residues in positions exposed from the hook-into-groove binding surface. To this end, the antiviral and NEC-binding properties of a selection of 21 warhead compounds were investigated. The combined findings are as follows: (i) warhead compounds exhibited a pronounced anti-HCMV potential in cell-culture-based infection models; (ii) computational analysis of NEC primary sequences and 3D structures revealed cysteine residues exposed to the hook-into-groove interaction surface; (iii) several of the active hit compounds exhibited NEC-blocking activity, as shown at the single-cell level by confocal imaging; (iv) the clinically approved warhead drug ibrutinib exerted a strong inhibitory impact on the pUL50–pUL53 core NEC interaction, as demonstrated by the NanoBiT assay system; and (v) the generation of recombinant HCMV ∆UL50-ΣUL53, allowing the assessment of viral replication under conditional expression of the viral core NEC proteins, was used for characterizing viral replication and a mechanistic evaluation of ibrutinib antiviral efficacy. Combined, the results point to a rate-limiting importance of the HCMV core NEC for viral replication and to the option of exploiting this determinant by the targeting of covalently NEC-binding warhead compounds.
Created from Fastlane, Scopus look-up
Keywords: antiviral targeting based on NEC 3D structures; conditional expression of viral core NEC proteins; covalently binding warhead compounds; human cytomegalovirus; nuclear egress complex (NEC); pronounced NEC-directed antiviral activity; regulation of viral replication

Association of early phenotypic behavioral alterations in human alpha-synuclein overexpressing transgenic rats with alpha-synuclein/huntingtin/amyloid-beta protein cross-seeding - Moceri, Sandra; Canneva, Fabio; Habermeyer, Johanna; Dobner, Julia; Schulze-Krebs, Anja; Puchades, Maja; Bjaalie, Jan G.; Kohl, Zacharias; Winkler, Jürgen; Timotius, Ivanna; Eskofier, Björn; Schilling, Stephan; et al. (Advances in Alzheimer's and Parkinson's Therapies an AAT-AD/PD Focus Meeting, 2018)

Association of prenatal alcohol exposure and prenatal maternal depression with offspring low-grade inflammation in early adolescence - Maschke, Janina; Roetner, Jakob; Bösl, Sophia; Plank, Anne-Christine; Rohleder, Nicolas; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; et al. (International Journal of Environmental Research and Public Health, 2021)
(1) This longitudinal study aimed to investigate the link between prenatal alcohol exposure and prenatal maternal depression with the offspring’s low-grade inflammatory status. (2) Prenatal alcohol exposure was determined via maternal self-report during the 3rd trimester of pregnancy (self-report+: n = 29) and the meconium alcohol metabolite Ethyl Glucuronide (EtG), collected at birth (≥30 ng/g: n = 23). The Edinburgh Postnatal Depression Scale (EPDS) was used to screen for prenatal maternal depressive symptoms during the 3rd trimester (≥10: n = 35). Fifteen years later, 122 adolescents (M = 13.32 years; 48.4% female) provided blood samples for the analysis of high sensitivity C-reactive protein (hsCRP; M = 0.91; SD = 1.28). (3) Higher hsCRP levels were found in EtG positive adolescents (p = 0.036, ηp2 = 0.04) and an inverse non-significant dose–response relation with hsCRP (r = −0.35, p = 0.113). For maternal self-reported prenatal alcohol consumption (p = 0.780, ηp2 = 0.00) and prenatal depressive symptoms (p = 0.360, ηp2 = 0.01) no differences for hsCRP levels between the affected and unaffected groups were found. (4) Adolescents with prenatal alcohol exposure are at risk for low-grade systemic inflammation. The EtG biomarker may be more accurate compared to self-reports. The findings suggest that prenatal maternal depression does not evoke low-grade systemic inflammation.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Early adolescence; High-sensitivity C-reactive protein (hsCRP); Low-grade systemic inflammation; Maternal self-report; Meconium ethyl glucuronide (EtG); Pregnancy; Prenatal alcohol exposure (PAE); Prenatal depression

A systems biology approach to identify the combination effects of human herpesvirus 8 genes on NF-κB activation - Konrad, Andreas; Wies, Effi; Thurau, Mathias; Marquardt, Gaby; Naschberger, Elisabeth; Hentschel, Sonja; Jochmann, Ramona; Schulz, Thomas F.; Erfle, Holger; Brors, Benedikt; Lausen, Berthold; Neipel, Frank; et al. (Journal of Virology, 2009)
Human herpesvirus 8 (HHV-8) is the etiologic agent of Kaposi's sarcoma and primary effusion lymphoma. Activation of the cellular transcription factor nuclear factor-kappa B (NF-κB) is essential for latent persistence of HHV-8, survival of HHV-8-infected cells, and disease progression. We used reverse-transfected cell microarrays (RTCM) as an unbiased systems biology approach to systematically analyze the effects of HHV-8 genes on the NF-κB signaling pathway. All HHV-8 genes individually (n = 86) and, additionally, all K and latent genes in pairwise combinations (n = 231) were investigated. Statistical analyses of more than 14,000 transfections identified ORF75 as a novel and confirmed K13 as a known HHV-8 activator of NF-κB. K13 and ORF75 showed cooperative NF-κB activation. Small interfering RNA-mediated knockdown of ORF75 expression demonstrated that this gene contributes significantly to NF-κB activation in HHV-8-infected cells. Furthermore, our approach confirmed K10.5 as an NF-κB inhibitor and newly identified K1 as an inhibitor of both K13- and ORF75-mediated NF-κB activation. All results obtained with RTCM were confirmed with classical transfection experiments. Our work describes the first successful application of RTCM for the systematic analysis of pathofunctions of genes of an infectious agent. With this approach, ORF75 and K1 were identified as novel HHV-8 regulatory molecules on the NF-κB signal transduction pathway. The genes identified may be involved in fine-tuning of the balance between latency and lytic replication, since this depends critically on the state of NF-κB activity. Copyright © 2009, American Society for Microbiology.
Created from Fastlane, Scopus look-up

Attenuated zoster vaccine is not recommended as a standard vaccine : Missed opportunity or logical implementation of the evidence-based approach of the Standing Committee on Vaccination - Überla, Klaus (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2017)
EVALuna2:33754

Attenuation of chemokine receptor function and surface expression as an immunomodulatory strategy employed by human cytomegalovirus is linked to vGPCR US28 - Frank, Theresa; Reichel, Anna; Larsen, Olav; Stilp, Anne-Charlotte; Rosenkilde, Mette M.; Stamminger, Thomas; Ozawa, Takeaki; Tschammer, Nuska (Cell Communication and Signaling, 2016)
Some herpesviruses like human cytomegalovirus (HCMV) encode viral G protein-coupled receptors that cause reprogramming of cell signaling to facilitate dissemination of the virus, prevent immune surveillance and establish life-long latency. Human GPCRs are known to function in complex signaling networks involving direct physical interactions as well as indirect crosstalk of orthogonal signaling networks. The human chemokine receptor CXCR4 is expressed on hematopoietic stem cells, leukocytes, endothelial and epithelial cells, which are infected by HCMV or display reservoirs of latency.We investigated the potential heteromerization of US28 with CXCR4 as well as the influence of US28 on CXCR4 signaling. Using Bioluminescence Resonance Energy Transfer and luciferase-complementation based methods we show that US28 expression exhibits negative effects on CXCR4 signaling and constitutive surface expression in HEK293T cells. Furthermore, we demonstrate that this effect is not mediated by receptor heteromerization but via signaling crosstalk. Additionally, we show that in HCMV, strain TB40E, infected HUVEC the surface expression of CXCR4 is strongly downregulated, whereas in TB40E-delUS28 infected cells, CXCR4 surface expression is not altered in particular at late time points of infection.We show that the vGPCR US28 is leading to severely disturbed signaling and surface expression of the chemokine receptor CXCR4 thereby representing an effective mechanism used by vGPCRs to reprogram host cell signaling. In contrast to other studies, we demonstrate that these effects are not mediated via heteromerization.
EVALuna2:8316

Attenuation of SARS-CoV-2 replication and associated inflammation by concomitant targeting of viral and host cap 2'-O-ribose methyltransferases - Bergant, Valter; Yamada, Shintaro; Grass, Vincent; Tsukamoto, Yuta; Lavacca, Teresa; Krey, Karsten; Muhlhofer, Maria-Teresa; Wittmann, Sabine; Enßer, Armin; Herrmann, Alexandra; Vom Hemdt, Anja; Tomita, Yuriko; et al. (EMBO Journal, 2022)
The SARS-CoV-2 infection cycle is a multistage process that relies on functional interactions between the host and the pathogen. Here, we repurposed antiviral drugs against both viral and host enzymes to pharmaceutically block methylation of the viral RNA 2'-O-ribose cap needed for viral immune escape. We find that the host cap 2'-O-ribose methyltransferase MTr1 can compensate for loss of viral NSP16 methyltransferase in facilitating virus replication. Concomitant inhibition of MTr1 and NSP16 efficiently suppresses SARS-CoV-2 replication. Using in silico target-based drug screening, we identify a bispecific MTr1/NSP16 inhibitor with anti-SARS-CoV-2 activity in vitro and in vivo but with unfavorable side effects. We further show antiviral activity of inhibitors that target independent stages of the host SAM cycle providing the methyltransferase co-substrate. In particular, the adenosylhomocysteinase (AHCY) inhibitor DZNep is antiviral in in vitro, in ex vivo, and in a mouse infection model and synergizes with existing COVID-19 treatments. Moreover, DZNep exhibits a strong immunomodulatory effect curbing infection-induced hyperinflammation and reduces lung fibrosis markers ex vivo. Thus, multispecific and metabolic MTase inhibitors constitute yet unexplored treatment options against COVID-19.
CRIS-Team WoS Importer:2022-08-05

Autofluorescent Artemisinin-Benzimidazole Hybrids via Organo-Click Reaction: Study of Antiviral Properties and Mode of Action in Living Cells - Herrmann, Lars; Hahn, Friedrich; Grau, Benedikt; Wild, Markus; Niesar, Aischa; Wangen, Christina; Kataev, Evgeny; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2023)
Drug modification by a fluorescent label is a common tool for studying its mechanism of action with fluorescence microscopy techniques. However, the attachment of a fluorescent label can significantly alter the polarity, solubility, and biological activity of the investigated drug, and, as a result, the studied mechanism of action can be misrepresented. Therefore, developing efficient drugs, which are inherently fluorescent and can be tracked directly in the cell is highly favorable. Here an easy formation of fluorescent hybrid drugs is presented, generated by a combination of two readily available non-fluorescent pharmacophores via a non-cleavable linker using a Ramachary-Bressy-Wang organocatalyzed azide-carbonyl [3+2] cycloaddition (organo-click) reaction. All newly prepared fluorescent compounds showed strong anti-HCMV activity (EC50 down to 0.07±0.00 μM), thus presenting a very promising drug developmental basis compared to the approved drug ganciclovir (EC50 2.60±0.50 μM). Remarkably, in vitro fluorescent imaging investigation of new compounds revealed induced changes in mitochondrial structures, which is a phenotypical hallmark of antiviral activity. This approach opens up new vistas for the easy formation of potent fluorescent drugs from readily available non-fluorescent parent compounds and might facilitate insight into their mode of action in living cells, avoiding the requirement of linkage to external fluorescent markers.
CRIS-Team Scopus Importer:2023-09-08
Keywords: artemisinin-benzimidazole hybrids; autofluorescent antivirals; confocal microscopy; organo-click reaction; [3+2] cycloaddition

Automated phenotyping and advanced data mining exemplified in rats transgenic for Huntington's disease - Urbach, Yvonne K.; Raber, Kerstin A.; Canneva, Fabio; Plank, Anne-Christine; Andreasson, Theresa; Ponten, Henrik; Kullingsjoe, Johan; Huu Phuc Nguyen,; Riess, Olaf; von Hörsten, Stephan (Journal of Neuroscience Methods, 2014)
The need for improving throughput, validity, and reliability in the behavioral characterization of rodents may benefit from integrating automated intra-home-cage-screening systems allowing the simultaneous detection of multiple behavioral and physiological parameters in parallel.To test this hypothesis, transgenic Huntington's disease (tgHD) rats were repeatedly screened within phenotyping home-cages (PhenoMaster and IntelliCage for rats), where spontaneous activity, feeding, drinking, temperature, and metabolic performance were continuously measured. Cognition and emotionality were evaluated within the same environment by means of operant learning procedures and refined analysis of the behavioral display under conditions of novelty. This investigator-independent approach was further correlated with behavioral display of the animals in classical behavioral assays. Multivariate analysis (MVA) including Principle Component Analysis (PCA) and Partial Least Squares Discriminant Analysis (PLS-DA) was used to explore correlation patterns of variables within and across the two genotypes.The automated systems traced previously undetected aspects in the phenotype of tgHD rats (circadian activity, energy metabolism, rearing), and out of those spontaneous free rearing correlated with individual performance in the accelerod test. PCA revealed a segregation by genotype in juvenile tgHD rats that differed from adult animals, being further resolved by PLS-DA detecting "temperature" (juvenile) and "rearing" (adult) as phenotypic key variables in the tgHD model.Intra-home-cage phenotyping in combination with MVA, is capable of characterizing a complex phenotype by detecting novel physiological and behavioral markers with high sensitivity and standardization using fewer human resources. A broader application of automated systems for large-scale screening is encouraged.
EVALuna2:24971

A viral kinase counteracts in vivo restriction of murine cytomegalovirus by SAMHD1 - Deutschmann, Janina; Schneider, Andrea; Gruska, Iris; Vetter, Barbara; Thomas, Dominique; Kießling, Melissa; Wittmann, Sabine; Herrmann, Alexandra; Schindler, Michael; Milbradt, Jens; Ferreirós, Nerea; Winkler, Thomas; et al. (Nature Microbiology, 2019)
The deoxynucleotide triphosphate (dNTP) hydrolase SAMHD1 inhibits retroviruses in non-dividing myeloid cells. Although antiviral activity towards DNA viruses has also been demonstrated, the role of SAMHD1 during cytomegalovirus (CMV) infection remains unclear. To determine the impact of SAMHD1 on the replication of CMV, we used murine CMV (MCMV) to infect a previously established SAMHD1 knockout mouse model and found that SAMHD1 inhibits the replication of MCMV in vivo. By comparing the replication of MCMV in vitro in myeloid cells and fibroblasts from SAMHD1-knockout and control mice, we found that the viral kinase M97 counteracts SAMHD1 after infection by phosphorylating the regulatory residue threonine 603. The phosphorylation of SAMHD1 in infected cells correlated with a reduced level of dNTP hydrolase activity and the loss of viral restriction. Together, we demonstrate that SAMHD1 acts as a restriction factor in vivo and we identify the M97-mediated phosphorylation of SAMHD1 as a previously undescribed viral countermeasure.
CRIS-Team Scopus Importer:2019-11-01

Background paper to the decision to recommend the vaccination with the inactivated herpes zoster subunit vaccine: Statement of the German Standing Committee on Vaccination (STIKO) at the Robert Koch Institute - Siedler, A.; Koch, J.; Garbe, E.; Hengel, H.; Von Kries, R.; Ledig, T.; Mertens, T.; Zepp, F.; Überla, Klaus (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2019)
CRIS-Team WoS Importer:2019-03-29

B-cell and antibody responses to SARS-CoV-2: infection, vaccination, and hybrid immunity - Lapuente, Dennis; Winkler, Thomas H.; Tenbusch, Matthias (Cellular & Molecular Immunology, 2023)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in 2019 prompted scientific, medical, and biotech communities to investigate infection- and vaccine-induced immune responses in the context of this pathogen. B-cell and antibody responses are at the center of these investigations, as neutralizing antibodies (nAbs) are an important correlate of protection (COP) from infection and the primary target of SARS-CoV-2 vaccine modalities. In addition to absolute levels, nAb longevity, neutralization breadth, immunoglobulin isotype and subtype composition, and presence at mucosal sites have become important topics for scientists and health policy makers. The recent pandemic was and still is a unique setting in which to study de novo and memory B-cell (MBC) and antibody responses in the dynamic interplay of infection- and vaccine-induced immunity. It also provided an opportunity to explore new vaccine platforms, such as mRNA or adenoviral vector vaccines, in unprecedented cohort sizes. Combined with the technological advances of recent years, this situation has provided detailed mechanistic insights into the development of B-cell and antibody responses but also revealed some unexpected findings. In this review, we summarize the key findings of the last 2.5 years regarding infection- and vaccine-induced B-cell immunity, which we believe are of significant value not only in the context of SARS-CoV-2 but also for future vaccination approaches in endemic and pandemic settings.
CRIS-Team Scopus Importer:2023-11-17
Keywords: IgG4; memory responses; neutralizing antibodies; SARS-CoV-2; vaccines

B cell repertoire analysis identifies new antigenic domains on glycoprotein B of human cytomegalovirus which are target of neutralizing antibodies - Pötzsch, Sonja; Spindler, Nadja; Wiegers, Anna-Katharina; Fisch, Tanja; Ruecker, Pia; Sticht, Heinrich; Grieb, Nina; Baroti, Tina; Weisel, Florian; Stamminger, Thomas; Martin-Parras, Luis; Mach, Michael; et al. (PLoS Pathogens, 2011)
Human cytomegalovirus (HCMV), a herpesvirus, is a ubiquitously distributed pathogen that causes severe disease in immunosuppressed patients and infected newborns. Efforts are underway to prepare effective subunit vaccines and therapies including antiviral antibodies. However, current vaccine efforts are hampered by the lack of information on protective immune responses against HCMV. Characterizing the B-cell response in healthy infected individuals could aid in the design of optimal vaccines and therapeutic antibodies. To address this problem, we determined, for the first time, the B-cell repertoire against glycoprotein B (gB) of HCMV in different healthy HCMV seropositive individuals in an unbiased fashion. HCMV gB represents a dominant viral antigenic determinant for induction of neutralizing antibodies during infection and is also a component in several experimental HCMV vaccines currently being tested in humans. Our findings have revealed that the vast majority (>90%) of gB-specific antibodies secreted from B-cell clones do not have virus neutralizing activity. Most neutralizing antibodies were found to bind to epitopes not located within the previously characterized antigenic domains (AD) of gB. To map the target structures of these neutralizing antibodies, we generated a 3D model of HCMV gB and used it to identify surface exposed protein domains. Two protein domains were found to be targeted by the majority of neutralizing antibodies. Domain I, located between amino acids (aa) 133-343 of gB and domain II, a discontinuous domain, built from residues 121-132 and 344-438. Analysis of a larger panel of human sera from HCMV seropositive individuals revealed positivity rates of >50% against domain I and >90% against domain II, respectively. In accordance with previous nomenclature the domains were designated AD-4 (Dom II) and AD-5 (Dom I), respectively. Collectively, these data will contribute to optimal vaccine design and development of antibodies effective in passive immunization. © 2011 Pötzsch et al.
EVALuna2:8099

Begomoviral Movement Protein Effects in Human and Plant Cells: Towards New Potential Interaction Partners - Krapp, Susanna; Schuy, Christian; Greiner, Eva; Stephan, Irina; Alberter, Barbara; Funk, Christina; Marschall, Manfred; Wege, Christina; Bailer, Susanne M.; Kleinow, Tatjana; Krenz, Bjoern (Viruses, 2017)
Geminiviral single-stranded circular DNA genomes replicate in nuclei so that the progeny DNA has to cross both the nuclear envelope and the plasmodesmata for systemic spread within plant tissues. For intra- and intercellular transport, two proteins are required: a nuclear shuttle protein (NSP) and a movement protein (MP). New characteristics of ectopically produced Abutilon mosaic virus (AbMV) MP (MPAbMV), either authentically expressed or fused to a yellow fluorescent protein or epitope tags, respectively, were determined by localization studies in mammalian cell lines in comparison to plant cells. Wild-type MPAbMVand the distinct MPAbMV: reporter protein fusions appeared as curled threads throughout mammalian cells. Co-staining with cytoskeleton markers for actin, intermediate filaments, or microtubules identified these threads as re-organized microtubules. These were, however, not stabilized by the viral MP, as demonstrated by nocodazole treatment. The MP of a related bipartite New World begomovirus, Cleome leaf crumple virus (ClLCrV), resulted in the same intensified microtubule bundling, whereas that of a nanovirus did not. The C-terminal section of MPAbMV, i.e., the protein's oligomerization domain, was dispensable for the effect. However, MP expression in plant cells did not affect the microtubules network. Since plant epidermal cells are quiescent whilst mammalian cells are proliferating, the replication-associated protein RepAbMVprotein was then co-expressed with MPAbMVto induce cell progression into S-phase, thereby inducing distinct microtubule bundling without MP recruitment to the newly formed threads. Co-immunoprecipitation of MPAbMVin the presence of RepAbMV, followed by mass spectrometry identified potential novel MPAbMV-host interaction partners: the peptidyl-prolyl cis-trans isomerase NIMA-interacting 4 (Pin4) and stomatal cytokinesis defective 2 (SCD2) proteins. Possible roles of these putative interaction partners in the begomoviral life cycle and cytoskeletal association modes are discussed.
EVALuna2:33750

Behavioural effects of APH199, a selective dopamine D4 receptor agonist, in animal models - Chestnykh, Daria; Graßl, Fabian; Pfeifer, Conrad; Dülk, Jonas; Ebner, Chiara; Walters, Mona; von Hörsten, Stephan; Kornhuber, Johannes; Kalinichenko, Liubov; Heinrich, Markus; Müller, Christian P. (Psychopharmacology, 2023)
Rationale: The dopamine D4 receptors (DRD4) play a key role in numerous brain functions and are involved in the pathogenesis of various psychiatric disorders. DRD4 ligands have been shown to moderate anxiety, reward and depression-like behaviours, and cognitive impairments. Despite a series of promising but ambiguous findings, the therapeutic advantages of DRD4 stimulation remain elusive. Objectives: The investigation focused on the behavioural effects of the recently developed DRD4 agonist, APH199, to evaluate its impact on anxiety, anhedonia, behavioural despair, establishment and retrieval of alcohol reinforcement, and amphetamine (AMPH)-induced symptoms. Methods: Male C57BL/6 J mice and Sprague–Dawley rats were examined in five independent experiments. We assessed APH199 (0.1–5 mg/kg, i.p.) effects on a broad range of behavioural parameters in the open field (OF) test, conditioned place preference test (CPP), elevated plus maze (EPM), light–dark box (LDB), novelty suppressed feeding (NSF), forced swim test (FST), sucrose preference test (SPT), AMPH-induced hyperlocomotion test (AIH), and prepulse inhibition (PPI) of the acoustic startle response in AMPH-sensitized rats. Results: APH199 caused mild and sporadic anxiolytic and antidepressant effects in EPM and FST, but no remarkable impact on behaviour in other tests in mice. However, we found a significant increase in AMPH-induced hyperactivity, suggesting an exaggeration of the psychotic-like responses in the AMPH-sensitized rats. Conclusions: Our data challenged the hypothesis of the therapeutic benefits of DRD4 agonists, pointing out a possible aggravation of psychosis. We suggest a need for further preclinical studies to ensure the safety of antipsychotics with DRD4 stimulating properties.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Alcohol; Anxiety; APH199; Depression; DRD4 agonist; Psychosis; Schizophrenia

Beware of manipulations on the genome: epigenetic destabilization through (foreign) DNA insertions - Doerfler, Walter (Epigenomics, 2016)
EVALuna2:8337

Bind&Bite: covalently stabilized heterodimeric coiled-coil peptides for the site-selective, cysteine-free chemical modification of proteins - Beutel, Jannis; Tannig, Pierre; Di Vincenzo, Riccardo; Schumacher, Thomas; Überla, Klaus; Eichler, Jutta (RSC Chemical Biology, 2023)
Ensuring site-selectivity in covalent chemical modification of proteins is one of the major challenges in chemical biology and related biomedical disciplines. Most current strategies either utilize the selectivity of proteases, or are based on reactions involving the thiol groups of cysteine residues. We have modified a pair of heterodimeric coiled-coil peptides to enable the selective covalent stabilization of the dimer without using enzymes or cysteine moieties. Fusion of one peptide to the protein of interest, in combination with linking the desired chemical modification to the complementary peptide, facilitates stable, regio-selective attachment of the chemical moiety to the protein, through the formation of the covalently stabilized coiled-coil. This ligation method, which is based on the formation of isoeptide and squaramide bonds, respectively, between the coiled-coil peptides, was successfully used to selectively modify the HIV-1 envelope glycoprotein. Covalent stabilization of the coiled-coil also facilitated truncation of the peptides by one heptad sequence. Furthermore, selective addressing of individual positions of the peptides enabled the generation of mutually selective coiled-coils. The established method, termed Bind&Bite, can be expected to be beneficial for a range of biotechnological and biomedical applications, in which chemical moieties need to be stably attached to proteins in a site-selective fashion.
CRIS-Team Scopus Importer:2023-09-15

Biographical Feature: Bernhard Fleckenstein - Thoma-Kreß, Andrea; Desrosiers, Ronald C.; Gack, Michaela U.; Jung, Jae U.; Überla, Klaus; Kirchhoff, Frank (Journal of Virology, 2021)
CRIS-Team Scopus Importer:2021-09-10
Keywords: Bernhard Fleckenstein; human herpesviruses; mentoring; obituary; retroviruses

Blocking counter regulation of unfolded protein response by targeted protein synthesis inhibition produces highly synergistic cell death in several cancer entities - Müller, Fabian; Gsottberger, Franziska; Meier, Clara; Petkovic, S.; Krumbholz, Manuela; Metzler, Markus; Mackensen, Andreas (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Bornavirus encephalitis as a differential diagnosis to seronegative autoimmune encephalitis - Meier, H.; Bauer, C.; Finkenzeller, W.; Nentwich, J.; Staedt, M.; Steininger, Philipp; Korn, Klaus; Enßer, Armin; Erbguth, F. (Der Nervenarzt, 2022)
CRIS-Team WoS Importer:2022-01-28

Both plasmacytoid dendritic cells and monocytes stimulate natural killer cells early during human herpes simplex virus type 1 infections - Vogel, Karin; Thomann, Sabrina; Vogel, Benjamin; Schuster, Philipp; Schmidt, Barbara (Immunology, 2014)
Herpes simplex virus type 1 (HSV-1), a member of the herpes virus family, is characterized by a short replication cycle, high cytopathogenicity and distinct neurotropism. Primary infection and reactivation may cause severe diseases in immunocompetent and immunosuppressed individuals. This study investigated the role of human plasmacytoid dendritic cells (pDC) in the activation of natural killer (NK) cells for the control of herpesviral infections. Within peripheral blood mononuclear cells, UV-inactivated HSV-1 and CpG-A induced CD69 up-regulation on NK cells, whereas infectious HSV-1 was particularly active in inducing NK cell effector functions interferon-? (IFN-?) secretion and degranulation. The pDC-derived IFN-? significantly contributed to NK cell activation, as evident from neutralization and cell depletion experiments. In addition, monocyte-derived tumour necrosis factor-? (TNF-?) induced after exposure to infectious HSV-1 was found to stimulate IFN-? secretion. A minority of monocytes was shown to be non-productively infected in experiments using fluorescently labelled viruses and quantitative PCR analyses. HSV-1-exposed monocytes up-regulated classical HLA-ABC and non-classical HLA-E molecules at the cell surface in an IFN-?-dependent manner, whereas stress molecules MICA/B were not induced. Notably, depletion of monocytes reduced NK cell effector functions induced by infectious HSV-1 (P < 0.05). Altogether, our data suggest a model in which HSV-1-stimulated pDC and monocytes activate NK cells via secretion of IFN-? and TNF-?. In addition, infection of monocytes induces NK cell effector functions via TNF-?-dependent and TNF-?-independent mechanisms. Hence, pDC and monocytes, which are among the first cells infiltrating herpetic lesions, appear to have important bystander functions for NK cells to control these viral infections.
EVALuna2:8241

Broad and potent antiviral activity of the NAE inhibitor MLN4924 - Le-Trilling, Vu Thuy Khanh; Megger, Dominik A.; Katschinski, Benjamin; Landsberg, Christine D.; Rueckborn, Meike U.; Tao, Sha; Krawczyk, Adalbert; Bayer, Wibke; Drexler, Ingo; Tenbusch, Matthias; Sitek, Barbara; Trilling, Mirko (Scientific Reports, 2016)
In terms of infected human individuals, herpesviruses range among the most successful virus families. Subclinical herpesviral infections in healthy individuals contrast with life-threatening syndromes under immunocompromising and immunoimmature conditions. Based on our finding that cytomegaloviruses interact with Cullin Roc ubiquitin ligases (CRLs) in the context of interferon antagonism, we systematically assessed viral dependency on CRLs by utilizing the drug MLN4924. CRL activity is regulated through the conjugation of Cullins with the ubiquitin-like molecule Nedd8. By inhibiting the Nedd8-activating Enzyme (NAE), MLN4924 interferes with Nedd8 conjugation and CRL activity. MLN4924 exhibited pronounced antiviral activity against mouse and human cytomegalovirus, herpes simplex virus (HSV)- 1 (including multi-drug resistant clinical isolates), HSV-2, adeno and influenza viruses. Human cytomegalovirus genome amplification was blocked at nanomolar MLN4924 concentrations. Global proteome analyses revealed that MLN4924 blocks cytomegaloviral replication despite increased IE1 amounts. Expression of dominant negative Cullins assigned this IE regulation to defined Cullin molecules and phenocopied the antiviral effect of MLN4924.
EVALuna2:8335

BRONJ-related jaw bone is associated with increased Dlx-5 and suppressed osteopontin-implication in the site-specific alteration of angiogenesis and bone turnover by bisphosphonates - Wehrhan, Falk; Amann, Kerstin Ute; Moebius, Patrick; Weber, Manuel; Preidl, Raimund; Ries, Jutta; Stockmann, Philipp (Clinical Oral Investigations, 2015)
Site-specific suppression of bone remodelling has been implicated in bisphosphonate-(BP)-related osteonecrosis of the jaws (BRONJ). Due to the origin of jaw bone from cranial neural crest, osseous differentiation is regulated specifically by the antagonizing BMP-2-downstream-transcription factors Msx-1 and Dlx-5. Osteopontin has been implicated in bone remodelling and angiogenesis. The osteoblast and osteoclast progenitor proliferation mediating Msx-1 has been demonstrated to be suppressed in BRONJ. In vitro BPs were shown to increase Dlx-5 and to suppress osteopontin expression. This study targeted Dlx-5 and osteopontin in BRONJ-related and BP-exposed jaw bone compared with healthy jaw bone samples at protein- and messenger RNA (mRNA) level, since increased Dlx-5 and suppressed osteopontin might account for impaired bone turnover in BRONJ.Fifteen BRONJ-exposed, 15 BP-exposed and 20 healthy jaw bone samples were processed for real-time reverse transcription polymerase chain reaction (RT-PCR) and for immunohistochemistry. Targeting Dlx-5, osteopontin and glyceraldehyde 3-phosphate dehydrogenase mRNA was extracted, quantified by the LabChip-method, followed by quantitative RT-PCR. For immunohistochemistry, an autostaining-based alkaline phosphatase antialkaline phosphatase (APAPP) staining kit was used. Semiquantitative assessment was performed measuring the ratio of stained cells/total number of cells (labelling index, Bonferroni adjustment).The labelling index was significant decreased for osteopontin (p < 0.017) and significantly increased for Dlx-5 (p < 0.021) in BRONJ samples. In BRONJ specimens, a significant fivefold decrease in gene expression for osteopontin (p < 0.015) and a significant eightfold increase in Dlx-5 expression (p < 0.012) were found.BRONJ-related suppression of bone turnover is consistent with increased Dlx-5 expression and with suppression of osteopontin. The BP-related impaired BMP-2-Msx-1-Dlx-5 axis might explain the jaw bone specific alteration by BP.The findings of this study help to explain the restriction of RONJ to craniofacial bones. BRONJ might serve as a model of disease elucidating the specific signal transduction of neural crest cell-derived bone structures in health and disease.
EVALuna2:24383

Butyrophilin 2a2 (Btn2a2) expression on thymic epithelial cells promotes central T cell tolerance and prevents autoimmune disease: Btn2a2 promotes central tolerance - Frech, Michael; Danzer, Heike; Uchil, Pooja; Azizov, Vugar; Schmid, Eva; Schälter, Fabian; Dürholz, Kerstin; Mauro, Daniele; Rauber, Simon; Munoz Becerra, Luis; Taher, Leila; Ciccia, Francesco; et al. (Journal of Autoimmunity, 2023)
Butyrophilins are surface receptors belonging to the immunoglobulin superfamily. While several members of the butyrophilin family have been implicated in the development of unconventional T cells, butyrophilin 2a2 (Btn2a2) has been shown to inhibit conventional T cell activation. Here, we demonstrate that in steady state, the primary source of Btn2a2 are thymic epithelial cells (TEC). Absence of Btn2a2 alters thymic T cell maturation and bypasses central tolerance mechanisms. Furthermore, Btn2a2−/− mice develop spontaneous autoimmunity resembling human primary Sjögren's Syndrome (pSS), including formation of tertiary lymphoid structures (TLS) in target organs. Ligation of Btn2a2 on developing thymocytes is associated with reduced TCR signaling and CD5 levels, while absence of Btn2a2 results in increased TCR signaling and CD5 levels. These results define a novel role for Btn2a2 in promoting central tolerance by modulating TCR signaling strength and indicate a potential mechanism of pSS development.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Autoimmune disease; Autoimmunity; Butyrophilin 2a2 (Btn2a2); Central tolerance; Primary sjögren's syndrome (pSS); Thymic epithelial cells (TEC)

Calcium phosphate nanoparticle-based vaccines as a platform for improvement of HIV-1 env antibody responses by intrastructural help - Damm, Dominik; Rojas-Sánchez, Leonardo; Theobald, Hannah; Sokolova, Viktoriya; Wyatt, Richard T.; Überla, Klaus; Epple, Matthias; Temchura, Vladimir (Nanomaterials, 2019)
Incorporation of immunodominant T-helper epitopes of licensed vaccines into virus-like particles (VLP) allows to harness T-helper cells induced by the licensed vaccines to provide intrastructural help (ISH) for B-cell responses against the surface proteins of the VLPs. To explore whether ISH could also improve antibody responses to calcium phosphate (CaP) nanoparticle vaccines we loaded the nanoparticle core with a universal T-helper epitope of Tetanus toxoid (p30) and functionalized the surface of CaP nanoparticles with stabilized trimers of the HIV-1 envelope (Env) resulting in Env-CaP-p30 nanoparticles. In contrast to soluble Env trimers, Env containing CaP nanoparticles induced activation of naïve Env-specific B-cells in vitro. Mice previously vaccinated against Tetanus raised stronger humoral immune responses against Env after immunization with Env-CaP-p30 than mice not vaccinated against Tetanus. The enhancing effect of ISH on anti-Env antibody levels was not attended with increased Env-specific IFN-γ CD4 T-cell responses that otherwise may potentially influence the susceptibility to HIV-1 infection. Thus, CaP nanoparticles functionalized with stabilized HIV-1 Env trimers and heterologous T-helper epitopes are able to recruit heterologous T-helper cells induced by a licensed vaccine and improve anti-Env antibody responses by intrastructural help.
CRIS-Team Scopus Importer:2019-10-29
Keywords: B-cell targeting; HIV-1 env trimers; Intrastructural help; Nano-vaccines

Capturing schizophrenia-like prodromal symptoms in a spinocerebellar ataxia-17 transgenic rat - Amato, Davide; Canneva, Fabio; Huu Phuc Nguyen,; Bauer, Peter; Riess, Olaf; von Hörsten, Stephan; Müller, Christian P. (Journal of Psychopharmacology, 2017)
RATIONALE: The polyglutamine disease spinocerebellar ataxia type 17 (SCA17) is a neurodegenerative disease leading to severe neurological symptoms during development. Additionally, patients affected by SCA17 display psychosis earlier than their motor disorders. OBJECTIVE: Here the putative psychotic phenotype and endophenotype of transgenic SCA17 rats was examined. METHODS: The expression of schizophrenia-like symptoms was evaluated over a longitudinal period before and after the onset of neurological symptoms in SCA17. To this end, transgenic SCA17 rats' monoamine neurotransmission was investigated along with their locomotion at baseline and in response to amphetamine using in-vivo microdialysis in free moving conditions, their sensorimotor gating using pre-pulse inhibition of startle reaction, and their object memory using the novel object recognition test as an index of cognitive impairments. RESULTS: Presymptomatic SCA17 rats displayed dysregulated monoamine levels at baseline and in response to amphetamine compared with control wild-type (wt) rats. At that stage, neither amphetamine-induced hyperlocomotion nor sensorimotor gating differed from that in wt rats. Symptomatic SCA17 rats developed sensorimotor gating deficits and also showed an impaired object memory, while their monoaminergic responses remained supersensitive to amphetamine. CONCLUSIONS: The data of the present study demonstrate a neurochemical endophenotype in SCA17 rats resembling that of prodromal schizophrenia. These findings suggest that a sensitization of the monoamine systems arises early in adulthood in SCA17 rats and may predispose them to express schizophrenia-like symptoms later in life.
EVALuna2:32791

Cars—a new perspective to hcmv treatment - Bednar, Christopher; Enßer, Armin (Viruses, 2021)
Human cytomegalovirus (HCMV), by primary infection or reactivation, represents a great risk for immune-suppressed or compromised patients. In immunocompetent humans, the immune system suppresses the spread of HCMV during an infection, resulting in a mostly asymptomatic or mild course of the disease, whereas in immune suppressed patients, the compromised host immune response cannot control the viral infection. Multiple viral immunomodulatory mechanisms additionally contribute to immune evasion. Use of chimeric antigen receptors (CARs), a treatment strategy adapted from cancer immunotherapy, is investigated for possible application to combat HCMV and other infections in immunocompromised patients. The administration of CAR+ T-cells directed against HCMV antigens can bypass viral immune evasion and may complement existing treatment methods. This review gives a short overview of HCMV, the obstacles of current treatment options as well as a brief introduction to CARs and the current research situation on CAR+ T-cells against HCMV.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Adoptive T-cell therapy; Antiviral immunotherapy; Chimeric antigen receptor (CAR); Cytotoxic T-lymphocytes; Human cytomegalovirus (HCMV)

CatWalk XT gait parameters: a review of reported parameters in pre-clinical studies of multiple central nervous system and peripheral nervous system disease models - Timotius, Ivanna K.; Roelofs, Reinko F.; Richmond-Hacham, Bar; Noldus, Lucas P.J.J.; von Hörsten, Stephan; Bikovski, Lior (Frontiers in Behavioral Neuroscience, 2023)
Automated gait assessment tests are used in studies of disorders characterized by gait impairment. CatWalk XT is one of the first commercially available automated systems for analyzing the gait of rodents and is currently the most used system in peer-reviewed publications. This automated gait analysis system can generate a large number of gait parameters. However, this creates a new challenge in selecting relevant parameters that describe the changes within a particular disease model. Here, for the first time, we performed a multi-disorder review on published CatWalk XT data. We identify commonly reported CatWalk XT gait parameters derived from 91 peer-reviewed experimental studies in mice, covering six disorders of the central nervous system (CNS) and peripheral nervous system (PNS). The disorders modeled in mice were traumatic brain injury (TBI), stroke, sciatic nerve injury (SNI), spinal cord injury (SCI), Parkinson’s disease (PD), and ataxia. Our review consisted of parameter selection, clustering, categorization, statistical evaluation, and data visualization. It suggests that certain gait parameters serve as potential indicators of gait dysfunction across multiple disease models, while others are specific to particular models. The findings also suggest that the more site-specific the injury is, the fewer parameters are reported to characterize its gait abnormalities. This study strives to present a clearly organized picture of gait parameters used in each one of the different mouse models, potentially helping novel CatWalk XT users to apply this information to similar or related mouse models they are working on.
CRIS-Team Scopus Importer:2023-07-07
Keywords: CatWalk XT; CNS; gait; locomotor deficits; mouse; PNS; rodents

CD161a-positive natural killer (NK) cells and α-smooth muscle actin-positive myofibroblasts were upregulated by extrarenal DPP4 in a rat model of acute renal rejection - Schmid, Franziska; Mayer, Carolin; Büttner-Herold, Maike; von Hörsten, Stephan; Amann, Kerstin Ute; Daniel, Christoph (Diabetes Research and Clinical Practice, 2021)
Aims: Systemic inhibition of dipeptidyl peptidase 4 (DPP4) showed a protective effect in several transplant models. Here we assessed the specific role of extrarenal DPP4 in renal transplant rejection. Methods: Kidneys from wildtype (wt) F344 rats were either transplanted in wt Dark Agouti or congenic rats not expressing DPP4. The remaining, not transplanted donor kidney served as healthy controls. To investigate early inflammatory events rats were sacrificed 3 days after transplantation and kidneys were evaluated for inflammatory cells, capillary rarefaction, proliferation, apoptosis and myofibroblasts by immunohistochemistry. Results: Capillary ERG-1-positive endothelial cells were significantly more abundant in renal cortex when transplanted into DPP4 deficient compared to wt recipients. In contrast, TGF-ß and myofibroblasts were reduced by more than 25% in kidneys transplanted into DPP4 deficient compared to wt recipients. Numbers of CD161a-positive NK-cells were significantly lower in allografts in DPP4 deficient compared to wt recipients. Numbers of all other investigated immune cells were not affected by the lack of extrarenal DPP4. Conclusion: In early transplant rejection extrarenal DPP4 is involved in the recruitment of NK-cells and early fibrosis. Beneficial effects were less pronounced than reported for systemic DPP4 inhibition, indicating that renal DPP4 is an important player in transplantation-mediated injury.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Extrarenal DPP4; Fibrosis; Inflammation; Renal transplantation

Cd4+ T cells induced by tuberculosis subunit vaccine h1 can improve the hiv-1 env humoral response by intrastructural help - Klessing, Stephan; Temchura, Vladimir; Tannig, Pierre; Peter, Antonia Sophia; Christensen, Dennis; Lang, Roland; Überla, Klaus (Vaccines, 2020)
The induction of a potent and long-lasting, broadly neutralizing antibody response is one of the most promising approaches in HIV-1 vaccination. Recently, we demonstrated that Gagspecific T helper cells induced by DNA priming can enhance and modulate the HIV Env-specific B cell response upon virus-like particle (VLP) boost by intrastructural help (ISH). In order to minimize the induction of potentially harmful HIV specific TH cells, we explored the possibility to harness the heterologous TH cells induced by a recombinant tuberculosis subunit vaccine H1, which contains a fusion protein of Ag85B and ESAT-6 antigens in combination with the liposomal adjuvant CAF01. To provide ISH, immunodominant MHC-II restricted peptides from the H1 vaccine were genetically incorporated into the HIV 1 Gag protein and used for HIV VLP production. ISH effects on Envspecific antibody levels and B cell differentiation were analyzed in mice primed against H1 and boosted with VLPs. In contrast to non-primed mice, a significant increase of Env-specific IgG levels for up to 26 weeks after the last immunization was observed. This increase was largely caused by elevated IgG2b and IgG2c levels in mice that received H1 priming. Additionally, ISH enhanced the frequency of Env-specific long-lived plasma cells in the bone marrow. In this study, we were able to demonstrate that a heterologous prime-boost regimen consisting of the H1 tuberculosis subunit vaccine and T helper epitope modified HIV-1 VLPs resulted in enhanced HIV Env antibody and B cell responses, mediated by intrastructural help.
CRIS-Team Scopus Importer:2020-10-23
Keywords: H1 tuberculosis vaccine; HIV-1 vaccine; IgG isotype modulation; Intrastructural help

CD83 and GRASP55 interact in human dendritic cells - Stein, Marcello F.; Blume, Katja; Heilingloh, Christiane; Kummer, Mirko; Biesinger, Brigitte; Sticht, Heinrich; Steinkasserer, Alexander (Biochemical and Biophysical Research Communications, 2015)
CD83 is one of the best known surface markers for mature human dendritic cells (DCs). The full-length 45 kDa type-I membrane-bound form (mbCD83) is strongly glycosylated upon DCs maturation. As co-stimulatory properties of CD83 are attributed to mbCD83 surface expression is required for efficient T-cell stimulation by mature DCs. By yeast two-hybrid screening, we were able to identify GRASP55 as interaction partner of CD83. DCs maturation induces endogenous CD83 protein expression with simultaneous regulation of CD83 glycosylation, interaction and co-localization with GRASP55 and CD83 surface exposure. GRASP55 is especially known for its role in maintaining Golgi architecture, but also plays a role in Golgi transport of specific cargo proteins bearing a C-terminal valine residue. Here we additionally demonstrate that binding of CD83 and GRASP55 rely on the C-terminal TELV-motif of CD83. Mutation of this TELV-motif not only disrupted binding to GRASP55, but also altered the glycosylation pattern of CD83 and reduced its membrane expression. Here we show for the first time that GRASP55 interacts with CD83 shortly after induction of DC maturation and that this interaction plays a role in CD83 glycosylation as well as in surface expression of CD83 on DCs.
EVALuna2:8259

Cell fusion induced by a fusion-active form of human cytomegalovirus glycoprotein B (gB) is inhibited by antibodies directed at antigenic domain 5 in the ectodomain of gB - Reuter, Nina; Kropff, Barbara; Schneiderbanger, Julia; Alt, Mira; Krawczyk, Adalbert; Sinzger, Christian; Winkler, Thomas; Britt, William J.; Mach, Michael; Thomas, Marco (Journal of Virology, 2020)
Human cytomegalovirus (HCMV) is a ubiquitous pathogen that can cause severe clinical disease in allograft recipients and infants infected in utero. Virus-neutralizing antibodies defined in vitro have been proposed to confer protection against HCMV infection, and the virion envelope glycoprotein B (gB) serves as a major target of neutralizing antibodies. The viral fusion protein gB is nonfusogenic on its own and requires glycoproteins H (gH) and L (gL) for membrane fusion, which is in contrast to requirements of related class III fusion proteins, including vesicular stomatitis virus glycoprotein G (VSV-G) or baculovirus gp64. To explore requirements for gB's fusion activity, we generated a set of chimeras composed of gB and VSV-G or gp64, respectively. These gB chimeras were intrinsically fusion active and led to the formation of multinucleated cell syncytia when expressed in the absence of other viral proteins. Utilizing a panel of virus-neutralizing gB-specific monoclonal antibodies (MAbs), we could demonstrate that syncytium formation of the fusogenic gB/VSV-G chimera can be significantly inhibited by only a subset of neutralizing MAbs which target antigenic domain 5 (AD-5) of gB. This observation argues for differential modes of action of neutralizing anti-gB MAbs and suggests that blocking the membrane fusion function of gB could be one mechanism of antibody-mediated virus neutralization. In addition, our data have important implications for the further understanding of the conformation of gB that promotes membrane fusion as well as the identification of structures in AD-5 that could be targeted by antibodies to block this early step in HCMV infection. IMPORTANCE HCMV is a major global health concern, and antiviral chemotherapy remains problematic due to toxicity of available compounds and the emergence of drug-resistant viruses. Thus, an HCMV vaccine represents a priority for both governmental and pharmaceutical research programs. A major obstacle for the development of a vaccine is a lack of knowledge of the nature and specificities of protective immune responses that should be induced by such a vaccine. Glycoprotein B of HCMV is an important target for neutralizing antibodies and, hence, is often included as a component of intervention strategies. By generation of fusion-active gB chimeras, we were able to identify target structures of neutralizing antibodies that potently block gB-induced membrane fusion. This experimental system provides an approach to screen for antibodies that interfere with gB's fusogenic activity. In summary, our data will likely contribute to both rational vaccine design and the development of antibody-based therapies against HCMV.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Antibodies; Cell-cell fusion; Glycoprotein B; Herpesvirus; Human cytomegalovirus

Cell surface markers in HTLV-1 pathogenesis - Kreß, Andrea; Grassmann, Ralph; Fleckenstein, Bernhard (Viruses, 2011)
The phenotype of HTLV-1-transformed CD4 + T lymphocytes largely depends on defined viral effector molecules such as the viral oncoprotein Tax. In this review, we exemplify the expression pattern of characteristic lineage markers, costimulatory receptors and ligands of the tumor necrosis factor superfamily, cytokine receptors, and adhesion molecules on HTLV-1-transformed cells. These molecules may provide survival signals for the transformed cells. Expression of characteristic surface markers might therefore contribute to persistence of HTLV-1-transformed lymphocytes and to the development of HTLV-1-associated disease. © 2011 by the authors; licensee MDPI, Basel, Switzerland.
Created from Fastlane, Scopus look-up
Keywords: ATLL; Cytokine receptor; Differentiation; HAM/TSP; HTLV-1; Interleukin; Oncoprotein; Phenotype; Tax; TNFR

Cellular and humoral immune responses to SARS-CoV-2 vaccination in patients after CD19.CAR T-cell therapy - Reimann, Hannah; Kremer, Anita; Blumenberg, Viktoria; Schmidt, Katja; Aigner, Michael; Jacobs, Benedikt; Eisenhauer, Nina; Kämpf, Alina; Rösler, Wolf; Kharboutli, Soraya; Mougiakakos, Dimitrios; Lang, Vanessa; et al. (Blood Advances, 2023)
EVALuna2:512817

Centrosomal protein TRIM43 restricts herpesvirus infection by regulating nuclear lamina integrity - Full, Florian; Van Gent, Michiel; Sparrer, Konstantin M. J.; Chiang, Cindy; Zurenski, Matthew A.; Scherer, Myriam; Brockmeyer, Norbert H.; Heinzerling, Lucie; Stürzl, Michael; Korn, Klaus; Stamminger, Thomas; Enßer, Armin; et al. (Nature Microbiology, 2019)
Tripartite motif (TRIM) proteins mediate antiviral host defences by either directly targeting viral components or modulating innate immune responses. Here we identify a mechanism of antiviral restriction in which a TRIM E3 ligase controls viral replication by regulating the structure of host cell centrosomes and thereby nuclear lamina integrity. Through RNAi screening we identified several TRIM proteins, including TRIM43, that control the reactivation of Kaposi's sarcoma-associated herpesvirus. TRIM43 was distinguished by its ability to restrict a broad range of herpesviruses and its profound upregulation during herpesvirus infection as part of a germline-specific transcriptional program mediated by the transcription factor DUX4. TRIM43 ubiquitinates the centrosomal protein pericentrin, thereby targeting it for proteasomal degradation, which subsequently leads to alterations of the nuclear lamina that repress active viral chromatin states. Our study identifies a role of the TRIM43-pericentrin-lamin axis in intrinsic immunity, which may be targeted for therapeutic intervention against herpesviral infections.
EVALuna2:35255

Cervical intraepithelial neoplasia grade 2/3: development during pregnancy and postpartum - Stübs, Frederik; Mergel, F.; Koch, M. C.; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; Mehlhorn, G. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Cervical intraepithelial neoplasia grade 3: development during pregnancy and postpartum - Stübs, Frederik; Mergel, Franziska; Koch, Martin; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; Mehlhorn, Grit (Archives of Gynecology and Obstetrics, 2022)
Purpose: The aims of the present study were to evaluate the development of untreated cervical intraepithelial neoplasia (CIN) 3 during pregnancy and to assess persistence, progression, and regression rates postpartum to identify factors associated with regression. Methods: In a tertiary gynecology and obstetrics department, a total of 154 pregnant women with CIN 3 were treated in the dysplasia unit. The follow-up findings were analyzed retrospectively on the basis of histological, cytological, and human papillomavirus (HPV) testing of 154 pregnant women confirmed as having CIN 3 in colposcopically guided biopsies. Results: The rates of persistence, regression, and progression of CIN 3 in these women were 76.1%, 20% and 3.2%, respectively. Data for the delivery mode was available for 126 women. The rate of regression was almost twice as high with vaginal delivery as with cesarean section, at 27.4 vs. 15.2%, whereas the rate of progression was lower with vaginal delivery, at 2.7 vs. 6.5%. Conclusion: The rate of persistence of CIN observed in this study is comparable to that reported in other studies. The study provides strong evidence for greater regression among women who have vaginal deliveries. Careful work-up is recommended postpartum for this group of women in order to rule out persistent CIN 3 or invasive disease.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Cervical dysplasia; High-grade squamous intraepithelial lesion (HSIL); Mode of delivery; Pregnancy; Treatment

Characterization of a universal screening approach for congenital CMV infection based on a highly-sensitive, quantitative, multiplex real-time PCR assay - Nagel, Angela; Dimitrakopoulou, Emmanouela; Teig, Norbert; Kern, Peter; Lücke, Thomas; Michna, Dariusz; Korn, Klaus; Steininger, Philipp; Shahada, Khalid; Neumann, Katrin; Überla, Klaus (PLoS ONE, 2020)
The majority of congenital cytomegalovirus (cCMV) infections are asymptomatic at birth and therefore not diagnosed. Approximately 10-15% of these infants develop late-onset hearing loss and other developmental disorders. Implementation of a universal screening approach at birth may allow early initiation of symptomatic interventions due to a closer follow-up of infants at risk and offers the opportunity to consider treatment of late-onset disease. Real-time PCR assays for the detection of CMV DNA in buccal swab samples demonstrated feasibility and good clinical sensitivity in comparison to a rapid culture screening assay. Because most cCMV infections remain asymptomatic, a universal screening assay that stratifies CMV infected infants according to low and high risk of late-onset cCMV disease could limit the parental anxiety and reduce follow-up costs. We therefore developed and characterized a screening algorithm based on a highly-sensitive quantitative real-time PCR assay that is compatible with centralized testing of samples from universal screening and allows to determine CMV DNA load of saliva samples either as International Units (IU)/ml saliva or IU/105 cell equivalents. 18 of 34 saliva samples of newborns that tested positively by the screening algorithm were confirmed by detection of CMV DNA in blood and/or urine samples obtained during the first weeks of life. All screening samples that could not be confirmed had viral loads of <2.3x105 IU/ml saliva (median: 6.8x103) or 1.3x105 IU/105 cell equivalents (median: 4.0x102). The viral load of screening samples with confirmed cCMV infection ranged from 7.5x102 to 8.2x109 IU/ml saliva (median: 9.3x107) or 1.5x102 to 5.6x1010 IU/105 cell equivalents (median: 3.5x106). Clinical follow-up of these newborns with confirmed cCMV infection should reveal whether the risk of late-onset cCMV disease correlates with CMV DNA load in early life saliva samples and whether a cut-off can be defined identifying cCMV infected infants with or without risk for late-onset cCMV disease.
CRIS-Team Scopus Importer:2020-01-21

Characterization of recombinant human cytomegaloviruses encoding IE1 mutants L174P and 1-382 reveals that viral targeting of PML bodies perturbs both intrinsic and innate immune responses - Scherer, Myriam; Otto, Victoria; Stump, Joachim; Klingl, Stefan; Müller, Regina; Reuter, Nina; Muller, Yves; Sticht, Heinrich; Stamminger, Thomas (Journal of Virology, 2015)
PML is the organizer of cellular structures termed nuclear domain 10 (ND10) or PML-nuclear bodies (PML-NBs) that act as key mediators of intrinsic immunity against human cytomegalovirus (HCMV) and other viruses. The antiviral function of ND10 is antagonized by viral regulatory proteins such as the immediate early protein IE1 of HCMV. IE1 interacts with PML through its globular core domain (IE1) and induces ND10 disruption in order to initiate lytic HCMV infection. Here, we investigate the consequences of a point mutation (L174P) in IE1CORE, which was shown to abrogate the interaction with PML, for lytic HCMV infection. We found that a recombinant HCMV encoding IE1-L174P displays a severe growth defect similar to that of an IE1 deletion virus. Bioinformatic modeling based on the crystal structure of IE1 suggested that insertion of proline into the highly alpha-helical domain severely affects its structural integrity. Consistently, L174P mutation abrogates the functionality of IE1 and results in degradation of the IE1 protein during infection. In addition, our data provide evidence that IE1 as expressed by a recombinant HCMV encoding IE1 1-382 not only is required to antagonize PML-mediated intrinsic immunity but also affects a recently described function of PML in innate immune signaling. We demonstrate a coregulatory role of PML in type I and type II interferon-induced gene expression and provide evidence that upregulation of interferon-induced genes is inhibited by IE1. In conclusion, our data suggest that targeting PML by viral regulatory proteins represents a strategy to antagonize both intrinsic and innate immune mechanisms.
EVALuna2:8299

Characterization of SARS-CoV-2 Escape Mutants to a Pair of Neutralizing Antibodies Targeting the RBD and the NTD - Peter, Antonia Sophia; Grüner, Eva; Socher, Eileen; Fraedrich, Kirsten; Richel, Elie; Müller-Schmucker, Sandra; Cordsmeier, Arne; Enßer, Armin; Sticht, Heinrich; Überla, Klaus (International Journal of Molecular Sciences, 2022)
Mutations in the spike protein of SARS-CoV-2 can lead to evasion from neutralizing antibodies and affect the efficacy of passive and active immunization strategies. Immunization of mice harboring an entire set of human immunoglobulin variable region gene segments allowed to identify nine neutralizing monoclonal antibodies, which either belong to a cluster of clonally related RBD or NTD binding antibodies. To better understand the genetic barrier to emergence of SARS-CoV-2 variants resistant to these antibodies, escape mutants were selected in cell culture to one antibody from each cluster and a combination of the two antibodies. Three independently derived escape mutants to the RBD antibody harbored mutations in the RBD at the position T478 or S477. These mutations impaired the binding of the RBD antibodies to the spike protein and conferred resistance in a pseudotype neutralization assay. Although the binding of the NTD cluster antibodies were not affected by the RBD mutations, the RBD mutations also reduced the neutralization efficacy of the NTD cluster antibodies. The mutations found in the escape variants to the NTD antibody conferred resistance to the NTD, but not to the RBD cluster antibodies. A variant resistant to both antibodies was more difficult to select and only emerged after longer passages and higher inoculation volumes. VOC carrying the same mutations as the ones identified in the escape variants were also resistant to neutralization. This study further underlines the rapid emergence of escape mutants to neutralizing monoclonal antibodies in cell culture and indicates the need for thorough investigation of escape mutations to select the most potent combination of monoclonal antibodies for clinical use.
CRIS-Team WoS Importer:2022-08-26

Characterization of Serum and Mucosal SARS-CoV-2-Antibodies in HIV-1-Infected Subjects after BNT162b2 mRNA Vaccination or SARS-CoV-2 Infection - Schmidt, Katja G.; Harrer, Ellen; Tascilar, Koray; Kuebel, Sabrina; El Kenz, Boutaina; Simon, David; Schett, Georg; Nganou-Makamdop, Krystelle; Harrer, Thomas; Hartmann, Fabian (Viruses, 2022)
Only limited data are available regarding the immunogenicity of the BNT162b2 mRNA vaccine in HIV-1+ patients. Therefore, we investigated the humoral immune response after BNT162b2-mRNA vaccination or SARS-CoV-2 infection in HIV-1+ patients on antiretroviral therapy compared to HIV-1-uninfected subjects. Serum and saliva samples were analysed by SARS-CoV-2 spike-specific IgG and IgA ELISAs and a surrogate neutralization assay. While all subjects developed anti-spike IgG and IgA and neutralizing antibodies in serum after two doses of BNT162b2 mRNA vaccine, the HIV-1+ subjects displayed significantly lower neutralizing capacity and anti-spike IgA in serum compared to HIV-1-uninfected subjects. Serum levels of anti-spike IgG and neutralizing activity were significantly higher in vaccinees compared to SARS-CoV-2 convalescents irrespective of HIV-1 status. Among SARS-CoV-2 convalescents, there was no significant difference in spike-specific antibody response between HIV-1+ and uninfected subjects. In saliva, anti-spike IgG and IgA antibodies were detected both in vaccinees and convalescents, albeit at lower frequencies compared to the serum and only rarely with detectable neutralizing activity. In summary, our study demonstrates that the BNT162b2 mRNA vaccine induces SARS-CoV-2-specific antibodies in HIV-1-infected patients on antiretroviral therapy, however, lower vaccine induced neutralization activity indicates a lower functionality of the humoral vaccine response in HIV-1+ patients.
CRIS-Team Scopus Importer:2022-04-15
Keywords: antibody; HIV-1; humoral immune response; mucosal immunity; SARS-CoV-2

Characterizing the interaction between the htlv-1 transactivator tax-1 with transcription elongation factor ell2 and its impact on viral transactivation - Kohrt, Stephan; Strobel, Sarah; Mann, Melanie; Sticht, Heinrich; Fleckenstein, Bernhard; Thoma-Kreß, Andrea (International Journal of Molecular Sciences, 2021)
The human T-cell leukemia virus type 1 (HTLV-1)-encoded transactivator and oncoprotein Tax-1 is essential for HTLV-1 replication. We recently found that Tax-1 interacts with transcription elongation factor for RNA polymerase II 2, ELL2, which enhances Tax-1-mediated transactivation of the HTLV-1 promotor. Here, we characterize the Tax-1:ELL2 interaction and its impact on viral transactivation by confocal imaging, co-immunoprecipitation, and luciferase assays. We found that Tax-1 and ELL2 not only co-precipitate, but also co-localize in dot-like structures in the nucleus. Tax-1:ELL2 complex formation occurred independently of Tax-1 point mutations, which are crucial for post translational modifications (PTMs) of Tax-1, suggesting that these PTMs are irrelevant for Tax-1:ELL2 interaction. In contrast, Tax-1 deletion mutants lacking either N-terminal (aa 1–37) or C-terminal regions (aa 150–353) of Tax-1 were impaired in interacting with ELL2. Contrary to Tax-1, the related, non-oncogenic Tax-2B from HTLV-2B did not interact with ELL2. Finally, we found that ELL2-R1 (aa 1–353), which carries an RNA polymerase II binding domain, and ELL2-R3 (aa 515–640) are sufficient to interact with Tax-1; however, only ELL2-truncations expressing R1 could enhance Tax-1-mediated transactivation of the HTLV-1 promoter. Together, this study identifies domains in Tax-1 and ELL2 being required for Tax-1:ELL2 complex formation and for viral transactivation.
CRIS-Team Scopus Importer:2021-12-24
Keywords: ELL2; HTLV-1; Human T-cell leukemia virus type 1; Tax-1; Tax-2; Transcription elongation factor for RNA polymerase II; Viral oncoprotein; Viral transactivation

Chemically sulfated polysaccharides from natural sources: Assessment of extraction-sulfation efficiencies, structural features and antiviral activities - Mukherjee, Shuvam; Ghosh, Kanika; Hahn, Friedrich; Wangen, Christina; Strojan, Hanife; Müller, Regina; Anand, Namrata; Ali, Imran; Bera, Kaushik; Ray, Bimalendu; Hutterer, Corina; Marschall, Manfred; et al. (International Journal of Biological Macromolecules, 2019)
The provisioning of compound libraries with a high degree of diversity and attractive pharmacological properties is a limiting step in drug development. This study reports the production of highly bioactive sulfated polysaccharides, originally present in a nonsulfated, dormant state in natural sources, and demonstrates their antiviral activity (human cytomegalovirus EC50 values of 2.34–7.77 μg/mL) at a low degree of cytotoxicity. Furthermore, data strongly suggested the inhibition of virus entry as the main mode of antiviral action. Remarkably, the utilized oleum-DMF reagent was able to generate a range of sulfated polysaccharides from various natural sources, possessing varying saccharide compositions, degrees of sulfation (0.4–1.7) and molecular masses (38–94,000 g/mol). Typically, in a matter of minutes, this reagent not only solubilized polysaccharides but also chemically converted their hydroxyl functionality into sulfates. The most active sulfated polysaccharide (EC50 of 2.62 μg/mL) proved to be a 94,000 g/mol branched glucan with sulfates at C-6/C-3,6/C-2,3,6 positions. In conclusion, the important determinants of such compounds' antiviral activity are: (i) degree of sulfation, (ii) molecular mass and (iii) structural features. Thus, our approach offers a huge prospect for the improvement of natural source-derived libraries based on biologically active polysaccharides with diversified chemical profiles.
CRIS-Team Scopus Importer:2019-06-28
Keywords: Antiviral activities; Functionalization; Natural products; Polysaccharides; Structural features

Chromatin-Remodeling Factor SPOC1 Acts as a Cellular Restriction Factor against Human Cytomegalovirus by Repressing the Major Immediate Early Promoter - Reichel, Anna; Stilp, Anne-Charlotte; Scherer, Myriam; Reuter, Nina; Lukassen, Sören; Kasmapour, Bahram; Schreiner, Sabrina; Cicin-Sain, Luka; Winterpacht, Andreas; Stamminger, Thomas (Journal of Virology, 2018)
The cellular protein SPOC1 (survival time-associated PHD [plant homeodomain] finger protein in ovarian cancer 1) acts as a regulator of chromatin structure and the DNA damage response. It binds H3K4me2/3-containing chromatin and promotes DNA condensation by recruiting corepressors such as KAP-1 and H3K9 methyltransferases. Previous studies identified SPOC1 as a restriction factor against human adenovirus (HAdV) infection that is antagonized by E1B-55K/E4-orf6-dependent proteasomal degradation. Here, we demonstrate that, in contrast to HAdV-infected cells, SPOC1 is transiently upregulated during the early phase of human cytomegalovirus (HCMV) replication. We show that the expression of immediate early protein 1 (IE1) is sufficient and necessary to induce SPOC1. Additionally, we discovered that during later stages of infection, SPOC1 is downregulated in a glycogen synthase kinase 3β (GSK-3β)-dependent manner. We provide evidence that SPOC1 overexpression severely impairs HCMV replication by repressing the initiation of viral immediate early (IE) gene expression. Consistently, we observed that SPOC1-depleted primary human fibroblasts displayed an augmented initiation of viral IE gene expression. This occurs in a multiplicity of infection (MOI)-dependent manner, a defining hallmark of intrinsic immunity. Interestingly, repression requires the presence of high SPOC1 levels at the start of infection, while later upregulation had no negative impact, suggesting distinct temporal roles of SPOC1 during the HCMV replicative cycle. Mechanistically, we observed a highly specific association of SPOC1 with the major immediate early promoter (MIEP), strongly suggesting that SPOC1 inhibits HCMV replication by MIEP binding and the subsequent recruitment of heterochromatin-building factors. Thus, our data add SPOC1 as a novel factor to the endowment of a host cell to restrict cytomegalovirus infections.IMPORTANCE Accumulating evidence indicates that during millennia of coevolution, host cells have developed a sophisticated compilation of cellular factors to restrict cytomegalovirus infections. Defining this equipment is important to understand cellular barriers against viral infection and to develop strategies to utilize these factors for antiviral approaches. So far, constituents of PML nuclear bodies and interferon gamma-inducible protein 16 (IFI16) were known to mediate intrinsic immunity against HCMV. In this study, we identify the chromatin modulator SPOC1 as a novel restriction factor against HCMV. We show that preexisting high SPOC1 protein levels mediate a silencing of HCMV gene expression via a specific association with an important viral cis-regulatory element, the major immediate early promoter. Since SPOC1 expression varies between cell types, this factor may play an important role in tissue-specific defense against HCMV.
EVALuna2:34842

Class switch towards non-inflammatory, spike-specific IgG4 antibodies after repeated SARS-CoV-2 mRNA vaccination - Irrgang, Pascal; Gerling, Juliane; Kocher, Katharina; Lapuente, Dennis; Steininger, Philipp; Habenicht, Katharina Marie; Wytopil, Monika; Beileke, Stephanie; Schäfer, Simon; Zhong, Jahn; Ssebyatika, George; Krey, Thomas; et al. (Science immunology, 2022)
RNA vaccines are efficient preventive measures to combat the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. High levels of neutralizing SARS-CoV-2 antibodies are an important component of vaccine-induced immunity. Shortly after the initial two mRNA vaccine doses, the immunoglobulin G (IgG) response mainly consists of the proinflammatory subclasses IgG1 and IgG3. Here, we report that several months after the second vaccination, SARS-CoV-2–specific antibodies were increasingly composed of noninflammatory IgG4, which were further boosted by a third mRNA vaccination and/or SARS-CoV-2 variant breakthrough infections. IgG4 antibodies among all spike-specific IgG antibodies rose, on average, from 0.04% shortly after the second vaccination to 19.27% late after the third vaccination. This induction of IgG4 antibodies was not observed after homologous or heterologous SARS-CoV-2 vaccination with adenoviral vectors. Single-cell sequencing and flow cytometry revealed substantial frequencies of IgG4-switched B cells within the spike-binding memory B cell population [median of 14.4%; interquartile range (IQR) of 6.7 to 18.1%] compared with the overall memory B cell repertoire (median of 1.3%; IQR of 0.9 to 2.2%) after three immunizations. This class switch was associated with a reduced capacity of the spike-specific antibodies to mediate antibody-dependent cellular phagocytosis and complement deposition. Because Fc-mediated effector functions are critical for antiviral immunity, these findings may have consequences for the choice and timing of vaccination regimens using mRNA vaccines, including future booster immunizations against SARS-CoV-2.<br

Clinical and immunological benefits of full primary COVID-19 vaccination in individuals with SARS-CoV-2 breakthrough infections: A prospective cohort study in non-hospitalized adults - Prelog, Martina; Jeske, Samuel D.; Asam, Claudia; Fuchs, Andre; Wieser, Andreas; Gall, Christine; Wytopil, Monika; Müller-Schmucker, Sandra; Beileke, Stephanie; Goekkaya, Mehmet; Kling, Elisabeth; Geldmacher, Christof; et al. (Journal of Clinical Virology, 2024)
Background: SARS-CoV-2 variants of concern (VOC) may result in breakthrough infections (BTIs) in vaccinated individuals. The aim of this study was to investigate the effects of full primary (two-dose) COVID-19 vaccination with wild-type-based SARS-CoV-2 vaccines on symptoms and immunogenicity of SARS-CoV-2 VOC BTIs. Methods: In a longitudinal multicenter controlled cohort study in Bavaria, Germany, COVID-19 vaccinated and unvaccinated non-hospitalized individuals were prospectively enrolled within 14 days of a PCR-confirmed SARS-CoV-2 infection. Individuals were visited weekly up to 4 times, performing a structured record of medical data and viral load assessment. SARS-CoV-2-specific antibody response was characterized by anti-spike-(S)- and anti-nucleocapsid-(N)-antibody concentrations, anti-S-IgG avidity and neutralization capacity. Results: A total of 300 individuals (212 BTIs, 88 non-BTIs) were included with VOC Alpha or Delta SARS-CoV-2 infections. Full primary COVID-19 vaccination provided a significant effectiveness against five symptoms (relative risk reduction): fever (33 %), cough (21 %), dysgeusia (22 %), dizziness (52 %) and nausea/vomiting (48 %). Full primary vaccinated individuals showed significantly higher 50 % inhibitory concentration (IC50) values against the infecting VOC compared to unvaccinated individuals at week 1 (269 vs. 56, respectively), and weeks 5–7 (1,917 vs. 932, respectively) with significantly higher relative anti-S-IgG avidity (78% vs. 27 % at week 4, respectively). Conclusions: Full primary COVID-19 vaccination reduced symptom frequencies in non-hospitalized individuals with BTIs and elicited a more rapid and longer lasting neutralization capacity against the infecting VOC compared to unvaccinated individuals. These results support the recommendation to offer at least full primary vaccination to all adults to reduce disease severity caused by immune escape-variants.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Antibodies; Breakthrough infection; COVID-19 symptoms; SARS-CoV-2; Vaccine effectiveness; Viral load

Clinical Characteristics of Influenza in Season 2017/2018 in a German Emergency Department: A Retrospective Analysis - Mohammad, Sonia; Korn, Klaus; Schellhaas, Barbara; Neurath, Markus; Görtz, Rüdiger (Microbiology Insights, 2019)
Introduction: Influenza infection is a viral disease with significant morbidity and mortality during the cold months. Clinical presentation typically includes cough, fever, and pain. Influenza disease is hardly diagnosed only on the basis of clinical symptoms due to similar clinical presentation of other diseases such as a typical cold or other flu-like diseases. We evaluated patients with proven influenza who presented at an emergency department of internal medicine in a university hospital according to the clinical presentation and different age groups. Materials and Methods: From October 2017 to April 2018, 723 reverse transcription-polymerase chain reaction (RT-PCR) tests for influenza were performed in the emergency department on patients with suspected influenza diagnosed clinically. A total of 240 influenza-positive patients were retrospectively assessed for documented main symptoms, vital parameters, risk factors for an unfavorable course, hospitalization, and death. Results: The mean age of influenza patients was 65 years. Overall, 30 patients were aged 18 to 39 years, 48 patients 40 to 59 years, and 162 patients ⩾60 years. Influenza B in 168 (70%) was predominant to 72 influenza A (mostly H1N1). In only 30% of the patients all three typical symptoms (cough, fever, and headache/myalgia) were documented. Headache or myalgia (with 34%) was rather uncommon in influenza B. Sudden onset was cited in only 5.4%; 57% of all influenza patients were in hospital for a mean of 7.1 days, and 5.8% of all influenza patients died. Patients aged above 60 years had more risk factors, showed typical symptoms less frequently, and were hospitalized longer than younger patients (<60 and <40 years). Conclusions: At an emergency department of internal medicine, influenza-diseased patients are of higher age, show an increased number of comorbidities, and are more likely to have milder symptoms documented. Elderly patients with influenza have a higher hospitalization rate with a longer hospital stay as compared with younger patients.
EVALuna2:212379

Clinically significant CMV (re)activation during or after radiotherapy/chemotherapy of the brain : Correlation with neurological deterioration and improvement upon antiviral treatment - Goerig, Nicole; Semrau, S.; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Dörfler, Arnd; Putz, Florian; Gaipl, Udo; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
For both patients with high-grade gliomas and multiple cerebral metastases, radio(chemo)therapy is the standard therapy. Neurological decline during treatment is rarely attributed to infections of the brain but to tumor progression or side effects of radiotherapy.We present 4 cases of cytomegalovirus (CMV) viremia associated with neurological deterioration, which occurred during or shortly after radiotherapy and/or chemotherapy of the brain (brain metastases 2, high-grade glioma 1, carcinoma infiltrating brain 1). In all cases, neurological decline was sudden and unexpected, and causes such as increased intracranial pressure or tumor progression could be excluded radiologically. Treatment with dexamethasone and mannitol had no or only very short-term effects. General infections were either excluded or receding before the neurological symptoms occurred. All patients presented with decreasing levels of thrombocytes. In all cases, CMV (re)activation could be proven using blood test for CMV-DNA. The anti-CMV-IgG status suggested reactivation rather than a primary infection. One patient died within 72 h of onset of the symptoms (results of CMV tests were received postmortem). Diagnosis of 3 patients allowed successful administration of antiviral treatment, which greatly improved the general and neurological conditions of the patients within 48 h.Neurological deterioration during RT is hardly ever attributed to viral infections. These cases suggest that CMV reactivation and subsequent infection might actually be causative and has to be considered and treated.Further prospective studies verifying and investigating this observation in terms of frequency and clinical relevance seem indicated.
EVALuna2:8302

Cloning of a passage-free SARS-CoV-2 genome and mutagenesis using red recombination - Herrmann, Alexandra; Jungnickl, Doris; Cordsmeier, Arne; Peter, Antonia Sophia; Überla, Klaus; Enßer, Armin (International Journal of Molecular Sciences, 2021)
The ongoing pandemic coronavirus (CoV) disease 2019 (COVID-19) by severe acute respiratory syndrome CoV-2 (SARS-CoV-2) has already caused substantial morbidity, mortality, and economic devastation. Reverse genetic approaches to generate recombinant viruses are a powerful tool to characterize and understand newly emerging viruses. To contribute to the global efforts for countermeasures to control the spread of SARS-CoV-2, we developed a passage-free SARS-CoV-2 clone based on a bacterial artificial chromosome (BAC). Moreover, using a Lambda-based Red recombination, we successfully generated different reporter and marker viruses, which replicated similar to a clinical isolate in a cell culture. Moreover, we designed a full-length reporter virus encoding an additional artificial open reading frame with wild-type-like replication features. The virus-encoded reporters were successfully applied to ease antiviral testing in cell culture models. Furthermore, we designed a new marker virus encoding 3xFLAG-tagged nucleocapsid that allows the detection of incoming viral particles and, in combination with bio-orthogonal labeling for the visualization of viral RNA synthesis via click chemistry, the spatiotemporal tracking of viral replication on the single-cell level. In summary, by applying BAC-based Red recombination, we developed a powerful, reliable, and convenient platform that will facilitate studies answering numerous questions concerning the biology of SARS-CoV-2.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Bacterial artificial chromosome; COVID-19 pandemic; Incoming viral particles; Recombinant virus; Red recombination; Reporter virus; Reverse genetics; SARS-CoV-2

Collagen iv (Col4a1, col4a2), a component of the viral biofilm, is induced by the htlv-1 oncoprotein tax and impacts virus transmission - Millen, Sebastian; Groß, Christine; Donhauser, Norbert; Mann, Melanie; Péloponèse, Jean Marie; Thoma-Kreß, Andrea (Frontiers in Microbiology, 2019)
Human T-cell leukemia virus type 1 (HTLV-1) is the etiologic agent for Adult T-Cell Leukemia/Lymphoma (ATLL) and HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP). HTLV-1 infects CD4+ T-cells via cell-to-cell transmission requiring reorganization of the cytoskeleton and expression of the viral transactivator and oncoprotein Tax. Viruses spread at the virological synapse (VS), a virus-induced specialized cell-cell contact, by polarized budding into synaptic clefts, and by cell surface transfer of viral biofilms (VBs). Since little is known about Tax’s role in formation of the VB, we asked which component of the VB is regulated by Tax and important for HTLV-1 transmission. Collagens are not only structural proteins of the extracellular matrix and basal membrane but also represent an important component of the VB. Here, we report that among the collagens known to be present in VBs, COL4 is specifically upregulated in the presence of HTLV-1 infection. Further, we found that transient expression of Tax is sufficient to induce COL4A1 and COL4A2 transcripts in Jurkat and CCRF-CEM T-cells, while robust induction of COL4 protein requires continuous Tax expression as shown in Tax-transformed T-cell lines. Repression of Tax led to a significant reduction of COL4A1/A2 transcripts and COL4 protein. Mechanistically, luciferase-based promoter studies indicate that Tax activates the COL4A2 and, to a less extent, the COL4A1 promoter. Imaging showing partial co-localization of COL4 with the viral Gag protein in VBs at the VS and transfer of COL4 and Gag to target cells suggests a role of COL4 in VB formation. Strikingly, in chronically infected C91-PL cells, knockout of COL4A2 impaired Gag transfer between infected T-cells and acceptor T-cells, while release of virus-like particles was unaffected. Taken together, we identified COL4 (COL4A1, COL4A2) as a component of the VB and a novel cellular target of Tax with COL4A2 appearing to impact virus transmission. Thus, this study is the first to provide a link between Tax’s activity and VB formation by hijacking COL4 protein functions.
CRIS-Team Scopus Importer:2019-11-15
Keywords: COL4A1; COL4A2; Collagen 4; Collagen IV; HTLV-1; Tax-1; Viral biofilm; Virus transmission

Combination immunotherapy with anti-PD-L1 antibody and depletion of regulatory T cells during acute viral infections results in improved virus control but lethal immunopathology - David, Paul; Drabczyk-Pluta, Malgorzata; Pastille, Eva; Knuschke, Torben; Werner, Tanja; Honke, Nadine; Megger, Dominik A.; Akhmetzyanova, Ilseyar; Shaabani, Namir; Eyking-Singer, Annette; Cario, Elke; Kershaw, Olivia; et al. (PLoS Pathogens, 2020)
Combination immunotherapy (CIT) is currently applied as a treatment for different cancers and is proposed as a cure strategy for chronic viral infections. Whether such therapies are efficient during an acute infection remains elusive. To address this, inhibitory receptors were blocked and regulatory T cells depleted in acutely Friend retrovirus-infected mice. CIT resulted in a dramatic expansion of cytotoxic CD4+ and CD8+ T cells and a subsequent reduction in viral loads. Despite limited viral replication, mice developed fatal immunopathology after CIT. The pathology was most severe in the gastrointestinal tract and was mediated by granzyme B producing CD4+ and CD8+ T cells. A similar post-CIT pathology during acute Influenza virus infection of mice was observed, which could be prevented by vaccination. Melanoma patients who developed immune-related adverse events under immune checkpoint CIT also presented with expanded granzyme-expressing CD4+ and CD8+ T cell populations. Our data suggest that acute infections may induce immunopathology in patients treated with CIT, and that effective measures for infection prevention should be applied.
CRIS-Team Scopus Importer:2020-04-10

Combinatorial drug treatments reveal promising anticytomegaloviral profiles for clinically relevant pharmaceutical kinase inhibitors (PKIs) - Wild, Markus; Kicuntod, Jintawee; Seyler, Lisa; Wangen, Christina; Bertzbach, Luca D.; Conradie, Andelé M.; Kaufer, Benedikt B.; Wagner, Sabrina; Michel, Detlef; Eickhoff, Jan; Tsogoeva, Svetlana; Bäuerle, Tobias; et al. (International Journal of Molecular Sciences, 2021)
Human cytomegalovirus (HCMV) is a human pathogenic herpesvirus associated with a variety of clinical symptoms. Current antiviral therapy is not always effective, so that improved drug classes and drug-targeting strategies are needed. Particularly host-directed antivirals, including pharmaceutical kinase inhibitors (PKIs), may help to overcome problems of drug resistance. Here, we focused on utilizing a selection of clinically relevant PKIs and determined their anticytomegaloviral efficacies. Particularly, PKIs directed to host or viral cyclin-dependent kinases, i.e., abemaciclib, LDC4297 and maribavir, exerted promising profiles against human and murine cytomegaloviruses. The anti-HCMV in vitro activity of the approved anti-cancer drug abemaciclib was confirmed in vivo using our luciferase-based murine cytomegalovirus (MCMV) animal model in immunocompetent mice. To assess drug combinations, we applied the Bliss independence checkerboard and Loewe additivity fixed-dose assays in parallel. Results revealed that (i) both affirmative approaches provided valuable information on anti-CMV drug efficacies and interactions, (ii) the analyzed combinations comprised additive, synergistic or antagonistic drug interactions consistent with the drugs’ antiviral mode-of-action, (iii) the selected PKIs, especially LDC4297, showed promising inhibitory profiles, not only against HCMV but also other α-, β-and γ-herpesviruses, and specifically, (iv) the combination treatment with LDC4297 and maribavir revealed a strong synergism against HCMV, which might open doors towards novel clinical options in the near future. Taken together, this study highlights the potential of therapeutic drug combinations of current developmental/preclinical PKIs.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Activity in vitro and in vivo; Antiviral drugs; Combinatorial drug analyses; Human cytomegalovirus; New synergistic combinations; Pharmaceutical kinase inhibitors (PKIs)

Combined cytotoxic activity of an infectious, but non-replicative herpes simplex virus type 1 and plasmacytoid dendritic cells against tumour cells - Thomann, Sabrina; Boscheinen, Jan; Vogel, Karin; Knipe, David M.; Deluca, Neal; Gross, Stefanie; Schuler-Thurner, Beatrice; Schuster, Philipp; Schmidt, Barbara (Immunology, 2015)
Malignant melanoma is an aggressive tumour of the skin with increasing incidence, frequent metastasis and poor prognosis. At the same time, it is an immunogenic type of cancer with spontaneous regressions. Most recently, the tumoricidal effect of plasmacytoid dendritic cells (pDC) and their capacity to overcome the immunosuppressive tumour microenvironment are being investigated. In this respect, we studied the effect of the infectious, but replication-deficient, herpes simplex virus 1 (HSV-1) d106S vaccine strain, which lacks essential immediate early genes, in pDC co-cultures with 11 melanoma cell lines. We observed a strong cytotoxic activity, inducing apoptotic and necrotic cell death in most melanoma cell lines. The cytotoxic activity of HSV-1 d106S plus pDC was comparable to the levels of cytotoxicity induced by natural killer cells, but required only a fraction of cells with effector : target ratios of 1 : 20 (P < 0·05). The suppressive activity of cell-free supernatants derived from virus-stimulated pDC was significantly neutralized using antibodies against the interferon-? receptor (P < 0·05). In addition to type I interferons, TRAIL and granzyme B contributed to the inhibitory effect of HSV-1 d106S plus pDC to a minor extent. UV-irradiated viral stocks were significantly less active than infectious particles, both in the absence and presence of pDC (P < 0·05), indicating that residual activity of HSV-1 d106S is a major component and sensitizes the tumour cells to interferon-producing pDC. Three leukaemic cell lines were also susceptible to this treatment, suggesting a general anti-tumour effect. In conclusion, the potential of HSV-1 d106S for therapeutic vaccination should be further evaluated in patients suffering from different malignancies.
EVALuna2:8282

Combined Treatment with Host-Directed and Anticytomegaloviral Kinase Inhibitors: Mechanisms, Synergisms and Drug Resistance Barriers. - Wild, Markus; Karner, Dubravka; Eickhoff, Jan; Wagner, Sabrina; Kicuntod, Jintawee; Chang, William; Barry, Peter; Jonjić, Stipan; Lenac Roviš, Tihana; Marschall, Manfred (Pharmaceutics, 2023)
Despite the availability of currently approved antiviral drugs, infections with human cytomegalovirus (HCMV) still cause clinically challenging, sometimes life-threatening situations. There is an urgent need for enhanced anti-HCMV drugs that offer improved efficacy, reduced dosages and options for long-term treatment without risk of the development of viral drug resistance. Recently, we reported the pronounced anti-HCMV efficacy of pharmacological inhibitors of cyclin-dependent kinases (CDKs), in particular, the potential of utilizing drug synergies upon combination treatment with inhibitors of host CDKs and the viral CDK-like kinase pUL97 (vCDK/pUL97). Here, we expand this finding by further assessing the in vitro synergistic antiviral interaction between vCDK and CDK inhibitors towards HCMV as well as non-human cytomegaloviruses. An extension of this synergy approach was achieved in vivo by using the recombinant MCMV-UL97/mouse model, confirming the high potential of combination treatment with the clinically approved vCDK inhibitor maribavir (MBV) and the developmental CDK7 inhibitor LDC4297. Moreover, mechanistic aspects of this synergistic drug combination were illustrated on the levels of intracellular viral protein transport and viral genome replication. The analysis of viral drug resistance did not reveal resistance formation in the case of MBV + LDC4297 combination treatment. Spanning various investigational levels, these new results strongly support our concept, employing the great potential of anti-HCMV synergistic drug treatment.
EVALuna2:545511

'Come together'-The Regulatory Interaction of Herpesviral Nuclear Egress Proteins Comprises Both Essential and Accessory Functions - Häge, Sigrun; Marschall, Manfred (Cells, 2022)
Herpesviral nuclear egress is a fine-tuned regulatory process that defines the nucleocytoplasmic release of viral capsids. Nuclear capsids are unable to traverse via nuclear pores due to the fact of their large size; therefore, herpesviruses evolved to develop a vesicular transport pathway mediating the transition across the two leaflets of the nuclear membrane. The entire process involves a number of regulatory proteins, which support the local distortion of the nuclear envelope. In the case of the prototype species of beta-Herpesvirinae, the human cytomegalovirus (HCMV), the nuclear egress complex (NEC) is determined by the core proteins pUL50 and pUL53 that oligomerize, form capsid docking lattices and mediate multicomponent assembly with NEC-associated viral and cellular proteins. The NEC-binding principle is based on the hook-into-groove interaction through an N-terminal hook-like pUL53 protrusion that embraces an alpha-helical pUL50 binding groove. Thus far, the function and characteristics of herpesviral core NECs have been well studied and point to the groove proteins, such as pUL50, as the multi-interacting, major determinants of NEC formation and egress. This review provides closer insight into (i) sequence and structure conservation of herpesviral core NEC proteins, (ii) experimentation on cross-viral core NEC interactions, (iii) the essential functional roles of hook and groove proteins for viral replication, (iv) an establishment of assay systems for NEC-directed antiviral research and (v) the validation of NEC as putative antiviral drug targets. Finally, this article provides new insights into the conservation, function and antiviral targeting of herpesviral core NEC proteins and, into the complex regulatory role of hook and groove proteins during the assembly, egress and maturation of infectious virus.
CRIS-Team WoS Importer:2022-06-24
Keywords: herpesviruses; human cytomegalovirus; regulation of viral replication; nuclear egress complex (NEC); NEC hook and groove proteins; functional properties; conditional expression; specialized functional aspects; efficiency of virus production; antiviral drug target

Comparative Immunogenicity of COVID-19 Vaccines in a Population-Based Cohort Study with SARS-CoV-2-Infected and Uninfected Participants - Peterhoff, David; Einhauser, Sebastian; Beileke, Stephanie; Niller, Hans Helmut; Günther, Felix; Schachtner, Michael; Asbach, Benedikt; Steininger, Philipp; Tenbusch, Matthias; Peter, Antonia Sophia; Gessner, Andre; Burkhardt, Ralph; et al. (Vaccines, 2022)
To assess vaccine immunogenicity in non-infected and previously infected individuals in a real-world scenario, SARS-CoV-2 antibody responses were determined during follow-up 2 (April 2021) of the population-based Tirschenreuth COVID-19 cohort study comprising 3378 inhabitants of the Tirschenreuth county aged 14 years or older. Seronegative participants vaccinated once with Vaxzevria, Comirnaty, or Spikevax had median neutralizing antibody titers ranging from ID50 = 25 to 75. Individuals with two immunizations with Comirnaty or Spikevax had higher median ID50s (of 253 and 554, respectively). Regression analysis indicated that both increased age and increased time since vaccination independently decreased RBD binding and neutralizing antibody levels. Unvaccinated participants with detectable N-antibodies at baseline (June 2020) revealed a median ID50 of 72 at the April 2021 follow-up. Previously infected participants that received one dose of Vaxzevria or Comirnaty had median ID50 to 929 and 2502, respectively. Individuals with a second dose of Comirnaty given in a three-week interval after the first dose did not have higher median antibody levels than individuals with one dose. Prior infection also primed for high systemic IgA levels in response to one dose of Comirnaty that exceeded IgA levels observed after two doses of Comirnaty in previously uninfected participants. Neutralizing antibody levels targeting the spike protein of Beta and Delta variants were diminished compared to the wild type in vaccinated and infected participants.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Comirnaty; Immunogenicity; Neutralizing anti-bodies; Population-based cohort; SARS-CoV-2; Spikevax; Vaccination; Variants of concern VoC; Vaxzevria

Comparison of C-Reactive Protein in Dried Blood Spots and Saliva of Healthy Adolescents - Plank, Anne-Christine; Maschke, Janina; Rohleder, Nicolas; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Eichler, Anna; Moll, Gunther; Kratz, Oliver (Frontiers in Immunology, 2021)
Background/AimDetermining C-reactive protein (CRP) by non-invasive methods is of great interest for research addressing inflammation in young people. However, direct comparisons of such methods applied in children and adolescents are lacking so far. This study aimed to evaluate the association between CRP measured in dried blood spots (DBS CRP) and in saliva (sCRP), two less invasive alternatives to venipuncture, in 12- to 14-year-old adolescents. To evaluate the validity of both measurements in the context of biobehavioral studies, the potential of DBS CRP and sCRP to discriminate between defined BMI subgroups was assessed. Materials and MethodsCRP levels in DBS and saliva collected from 87 healthy adolescents (M = 13.25 years, SD = 0.30, 51.7% females) were determined using high sensitive CRP ELISA for serum and salivary CRP ELISA, respectively. Characteristics and correlation of both measurements were assessed for the total sample and for three subgroups classified by BMI percentile ranges (A: <= 25; B: 26-74; C: >= 75). ResultsIn the total sample, DBS CRP and sCRP were significantly associated (r = 0.59, p < 0.001). Splitting the sample into BMI-dependent subgroups revealed similarly strong associations of DBS CRP with sCRP for all three groups (A: r = 0.51; B: r = 0.61; C: r = 0.53). However, comparing the mean CRP values per BMI subgroup, one-way ANOVA reported significant differences for DBS CRP, but not for sCRP mean values. ConclusionsThe significant correlation of DBS CRP with sCRP was independent of the investigated BMI range groups, yet BMI-dependent distinction was only provided by DBS CRP mean values. Overall, our results suggest that DBS CRP is likely to reflect systemic inflammation more precisely. Salivary CRP can be alternatively determined in studies with adolescents when conditions require it, given the oral health status is assessed. Considering that DBS CRP and sCRP share only 35% of common variance, further studies should examine their specific validity.
CRIS-Team WoS Importer:2022-01-14

Compensatory neuritogenesis of serotonergic afferents within the striatum of a transgenic rat model of Parkinson's disease - Stemick, Judith; Gauer, Carina; Wihan, Jeanette; Moceri, Sandra; Xiang, Wei; von Hörsten, Stephan; Kohl, Zacharias; Winkler, Jürgen (Brain Research, 2020)
The majority of patients with Parkinson's disease (PD) suffer from L-DOPA-induced dyskinesia (LID). Besides a dysfunctional dopaminergic system, changes of the serotonergic network may be linked to this severe and adverse symptom. Particularly, serotonergic neurons have the potential to synthesize dopamine, likely associated with a disproportional dopamine release within the striatum. We hypothesized that the serotonergic system is adaptively altered in the striatum due to the reduced dopaminergic input. To answer this question, we analyzed a transgenic rat PD model ubiquitously expressing human α-synuclein using a bacterial artificial chromosome. Neurite analysis showed a profound loss of dopaminergic fibers by 30–40% within the dorsal striatum paralleled by a 50% reduction of dopaminergic neurons in the substantia nigra pars compacta. In contrast, serotonergic fibers showed an increased fiber density in the dorsal striatum by 100%, while the number of serotonergic neurons within the raphe nuclei (RN) and its proximal neuritic processes were unaffected. Furthermore, both the dopaminergic and serotonergic fiber density remained unchanged in the neighboring motor cortex M1/M2. Interestingly, essential enzymes required for L-DOPA turnover and dopamine release were expressed in serotonergic neurons of the RN. In parallel, the serotonergic autoreceptor levels involved in a serotonergic negative feedback loop were reduced within the striatum, suggesting a dysfunctional neurotransmitter release. Overall, the increased serotonergic fiber density with its capacity for dopamine release within the striatum suggests a compensatory, site-specific serotonergic neuritogenesis. This maladaptive serotonergic plasticity may be linked to adverse symptoms such as LIDs in PD.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Dopamine; L-DOPA-induced dyskinesia; Parkinson's disease; Serotonin; Striatum; α-synuclein

Complement Activation in Kidneys of Patients With COVID-19 - Pfister, Frederick; Vonbrunn, Eva; Ries, Tajana; Jäck, Hans-Martin; Überla, Klaus; Lochnit, Günter; Sheriff, Ahmed; Herrmann, Martin; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2021)
Most patients who became critically ill following infection with COVID-19 develop severe acute respiratory syndrome (SARS) attributed to a maladaptive or inadequate immune response. The complement system is an important component of the innate immune system that is involved in the opsonization of viruses but also in triggering further immune cell responses. Complement activation was seen in plasma adsorber material that clogged during the treatment of critically ill patients with COVID-19. Apart from the lung, the kidney is the second most common organ affected by COVID-19. Using immunohistochemistry for complement factors C1q, MASP-2, C3c, C3d, C4d, and C5b-9 we investigated the involvement of the complement system in six kidney biopsies with acute kidney failure in different clinical settings and three kidneys from autopsy material of patients with COVID-19. Renal tissue was analyzed for signs of renal injury by detection of thrombus formation using CD61, endothelial cell rarefaction using the marker E-26 transformation specific-related gene (ERG-) and proliferation using proliferating cell nuclear antigen (PCNA)-staining. SARS-CoV-2 was detected by in situ hybridization and immunohistochemistry. Biopsies from patients with hemolytic uremic syndrome (HUS, n = 5), severe acute tubular injury (ATI, n = 7), zero biopsies with disseminated intravascular coagulation (DIC, n = 7) and 1 year protocol biopsies from renal transplants (Ctrl, n = 7) served as controls. In the material clogging plasma adsorbers used for extracorporeal therapy of patients with COVID-19 C3 was the dominant protein but collectin 11 and MASP-2 were also identified. SARS-CoV-2 was sporadically present in varying numbers in some biopsies from patients with COVID-19. The highest frequency of CD61-positive platelets was found in peritubular capillaries and arteries of COVID-19 infected renal specimens as compared to all controls. Apart from COVID-19 specimens, MASP-2 was detected in glomeruli with DIC and ATI. In contrast, the classical pathway (i.e. C1q) was hardly seen in COVID-19 biopsies. Both C3 cleavage products C3c and C3d were strongly detected in renal arteries but also occurs in glomerular capillaries of COVID-19 biopsies, while tubular C3d was stronger than C3c in biopsies from COVID-19 patients. The membrane attack complex C5b-9, demonstrating terminal pathway activation, was predominantly deposited in COVID-19 biopsies in peritubular capillaries, renal arterioles, and tubular basement membrane with similar or even higher frequency compared to controls. In conclusion, various complement pathways were activated in COVID-19 kidneys, the lectin pathway mainly in peritubular capillaries and in part the classical pathway in renal arteries whereas the alternative pathway seem to be crucial for tubular complement activation. Therefore, activation of the complement system might be involved in the worsening of renal injury. Complement inhibition might thus be a promising treatment option to prevent deregulated activation and subsequent collateral tissue injury.
CRIS-Team Scopus Importer:2021-03-05
Keywords: complement—immunological term; COVID-19; endothelial injury; kidney; lectin pathway activation

Comprehensive phenotyping revealed transient startle response reduction and histopathological gadolinium localization to perineuronal nets after gadodiamide administration in rats - Habermeyer, Johanna; Boyken, Janina; Harrer, Julia; Canneva, Fabio; Ratz, Veronika; Moceri, Sandra; Admard, Jakob; Casadei, Nicolas; Jost, Gregor; Bäuerle, Tobias; Frenzel, Thomas; Schmitz, Christoph; et al. (Scientific Reports, 2020)
Gadolinium based contrast agents (GBCAs) are widely used in clinical MRI since the mid-1980s. Recently, concerns have been raised that trace amounts of Gadolinium (Gd), detected in brains even long time after GBCA application, may cause yet unrecognized clinical consequences. We therefore assessed the behavioral phenotype, neuro-histopathology, and Gd localization after repeated administration of linear (gadodiamide) or macrocyclic (gadobutrol) GBCA in rats. While most behavioral tests revealed no difference between treatment groups, we observed a transient and reversible decrease of the startle reflex after gadodiamide application. Residual Gd in the lateral cerebellar nucleus was neither associated with a general gene expression pathway deregulation nor with neuronal cell loss, but in gadodiamide-treated rats Gd was associated with the perineuronal net protein aggrecan and segregated to high molecular weight fractions. Our behavioral finding together with Gd distribution and speciation support a substance class difference for Gd presence in the brain after GBCA application.
CRIS-Team WoS Importer:2021-01-22

Concordance Rate of Colposcopy in Detecting Cervical Intraepithelial Lesions - Stübs, Frederik; Dietl, Anna; Behrens, Annika; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Schulmeyer, Carla; Gaß, Paul; Koch, Martin C. (Diagnostics, 2022)
Background: The purpose of this research is to estimate the rate of concordance, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of colposcopy for high-grade squamous lesions and carcinomas (HSIL+). Methods: We conducted a retrospective study of colposcopies performed in the certified Dysplasia Unit in Erlangen between January 2015 and May 2022 (7.5 years). The colposcopic findings were correlated with biopsies obtained during examinations or surgery. Cases without histology were excluded. The primary outcome was the rate of concordance between the colposcopic and histological findings in relation to the type of transformation zone (TZ), examiner's level of experience and age of the patients. Results: A total of 4778 colposcopies in 4001 women were analyzed. The rates of concordance for CIN I/LSIL, CIN II/HSIL, CIN III/HSIL, and carcinoma were 43.4%, 59.5%, 78.5%, and 53.9%, respectively. The rate of concordance was lowest for TZ3 and highest for colposcopists with more than 10 years' experience. Conclusions: Colposcopy is an important, feasible, and effective method. Careful work-up needs to be performed for women with TZ3 who are over 35 years old, as they are at the highest risk of being misdiagnosed. The highest concordance for detecting HSIL+ was seen for colposcopists with >10 years' experience.
CRIS-Team WoS Importer:2022-11-11

Conjugation of native‐like hiv‐1 envelope trimers onto liposomes using edc/sulfo‐nhs chemistry: Requirements and limitations - Suleiman, Ehsan; Mayer, Julia; Lehner, Elisabeth; Kohlhauser, Bianca; Katholnig, Alexandra; Batzoni, Mirjam; Damm, Dominik; Temchura, Vladimir; Wagner, Andreas; Überla, Klaus; Vorauer‐uhl, Karola (Pharmaceutics, 2020)
The display of native‐like human immunodeficiency virus type 1 envelope (HIV‐1 Env) trimers on liposomes has gained wide attention over the last few years. Currently, available methods have enabled the preparation of Env‐liposome conjugates of unprecedented quality. However, these protocols require the Env trimer to be tagged and/or to carry a specific functional group. For this reason, we have investigated N‐(3‐Dimethylaminopropyl)‐N′‐ethylcarbodiimide/N‐ Hydroxysulfosuccinimide (EDC/Sulfo‐NHS) chemistry for its potential to covalently conjugate tag-free, non‐functionalized native‐like Env trimers onto the surface of carboxyl‐functionalized liposomes. The preservation of the liposome’s physical integrity and the immunogen’s conformation required a fine‐tuned two‐step approach based on the controlled use of β‐ mercaptoethanol. The display of Env trimers was strictly limited to activated liposomes of positive charge, i.e., liposomes with a positive zeta potential that carry amine‐reactive Sulfo‐NHS esters on their surface. In agreement with that, conjugation was found to be highly ionic strength‐ and pH-dependent. Overall, we have identified electrostatic pre‐concentration (i.e., close proximity between negatively charged Env trimers and positively charged liposomes established through electrostatic attraction) to be crucial for conjugation reactions to proceed. The present study highlights the requirements and limitations of potentially scalable EDC/Sulfo‐NHS‐based approaches and represents a solid basis for further research into the controlled conjugation of tag‐free, non-functionalized native‐like Env trimers on the surface of liposomes, and other nanoparticles.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Covalent conjugation; EDC/Sulfo‐NHS; HIV‐1; Intrastructural help; Liposomes; Native-like Env trimers; Particulate display; Pre‐concentration; Protein‐liposome conjugates; Tag‐free conjugation; Vaccines

Consecutive Inhibition of ISG15 Expression and ISGylation by Cytomegalovirus Regulators - Kim, Ye Ji; Kim, Eui Tae; Kim, Young-Eui; Lee, Myoung Kyu; Kwon, Ki Mun; Kim, Keun Il; Stamminger, Thomas; Ahn, Jin-Hyun (PLoS Pathogens, 2016)
Interferon-stimulated gene 15 (ISG15) encodes an ubiquitin-like protein that covalently conjugates protein. Protein modification by ISG15 (ISGylation) is known to inhibit the replication of many viruses. However, studies on the viral targets and viral strategies to regulate ISGylation-mediated antiviral responses are limited. In this study, we show that human cytomegalovirus (HCMV) replication is inhibited by ISGylation, but the virus has evolved multiple countermeasures. HCMV-induced ISG15 expression was mitigated by IE1, a viral inhibitor of interferon signaling, however, ISGylation was still strongly upregulated during virus infection. RNA interference of UBE1L (E1), UbcH8 (E2), Herc5 (E3), and UBP43 (ISG15 protease) revealed that ISGylation inhibits HCMV growth by downregulating viral gene expression and virion release in a manner that is more prominent at low multiplicity of infection. A viral regulator pUL26 was found to interact with ISG15, UBE1L, and Herc5, and be ISGylated. ISGylation of pUL26 regulated its stability and inhibited its activities to suppress NF-?B signaling and complement the growth of UL26-null mutant virus. Moreover, pUL26 reciprocally suppressed virus-induced ISGylation independent of its own ISGylation. Consistently, ISGylation was more pronounced in infections with the UL26-deleted mutant virus, whose growth was more sensitive to IFN? treatment than that of the wild-type virus. Therefore, pUL26 is a viral ISG15 target that also counteracts ISGylation. Our results demonstrate that ISGylation inhibits HCMV growth at multiple steps and that HCMV has evolved countermeasures to suppress ISG15 transcription and protein ISGylation, highlighting the importance of the interplay between virus and ISGylation in productive viral infection.
EVALuna2:8327

Continuous monitoring of SARS-CoV-2 seroprevalence in children using residual blood samples from routine clinical chemistry - Wachter, Felix; Regensburger, Adrian; Peter, Antonia Sophia; Knieling, Ferdinand; Wagner, Alexandra; Simon, David; Hörning, André; Wölfle, Joachim; Überla, Klaus; Neubert, Antje; Rauh, Manfred (Clinical Chemistry and Laboratory Medicine, 2022)
Objectives The assessment of SARS-CoV-2 infections in children is still challenging, but essential for appropriate political decisions. The aim of this study was to investigate whether residual blood samples can be used for SARS-CoV-2 seroprevalence monitoring in pediatrics. Methods In this repeated cross-sectional cohort study, anonymous residual blood samples from pediatric patients aged 0-17 years were collected in three time-periods (Oct.-Nov. 2020, April 2021, and June-July 2021) and analyzed for SARS-CoV-2 Spike protein (anti-S) and nucleocapsid (anti-N) antibodies using commercial antibody assays. 28 reactive samples were used to compare antibody levels with a pseudotyped neutralization assay. The results were further compared to the official national COVID-19 surveillance data to calculate the number of unreported cases. Results In total, n=2,626 individual blood samples were analyzed. In this unvaccinated pediatric cohort anti-S and anti-N antibody seroprevalence increased over the three time periods (anti-S: 1.38-9.16%, and 14.59%; anti-N: 1.26%, to 6.19%, and 8.56%). Compared to the national surveillance data this leads to a 3.93-5.66-fold increase in the number of unreported cases. However, a correlation between the cumulative incidence of the individual provinces and our assigned data was found (r=0.74, p=0.0151). In addition, reactive samples with anti-S and anti-N and samples with only anti-S showed neutralization capabilities (11/14 and 8/14, respectively). Anti-S levels were not significantly different between age groups and sexes (all p>0.05). Conclusions The present study suggests that residual blood samples from routine laboratory chemistry could be included in the estimation of the total SARS-CoV-2 seroprevalence in children.
CRIS-Team WoS Importer:2022-03-11
Keywords: COVID-19; pediatrics; prevalence; SARS-CoV-2

Contribution of the Major ND10 Proteins PML, hDaxx and Sp100 to the Regulation of Human Cytomegalovirus Latency and Lytic Replication in the Monocytic Cell Line THP-1 - Wagenknecht, Nadine; Reuter, Nina; Scherer, Myriam; Reichel, Anna; Müller, Regina; Stamminger, Thomas (Viruses, 2015)
Promyelocytic leukemia nuclear bodies, also termed nuclear domain 10 (ND10), have emerged as nuclear protein accumulations mediating an intrinsic cellular defense against viral infections via chromatin-based mechanisms, however, their contribution to the control of herpesviral latency is still controversial. In this study, we utilized the monocytic cell line THP-1 as an in vitro latency model for human cytomegalovirus infection (HCMV). Characterization of THP-1 cells by immunofluorescence andWestern blot analysis confirmed the expression of all major ND10 components. THP-1 cells with a stable, individual knockdown of PML, hDaxx or Sp100 were generated. Importantly, depletion of the major ND10 proteins did not prevent the terminal cellular differentiation of THP-1 monocytes. After construction of a recombinant, endotheliotropic human cytomegalovirus expressing IE2-EYFP, we investigated whether the depletion of ND10 proteins affects the onset of viral IE gene expression. While after infection of differentiated, THP-1-derived macrophages as well as during differentiation-induced reactivation from latency an increase in the number of IE-expressing cells was readily detectable in the absence of the major ND10 proteins, no effect was observed in non-differentiated monocytes. We conclude that PML, hDaxx and Sp100 primarily act as cellular restriction factors during lytic HCMV replication and during the dynamic process of reactivation but do not serve as key determinants for the establishment of HCMV latency.
EVALuna2:8283

Controlled crystal dehydration triggers a space-group switch and shapes the tertiary structure of cytomegalovirus immediate-early 1 (IE1) protein - Klingl, Stefan; Scherer, Myriam; Stamminger, Thomas; Muller, Yves (Acta Crystallographica Section D: Biological Crystallography, 2015)
Cytomegalovirus immediate-early 1 (IE1) protein is a key viral effector protein that reprograms host cells. Controlled dehydration experiments with IE1 crystals not only extended their diffraction limit from 2.85 to 2.3Å resolution but also triggered a monoclinic to tetragonal space-group transition with only minor alterations in the unit-cell parameters. An analysis of the pre-dehydration and post-dehydration crystal structures shows how dehydration rearranges the packing of IE1 molecules to meet the unit-cell constraints of the higher lattice symmetry. The transition from P21 to P43 reduces the number of copies in the asymmetric unit from four to two, and molecules previously related by noncrystallographic symmetry merge into identical crystallographic copies in the tetragonal space group. At the same time, dehydration considerably alters the tertiary structure of one of the two remaining IE1 chains in the asymmetric unit. It appears that this conformational switch is required to compensate for a transition that is assumed to be unfavourable, namely from a highly preferred to a rarely observed space group. At the same time, the dehydration-triggered molecular reshaping could reveal an inherent molecular flexibility that possibly informs on the biological function of IE1, namely on its binding to target proteins from the host cell.
Keywords: free-mounting system; humidity-control device; improved scattering and diffraction; lattice symmetry increase; space-group transition; viral effector protein

Control of Murine Cytomegalovirus Infection by γδ T Cells - Sell, Sabrina; Dietz, Monika; Schneider, Andrea; Holtappels, Rafaela; Mach, Michael; Winkler, Thomas (PLoS Pathogens, 2015)
Infections with cytomegalovirus (CMV) can cause severe disease in immunosuppressed patients and infected newborns. Innate as well as cellular and humoral adaptive immune effector functions contribute to the control of CMV in immunocompetent individuals. None of the innate or adaptive immune functions are essential for virus control, however. Expansion of γδ T cells has been observed during human CMV (HCMV) infection in the fetus and in transplant patients with HCMV reactivation but the protective function of γδ T cells under these conditions remains unclear. Here we show for murine CMV (MCMV) infections that mice that lack CD8 and CD4 αβ-T cells as well as B lymphocytes can control a MCMV infection that is lethal in RAG-1 mice lacking any T- and B-cells. γδ T cells, isolated from infected mice can kill MCMV infected target cells in vitro and, importantly, provide long-term protection in infected RAG-1 mice after adoptive transfer. γδ T cells in MCMV infected hosts undergo a prominent and long-lasting phenotypic change most compatible with the view that the majority of the γδ T cell population persists in an effector/memory state even after resolution of the acute phase of the infection. A clonotypically focused Vγ1 and Vγ2 repertoire was observed at later stages of the infection in the organs where MCMV persists. These findings add γδ T cells as yet another protective component to the anti-CMV immune response. Our data provide clear evidence that γδ T cells can provide an effective control mechanism of acute CMV infections, particularly when conventional adaptive immune mechanisms are insufficient or absent, like in transplant patient or in the developing immune system in utero. The findings have implications in the stem cell transplant setting, as antigen recognition by γδ T cells is not MHC-restricted and dual reactivity against CMV and tumors has been described.

Correction to: Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections (European Journal of Clinical Microbiology & Infectious Diseases, (2021), 10.1007/s10096-021-04285-4) - Huber, Timo; Steininger, Philipp; Irrgang, Pascal; Korn, Klaus; Tenbusch, Matthias; Diesch, Katharina; Achenbach, Susanne; Kremer, Andreas; Werblow, Marissa; Vetter, Marcel; Bogdan, Christian; Held, Jürgen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
In the originally published version of the article, captions of Figures 1, 2, 3, 4, and 5 have missing figure denominations. The figures are presented here with correct captions. Layout adjustments are also made to Tables 2-5 for readability. The original article has been corrected. (Figure presented.).
CRIS-Team Scopus Importer:2021-07-30

Correlation of Hif1a expression of primary oral squamous cell carcinomas with histomorphologic parameters and macrophage polarization - Wehrhan, Falk; Möbius, Patrick; Amann, Kerstin Ute; Geppert, Carol-Immanuel; Preidl, Raimund; Ries, Jutta; Neukam, Friedrich Wilhelm; Weber, Manuel (2018)
EVALuna2:34066

Covalent coupling of HIV-1 glycoprotein trimers to biodegradable calcium phosphate nanoparticles via genetically encoded aldehyde-tags - Damm, Dominik; Kostka, K.; Weingärtner, Christoph; Wagner, Jannik; Rojas-Sánchez, L.; Gensberger-Reigl, Sabrina; Sokolova, V.; Überla, Klaus; Epple, M.; Temchura, Vladimir (Acta Biomaterialia, 2022)
The usage of antigen-functionalized nanoparticles has become a major focus in the field of experimental HIV-1 vaccine research during the last decade. Various molecular mechanisms to couple native-like trimers of the HIV-1 envelope protein (Env) onto nanoparticle surfaces have been reported, but many come with disadvantages regarding the coupling efficiency and stability. In this study, a short amino acid sequence (“aldehyde-tag”) was introduced at the C-terminus of a conformationally stabilized native-like Env. The post-translational conversion of a tag-associated cysteine to formylglycine creates a site-specific aldehyde group without alteration of the Env antigenicity. This aldehyde group was further utilized for bioconjugation of Env trimers. We demonstrated that the low acidic environment necessary for this bioconjugation is not affecting the trimer conformation. Furthermore, we developed a two-step coupling method for pH-sensitive nanoparticles. To this end, we conjugated aldehyde-tagged Env with Propargyl-PEG3-aminooxy linker (oxime ligation; Step-one) and coupled these conjugates by copper-catalyzed azide-alkyne cycloaddition (Click reaction; Step-two) to calcium phosphate nanoparticles (CaPs) functionalized with terminal azide groups. CaPs displaying orthogonally arranged Env trimers on their surface (o-CaPs) were superior in activation of Env-specific B-cells (in vitro) and induction of Env-specific antibody responses (in vivo) compared to CaPs with Env trimers coupled in a randomly oriented manner. Taken together, we present a reliable method for the site-specific, covalent coupling of HIV-1 Env native-like trimers to the surface of nanoparticle delivery systems. This method can be broadly applied for functionalization of nanoparticle platforms with conformationally stabilized candidate antigens for both vaccination and diagnostic approaches. Statement of significance: During the last decade antigen-functionalized nanoparticles have become a major focus in the field of experimental HIV-1 vaccines. Rational design led to the production of conformationally stabilized HIV-1 envelope protein (Env) trimers - the only target for the humoral immune system. Various molecular mechanisms to couple Env trimers onto nanoparticle surfaces have been reported, but many come with disadvantages regarding the coupling efficiency and stability. In this paper, we describe a highly selective bio-conjugation of Env trimers to the surface of medically relevant calcium phosphate nanoparticles. This method maintains the native-like protein conformation and has a broad potential application in functionalization of nanoparticle platforms with stabilized candidate antigens (including stabilized spike proteins of coronaviruses) for both vaccination and diagnostic approaches.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Aldehyde-tag; Calcium phosphate nanoparticles; HIV-1 Env native-like trimers; Orthogonal; Site-specific coupling; Surface conjugation

COVID-19 effects on the kidney. - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV‑2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV‑2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
EVALuna2:421391

COVID-19 effects on the kidney - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV-2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV-2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
CRIS-Team WoS Importer:2021-02-19

Crnkl1 is a highly selective regulator of intron-retaining HIV-1 and cellular mrnas - Xiao, Han; Wyler, Emanuel; Milek, Miha; Grewe, Bastian; Kirchner, Philipp; Ekici, Arif Bülent; Silva, Ana Beatriz Oliveira Villela; Jungnickl, Doris; Full, Florian; Thomas, Marco; Landthaler, Markus; Enßer, Armin; et al. (mBio, 2021)
The HIV-1 Rev protein is a nuclear export factor for unspliced and incom-pletely spliced HIV-1 RNAs. Without Rev, these intron-retaining RNAs are trapped in the nucleus. A genome-wide screen identified nine proteins of the spliceosome, which all enhanced expression from the HIV-1 unspliced RNA after CRISPR/Cas knockdown. Depletion of DHX38, WDR70, and four proteins of the Prp19-associated complex (ISY1, BUD31, XAB2, and CRNKL1) resulted in a more than 20-fold enhancement of unspliced HIV-1 RNA levels in the cytoplasm. Targeting of CRNKL1, DHX38, and BUD31 affected nuclear export efficiencies of the HIV-1 unspliced RNA to a much larger extent than splicing. Transcriptomic analyses further revealed that CRNKL1 also suppresses cyto-plasmic levels of a subset of cellular mRNAs, including some with selectively retained introns. Thus, CRNKL1-dependent nuclear retention is a novel cellular mechanism for the regulation of cytoplasmic levels of intron-retaining HIV-1 mRNAs, which HIV-1 may have harnessed to direct its complex splicing pattern. IMPORTANCE To regulate its complex splicing pattern, HIV-1 uses the adaptor protein Rev to shuttle unspliced or partially spliced mRNA from the nucleus to the cyto-plasm. In the absence of Rev, these RNAs are retained in the nucleus, but it is unclear why. Here we identify cellular proteins whose depletion enhances cytoplas-mic levels of the HIV-1 unspliced RNA. Depletion of one of them, CRNKL1, also increases cytoplasmic levels of a subset of intron-retaining cellular mRNA, suggesting that CRNKL1-dependent nuclear retention may be a basic cellular mechanism exploited by HIV-1.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Association; CRNKL1; Human immunodeficiency virus; Intron-retaining RNA; Nuclear retention; RNA splicing

Crystal structure of cytomegalovirus IE1 protein reveals targeting of TRIM family member PML via coiled-coil interactions - Scherer, Myriam; Klingl, Stefan; Sevvana, Madhumati; Otto, Victoria; Schilling, Eva-Maria; Stump, Joachim; Müller, Regina; Reuter, Nina; Sticht, Heinrich; Muller, Yves; Stamminger, Thomas (PLoS Pathogens, 2014)
PML nuclear bodies (PML-NBs) are enigmatic structures of the cell nucleus that act as key mediators of intrinsic immunity against viral pathogens. PML itself is a member of the E3-ligase TRIM family of proteins that regulates a variety of innate immune signaling pathways. Consequently, viruses have evolved effector proteins to modify PML-NBs; however, little is known concerning structure-function relationships of viral antagonists. The herpesvirus human cytomegalovirus (HCMV) expresses the abundant immediate-early protein IE1 that colocalizes with PML-NBs and induces their dispersal, which correlates with the antagonization of NB-mediated intrinsic immunity. Here, we delineate the molecular basis for this antagonization by presenting the first crystal structure for the evolutionary conserved primate cytomegalovirus IE1 proteins. We show that IE1 consists of a globular core (IE1CORE) flanked by intrinsically disordered regions. The 2.3 Å crystal structure of IE1CORE displays an all ?-helical, femur-shaped fold, which lacks overall fold similarity with known protein structures, but shares secondary structure features recently observed in the coiled-coil domain of TRIM proteins. Yeast two-hybrid and coimmunoprecipitation experiments demonstrate that IE1CORE binds efficiently to the TRIM family member PML, and is able to induce PML deSUMOylation. Intriguingly, this results in the release of NB-associated proteins into the nucleoplasm, but not of PML itself. Importantly, we show that PML deSUMOylation by IE1CORE is sufficient to antagonize PML-NB-instituted intrinsic immunity. Moreover, co-immunoprecipitation experiments demonstrate that IE1CORE binds via the coiled-coil domain to PML and also interacts with TRIM5? We propose that IE1CORE sequesters PML and possibly other TRIM family members via structural mimicry using an extended binding surface formed by the coiled-coil region. This mode of interaction might render the antagonizing activity less susceptible to mutational escape.
EVALuna2:8238

Crystal structure of the human cytomegalovirus pUL50-pUL53 core nuclear egress complex provides insight into a unique assembly scaffold for virus-host protein interactions - Walzer, Sascha; Egerer-Sieber, Claudia; Sticht, Heinrich; Sevvana, Madhumati; Hohl, Katharina; Milbradt, Jens; Muller, Yves; Marschall, Manfred (Journal of Biological Chemistry, 2015)
Nuclear replication of cytomegalovirus relies on elaborate mechanisms of nucleocytoplasmic egress of viral particles. Thus, the role of two essential and conserved viral nuclear egress proteins, pUL50 and pUL53, is pivotal. pUL50 and pUL53 heterodimerize and form a core nuclear egress complex (NEC), which is anchored to the inner nuclear membrane and provides a scaffold for the assembly of a multimeric viral-cellular NEC. Here, we report the crystal structure of the pUL50-pUL53 heterodimer (amino acids 1-175 and 50-292, respectively) at 2.44 Å resolution. Both proteins adopt a globular fold with mixed α and β secondary structure elements. pUL53-specific features include a zinc-binding site and a hook-like N-terminal extension, the latter representing a hallmark element of the pUL50-pUL53 interaction. The hook-like extension (amino acids 59-87) embraces pUL50 and contributes 1510 Å to the total interface area (1880Å). The pUL50 structure overall resembles the recently published NMR structure of the murine cytomegalovirus homolog pM50 but reveals a considerable repositioning of the very C-terminal α-helix of pUL50 upon pUL53 binding. pUL53 shows structural resemblance with the GHKL domain of bacterial sensory histidine kinases. A close examination of the crystal structure indicates partial assembly of pUL50-pUL53 heterodimers to hexameric ring-like structures possibly providing additional scaffolding opportunities for NEC. In combination, the structural information on pUL50-pUL53 considerably improves our understanding of the mechanism of HCMV nuclear egress. It may also accelerate the validation of the NEC as a unique target for developing a novel type of antiviral drug and improved options of broad-spectrum antiherpesviral therapy.

Cut to the chase: a review of CD26/dipeptidyl peptidase-4's (DPP4) entanglement in the immune system - Klemann, Christian; Wagner, L.; Stephan, M.; von Hörsten, Stephan (Clinical and Experimental Immunology, 2016)
CD26/DPP4 (dipeptidyl peptidase 4/DP4/DPPIV) is a surface T cell activation antigen and has been shown to have DPP4 enzymatic activity, cleaving-off amino-terminal dipeptides with either L-proline or L-alanine at the penultimate position. It plays a major role in glucose metabolism by N-terminal truncation and inactivation of the incretins glucagon-like peptide-1 (GLP) and gastric inhibitory protein (GIP). In 2006, DPP4 inhibitors have been introduced to clinics and have been demonstrated to efficiently enhance the endogenous insulin secretion via prolongation of the half-life of GLP-1 and GIP in patients. However, a large number of studies demonstrate clearly that CD26/DPP4 also plays an integral role in the immune system, particularly in T cell activation. Therefore, inhibition of DPP4 might represent a double-edged sword. Apart from the metabolic benefit, the associated immunological effects of long term DPP4 inhibition on regulatory processes such as T cell homeostasis, maturation and activation are not understood fully at this stage. The current data point to an important role for CD26/DPP4 in maintaining lymphocyte composition and function, T cell activation and co-stimulation, memory T cell generation and thymic emigration patterns during immune-senescence. In rodents, critical immune changes occur at baseline levels as well as after in-vitro and in-vivo challenge. In patients receiving DPP4 inhibitors, evidence of immunological side effects also became apparent. The scope of this review is to recapitulate the role of CD26/DPP4 in the immune system regarding its pharmacological inhibition and T cell-dependent immune regulation.
EVALuna2:24976

Cyclin‐Dependent Kinases (CDKs) and the Human Cytomegalovirus‐Encoded CDK Ortholog pUL97 Represent Highly Attractive Targets for Synergistic Drug Combinations - Wild, Markus; Hahn, Friedrich; Brückner, Nadine; Schütz, Martin; Wangen, Christina; Wagner, Sabrina; Sommerer, Markus; Strobl, Stefan; Marschall, Manfred (International Journal of Molecular Sciences, 2022)
Human cytomegalovirus (HCMV) is a pathogenic human herpesvirus associated with serious, potentially life‐threatening symptoms in the immunocompromised or immunonaïve host. The limitations encountered by antiviral therapy options currently available include a narrow panel of accessible targets, the induction of viral drug resistance as well as severe drug dosage‐mediated side‐effects. Improved drug‐targeting strategies to resolve these issues are the focus of our investigations. In particular, pharmaceutical kinase inhibitors (PKIs), either directed to host kinases or directed to the viral protein kinase pUL97, have been considered to overcome these restrictions. Recently, we reported the identification of a synergistic combination of two PKIs directed to host cyclin‐dependent kinase 7 (CDK7) and viral CDK ortholog pUL97. Here, we substantiate these findings with the following results: (i) true drug synergy was exhibited by various chemical classes of PKI pairs directed to pUL97 and CDK7; (ii) no putative amplification of cytotoxicity by these drug combinations was observed; (iii) a reduction in drug dosage levels for synergistic combinations was defined on a quantitative basis and compared to monotreatments; (iv) the quantities of target proteins CDK7 and pUL97 expressed in HCMV‐infected cells were assessed by confocal imaging, indicating a strong down‐modulation of CDK7 levels as a result of synergistic drug treatment; (v) the functional importance of these target kinases, both binding to cyclin H, was illustrated by assessing HCMV replication under the viral genomic deletion of ORF‐UL97 or cellular cyclin knock‐out; (vi) new combinations of HCMV‐specific drug synergy were demonstrated for solely host‐directed treatments using PKIs against CDK2, CDK7, CDK8 and/or CDK9 and (vii) a triple PKI combination provided further support for the synergy approach. With these combined findings, this study highlights the potential of therapeutic drug combinations of approved, developmental and preclinical PKIs for expanding future options for anti‐HCMV therapy.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Antiviral drug; Antiviral drug synergism; Cyclin‐dependent kinase (CDK); Direct‐acting antiviral (DAA); Drug combinations; Host‐directed antiviral (HDA); Human cytomegalovirus; New synergistic drug‐target combinations; Pharmaceutical kinase inhibitor (PKI); Viral CDK pUL97 (vCDK)

Cyclins B1, T1, and H differ in their molecular mode of interaction with cytomegalovirus protein kinase pUL97 - Steingruber, Mirjam; Keller, Lena; Socher, Eileen; Ferre, Sabrina; Hesse, Anne-Marie; Coute, Yohann; Hahn, Friedrich; Buescher, Nicole; Plachter, Bodo; Sticht, Heinrich; Marschall, Manfred (Journal of Biological Chemistry, 2019)
Human cytomegalovirus (HCMV) is a common -herpesvirus causing life-long latent infections. HCMV replication interferes with cell cycle regulation in host cells because the HCMV-encoded cyclin-dependent kinase (CDK) ortholog pUL97 extensively phosphorylates the checkpoint regulator retinoblastoma protein. pUL97 also interacts with cyclins B1, T1, and H, and recent findings have strongly suggested that these interactions influence pUL97 substrate recognition. Interestingly, here we detected profound mechanistic differences among these pUL97– cyclin interactions. Our study revealed the following. (i) pUL97 interacts with cyclins B1 and H in a manner dependent on pUL97 activity and HCMV-specific cyclin modulation, respectively. (ii) The phosphorylated state of both proteins is an important determinant of the pUL97–cyclin B1 interaction. (iii) Activated phospho-Thr-315 cyclin H is up-regulated during HCMV replication. (iv) Thr-315 phosphorylation is independent of intracellular pUL97 or CDK7 activity. (v) pUL97-mediated in vitro phosphorylation is detectable for cyclin B1 but not H. (vi) Mutual transphosphorylation between pUL97 and CDK7 is not detectable, and an MS-based phosphosite analysis indicated that pUL97 might unexpectedly not be phosphorylated in its T-loop. (vii) The binary complexes pUL97– cyclin H and CDK7– cyclin H as well as the ternary complex pUL97– cyclin-H–CDK7 are detectable in an assembly-based CoIP approach. (viii) pUL97 self-interaction can be bridged by the transcriptional cyclins T1 or H but not by the classical cell cycle–regulating B1 cyclin. Combined, our findings unravel a number of cyclin type–specific differences in pUL97 interactions and suggest a multifaceted regulatory impact of cyclins on HCMV replication.
CRIS-Team Scopus Importer:2019-05-03

Cytokine production of leukocytes in response to respiratory syncytial-virus is increased in severe asthma - Jameel, Jamal K.; Yanik, S.; Weidinger, D.; Rohde, S.; Buelthoff, E.; Yusuf, F.; Kronsbein, J.; Tenbusch, Matthias; Knobloch, J. (PNEUMOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-10

Cytology and High-Risk Human Papillomavirus Test for Cervical Cancer Screening Assessment - Stübs, Frederik; Koch, Martin C.; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Schulmeyer, Carla; Gaß, Paul (Diagnostics, 2022)
Background: A new nationwide screening strategy was implemented in Germany in January 2020. No data are available for women referred to certified dysplasia units for secondary clarification after primary diagnosis by a local physician. We therefore investigated combined testing with Papanicolaou smears and high-risk human papillomavirus (hrHPV) and compared the data with the final histological findings. Methods: Between January 2015 and October 2020, all referred women who underwent colposcopy of the uterine cervix in our certified dysplasia unit were included. Cytology findings were classified using the Munich III nomenclature. Results: A total of 3588 colposcopies were performed in 3118 women, along with Pap smear and hrHPV co-testing, followed by histology. Women with Pap II-p (ASC-US) and a positive hrHPV co-test had a 22.4% risk for cervical intraepithelial neoplasia (CIN) 3/high-grade squamous intraepithelial lesion (HSIL). The risk of CIN 3/HSIL was 83.8% in women with Pap IVa-p (HSIL) and a positive hrHPV co-test. A positive hrHPV co-test increased the risk for HSIL+ (OR 5.942; 95% CI, 4.617 to 7.649; p < 0.001) as compared to a negative hrHPV co-test. Conclusions: The accuracy of Pap smears is comparable with the screening results. A positive hrHPV test increases the risk for HSIL+ fivefold. Colposcopy is necessary to diagnose HSIL+ correctly.
CRIS-Team WoS Importer:2022-08-12

Cytology and HPV Co-Testing for Detection of Vaginal Intraepithelial Neoplasia: A Retrospective Study. - Stübs, Frederik; Dietl, Anna; Koch, Martin C.; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Mehlhorn, Grit; Beckmann, Matthias; Schulmeyer, Carla; Heindl, Felix; Emons, Julius; et al. (Cancers, 2023)
(1) Background: Vaginal intraepithelial neoplasia (VaIN) is a rare premalignant disease caused by persistent human papillomavirus (HPV) infection. Diagnosing VaIN is challenging; abnormal cytology and positive HPV tests are usually the first signs, but published data on their accuracy for detecting it are rare and contradictory. The aim of this study is to compare the results of hrHPV and cytology co-testing with the histological findings of the vagina. (2) Methods: In the certified Dysplasia Unit at Erlangen University Hospital, cytology and HPV samples from the uterine cervix or vaginal wall after hysterectomy were obtained between 2015 and 2023 and correlated with histological findings in biopsies from the vaginal wall. Women without vaginal biopsy findings or concomitant cervical disease were excluded. (3) Results: In all, 279 colposcopies in 209 women were included. The histological results were: benign (n = 86), VaIN I/vLSIL (n = 116), VaIN II/vHSIL (n = 41), VaIN III/vHSIL (n = 33), and carcinoma (n = 3). Accuracy for detecting VaIN was higher in women with previous hysterectomies. Positive HPV testing during colposcopy increased the likelihood for VaIN II/III/vHSIL threefold. The detection rate for VaIN III/vHSIL was 50% after hysterectomy and 36.4% without hysterectomy. (4) Conclusions: Women with risk factors for VaIN, including HPV-16 infection or prior HPV-related disease, need careful work-up of the entire vaginal wall. Hysterectomy for HPV-related disease and a history of cervical intraepithelial neoplasia (CIN) also increased the risk for VaIN II/III/vHSIL.
EVALuna2:540622

Cytology and hrHPV for cervical cancer screening assessment - Stübs, Frederik; Koch, M. C.; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, G.; Gaß, Paul; Schulmeyer, Carla (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Cytomegalovirus chemokine receptor M33 knockout reduces chronic allograft rejection in a murine aortic transplant model - Fritz, Niklas; Stamminger, Thomas; Ramsperger-Gleixner, Martina; Kuckhahn, Annika V.; Müller, Regina; Weyand, Michael; Heim, Christian (Transplant Immunology, 2021)
Background: Numerous studies suggest that cytomegalovirus (CMV) infection may act as isolated risk factor in the development of cardiac allograft vasculopathy (CAV). Viral G protein-coupled receptors (GPCRs) are thought to contribute to the pathogenic changes associated with CMV infection. The aim of this study was to investigate the role of murine cytomegalovirus GPCR M33 in the development of CAV in a murine aortic allograft model. Methods: MHC I-mismatched aortas of C.B10 (H2b) mice were transplanted into BALB/c (H2d) recipients, which were either mock-infected, infected with wild type (WT) MCMV or MCMV with a deleted M33-receptor gene (delM33). Persistence of cytomegalovirus infection was confirmed by qPCR and by luciferase assay to ensure active viral replication. Grafts were harvested on days 21 and 37 for intragraft mRNA expression and histological analysis. Results: Active viral replication was demonstrated and MCMV presence was confirmed by PCR within spleen, liver, salivary glands, lung and the aortic transplant. Infection with delM33 resulted in significantly less intimal proliferation compared to WT-MCMV but more pronounced proliferation than in mock-infected allografts (32.19% [delM33] vs. 41.71% [WT-MCMV] vs. 24.33% [MCMV-]). Intragraft expression of most analyzed genes was significantly increased in infected mice. VCAM-1, ICAM-1, PDGFβ, CXCR3 and Granzyme B were distinctly less expressed in grafts of delM33 infected compared to WT infected mice. Cellular infiltration revealed reduced dendritic cells and T cells in grafts infected with delM33 compared to WT MCMV. Conclusions: These data suggest that the MCMV encoded receptor M33 plays an important role as a viral effector mechanism contributing to the development of CAV in a murine aortic transplant model.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Cardiac allograft vasculopathy; CAV; Chemokine receptor; M33; Murine cytomegalovirus; US28

Cytomegalovirus cyclin-dependent kinase ortholog vCDK/pUL97 undergoes regulatory interaction with human cyclin H and CDK7 to codetermine viral replication efficiency - Schütz, Martin; Wangen, Christina; Sommerer, Markus; Kögler, Melanie; Eickhoff, Jan; Degenhart, Carsten; Klebl, Bert; Naing, Zin; Egilmezer, Ece; Hamilton, Stuart T.; Rawlinson, William D.; Sticht, Heinrich; et al. (Virus Research, 2023)
Human cytomegalovirus (HCMV) infection is shaped by a tightly regulated interplay between viral and cellular proteins. Distinct kinase activities, such as the viral cyclin-dependent kinase ortholog (vCDK) pUL97 and cellular CDK7 are both crucial for efficient viral replication. Previously, we reported that both kinases, vCDK/pUL97 and CDK7, interact with cyclin H, thereby achieving an enhanced level of kinase activity and overall functionality in viral replication. Here we provide a variety of novel results, as generated on a methodologically extended basis, and present a concept for the codetermination of viral replication efficiency through these kinase activities: (i) cyclin H expression, in various human cell types, is substantially upregulated by strains of HCMV including the clinically relevant HCMV Merlin; (ii) vCDK/pUL97 interacts with human cyclin H in both HCMV-infected and plasmid-transfected cell systems; (iii) a doxycycline-inducible shRNA-dependent knock-down (KD) of cyclin H significantly reduces pUL97 activity (qSox in vitro kinase assay); (iv) accordingly, pUL97 in vitro kinase activity is seen significantly increased upon addition of recombinant cyclin H; (v) as a point of specific importance, human CDK7 activity shows an increase by vCDK/pUL97-mediated trans-stimulation (whereas pUL97 is not stimulated by CDK7); (vi) phosphosite-specific antibodies indicate an upregulated CDK7 phosphorylation upon HCMV infection, as mediated through a pUL97-specific modulatory effect (i.e. shown by pUL97 inhibitor treatment or pUL97-deficient viral mutant); (vii) finally, an efficient KD of cyclin H in primary fibroblasts generally results in an impaired HCMV replication efficiency as measured on protein and genomic levels. These results show evidence for the codetermination of viral replication by vCDK/pUL97, cyclin H and CDK7, thus supporting the specific importance of cyclin H as a central regulatory factor, and suggesting novel targeting options for antiviral drugs.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Codetermination of viral replication; Cyclin H knock-down; Functional importance of cyclin H; Human cytomegalovirus; Modulation of vCDK/pUL97 activity in vitro; Options for antiviral drug targeting; pUL97-mediated CDK7 trans-stimulation; vCDK/pUL97–cyclin binding; Viral cyclin-dependent kinase (CDK) ortholog

Cytomegalovirus-Infected Cells Resist T Cell Mediated Killing in an HLA-Recognition Independent Manner - Proff, Julia; Walterskirchen, Christian; Brey, Charlotte; Geyeregger, Rene; Full, Florian; Enßer, Armin; Lehner, Manfred; Holter, Wolfgang (Frontiers in Microbiology, 2016)
In order to explore the potential of HLA-independent T cell therapy for human cytomegalovirus (HCMV) infections, we developed a chimeric antigen receptor (CAR) directed against the HCMV encoded glycoprotein B (gB), which is expressed at high levels on the surface of infected cells. T cells engineered with this anti-gB CAR recognized HCMV-infected cells and released cytokines and cytotoxic granules. Unexpectedly, and in contrast to analogous approaches for HIV, Hepatitis B or Hepatitis C virus, we found that HCMV-infected cells were resistant to killing by the CAR-modified T cells. In order to elucidate whether this phenomenon was restricted to the use of CARs, we extended our experiments to T cell receptor (TCR)-mediated recognition of infected cells. To this end we infected fibroblasts with HCMV-strains deficient in viral inhibitors of antigenic peptide presentation and targeted these HLA-class I expressing peptide-loaded infected cells with peptide-specific cytotoxic T cells (CTLs). Despite strong degranulation and cytokine production by the T cells, we again found significant inhibition of lysis of HCMV-infected cells. Impairment of cell lysis became detectable 1 day after HCMV infection and gradually increased during the following 3 days. We thus postulate that viral anti-apoptotic factors, known to inhibit suicide of infected host cells, have evolved additional functions to directly abrogate T cell cytotoxicity. In line with this hypothesis, CAR-T cell cytotoxicity was strongly inhibited in non-infected fibroblasts by expression of the HCMV-protein UL37x1, and even more so by additional expression of UL36. Our data extend the current knowledge on Betaherpesviral evasion from T cell immunity and show for the first time that, beyond impaired antigen presentation, infected cells are efficiently protected by direct blockade of cytotoxic effector functions through viral proteins.
EVALuna2:8321

Cytomegalovirus Infection of the Rat Developing Brain In Utero Prominently Targets Immune Cells and Promotes Early Microglial Activation - Cloarec, Robin; Bauer, Sylvian; Luche, Herve; Buhler, Emmanuelle; Pallesi-Pocachard, Emilie; Salmi, Manal; Courtens, Sandra; Massacrier, Annick; Grenot, Pierre; Teissier, Natacha; Watrin, Francoise; Schaller, Fabienne; et al. (PLoS ONE, 2016)
Congenital cytomegalovirus infections are a leading cause of neurodevelopmental disorders in human and represent a major health care and socio-economical burden. In contrast with this medical importance, the pathophysiological events remain poorly known. Murine models of brain cytomegalovirus infection, mostly neonatal, have brought recent insights into the possible pathogenesis, with convergent evidence for the alteration and possible involvement of brain immune cells.In order to confirm and expand those findings, particularly concerning the early developmental stages following infection of the fetal brain, we have created a model of in utero cytomegalovirus infection in the developing rat brain. Rat cytomegalovirus was injected intraventricularly at embryonic day 15 (E15) and the brains analyzed at various stages until the first postnatal day, using a combination of gene expression analysis, immunohistochemistry and multicolor flow cytometry experiments.Rat cytomegalovirus infection was increasingly seen in various brain areas including the choroid plexi and the ventricular and subventricular areas and was prominently detected in CD45low/int, CD11b+ microglial cells, in CD45high, CD11b+ cells of the myeloid lineage including macrophages, and in CD45+, CD11b- lymphocytes and non-B non-T cells. In parallel, rat cytomegalovirus infection of the developing rat brain rapidly triggered a cascade of pathophysiological events comprising: chemokines upregulation, including CCL2-4, 7 and 12; infiltration by peripheral cells including B-cells and monocytes at E17 and P1, and T-cells at P1; and microglia activation at E17 and P1.In line with previous findings in neonatal murine models and in human specimen, our study further suggests that neuroimmune alterations might play critical roles in the early stages following cytomegalovirus infection of the brain in utero. Further studies are now needed to determine which role, whether favorable or detrimental, those putative double-edge swords events actually play.
EVALuna2:8313

Cytomegalovirus pUL50 is the multi-interacting determinant of the core nuclear egress complex (NEC) that recruits cellular accessory NEC components - Sonntag, Ellen; Hamilton, Stuart T.; Bahsi, Hanife; Wagner, Sabrina; Jonjic, Stipan; Rawlinson, William D.; Marschall, Manfred; Milbradt, Jens (Journal of General Virology, 2016)
Nuclear egress of herpesvirus capsids through the nuclear envelope is mediated by the multimeric nuclear egress complex (NEC). The human cytomegalovirus (HCMV) core NEC is defined by an interaction between the membrane-anchored pUL50 and its nuclear co-factor pUL53, tightly associated through heterodimeric corecruitment to the nuclear envelope. Cellular proteins, such as p32/gC1qR, emerin and protein kinase C (PKC), are recruited by direct interaction with pUL50 for the multimeric extension of the NEC. As a functionally important event, the recruitment of both viral and cellular protein kinases leads to site-specific lamin phosphorylation and nuclear lamina disassembly. In this study, interaction domains within pUL50 for its binding partners were defined by co-immunoprecipitation. The interaction domain for pUL53 is located within the pUL50 N-terminus (residues 10-169), interaction domains for p32/gC1qR (100-358) and PKC (100-280) overlap in the central part of pUL50, and the interaction domain for emerin is located in the C-terminus (265-397). Moreover, expression and formation of core NEC proteins at the nuclear rim were consistently detected in cells permissive for productive HCMV replication, including two trophoblast-cell lines. Importantly, regular nuclear-rim formation of the core NEC was blocked by inhibition of cyclin-dependent kinase (CDK) activity. In relation to the recently published crystal structure of the HCMV core NEC, our findings result in a refined view of NEC assembly. In particular, we suggest that CDKs may play an important regulatory role in NEC formation during HCMV replication.
EVALuna2:8320

Cytoplasmic HIV-RNA in monocytes determines microglial activation and neuronal cell death in HIV-associated neurodegeneration - Faissner, Simon; Ambrosius, Bjoern; Schanzmann, Kirsten; Grewe, Bastian; Potthoff, Anja; Muench, Jan; Sure, Ulrich; Gramberg, Thomas; Wittmann, Sabine; Brockmeyer, Norbert; Ueberla, Klaus; Gold, Ralf; et al. (Experimental Neurology, 2014)
Despite highly active antiretroviral therapy, HIV-associated neurocognitive disorders (HAND) are still highly prevalent. Direct neurotoxicity of microglia activated by HIV-infected monocytes independent from viral replication may account for this observation. To investigate underlying molecular and viral determinants, human monocytoid cells (U937) transduced with HIV-particles were co-cultured with primary human microglia or astrocytes. Using genetically-engineered HIV-particles key steps of infection were examined. Levels of pro-inflammatory/neurotoxic cytokines were investigated in co-culture supernatants by flow cytometry. Neurotoxicity mediated by the supernatants was analysed using primary cortical rat neurons. To corroborate our findings, cytokine profiles in cerebrospinal fluid (CSF) of neuropsychologically asymptomatic HIV positive (HIV(+)) patients (n=45) were correlated with neurofilament H (NfH) as surrogate of neuronal/axonal degeneration. In contrast to direct exposure of HIV to microglia, only the presence of HIV-transduced monocytoid cells strongly activated human microglia as evidenced by enhanced secretion of CXCL10, CCL5, CCL2, and IL-6 (1.3-7.1-fold; p<0.01) leading to two-fold increased neurotoxicity (p<0.001). In direct comparison, astrocyte activation by HIV-transduced monocytoid cells was limited. Using different mutant HIV-particles we show that the presence of cytoplasmic HIV-RNA in monocytoid cells is the viral determinant for this unique microglial activation pattern and subsequent neuronal cell death; reverse transcription and expression of viral genes were not essential. In CSF of presymptomatic HIV(+) patients, CXCL10, CCL5 and IL-6 were correlated with NfH as surrogate marker of neurodegeneration as well as CSF-pleocytosis. In conclusion, cytosolic viral RNA in monocytes is mandatory for subsequent microglial activation and neurotoxicity; activated astrocytes may augment neuroinflammation. In addition, neuroinflammation and neurodegeneration occur even in preclinical HIV(+) patients and are associated with cytokines regulated in vitro. Our data may aid in the development of biomarkers and glia-directed therapeutic approaches of HAND.
EVALuna2:8227

Decorated and Encapsulated: Virus-Like Particles Against Viral Infections - Temchura, Vladimir (Vaccines, 2021)
CRIS-Team WoS Importer:2021-04-16

Deeper Insight into the Six-Step Domino Reaction of Aldehydes with Malononitrile and Evaluation of Antiviral and Antimalarial Activities of the Obtained Bicyclic Products. - Bock, Christina; Gangajji, Parameshwarappa; Bönisch, Simon; Bauer, Walter; Hutterer, Corina; Leidenberger, Maria; Friedrich, Oliver; Marschall, Manfred; Kappes, Bärbel; Görling, Andreas; Tsogoeva, Svetlana (ChemistryOpen, 2017)
The straightforward and efficient synthesis of complex aza- and carbobicyclic compounds, which are of importance for medicinal chemistry, is a challenge for modern chemical methodology. An unprecedented metal-free six-step domino reaction of aldehydes with malononitrile was presented in our previous study to provide, in a single operation, these bicyclic nitrogen-containing molecules. Presented here is a deeper investigation of this atom-economical domino process by extending the scope of aldehydes, performing post-modifications of domino products, applying bifunctional organocatalysts and comprehensive NMR studies of selected domino products. The thermodynamic aspects of the overall reaction are also demonstrated using DFT methods in conjunction with a semi-empirical treatment of van der Waals interactions. Furthermore, biological studies of seven highly functionalized and artemisinin-containing domino products against human cytomegalovirus (HCMV) and Plasmodium falciparum 3D7 are presented. Remarkably, in vitro tests against HCMV revealed five domino products to be highly active compounds (EC50 0.071-1.8 μm), outperforming the clinical reference drug ganciclovir (EC50 2.6 μm). Against P. falciparum 3D7, three of the investigated artemisinin-derived domino products (EC50 0.72-1.8 nm) were more potent than the clinical drug chloroquine (EC50 9.1 nm).

Deficiency for SAMHD1 activates MDA5 in a cGAS/STING-dependent manner - Schumann, Tina; Ramon, Santiago Costas; Schubert, Nadja; Mayo, Mohamad Aref; Hega, Melanie; Maser, Katharina Isabell; Ada, Servi Remzi; Sydow, Lukas; Hajikazemi, Mona; Badstübner, Markus; Müller, Patrick; Ge, Yan; et al. (Journal of Experimental Medicine, 2023)
Defects in nucleic acid metabolizing enzymes can lead to spontaneous but selective activation of either cGAS/STING or RIG-like receptor (RLR) signaling, causing type I interferon-driven inflammatory diseases. In these pathophysiological conditions, activation of the DNA sensor cGAS and IFN production are linked to spontaneous DNA damage. Physiological, or tonic, IFN signaling on the other hand is essential to functionally prime nucleic acid sensing pathways. Here, we show that low-level chronic DNA damage in mice lacking the Aicardi-Goutières syndrome gene SAMHD1 reduced tumor-free survival when crossed to a p53-deficient, but not to a DNA mismatch repair-deficient background. Increased DNA damage did not result in higher levels of type I interferon. Instead, we found that the chronic interferon response in SAMHD1-deficient mice was driven by the MDA5/MAVS pathway but required functional priming through the cGAS/STING pathway. Our work positions cGAS/STING upstream of tonic IFN signaling in Samhd1-deficient mice and highlights an important role of the pathway in physiological and pathophysiological innate immune priming.
CRIS-Team Scopus Importer:2022-11-25

Definition of a New HLA B*52-Restricted Rev CTL Epitope Targeted by an HIV-1-Infected Controller - El Kenz, Boutaina; Schmidt, Katja; Ogungbemi-Alt, Victoria K.; Bergmann, Silke; Steininger, Philipp; Korn, Klaus; Spriewald, Bernd; Harrer, Ellen; Nganou-Makamdop, Krystelle; Harrer, Thomas (Viruses, 2023)
The analysis of T-cell responses in HIV-1-infected controllers may contribute to a better understanding of the protective components of the immune system. Here, we analyzed the HIV-1-specific T-cell response in a 59-year-old HIV-1-infected controller, infected for at least seven years, who presented with low viral loads ranging from <20 copies/mL to 200 copies/mL and normal CD4 counts of >800 cells/µL. In γ-IFN-ELISpot assays using freshly isolated PBMCs, he displayed a very strong polyclonal T-cell response to eight epitopes in Gag, Nef and Rev; with the dominant responses directed against the HLA-B*57-epitope AISPRTLNAW and against a so-far-unknown epitope within Rev. Further analyses using peptide-stimulated T-cell lines in γ-IFN-ELISpot assays delineated the peptide RQRQIRSI (Rev-RI8) as a newly defined HLA-B*52-restricted epitope located within a functionally important region of Rev. Peptide-stimulation assays in 15 HLA-B*52-positive HIV-1-infected subjects, including the controller, demonstrated recognition of the Rev-RI8 epitope in 6/15 subjects. CD4 counts before the start of antiviral therapy were significantly higher in subjects with recognition of the Rev-RI8 epitope. Targeting of the Rev-RI8 epitope in Rev by CTL could contribute to the positive association of HLA-B*52 with a more favorable course of HIV-1-infection.
CRIS-Team Scopus Importer:2023-03-10
Keywords: CTL; elite controller; epitope; HIV-1 infection; HLA B*52; Rev

Dendritic cell targeted HIV-1 gag protein vaccine provides help to a recombinant Newcastle disease virus vectored vaccine including mobilization of protective CD8+ T cells - Ngu, Loveline N.; Nji, Nadesh N.; Ambada, Georgia; Ngoh, Apeh A.; Njambe Priso, Ghislain D.; Tchadji, Jules C.; Lissom, Abel; Magagoum, Suzanne H.; Sake, Carol N.; Tchouangueu, Thibau F.; Chukwuma, George O.; Okoli, Arinze S.; et al. (Immunity, Inflammation and Disease, 2018)
INTRODUCTION: Recombinant Newcastle Disease virus (rNDV) vectored vaccines are safe mucosal applicable vaccines with intrinsic immune-modulatory properties for the induction of efficient immunity. Like all viral vectored vaccines repeated inoculation via mucosal routes invariably results to immunity against viral vaccine vectors. To obviate immunity against viral vaccine vectors and improve the ability of rNDV vectored vaccines in inducing T cell immunity in murine air way we have directed dendritic cell targeted HIV-1 gag protein (DEC-Gag) vaccine; for the induction of helper CD4+ T cells to a Recombinant Newcastle disease virus expressing codon optimized HIV-1 Gag P55 (rNDV-L-Gag) vaccine. METHODS: We do so through successive administration of anti-DEC205-gagP24 protein plus polyICLC (DEC-Gag) vaccine and rNDV-L-Gag. First strong gag specific helper CD4+ T cells are induced in mice by selected targeting of anti-DEC205-gagP24 protein vaccine to dendritic cells (DC) in situ together with polyICLC as adjuvant. This targeting helped T cell immunity develop to a subsequent rNDV-L-Gag vaccine and improved both systemic and mucosal gag specific immunity. RESULTS: This sequential DEC-Gag vaccine prime followed by an rNDV-L-gag boost results to improved viral vectored immunization in murine airway, including mobilization of protective CD8+ T cells to a pathogenic virus infection site. CONCLUSION: Thus, complementary prime boost vaccination, in which prime and boost favor distinct types of T cell immunity, improves viral vectored immunization, including mobilization of protective CD8+ T cells to a pathogenic virus infection site such as the murine airway.
EVALuna2:35818

Deregulation of Fas ligand expression as a novel cause of autoimmune lymphoproliferative syndrome-like disease - Nabhani, Schafiq; Ginzel, Sebastian; Miskin, Hagit; Revel-Vilk, Shoshana; Harlev, Dan; Fleckenstein, Bernhard; Hoenscheid, Andrea; Oommen, Prasad T.; Kuhlen, Michaela; Thiele, Ralf; Laws, Hans-Juergen; Borkhardt, Arndt; et al. (Haematologica, 2015)
Autoimmune lymphoproliferative syndrome is frequently caused by mutations in genes involved in the Fas death receptor pathway, but for 20-30% of patients the genetic defect is unknown. We observed that treatment of healthy T cells with interleukin-12 induces upregulation of Fas ligand and Fas ligand-dependent apoptosis. Consistently, interleukin-12 could not induce apoptosis in Fas ligand-deficient T cells from patients with autoimmune lymphoproliferative syndrome. We hypothesized that defects in the interleukin-12 signaling pathway may cause a similar phenotype as that caused by mutations of the Fas ligand gene. To test this, we analyzed 20 patients with autoimmune lymphoproliferative syndrome of unknown cause by whole-exome sequencing. We identified a homozygous nonsense mutation (c.698G>A, p.R212*) in the interleukin-12/interleukin-23 receptor-component IL12RB1 in one of these patients. The mutation led to IL12RB1 protein truncation and loss of cell surface expression. Interleukin-12 and -23 signaling was completely abrogated as demonstrated by deficient STAT4 phosphorylation and interferon ? production. Interleukin-12-mediated expression of membrane-bound and soluble Fas ligand was lacking and basal expression was much lower than in healthy controls. The patient presented with the classical symptoms of autoimmune lymphoproliferative syndrome: chronic non-malignant, non-infectious lymphadenopathy, splenomegaly, hepatomegaly, elevated numbers of double-negative T cells, autoimmune cytopenias, and increased levels of vitamin B12 and interleukin-10. Sanger sequencing and whole-exome sequencing excluded the presence of germline or somatic mutations in genes known to be associated with the autoimmune lymphoproliferative syndrome. Our data suggest that deficient regulation of Fas ligand expression by regulators such as the interleukin-12 signaling pathway may be an alternative cause of autoimmune lymphoproliferative syndrome-like disease.
EVALuna2:8295

Design and Functional Characterization of HIV-1 Envelope Protein-Coupled T Helper Liposomes - Damm, Dominik; Suleiman, Ehsan; Theobald, Hannah; Wagner, Jannik; Batzoni, Mirjam; Kohlhauser, Bianca Ahlfeld Née; Walkenfort, Bernd; Albrecht, Jens Christian; Ingale, Jidnyasa; Yang, Lifei; Hasenberg, Mike; Wyatt, Richard T.; et al. (Pharmaceutics, 2022)
Functionalization of experimental HIV-1 virus-like particle vaccines with heterologous T helper epitopes (T helper VLPs) can modulate the humoral immune response via intrastructural help (ISH). Current advances in the conjugation of native-like HIV-1 envelope trimers (Env) onto liposomes and encapsulation of peptide epitopes into these nanoparticles renders this GMP-scalable liposomal platform a feasible alternative to VLP-based vaccines. In this study, we designed and analyzed customizable Env-conjugated T helper liposomes. First, we passively encapsulated T helper peptides into a well-characterized liposome formulation displaying a dense array of Env trimers on the surface. We confirmed the closed pre-fusion state of the coupled Env trimers by immunogold staining with conformation-specific antibodies. These peptide-loaded Env-liposome conjugates efficiently activated Env-specific B cells, which further induced proliferation of CD4+ T cells by presentation of liposome-derived peptides on MHC-II molecules. The peptide encapsulation process was then quantitatively improved by an electrostatically driven approach using an overall anionic lipid formulation. We demonstrated that peptides delivered by liposomes were presented by DCs in secondary lymphoid organs after intramuscular immunization of mice. UFO (uncleaved prefusion optimized) Env trimers were covalently coupled to peptide-loaded anionic liposomes by His-tag/NTA(Ni) interactions and EDC/Sulfo-NHS crosslinking. EM imaging revealed a moderately dense array of well-folded Env trimers on the liposomal surface. The conformation was verified by liposomal surface FACS. Furthermore, anionic Env-coupled T helper liposomes effectively induced Env-specific B cell activation and proliferation in a comparable range to T helper VLPs. Taken together, we demonstrated that T helper VLPs can be substituted with customizable and GMP-scalable liposomal nanoparticles as a perspective for future preclinical and clinical HIV vaccine applications. The functional nanoparticle characterization assays shown in this study can be applied to other systems of synthetic nanoparticles delivering antigens derived from various pathogens.
CRIS-Team Scopus Importer:2022-07-15
Keywords: coupling mechanism; Env trimer; functionalization; GMP; HIV; immunogold staining; intrastructural help; peptide encapsulation; T helper liposomes; vaccine

Destabilization of the human epigenome: consequences of foreign DNA insertions - Weber, Stefanie; Hofmann, Andrea; Herms, Stefan; Hoffmann, Per; Doerfler, Walter (Epigenomics, 2015)
We previously reported changes of DNA methylation and transcription patterns in mammalian cells that carry integrated foreign DNA. Experiments were now designed to assess the epigenetic consequences of inserting a 5.6 kbp plasmid into the human genome.Differential transcription and CpG methylation patterns were compared between transgenomic and nontransgenomic cell clones by using gene chip microarray systems.In 4.7% of the 28.869 gene segments analyzed, transcriptional activities were up- or downregulated in the transgenomic cell clones. Genome-wide profiling revealed differential methylation in 3791 of > 480,000 CpG's examined in transgenomic versus nontransgenomic clones.The data document genome-wide effects of foreign DNA insertions on the epigenetic stability of human cells. Many fields in experimental biology and medicine employ transgenomic or otherwise genome-manipulated cells or organisms without considering the epigenetic consequences for the recipient genomes.
EVALuna2:8268

Detection of antibody-secreting cells specific for the cytomegalovirus and herpes simplex virus surface antigens - Alt, Mira; Falk, Jessica; Eis-Huebinger, Anna Maria; Kropff, Barbara; Sinzger, Christian; Krawczyk, Adalbert (Journal of Immunological Methods, 2018)
Infections with the herpes simplex virus (HSV) and the human cytomegalovirus (HCMV) can lead to life-threatening diseases, particularly in immunosuppressed patients. Furthermore, HSV infections at birth (herpes neonatorum) can result in a disseminated disease associated with a fatal multiorgan failure. Congenital HCMV infections can result in miscarriage, serious birth defects or developmental disabilities. Antibody-based interventions with hyperimmunoglobulins showed encouraging results in clinical studies, but clearly need to be improved. The isolation of highly neutralizing monoclonal antibodies is a promising strategy to establish potent therapy options against HSV and HCMV infections. Monoclonal antibodies are commonly isolated from hybridomas or EBV-immortalized B-cell clones. The screening procedure to identify virus-specific cells from a cell mixture is a challenging step, since most of the highly neutralizing antibodies target complex conformational epitopes on the virus surface. Conventional assays such as ELISA are based on purified viral proteins and inappropriate to display complex epitopes. To overcome this obstacle, we have established two full-virus based methods that allow screening for cells and antibodies targeting complex conformational epitopes on viral surface antigens. The methods are suitable to detect surface antigen-specific cells from a cell mixture and may facilitate the isolation of highly neutralizing antibodies against HSV and HCMV.
EVALuna2:35357

Detection of asymptomatic SARS-CoV-2 infections in daycare centers, schools, and companies for regional pandemic containment by a PCR testing laboratory cooperative between July 2021 and June 2022 - Bertram, Ralph; Grebenstein, Laura; Gualdi, Stefanie; Seibold, Bernd; Birkmann, Ralf; Korn, Klaus; Bisping, Johannes; Schabik, Ralf (GMS Hygiene and Infection Control, 2022)
As an important element in the regional containment of the COVID-19 pandemic a PCR testing laboratory with a cooperative character was founded in spring 2021 to screen for SARS-CoV-2 in the Nuremberg region, Germany. The aim was to detect asymptomatic infections in day care facilities for children, schools, and companies. The laboratory used an established RT-PCR protocol and analyzed approximately 18,500 pools of up to 25 pooled samples each from gargles or swabs ("lolli-pops") from up to 135 facilities between July 2021 and June 2022. Usually, the participating facilities were informed about positive pools within a few hours. Retention samples from positive pools were usually analyzed on the same day, and the results were reported to the facilities as well as the German Electronic Reporting and Information System (DEMIS). In the laboratory results, both the local incidences and the transition from the Delta-to the Omicron surge in early 2022 were well reflected. It is plausible that about 4,800 secondary infections could be prevented from the approximately 1,570 positive individual samples detected in conjunction with appropriate isolation measures. Such a PCR laboratory, which is characterized by short response times and high flexibility, can thus provide valuable services for regional surveil-lance of infection incidence.
CRIS-Team WoS Importer:2022-12-23

Detection of pre-existing neutralizing antibodies against Ad26 in HIV-1-infected individuals not responding to the Ad26.COV2.S vaccine - Schmidt, Katja; Harrer, Ellen; Schönau, Verena; Simon, David; Kleyer, Arnd; Steininger, Philipp; Korn, Klaus; Schett, Georg; Knobloch, Carina; Nganou-Makamdop, Krystelle; Harrer, Thomas (Infection, 2023)
Purpose: The Ad26.COV2.S vaccine is a replication-incompetent human adenovirus type 26 vector encoding the SARS-CoV-2 spike protein. In a phase 1-2a trial, a single dose of Ad26.COV2.S induced SARS-CoV-2 spike-specific antibodies in ≥ 96% of healthy adults. To investigate vaccine immunogenicity in HIV-1-infection, we measured SARS-CoV-2 spike-specific antibodies in Ad26.COV2.S vaccinated HIV-1-infected patients and analyzed the presence of pre-existing Ad26 neutralizing antibodies. Methods: We included all Ad26.COV2.S vaccinated HIV-1-infected patients of Erlangen HIV cohort fulfilling all inclusion criteria. The study cohort consisted of 15 HIV-1-infected patients and three HIV-1-uninfected subjects who received the Ad26.COV2.S vaccine between April and November 2021. Pre-vaccination sera were collected between October 2014 and June 2021, post-vaccination sera between June and December 2021. Neutralizing antibodies towards Ad26 were determined by a FACS-based inhibition assay measuring the expression of SARS-CoV-2 spike and adenoviral proteins in HEK293T cells after in-vitro transduction with Ad26.COV2.S or the control ChAdOx1-S. Results: Six out of 15 HIV-1-infected patients failed to develop SARS-CoV-2-specific antibodies and four patients developed weak antibody responses after vaccination with Ad26.COV2.S. Pre-vaccination sera of four of the six vaccine non-responders showed neutralizing activity towards Ad26.COV2.S but not toward the ChAdOx1-S vaccine at 1:50 dilution. After Ad26.COV2.S vaccination, 17 of the 18 subjects developed strong Ad26-neutralizing activity and only one of the 18 subjects showed neutralizing activity towards the ChAdOx1-S vaccine. Conclusion: Ad26.COV2.S vaccination showed a high failure rate in HIV-1-infected patients. Pre-existing immunity against Ad26 could be an important contributor to poor vaccine efficacy in a subgroup of patients.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Ad26.COV2.S; Adenovirus 26; HIV-1; Neutralizing antibodies; SARS-CoV-2; SARS-CoV-2 vaccine

Development of a PROTAC-based targeting strategy provides a mechanistically unique mode of anti-cytomegalovirus activity - Hahn, Friedrich; Hamilton, Stuart T.; Wangen, Christina; Wild, Markus; Kicuntod, Jintawee; Brückner, Nadine; Follett, Jasmine E.L.; Herrmann, Lars; Kheimar, Ahmed; Kaufer, Benedikt B.; Rawlinson, William D.; Tsogoeva, Svetlana; et al. (International Journal of Molecular Sciences, 2021)
Human cytomegalovirus (HCMV) is a major pathogenic herpesvirus that is prevalent worldwide and it is associated with a variety of clinical symptoms. Current antiviral therapy options do not fully satisfy the medical needs; thus, improved drug classes and drug-targeting strategies are required. In particular, host-directed antivirals, including pharmaceutical kinase inhibitors, might help improve the drug qualities. Here, we focused on utilizing PROteolysis TArgeting Chimeras (PROTACs), i.e., hetero-bifunctional molecules containing two elements, namely a target-binding molecule and a proteolysis-inducing element. Specifically, a PROTAC that was based on a cyclin-dependent kinase (CDK) inhibitor, i.e., CDK9-directed PROTAC THAL-SNS032, was analyzed and proved to possess strong anti-HCMV AD169-GFP activity, with values of EC50 of 0.030 µM and CC50 of 0.175 µM (SI of 5.8). Comparing the effect of THAL-SNS032 with its non-PROTAC counterpart SNS032, data indicated a 3.7-fold stronger anti-HCMV efficacy. This antiviral activity, as illustrated for further clinically relevant strains of human and murine CMVs, coincided with the mid-nanomolar concentration range necessary for a drug-induced degradation of the primary (CDK9) and secondary targets (CDK1, CDK2, CDK7). In addition, further antiviral activities were demonstrated, such as the inhibition of SARS-CoV-2 replication, whereas other investigated human viruses (i.e., varicella zoster virus, adenovirus type 2, and Zika virus) were found insensitive. Combined, the antiviral quality of this approach is seen in its (i) mechanistic uniqueness; (ii) future options of combinatorial drug treatment; (iii) potential broad-spectrum activity; and (iv) applicability in clinically relevant antiviral models. These novel data are discussed in light of the current achievements of anti-HCMV drug development.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Antiviral drugs; Direct-acting antivirals; Host-directed antivirals; Human cytomegalovirus; Human/animal pathogenic viruses; New drug qualities; PROTAC-based targeting strategy; PROteolysis TArgeting Chimeras

Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections - Huber, Timo; Steininger, Philipp; Irrgang, Pascal; Korn, Klaus; Tenbusch, Matthias; Diesch, Katharina; Achenbach, Susanne; Kremer, Andreas; Werblow, Marissa; Vetter, Marcel; Bogdan, Christian; Held, Jürgen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
SARS-CoV-2 antibody assays are used for epidemiological studies and for the assessment of vaccine responses in highly vulnerable patients. So far, data on cross-reactivity of SARS-CoV-2 antibody assays is limited. Here, we compared four enzyme-linked immunosorbent assays (ELISAs; Vircell SARS-CoV-2 IgM/IgA and IgG, Euroimmun SARS-CoV-2 IgA and IgG) for detection of anti-SARS-CoV-2 antibodies in 207 patients with COVID-19, 178 patients with serological evidence of different bacterial infections, 107 patients with confirmed viral respiratory disease, and 80 controls from the pre-COVID-19 era. In COVID-19 patients, the assays showed highest sensitivity in week 3 (Vircell-IgM/A and Euroimmun-IgA: 78.9% each) and after week 7 (Vircell-IgG: 97.9%; Euroimmun-IgG: 92.1%). The antibody indices were higher in patients with fatal disease. In general, IgM/IgA assays had only limited or no benefit over IgG assays. In patients with non-SARS-CoV-2 respiratory infections, IgG assays were more specific than IgM/IgA assays, and bacterial infections were associated with more false-positive results than viral infections. The specificities in bacterial and viral infections were 68.0 and 81.3% (Vircell-IgM/IgA), 84.8 and 96.3% (Euroimmun-IgA), 97.8 and 86.0% (Vircell-IgG), and 97.8 and 99.1% (Euroimmun-IgG), respectively. Sera from patients positive for antibodies against Mycoplasma pneumoniae, Chlamydia psittaci, and Legionella pneumophila yielded particularly high rates of unspecific false-positive results in the IgM/IgA assays, which was revealed by applying a highly specific flow-cytometric assay using HEK 293 T cells expressing the SARS-CoV-2 spike protein. Positive results obtained with anti-SARS-CoV-2 IgM/IgA ELISAs require careful interpretation, especially if there is evidence for prior bacterial respiratory infections.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Antibody; Bacterial infections; Coronavirus; COVID-19; Euroimmun; SARS-CoV-2; Vircell

Diazadispiroalkane derivatives are new viral entry inhibitors - Adfeldt, Rebekka; Schmitz, Janna; Kropff, Barbara; Thomas, Marco; Monakhova, Natalia; Hölper, Julia E.; Klupp, Barbara G.; Mettenleiter, Thomas C.; Makarov, Vadim; Bogner, Elke (Antimicrobial Agents and Chemotherapy, 2021)
Herpesviruses are widespread and can cause serious illness. Many currently available antiviral drugs have limited effects, result in rapid development of resistance, and often exhibit dose-dependent toxicity. Especially for human cytomegalovirus (HCMV), new well-tolerated compounds with novel mechanisms of action are urgently needed. In this study, we characterized the antiviral activity of two new diazadispiroalkane derivatives, 11826091 and 11826236. These two small molecules exhibited strong activity against low-passage-number HCMV. Pretreatment of cellfree virus with these compounds greatly reduced infection. Time-of-addition assays where 11826091 or 11826236 was added to cells before infection, before and during infection, or during or after infection demonstrated an inhibitory effect on early steps of infection. Interestingly, 11826236 had an effect by addition to cells after infection. Results from entry assays showed the major effect to be on attachment. Only 11826236 had a minimal effect on penetration comparable to heparin. Further, no effect on virus infection was found for cell lines with a defect in heparan sulfate expression or lacking all surface glycosaminoglycans, indicating that these small molecules bind to heparan sulfate on the cell surface. To test this further, we extended our analyses to pseudorabies virus (PrV), a member of the Alphaherpesvirinae, which is known to use cell surface heparan sulfate for initial attachment via nonessential glycoprotein C (gC). While infection with PrV wild type was strongly impaired by 11826091 or 11826236, as with heparin, a mutant lacking gC was unaffected by either treatment, demonstrating that primary attachment to heparan sulfate via gC is targeted by these small molecules.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Antiviral activity; Entry inhibitors; Heparan sulfate binding; Human cytomegalovirus; New mode of action; Pseudorabies virus; Virus attachment

Differences in Growth Properties among Two Human Cytomegalovirus Glycoprotein O Genotypes - Kalser, Julia; Adler, Barbara; Mach, Michael; Kropff, Barbara; Puchhammer-Stoeckl, Elisabeth; Goerzer, Irene (Frontiers in Microbiology, 2017)
Glycoprotein O (gO) of the human cytomegalovirus (HCMV) is the critical subunit of the envelope trimer gH/gL/gO as it interacts with platelet-derived growth factor alpha receptor upon fibroblast entry, and triggers gB-mediated fusion for fibroblast and epithelial cell infection. Eight genotypes (GT) of the highly polymorphic gO gene are described, yet it is unclear whether the distinct GTs differ in their function. Thus, we aimed to elucidate potential functional differences between two highly diverse gO GTs in an otherwise genomically identical HCMV strain. Therefore, resident gO GT1c sequence of strain TB40-BAC4-luc was entirely replaced by gO GT4 of strain Towne and both, GT1c and GT4 viruses, were investigated for their growth properties in fibroblasts and epithelial cells. In addition, two conserved gO cysteines involved in gH/gL/gO stabilization were mutated to serine either in GT1c (C218S and C343S) or GT4 (C216S and C336S) and their effects on cell-free infectivity were assessed. GT4 viruses displayed a significantly enhanced epithelial cell tropism and this resulted in higher virus release upon replication in epithelial cells when compared to GT1c viruses. Further, when the two cysteines were individually mutated in gO GT1c no impairment in cell-free infectivity was observed. This, however, was in sharp contrast to gO GT4, in which both of the corresponding cysteine mutations led to a substantial reduction in cell-free infectivity which was even more pronounced upon mutation of GT4-C336 than of GT4-C216. In conclusion, these findings provide evidence that the two highly diverse gO genotypes, GT1c and GT4, differ in their functional properties as revealed by their different infection capacities for epithelial cells and by their different responsiveness to mutation of strictly conserved cysteine residues. Thus, it is likely that the gO heterogeneity influences cell-free infectivity of HCMV alsoin vivowhich may have important implications for virus host transmission.
EVALuna2:33757

Differential induction of lung-resident memory T cells through infection or viral vector immunization - Schmidt, Anna; Fuchs, Julian; Lapuente, Dennis; Huebner, J.; Vieira Antao, Ana Isabel; Irrgang, P.; Paudyal, B.; Mcnee, A.; Vatzia, E.; Carr, V.; Villanueva, S.; Manjegowda, T.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Differential Levels and Phosphorylation of Type 1 Inositol 1,4,5-Trisphosphate Receptor in Four Different Murine Models of Huntington Disease - Post, Joakim Iver; Leergaard, Trygve B.; Ratz, Veronika; Walaas, S. Ivar; von Hörsten, Stephan; Nissen-Meyer, Lise Sofie H. (Journal of Huntington's Disease, 2019)
Background: The intracellular ion channel type 1 inositol 1,4,5-trisphosphate receptor (IP(3)R1) releases Ca-2(+) from the endoplasmic reticulum upon stimulation with IP3. Perturbation of IP(3)R1 has been implicated in the development of several neurodegenerative disorders, including Huntington disease (HD).
CRIS-Team WoS Importer:2019-09-13

Differential OVA-induced pulmonary inflammation and unspecific reaction in Dark Agouti (DA) rats contingent on CD26/DPPIV deficiency - Tasic, Tihana; Stephan, Michael; von Hörsten, Stephan; Pabst, Reinhard; Schmiedl, Andreas (Immunobiology, 2014)
Many disease models have shown that, within the species rat, different strains are differentially susceptible to asthma-induced inflammation depending on the genetic background. Likewise, CD26/DPPIV-deficiency in asthmatic F344 rats has been shown to result in a less pronounced inflammation and in increased Treg cell influx into the lung compared to wild-types. The aim of the present study was to investigate whether the genetic background of the animals interferes with CD26/DPPIV-deficiency in a model of allergic-like inflammation, or whether the deficiency per se is the predominant regulator of the inflammation. Therefore, we hypothesised that CD26/DPPIV-deficient Dark Agouti (DA) rats also exhibit a less pronounced ovalbumin (OVA)-induced inflammation compared to wild-types. After sensitisation with OVA, Al(OH)3 and heat-killed Bordetella pertussis bacilli, animals were challenged three times with 5% aerosolized OVA at intervals of 24h, i.e., on three consecutive days. 24h after the third challenge, animals were sacrificed and examined. In both wild-type and CD26/DPPIV-deficient rat groups, asthma induction led to (1) lung inflammation, (2) significantly increased eosinophil infiltration in the BALF, (3) significantly increased IgE serum levels, (4) a significant increase of inflammatory cytokines, (5) a significant increase of different T cell populations in the lungs and in their draining lymph nodes, as well as to (6) a significantly higher number of all T lymphocyte subtypes in the blood. Thus, the degree of the OVA-induced Th2-driven pulmonary inflammation was similarly pronounced in both wild-type and CD26/DPPIV-deficient DA rats.
EVALuna2:24970

Differential properties of cytomegalovirus pUL97 kinase isoforms affect viral replication and maribavir susceptibility - Webel, Rike; Hakki, Morgan; Prichard, Mark N.; Rawlinson, William D.; Marschall, Manfred; Chou, Sunwen (Journal of Virology, 2014)
The human cytomegalovirus (HCMV)-encoded kinase pUL97 is required for efficient viral replication. Previous studies described two isoforms of pUL97, the full-length isoform (M1) and a smaller isoform likely resulting from translation initiation at codon 74 (M74). Here, we report the detection of a third pUL97 isoform during viral infection resulting from translation initiation at codon 157 (isoform M157). The consistent expression of isoform M157 as a minor component of pUL97 during infection with clinical and laboratory-adapted HCMV strains was suppressed when codon 157 was mutagenized. Viral mutants expressing specific isoforms were generated to compare their growth and drug susceptibility phenotypes, as well as pUL97 intracellular localization patterns and kinase activities. The exclusive expression of isoform M157 resulted in substantially reduced viral growth and resistance to the pUL97 inhibitor maribavir while retaining susceptibility to ganciclovir. Confocal imaging demonstrated reduced nuclear import of amino-terminal deletion isoforms compared to isoform M1. Isoform M157 showed reduced efficiency of various substrate protein interactions and autophosphorylation, whereas Rb phosphorylation was preserved. These results reveal differential properties of pUL97 isoforms that affect viral replication, with implications for the antiviral efficacy of maribavir.The HCMV UL97 kinase performs important functions in viral replication that are targeted by the antiviral drug maribavir. Here, we describe a naturally occurring short isoform of the kinase that when expressed by itself in a recombinant virus results in altered intracellular localization, impaired growth, and high-level resistance to maribavir compared to those of the predominant full-length counterpart. This is another factor to consider in explaining why maribavir appears to have variable antiviral activity in cell culture and in vivo.
EVALuna2:8230

Differential severity of LPS-induced lung injury in CD26/DPP4 positive and deficient F344 rats - Zientara, Alicja; Stephan, Michael; von Hörsten, Stephan; Schmiedl, Andreas (Histology and Histopathology, 2019)
BACKGROUND: Lipopolysaccharide (LPS) induced inflammation often leads to lung injury, in which pulmonary recruitment of neutrophils plays a pivotal role. Inflammatory processes are influenced by CD26/DPP4, highly expressed in lungs. Asthma induced CD26/DPP4 deficient (CD26/DPP4⁻) Fischer (F) 344 rats suffering from a transport block in the rER caused by a point mutation showed reduced pulmonary inflammation and reduced expression of immunomodulating surfactant proteins (SP). The degree of LPS induced lung injury in CD26/DPP4 deficient rats has not been investigated so far. OBJECTIVE: We hypothesize that LPS induced lung injury leads not only to an attenuated inflammation but also to a reduced SP expression and decreased structural damage in CD26/DPP4⁻ rats. METHODS: Both genotypes were intratracheally instilled with 250 µl LPS or with 250 µl 0.9% NaCl. Nine hours later animals were killed and either bronchoalveolar lavage was carried out to determine inflammatory cells and surface tension or lung blocks were removed and processed for histology, immunohistochemistry, electron microscopy or qRt-PCR analyses and Western Blot analyses. RESULTS: Signs of acute lung injury, such as structural damage of the blood gas barrier occurred only sporadically in both genotypes. LPS-induced CD26/DPP4⁻ rats showed decreased gene expression of SP-A and SP-D and reduced signs of lung inflammation associated with a reduced alveolar influx of macrophages and neutrophils. CONCLUSIONS: Less pulmonary inflammation combined with less structural alterations and minor expression of immunomodulating SP may be an indication of the critical role of CD26/DPP4 in regulating lung inflammation.
CRIS-Team Scopus Importer:2019-10-15

Differential transgene expression patterns in Alzheimer mouse models revealed by novel human amyloid precursor protein-specific antibodies - Hoefling, Corinna; Morawski, Markus; Zeitschel, Ulrike; Zanier, Elisa R.; Moschke, Katrin; Serdaroglu, Alperen; Canneva, Fabio; von Hörsten, Stephan; De Simoni, Maria-Grazia; Forloni, Gianluigi; Jaeger, Carsten; Kremmer, Elisabeth; et al. (Aging Cell, 2016)
Alzheimer's disease (AD) is histopathologically characterized by neurodegeneration, the formation of intracellular neurofibrillary tangles and extracellular A? deposits that derive from proteolytic processing of the amyloid precursor protein (APP). As rodents do not normally develop A? pathology, various transgenic animal models of AD were designed to overexpress human APP with mutations favouring its amyloidogenic processing. However, these mouse models display tremendous differences in the spatial and temporal appearance of A? deposits, synaptic dysfunction, neurodegeneration and the manifestation of learning deficits which may be caused by age-related and brain region-specific differences in APP transgene levels. Consequentially, a comparative temporal and regional analysis of the pathological effects of A? in mouse brains is difficult complicating the validation of therapeutic AD treatment strategies in different mouse models. To date, no antibodies are available that properly discriminate endogenous rodent and transgenic human APP in brains of APP-transgenic animals. Here, we developed and characterized rat monoclonal antibodies by immunohistochemistry and Western blot that detect human but not murine APP in brains of three APP-transgenic mouse and one APP-transgenic rat model. We observed remarkable differences in expression levels and brain region-specific expression of human APP among the investigated transgenic mouse lines. This may explain the differences between APP-transgenic models mentioned above. Furthermore, we provide compelling evidence that our new antibodies specifically detect endogenous human APP in immunocytochemistry, FACS and immunoprecipitation. Hence, we propose these antibodies as standard tool for monitoring expression of endogenous or transfected APP in human cells and APP expression in transgenic animals.
EVALuna2:24975

Differential upregulation of host cell protein kinases by the replication of α-, β- and γ-herpesviruses provides a signature of virus-specific signalling - Marschall, Manfred; Strojan, Hanife; Kiener, Richard; Wangen, Christina; Sonntag, Eric; Müller, Regina; Zeitträger, Isabel; Wagner, Sabrina; Stamminger, Thomas; Milbradt, Jens; Behrends, Uta; Körber, Nina; et al. (Journal of General Virology, 2020)
Infections with human herpesviruses share several molecular characteristics, but the diversified medical outcomes are distinct to viral subfamilies and species. Notably, both clinical and molecular correlates of infection are a challenging field and distinct patterns of virus-host interaction have rarely been defined; this study therefore focuses on the search for virus-specific molecular indicators. As previous studies have demonstrated the impact of herpesvirus infections on changes in host signalling pathways, we illustrate virus-modulated expression levels of individual cellular protein kinases. Current data reveal (i) α-, β- and γ-herpesvirus-specific patterns of kinase modulation as well as (ii) differential levels of up-/downregulated kinase expression and phosphorylation, which collectively suggest (iii) defined signalling patterns specific for the various viruses (VSS) that may prove useful for defining molecular indicators. Combined, the study confirms the correlation between herpesviral replication and modulation of signalling kinases, possibly exploitable for the in vitro characterization of viral infections.
CRIS-Team Scopus Importer:2020-04-10
Keywords: differential upregulation of cellular kinases; herpesviral replication; modulation of the host kinome; primary human fibroblasts; signature of virus-specific signalling

Dipeptidylpeptidase 4 as a Marker of Activated Fibroblasts and a Potential Target for the Treatment of Fibrosis in Systemic Sclerosis - Soare, Alina; Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Dees, Clara; Rauber, Simon; Wohlfahrt, Thomas; Chen, Chih Wei; Ludolph, Ingo; Horch, Raymund E.; Bäuerle, Tobias; von Hörsten, Stephan; Mihai, Carina; et al. (Arthritis and Rheumatology, 2020)
Objective: Expression of dipeptidylpeptidase 4 (DPP-4) identifies a dermal fibroblast lineage involved in scarring during wound healing. The role of DDP-4 in tissue fibrosis is, however, unknown. The aim of the present study was to evaluate DPP-4 as a potential target for the treatment of fibrosis in patients with systemic sclerosis (SSc). Methods: Expression of DPP-4 in skin biopsy samples and dermal fibroblasts was analyzed by real-time polymerase chain reaction, immunofluorescence, and Western blot analyses. The activity of DPP-4 was modulated by overexpression, knockdown, and pharmacologic inhibition of DPP4 using sitagliptin and vildagliptin. The effects of DPP4 inhibition were analyzed in human dermal fibroblasts and in different mouse models of SSc (each n = 6). Results: The expression of DPP-4 and the number of DPP-4–positive fibroblasts were increased in the fibrotic skin of SSc patients, in a transforming growth factor β (TGFβ)–dependent manner. DPP-4–positive fibroblasts expressed higher levels of myofibroblast markers and collagen (each P < 0.001 versus healthy controls). Overexpression of DPP4 promoted fibroblast activation, whereas pharmacologic inhibition or genetic inactivation of DPP4 reduced the proliferation, migration, and expression of contractile proteins and release of collagen (each P < 0.001 versus control mice) by interfering with TGFβ-induced ERK signaling. DPP4-knockout mice were less sensitive to bleomycin-induced dermal and pulmonary fibrosis (P < 0.0001 versus wild-type controls). Treatment with DPP4 inhibitors promoted regression of fibrosis in mice that had received bleomycin challenge and mice with chronic graft-versus-host disease, and ameliorated fibrosis in TSK1 mice (each P < 0.001 versus untreated controls). These antifibrotic effects were associated with a reduction in inflammation. Conclusion: DPP-4 characterizes a population of activated fibroblasts and shows that DPP-4 regulates TGFβ-induced fibroblast activation in the fibrotic skin of SSc patients. Inhibition of DPP4 exerts potent antifibrotic effects when administered in well-tolerated doses. As DPP4 inhibitors are already in clinical use for diabetes, these results may have direct translational implications for the treatment of fibrosis in patients with SSc.
CRIS-Team Scopus Importer:2020-01-10

Discovery of a Novel Antiviral Effect of the Restriction Factor SPOC1 against Human Cytomegalovirus - Kuderna, Anna K.; Reichel, Anna; Tillmanns, Julia; Class, Maja; Scherer, Myriam; Stamminger, Thomas (Viruses, 2024)
The chromatin-remodeler SPOC1 (PHF13) is a transcriptional co-regulator and has been identified as a restriction factor against various viruses, including human cytomegalovirus (HCMV). For HCMV, SPOC1 was shown to block the onset of immediate-early (IE) gene expression under low multiplicities of infection (MOI). Here, we demonstrate that SPOC1-mediated restriction of IE expression is neutralized by increasing viral titers. Interestingly, our study reveals that SPOC1 exerts an additional antiviral function beyond the IE phase of HCMV replication. Expression of SPOC1 under conditions of high MOI resulted in severely impaired viral DNA replication and viral particle release, which may be attributed to inefficient viral transcription. With the use of click chemistry, the localization of viral DNA was investigated at late time points after infection. Intriguingly, we detected a co-localization of SPOC1, RNA polymerase II S5P and polycomb repressor complex 2 (PRC2) components in close proximity to viral DNA in areas that are hypothesized to harbor viral transcription sites. We further identified the N-terminal domain of SPOC1 to be responsible for interaction with EZH2, a subunit of the PRC2 complex. With this study, we report a novel and potent antiviral function of SPOC1 against HCMV that is efficient even with unrestricted IE gene expression.
CRIS-Team Scopus Importer:2024-04-05
Keywords: antiviral; chromatin remodeler; dual role; human cytomegalovirus; restriction factor; RNA Pol II; viral transcription

Disrupted-in-Schizophrenia 1 (DISC1) Overexpression and Juvenile Immune Activation Cause Sex-Specific Schizophrenia-Related Psychopathology in Rats - Uzuneser, Taygun; Speidel, Jil; Kogias, Georgios; Wang, An-Li; Silva, Maria A. De Souza; Huston, Joseph P.; Zoicas, Iulia; von Hörsten, Stephan; Kornhuber, Johannes; Korth, Carsten; Müller, Christian P. (Frontiers in Psychiatry, 2019)
Synaptic pruning is a critical refinement step during neurodevelopment, and schizophrenia has been associated with overpruning of cortical dendritic spines. Both human studies and animal models implicate disrupted-in-schizophrenia 1 (DISC1) gene as a strong susceptibility factor for schizophrenia. Accumulating evidence supports the involvement of DISC1 protein in the modulation of synaptic elimination during critical periods of neurodevelopment and of dopamine D2-receptor-mediated signaling during adulthood. In many species, synaptic pruning occurs during juvenile and adolescent periods and is mediated by microglia, which can be over-activated by an immune challenge, giving rise to overpruning. Therefore, we sought to investigate possible interactions between a transgenic DISC1 model (tgDISC1) and juvenile immune activation (JIA) by the bacterial cell wall endotoxin lipopolysaccharide on the induction of schizophrenia-related behavioral and neurochemical disruptions in adult female and male rats. We examined possible behavioral aberrations along three major symptom dimensions of schizophrenia including psychosis, social and emotional disruptions, and cognitive impairments. We detected significant gene environment interactions in the amphetamine-induced locomotion in female animals and in the amphetamine-induced anxiety in male animals. Surprisingly, gene environment interactions improved social memory in both male and female animals. JIA alone disrupted spatial memory and recognition memory, but only in male animals. DISC1 overexpression alone induced an improvement in sensorimotor gating, but only in female animals. Our neurochemical analyses detected sex- and manipulation-dependent changes in the postmortem monoamine content of animals. Taken together, we here report sex-specific effects of environment and genotype as well as their interaction on behavioral phenotypes and neurochemical profiles relevant for schizophrenia.
CRIS-Team WoS Importer:2019-04-18

DNA extraction from clotted blood in genotyping quality - Stanzick, Kira J.; Simon, Josef; Zimmermann, Martina E.; Schachtner, Michael; Peterhoff, David; Niller, Hans-Helmut; Überla, Klaus; Wagner, Ralf; Heid, Iris M.; Stark, Klaus J. (Biotechniques, 2023)
DNA extraction from frozen blood clots is challenging. Here, the authors applied QIAGEN Clotspin Baskets and the Gentra Puregene Blood Kit for DNA extraction to cellular fraction of 5.5 ml whole blood without anticoagulating additives. The amount and quality of extracted DNA were assessed via spectrophotometer and gel electrophoresis. Results from array-based genotyping were analyzed. All steps were compared with DNA isolated from anticoagulated blood samples from a separate study. The quality and concentration of DNA extracted from clotted blood were comparable to those of DNA extracted from anticoagulated blood. DNA yield was on average 27 mu g per ml clotted blood, with an average purity of 1.87 (A260/A280). Genotyping quality was similar for both DNA sources (call rate: 99.56% from clotted vs 99.49% from anticoagulated blood).
CRIS-Team WoS Importer:2023-01-20

DNA methylation and transcription in HERV (K, W, E) and LINE sequences remain unchanged upon foreign DNA insertions - Weber, Stefanie; Jung, Susan; Doerfler, Walter (Epigenomics, 2016)
DNA methylation and transcriptional profiles were determined in the regulatory sequences of the human endogenous retroviral (HERV-K, -W, -E) and LINE-1.2 elements and were compared between non-transgenomic and plasmid-transgenomic cells.DNA methylation profiles in the HERV (K, W, E) and LINE sequences were determined by bisulfite genomic sequencing. The transcription of these genome segments was assessed by quantitative real-time PCR.In HERV-K, HERV-W and LINE-1.2 the levels of DNA methylation ranged between 75 and 98%, while in HERV-E they were around 60%. Nevertheless, the HERV and LINE-1.2 sequences were actively transcribed. No differences were found in comparisons of HERV and LINE-1.2 CpG methylation and transcription patterns between non-transgenomic and plasmid-transgenomic HCT116 cells.The insertion of a 5.6 kbp plasmid into the HCT116 genome had no effect on the HERV and LINE-1.2 methylation and transcription profiles, although other parts of the HCT116 genome had shown marked changes. These repetitive sequences are transcribed, probably because the large number of HERV and LINE-1.2 elements harbor copies with non- or hypo-methylated long terminal repeat sequences.
EVALuna2:8330

DNA vaccines encoding DEC205-targeted antigens: immunity or tolerance? - Niezold, Thomas; Bonsmann, Michael Storcksdieck Genannt; Maaske, Andre; Temchura, Vladimir; Heinecke, Vanessa; Hannaman, Drew; Buer, Jan; Ehrhardt, Christina; Hansen, Wiebke; Überla, Klaus; Tenbusch, Matthias (Immunology, 2015)
Targeting of antigens to the endocytic uptake receptor DEC205 resulted in enhanced antigen presentation by dendritic cells (DCs). In combination with adjuvants for DC maturation, proteins coupled to an antibody against DEC205 induced strong pathogen-specific immune responses, whereas without additional adjuvant tolerance could be induced. As less is known about DNA vaccines encoding DEC205-targeted antigens, we explored the immunogenicity and efficacy of a dendritic cell-targeted DNA vaccine against influenza A virus (IAV) delivered by electroporation. Although coupling of haemagglutinin to a single-chain antibody against DEC205 enhanced antigen presentation on MHC class II and activation of T-cell receptor-transgenic CD4 T cells, the T-cell responses induced by the targeted DNA vaccine in wild-type BALB/c mice were significantly reduced compared with DNA encoding non-targeted antigens. Consistently, these mice were less protected against an IAV infection. Adoptive transfer experiments were performed to assess the fate of the antigen-specific T cells in animals vaccinated with DNA encoding DEC205-targeted antigens. By this, we could exclude the general deletion of antigen-specific T cells as cause for the reduced efficacy, but observed a local expansion of antigen-specific regulatory T cells, which could suppress the activation of effector cells. In conclusion, DNA vaccines encoding DEC205-targeted antigens induce peripheral tolerance rather than immunity in our study. Finally, we evaluated our DNA vaccines as prophylactic or therapeutic treatment in an allergen-induced asthma mouse model.
EVALuna2:8290

DPP4-deficient congenic rats display blunted stress, improved fear extinction and increased central NPY - Canneva, Fabio; Golub, Yulia; Distler, Jörg; Dobner, Julia; Meyer, Sarah Katharina; von Hörsten, Stephan (Psychoneuroendocrinology, 2015)
Inhibitors of dipeptidyl peptidase 4 (DPP4, CD26) are used for the treatment of type 2 diabetic patients and better glucose tolerance has been confirmed in functionally DPP4-deficient congenic rats (DPP4mut), along with immunological alterations and, interestingly, a stress-resilient phenotype. All these findings are in agreement with the "moonlighting" properties of DPP4, whose proteolytic action is responsible for the inactivation of a number of regulatory peptides including, but not limited to, neuropeptide Y (NPY). Among all candidate substrates, DPP4 displays highest affinity for NPY, an endogenous anxiolytic neurotransmitter that is suggested as a candidate biomarker in post-traumatic stress disorder (PTSD) and depression.Central and peripheral NPY levels were measured by ELISA in DPP4mut and DAwt rats revealing a significantly higher concentration of the peptide in the CSF of DPP4mut animals. This finding positively correlated with the blunted stress phenotype measured on an analgesia-meter. Additionally, when a classical fear-conditioning paradigm was investigated, short-term fear extinction was significantly potentiated in DPP4mut rats as compared to wt controls.Our findings indicate a positive correlation between reduced stress-responsiveness and increased central NPY, in DPP4mut rats. Most interestingly, the behavioral phenotype extends to facilitation of fear extinction. These observations raise further interest in DPP4-modulating drugs for the potential effect on NPY metabolism, as a therapeutic tool for psychiatric conditions such as anxiety disorders and PTSD.
EVALuna2:13098

DPP4 inhibitors increase differentially the expression of surfactant proteins in Fischer 344 rats - Schmiedl, A.; Gruetzner, D.; Hoffmann, T.; von Hörsten, Stephan; Stephan, M. (Acta Physiologica, 2014)
Intact surface active agent (surfactant) composed of surfactant-associated proteins (SPs) and lipids is necessary for respiration and prevents alveoli from collapsing. CD26, a transmembrane glycoprotein exerting dipeptidyl peptidase activity (DPP4), highly expressed in lung parenchyma, is involved in inflammatory processes. A pharmacological inhibition of DPP4 influenced not only the inflammation but also elevated the SPs. Thus, DPP4 inhibitors may be a novel drug for treatment of diseases with surfactant deficiency. Therefore, we tested firstly the hypothesis that DPP4 inhibitors increase the expression of SPs in healthy rats.SP mRNA and protein expression were determined different times after nebulization of aerosolized DPP4 inhibitors [L-isoleucine-thiazolidide (L-Ile-Thia), L-valine-pyrrolidide (L-Val-Pyrr)], budesonide, saline or stereoisomers.Compared with negative controls (1) L-Ile-Thia as well as budesonide led to a significant higher and L-Val-Pyrr had the tendency to a significant higher expression of SP-A mRNA 6 h after nebulization, (2) the expression of SP-D mRNA increased significantly 6 h after nebulization with L-Ile-Thia and 3 and 6 h after nebulization with Val-pyrr, (3) SP-B mRNA levels showed significantly higher values 3 and 6 h after nebulization with L-Val-Pyrr, (4) protein levels of SP-A, SP-B and SP-C were elevated significantly 6 h after nebulization with L-Val-Pyrr as well as with budesonide, and (5) phospholipids were also increased in response to DPP4 inhibition; the minimal surface tension was comparable.DPP4 inhibition influence differently the expression of surfactant proteins in healthy rats and may be suitable to elevate surfactant synthesis in different diseases accompanied with surfactant deficiencies.
EVALuna2:24972

Dual signaling via interferon and DNA damage response elicits entrapment by giant PML nuclear bodies - Scherer, Myriam; Read, Clarissa; Neusser, Gregor; Kranz, Christine; Kuderna, Anna K.; Müller, Regina; Full, Florian; Wörz, Sonja; Reichel, Anna; Schilling, Eva Maria; Walther, Paul; Stamminger, Thomas (eLife, 2022)
PML nuclear bodies (PML-NBs) are dynamic interchromosomal macromolecular complexes implicated in epigenetic regulation as well as antiviral defense. During herpesvirus infec-tion, PML-NBs induce epigenetic silencing of viral genomes, however, this defense is antagonized by viral regulatory proteins such as IE1 of human cytomegalovirus (HCMV). Here, we show that PML-NBs undergo a drastic rearrangement into highly enlarged PML cages upon infection with IE1-deficient HCMV. Importantly, our results demonstrate that dual signaling by interferon and DNA damage response is required to elicit giant PML-NBs. DNA labeling revealed that invading HCMV genomes are entrapped inside PML-NBs and remain stably associated with PML cages in a transcrip-tionally repressed state. Intriguingly, by correlative light and transmission electron microscopy (EM), we observed that PML cages also entrap newly assembled viral capsids demonstrating a second defense layer in cells with incomplete first-line response. Further characterization by 3D EM showed that hundreds of viral capsids are tightly packed into several layers of fibrous PML. Overall, our data indicate that giant PML-NBs arise via combined interferon and DNA damage signaling which trig-gers entrapment of both nucleic acids and proteinaceous components. This represents a multilay-ered defense strategy to act in a cytoprotective manner and to combat viral infections.
CRIS-Team Scopus Importer:2022-04-15

Dual T cell- and B cell-intrinsic deficiency in humans with biallelic RLTPR mutations - Wang, Yi; Ma, Cindy S.; Ling, Yun; Bousfiha, Aziz; Camcioglu, Yildiz; Jacquot, Serge; Payne, Kathryn; Crestani, Elena; Roncagalli, Romain; Belkadi, Aziz; Kerner, Gaspard; Lorenzo, Lazaro; et al. (Journal of Experimental Medicine, 2016)
Combined immunodeficiency (CID) refers to inborn errors of human T cells that also affect B cells because of the T cell deficit or an additional B cell-intrinsic deficit. In this study, we report six patients from three unrelated families with biallelic loss-of-function mutations in RLTPR, the mouse orthologue of which is essential for CD28 signaling. The patients have cutaneous and pulmonary allergy, as well as a variety of bacterial and fungal infectious diseases, including invasive tuberculosis and mucocutaneous candidiasis. Proportions of circulating regulatory T cells and memory CD4(+) T cells are reduced. Their CD4(+) T cells do not respond to CD28 stimulation. Their CD4(+) T cells exhibit a "Th2" cell bias ex vivo and when cultured in vitro, contrasting with the paucity of "Th1," "Th17," and T follicular helper cells. The patients also display few memory B cells and poor antibody responses. This B cell phenotype does not result solely from the T cell deficiency, as the patients' B cells fail to activate NF-?B upon B cell receptor (BCR) stimulation. Human RLTPR deficiency is a CID affecting at least the CD28-responsive pathway in T cells and the BCR-responsive pathway in B cells.
EVALuna2:8338

Dynamic Angiography and Perfusion Imaging Using Flat Detector CT in the Angiography Suite: A Pilot Study in Patients with Acute Middle Cerebral Artery Occlusions - Struffert, Tobias; Deuerling-Zheng, Y.; Kloska, Stephan; Engelhorn, Tobias; Lang, Sabine; Mennecke, Angelika; Manhart, M.; Strother, C. M.; Schwab, Sibylle; Dörfler, Arnd (American Journal of Neuroradiology, 2015)
Perfusion and angiographic imaging using intravenous contrast application to evaluate stroke patients is now technically feasible by flat detector CT performed by the angiographic system. The aim of this pilot study was to show the feasibility and qualitative comparability of a novel flat detector CT dynamic perfusion and angiographic imaging protocol in comparison with a multimodal stroke MR imaging protocol.In 12 patients with acute stroke, MR imaging and the novel flat detector CT protocol were performed before endovascular treatment. Perfusion parameter maps (MTT, TTP, CBV, CBF) and MIP/volume-rendering technique images obtained by using both modalities (MR imaging and flat detector CT) were compared.Comparison of MIP/volume-rendering technique images demonstrated equivalent visibility of the occlusion site. Qualitative comparison of perfusion parameter maps by using ASPECTS revealed high Pearson correlation coefficients for parameters CBF, MTT, and TTP (0.95-0.98), while for CBV, the coefficient was lower (0.49).We have shown the feasibility of a novel dynamic flat detector CT perfusion and angiographic protocol for the diagnosis and triage of patients with acute ischemic stroke. In a qualitative comparison, the parameter maps and MIP/volume-rendering technique images compared well with MR imaging. In our opinion, this flat detector CT application may substitute for multisection CT imaging in selected patients with acute stroke so that in the future, patients with acute stroke may be directly referred to the angiography suite, thereby avoiding transportation and saving time.
EVALuna2:22353

Dynamic footprint based locomotion sway assessment in α-synucleinopathic mice using Fast Fourier Transform and Low Pass Filter - Timotius, Ivanna; Canneva, Fabio; Minakaki, Georgia; Pasluosta, Cristian Federico; Moceri, Sandra; Casadei, Nicolas; Riess, Olaf; Winkler, Jürgen; Klucken, Jochen; von Hörsten, Stephan; Eskofier, Björn (Journal of Neuroscience Methods, 2018)
Background Sway is a crucial gait characteristic tightly correlated with the risk of falling in patients with Parkinson´s disease (PD). So far, the swaying pattern during locomotion has not been investigated in rodent models using the analysis of dynamic footprint recording obtained from the CatWalk gait recording and analysis system. New Methods We present three methods for describing locomotion sway and apply them to footprint recordings taken from C57BL6/N wild-type mice and two different α-synuclein transgenic PD-relevant mouse models (α-synm-ko, α-synm-koxα-synh-tg). Individual locomotion data were subjected to three different signal processing analytical approaches: the first two methods are based on Fast Fourier Transform (FFT), while the third method uses Low Pass Filters (LPF). These methods use the information associated with the locomotion sway and generate sway-related parameters. Results The three proposed methods were successfully applied to the footprint recordings taken from all paws as well as from front/hind-paws separately. Nine resulting sway-related parameters were generated and successfully applied to differentiate between the mouse models under study. Namely, α-synucleinopathic mice revealed higher sway and sway itself was significantly higher in the α-synm-koxα-synh-tg mice compared to their wild-type littermates in eight of the nine sway-related parameters. Comparison with Existing Method Previous locomotion sway index computation is based on the estimated center of mass position of mice. Conclusions The methods presented in this study provide a sway-related gait characterization. Their application is straightforward and may lead to the identification of gait pattern derived biomarkers in rodent models of P
EVALuna2:32788
Keywords: Locomotion; sway; gait analysis; CatWalk system; Parkinson's disease; alpha-synuclein transgenic

Dynamic footprints of α-synucleinopathic mice recorded by CatWalk gait analysis - Timotius, Ivanna; Canneva, Fabio; Minakaki, Georgia; Pasluosta, Cristian Federico; Moceri, Sandra; Casadei, Nicolas; Riess, Olaf; Winkler, Jürgen; Klucken, Jochen; von Hörsten, Stephan; Eskofier, Björn (Data in Brief, 2018)
Characterizing gait is important in the study of movement disorders, also in clinical mouse models. Gait data are therefore necessary for the development of gait analysis methods and the study of diseases. This article presents gait data of two α-synucleinopathic transgenic mouse models and their non-transgenic littermate, backcrossed into the C57BL/6N genetic background. The animal gait was recorded using CatWalk system, which provides the information for each run about the paw positions, paw print sizes, and paw intensities as a function of time or video frame. A total of 90 run data files are provided in this article.
Keywords: Data; gait analysis; CatWalk system; Parkinson's disease; alpha-synuclein transgenic.

Dynamic regulatory interaction between cytomegalovirus major tegument protein pp65 and protein kinase pUL97 in intracellular compartments, dense bodies and virions - König, Patrick; Buescher, Nicoie; Steingruber, Mirjam; Socher, Eileen; Sticht, Heinrich; Tenzer, Stefan; Plachter, Bodo; Marschall, Manfred (Journal of General Virology, 2017)
Human cytomegalovirus (HCMV) is a ubiquitous pathogen of considerable clinical importance. Understanding the processes that are important for viral replication is essential for the development of therapeutic strategies against HCMV infection. The HCMV-encoded protein kinase pUL97 is an important multifunctional regulator of viral replication. Several viral and cellular proteins are phosphorylated by pUL97. The phosphoprotein pp65 is one important substrate of pUL97. It is the most abundant tegument protein of HCMV virions, mediating the upload of other virion constituents and contributing to particle integrity. Further to that, it interferes with host innate immune defences, thereby enabling efficient viral replication. By applying different approaches, we characterized the pp65-pUL97 interaction in various compartments. Specifically, the pUL97 interaction domain of pp65 was defined (282-415). A putative cyclin bridge that enhances pUL97-pp65 interaction was identified. The impact of pUL97 mutation on virion and dense body morphogenesis was addressed using pUL97 mutant viruses. Alterations in the proteome of viral particles were seen, especially with mutant viruses expressing cytoplasmic variants of pUL97. On the basis of these data we postulate a so far poorly recognized functional relationship between pp65 and pUL97, and present a refined model of pp65-pUL97 interaction.
EVALuna2:33718

Dynamics of humoral and cellular immune responses after homologous and heterologous SARS-CoV-2 vaccination with ChAdOx1 nCoV-19 and BNT162b2 - Vogel, Emanuel; Kocher, Katharina; Priller, Alina; Cheng, Cho Chin; Steininger, Philipp; Liao, Bo Hung; Körber, Nina; Willmann, Annika; Irrgang, Pascal; Held, Jürgen; Moosmann, Carolin; Schmidt, Viviane; et al. (EBioMedicine, 2022)
Background: Vaccines are an important means to overcome the SARS-CoV-2 pandemic. They induce specific antibody and T-cell responses but it remains open how well vaccine-induced immunity is preserved over time following homologous and heterologous immunization regimens. Here, we compared the dynamics of humoral and cellular immune responses up to 180 days after homologous or heterologous vaccination with either ChAdOx1-nCoV-19 (ChAd) or BNT162b2 (BNT) or both. Methods: Various tests were used to determine the humoral and cellular immune response. To quantify the antibody levels, we used the surrogate neutralization (sVNT) assay from YHLO, which we augmented with pseudo- and real virus neutralization tests (pVNT and rVNT). Antibody avidity was measured by a modified ELISA. To determine cellular reactivity, we used an IFN-γ Elispot, IFN-γ/IL Flurospot, and intracellular cytokine staining. Findings: Antibody responses significantly waned after vaccination, irrespective of the regimen. The capacity to neutralize SARS-CoV-2 – including variants of concern such as Delta or Omicron – was superior after heterologous compared to homologous BNT vaccination, both of which resulted in longer-lasting humoral immunity than homologous ChAd immunization. All vaccination regimens induced stable, polyfunctional T-cell responses. Interpretation: These findings demonstrate that heterologous vaccination with ChAd and BNT is a potent alternative to induce humoral and cellular immune protection in comparison to the homologous vaccination regimens. Funding: The study was funded by the German Centre for Infection Research (DZIF), the European Union's “Horizon 2020 Research and Innovation Programme" under grant agreement No. 101037867 (VACCELERATE), the “Bayerisches Staatsministerium für Wissenschaft und Kunst” for the CoVaKo-2021 and the For-COVID projects and the Helmholtz Association via the collaborative research program “CoViPa”. Further support was obtained from the Federal Ministry of Education and Science (BMBF) through the “Netzwerk Universitätsmedizin”, project “B-Fast” and “Cov-Immune”. KS is supported by the German Federal Ministry of Education and Research (BMBF, 01KI2013) and the Else Kröner-Stiftung (2020_EKEA.127).
CRIS-Team Scopus Importer:2022-10-21
Keywords: antibody avidity; BNT162b2; ChAdOx1-nCoV-19; COVID-19; Heterologous vaccination; long-term; maintenance; SARS-CoV-2; T cell immunity; vaccine

E2F/Rb Family Proteins Mediate Interferon Induced Repression of Adenovirus Immediate Early Transcription to Promote Persistent Viral Infection - Zheng, Yueting; Stamminger, Thomas; Hearing, Patrick (PLoS Pathogens, 2016)
Interferons (IFNs) are cytokines that have pleiotropic effects and play important roles in innate and adaptive immunity. IFNs have broad antiviral properties and function by different mechanisms. IFNs fail to inhibit wild-type Adenovirus (Ad) replication in established cancer cell lines. In this study, we analyzed the effects of IFNs on Ad replication in normal human cells. Our data demonstrate that both IFN? and IFN? blocked wild-type Ad5 replication in primary human bronchial epithelial cells (NHBEC) and TERT-immortalized normal human diploid fibroblasts (HDF-TERT). IFNs inhibited the replication of divergent adenoviruses. The inhibition of Ad5 replication by IFN? and IFN? is the consequence of repression of transcription of the E1A immediate early gene product. Both IFN? and IFN? impede the association of the transactivator GABP with the E1A enhancer region during the early phase of infection. The repression of E1A expression by IFNs requires a conserved E2F binding site in the E1A enhancer, and IFNs increased the enrichment of the E2F-associated pocket proteins, Rb and p107, at the E1A enhancer in vivo. PD0332991 (Pabociclib), a specific CDK4/6 inhibitor, dephosphoryles pocket proteins to promote their interaction with E2Fs and inhibited wild-type Ad5 replication dependent on the conserved E2F binding site. Consistent with this result, expression of the small E1A oncoprotein, which abrogates E2F/pocket protein interactions, rescued Ad replication in the presence of IFN? or IFN?. Finally, we established a persistent Ad infection model in vitro and demonstrated that IFN? suppresses productive Ad replication in a manner dependent on the E2F binding site in the E1A enhancer. This is the first study that probes the molecular basis of persistent adenovirus infection and reveals a novel mechanism by which adenoviruses utilize IFN signaling to suppress lytic virus replication and to promote persistent infection.
EVALuna2:8310

Early Alterations in Operant Performance and Prominent Huntingtin Aggregation in a Congenic F344 Rat Line of the Classical CAGn51truncModel of Huntington Disease - Plank, Anne-Christine; Canneva, Fabio; Raber, Kerstin A.; Urbach, Yvonne K.; Dobner, Julia; Puchades, Maja; Bjaalie, Jan G.; Gillmann, Clarissa; Bäuerle, Tobias; Riess, Olaf; Nguyen, Hoa H. P.; von Hörsten, Stephan (Frontiers in Neuroscience, 2018)
The transgenic rat model of Huntington disease expressing a fragment of mutant HTT (tgHD rat) has been thoroughly characterized and reproduces hallmark symptoms of human adult-onset HD. Pursuing the optimization of this model for evaluation of translational therapeutic approaches, the F344 inbred rat strain was considered as advantageous genetic background for the expression of the HD transgenic construct. In the present study, a novel congenic line of the SPRDtgHD transgenic model of HD, carrying 51 CAG repeats, was generated on the F344 rat genetic background. To assess the behavioral phenotype, classical assays investigating motor function, emotion, and sensorimotor gating were applied, along with automated screening of metabolic and activity parameters as well as operant conditioning tasks. The neuropathological phenotype was analyzed by immunohistochemistry andex vivomagnetic resonance imaging. F344tgHD rats displayed markedly reduced anxiety-like behavior in the social interaction test and elevated impulsivity traits already at 3 months of age. Neuropathologically, reduced striatal volume and pronounced aggregation of mutant huntingtin in several brain regions were detected at later disease stage. In conclusion, the congenic F344tgHD model reproduces key aspects of the human HD phenotype, substantiating its value for translational therapeutic approaches.
EVALuna2:32797

Early Mortality of Brain Cancer Patients and its Connection to Cytomegalovirus Reactivation During Radiochemotherapy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Rühle, Paul-Friedrich; Putz, Florian; Semrau, Sabine; et al. (Clinical Cancer Research, 2020)
PURPOSE: If routine diagnostics are inconclusive, neurologic deterioration and death of patients with brain cancer are attributed to tumor or therapy. Therefore, diagnosing symptoms of encephalopathy caused by human cytomegalovirus (HCMV) reactivation remains uncommon. We investigated the role of HCMV reactivation in neurologic decline and clinical outcome after the start of radiochemotherapy. EXPERIMENTAL DESIGN: HCMV analyses and extended MRI studies including additional independent retrospective neuroradiologic evaluation were performed at predetermined intervals and in case of sudden neurologic decline for 118 adult patients: 63 histologically proven high-grade gliomas, 55 with brain metastases. Immunophenotyping from simultaneously taken whole-blood samples was carried out to detect immune cells serving as prognostic marker for HCMV-associated complications. Symptomatic viremia and overall survival (OS) were the endpoints. RESULTS: Twenty-four percent (28/118) of all patients (12/44 glioblastoma, 3/13 anaplastic astrocytoma; 8/31 non-small cell lung cancer (NSCLC), 13/24 other brain metastases) developed HCMV-viremia during or within 4 weeks after radiotherapy; 21 of 28 patients experienced concurrent major neurologic decline, reversible by antiviral treatment. Identified by immunophenotyping, pretherapeutically low basophil counts predicted a high-risk for HCMV-associated encephalopathy (glioblastoma: P = 0.002, NSCLC: P = 0.02). Median OS was substantially reduced after HCMV-associated encephalopathy without MRI signs of tumor progression [glioblastoma: 99 vs. 570 days (calculated 1-year OS: 22% vs. 69%; P = 0.01) and NSCLC: 47 vs. 219 days (calculated 1-year OS: 0% vs. 32%; P = 0.02)]. CONCLUSIONS: For patients with brain cancer, HCMV reactivation after the start of radiochemotherapy is a frequent risk for cognitively detrimental but treatable encephalopathy and premature death. Routinely performed HCMV diagnostics, assessing basophil counts and study-based anti-viral regimens, are necessary to combat this hidden threat.See related commentary by Lawler et al., p. 3077.
CRIS-Team Scopus Importer:2020-07-17

Early Nuclear Events after Herpesviral Infection - Full, Florian; Enßer, Armin (Journal of Clinical Medicine, 2019)
Herpesviruses are important pathogens that can cause significant morbidity and mortality in the human population. Herpesviruses have a double-stranded DNA genome, and viral genome replication takes place inside the nucleus. Upon entering the nucleus, herpesviruses have to overcome the obstacle of cellular proteins in order to enable viral gene expression and genome replication. In this review, we want to highlight cellular proteins that sense incoming viral genomes of the DNA-damage repair (DDR) pathway and of PML-nuclear bodies (PML-NBs) that all can act as antiviral restriction factors within the first hours after the viral genome is released into the nucleus. We show the function and significance of both nuclear DNA sensors, the DDR and PML-NBs, and demonstrate for three human herpesviruses of the alpha-, beta- and gamma-subfamilies, HSV-1, HCMV and KSHV respectively, how viral tegument proteins antagonize these pathways.
CRIS-Team WoS Importer:2019-10-25

Early postnatal behavioral, cellular, and molecular changes in models of Huntington disease are reversible by HDAC inhibition - Siebzehnrubl, Florian A.; Reber, Kerstin A.; Urbach, Yvonne K.; Schulze-Krebs, Anja; Canneva, Fabio; Moceri, Sandra; Habermeyer, Johanna; Achoui, Dalila; Gupta, Bhavana; Steindler, Dennis A.; Stephan, Michael; Huu Phuc Nguyen,; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Huntington disease (HD) is an autosomal dominant neurodegenerative disorder caused by expanded CAG repeats in the huntingtin gene (HTT). Although mutant HTT is expressed during embryonic development and throughout life, clinical HD usually manifests later in adulthood. A number of studies document neurodevelopmental changes associated with mutant HTT, but whether these are reversible under therapy remains unclear. Here, we identify very early behavioral, molecular, and cellular changes in preweaning transgenic HD rats and mice. Reduced ultrasonic vocalization, loss of prepulse inhibition, and increased risk taking are accompanied by disturbances of dopaminergic regulation in vivo, reduced neuronal differentiation capacity in subventricular zone stem/progenitor cells, and impaired neuronal and oligodendrocyte differentiation of mouse embryo-derived neural stem cells in vitro. Interventional treatment of this early phenotype with the histone deacetylase inhibitor (HDACi) LBH589 led to significant improvement in behavioral changes and markers of dopaminergic neurotransmission and complete reversal of aberrant neuronal differentiation in vitro and in vivo. Our data support the notion that neurodevelopmental changes contribute to the prodromal phase of HD and that early, presymptomatic intervention using HDACi may represent a promising novel treatment approach for HD.
EVALuna2:36091

Editorial: Strategies to Defeat HIV - Serra-Moreno, Ruth; Gramberg, Thomas (Current HIV Research, 2016)
EVALuna2:8303

Effect of mucosal adjuvant IL-1β on heterotypic immunity in a pig influenza model - Schmidt, Anna; Paudyal, Basudev; Villanueva-Hernández, Sonia; Mcnee, Adam; Vatzia, Eleni; Carr, Brigid Veronica; Schmidt, Selma; Mccarron, Amy; Martini, Veronica; Schroedel, Silke; Thirion, Christian; Waters, Ryan; et al. (Frontiers in Immunology, 2023)
T cell responses directed against highly conserved viral proteins contribute to the clearance of the influenza virus and confer broadly cross-reactive and protective immune responses against a range of influenza viruses in mice and ferrets. We examined the protective efficacy of mucosal delivery of adenoviral vectors expressing hemagglutinin (HA) and nucleoprotein (NP) from the H1N1 virus against heterologous H3N2 challenge in pigs. We also evaluated the effect of mucosal co-delivery of IL-1β, which significantly increased antibody and T cell responses in inbred Babraham pigs. Another group of outbred pigs was first exposed to pH1N1 as an alternative means of inducing heterosubtypic immunity and were subsequently challenged with H3N2. Although both prior infection and adenoviral vector immunization induced strong T-cell responses against the conserved NP protein, none of the treatment groups demonstrated increased protection against the heterologous H3N2 challenge. Ad-HA/NP+Ad-IL-1β immunization increased lung pathology, although viral load was unchanged. These data indicate that heterotypic immunity may be difficult to achieve in pigs and the immunological mechanisms may differ from those in small animal models. Caution should be applied in extrapolating from a single model to humans.
CRIS-Team Scopus Importer:2023-05-19
Keywords: heterotypic protection; IL-1β; influenza virus; lung-resident memory T-cells; mucosal immunity; pig; porcine B cells; porcine T-cells

Effects of In utero environment and maternal behavior on neuroendocrine and behavioral alterations in a mouse model of prenatal trauma - Golub, Yulia; Canneva, F.; Funke, R.; Frey, Silke; Distler, Jörg; von Hörsten, Stephan; Freitag, C. M.; Kratz, Oliver; Moll, Gunther; Solati, Jalal (Developmental Neurobiology, 2016)
Maternal posttraumatic stress disorder (PTSD) following trauma exposure during pregnancy is associated with an increased risk of affective disorders in children. To investigate the mechanisms by which prenatal trauma and/or maternal PTSD affect brain development and behavior we established a mouse model of prenatal traumatic (PT) experience based on the application of an electric foot shock to C57Bl/6N female mice on the gestational day 12 during their pregnancy. The model is based on a previously validated animal model of PTSD. We found high anxiety levels and poor maternal care along with reduced serum prolactin and increased corticosterone levels in dams following maternal trauma (MT). PT-pups were born smaller and stayed smaller throughout their life. We show increased time and frequency of ultrasonic calls in PT-pups when separated from the mothers on the postnatal day (PND) 9. Cross-fostering experiments reveal lower anxiety levels in PT pups raised by healthy mothers as compared to trauma-naive pups raised by MT-dams. Importantly, the combination of prenatal trauma and being raised by a traumatized mother leads to: (1) the highest corticosterone levels in pups, (2) longest USV-call time and (3) highest anxiety levels in comparison to other experimental groups. Our data indicates a distinct change in maternal care following MT which is possibly associated with trauma-induced decrease in prolactin levels. Furthermore, we show that maternal behavior is crucial for the development of the offspring anxiety and specific aspects in maternal care overwrite to a significant extend the effects of in utero and postnatal environment. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 76: 1254-1265, 2016.
EVALuna2:13269

Efficient generation of human natural killer cell lines by viral transformation - Vogel, Benjamin; Tennert, K.; Full, F.; Enßer, Armin (Leukemia, 2014)
EVALuna2:8207

Electrostatically driven encapsulation of hydrophilic, non-conformational peptide epitopes into liposomes - Suleiman, Ehsan; Damm, Dominik; Batzoni, Mirjam; Temchura, Vladimir; Wagner, Andreas; Überla, Klaus; Vorauer-Uhl, Karola (Pharmaceutics, 2019)
Since the first use of liposomes as carriers for antigens, much work has been done to elucidate the mechanisms involved in the encapsulation of vaccine-relevant biomolecules. However, only a few studies have specifically investigated the encapsulation of hydrophilic, non-conformational peptide epitopes. We performed comprehensive and systematic screening studies, in order to identify conditions that favor the electrostatic interaction of such peptides with lipid membranes. Moreover, we have explored bi-terminal sequence extension as an approach to modify the isoelectric point of peptides, in order to modulate their membrane binding behavior and eventually shift/expand the working range under which they can be efficiently encapsulated in an electrostatically driven manner. The findings of our membrane interaction studies were then applied to preparing peptide-loaded liposomes. Our results show that the magnitude of membrane binding observed in our exploratory in situ setup translates to corresponding levels of encapsulation efficiency in both of the two most commonly employed methods for the preparation of liposomes, i.e., thin-film hydration and microfluidic mixing. We believe that the methods and findings described in the present studies will be of use to a wide audience and can be applied to address the ongoing relevant issue of the efficient encapsulation of hydrophilic biomolecules.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Electrostatic interactions; Encapsulation; Encapsulation efficiency; Hydrophilic peptides; In situ binding; Liposomes; Microfluidics; Peptide-membrane interaction; Peptides; Vaccines

Elevated cyclic AMP levels in T lymphocytes transformed by human T-cell lymphotropic virus type 1 - Kreß, Andrea; Schneider, Grit; Pichler, Klemens; Kalmer, Martina; Fleckenstein, Bernhard; Grassmann, Ralph (Journal of Virology, 2010)
Human T-cell lymphotropic virus type 1 (HTLV-1), the cause of adult T-cell leukemia/lymphoma (ATLL), transforms CD4+ T cells to permanent growth through its transactivator Tax. HTLV-1-transformed cells share phenotypic properties with memory and regulatory T cells (T-reg). Murine T-reg-mediated suppression employs elevated cyclic AMP (cAMP) levels as a key regulator. This led us to determine cAMP levels in HTLV-1-transformed cells. We found elevated cAMP concentrations as a consistent feature of all HTLV-1-transformed cell lines, including in vitro-HTLV-1-transformed, Tax-transformed, and patient-derived cells. In transformed cells with conditional Tax expression, high cAMP levels coincided with the presence of Tax but were lost without it. However, transient ectopic expression of Tax alone was not sufficient to induce cAMP. We found specific downregulation of the cAMP-degrading phosphodiesterase 3B (PDE3B) in HTLV-1-transformed cells, which was independent of Tax in transient expression experiments. This is in line with the notion that PDE3B transcripts and cAMP levels are inversely correlated. Overexpression of PDE3B led to a decrease of cAMP in HTLV-1-transformed cells. Decreased expression of PDE3B was associated with inhibitory histone modifications at the PDE3B promoter and the PDE3B locus. In summary, Tax transformation and its continuous expression contribute to elevated cAMP levels, which may be regulated through PDE3B suppression. This shows that HTLV-1-transformed cells assume biological features of long-lived T-cell populations that potentially contribute to viral persistence. Copyright © 2010, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

Emerging Role of PML Nuclear Bodies in Innate Immune Signaling - Scherer, Myriam; Stamminger, Thomas (Journal of Virology, 2016)
Research in the last 2 decades has demonstrated that a specific organelle of the cell nucleus, termed PML nuclear body (PML-NB) or nuclear domain 10 (ND10), is frequently modified during viral infection. This correlates with antagonization of a direct repressive function of individual PML-NB components, such as the PML, hDaxx, Sp100, or ATRX protein, that are able to act as cellular restriction factors. Recent studies now reveal an emerging role of PML-NBs as coregulatory structures of both type I and type II interferon responses. This emphasizes that targeting of PML-NBs by viral regulatory proteins has evolved as a strategy to compromise intrinsic antiviral defense and innate immune responses.
EVALuna2:8322

Emerging roles of cytomegalovirus-encoded G protein-coupled receptors during lytic and latent infection - Frank, Theresa; Niemann, Ina; Reichel, Anna; Stamminger, Thomas (Medical Microbiology and Immunology, 2019)
Cytomegaloviruses (CMVs) have developed multiple diverse strategies to ensure their replicative success and to evade immune recognition. Given the fact that G protein-coupled receptors (GPCRs) are key regulators of numerous cellular processes and modify a variety of signaling pathways, it is not surprising that CMVs and other herpesviruses have hijacked mammalian GPCRs during their coevolution. Human cytomegalovirus (HCMV) encodes for four viral GPCR homologues (vGPCRs), termed US27, US28, UL33, and UL78. Although HCMV-encoded GPCRs were first described in 1990, the pivotal functions of these viral receptor proteins were detected only recently. Here, we summarize seminal knowledge on the functions of herpesviral vGPCRs with a focus on novel roles of cytomegalovirus-encoded vGPCRs for viral spread and the regulation of latency.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Cell signaling; Chemokine receptor; Cytomegalovirus; G protein-coupled receptor (GPCR); US28

Endogenous mouse huntingtin is highly abundant in cranial nerve nuclei, co-aggregates to Abeta plaques and is induced in reactive astrocytes in a transgenic mouse model of Alzheimer's disease - Hartlage-Ruebsamen, Maike; Ratz, Veronika; Zeitschel, Ulrike; Finzel, Lukas; Machner, Lisa; Koeppen, Janett; Schulze, Anja; Demuth, Hans-Ulrich; von Hörsten, Stephan; Hoefling, Corinna; Rossner, Steffen (Acta Neuropathologica Communications, 2019)
Pathogenic variants of the huntingtin (HTT) protein and their aggregation have been investigated in great detail in brains of Huntington's disease patients and HTT-transgenic animals. However, little is known about the physiological brain region- and cell type-specific HTT expression pattern in wild type mice and a potential recruitment of endogenous HTT to other pathogenic protein aggregates such as amyloid plaques in cross seeding events. Employing a monoclonal anti-HTT antibody directed against the HTT mid-region and using brain tissue of three different mouse strains, we detected prominent immunoreactivity in a number of brain areas, particularly in cholinergic cranial nerve nuclei, while ubiquitous neuronal staining appeared faint. The region-specific distribution of endogenous HTT was found to be comparable in wild type rat and hamster brain. In human amyloid precursor protein transgenic Tg2576 mice with amyloid plaque pathology, similar neuronal HTT expression patterns and a distinct association of HTT with Abeta plaques were revealed by immunohistochemical double labelling. Additionally, the localization of HTT in reactive astrocytes was demonstrated for the first time in a transgenic Alzheimer's disease animal model. Both, plaque association of HTT and occurrence in astrocytes appeared to be age-dependent. Astrocytic HTT gene and protein expression was confirmed in primary cultures by RT-qPCR and by immunocytochemistry. We provide the first detailed analysis of physiological HTT expression in rodent brain and, under pathological conditions, demonstrate HTT aggregation in proximity to Abeta plaques and Abeta-induced astrocytic expression of endogenous HTT in Tg2576 mice.
CRIS-Team WoS Importer:2019-06-04

Enhanced Spike-specific, but attenuated Nucleocapsid-specific T cell responses upon SARS-CoV-2 breakthrough versus non-breakthrough infections - Ahmed, Mohamed Ibraheem Mahmoud; Diepers, Paulina; Janke, Christian; Plank, Michael; Eser, Tabea M.; Rubio-Acero, Raquel; Fuchs, Anna; Baranov, Olga; Castelletti, Noemi; Kroidl, Inge; Olbrich, Laura; Bauer, Bernadette; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2 vaccine breakthrough infections frequently occurred even before the emergence of Omicron variants. Yet, relatively little is known about the impact of vaccination on SARS-CoV-2-specific T cell and antibody response dynamics upon breakthrough infection. We have therefore studied the dynamics of CD4 and CD8 T cells targeting the vaccine-encoded Spike and the non-encoded Nucleocapsid antigens during breakthrough infections (BTI, n=24) and in unvaccinated control infections (non-BTI, n=30). Subjects with vaccine breakthrough infection had significantly higher CD4 and CD8 T cell responses targeting the vaccine-encoded Spike during the first and third/fourth week after PCR diagnosis compared to non-vaccinated controls, respectively. In contrast, CD4 T cells targeting the non-vaccine encoded Nucleocapsid antigen were of significantly lower magnitude in BTI as compared to non-BTI. Hence, previous vaccination was linked to enhanced T cell responses targeting the vaccine-encoded Spike antigen, while responses against the non-vaccine encoded Nucleocapsid antigen were significantly attenuated.
CRIS-Team WoS Importer:2023-01-27

Enhancement and induction of HIV-1 infection through an assembled peptide derived from the CD4 binding site of gp120 - Groß, Andrea; Roedel, Katja; Kneidl, Barbara; Donhauser, Norbert; Mössl, Marek; Lump, Edina; Muench, Jan; Schmidt, Barbara; Eichler, Jutta (ChemBioChem, 2015)
Contact between the human immunodeficiency virus (HIV-1) and its target cell is initiated by the interaction of viral gp120 with cellular CD4. An assembled peptide (CD4bs-M) that presents the CD4 binding site of gp120 was previously shown to inhibit the gp120-CD4 interaction. Here, we demonstrate that CD4bs-M selectively enhances infection of cells with HIV-1, whereas infection with herpes simplex virus remains largely unaffected. The effects of CD4bs-M variants containing D-amino acids, or prolines at selected positions, point to the importance of side chain orientation and spatial orientation of this fragment. Furthermore, CD4bs-M was shown to assemble into amyloid-like fibrils that capture HIV-1 particles, which likely contributes to the infection-enhancing effect. Beyond infection enhancement, CD4bs-M enabled HIV-1 infection of CD4-negative cells, suggesting that binding of the peptide to gp120 facilitates interaction of gp120 with coreceptors, which might in turn enhance HIV-1 entry.
EVALuna2:8271

Epidemiology of Human Parechovirus Type 3 Upsurge in 2 Hospitals, Freiburg, Germany, 2018 - Elling, Roland; Boettcher, Sindy; Du Bois, Florian; Mueller, Alexandra; Prifert, Christiane; Weissbrich, Benedikt; Hofmann, Joerg; Korn, Klaus; Eis-Huebinger, Anna-Maria; Hufnagel, Markus; Panning, Marcus (Emerging Infectious Diseases, 2019)
In 2018, a cluster of pediatric human parechovirus (HPeV) infections in 2 neighboring German hospitals was detected. Viral protein 1 sequence analysis demonstrated co-circulation of different HPeV-3 sublineages and of HPeV-1 and -5 strains, thereby excluding a nosocomial outbreak. Our findings underline the need for HPeV diagnostics and sequence analysis for outbreak investigations.
CRIS-Team WoS Importer:2019-07-19

Epigenetic analysis of HIV-1 proviral genomes from infected individuals: predominance of unmethylated CpG's - Weber, Stefanie; Weiser, Barbara; Kemal, Kimdar S.; Burger, Harold; Ramirez, Christina M.; Korn, Klaus; Anastos, Kathryn; Kaul, Rupert; Kovacs, Colin; Doerfler, Walter (Virology, 2014)
Efforts to cure HIV-1 infections aim at eliminating proviral DNA. Integrated DNA from various viruses often becomes methylated de novo and transcriptionally inactivated. We therefore investigated CpG methylation profiles of 55 of 94 CpG's (58.5%) in HIV-1 proviral genomes including ten CpG's in each LTR and additional CpG's in portions of gag, env, nef, rev, and tat genes. We analyzed 33 DNA samples from PBMC's of 23 subjects representing a broad spectrum of HIV-1 disease. In 22 of 23 HIV-1-infected individuals, there were only unmethylated CpG's regardless of infection status. In one long term nonprogressor, however, methylation of proviral DNA varied between 0 and 75% over an 11-year period although the CD4+ counts remained stable. Hence levels of proviral DNA methylation can fluctuate. The preponderance of unmethylated CpG's suggests that proviral methylation is not a major factor in regulating HIV-1 proviral activity in PBMC's. Unmethylated CpG's may play a role in HIV-1 immunopathogenesis.
EVALuna2:8239

Epigenetic consequences of genome manipulations: caveats for human germline therapy and genetically modified organisms - Doerfler, Walter (Epigenomics, 2019)
CRIS-Team WoS Importer:2019-03-01

Epitope-Specific Humoral Responses to Human Cytomegalovirus Glycoprotein-B Vaccine With MF59: Anti-AD2 Levels Correlate With Protection From Viremia - Baraniak, Ilona; Kropff, Barbara; Mclean, Gary R.; Pichon, Sylvie; Piras-Douce, Fabienne; Milne, Richard S. B.; Smith, Colette; Mach, Michael; Griffiths, Paul D.; Reeves, Matthew B. (Journal of Infectious Diseases, 2018)
The human cytomegalovirus (HCMV) virion envelope protein glycoprotein B (gB) is essential for viral entry and represents a major target for humoral responses following infection. Previously, a phase 2 placebo-controlled clinical trial conducted in solid organ transplant candidates demonstrated that vaccination with gB plus MF59 adjuvant significantly increased gB enzyme-linked immunosorbent assay (ELISA) antibody levels whose titer correlated directly with protection against posttransplant viremia. The aim of the current study was to investigate in more detail this protective humoral response in vaccinated seropositive transplant recipients. We focused on 4 key antigenic domains (AD) of gB (AD1, AD2, AD4, and AD5), measuring antibody levels in patient sera and correlating these with posttransplant HCMV viremia. Vaccination of seropositive patients significantly boosted preexisting antibody levels against the immunodominant region AD1 as well as against AD2, AD4, and AD5. A decreased incidence of viremia correlated with higher antibody levels against AD2 but not with antibody levels against the other 3 ADs. Overall, these data support the hypothesis that antibodies against AD2 are a major component of the immune protection of seropositives seen following vaccination with gB/MF59 vaccine and identify a correlate of protective immunity in allograft patients.
EVALuna2:35273

Epstein-Barr virus-driven B cell lymphoma mediated by a direct LMP1-TRAF6 complex - Giehler, Fabian; Ostertag, Michael S.; Sommermann, Thomas; Weidl, Daniel; Sterz, Kai R.; Kutz, Helmut; Moosmann, Andreas; Feller, Stephan M.; Geerlof, Arie; Biesinger, Brigitte; Popowicz, Grzegorz M.; Kirchmair, Johannes; et al. (Nature Communications, 2024)
Epstein-Barr virus (EBV) latent membrane protein 1 (LMP1) drives viral B cell transformation and oncogenesis. LMP1’s transforming activity depends on its C-terminal activation region 2 (CTAR2), which induces NF-κB and JNK by engaging TNF receptor-associated factor 6 (TRAF6). The mechanism of TRAF6 recruitment to LMP1 and its role in LMP1 signalling remains elusive. Here we demonstrate that TRAF6 interacts directly with a viral TRAF6 binding motif within CTAR2. Functional and NMR studies supported by molecular modeling provide insight into the architecture of the LMP1-TRAF6 complex, which differs from that of CD40-TRAF6. The direct recruitment of TRAF6 to LMP1 is essential for NF-κB activation by CTAR2 and the survival of LMP1-driven lymphoma. Disruption of the LMP1-TRAF6 complex by inhibitory peptides interferes with the survival of EBV-transformed B cells. In this work, we identify LMP1-TRAF6 as a critical virus-host interface and validate this interaction as a potential therapeutic target in EBV-associated cancer.
CRIS-Team Scopus Importer:2024-01-19

Eradication of measles: remaining challenges - Holzmann, Heidemarie; Hengel, Hartmut; Tenbusch, Matthias; Doerr, H. W. (Medical Microbiology and Immunology, 2016)
Measles virus (MeV) is an aerosol-borne and one of the most contagious pathogenic viruses known. Almost every MeV infection becomes clinically manifest and can lead to serious and even fatal complications, especially under conditions of malnutrition in developing countries, where still 115,000 to 160,000 patients die from measles every year. There is no specific antiviral treatment. In addition, MeV infections cause long-lasting memory B and T cell impairment, predisposing people susceptible to opportunistic infections for years. A rare, but fatal long-term consequence of measles is subacute sclerosing panencephalitis. Fifteen years ago (2001), WHO has launched a programme to eliminate measles by a worldwide vaccination strategy. This is promising, because MeV is a human-specific morbillivirus (i.e. without relevant animal reservoir), safe and potent vaccine viruses are sufficiently produced since decades for common application, and millions of vaccine doses have been used globally without any indications of safety and efficacy issues. Though the prevalence of wild-type MeV infection has decreased by >90 % in Europe, measles is still not eliminated and has even re-emerged with recurrent outbreaks in developed countries, in which effective vaccination programmes had been installed for decades. Here, we discuss the crucial factors for a worldwide elimination of MeV: (1) efficacy of current vaccines, (2) the extremely high contagiosity of MeV demanding a >95 % vaccination rate based on two doses to avoid primary vaccine failure as well as the installation of catch-up vaccination programmes to fill immunity gaps and to achieve herd immunity, (3) the implications of sporadic cases of secondary vaccine failure, (4) organisation, acceptance and drawbacks of modern vaccination campaigns, (5) waning public attention to measles, but increasing concerns from vaccine-associated adverse reactions in societies with high socio-economic standards and (6) clinical, epidemiological and virological surveillance by the use of modern laboratory diagnostics and reporting systems. By consequent implementation of carefully designed epidemiologic and prophylactic measures, it should be possible to eradicate MeV globally out of mankind, as the closely related morbillivirus of rinderpest could be successfully eliminated out of the cattle on a global scale.
EVALuna2:8323

Erratum: Intrastructural Help: Harnessing T Helper Cells Induced by Licensed Vaccines for Improvement of HIV Env Antibody Responses to Virus-Like Particle Vaccines (Journal of Virology (2018) 92:14 (e00141-18) Doi:10.1128/JVI.00141-18) - Elsayed, Hassan; Nabi, Ghulam; McKinstry, William J.; Khoo, Keith K.; Mak, Johnson; Salazar, Andres M.; Tenbusch, Matthias; Temchura, Vladimir; Überla, Klaus (Journal of Virology, 2022)
Volume 92, no.14, e00141-18, 2018, https://doi.org/10.1128/JVI.00141-18. Page 14: The first sentence of Acknowledgments should be replaced with the following. This project has received funding from the European Union’s Horizon 2020 research and innovation programme under grant agreement no. 681137, from the Deutsche Forschungsgemeinschaft (transregional collaborative research grant TRR60), and through the Collaboration on AIDS Vaccine Discovery (CAVD) by the Bill & Melinda Gates Foundation.
CRIS-Team Scopus Importer:2022-02-25

Erratum to: Bornavirus encephalitis as a differential diagnosis to seronegative autoimmune encephalitis (Der Nervenarzt, (2022), 10.1007/s00115-021-01259-x) Erratum zu: Die Borna-Virus-Enzephalitis als Differenzialdiagnose zur seronegativen Autoimmunenzephalitis (Der Nervenarzt, (2022), 10.1007/s00115-021-01259-x) - Meier, H.; Bauer, C.; Finkenzeller, W.; Nentwich, J.; Städt, M.; Steininger, Philipp; Korn, Klaus; Enßer, Armin; Erbguth, F. (Der Nervenarzt, 2022)
CRIS-Team Scopus Importer:2022-05-06

Erratum to: The Antidepressant Fluoxetine Mobilizes Vesicles to the Recycling Pool of Rat Hippocampal Synapses During High Activity - Jung, Jasmin; Loy, Kristina; Schilling, Eva-Maria; Röther, Mareike; Brauner, Jan M.; Huth, Tobias; Schlötzer-Schrehardt, Ursula; Alzheimer, Christian; Kornhuber, Johannes; Welzel, Oliver; Groemer, Teja W. (Molecular Neurobiology, 2017)
EVALuna2:21331

Erratum zu: Nachweis einer Infektion mit Humanem Immundefizienzvirus (HIV): Serologisches Screening mit nachfolgender Bestätigungsdiagnostik durch Antikörper-basierte Testsysteme und/oder durch HIV-Nukleinsäure-Nachweis - Rabenau, Holger F.; Bannert, Norbert; Berger, Annemarie; Mantke, Oliver Donoso; Eberle, Josef; Enders, Martin; Fickenscher, Helmut; Grunert, Hans-Peter; Guertler, Lutz; Heim, Albert; Huzly, Daniela; Kaiser, Rolf; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2015)
EVALuna2:8270

Essential concepts are missing: Foreign DNA in food invades the organisms' cells and can lead to stochastic epigenetic alterations with a wide range of possible pathogenetic consequences - Doerfler, Walter (Clinical Epigenetics, 2020)
In this article, a new concept for general pathogenesis has been proposed. Advances in molecular genetics have led to the realization that essential concepts in the framework of molecular biology are still missing. Clinical medicine is plagued by similar shortcomings: The questioning of current paradigms could open new vistas and invite challenging approaches. This article presents an unconventional idea. Foreign DNA which is regularly ingested with the essential food supply is not completely degraded. Small quantities of fragmented DNA rather persist transiently in the gastro-intestinal tract of mice and can be traced to various organ systems, except for cells in the germ line. Foreign DNA entering and persisting in mammalian cells can stochastically lead to genome-wide alterations of transcriptional and CpG DNA methylation profiles. In the course of food-ingested DNA invading somatic cells, completely new cell types can be generated which might be involved in the causation of common ailments. Projects emanating from this perception merit critical analysis and rigorous pursuit.
CRIS-Team Scopus Importer:2020-02-18
Keywords: A new concept in general pathogenesis; Epigenetic alterations upon foreign DNA intrusions; Foreign DNA in mammalian cells and organisms; Origin of novel cell types; Relevance for pathogenesis of common human diseases; Stochastic alterations of cell type; Uptake and persistence of food-ingested foreign DNA

Estimates and determinants of sars-cov-2 seroprevalence and infection fatality ratio using latent class analysis: The population-based tirschenreuth study in the hardest-hit german county in spring 2020 - Wagner, Ralf; Peterhoff, David; Beileke, Stephanie; Günther, Felix; Berr, Melanie; Einhauser, Sebastian; Schütz, Anja; Niller, Hans Helmut; Steininger, Philipp; Knöll, Antje; Tenbusch, Matthias; Maier, Clara; et al. (Viruses, 2021)
SARS-CoV-2 infection fatality ratios (IFR) remain controversially discussed with implications for political measures. The German county of Tirschenreuth suffered a severe SARS-CoV-2 outbreak in spring 2020, with particularly high case fatality ratio (CFR). To estimate seroprevalence, underreported infections, and IFR for the Tirschenreuth population aged ≥14 years in June/July 2020, we conducted a population-based study including home visits for the elderly, and analyzed 4203 participants for SARS-CoV-2 antibodies via three antibody tests. Latent class analysis yielded 8.6% standardized county-wide seroprevalence, a factor of underreported infections of 5.0, and 2.5% overall IFR. Seroprevalence was two-fold higher among medical workers and one third among current smokers with similar proportions of registered infections. While seroprevalence did not show an age-trend, the factor of underreported infections was 12.2 in the young versus 1.7 for ≥85-year-old. Age-specific IFRs were <0.5% below 60 years of age, 1.0% for age 60–69, and 13.2% for age 70+. Senior care homes accounted for 45% of COVID-19-related deaths, reflected by an IFR of 7.5% among individuals aged 70+ and an overall IFR of 1.4% when excluding senior care home residents from our computation. Our data underscore senior care home infections as key determinant of IFR additionally to age, insufficient targeted testing in the young, and the need for further investigations on behavioral or molecular causes of the fewer infections among current smokers.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Antibodies; CLIA; ELISA; Infection fatality ratio; Latent class analysis; SARS-CoV-2; Senior care homes; Seroprevalence; Smoking; Underreported infections

Ethanol consumption decreases autoantibody titers by blocking IL-21 secretion of Tfh cells during the development of arthritis - Azizov, Vugar; Dietel, K.; Kolenbrander, A.; Seubert, S.; Steffen, F.; Meidenbauer, J.; Steffen, Ulrike; Hofmann, Jörg; Nimmerjahn, Falk; Linker, R.; Wirtz, Stefan; Sarter-Zaiss, Kerstin; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Ethanol consumption inhibits TFH cell responses and the development of autoimmune arthritis - Azizov, Vugar; Dietel, Katharina; Steffen, Franziska; Dürholz, Kerstin; Meidenbauer, Julia; Lucas, Sébastien; Frech, Michael; Omata, Yasunori; Tajik, Narges; Knipfer, Lisa; Kolenbrander, Anne; Seubert, Silvia; et al. (Nature Communications, 2020)
Alcohol consumption is a consistent protective factor for the development of autoimmune diseases such as rheumatoid arthritis (RA). The underlying mechanism for this tolerance-inducing effect of alcohol, however, is unknown. Here we show that alcohol and its metabolite acetate alter the functional state of T follicular helper (TFH) cells in vitro and in vivo, thereby exerting immune regulatory and tolerance-inducing properties. Alcohol-exposed mice have reduced Bcl6 and PD-1 expression as well as IL-21 production by TFH cells, preventing proper spatial organization of TFH cells to form TFH:B cell conjugates in germinal centers. This effect is associated with impaired autoantibody formation, and mitigates experimental autoimmune arthritis. By contrast, T cell independent immune responses and passive models of arthritis are not affected by alcohol exposure. These data clarify the immune regulatory and tolerance-inducing effect of alcohol consumption.
CRIS-Team Scopus Importer:2020-05-05

Evaluation of adenovirus 19a as a novel vector for mucosal vaccination against influenza A viruses - Lapuente, Dennis; Ruzsics, Zsolt; Thirion, Christian; Tenbusch, Matthias (Vaccine, 2018)
Since preexisting immunity and enhanced infection rates in a clinical trial of an HIV vaccine have raised some concerns on adenovirus (Ad) serotype 5-based vaccines, we evaluated the subgroup D adenovirus serotype Ad19a for its suitability as novel viral vector vaccine against mucosal infections. In BALB/c mice, we compared the immunogenicity and efficacy of E1/E3-deleted Ad19a vectors encoding the influenza A virus (IAV)-derived antigens hemagglutinin (HA) and nucleoprotein (NP) to the most commonly used Ad5 vectors. The adenoviral vectors were applied intranasally and induced detectable antigen-specific T cell responses in the lung and in the spleen as well as robust antibody responses. A prior DNA immunization significantly improved the immunogenicity of both vectors and resulted in full protection against a lethal infection with a heterologous H3N2 virus. Nevertheless, the Ad5-based vectors were slightly superior in reducing viral replication in the lung which corresponded to higher NP-specific T cell responses measured in the lungs. (C) 2018 Elsevier Ltd. All rights reserved.
EVALuna2:35279

Exosomes from human immunodeficiency virus type 1 (HIV-1)-infected cells license quiescent CD4+ T lymphocytes to replicate HIV-1 through a Nef- and ADAM17-dependent mechanism - Arenaccio, Claudia; Chiozzini, Chiara; Columba-Cabezas, Sandra; Manfredi, Francesco; Affabris, Elisabetta; Baur, Andreas; Federico, Maurizio (Journal of Virology, 2014)
Resting CD4+ T lymphocytes resist human immunodeficiency virus (HIV) infection. Here, we provide evidence that exosomes from HIV-1-infected cells render resting human primary CD4+ T lymphocytes permissive to HIV-1 replication. These results were obtained with transwell cocultures of HIV-1-infected cells with quiescent CD4+ T lymphocytes in the presence of inhibitors of exosome release and were confirmed using exosomes purified from supernatants of HIV-1-infected primary CD4+ T lymphocytes. We found that the expression of HIV-1 Nef in exosome-producing cells is both necessary and sufficient for cell activation as well as HIV-1 replication in target CD4+ T lymphocytes. We also identified a Nef domain important for the effects we observed, i.e., the 62EEEE65 acidic cluster domain. In addition, we observed that ADAM17, i.e., a disintegrin and metalloprotease converting pro-tumor necrosis factor alpha (TNF-?) in its mature form, associates with exosomes from HIV-1-infected cells, and plays a key role in the HIV-1 replication in quiescent CD4+ T lymphocytes. Treatment with an inhibitor of ADAM17 abolished both activation and HIV-1 replication in resting CD4+ T lymphocytes. TNF-? is the downstream effector of ADAM17 since the treatment of resting lymphocytes with anti-TNF-? antibodies blocked the HIV-1 replication. The data presented here are consistent with a model where Nef induces intercellular communication through exosomes to activate bystander quiescent CD4+ T lymphocytes, thus stimulating viral spread.Overall, our findings support the idea that HIV evolved to usurp the exosome-based intercellular communication network to favor its spread in infected hosts.
EVALuna2:19488

Exploiting the amazing diversity of natural source-derived polysaccharides: Modern procedures of isolation, engineering, and optimization of antiviral activities - Ray, Bimalendu; Schütz, Martin; Mukherjee, Shuvam; Jana, Subrata; Ray, Sayani; Marschall, Manfred (Polymers, 2021)
Naturally occurring polysaccharide sulfates are highly diverse, owning variations in the backbone structure, linkage pattern and stereochemistry, branching diversity, sulfate content and positions of sulfate group(s). These structural characteristics bring about diverse sulfated polymers with dissimilar negative charge densities and structure–activity relationships. Herein, we start with a short discussion of techniques needed for extraction, purification, chemical sulfation, and structural characterization of polysaccharides. Processes of isolation and sulfation of plant-derived polysaccharides are challenging and usually involve two steps. In this context, we describe an integrated extraction-sulfation procedure that produces polysaccharide sulfates from natural products in one step, thereby generating additional pharmacological activities. Finally, we provide examples of the spectrum of natural source-derived polysaccharides possessing specific features of bioactiv-ity, in particular focusing on current aspects of antiviral drug development and drug–target inter-action. Thus, the review presents a detailed view on chemically engineered polysaccharides, espe-cially sulfated derivatives, and underlines their promising biomedical perspectives.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Amalgamated extraction-sulfation methods; Broad-spectrum bioactivity; Chemical profiles; Natural source-derived compounds; Polysaccharide sulfates; Specific antiviral activities; Structure–activity relationships

Exploring Reference Values for Hair Cortisol: Hair Weight versus Hair Protein - Frisch, Nadine; Eichler, Anna; Plank, Anne-Christine; Golub, Yulia; Moll, Gunther; Kratz, Oliver (Therapeutic Drug Monitoring, 2020)
BACKGROUND: As a marker of cumulative cortisol activity, hair cortisol has received attention in clinical and methodological research. Currently, it is common practice to relate hair cortisol concentration (HCC) to hair weight. The present paper explores hair protein concentration (HPC) as another possible reference value for HCC. METHODS: For n = 18 hair samples cut from the posterior vertex, the HCC, HPC, and hair sample weight were determined, and the cortisol-to-weight and cortisol-to-protein ratios were calculated. Correlations were analyzed between HCC, HPC, and hair sample weight as well as between the cortisol-to-weight and cortisol-to-protein ratios. Hair sample weight and HPC were included as independent variables in a stepwise linear regression model to predict HCC. RESULTS: HCC and HPC did not correlate significantly (r = .393, p = .106); however, the correlation between HCC and hair sample weight was significant (r = .520, p = .027). HPC and hair sample weight (r = .605, p = .008) as well as the cortisol-to-weight and cortisol-to-protein ratios (r = .858, p < .000) showed a high correlation. Hair sample weight was the better predictor of HCC (β = .520, p = .027) than HPC (β = .125, p = .657). CONCLUSIONS: The results indicate that hair sample weight is the more suitable reference value for HCC. Thus, the standard cortisol-to-weight ratio should be used as the preferred expression for cumulative cortisol activity measured in scalp hair. However, calculating the cortisol-to-protein ratio can be considered as an alternative if the hair sample weight is not available.
CRIS-Team Scopus Importer:2020-06-30

Exploring Reference Values for Hair Cortisol: Hair Weight Versus Hair Protein. - Frisch, Nadine; Eichler, Anna; Plank, Anne-Christine; Golub, Yulia; Moll, Gunther; Kratz, Oliver (Therapeutic Drug Monitoring, 2020)
BACKGROUND: As a marker of cumulative cortisol activity, hair cortisol has received attention in clinical and methodological research. Currently, it is a common practice to relate the hair cortisol concentration (HCC) to hair weight. This article explores the hair protein concentration (HPC) as another possible reference value for HCC. METHODS: For n = 18 hair samples cut from the posterior vertex, the HCC, HPC, and hair sample weight were determined, and the cortisol-to-weight and cortisol-to-protein ratios were calculated. Correlations were analyzed between the HCC, HPC, and hair sample weight as well as between the cortisol-to-weight and cortisol-to-protein ratios. Hair sample weight and HPC were included as independent variables in a stepwise linear regression model to predict HCC. RESULTS: The HCC and HPC did not correlate significantly (r = 0.393, P = 0.106); however, the correlation between HCC and hair sample weight was significant (r = 0.520, P = 0.027). The HPC and hair sample weight (r = 0.605, P = 0.008) as well as the cortisol-to-weight and cortisol-to-protein ratios (r = 0.858, P < 0.000) showed a high correlation. The hair sample weight was the better predictor of the HCC (β = 0.520, P = 0.027) than HPC (β = 0.125, P = 0.657). CONCLUSIONS: The results indicate that the hair sample weight is the more suitable reference value for the HCC. Thus, the standard cortisol-to-weight ratio should be used as the preferred expression for the cumulative cortisol activity measured in the scalp hair. However, calculating the cortisol-to-protein ratio can be considered as an alternative if the hair sample weight is not available.
EVALuna2:384364
Keywords: hair cortisol; hair protein; hypothalamic-pituitary-adrenal axis; methodology; stress

Exploring the Human Cytomegalovirus Core Nuclear Egress Complex as a Novel Antiviral Target: A New Type of Small Molecule Inhibitors - Alkhashrom, Sewar; Kicuntod, Jintawee; Häge, Sigrun; Schweininger, Johannes; Muller, Yves; Lischka, Peter; Marschall, Manfred; Eichler, Jutta (Viruses, 2021)
Nuclear egress is an essential process in the replication of human cytomegalovirus (HCMV), as it enables the migration of newly formed viral capsids from the nucleus into the cytoplasm. Inhibition of the HCMV core nuclear egress complex (core NEC), composed of viral proteins pUL50 and pUL53, has been proposed as a potential new target for the treatment of HCMV infection and disease. Here, we present a new type of small molecule inhibitors of HCMV core NEC formation, which inhibit the pUL50-pUL53 interaction at nanomolar concentrations. These inhibitors, i.e., verteporfin and merbromin, were identified through the screening of the Prestwick Chemical Library® of approved drug compounds. The inhibitory effect of merbromin is both compound- and target-specific, as no inhibition was seen for other mercury-organic compounds. Furthermore, merbromin does not inhibit an unrelated protein-protein interaction either. More importantly, merbromin was found to inhibit HCMV infection of cells in three different assays, as well as to disrupt HCMV NEC nuclear rim formation. Thus, while not being an ideal drug candidate by itself, merbromin may serve as a blueprint for small molecules with high HCMV core NEC inhibitory potential, as candidates for novel anti-herpesviral drugs.
CRIS-Team Scopus Importer:2021-04-16
Keywords: antiviral activity; core NEC inhibitor; human cytomegalovirus; nuclear egress complex (NEC); small molecule inhibitor

EXPRESSION OF FKBP51 AND HAP40 PROTEIN IN A CONGENIC RAT MODEL OF HUNTINGTON DISEASE - Ratz, Veronika; Plank, Anne-Christine; Schulze-Krebs, Anja; von Hörsten, Stephan (2018)
EVALuna2:36093

Expression of HTLV-1 Genes in T-Cells Using RNA Electroporation - Manicone, Mariangela; Rende, Francesca; Cavallari, Ilaria; Thoma-Kreß, Andrea; Ciminale, Vincenzo (Methods in Molecular Biology, 2017)
Human T-cell leukemia virus type 1 (HTLV-1) infects about 20 million people world-wide. Around 5% of the infected individuals develop adult T-cell leukemia (ATL) or a neurological disease termed tropical spastic paraparesis (TSP) after a clinical latency of years to decades. Through the use of two promoters and alternative splicing HTLV-1 expresses at least 12 different proteins. HTLV-1 establishes a life-long persistent infection by inducing the clonal expansion of infected cells, a property largely ascribed to the viral genes Tax and HBZ. However, the fact that ATL arises in a minority of infected individuals after a long clinical latency suggests the existence of factors counterbalancing the oncogenic potential of HTLV-1 in the context of natural infection.To study the role of the different HTLV-1 gene products in the HTLV-1 life cycle, we optimized a transfection protocol for primary T-cells using an approach based on the electroporation of in vitro-transcribed RNA. Results showed that the RNA transfection technique combines a high transfection efficiency with low toxicity, not only in Jurkat T-cells but also in primary T-cells. These findings suggest that RNA electroporation is preferable for experiments aimed at investigating the role of HTLV-1 gene products in the context of primary T-cells, which represent the main target of HTLV-1 in vivo.
EVALuna2:35815

Extracapsular dissection in the parapharyngeal space: benefits and potential pitfalls - Mantsopoulos, K.; Müller, Sandra; Agaimy, Abbas; Goncalves, M.; Koch, Matthias; Wüst, Wolfgang; Bohr, Christopher; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2017)
The aim of this study was to investigate the benefits and potential pitfalls of transcervical extracapsular dissection in the treatment of parotid gland tumours in the parapharyngeal space. We retrospectively evaluated the records of all patients with parapharyngeal parotid gland lesions treated between 2000 and 2015 by transcervical extracapsular dissection. Patients having revision operations and patients whose records were not complete were excluded, leaving 49 patients in the study. We found acceptable oncological and functional outcomes throughout. Special attention should be paid in cases with multilobular growth of the tumour on magnetic resonance imaging, satellite tumours of pleomorphic adenomas, tumours in broad contact with the inner surface of the deep lobe, and lesions suspected of malignancy. Extracapsular dissection in the parapharyngeal region is associated with acceptable oncological and functional outcomes. These outcomes can be expected only after a thorough assessment of patient's history and preoperative imaging.
EVALuna2:6890

Extracellular vesicles from mature dendritic cells (DC) differentiate monocytes into immature DC - Schierer, Stefan; Ostalecki, Christian; Zinser, Elisabeth; Lamprecht, Ricarda; Plosnita, Bianca; Stich, Lena; Dörrie, Jan; Lutz, Manfred B.; Schuler, Gerold; Baur, Andreas (Life Science Alliance, 2018)
During inflammation, murine and human monocytes can develop into dendritic cells (DC), but this process is not entirely understood. Here, we demonstrate that extracellular vesicles (EV) secreted by mature human DC (maDC) differentiate peripheral monocytes into immature DC, expressing a unique marker pattern, including 6-sulfo LacNAc (slan), Zbtb46, CD64, and CD14. While EV from both maDC and immature DC differentiated monocytes similar to GM-CSF/IL-4 stimulation, only maDC-EV produced precursors, which upon maturation stimulus developed into T-cell-activating and IL-12p70-secreting maDC. Mechanistically, maDC-EV induced cell signaling through GM-CSF, which was abundant in EV as were IL-4 and other cytokines and chemokines. When injected into the mouse skin, murine maDC-EV attracted immune cells including monocytes that developed activation markers typical for inflammatory cells. Skin-injected EV also reached lymph nodes, causing a similar immune cell infiltration. We conclude that DC-derived EV likely serve to perpetuate an immune reaction and may contribute to chronic inflammation.
EVALuna2:36337

Ex Vivo Blockade of the PD-1 Pathway Improves Recall IFNγ Responses of HIV-Infected Persons on Antiretroviral Therapy - Fischhaber, Natalie; Schmiedeberg, Moritz; Kübel, Sabrina; Harrer, Ellen; Harrer, Thomas; Nganou-Makamdop, Krystelle (Vaccines, 2023)
Despite antiretroviral therapy (ART), immune exhaustion persists in HIV infection and limits T cell responses to HIV or other pathogens. Moreover, HIV infection results in the loss of pre-existing immunity. Here, we investigated the effect of blocking the PD-1 pathway on recall IFNγ responses to tetanus toxoid (TT) and measles virus (MV) antigens in HIV-infected persons on ART with prior TT and MV immunity. The ex vivo treatment of lymphocytes with anti-PD-1 and anti-PD-L1 antibodies significantly increased TT- and MV-specific IFNγ responses. The responses to TT and MV antigens alone or in combination with antibodies blocking the PD-1 pathway positively correlated with CD4 T cell levels. Furthermore, T cell PD-1 expression levels inversely correlated with recall IFNγ responses in combination with antibodies blocking the PD-1 pathway but not with IFNγ responses to antigens only. Our study suggested that targeting the PD-1 pathway may boost vaccine-induced pre-existing immunity in HIV-infected persons on ART depending on the degree of immune exhaustion.
CRIS-Team Scopus Importer:2023-03-17
Keywords: anti-PD-1; anti-PD-L1; HIV infection; PD-1 pathway; T cell exhaustion; vaccine-induced immunity

Facile access to potent antiviral quinazoline heterocycles with fluorescence properties via merging metal-free domino reactions - Held, Felix; Guryev, Anton; Fröhlich, Tony; Hampel, Frank; Kahnt, Axel; Hutterer, Corina; Steingruber, Mirjam; Bahsi, Hanife; Von Bojnicic-Kninski, Clemens; Mattes, Daniela S.; Foertsch, Tobias C.; Nesterov-Mueller, Alexander; et al. (Nature Communications, 2017)
Most of the known approved drugs comprise functionalized heterocyclic compounds as subunits. Among them, non-fluorescent quinazolines with four different substitution patterns are found in a variety of clinically used pharmaceuticals, while 4,5,7,8-substituted quinazolines and those displaying their own specific fluorescence, favourable for cellular uptake visualization, have not been described so far. Here we report the development of a one-pot synthetic strategy to access these 4,5,7,8-substituted quinazolines, which are fluorescent and feature strong antiviral properties (EC50down to 0.6±0.1 μM) against human cytomegalovirus (HCMV). Merging multistep domino processes in one-pot under fully metal-free conditions leads to sustainable, maximum efficient and high-yielding organic synthesis. Furthermore, generation of artesunic acid-quinazoline hybrids and their application against HCMV (EC50down to 0.1±0.0 μM) is demonstrated. Fluorescence of new antiviral hybrids and quinazolines has potential applications in molecular imaging in drug development and mechanistic studies, avoiding requirement of linkage to external fluorescent markers.
EVALuna2:33762

Fatal Encephalitis Associated with Borna Disease Virus 1 - Korn, Klaus; Coras, Roland; Bobinger, Tobias; Herzog, Sibylle M.; Lücking, Hannes; Stoehr, Roland; Huttner, Hagen; Hartmann, Arndt; Enßer, Armin (New England Journal of Medicine, 2018)
EVALuna2:34851

Fatal Lymphoproliferative Disease in Two Siblings Lacking Functional FAAP24 - Daschkey, Svenja; Bienemann, Kirsten; Schuster, Volker; Kreth, Hans Wolfgang; Linka, Rene Martin; Hoenscheid, Andrea; Fritz, Gerhard; Johannes, Christian; Fleckenstein, Bernhard; Kempkes, Bettina; Gombert, Michael; Ginzel, Sebastian; et al. (Journal of Clinical Immunology, 2016)
Hereditary defects in several genes have been shown to disturb the normal immune response to EBV and to give rise to severe EBV-induced lymphoproliferation in the recent years. Nevertheless, in many patients, the molecular basis of fatal EBV infection still remains unclear. The Fanconi anemia-associated protein 24 (FAAP24) plays a dual role in DNA repair. By association with FANCM as component of the FA core complex, it recruits the FA core complex to damaged DNA. Additionally, FAAP24 has been shown to evoke ATR-mediated checkpoint responses independently of the FA core complex. By whole exome sequencing, we identified a homozygous missense mutation in the FAAP24 gene (cC635T, pT212M) in two siblings of a consanguineous Turkish family who died from an EBV-associated lymphoproliferative disease after infection with a variant EBV strain, expressing a previously unknown EBNA2 allele.In order to analyze the functionality of the variant FAAP24 allele, we used herpes virus saimiri-transformed patient T cells to test endogenous cellular FAAP24 functions that are known to be important in DNA damage control. We saw an impaired FANCD2 monoubiquitination as well as delayed checkpoint responses, especially affecting CHK1 phosphorylation in patient samples in comparison to healthy controls. The phenotype of this FAAP24 mutation might have been further accelerated by an EBV strain that harbors an EBNA2 allele with enhanced activities compared to the prototype laboratory strain B95.8. This is the first report of an FAAP24 loss of function mutation found in human patients with EBV-associated lymphoproliferation.
EVALuna2:8324

Fatal Puumala Hantavirus Infection in a Patient with Common Variable Immunodeficiency (CVID) - Steininger, Philipp; Herbst, Larissa; Bihlmaier, Karl; Willam, Carsten; Koerper, Sixten; Schrezenmeier, Hubert; Klueter, Harald; Pfister, Frederick; Amann, Kerstin Ute; Weiss, Sabrina; Krueger, Detlev H.; Zimmermann, Robert; et al. (Microorganisms, 2023)
Puumala hantavirus (PUUV) infections usually show a mild or moderate clinical course, but may sometimes also lead to life-threatening disease. Here, we report on a 60-year-old female patient with common variable immunodeficiency (CVID) who developed a fatal PUUV infection with persistent renal failure, thrombocytopenia, and CNS infection with impaired consciousness and tetraparesis. Hantavirus-specific antibodies could not be detected due to the humoral immunodeficiency. Diagnosis and virological monitoring were based on the quantitative detection of PUUV RNA in blood, cerebrospinal fluid, bronchial lavage, and urine, where viral RNA was found over an unusually extended period of one month. Due to clinical deterioration and virus persistence, treatment with ribavirin was initiated. Additionally, fresh frozen plasma (FFP) from convalescent donors with a history of PUUV infection was administered. Despite viral clearance, the clinical condition of the patient did not improve and the patient died on day 81 of hospitalization. This case underlines the importance of the humoral immune response for the course of PUUV disease and illustrates the need for PCR-based virus diagnostics in those patients. Due to its potential antiviral activity, convalescent plasma should be considered in the therapy of severe hantavirus diseases.
CRIS-Team Scopus Importer:2023-03-10
Keywords: common variable immunodeficiency; convalescent plasma; encephalitis; Puumala hantavirus; ribavirin

FDG ?PET Fails to Detect a Disease-Specific Phenotype in Rats Transgenic for Huntington's Disease - A 15 Months Follow-up Study - Reilmann, Ralf; Lippross, Veronika; Hölzner, Eva; Gigengack, Fabian; Bohlen, Stefan; Kugel, Harald; Deppe, Michael; Osada, Nani; Lücke, M; Riess, Olaf; Nguyen, Huu Phuc; von Hörsten, Stephan; et al. (Journal of Huntington's Disease, 2015)
FDG-PET detects hypometabolism in premanifest and symptomatic Huntington's disease (HD). A cross-sectional study suggested that whole-brain FDG-PET is capable to detect a phenotype in transgenic (tg) HD rats. Recently, a longitudinal follow-up study showed no FDG-PET changes in tgHD rats. Both studies applied small sample sizes and analysis was limited to whole-brain or striatum.We therefore performed a follow-up study in a larger cohort of tgHD and wild-type (wt) rats encompassing several pre-defined regions of interest (ROIs) and hypothesis free voxel-by-voxel SPM analysis to clarify whether FDG-PET can detect a phenotype in tgHD rats and to determine onset ...and effect sizes of changes over time.N = 19 tgHD- and n = 20 wt-rats, mixed gender, were included. Repeated small animal FDG-?PET and MRI were performed at 5,10,15, and 20 months of age. ROIs encompassing entire brain, cortex, striatum, thalamus, subventricular-zone, and cerebellum were placed manually on the MRI and transferred to the co-registered ?PET. Mean and maximal FDG-PET activities within ROIs were calculated and normalized to cerebellar FDG uptake. Activity and spatially normalized FDG-?PET were compared between groups on a hypothesis-free voxel-by-voxel basis using SPM.FDG uptake showed changes over time in both tgHD- and wt-rats, however, there was no consistent difference between tgHD- and wt-rats in both the manual ROI and SPM analysis.In this transgenic rat model of HD FDG-?PET imaging does not detect significant alterations at the ages investigated. Further investigations are warranted employing other age groups and alternative imaging biomarkers for neuronal degeneration, respectively.
EVALuna2:24981

Forced expiration measurements in mouse models of obstructive and restrictive lung diseases - Devos, Fien C.; Maaske, Andre; Robichaud, Annette; Pollaris, Lore; Seys, Sven; Lopez, Carolina Aznar; Verbeken, Erik; Tenbusch, Matthias; Lories, Rik; Nemery, Benoit; Hoet, Peter H. M.; Vanoirbeek, Jeroen A. J. (Respiratory Research, 2017)
BACKGROUND: Pulmonary function measurements are important when studying respiratory disease models. Both resistance and compliance have been used to assess lung function in mice. Yet, it is not always clear how these parameters relate to forced expiration (FE)-related parameters, most commonly used in humans. We aimed to characterize FE measurements in four well-established mouse models of lung diseases. METHOD: Detailed respiratory mechanics and FE measurements were assessed concurrently in Balb/c mice, using the forced oscillation and negative pressure-driven forced expiration techniques, respectively. Measurements were performed at baseline and following increasing methacholine challenges in control Balb/c mice as well as in four disease models: bleomycin-induced fibrosis, elastase-induced emphysema, LPS-induced acute lung injury and house dust mite-induced asthma. RESULTS: Respiratory mechanics parameters (airway resistance, tissue damping and tissue elastance) confirmed disease-specific phenotypes either at baseline or following methacholine challenge. Similarly, lung function defects could be detected in each disease model by at least one FE-related parameter (FEV0.1, FEF0.1, FVC, FEV0.1/FVC ratio and PEF) at baseline or during the methacholine provocation assay. CONCLUSIONS: FE-derived outcomes in four mouse disease models behaved similarly to changes found in human spirometry. Routine combined lung function assessments could increase the translational utility of mouse models.
EVALuna2:33760

Four-and-a-Half LIM-Domain Protein 2 (FHL2) Induces Neuropeptide Y (NPY) in Macrophages in Visceral Adipose Tissue and Promotes Diet-Induced Obesity - Sommer, Judith; Ehnis, Hanna; Seitz, Tatjana; Schneider, Julia; Wild, Andreas; Moceri, Sandra; Buechler, Christa; Bozec, Aline; Weber, Georg; Merkel, Susanne; Beckervordersandforth, Ruth; Steinkasserer, Alexander; et al. (International Journal of Molecular Sciences, 2023)
Obesity is characterized by the expansion of the adipose tissue, usually accompanied by inflammation, with a prominent role of macrophages infiltrating the visceral adipose tissue (VAT). This chronic inflammation is a major driver of obesity-associated comorbidities. Four-and-a-half LIM-domain protein 2 (FHL2) is a multifunctional adaptor protein that is involved in the regulation of various biological functions and the maintenance of the homeostasis of different tissues. In this study, we aimed to gain new insights into the expression and functional role of FHL2 in VAT in diet-induced obesity. We found enhanced FHL2 expression in the VAT of mice with Western-type diet (WTD)-induced obesity and obese humans and identified macrophages as the cellular source of enhanced FHL2 expression in VAT. In mice with FHL2 deficiency (FHL2KO), WTD feeding resulted in reduced body weight gain paralleled by enhanced energy expenditure and uncoupling protein 1 (UCP1) expression, indicative of activated thermogenesis. In human VAT, FHL2 was inversely correlated with UCP1 expression. Furthermore, macrophage infiltration and the expression of the chemokine MCP-1, a known promotor of macrophage accumulation, was significantly reduced in WTD-fed FHL2KO mice compared with wild-type (wt) littermates. While FHL2 depletion did not affect the differentiation or lipid metabolism of adipocytes in vitro, FHL2 depletion in macrophages resulted in reduced expressions of MCP-1 and the neuropeptide Y (NPY). Furthermore, WTD-fed FHL2KO mice showed reduced NPY expression in VAT compared with wt littermates, and NPY expression was enhanced in VAT resident macrophages of obese individuals. Stimulation with recombinant NPY induced not only UCP1 expression and lipid accumulation but also MCP-1 expression in adipocytes. Collectively, these findings indicate that FHL2 is a positive regulator of NPY and MCP-1 expression in macrophages and herewith closely linked to the mechanism of obesity-associated lipid accumulation and inflammation in VAT. Thus, FHL2 appears as a potential novel target to interfere with the macrophage–adipocyte crosstalk in VAT for treating obesity and related metabolic disorders.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adipocytes; FHL2; macrophages; MCP-1; NPY; obesity; thermogenesis

Frequent occurrence of therapeutically reversible CMV-associated encephalopathy during radiotherapy of the brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Ruehle, Paul F.; Putz, Florian; Semrau, Sabine; et al. (Neuro-Oncology, 2016)
Neurological decline during radio(chemo)therapy of the brain is often attributed to disease progression or side effects of radiotherapy. Diagnosis of opportunistic neurotropic infections such as cytomegalovirus (CMV) infections is uncommon, even though high-grade gliomas and some brain metastases are known to contain CMV particles. We prospectively examined the frequency of CMV encephalopathy during radiotherapy of the brain.Fifty patients requiring whole-brain radiotherapy for brain metastases (n = 27) or local radio(chemo)therapy of the brain for high-grade gliomas (n = 23) were observed in the prospective observational GLIO-CMV-01 study. MRIs and blood samples were obtained before, halfway through, and at the end of radiotherapy. MRIs were screened for disease progression or increased intracranial pressure. Blood was tested for anti-CMV immunoglobulin (Ig)M, anti-CMV IgG, and CMV DNA.Thirty-two of 50 (64%) patients were positive for anti-CMV IgG before radio(chemo)therapy. Fifteen of those 32 (48%) developed viremia during or up to 28 days after treatment. Thirteen of those 15 (87%) required treatment for CMV-associated encephalopathy. MRIs were negative for disease progression, edema, or bleeding. None of the patients negative for anti-CMV IgG developed viremia, suggesting a reactivation rather than a primary infection.In the group at risk consisting of anti-CMV IgG+ patients, age >65 (P = .004) and the amount of dexamethasone taken during radio(chemo)therapy (P = .004) were associated with an increased risk for CMV-associated encephalopathy. One hundred and fifty days after the start of radio(chemo)therapy, survival was 74% (14/19) (no encephalopathy) versus 54% (7/13) (encephalopathy) (odds ratio, 0.42; 95% CI, 0.03-1.86; P = .25).CMV reactivation frequently causes encephalopathy during radio(chemo)therapy of the brain. The unexpected high incidence of this infection makes it highly clinically relevant for every treating physician.
EVALuna2:8306

Functionality of antigen-specific T cell receptor repertoires after SARS-CoV-2 vaccination - Kocher, Katharina; Drost, F.; Schuelein, C.; Moosmann, Carolin; D'Ippolito, E.; Busch, D. H.; Bogdan, Christian; Tenbusch, Matthias; Schubert, B.; Schober, Kilian (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Functional Relevance of the Interaction between Human Cyclins and the Cytomegalovirus-Encoded CDK-Like Protein Kinase pUL97 - Schütz, Martin; Steingruber, Mirjam; Socher, Eileen; Müller, Regina; Wagner, Sabrina; Kögel, Merle; Sticht, Heinrich; Marschall, Manfred (Viruses, 2021)
The replication of human cytomegalovirus (HCMV) is characterized by a complex network of virus–host interaction. This involves the regulatory viral protein kinase pUL97, which represents a viral cyclin-dependent kinase ortholog (vCDK) combining typical structural and functional features of host CDKs. Notably, pUL97 interacts with the three human cyclin types T1, H and B1, whereby the binding region of cyclin T1 and the region conferring oligomerization of pUL97 were both assigned to amino acids 231–280. Here, we addressed the question of whether recombinant HCMVs harboring deletions in this region were impaired in cyclin interaction, kinase functionality or viral replication. To this end, recombinant HCMVs were generated by traceless BACmid mutagenesis and were phenotypically characterized using a methodological platform based on qPCR, coimmunoprecipitation, in vitro kinase assay (IVKA), Phos-tag Western blot and confocal imaging analysis. Combined data illustrate the following: (i) infection kinetics of all three recombinant HCMVs, i.e., ORF-UL97 ∆231–255, ∆256–280 and ∆231–280, showed impaired replication efficiency compared to the wild type, amongst which the largest deletion exhibited the most pronounced defect; (ii) specifically, this mutant ∆231–280 showed a loss of interaction with cyclin T1, as demonstrated by CoIP and confocal imaging; (iii) IVKA and Phos-tag analyses revealed strongly affected kinase activity for ∆231–280, with strong impairment of both autophosphorylation and substrate phosphorylation, but less pronounced impairments for ∆231–255 and ∆256–280; and (iv) a bioinformatic assessment of the pUL97–cyclin T1 complex led to the refinement of our current binding model. Thus, the results provide initial evidence for the functional importance of the pUL97–cyclin interaction concerning kinase activity and viral replication fitness.<br
Keywords: human cytomegalovirus; virus-encoded kinase pUL97; viral CDK ortholog; interaction with human cyclin T1; replication-impaired viral mutants; defects in pUL97 activities; pUL97–cyclin functional importance

Futures Studies in Document Logistics – Vision of a paperless World? - von der Gracht, Heiko; Walter, Stephanie; Jahns, Christopher (Supply Chain Practice, 2007)

Galectin 3 expression in primary oral squamous cell carcinomas - Weber, Manuel; Buettner-Herold, Maike; Distel, Luitpold; Ries, Jutta; Möbius, Patrick; Preidl, Raimund; Geppert, Carol-Immanuel; Neukam, Friedrich Wilhelm; Wehrhan, Falk (BMC Cancer, 2017)
Immunologic factors can promote the progression of oral squamous cell carcinomas (oscc). The phylogenetic highly conserved protein Galectin 3 (Gal3) contributes to cell differentiation and immune homeostasis. There is evidence that Gal3 is involved in the progression of oscc and influences the regulation of macrophage polarization. Macrophage polarization (M1 vs. M2) in solid malignancies like oscc contributes to tumor immune-escape. However, the relationship between macrophage polarization and Gal3 expression in oscc is not yet understood. The current study analyzes the association between histomorphologic parameters (T-, N-, L- Pn-status, grading) and Gal3 expression resp. the ratio between Gal3 expressing cells and CD68 positive macrophages in oscc specimens.Preoperative diagnostic biopsies (n = 26) and tumor resection specimens (n = 34) of T1/T2 oscc patients were immunohistochemically analyzed for Gal3 and CD68 expression. The number of Gal3 expressing cells and the ratio between CD68 and Gal3 expressing cells was quantitatively assessed.In biopsy and tumor resection specimens, the number of Gal3 positive cells as well as the Gal3/CD68 ratio were significantly (p < 0.05) higher in T2 oscc compared to T1 cases. In biopsy specimens, a significantly (p < 0.05) increased Gal3 expression and Gal3/CD68 ratio was associated with the progression marker lymph vessel infiltration (L1). Tumor resection specimens of cases with lymph node metastases (N+) had a significantly (p < 0.05) increased Gal3 expression. Additionally, a high Gal3/CD68 ratio correlated significantly (p < 0.05) with higher grading (G3) in tumor resection specimens.High Gal3 expression in oscc is associated with tumor size (T-status) and parameters of malignancy (N-, L-status, grading). Gal3 might contribute to M2 macrophage mediated local immune tolerance. Gal3 expression shows association with prognosis in oscc and represent a potential therapeutic target.
EVALuna2:24446

Galectin 3 expression in regional lymph nodes and lymph node metastases of oral squamous cell carcinomas - Wehrhan, Falk; Büttner-Herold, Maike; Distel, Luitpold; Ries, Jutta; Möbius, Patrick; Preidl, Raimund; Geppert, Carol-Immanuel; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Weber, Manuel (BMC Cancer, 2018)
BACKGROUND: Neck dissection is standard in surgical management of oral squamous cell carcinomas (oscc). However, the immunologic link between primary tumor and lymph nodes is insufficiently understood. Galectin 3 (Gal3) promotes M2 polarization of macrophages and contributes to immunosuppression. The current study analyzes the association between Gal3 expression in regional lymph nodes of oscc with histomorphologic parameters (T-, N-, L- Pn-stage, grading) of the primary tumor. Additionally, Gal3 expression is correlated with markers of macrophage polarization (M1 vs. M2). METHODS: Preoperative diagnostic biopsies (n = 26), tumor resection specimens (n = 34), tumor-free lymph nodes (n = 28) and lymph node metastases (n = 10) of T1/T2 oscc patients were immunohistochemically analyzed for Gal3 and macrophage marker (CD68, CD11c, CD163 and MRC1) expression. The number of positive cells and the expression ratios were quantitatively assessed. RESULTS: High Gal3 expression in tumor-free regional lymph nodes was significantly (p < 0.05) associated with increased tumor size. The epithelial compartment of lymph node metastases showed a significantly (p < 0.05) increased Gal3 expression compared to biopsies and tumor resection specimens. Cell density of M2 macrophages was significantly (p < 0.05) and positively correlated with the number of Gal3 expressing cells in lymph nodes and tumor specimens. CONCLUSION: Gal3 expression in regional lymph nodes might be associated with oscc progression. The increased Gal3 expression in regional lymph nodes of larger tumors underlines the need of immunomodulatory treatment concepts in early-stage oscc. Blocking of Gal3 might be a therapeutic option in oral cancer.
EVALuna2:34900

Gammaherpesviral Tegument Proteins, PML-Nuclear Bodies and the Ubiquitin-Proteasome System - Full, Florian; Hahn, Alexander S.; Grosskopf, Anna K.; Enßer, Armin (Viruses, 2017)
Gammaherpesviruses like Epstein-Barr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (KSHV) subvert the ubiquitin proteasome system for their own benefit in order to facilitate viral gene expression and replication. In particular, viral tegument proteins that share sequence homology to the formylglycineamide ribonucleotide amidotransferase (FGARAT, or PFAS), an enzyme in the cellular purine biosynthesis, are important for disrupting the intrinsic antiviral response associated with Promyelocytic Leukemia (PML) protein-associated nuclear bodies (PML-NBs) by proteasome-dependent and independent mechanisms. In addition, all herpesviruses encode for a potent ubiquitin protease that can efficiently remove ubiquitin chains from proteins and thereby interfere with several different cellular pathways. In this review, we discuss mechanisms and functional consequences of virus-induced ubiquitination and deubiquitination for early events in gammaherpesviral infection.
EVALuna2:33753

Gene-dosage- and sex-dependent differences in the prodromal-Like phase of the F344tgHD rat model for Huntington disease - Ratz-Wirsching, Veronika; Habermeyer, Johanna; Moceri, Sandra; Harrer, Julia; Schmitz, Christoph; von Hörsten, Stephan (Frontiers in Neuroscience, 2024)
In Huntington disease (HD) the prodromal phase has been increasingly investigated and is currently in focus for early interventional treatments. Also, the influence of sex on disease progression and severity in patients is under discussion, as a sex-specific impact has been reported in transgenic rodent models for HD. To this end, we have been studying these aspects in Sprague Dawley rats transgenic for HD. Here, we took up on the congenic F344tgHD rat model, expressing a fragmented Htt construct with 51 CAG repeats on an inbred F344 rat background and characterized potential sexual dimorphism and gene-dosage effects in rats during the pre-symptomatic phase (1–8 months of age). Our study comprises a longitudinal phenotyping of motor function, emotion and sensorimotor gating, as well as screening of metabolic parameters with classical and automated assays in combination with investigation of molecular HD hallmarks (striatal cell number and volume estimation, appearance of HTT aggregates). Differences between sexes became apparent during middle age, particularly in the motor and sensorimotor domains. Female individuals were generally more active, demonstrated different gait characteristics than males and less anxiolytic-like behavior. Alterations in both the time course and affected behavioral domains varied between male and female F344tgHD rats. First subtle behavioral anomalies were detected in transgenic F344tgHD rats prior to striatal MSN cell loss, revealing a prodromal-like phase in this model. Our findings demonstrate that the congenic F344tgHD rat model shows high face-validity, closely resembling the human disease’s temporal progression, while having a relatively low number of CAG repeats, a slowly progressing pathology with a prodromal-like phase and a comparatively subtle phenotype. By differentiating the sexes regarding HD-related changes and characterizing the prodromal-like phase in this model, these findings provide a foundation for future treatment studies.
CRIS-Team Scopus Importer:2024-03-01
Keywords: behavioral phenotyping; gene-dosage; Huntington disease; prodrome; sex differences; striatal atrophy

Generation of a Gaussia luciferase-expressing endotheliotropic cytomegalovirus for screening approaches and mutant analyses - Falk, Jessica J.; Sampaio, Kerstin Laib; Stegmann, Cora; Lieber, Diana; Kropff, Barbara; Mach, Michael; Sinzger, Christian (Journal of Virological Methods, 2016)
For many questions in human cytomegalovirus (HCMV) research, assays are desired that allow robust and fast quantification of infection efficiencies under high-throughput conditions. The secreted Gaussia luciferase has been demonstrated as a suitable reporter in the context of a fibroblast-adapted HCMV strain, which however is greatly restricted in the number of cell types to which it can be applied. We inserted the Gaussia luciferase expression cassette into the BAC-cloned virus strain TB40-BAC4, which displays the natural broad cell tropism of HCMV and hence allows application to screening approaches in a variety of cell types including fibroblasts, epithelial, and endothelial cells. Here, we applied the reporter virus TB40-BAC4-IE-GLuc to identify mouse hybridoma clones that preferentially neutralize infection of endothelial cells. In addition, as the Gaussia luciferase is secreted into culture supernatants from infected cells it allows kinetic analyses in living cultures. This can speed up and facilitate phenotypic characterization of BAC-cloned mutants. For example, we analyzed a UL74 stop-mutant of TB40-BAC4-IE-GLuc immediately after reconstitution in transfected cultures and found the increase of luciferase delayed and reduced as compared to wild type. Phenotypic monitoring directly in transfected cultures can minimize the risk of compensating mutations that might occur with extended passaging.
EVALuna2:8325

Generation of an oncolytic herpes simplex virus 1 expressing human MelanA - Boscheinen, Jan; Thomann, Sabrina; Knipe, David M.; Deluca, Neal; Schuler-Thurner, Beatrice; Gross, Stefanie; Dörrie, Jan; Schaft, Niels; Bach, Christian; Rohrhofer, Anette; Werner-Klein, Melanie; Schmidt, Barbara; et al. (Frontiers in Immunology, 2019)
Robust anti-tumor immunity requires innate as well as adaptive immune responses. We have shown that plasmacytoid dendritic cells develop killer cell-like activity in melanoma cell cocultures after exposure to the infectious but replication-deficient herpes simplex virus 1 (HSV-1) d106S. To combine this innate effect with an enhanced adaptive immune response, the gene encoding human MelanA/MART-1 was inserted into HSV-1 d106S via homologous recombination to increase direct expression of this tumor antigen. Infection of Vero cells using this recombinant virus confirmed MelanA expression by Western blotting, flow cytometry, and immunofluorescence. HSV-1 d106S-MelanA induced expression of the transgene in fibroblast and melanoma cell lines not naturally expressing MelanA. Infection of a melanoma cell line with CRISPR-Cas9-mediated knockout of MelanA confirmed de novo expression of the transgene in the viral context. Dependent on MelanA expression, infected fibroblast and melanoma cell lines induced degranulation of HLA-matched MelanA-specific CD8+ T cells, followed by killing of infected cells. To study infection of immune cells, we exposed peripheral blood mononuclear cells and in vitro-differentiated macrophages to the parental HSV-1 d106S, resulting in expression of the transgene GFP in CD11c+ cells and macrophages. These data provide evidence that the application of MelanA-encoding HSV-1 d106S could enhance adaptive immune responses and re-direct MelanA-specific CD8+ T cells to tumor lesions, which have escaped adaptive immune responses via downregulation of their tumor antigen. Hence, HSV-1 d106S-MelanA harbors the potential to induce innate immune responses in conjunction with adaptive antitumor responses by CD8+ T cells, which should be evaluated in further studies.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Cytotoxic T cell response; Herpes virus; Malignant melanoma; Oncolytic viruses; Vaccine

Generation of T follicular helper cells in vitro: requirement for B-cell receptor cross-linking and cognate B- and T-cell interaction - Kolenbrander, Anne; Grewe, Bastian; Nemazee, David; Überla, Klaus; Temchura, Vladimir (Immunology, 2018)
The minimum requirements for invitro modelling of natural CD4(+) T-cell differentiation into T follicular helper (Tfh) cells are still under investigation. We co-cultured wild-type and T-cell receptor (TCR) transgenic CD4(+) T cells from naive mice with dendritic cells and B-cell receptor (BCR) transgenic B cells in the presence of HIV-derived virus-like particles containing matched B-cell and T-cell epitopes. This co-culturing induced co-expression of Tfh-master regulator transcription factor BCL-6 and CXCR5 in up to 10% of the wild-type and up to 40% of the TCR-transgenic CD4(+) T cells. Phenotypic markers, production of interleukin-21 and isotype switching of the B cells to IgG1 further indicated a helper function of the induced Tfh cells invitro. Dendritic cells supported the generation of functional Tfh cells, but were unable to induce them without cognate B cells. Hence, our study presents a robust experimental system for efficient generation of functionally active Tfh cells invitro and confirms the importance of cognate B- and T-cell cross-talk for the Tfh differentiation process.
EVALuna2:35291

Genetic co-administration of soluble PD-1 ectodomains modifies immune responses against influenza a virus induced by DNA vaccination - Tannig, Pierre; Peter, Antonia Sophia; Lapuente, Dennis; Klessing, Stephan; Schmidt, Anna; Damm, Dominik; Tenbusch, Matthias; Überla, Klaus; Temchura, Vladimir (Vaccines, 2020)
Due to the low efficacy and the need for seasonal adaptation of currently licensed influenza A vaccines, the importance of alternative vaccination strategies is increasingly recognized. Considering that DNA vaccines can be rapidly manufactured and readily adapted with novel antigen sequences, genetic vaccination is a promising immunization platform. However, the applicability of different genetic adjuvants to this approach still represents a complex challenge. Immune checkpoints are a class of molecules involved in adaptive immune responses and germinal center reactions. In this study, we immunized mice by intramuscular electroporation with a DNA-vaccine encoding hemagglutinin (HA) and nucleoprotein (NP) of the influenza A virus. The DNA-vaccine was applied either alone or in combination with genetic adjuvants encoding the soluble ectodomains of programmed cell death protein-1 (sPD-1) or its ligand (sPD-L1). Co-administration of genetic checkpoint adjuvants did not significantly alter immune responses against NP. In contrast, sPD-1 co-electroporation elevated HA-specific CD4+ T cell responses, decreased regulatory CD4+ T cell pools, and modulated the IgG2a-biased HA antibody pattern towards an isotype-balanced IgG response with a trend to higher influenza neutralization in vitro. Taken together, our data demonstrate that a genetic DNA-adjuvant encoding soluble ectodomains of sPD-1 was able to modulate immune responses induced by a co-administered influenza DNA vaccine.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Checkpoint blockade; DNA adjuvants; DNA vaccine; Immunomodulation; Influenza A; Intramuscular electroporation; Soluble PD-1; Soluble PD-L1

GLIO-CMV-01: Identification of immune biomarkers for CMV-related encephalitis during radiotherapy of the brain - Donaubauer, Anna-Jasmina; Becker, I.; Rühle, Paul-Friedrich; Goerig, Nicole; Pohn, A.; Winkler, Thomas; Korn, Klaus; Überla, Klaus; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36498

GLIO-CMV-01: Identification of immune biomarkers for CMV related encephalitis during standard brain radiotherapy - Rühle, Paul-Friedrich; Goerig, Nicole; Korn, Klaus; Überla, Klaus; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2017)
EVALuna2:32892

Glutamic Acid Residues in HIV-1 p6 Regulate Virus Budding and Membrane Association of Gag - Friedrich, Melanie; Setz, Christian; Hahn, Friedrich; Matthaei, Alina; Fraedrich, Kirsten; Rauch, Pia; Henklein, Petra; Traxdorf, Maximilian; Fossen, Torgils; Schubert, Ulrich (Viruses, 2016)
The HIV-1 Gag p6 protein regulates the final abscission step of nascent virions from the cell membrane by the action of its two late (L-) domains, which recruit Tsg101 and ALIX, components of the ESCRT system. Even though p6 consists of only 52 amino acids, it is encoded by one of the most polymorphic regions of the HIV-1 gag gene and undergoes various posttranslational modifications including sumoylation, ubiquitination, and phosphorylation. In addition, it mediates the incorporation of the HIV-1 accessory protein Vpr into budding virions. Despite its small size, p6 exhibits an unusually high charge density. In this study, we show that mutation of the conserved glutamic acids within p6 increases the membrane association of Pr55 Gag followed by enhanced polyubiquitination and MHC-I antigen presentation of Gag-derived epitopes, possibly due to prolonged exposure to membrane bound E3 ligases. The replication capacity of the total glutamic acid mutant E0A was almost completely impaired, which was accompanied by defective virus release that could not be rescued by ALIX overexpression. Altogether, our data indicate that the glutamic acids within p6 contribute to the late steps of viral replication and may contribute to the interaction of Gag with the plasma membrane.
EVALuna2:8333

Glycoprotein N subtypes of human cytomegalovirus induce a strain-specific antibody response during natural infection - Burkhardt, Christiane; Himmelein, Susanne; Britt, William; Winkler, Thomas; Mach, Michael (Journal of General Virology, 2009)
Human cytomegalovirus (HCMV) encodes several highly polymorphic envelope glycoproteins; however, the biological relevance of this polymorphism is unclear. Glycoprotein N (gN) is one member of this polymorphic protein family. Four major gN genotypes (gN1-4) have been identified. We have tested the hypothesis that the gN polymorphism represents a mechanism to evade a neutralizing antiviral antibody response. Four recombinant viruses that differed only in the expression of the gN genotype were constructed on the genetic background of HCMV strain AD169. Exchange of gN genotypes had a minor detectable influence on virus replication, gN expression and gN-gM complex formation. Randomly selected human sera were analysed for neutralizing activity against the recombinant viruses. Of these, 70% showed no difference in neutralizing titre between the viruses, whereas 30% showed strain-specific neutralization. Differences in 50% neutralization titre reached >8-fold. Viruses expressing the gN4 genotype were neutralized significantly better than those expressing the other gN genotypes. Strain specificity, or lack thereof, could not be attributed to the presence or absence of anti-gN antibodies, as all sera contained antibodies reacting with gN (as determined by ELISA). Thus, polymorphism of gN could contribute to evasion of an efficient neutralizing-antibody response and facilitate reinfection in previously seropositive individuals. © 2009 SGM.

Glycosylation of HIV Env Impacts IgG Subtype Responses to Vaccination - Hess, Rebecca; Bonsmann, Michael Storcksdieck Genannt; Lapuente, Dennis; Maaske, Andre; Kirschning, Carsten; Ruland, Juergen; Lepenies, Bernd; Hannaman, Drew; Tenbusch, Matthias; Überla, Klaus (Viruses, 2019)
The envelope protein (Env) is the only surface protein of the human immunodeficiency virus (HIV) and as such the exclusive target for protective antibody responses. Experimental evidences from mouse models suggest a modulating property of Env to steer antibody class switching towards the less effective antibody subclass IgG1 accompanied with strong TH2 helper responses. By simple physical linkage we were able to imprint this bias, exemplified by a low IgG2a/IgG1 ratio of antigen-specific antibodies, onto an unrelated antigen, namely the HIV capsid protein p24. Here, our results indicate the glycan moiety of Env as the responsible immune modulating activity. Firstly, in Card9(-/-) mice lacking specific C-Type lectin responsiveness, DNA immunization significantly increased the IgG2a/IgG1 ratio for the Env-specific antibodies while the antibody response against the F-protein of the respiratory syncytial virus (RSV) serving as control antigen remained unchanged. Secondly, sequential shortening of the Env encoding sequence revealed the C2V3 domain as responsible for the strong IgG1 responses and TH2 cytokine production. Removing all potential N-glycosylation sites from the C2V3 domain by site-specific mutagenesis reversed the vaccine-induced immune response towards a Th1-dominated T-cell response and a balanced IgG2a/IgG1 ratio. Accordingly, the stretch of oligomannose glycans in the C2V3 domain of Env might mediate a specific uptake and/or signaling modus in antigen presenting cells by involving interaction with an as yet unknown C-type lectin receptor. Our results contribute to a deeper understanding of the impact of Env glycosylation on HIV antigen-specific immune responses, which will further support HIV vaccine development.
CRIS-Team WoS Importer:2019-03-22

Gut as viral reservoir: Lessons from gut viromes, HIV and COVID-19 - Neurath, Markus; Überla, Klaus; Ng, Siew C. (Gut, 2021)
CRIS-Team Scopus Importer:2021-05-07
Keywords: immunology

Gut-to-brain spreading of pathology in synucleinopathies: A focus on molecular signalling mediators - Schmitt, Verena; Masanetz, Rebecca Katharina; Weidenfeller, Martin; Ebbinghaus, Lara Savannah; Süß, Patrick; Rosshart, Stephan Patrick; von Hörsten, Stephan; Zunke, Friederike; Winkler, Jürgen; Xiang, Wei (Behavioural Brain Research, 2023)
Synucleinopathies are a group of neurodegenerative disorders, classically characterized by the accumulation of aggregated alpha synuclein (aSyn) in the central nervous system. Parkinson's disease (PD) and multiple system atrophy (MSA) are the two prominent members of this family. Current treatment options mainly focus on the motor symptoms of these diseases. However, non-motor symptoms, including gastrointestinal (GI) symptoms, have recently gained particular attention, as they are frequently associated with synucleinopathies and often arise before motor symptoms. The gut-origin hypothesis has been proposed based on evidence of an ascending spreading pattern of aggregated aSyn from the gut to the brain, as well as the comorbidity of inflammatory bowel disease and synucleinopathies. Recent advances have shed light on the mechanisms underlying the progression of synucleinopathies along the gut-brain axis. Given the rapidly expanding pace of research in the field, this review presents a summary of the latest findings on the gut-to-brain spreading of pathology and potential pathology-reinforcing mediators in synucleinopathies. Here, we focus on 1) gut-to-brain communication pathways, including neuronal pathways and blood circulation, and 2) potential molecular signalling mediators, including bacterial amyloid proteins, microbiota dysbiosis-induced alterations in gut metabolites, as well as host-derived effectors, including gut-derived peptides and hormones. We highlight the clinical relevance and implications of these molecular mediators and their possible mechanisms in synucleinopathies. Moreover, we discuss their potential as diagnostic markers in distinguishing the subtypes of synucleinopathies and other neurodegenerative diseases, as well as for developing novel individualized therapeutic options for synucleinopathies.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Alpha synuclein; Gut-to-brain communication; Inflammatory bowel disease; Multiple system atrophy; Parkinson's disease

HDAC inhibitors Panobinostat and Romidepsin enhance tax transcription in HTLV-1-infected cell lines and freshly isolated patients' T-cells - Schnell, Annika; Kohrt, Stephan; Aristodemou, Aris; Taylor, Graham P.; Bangham, Charles R. M.; Thoma-Kreß, Andrea (Frontiers in Immunology, 2022)
The viral transactivator Tax plays a key role in HTLV-1 reactivation and de novo infection. Previous approaches focused on the histone deacetylase inhibitor (HDACi) Valproate as a latency-reversing agent to boost Tax expression and expose infected cells to the host's immune response. However, following treatment with Valproate proviral load decreases in patients with HAM/TSP were only transient. Here, we hypothesize that other compounds, including more potent and selective HDACi, might prove superior to Valproate in manipulating Tax expression. Thus, a panel of HDACi (Vorinostat/SAHA/Zolinza, Panobinostat/LBH589/Farydak, Belinostat/PXD101/Beleodaq, Valproate, Entinostat/MS-275, Romidepsin/FK228/Istodax, and MC1568) was selected and tested for toxicity and potency in enhancing Tax expression. The impact of the compounds was evaluated in different model systems, including transiently transfected T-cells, chronically HTLV-1-infected T-cell lines, and freshly isolated PBMCs from HTLV-1 carriers ex vivo. We identified the pan-HDACi Panobinostat and class I HDACi Romidepsin as particularly potent agents at raising Tax expression. qRT-PCR analysis revealed that these inhibitors considerably boost tax and Tax-target gene transcription. However, despite this significant increase in tax transcription and histone acetylation, protein levels of Tax were only moderately enhanced. In conclusion, these data demonstrate the ability of Panobinostat and Romidepsin to manipulate Tax expression and provide a foundation for further research into eliminating latently infected cells. These findings also contribute to a better understanding of conditions limiting transcription and translation of viral gene products.
CRIS-Team WoS Importer:2022-09-16

Herpes simplex virus encephalitis after temporal lobe resection: an infrequent but treatable complication of epilepsy surgery - Martínez-Poles, J.; Toledano, R.; Aledo-Serrano,; Korn, Klaus; Coras, Roland; Blümcke, Ingmar; García-Morales, I.; Álvarez-Linera, J.; Gil-Nagel, A. (European Journal of Neurology, 2020)
CRIS-Team Scopus Importer:2020-09-11
Keywords: clinical and diagnostic investigations; encephalitis; epilepsy; imaging; infections; magnetic resonance imaging (MRI); management; neurological disorders; surgery

Heterologous prime–boost vaccination with ChAdOx1 nCoV-19 and BNT162b2 - Tenbusch, Matthias; Schumacher, Sofie; Vogel, Emanuel; Priller, Alina; Held, Jürgen; Steininger, Philipp; Beileke, Stephanie; Irrgang, Pascal; Brockhoff, Ronja; Salmanton-García, Jon; Tinnefeld, Kathrin; Mijocevic, Hrvoje; et al. (Lancet Infectious Diseases, 2021)
CRIS-Team Scopus Importer:2021-09-10

Higher Infection Risk among Health Care Workers and Lower Risk among Smokers Persistent across SARS-CoV-2 Waves-Longitudinal Results from the Population-Based TiKoCo Seroprevalence Study - Guenther, Felix; Einhauser, Sebastian; Peterhoff, David; Wiegrebe, Simon; Niller, Hans Helmut; Beileke, Stephanie; Steininger, Philipp; Burkhardt, Ralph; Kuechenhoff, Helmut; Gefeller, Olaf; Überla, Klaus; Heid, Iris M.; et al. (International Journal of Environmental Research and Public Health, 2022)
SARS-CoV-2 seroprevalence was reported as substantially increased in medical personnel and decreased in smokers after the first wave in spring 2020, including in our population-based Tirschenreuth Study (TiKoCo). However, it is unclear whether these associations were limited to the early pandemic and whether the decrease in smokers was due to reduced infection or antibody response. We evaluated the association of occupation and smoking with period-specific seropositivity: for the first wave until July 2020 (baseline, BL), the low infection period in summer (follow-up 1, FU1, November 2020), and the second/third wave (FU2, April 2021). We measured binding antibodies directed to SARS-CoV-2 nucleoprotein (N), viral spike protein (S), and neutralizing antibodies at BL, FU1, and FU2. Previous infection, vaccination, smoking, and occupation were assessed by questionnaires. The 4181 participants (3513/3374 at FU1/FU2) included 6.5% medical personnel and 20.4% current smokers. At all three timepoints, new seropositivity was higher in medical personnel with ORs = 1.99 (95%-CI = 1.36-2.93), 1.41 (0.29-6.80), and 3.17 (1.92-5.24) at BL, FU1, and FU2, respectively, and nearly halved among current smokers with ORs = 0.47 (95%-CI = 0.33-0.66), 0.40 (0.09-1.81), and 0.56 (0.33-0.94). Current smokers compared to never-smokers had similar antibody levels after infection or vaccination and reduced odds of a positive SARS-CoV-2 result among tested. Our data suggest that decreased seroprevalence among smokers results from fewer infections rather than reduced antibody response. The persistently higher infection risk of medical staff across infection waves, despite improved means of protection over time, underscores the burden for health care personnel.
CRIS-Team WoS Importer:2023-01-13

Highly Conserved Interaction Profiles between Clinically Relevant Mutants of the Cytomegalovirus CDK-like Kinase pUL97 and Human Cyclins: Functional Significance of Cyclin H - Schütz, Martin; Müller, Regina; Socher, Eileen; Wangen, Christina; Full, Florian; Wyler, Emanuel; Wong, Diana D.; Scherer, Myriam; Stamminger, Thomas; Chou, Sunwen; Rawlinson, William D.; Hamilton, Stuart T.; et al. (International Journal of Molecular Sciences, 2022)
The complex host interaction network of human cytomegalovirus (HCMV) involves the regulatory protein kinase pUL97, which represents a viral cyclin-dependent kinase (CDK) ortholog. pUL97 interacts with the three human cyclin types T1, H, and B1, whereby the binding region of cyclin T1 and the pUL97 oligomerization region were both assigned to amino acids 231-280. We further addressed the question of whether HCMVs harboring mutations in ORF-UL97, i.e., short deletions or resistance-conferring point mutations, are affected in the interaction with human cyclins and viral replication. To this end, clinically relevant UL97 drug-resistance-conferring mutants were analyzed by whole-genome sequencing and used for genetic marker transfer experiments. The recombinant HCMVs indicated conservation of pUL97–cyclin interaction, since all viral UL97 point mutants continued to interact with the analyzed cyclin types and exerted wild-type-like replication fitness. In comparison, recombinant HCMVs UL97 Δ231-280 and also the smaler deletion Δ236-275, but not Δ241-270, lost interaction with cyclins T1 and H, showed impaired replication efficiency, and also exhibited reduced kinase activity. Moreover, a cellular knock-out of cyclins B1 or T1 did not alter HCMV replication phenotypes or pUL97 kinase activity, possibly indicating alternative, compensatory pUL97–cyclin interactions. In contrast, however, cyclin H knock-out, similar to virus deletion mutants in the pUL97–cyclin H binding region, exhibited strong defective phenotypes of HCMV replication, as supported by reduced pUL97 kinase activity in a cyclin H-dependent coexpression setting. Thus, cyclin H proved to be a very relevant determinant of pUL97 kinase activity and viral replication efficiency. As a conclusion, the results provide evidence for the functional importance of pUL97–cyclin interaction. High selective pressure on the formation of pUL97–cyclin complexes was identified by the use of clinically relevant mutants<br

Highly potent artemisinin-derived dimers and trimers: Synthesis and evaluation of their antimalarial, antileukemia and antiviral activities. - Reiter, Christoph; Fröhlich, Tony; Gruber, Lisa; Hutterer, Corina; Marschall, Manfred; Voigtländer, Cornelia; Friedrich, Oliver; Kappes, Bärbel; Efferth, Thomas; Tsogoeva, Svetlana (Bioorganic & medicinal chemistry, 2015)
New pharmaceutically active compounds can be obtained by modification of existing drugs to access more effective agents in the wake of drug resistance amongst others. To achieve this goal the concept of hybridization was established during the last decade. We employed this concept by coupling two artemisinin-derived precursors to obtain dimers or trimers with increased in vitro activity against Plasmodiumfalciparum 3D7 strain, leukemia cells (CCRF-CEM and multidrug-resistant subline CEM/ADR5000) and human cytomegalovirus (HCMV). Dimer 4 (IC50 of 2.6nM) possess superior antimalarial activity compared with its parent compound artesunic acid(3) (IC50 of 9.0nM). Dimer5 and trimers6 and 7 display superior potency against both leukemia cell lines (IC50 up to 0.002μM for CCRF-CEM and IC50 up to 0.20μM for CEM/ADR5000) and are even more active than clinically used doxorubicin (IC50 1.61μM for CEM/ADR5000). With respect to anti-HCMV activity, trimer6 is the most efficient hybrid (IC50 0.04μM) outperforming ganciclovir (IC50 2.6μM), dihydroartemisinin(IC50 >10μM) and artesunic acid (IC50 3.8μM).
Keywords: Artemisinin-derived hybrids; Artemisinin-derived dimers; Artemisinin-derived trimers; Antimalarial activity; Anticancer activity; Antiviral activity

High-resolution crystal structures of two prototypical β- And γ-herpesviral nuclear egress complexes unravel the determinants of subfamily specificity - Muller, Yves; Häge, Sigrun; Alkhashrom, Sewar; Höllriegl, Tobias; Weigert, Sebastian; Dolles, Simon; Hof, Kerstin; Walzer, Sascha; Egerer-Sieber, Claudia; Conrad, Marcus; Holst, Stephanie; Lösing, Josephine; et al. (Journal of Biological Chemistry, 2020)
Herpesviruses uniquely express two essential nuclear egress-regulating proteins forming a heterodimeric basic structure of the nuclear egress complex (core NEC). These core NECs serve as a hexameric lattice-structured platform for capsid docking and recruit viral and cellular NEC-associated factors that jointly exert nuclear lamina- and membrane-rearranging functions (multicomponent NEC). Here, we report the X-ray structures of β- and γ-herpesvirus core NECs obtained through an innovative recombinant expression strategy based on NEC-hook::NEC-groove protein fusion constructs. This approach yielded the first structure of γ-herpesviral core NEC, namely the 1.56 Å structure of Epstein-Barr virus (EBV) BFRF1-BFLF2, as well as an increased resolution 1.48 Å structure of human cytomegalovirus (HCMV) pUL50-pUL53. Detailed analysis of these structures revealed that the prominent hook segment is absolutely required for core NEC formation and contributes approximately 80% of the interaction surface of the globular domains of NEC proteins. Moreover, using HCMV::EBV hook domain swap constructs, computational prediction of the roles of individual hook residues for binding, and quantitative binding assays with synthetic peptides presenting the HCMV- and EBV-specific NEC hook sequences, we characterized the unique hook-into-groove NEC interaction at various levels. Although the overall physicochemical characteristics of the protein interfaces differ considerably in these β- and γ-herpesvirus NECs, the binding free energy contributions of residues displayed from identical positions are similar. In summary, the results of our study reveal critical details of the molecular mechanism of herpesviral NEC interactions and highlight their potential as an antiviral drug target.
CRIS-Team Scopus Importer:2020-03-17

High throughput screening of gene functions in mammalian cells using reversely transfected cell arrays: review and protocol. - Stürzl, Michael; Konrad, Andreas; Sander, Gaby; Wies, Effi; Neipel, Frank; Naschberger, Elisabeth; Reipschlaeger, Simone; Gonin-Laurent, Nathalie; Horch, Raymund E.; Kneser, Ulrich; Hohenberger, Werner; Erfle, Holger; et al. (Combinatorial Chemistry & High Throughput Screening, 2008)
Reversely transfected cell microarrays (RTCM) have been introduced as a method for parallel high throughput analysis of gene functions in mammalian cells. Hundreds to thousands of different recombinant DNA or RNA molecules can be transfected into different cell clusters at the same time on a single glass slide with this method. This allows either the simultaneous overexpression or–by using the recently developed RNA interference (RNAi) techniques–knockdown of a huge number of target genes. A growing number of sophisticated detection systems have been established to determine quantitatively the effects of the transfected molecules on the cell phenotype. Several different cell types have been successfully used for this procedure. This review summarizes the presently available knowledge on this technique and provides a laboratory protocol.

HIV-1 fusion is blocked through binding of GB Virus C E2D peptides to the HIV-1 gp41 disulfide loop - Eißmann, Kristin; Müller, Sebastian; Sticht, Heinrich; Jung, Susan; Zou, Peng; Jiang, Shibo; Gross, Andrea; Eichler, Jutta; Fleckenstein, Bernhard; Reil, Heide (PLoS ONE, 2013)
A strategy for antiviral drug discovery is the elucidation and imitation of viral interference mechanisms. HIV-1 patients benefit from a coinfection with GB Virus C (GBV-C), since HIV-positive individuals with long-term GBV-C viraemia show better survival rates than HIV-1 patients without persisting GBV-C. A direct influence of GBV-C on HIV-1 replication has been shown in coinfection experiments. GBV-C is a human non-pathogenic member of the flaviviridae family that can replicate in T and B cells. Therefore, GBV-C shares partly the same ecological niche with HIV-1. In earlier work we have demonstrated that recombinant glycoprotein E2 of GBV-C and peptides derived from the E2 N-terminus interfere with HIV entry. In this study we investigated the underlying mechanism. Performing a virus-cell fusion assay and temperature-arrested HIV-infection kinetics, we provide evidence that the HIV-inhibitory E2 peptides interfere with late HIV-1 entry steps after the engagement of gp120 with CD4 receptor and coreceptor. Binding and competition experiments revealed that the N-terminal E2 peptides bind to the disulfide loop region of HIV-1 transmembrane protein gp41. In conjunction with computational analyses, we identified sequence similarities between the N-termini of GBV-C E2 and the HIV-1 glycoprotein gp120. This similarity appears to enable the GBV-C E2 N-terminus to interact with the HIV-1 gp41 disulfide loop, a crucial domain involved in the gp120-gp41 interface. Furthermore, the results of the present study provide initial proof of concept that peptides targeted to the gp41 disulfide loop are able to inhibit HIV fusion and should inspire the development of this new class of HIV-1 entry inhibitors.
EVALuna2:8190

HIV-1 mRNA electroporation of PBMC: A simple and efficient method to monitor T-cell responses against autologous HIV-1 in HIV-1-infected patients - Etschel, Jennifer K.; Hueckelhoven, Angela G.; Hofmann, Christian; Zitzelsberger, Kathrin; Maurer, Katja; Bergmann, Silke; Müller-Schmucker, Sandra; Wittmann, Jürgen; Spriewald, Bernd; Dörrie, Jan; Schaft, Niels; Harrer, Thomas (Journal of Immunological Methods, 2012)
Efficient monitoring of HIV-1-specific T-cells is crucial for the development of HIV-1 vaccines and immunotherapies. Currently, mainly peptides and vaccinia vectors are used for detection of HIV-1-specific cytotoxic T-lymphocytes (CTL), however, as HIV-1 is a variable virus, it is unknown to what extent the T-cell response against the autologous virus is under- or overestimated by using antigens from heterologous viral strains. Therefore, we established a new method for immunomonitoring of CTL using electroporation of peripheral blood mononuclear cells (PBMC) with mRNA derived from autologous viral strains. From six HIV-1-infected patients virus derived mRNA was produced after PCR-based cloning of autologous gag (n = 5) and/or nef genes (n = 3) from plasma and electroporated into PBMC from patients and healthy donors. Electroporation of PBMC with mRNA resulted in efficient protein expression with good induction of γ-interferon (γ-IFN) release by specific T-cells comparable to peptide pools and better than recombinant vaccinia viruses. Three mRNA encoded autologous Gag proteins and one autologous mRNA encoded Nef protein were better recognized by autologous PBMC in comparison to heterologous mRNA encoded Gag or Nef proteins (SF2 or HXB2). However, in one case each, mRNA encoded autologous Gag or Nef, respectively, was recognized less efficiently due to the presence of CTL escape mutations. In summary, electroporation of PBMC with mRNA is a very efficient, easy and rapid method for immunomonitoring of HIV-1-specific T-cell responses against autologous viral strains. Our data demonstrate that patients' CTL responses against autologous viral strains may be under- or overestimated by using antigens from heterologous viral strains. © 2012 Elsevier B.V.
CRIS-Team Scopus Importer:2021-10-01
Keywords: CTL; HIV-1; Immunomonitoring; MRNA electroporation

HIV-1 neutralizing antibodies provide sterilizing immunity by blocking infection of the first cells - Stab, Viktoria; Stahl-Hennig, Christiane; Enßer, Armin; Richel, Elie; Fraedrich, Kirsten; Sauermann, Ulrike; Tippler, Bettina; Klein, Florian; Burton, Dennis R.; Tenbusch, Matthias; Überla, Klaus (Cell Reports Medicine, 2023)
Neutralizing antibodies targeting HIV-1 Env have been shown to protect from systemic infection. To explore whether these antibodies can inhibit infection of the first cells, challenge viruses based on simian immunodeficiency virus (SIV) were developed that use HIV-1 Env for entry into target cells during the first replication cycle, but then switch to SIV Env usage. Antibodies binding to Env of HIV-1, but not SIV, block HIV-1 Env-mediated infection events after rectal exposure of non-human primates to the switching challenge virus. After natural exposure to HIV-1, such a reduction of the number of first infection events should be sufficient to provide sterilizing immunity in the strictest sense in most of the exposed individuals. Since blocking infection of the first cells avoids the formation of latently infected cells and reduces the risk of emergence of antibody-resistant mutants, it may be the best mode of protection.
CRIS-Team Scopus Importer:2023-10-20
Keywords: AIDS; Fc-effector function; HIV; mucosal immunity; neutralizing antibody; sterilizing immunity

HIV-1 Viral Protein R Couples Metabolic Inflexibility With White Adipose Tissue Thermogenesis - Agarwal, Neeti; Iyer, Dinakar; Saha, Pradip; Cox, Aaron R.; Xia, Yan; Utay, Netanya S.; Somasundaram, Anoma; Schubert, Ulrich; Lake, Jordan E.; Hartig, Sean M.; Balasubramanyam, Ashok (Diabetes, 2021)
Persons living with HIV (PLWH) manifest chronic disorders of brown and white adipose tissues that lead to diabetes and metabolic syndrome. The mechanisms that link viral factors to defective adipose tissue function and abnormal energy balance in PLWH remain incompletely understood. Here, we explored how the HIV accessory protein viral protein R (Vpr) contributes to adaptive thermogenesis in two mouse models and human adipose tissues. Uncoupling protein 1 (UCP1) gene expression was strongly increased in subcutaneous white adipose tissue (WAT) biopsy specimens from PLWH and in subcutaneous WAT of the Vpr mice, with nearly equivalent mRNA copy number. Histology and functional studies confirmed beige transformation in subcutaneous but not visceral WAT in the Vpr mice. Measurements of energy balance indicated Vpr mice displayed metabolic inflexibility and could not shift efficiently from carbohydrate to fat metabolism during day-night cycles. Furthermore, Vpr mice showed a marked inability to defend body temperature when exposed to 4 degrees C. Importantly, Vpr couples higher tissue catecholamine levels with UCP1 expression independent of beta -adrenergic receptors. Our data reveal surprising deficits of adaptive thermogenesis that drive metabolic inefficiency in HIV-1 Vpr mouse models, providing an expanded role for viral factors in the pathogenesis of metabolic disorders in PLWH.
CRIS-Team WoS Importer:2021-10-22

HIV-1 viral protein R (Vpr) induces fatty liver in mice via LXRα and PPARα dysregulation: implications for HIV-specific pathogenesis of NAFLD - Agarwal, Neeti; Iyer, Dinakar; Gabbi, Chiara; Saha, Pradip; Patel, Sanjeet G; Mo, Qianxing; Chang, Benny; Goswami, Biman; Schubert, Ulrich; Kopp, Jeffrey B.; Lewis, Dorothy E; Balasubramanyam, Ashok (Scientific Reports, 2017)
HIV patients develop hepatic steatosis. We investigated hepatic steatosis in transgenic mice expressing the HIV-1 accessory protein Vpr (Vpr-Tg) in liver and adipose tissues, and WT mice infused with synthetic Vpr. Vpr-Tg mice developed increased liver triglyceride content and elevated ALT, bilirubin and alkaline phosphatase due to three hepatic defects: 1.6-fold accelerated de novo lipogenesis (DNL), 45% slower fatty acid ß-oxidation, and 40% decreased VLDL-triglyceride export. Accelerated hepatic DNL was due to coactivation by Vpr of liver X receptor-α (LXRα) with increased expression of its lipogenic targets Srebp1c, Chrebp, Lpk, Dgat, Fasn and Scd1, and intranuclear SREBP1c and ChREBP. Vpr enhanced association of LXRα with Lxrα and Srebp1c promoters, increased LXRE-LXRα binding, and broadly altered hepatic expression of LXRα-regulated lipid metabolic genes. Diminished hepatic fatty acid ß-oxidation was associated with decreased mRNA expression of Pparα and its targets Cpt1, Aox, Lcad, Ehhadh, Hsd10 and Acaa2, and blunted VLDL export with decreased expression of Mttp and its product microsomal triglyceride transfer protein. With our previous findings that Vpr circulates in HIV patients (including those with undetectable plasma HIV-1 RNA), co-regulates the glucocorticoid receptor and PPARγ and transduces hepatocytes, these data indicate a potential role for Vpr in HIV-associated fatty liver disease.
EVALuna2:35296

HIV-1 Vpu mediated downregulation of CD155 requires alanine residues 10, 14 and 18 of the transmembrane domain - Bolduan, Sebastian; Reif, Tatjana; Schindler, Michael; Schubert, Ulrich (Virology, 2014)
HIV-1 NL4-3 Vpu induces downregulation of cell surface CD155, a ligand for the DNAM-1 activating receptor of NK and CD8(+) T cells, to evade NK cell mediated immune response. Here we show that the conserved alanine residues at positions 10, 14 and 18 in the TM domain of Vpu are required for the efficient downregulation of cell surface CD155. In contrast, the CK-2 phosphorylation sites and the second ?-helix in the cytoplasmic Vpu domain have no influence on the surface expression of CD155. Thus, compared to Vpu?s effect on CD4, NTB-A and tetherin, the Vpu mediated downregulation of CD155 is an independent Vpu function. We finally show that in contrast to other lentiviral strains, only Vpu and Nef from HIV-1 M NL4-3 potently interfere with CD155 surface expression. Thus, Vpu seems to subvert NK cell responses against HIV-1 infected T cells by modulation of receptors necessary for NK cell activation.
EVALuna2:8229

HIV-Nef and ADAM17-Containing Plasma Extracellular Vesicles Induce and Correlate with Immune Pathogenesis in Chronic HIV Infection - Lee, Jung-Hyun; Schierer, Stephan; Blume, Katja; Dindorf, Jochen; Wittki, Sebastian; Xiang, Wei; Ostalecki, Christian; Koliha, Nina; Wild, Stefan; Schuler, Gerold; Fackler, Oliver T.; Saksela, Kalle; et al. (EBioMedicine, 2016)
Antiretroviral therapy (ART) efficiently suppresses HIV replication but immune activation and low CD4 T cell counts often persist. The underlying mechanism of this ART-resistant pathogenesis is not clear. We observed that levels of plasma extracellular vesicles (pEV) are strongly elevated in HIV infection and do not decline during ART. Surprisingly, these vesicles contained the viral accessory proteins Nef and Vpu, which are assumed to be not expressed under efficient ART, as well as pro-inflammatory effectors, including activated ADAM17. HIV pEV were characterized by the presence of activated ?v?3 and absence of CD81 and Tsg101. Correlating with immune activation, peripheral monocytes ingested large amounts of pEV, giving rise to an increased population of CD1c(+) CD14(+) cells that secreted inflammatory cytokines. Importantly, the pro-inflammatory content, particularly ADAM17 activity, correlated with low T cell counts. Preliminary evidence suggested that HIV pEV derived from peripheral mononuclear cells and from an unknown myeloid cell population. In summary we propose an important role of pro-inflammatory pEV in chronic HIV infection due to ongoing viral Nef activity.
EVALuna2:4716

HIV Nef- and Notch1-dependent Endocytosis of ADAM17 Induces Vesicular TNF Secretion in Chronic HIV Infection - Ostalecki, Christian; Wittki, Sebastian; Lee, Jung-Hyun; Geist, Miriam M.; Tibroni, Nadine; Harrer, Thomas; Schuler, Gerold; Fackler, Oliver T.; Baur, Andreas (EBioMedicine, 2016)
Tumor necrosis factor (TNF) is a key cytokine in HIV replication and pathogenesis. For reasons that are not entirely clear, the cytokine remains upregulated despite anti-retroviral therapy (ART). Here we demonstrate that HIV Nef induces an alternative TNF secretion mechanism that remains active in chronic infection. Ingestion of Nef-containing plasma extracellular vesicles (pEV) from ART patients by primary immune cells, but also Nef expression, induced intracellular proTNF cleavage and secretion of vesicular TNF endosomes. Key event was the Nef-mediated routing of the TNF-converting enzyme ADAM17 into Rab4+ early endosomes and the Rab27+ secretory pathway. Analysis of lymph-node tissue by multi-epitope-ligand-cartography (MELC) confirmed a vesicular TNF secretion phenotype that co-localized with persistent Nef expression, and implicated Notch1 as an essential co-factor. Surprisingly Notch1 had no transcriptional effect but was required for the endosomal trafficking of ADAM17. We conclude that Nef expression and Nef-containing pEV mobilize TNF from endosomal compartments in acute and chronic infection.
EVALuna2:13372

HIV Nef, paxillin, and Pak1/2 regulate activation and secretion of TACE/ADAM10 proteases - Lee, Jung-Hyun; Wittki, Sebastian; Braeu, Tanja; Dreyer, Florian; Kraetzel, Kirsten; Dindorf, Jochen; Johnston, Ian C. D.; Gross, Stefanie; Kremmer, Elisabeth; Zeidler, Reinhard; Schlötzer-Schrehardt, Ursula; Lichtenheld, Mathias; et al. (Molecular Cell, 2013)
The HIV Nef protein recruits the polycomb protein Eed and mimics an integrin receptor signal for reasons that are not entirely clear. Here we demonstrate that Nef and Eed complex with the integrin effector paxillin to recruit and activate TNF? converting enzyme (TACE alias ADAM 17) and its close relative ADAM10. The activated proteases cleaved proTNF? and were shuttled into extracellular vesicles (EVs). Peripheral blood mononuclear cells that ingested these EVs released TNF?. Analyzing the mechanism, we found that Pak2, an established host cell effector of Nef, phosphorylated paxillin on Ser272/274 to induce TACE-paxillin association and shuttling into EVs via lipid rafts. Conversely, Pak1 phosphorylated paxillin on Ser258, which inhibited TACE association and lipid raft transfer. Interestingly, melanoma cells used an identical mechanism to shuttle predominantly ADAM10 into EVs. We conclude that HIV-1 and cancer cells exploit a paxillin/integrin-controlled mechanism to release TACE/ADAM10-containing vesicles, ensuring better proliferation/growth conditions in their microenvironment.
EVALuna2:12854

Homologous COVID-19 BNT162b2 mRNA Vaccination at a German Tertiary Care University Hospital: A Survey-Based Analysis of Reactogenicity, Safety, and Inability to Work among Healthcare Workers - Niekrens, Valentin; Esse, Jan; Held, Jürgen; Knobloch, Carina; Steininger, Philipp; Kunz, Bernd; Seggewies, Christof; Bogdan, Christian (Vaccines, 2022)
At the start of the SARS-CoV-2 pandemic, healthcare workers had an increased risk of acquiring coronavirus disease (COVID)-19. As tertiary care hospitals are critical for the treatment of severely ill patients, the University Hospital Erlangen offered BNT162b2 mRNA vaccination against COVID-19 to all employees when the vaccine became available in Germany. Here, we performed a survey to assess the age- and sex-dependent reactogenicity and safety of BNT162b2 in a real-life setting with a special emphasis on the rate of vaccine-related incapacity to work amongst the employees. All vaccinated employees were invited to participate in the survey and received access to an electronic questionnaire between 31 March and 14 June 2021, which allowed them to report local and systemic adverse effects after the first or second vaccine dose. A total of 2372 employees completed the survey. After both the first and second dose, women had a higher risk than men for vaccine-related systemic side effects (odds ratio (OR) 1.48 (1.24-1.77) and 1.49 (1.23-1.81), respectively) and for inability to work (OR 1.63 (1.14-2.34) and 1.85 (1.52-2.25), respectively). Compared to employees >= 56 years of age, younger vaccinated participants had a higher risk of systemic reactions after the first (OR 1.35 (1.07-1.70)) and second vaccination (OR 2.08 (1.64-2.63)) and were more often unable to work after dose 2 (OR 2.20 (1.67-2.88)). We also recorded four anaphylactic reactions and received two reports of severe adverse effects indicative of vaccine complications. After the first and second vaccination, 7.9% and 34.7% of the survey participants, respectively, were temporarily unable to work, which added up to 1700 days of sick leave in this cohort. These real-life data extend previous results on the reactogenicity and safety of BNT162b2. Loss of working time due to vaccine-related adverse effects was substantial, but was outweighed by the potential benefit of prevented cases of COVID-19.
CRIS-Team WoS Importer:2022-06-10

Host Anti-antibody Responses Following Adeno-associated Virus-mediated Delivery of Antibodies Against HIV and SIV in Rhesus Monkeys - Martinez-Navio, Jose M.; Fuchs, Sebastian; Pedreno-Lopez, Sonia; Rakasz, Eva G.; Gao, Guangping; Desrosiers, Ronald C. (Molecular Therapy, 2016)
Long-term delivery of antibodies against the human immunodeficiency virus (HIV) using adeno-associated virus (AAV) vectors is a promising approach for the prevention or treatment of HIV infection. However, host antibody responses to the delivered antibody are a serious concern that could significantly limit the applicability of this approach. Here, we describe the dynamics and characteristics of the anti-antibody responses in monkeys that received either rhesus anti-simian immunodeficiency virus (SIV) antibodies (4L6 or 5L7) in prevention trials or a combination of rhesusized human anti-HIV antibodies (1NC9/8ANC195/3BNC117 or 10-1074/10E8/3BNC117) in therapy trials, all employing AAV1 delivery of IgG1. Eight out of eight monkeys that received the anti-HIV antibodies made persisting antibody responses to all three antibodies in the mix. Six out of six uninfected monkeys that received the anti-SIV antibody 4L6 and three out of six of those receiving anti-SIV antibody 5L7 also generated anti-antibodies. Both heavy and light chains were targeted, predominantly or exclusively to variable regions, and reactivity to complementarity-determining region (CDR)-H3 peptide could be demonstrated. There was a highly significant correlation of the magnitude of anti-antibody responses with the degree of sequence divergence of the delivered antibody from germline. Our results suggest the need for effective strategies to counteract the problem of antibody responses to AAV-delivered antibodies.
EVALuna2:8300

HTLV-1 associated myelopathy after renal transplantation - Goevert, Felix; Krumbholz, Andi; Witt, Karsten; Hopfner, Franziska; Feldkamp, Thorsten; Korn, Klaus; Knöll, Antje; Jansen, Olav; Deuschl, Guenther; Fickenscher, Helmut (Journal of Clinical Virology, 2015)
EVALuna2:8278

Human alpha-synuclein overexpressing MBP29 mice mimic functional and structural hallmarks of the cerebellar subtype of multiple system atrophy - Mészáros, Lisa; Riemenschneider, Markus J.; Gaßner, Heiko; Marxreiter, Franz; von Hörsten, Stephan; Hoffmann, Alana; Winkler, Jürgen (Acta Neuropathologica Communications, 2021)
Multiple system atrophy (MSA) is a rare, but fatal atypical parkinsonian disorder. The prototypical pathological hallmark are oligodendroglial cytoplasmic inclusions (GCIs) containing alpha-synuclein (α-syn). Currently, two MSA phenotypes are classified: the parkinsonian (MSA-P) and the cerebellar subtype (MSA-C), clinically characterized by predominant parkinsonism or cerebellar ataxia, respectively. Previous studies have shown that the transgenic MSA mouse model overexpressing human α-syn controlled by the oligodendroglial myelin basic protein (MBP) promoter (MBP29-hα-syn mice) mirrors crucial characteristics of the MSA-P subtype. However, it remains elusive, whether this model recapitulates important features of the MSA-C-related phenotype. First, we examined MSA-C-associated cerebellar pathology using human post-mortem tissue of MSA-C patients and controls. We observed the prototypical GCI pathology and a preserved number of oligodendrocytes in the cerebellar white matter (cbw) accompanied by severe myelin deficit, microgliosis, and a profound loss of Purkinje cells. Secondly, we phenotypically characterized MBP29-hα-syn mice using a dual approach: structural analysis of the hindbrain and functional assessment of gait. Matching the neuropathological features of MSA-C, GCI pathology within the cbw of MBP29-hα-syn mice was accompanied by a severe myelin deficit despite an increased number of oligodendrocytes and a high number of myeloid cells even at an early disease stage. Intriguingly, MBP29-hα-syn mice developed a significant loss of Purkinje cells at a more advanced disease stage. Catwalk XT gait analysis revealed decreased walking speed, increased stride length and width between hind paws. In addition, less dual diagonal support was observed toward more dual lateral and three paw support. Taken together, this wide-based and unsteady gait reflects cerebellar ataxia presumably linked to the cerebellar pathology in MBP29-hα-syn mice. In conclusion, the present study strongly supports the notion that the MBP29-hα-syn mouse model mimics important characteristics of the MSA-C subtype providing a powerful preclinical tool for evaluating future interventional strategies.[Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-04-30
Keywords: Cerebellar ataxia; Cerebellar pathology; Gait analysis; Multiple system atrophy

Human cytomegaloviral multifunctional protein kinase pUL97 impairs zebrafish embryonic development and increases mortality - Cazorla-Vázquez, Salvador; Steingruber, Mirjam; Marschall, Manfred; Engel, Felix (Scientific Reports, 2019)
Cytomegalovirus is a worldwide-distributed human pathogen, which is the leading cause of congenital virus infection, affecting 0.5 to 2% of live births. To date, it is largely unclear which molecular mechanisms underlie the symptomatic outcomes. This is mainly due to species specificity and limited homology among cytomegalovirus genomes. As it is not possible to infect model organisms with human cytomegalovirus, the aim of this study was to develop a heterologous system allowing in the future the elucidation of the pathological role of individual viral proteins. As a model organism the zebrafish has been chosen due to its ease of manipulation and characterization as well as its large offspring. As cytomegalovirus model protein, pUL97 was characterized because it is multiply involved in virus-host interaction. Here, we show in zebrafish embryos, that (i) pUL97 can be expressed in zebrafish, (ii) increasing pUL97 expression levels quantitatively correlate with both minor and major pathological defects, (iii) pUL97 expression impairs cell cycle progression and induces cell death, (iv) active pUL97, but not an inactive mutant, induces excess mortality, and (v) co-administration of a pUL97 inhibitor reduces embryonic pathology. Collectively, these data indicate the suitability of zebrafish to elucidate the pathological role of human cytomegaloviral proteins.
CRIS-Team Scopus Importer:2019-05-24

Human cytomegalovirus (CMV) dysregulates neurodevelopmental pathways in cerebral organoids - Egilmezer, Ece; Hamilton, Stuart T.; Foster, Charles S.P.; Marschall, Manfred; Rawlinson, William D. (Communications Biology, 2024)
Human cytomegalovirus (CMV) infection is the leading non-genetic aetiology of congenital malformation in developed countries, causing significant fetal neurological injury. This study investigated potential CMV pathogenetic mechanisms of fetal neural malformation using in vitro human cerebral organoids. Cerebral organoids were permissive to CMV replication, and infection dysregulated cellular pluripotency and differentiation pathways. Aberrant expression of dual-specificity tyrosine phosphorylation-regulated kinases (DYRK), sonic hedgehog (SHH), pluripotency, neurodegeneration, axon guidance, hippo signalling and dopaminergic synapse pathways were observed in CMV-infected organoids using immunofluorescence and RNA-sequencing. Infection with CMV resulted in dysregulation of 236 Autism Spectrum Disorder (ASD)-related genes (p = 1.57E-05) and pathways. This notable observation suggests potential links between congenital CMV infection and ASD. Using DisGeNET databases, 103 diseases related to neural malformation or mental disorders were enriched in CMV-infected organoids. Cytomegalovirus infection-related dysregulation of key cerebral cellular pathways potentially provides important, modifiable pathogenetic mechanisms for congenital CMV-induced neural malformation and ASD.
CRIS-Team Scopus Importer:2024-03-29

Human cytomegalovirus envelope protein gpul132 regulates infectious virus production through formation of the viral assembly compartment - Wu, Hui; Kropff, Barbara; Mach, Michael; Britt, William J. (Mbio, 2020)
The human cytomegalovirus (HCMV) UL132 open reading frame encodes a 270-amino-acid type I envelope glycoprotein, gpUL132. The deletion of UL132 (ΔUL132) from the HCMV genome results in a pronounced deficit in virus yield, with an approximately 2-log decrease in the production of infectious virus compared to the wild-type (WT) virus. Characterization of the ΔUL132 mutant virus indicated that it was less infectious with a high particle-to-infectious unit ratio and an altered composition of virion proteins compared to the WT virus. In addition, the viral assembly compartment (AC) failed to form in cells infected with the ΔUL132 mutant virus. The expression of gpUL132 in trans rescued the defects in the morphogenesis of the AC in cells infected with the ΔUL132 mutant virus and in infectious virus production. Furthermore, using cell lines expressing chimeric proteins, we demonstrated that the cytosolic domain of gpUL132 was sufficient to rescue AC formation and WT levels of virus production. Progeny virions from ΔUL132-infected cells expressing the cytosolic domain of gpUL132 exhibited particle-to-infectious unit ratios similar to those of the WT virus. Together, our findings argue that gpUL132 is essential for HCMV AC formation and the efficient production of infectious particles, thus highlighting the importance of this envelope protein for the virus-induced reorganization of intracellular membranes and AC formation in the assembly of infectious virus. IMPORTANCE Following infection of permissive cells, human cytomegalovirus (HCMV) induces the reorganization of intracellular membranes resulting in the formation of a distinctive membranous compartment in the cytoplasm of infected cells. This compartment has been designated the viral assembly compartment (AC) and is thought to be a site for cytoplasmic virion assembly and envelopment. In this study, we have demonstrated that a single virion envelope glycoprotein is essential for AC formation in infected cells, and in its absence, there is a significant decrease in the production of infectious virions. These findings are consistent with those from other studies that have demonstrated the importance of host cell proteins in the formation of the AC and demonstrate a critical role of a single virion protein in AC formation and the efficient assembly of infectious virus.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Human cytomegalovirus; Viral assembly compartment; Virion envelope protein; Virus glycoproteins

Human Cytomegalovirus infection leads to elevated levels of transplant arteriosclerosis in a humanised mouse aortic xenograft model - Heim, Christian; Weyand, Michael; Stamminger, Thomas; Ensminger, Stephan; et al. (American Journal of Transplantation, 2012)

Human Cytomegalovirus Nuclear Capsids Associate with the Core Nuclear Egress Complex and the Viral Protein Kinase pUL97 - Milbradt, Jens; Sonntag, Eric; Wagner, Sabrina; Strojan, Hanife; Wangen, Christina; Rovis, Tihana Lenac; Lisnic, Berislav; Jonjic, Stipan; Sticht, Heinrich; Britt, William J.; Schlötzer-Schrehardt, Ursula; Marschall, Manfred (Viruses, 2018)
The nuclear phase of herpesvirus replication is regulated through the formation of regulatory multi-component protein complexes. Viral genomic replication is followed by nuclear capsid assembly, DNA encapsidation and nuclear egress. The latter has been studied intensely pointing to the formation of a viral core nuclear egress complex (NEC) that recruits a multimeric assembly of viral and cellular factors for the reorganization of the nuclear envelope. To date, the mechanism of the association of human cytomegalovirus (HCMV) capsids with the NEC, which in turn initiates the specific steps of nuclear capsid budding, remains undefined. Here, we provide electron microscopy-based data demonstrating the association of both nuclear capsids and NEC proteins at nuclear lamina budding sites. Specifically, immunogold labelling of the core NEC constituent pUL53 and NEC-associated viral kinase pUL97 suggested an intranuclear NEC-capsid interaction. Staining patterns with phospho-specific lamin A/C antibodies are compatible with earlier postulates of targeted capsid egress at lamina-depleted areas. Important data were provided by co-immunoprecipitation and in vitro kinase analyses using lysates from HCMV-infected cells, nuclear fractions, or infectious virions. Data strongly suggest that nuclear capsids interact with pUL53 and pUL97. Combined, the findings support a refined concept of HCMV nuclear trafficking and NEC-capsid interaction.
EVALuna2:33716

Human Cytomegalovirus Nuclear Egress Proteins Ectopically Expressed in the Heterologous Environment of Plant Cells are Strictly Targeted to the Nuclear Envelope - Lamm, Christian; Link, Katrin; Wagner, Sabrina; Milbradt, Jens; Marschall, Manfred; Sonnewald, Uwe (Viruses, 2016)
In all eukaryotic cells, the nucleus forms a prominent cellular compartment containing the cell's nuclear genome. Although structurally similar, animal and plant nuclei differ substantially in details of their architecture. One example is the nuclear lamina, a layer of tightly interconnected filament proteins (lamins) underlying the nuclear envelope of metazoans. So far no orthologous lamin genes could be detected in plant genomes and putative lamin-like proteins are only poorly described in plants. To probe for potentially conserved features of metazoan and plant nuclear envelopes, we ectopically expressed the core nuclear egress proteins of human cytomegalovirus pUL50 and pUL53 in plant cells. pUL50 localizes to the inner envelope of metazoan nuclei and recruits the nuclear localized pUL53 to it, forming heterodimers. Upon expression in plant cells, a very similar localization pattern of both proteins could be determined. Notably, pUL50 is specifically targeted to the plant nuclear envelope in a rim-like fashion, a location to which coexpressed pUL53 becomes strictly corecruited from its initial nucleoplasmic distribution. Using pUL50 as bait in a yeast two-hybrid screening, the cytoplasmic re-initiation supporting protein RISP could be identified. Interaction of pUL50 and RISP could be confirmed by coexpression and coimmunoprecipitation in mammalian cells and by confocal laser scanning microscopy in plant cells, demonstrating partial pUL50-RISP colocalization in areas of the nuclear rim and other intracellular compartments. Thus, our study provides strong evidence for conserved structural features of plant and metazoan nuclear envelops and identifies RISP as a potential pUL50-interacting plant protein.
Keywords: pUL53; plant cells; nuclear envelope; pUL50; re-initiation supporting protein RISP; human cytomegalovirus

Human cytomegalovirus overcomes SAMHD1 restriction in macrophages via pUL97 - Businger, Ramona; Deutschmann, Janina; Gruska, Iris; Milbradt, Jens; Wiebusch, Lüder; Gramberg, Thomas; Schindler, Michael (Nature Microbiology, 2019)
The host restriction factor sterile alpha motif and histidine–aspartate domain-containing protein 1 (SAMHD1) is an important component of the innate immune system. By regulating the intracellular nucleotide pool, SAMHD1 influences cell division and restricts the replication of viruses that depend on high nucleotide concentrations. Human cytomegalovirus (HCMV) is a pathogenic virus with a tropism for non-dividing myeloid cells, in which SAMHD1 is catalytically active. Here we investigate how HCMV achieves efficient propagation in these cells despite the SAMHD1-mediated dNTP depletion. Our analysis reveals that SAMHD1 has the capability to suppress HCMV replication. However, HCMV has evolved potent countermeasures to circumvent this block. HCMV interferes with SAMHD1 steady-state expression and actively induces SAMHD1 phosphorylation using the viral kinase pUL97 and by hijacking cellular kinases. These actions convert SAMHD1 to its inactive phosphorylated form. This mechanism of SAMHD1 inactivation by phosphorylation might also be used by other viruses to overcome intrinsic immunity.
CRIS-Team Scopus Importer:2019-11-01

Human Cytomegalovirus Particles Treated with Specific Antibodies Induce Intrinsic and Adaptive but Not Innate Immune Responses - Wu, Zeguang; Qin, Ruifang; Wang, Li; Bosso, Matteo; Scherer, Myriam; Stamminger, Thomas; Hotter, Dominik; Mertens, Thomas; Frascaroli, Giada (Journal of Virology, 2017)
Human cytomegalovirus (HCMV) persistently infects 40% to 100% of the human population worldwide. Experimental and clinical evidence indicates that humoral immunity to HCMV plays an important role in restricting virus dissemination and protecting the infected host from disease. Specific immunoglobulin preparations from pooled plasma of adults selected for high titers of HCMV antibodies have been used for the prevention of CMV disease in transplant recipients and pregnant women. Even though incubation of HCMV particles with these preparations leads to the neutralization of viral infectivity, it is still unclear whether the antibody-treated HCMV particles (referred to here as HCMV-Ab) enter the cells and modulate antiviral immune responses. Here we demonstrate that HCMV-Ab did enter macrophages. HCMV-Ab did not initiate the expression of immediate early antigens (IEAs) in macrophages, but they induced an antiviral state and rendered the cells less susceptible to HCMV infection upon challenge. Resistance to HCMV infection seemed to be due to the activation of intrinsic restriction factors and was independent of interferons. In contrast to actively infected cells, autologous NK cells did not degranulate against HCMV-Ab-treated macrophages, suggesting that these cells may not be eliminated by innate effector cells. Interestingly, HCMV-Ab-treated macrophages stimulated the proliferation of autologous adaptive CD4+and CD8+T cells. Our findings not only expand the current knowledge on virus-antibody immunity but may also be relevant for future vaccination strategies.IMPORTANCEHuman cytomegalovirus (HCMV), a common herpesvirus, establishes benign but persistent infections in immunocompetent hosts. However, in subjects with an immature or dysfunctional immune system, HCMV is a major cause of morbidity and mortality. Passive immunization has been used in different clinical settings with variable clinical results. Intravenous hyperimmune globulin preparations (IVIg) are obtained from pooled adult human plasma selected for high anti-CMV antibody titers. While HCMV neutralization can be shownin vitrousing different systems, data are lacking regarding the cross-influence of IVIg administration on the cellular immune responses. The aim of this study was to evaluate the effects of IVIg on distinct components of the immune response against HCMV, including antigen presentation by macrophages, degranulation of innate natural killer cells, and proliferation of adaptive CD4+and CD8+T cells.
EVALuna2:33751

Human cytomegalovirus replication is strictly inhibited by siRNAs targeting UL54, UL97 or UL122/123 gene transcripts - Hamilton, Stuart T.; Milbradt, Jens; Marschall, Manfred; Rawlinson, William D. (PLoS ONE, 2014)
Human cytomegalovirus (HCMV) causes severe sequelae in immunocompromised hosts. Current antiviral therapies have serious adverse effects, with treatment in many clinical settings problematic, making new therapeutic approaches necessary. We examined the in vitro efficacy of small interfering RNAs (siRNAs) targeting the HCMV gene transcripts UL54 (DNA polymerase), UL97 (protein kinase) and UL122/123 (immediate-early proteins) as inhibitors of viral protein expression and virus replication in cell cultures. Two siRNAs for each HCMV target (designated A and B) were assessed for inhibition efficacy using western blot and standard plaque assays. Continuous human embryonic kidney 293T cells were treated with HCMV or non-specific scrambled (siSc) siRNA followed by transfection with plasmids expressing the target transcripts. Human MRC-5 fibroblasts were HCMV-siRNA or siSc treated, infected with HCMV strain AD169 (1 pfu/cell) and HCMV immediate-early (IE1p72 and IE2p86), early (pp65), early-late (pUL97) and true late (MCP) protein and virus progeny production measured during a single round of replication. Concordant results showed siUL54B, siUL97A and siUL122B displayed the most potent inhibitory effects with a reduction of 92.7%, 99.6% and 93.7% in plasmid protein expression, 65.9%, 58.1% and 64.8% in total HCMV protein expression and 97.2%, 96.2% and 94.3% (p<0.0001) in viral progeny production respectively. Analysing the siRNA inhibitory effects during multiple rounds of HCMV replication at a multiplicity of infection of 0.001 pfu/cell, siUL54B, siUL97A and siUL122B treatment resulted in a reduction of 80.0%, 59.6% and 84.5% in total HCMV protein expression, 52.9%, 49.2% and 58.3% in number of cells infected and 98.5%, 91.4% and 99.1% (p<0.0001) in viral progeny production at 7 dpi respectively. These results suggest potential in vivo siRNA therapies targeting the HCMV gene transcripts UL54, UL97 and UL122/123 would be highly effective, however, the antiviral efficacy of siRNAs targeting UL97 may be more highly dependent on viral load and methods of administration.
EVALuna2:8236

Human cytomegalovirus utilises cellular dual-specificity tyrosine phosphorylation-regulated kinases during placental replication - Hamilton, Stuart T.; Hutterer, Corina; Egilmezer, Ece; Steingruber, Mirjam; Milbradt, Jens; Marschall, Manfred; Rawlinson, William D. (Placenta, 2018)
Introduction: Congenital cytomegalovirus (HCMV) infection may cause significant fetal malformation and in severe cases fetal and neonatal death. Fetal injury may be caused indirectly by the placental response to infection. Dual-specificity tyrosine phosphorylation-regulated kinases (DYRKs) have recently been identified as critical kinases for HCMV replication. In this study we provide first evidence that DYRK1A and DYRK1B are utilised during HCMV placental replication. Methods: DYRK expression was investigated in AD169-and Merlin-infected TEV-1 trophoblast cells, ex vivo placental explants and naturally infected clinical placentae by immunofluorescence, western blot, co-immunoprecipitation and RT-qPCR. Results: HCMV-infected placental cells showed accumulation and re-localisation of DYRK1A and DYRK1B protein to areas of cytoplasmic virion assembly complexes and nuclear viral replication compartments, respectively. This accumulation was a result of upregulated DYRK1A/B protein expression with HCMV inducing up to a 5.3fold increase in DYRK1A and up to a 4.7-fold increase in DYRK1B protein, relative to mock-infected TEV-1 cells (p < 0.0001). Increased DYRK protein expression was correlated with DYRK1A/B mRNA upregulation, with HCMV-infected cells showing up to a 3.7-fold increase and 2.9-fold increase in DYRK1A and DYRK1B mRNA levels respectively (p < 0.05). Protein-protein interactions were detected between DYRK1A/1B complexes and HCMV immediate early IE2p86, early pp65 and pUL44 and late pp150 proteins. Treatment of HCMV-infected TEV-1 cells and placental explants with DYRK inhibitors significantly inhibited HCMV replication (p < 0.05) indicating these cellular kinases are required during HCMV placental replication. Conclusion: HCMV modulates cellular DYRKs during placental replication which may have implications for congenital HCMV pathogenesis and represent promising antiviral targets.
EVALuna2:35259

Human herpesvirus-8 (HHV-8) gene expression in Kaposi's sarcoma (KS) primary lesions: an in situ hybridization study. - Stürzl, Michael; Wunderlich, A; Ascherl, Gudrun; Hohenadl, C; Monini, Paolo; Zietz, Christian; Browning, Philip J.; Neipel, Frank; Biberfeld, Peter; Ensoli, Barbara (Leukemia, 1999)

Human herpesvirus 8 molecular mimicry of ephrin ligands facilitates cell entry and triggers EphA2 signaling - Light, Taylor P.; Brun, Delphine; Guardado-Calvo, Pablo; Pederzoli, Riccardo; Haouz, Ahmed; Neipel, Frank; Rey, Félix A.; Hristova, Kalina; Backovic, Marija (Plos Biology, 2021)
Human herpesvirus 8 (HHV-8) is an oncogenic virus that enters : cells by fusion of the viral and endosomal cellular membranes in a process mediated by viral surface glycoproteins. One of the cellular receptors hijacked by HHV-8 to gain access to cells is the EphA2 tyrosine kinase receptor, and the mechanistic basis of EphA2-mediated viral entry remains unclear. Using X-ray structure analysis, targeted mutagenesis, and binding studies, we here show that the HHV-8 envelope glycoprotein complex H and L (gH/gL) binds with subnanomolar affinity to EphA2 via molecular mimicry of the receptor’s cellular ligands, ephrins (Eph family receptor interacting proteins), revealing a pivotal role for the conserved gH residue E52 and the amino-terminal peptide of gL. Using FSI-FRET and cell contraction assays, we further demonstrate that the gH/gL complex also functionally mimics ephrin ligand by inducing EphA2 receptor association via its dimerization interface, thus triggering receptor signaling for cytoskeleton remodeling. These results now provide novel insight into the entry mechanism of HHV-8, opening avenues for the search of therapeutic agents that could interfere with HHV-8–related diseases.
CRIS-Team Scopus Importer:2021-09-24

Human IFN-gamma immunity to mycobacteria is governed by both IL-12 and IL-23 - Martinez-Barricarte, Ruben; Markle, Janet G.; Ma, Cindy S.; Deenick, Elissa K.; Ramirez-Alejo, Noe; Mele, Federico; Latorre, Daniela; Mandaviani, Seyed Alireza; Aytekin, Caner; Mansouri, Davood; Bryant, Vanessa L.; Jabot-Hanin, Fabienne; et al. (Science immunology, 2018)
Hundreds of patients with autosomal recessive, complete IL-12p40 or IL-12R beta 1 deficiency have been diagnosed over the last 20 years. They typically suffer from invasive mycobacteriosis and, occasionally, from mucocutaneous candidiasis. Susceptibility to these infections is thought to be due to impairments of IL-12-dependent IFN-gamma immunity and IL-23-dependent IL-17A/IL-17F immunity, respectively. We report here patients with autosomal recessive, complete IL-12R beta 2 or IL-23R deficiency, lacking responses to IL-12 or IL-23 only, all of whom, unexpectedly, display mycobacteriosis without candidiasis. We show that alpha beta T, gamma delta T, B, NK, ILC1, and ILC2 cells from healthy donors preferentially produce IFN-gamma in response to IL-12, whereas NKT cells and MAIT cells preferentially produce IFN-gamma in response to IL-23. We also show that the development of IFN-gamma-producing CD4(+) T cells, including, in particular, mycobacterium-specific T(H)1* cells (CD45RA(-)CCR6(+)), is dependent on both IL-12 and IL-23. Last, we show that IL12RB1, IL12RB2, and IL23R have similar frequencies of deleterious variants in the general population. The comparative rarity of symptomatic patients with IL-12R beta 2 or IL-23R deficiency, relative to IL-12R beta 1 deficiency, is, therefore, due to lower clinical penetrance. There are fewer symptomatic IL-23R- and IL-12R beta 2-deficient than IL-12R beta 1-deficient patients, not because these genetic disorders are rarer, but because the isolated absence of IL-12 or IL-23 is, in part, compensated by the other cytokine for the production of IFN-gamma, thereby providing some protection against mycobacteria. These experiments of nature show that human IL-12 and IL-23 are both required for optimal IFN-gamma-dependent immunity to mycobacteria, both individually and much more so cooperatively.
EVALuna2:35258

Human papilloma virus genotype distribution in women with premalignant or malignant lesions of the uterine cervix - Stübs, Frederik; Gaß, Paul; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Koch, Martin (Archives of Gynecology and Obstetrics, 2021)
Objective: Cervical cancer is caused by persistent infection with high-risk human papillomavirus (hrHPV). Cytology-based national screening programs have reduced the incidence and mortality of cervical cancer. Different hrHPV subtypes have different carcinogenic potentials. This study evaluated the distribution of different types of hrHPV relative to age in cervical cancer and its precursor lesions. Methods: HPV testing was performed between November 2018 and February 2020 using the Abbott RealTime high-risk HPV assay on an Abbott m2000sp instrument. This assay separately detects HPV-16, HPV-18, and a pool of 12 additional hrHPV types (HPV-31, -33, -35, -39, -45, -51, -52, -56, -58, -59, -66, and -68). Results: The study included 652 women with HPV samples and biopsies of the cervix or histology samples obtained during surgery. In all, 30.8% (95% CI, 27.3–34.6%) were HPV-negative. Among HPV-positive women, HPV-16, HPV-18, and “HPV other” types were found in 33.5, 4.4, and 49.4%, respectively. Cervical intraepithelial neoplasia (CIN) 3/high-grade squamous intraepithelial lesions (HSILs) in women ≤ 34 years were positive for HPV-16 in 54.5% of cases and in those ≥ 35 years in 45.4% of cases. Among women with cervical cancer, 75.8% were infected with HPV-16 or had coinfection with HPV-16 and “HPV other”. Conclusions: HPV-16 is the most common type of hrHPV in HSIL + lesions. It is more common in women diagnosed with CIN 3/HSIL who are aged ≤ 35 and is decreasing with age. Therefore, women age ≥ 35 with persistent infection with this type of hrHPV need careful surveillance, as they are at high risk of progression to cervical cancer.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Age-distribtuion of HPV; Cervical cancer; Colposcopy; HPV-distribution; HSIL

Human promyelocytic leukemia protein is targeted to distinct subnuclear domains in plant nuclei and colocalizes with nucleolar constituents in a SUMO-dependent manner - Lamm, Christian; Scherer, Myriam; Reuter, Nina; Amin, Bushra; Stamminger, Thomas; Sonnewald, Uwe (FEBS Open Bio, 2016)
Eukaryotic nuclei are subdivided into subnuclear structures. Among the most prominent of these structures are the nucleolus and the PML nuclear bodies (PML-NBs). PML-NBs are spherical multiprotein aggregates of varying size localized in the interchromosomal area. PML-NB formation is dependent on the presence of the promyelocytic leukemia protein (PML) as well as on post-translational modification of core components by covalent attachment of the small ubiquitin-like modifier (SUMO). So far, PML-NBs as well as PML have been described in mammalian cells only, whereas no orthologs are known in the plant kingdom. In order to investigate conserved mechanisms in PML targeting, we expressed human PML (hPML) fused to the GFP in Nicotiana benthamiana. Using confocal laser scanning microscopy and coimmunoprecipitation followed by mass spectrometric analysis, we found the fusion protein in association with nucleolar constituents. Importantly, mutants of hPML, which are no longer SUMOylated, showed altered localizations, implying SUMO-dependent targeting of hPML in plants as has previously been shown for mammalian cells. Interestingly, in the presence of proteasome inhibitors, hPML could also be found in the nucleolus of mammalian cells suggesting conserved targeting mechanisms of PML across kingdoms. Finally, Solanum tuberosum COP1, a proposed PML-like protein from plants, was fused to the red fluorescent protein (RFP) and coexpressed with hPML::eGFP. Microscopic analysis confirmed the localization of COP1::RFP in nuclear speckles. However, hPML::eGFP did not colocalize with COP1::RFP. Hence, we conclude that plants do not possess specialized PML-NBs, but that their functions may be covered by other subnuclear structures like the nucleolus.
Keywords: nucleolus; plant subnuclear structures; promyelocytic leukemia protein; nuclear bodies; small ubiquitin like modifier

Human TRIM5 alpha senses and restricts LINE-1 elements - Volkmann, Bianca; Wittmann, Sabine; Lagisquet, Justine; Deutschmann, Janina; Eißmann, Kristin; Ross, James J.; Biesinger, Brigitte; Gramberg, Thomas (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Mobile genetic elements have significantly shaped our genomic landscape. LINE-1 retroelements are the only autonomously active elements left in the human genome. Since new insertions can have detrimental consequences, cells need to efficiently control LINE-1 retrotransposition. Here, we demonstrate that the intrinsic immune factor TRIM5 alpha senses and restricts LINE-1 retroelements. Previously, rhesus TRIM5 alpha has been shown to efficiently block HIV-1 replication, while human TRIM5 alpha was found to be less active. Surprisingly, we found that both human and rhesus TRIM5 alpha efficiently repress human LINE-1 retrotransposition. TRIM5 alpha interacts with LINE-1 ribonucleoprotein complexes in the cytoplasm, which is essential for restriction. In line with its postulated role as pattern recognition receptor, we show that TRIM5 alpha also induces innate immune signaling upon interaction with LINE-1 ribonucleoprotein complexes. The signaling events activate the transcription factors AP-1 and NF-kappa B, leading to the down-regulation of LINE-1 promoter activity. Together, our findings identify LINE-1 as important target of human TRIM5 alpha, which restricts and senses LINE-1 via two distinct mechanisms. Our results corroborate TRIM5 alpha as pattern recognition receptor and shed light on its previously undescribed activity against mobile genetic elements, such as LINE-1, to protect the integrity of our genome.
CRIS-Team WoS Importer:2020-08-21

Human TYK2 deficiency: Mycobacterial and viral infections without hyper-IgE syndrome - Kreins, Alexandra Y.; Ciancanelli, Michael J.; Okada, Satoshi; Kong, Xiao-Fei; Ramirez-Alejo, Noe; Kilic, Sara Sebnem; El Baghdadi, Jamila; Nonoyama, Shigeaki; Mahdaviani, Seyed Alireza; Ailal, Fatima; Bousfiha, Aziz; Mansouri, Davood; et al. (Journal of Experimental Medicine, 2015)
Autosomal recessive, complete TYK2 deficiency was previously described in a patient (P1) with intracellular bacterial and viral infections and features of hyper-IgE syndrome (HIES), including atopic dermatitis, high serum IgE levels, and staphylococcal abscesses. We identified seven other TYK2-deficient patients from five families and four different ethnic groups. These patients were homozygous for one of five null mutations, different from that seen in P1. They displayed mycobacterial and/or viral infections, but no HIES. All eight TYK2-deficient patients displayed impaired but not abolished cellular responses to (a) IL-12 and IFN-?/?, accounting for mycobacterial and viral infections, respectively; (b) IL-23, with normal proportions of circulating IL-17(+) T cells, accounting for their apparent lack of mucocutaneous candidiasis; and (c) IL-10, with no overt clinical consequences, including a lack of inflammatory bowel disease. Cellular responses to IL-21, IL-27, IFN-?, IL-28/29 (IFN-?), and leukemia inhibitory factor (LIF) were normal. The leukocytes and fibroblasts of all seven newly identified TYK2-deficient patients, unlike those of P1, responded normally to IL-6, possibly accounting for the lack of HIES in these patients. The expression of exogenous wild-type TYK2 or the silencing of endogenous TYK2 did not rescue IL-6 hyporesponsiveness, suggesting that this phenotype was not a consequence of the TYK2 genotype. The core clinical phenotype of TYK2 deficiency is mycobacterial and/or viral infections, caused by impaired responses to IL-12 and IFN-?/?. Moreover, impaired IL-6 responses and HIES do not appear to be intrinsic features of TYK2 deficiency in humans.
EVALuna2:8293

Identifying neuropeptide Y (NPY) as the main stress-related substrate of dipeptidyl peptidase 4 (DPP4) in blood circulation - Wagner, Leona; Kaestner, Florian; Wolf, Raik; Stiller, Harald; Heiser, Ulrich; Manhart, Susanne; Hoffmann, Torsten; Rahfeld, Jens-Ulrich; Demuth, Hans-Ulrich; Rothermundt, Matthias; von Hörsten, Stephan (Neuropeptides, 2016)
Dipeptidyl peptidase 4 (DPP4; EC 3.4.14.5; CD26) is a membrane-bound or shedded serine protease that hydrolyzes dipeptides from the N-terminus of peptides with either proline or alanine at the penultimate position. Substrates of DPP4 include several stress-related neuropeptides implicated in anxiety, depression and schizophrenia. A decline of DPP4-like activity has been reported in sera from depressed patient, but not fully characterized regarding DPP4-like enzymes, therapeutic interventions and protein.Sera from 16 melancholic- and 16 non-melancholic-depressed patients were evaluated for DPP4-like activities and the concentration of soluble DPP4 protein before and after treatment by anti-depressive therapies. Post-translational modification of DPP4-isoforms and degradation of NPY, Peptide YY (PYY), Galanin-like peptide (GALP), Orexin B (OrxB), OrxA, pituitary adenylate cyclase-activating polypeptide (PACAP) and substance P (SP) were studied in serum and in ex vivo human blood. N-terminal truncation of biotinylated NPY by endothelial membrane-bound DPP4 versus soluble DPP4 was determined in rat brain perfusates and spiked sera.Lower DPP4 activities in depressed patients were reversed by anti-depressive treatment. In sera, DPP4 contributed to more than 90% of the overall DPP4-like activity and correlated with its protein concentration. NPY displayed equal degradation in serum and blood, and was equally truncated by serum and endothelial DPP4. In addition, GALP and rat OrxB were identified as novel substrates of DPP4.NPY is the best DPP4-substrate in blood, being truncated by soluble and membrane DPP4, respectively. The decline of soluble DPP4 in acute depression could be reversed upon anti-depressive treatment. Peptidases from three functional compartments regulate the bioactivity of NPY in blood.
EVALuna2:24977

IFI16 Targets the Transcription Factor Sp1 to Suppress HIV-1 Transcription and Latency Reactivation - Hotter, Dominik; Bosso, Matteo; Jønsson, Kasper L.; Krapp, Christian; Stürzel, Christina M.; Das, Atze; Littwitz-Salomon, Elisabeth; Berkhout, Ben; Russ, Alina; Wittmann, Sabine; Gramberg, Thomas; Zheng, Yue; et al. (Cell Host & Microbe, 2019)
The interferon γ-inducible protein 16 (IFI16) is known as immune sensor of retroviral DNA intermediates. We show that IFI16 restricts HIV-1 independently of immune sensing by binding and inhibiting the host transcription factor Sp1 that drives viral gene expression. This antiretroviral activity and ability to bind Sp1 require the N-terminal pyrin domain and nuclear localization of IFI16, but not the HIN domains involved in DNA binding. Highly prevalent clade C HIV-1 strains are more resistant to IFI16 and less dependent on Sp1 than other HIV-1 subtypes. Furthermore, inhibition of Sp1 by IFI16 or pharmacologically by Mithramycin A suppresses reactivation of latent HIV-1 in CD4+ T cells. Finally, IFI16 also inhibits retrotransposition of LINE-1, known to engage Sp1, and murine IFI16 homologs restrict Friend retrovirus replication in mice. Thus, IFI16 restricts retroviruses and retrotransposons by interfering with Sp1-dependent gene expression, and evasion from this restriction may facilitate spread of HIV-1 subtype C.
CRIS-Team Scopus Importer:2019-06-18
Keywords: HIV-1; interferon γ-inducible PYHIN protein 16; PYHIN proteins; restriction factors; Sp1 transcription factor

IL-1 beta as mucosal vaccine adjuvant: the specific induction of tissue-resident memory T cells improves the heterosubtypic immunity against influenza A viruses - Lapuente, D.; Bonsmann, M. Storcksdieck Genannt; Maaske, A.; Stab, V.; Heinecke, V.; Watzstedt, K.; Hess, R.; Westendorf, A. M.; Bayer, W.; Ehrhardt, C.; Tenbusch, Matthias (Mucosal Immunology, 2018)
A universal influenza vaccine must provide protection against antigenically divergent influenza viruses either through broadly neutralizing antibodies or cross-reactive T cells. Here, intranasal immunizations with recombinant adenoviral vectors (rAd) encoding hemagglutinin (HA) and nucleoprotein (NP) in combination with rAd-Interleukin-(IL)-1 beta or rAd-IL-18 were evaluated for their efficacy in BALB/c mice. Mucosal delivery of rAd-IL-1 beta enhanced HA-specific antibody responses including strain-specific neutralizing antibodies. Nevertheless, the beneficial effects on the local T cell responses were much more impressive reflected by increased numbers of CD103(+)CD69(+) tissue-resident memory T cells (T-RM). This increased immunogenicity translated into superior protection against infections with homologous and heterologous strains including H1N1, pH1N1, H3N2, and H7N7. Inhibition of the egress of circulating T cells out of the lymph nodes during the heterologous infection had no impact on the degree of protection underscoring the unique potential of T-RM for the local containment of mucosal infections. The local co-expression of IL-1 beta and antigen lead to the activation of critical checkpoints in the formation of T-RM including activation of epithelial cells, expression of chemokines and adhesion molecules, recruitment of lung-derived CD103(+) DCs, and finally local T-RM imprinting. Given the importance of T-RM-mediated protection at mucosal barriers, this study has major implications for vaccine development.
EVALuna2:35271

IL-1 beta as mucosal vaccine adjuvant: The specific induction of tissue-resident memory T cells leads to an enhanced protection against heterologous IAV - Lapuente, D.; Bonsmann, M. Storcksdieck Genannt; Maaske, A.; Stab, V.; Heinecke, V.; Watzstedt, K.; Hess, R.; Westendorf, A.; Bayer, W.; Ehrhardt, C.; Tenbusch, Matthias (2017)
EVALuna2:33745

Imbalance of the oxytocin-vasopressin system contributes to the neuropsychiatric phenotype in the BACHD mouse model of Huntington disease - Cheong, Rachel Y.; Tonetto, Simone; von Hörsten, Stephan; Petersén, Åsa (Psychoneuroendocrinology, 2020)
Neuropsychiatric disturbances with altered social cognition, depression and anxiety are among the most debilitating early features in the fatal neurodegenerative disorder Huntington disease (HD) which is caused by an expanded CAG repeat in the huntingtin gene. The underlying neurobiological mechanisms are not known. Neuropathological analyses of postmortem human HD hypothalamic tissue have demonstrated loss of the neuropeptides oxytocin and vasopressin. The dynamic interplay between these neuropeptides is crucial for modulating emotional and social behavior but its role in HD is unclear. In the present study, we have investigated the effect of expressing the mutant huntingtin gene on the development of behavioral changes using the transgenic BACHD mouse model at different ages. We show for the first time that BACHD mice exhibit deficits in social behavior with parallel aberrations in the balance of the oxytocin-vasopressin system. Importantly, our data also show that restoration of the interplay within the system with an acute dose of intranasal oxytocin immediately prior to behavioral testing can rescue the depressive-like phenotype but not anxiety-like behavior in this transgenic model. These findings demonstrate that imbalances in the oxytocin-vasopressin interplay contribute to the neuropsychiatric component of HD and suggest that interventions aimed at restoring the blunted levels of oxytocin may confer therapeutic benefits for this disease.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Huntington's disease; Hypothalamus; Neuropsychiatric behavior; Oxytocin; Vasopressin

Immune‐modulating drug MP1032 with SARS‐CoV‐2 antiviral activity in vitro: A potential multi‐target approach for prevention and early intervention treatment of COVID‐19 - Schumann, Sara; Kaiser, Astrid; Nicoletti, Ferdinando; Mangano, Katia; Fagone, Paolo; van Wijk, Eduard; Yan, Yu; Schulz, Petra; Ludescher, Beate; Niedermaier, Michael; von Wegerer, Joerg; Rauch, Pia; et al. (International Journal of Molecular Sciences, 2020)
At least since March 2020, the severe acute respiratory syndrome coronavirus type 2 (SARS‐CoV‐2) pandemic and the multi‐organ coronavirus disease 2019 (COVID‐19) are keeping a firm grip on the world. Although most cases are mild, older patients and those with co‐morbidities are at increased risk of developing a cytokine storm, characterized by a systemic inflammatory response leading to acute respiratory distress syndrome and organ failure. The present paper focuses on the small molecule MP1032, describes its mode of action, and gives rationale why it is a promising option for the prevention/treatment of the SARS‐CoV‐2‐induced cytokine storm. MP1032 is a phase‐pure anhydrous polymorph of 5‐amino‐2,3‐dihydro‐1,4‐phthalazinedione sodium salt that exhibits good stability and bioavailability. The physiological action of MP1032 is based on a multi‐target mechanism including localized, self‐limiting reactive oxygen species (ROS) scavenging activities that were demonstrated in a model of lipopolysaccharide (LPS)‐induced joint inflammation. Furthermore, its immune‐regulatory and PARP‐1‐modulating properties, coupled with antiviral effects against SARS‐CoV‐2, have been demonstrated in various cell models. Preclinical efficacy was elucidated in LPS‐induced endotoxemia, a model with heightened innate immune responses that shares many similarities to COVID‐19. So far, during oral clinical development with three‐month daily administrations, no serious adverse drug reactions occurred, highlighting the outstanding safety profile of MP1032.
CRIS-Team Scopus Importer:2020-11-27
Keywords: COVID‐19; COVID‐19 drugs; Cytokine storm; Drug development; Inflammation; Oxidative stress; SARS‐CoV‐2

Immune suppression of vaccine-induced CD8(+) T-cell responses by gamma retrovirus envelope is mediated by interleukin-10-producing CD4(+) T cells - Podschwadt, Philip; Malyshkina, Anna; Windmann, Sonja; Papadamakis, Athanasios; Kerkmann, Leonie; Lapuente, Dennis; Tenbusch, Matthias; Lu, Mengji; Schindler, Michael; Lang, Karl Sebastian; Hansen, Wiebke; Bayer, Wibke (Frontiers in Immunology, 2022)
Retroviral envelope (Env) proteins have long been recognized to exhibit immunosuppressive properties, which affect the CD8(+) T-cell response to an infection but also to immunization. Interestingly, we previously showed in the Friend murine leukemia virus (F-MuLV) model that the surface Env protein gp70 also plays a role in immunosuppression, in addition to the immunosuppressive function attributed to the transmembrane Env protein. We now demonstrate that immunization with F-MuLV Env leads to a significant increase in interleukin-10 (IL-10)-producing CD4(+) T cells and that the induction of CD8(+) T-cell responses in the presence of Env is rescued if the capacity of CD4(+) T cells to produce IL-10 is abrogated, indicating a mechanistic role of IL-10-producing CD4(+) T cells in mediating the Env-induced suppression of CD8(+) T-cell responses in Env co-immunization. We found that CD8(+) T-cell responses against different immunogens are not all equally affected. On the other hand, suppression of immunity was observed not only in co-immunization experiments but also for immune control of subcutaneous tumor growth after an Env immunization. Finally, we show that suppression of CD8(+) T cells by the surface Env protein is observed not only for Friend MuLV Env but also for the Env proteins of other gamma retroviruses. Taken together, our results show that IL-10-producing CD4(+) T cells mechanistically underlie the Env-mediated suppression of CD8(+) T-cell responses and suggest the presence of an immunosuppressive motif in the surface Env protein of gamma retroviruses.
CRIS-Team WoS Importer:2023-01-13

Immunodominance of Adenovirus-Derived CD8+T Cell Epitopes Interferes with the Induction of Transgene-Specific Immunity in Adenovirus-Based Immunization - Schoene, Dominik; Hrycak, Camilla Patrizia; Windmann, Sonja; Lapuente, Dennis; Dittmer, Ulf; Tenbusch, Matthias; Bayer, Wibke (Journal of Virology, 2017)
Adenovirus (Ad)-based immunization is a popular approach in vaccine development, and Ad-based vectors are renowned for their potential to induce strong CD8+T cell responses to the encoded transgene. Surprisingly, we previously found in the mouse Friend retrovirus (FV) model that Ad-based immunization did not induce CD8+T cell responses to the FV Leader-Gag-derived immunodominant epitope GagL85-93We show now that induction of GagL85-93-specific CD8+T cells was highly effective when leader-Gag was delivered by plasmid DNA immunization, implying a role for Ad-derived epitopes in mediating unresponsiveness. By immunizing with DNA constructs encoding strings of GagL85-93and the two Ad-derived epitopes DNA-binding protein418-426(DBP418-426) and hexon486-494, we confirmed that Ad epitopes prevent induction of GagL85-93-specific CD8+T cells. Interestingly, while DBP418-426did not interfere with GagL85-93-specific CD8+T cell induction, the H-2Dd-restricted hexon486-494suppressed the CD8+T cell response to the H-2Db-restricted GagL85-93strongly in H-2b/dmice but not in H-2b/bmice. This finding indicates that competition occurs at the level of responding CD8+T cells, and we could indeed demonstrate that coimmunization with an interleukin 2 (IL-2)-encoding plasmid restored GagL85-93-specific CD8+T cell responses to epitope strings in the presence of hexon486-494IL-2 codelivery did not restore GagL85-93responsiveness in Ad-based immunization, however, likely due to the presence of further epitopes in the Ad vector. Our findings show that seemingly immunodominant transgene epitopes can be dominated by Ad-derived epitopes. These findings underline the importance of thorough characterization of vaccine vectors, and modifications of vectors or immunogens may be required to prevent impaired transgene-specific immune responses.IMPORTANCEAd-based vectors are widely used in experimental preclinical and clinical immunization studies against numerous infectious agents, such as human immunodeficiency virus, Ebola virus,Plasmodium falciparum, orMycobacterium tuberculosisPreexisting immunity to Ad-based vectors is widely recognized as a hindrance to the widespread use of Ad-based vectors for immunizations in humans; however, our data show that an immune response to Ad-derived T cell epitopes can also result in loss or impairment of transgene-specific immune responses in prenaive vaccinees due to immune competition. Our results highlight that seemingly immunodominant epitopes may be affected by dominance of vector-derived epitopes, and modifications of the vector design or the immunogens employed in immunization may lead to more effective vaccines.
EVALuna2:33756

Immunogenic and tolerogenic effects of the chimeric IL-2-diphtheria toxin cytocidal agent Ontak(®) on CD25(+) cells - Lutz, Manfred B.; Baur, Andreas; Schuler-Thurner, Beatrice; Schuler, Gerold (OncoImmunology, 2014)
Ontak(®), a conjugate between IL-2 and a diphtheria toxin fragment, was recently investigated in cancer clinical trials aiming to kill CD25(+) regulatory T cells (Tregs). We found that the activity of Ontak(®) was more complex on Tregs and conventional T cells (Tconvs) than anticipated, including a novel strong influence on dendritic cells (DCs).
EVALuna2:19435

Immunogenicity of Recombinant Lipid-Based Nanoparticle Vaccines: Danger Signal vs. Helping Hand - Temchura, Vladimir; Wagner, Jannik; Damm, Dominik (Pharmaceutics, 2024)
Infectious diseases are a predominant problem in human health. While the incidence of many pathogenic infections is controlled by vaccines, some pathogens still pose a challenging task for vaccine researchers. In order to face these challenges, the field of vaccine development has changed tremendously over the last few years. For non-replicating recombinant antigens, novel vaccine delivery systems that attempt to increase the immunogenicity by mimicking structural properties of pathogens are already approved for clinical applications. Lipid-based nanoparticles (LbNPs) of different natures are vesicles made of lipid layers with aqueous cavities, which may carry antigens and other biomolecules either displayed on the surface or encapsulated in the cavity. However, the efficacy profile of recombinant LbNP vaccines is not as high as that of live-attenuated ones. This review gives a compendious picture of two approaches that affect the immunogenicity of recombinant LbNP vaccines: (i) the incorporation of immunostimulatory agents and (ii) the utilization of pre-existing or promiscuous cellular immunity, which might be beneficial for the development of tailored prophylactic and therapeutic LbNP vaccine candidates.
CRIS-Team Scopus Importer:2024-02-02
Keywords: adjuvants; cellular immunity; heterologous T cell help; immunogenicity; intrastructural help; lipid-based nanoparticles; liposomes; Toll-like receptor ligand; universal T cell epitope; vaccine antigen

Immunohistochemical Demonstration of the pGlu79 alpha-Synuclein Fragment in Alzheimer's Disease and Its Tg2576 Mouse Model - Bluhm, Alexandra; Schrempel, Sarah; Schilling, Stephan; von Hörsten, Stephan; Schulze, Anja; Rossner, Steffen; Hartlage-Ruebsamen, Maike (Biomolecules, 2022)
The deposition of beta-amyloid peptides and of alpha-synuclein proteins is a neuropathological hallmark in the brains of Alzheimer's disease (AD) and Parkinson's disease (PD) subjects, respectively. However, there is accumulative evidence that both proteins are not exclusive for their clinical entity but instead co-exist and interact with each other. Here, we investigated the presence of a newly identified, pyroglutamate79-modified alpha-synuclein variant (pGlu79-aSyn)-along with the enzyme matrix metalloproteinase-3 (MMP-3) and glutaminyl cyclase (QC) implicated in its formation-in AD and in the transgenic Tg2576 AD mouse model. In the human brain, pGlu79-aSyn was detected in cortical pyramidal neurons, with more distinct labeling in AD compared to control brain tissue. Using immunohistochemical double and triple labelings and confocal laser scanning microscopy, we demonstrate an association of pGlu79-aSyn, MMP-3 and QC with beta-amyloid plaques. In addition, pGlu79-aSyn and QC were present in amyloid plaque-associated reactive astrocytes that were also immunoreactive for the chaperone heat shock protein 27 (HSP27). Our data are consistent for the transgenic mouse model and the human clinical condition. We conclude that pGlu79-aSyn can be generated extracellularly or within reactive astrocytes, accumulates in proximity to beta-amyloid plaques and induces an astrocytic protein unfolding mechanism involving HSP27.
CRIS-Team WoS Importer:2022-08-12

Impact of Adenovirus E4-ORF3 Oligomerization and Protein Localization on Cellular Gene Expression - Vink, Elizabeth I.; Zheng, Yueting; Yeasmin, Rukhsana; Stamminger, Thomas; Krug, Laurie T.; Hearing, Patrick (Viruses, 2015)
The Adenovirus E4-ORF3 protein facilitates virus replication through the relocalization of cellular proteins into nuclear inclusions termed tracks. This sequestration event disrupts antiviral properties associated with target proteins. Relocalization of Mre11-Rad50-Nbs1 proteins prevents the DNA damage response from inhibiting Ad replication. Relocalization of PML and Daxx impedes the interferon-mediated antiviral response. Several E4-ORF3 targets regulate gene expression, linking E4-ORF3 to transcriptional control. Furthermore, E4-ORF3 was shown to promote the formation of heterochromatin, down-regulating p53-dependent gene expression. Here, we characterize how E4-ORF3 alters cellular gene expression. Using an inducible, E4-ORF3-expressing cell line, we performed microarray experiments to highlight cellular gene expression changes influenced by E4-ORF3 expression, identifying over four hundred target genes. Enrichment analysis of these genes suggests that E4-ORF3 influences factors involved in signal transduction and cellular defense, among others. The expression of mutant E4-ORF3 proteins revealed that nuclear track formation is necessary to induce these expression changes. Through the generation of knockdown cells, we demonstrate that the observed expression changes may be independent of Daxx and TRIM33 suggesting that an additional factor(s) may be responsible. The ability of E4-ORF3 to manipulate cellular gene expression through the sequestration of cellular proteins implicates a novel role for E4-ORF3 in transcriptional regulation.
EVALuna2:8288

Impaired cytokine production of circulating immune cells in severe asthma in response to Influenza virus - Jameel, K. Jamal; Yanik, S.; Kamaci, C.; Weidinger, D.; Buelthoff, E.; Rohde, S.; Yusuf, F.; Kronsbein, J.; Tenbusch, Matthias; Knobloch, J. (EUROPEAN RESPIRATORY JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Impaired Decision Making and Loss of Inhibitory-Control in a Rat Model of Huntington Disease - El Massioui, Nicole; Lamirault, Charlotte; Yague, Sara; Adjeroud, Najia; Garces, Daniel; Maillard, Alexis; Tallot, Lucille; Yu-Taeger, Libo; Riess, Olaf; Allain, Philippe; Huu Phuc Nguyen,; von Hörsten, Stephan; et al. (Frontiers in Behavioral Neuroscience, 2016)
Cognitive deficits associated with Huntington disease (HD) are generally dominated by executive function disorders often associated with disinhibition and impulsivity/compulsivity. Few studies have directly examined symptoms and consequences of behavioral disinhibition in HD and its relation with decision-making. To assess the different forms of impulsivity in a transgenic model of HD (tgHD rats), two tasks assessing cognitive/choice impulsivity were used: risky decision-making with a rat gambling task (RGT) and intertemporal choices with a delay discounting task (DD). To assess waiting or action impulsivity the differential reinforcement of low rate of responding task (DRL) was used. In parallel, the volume as well as cellular activity of the amygdala was analyzed. In contrast to WT rats, 15 months old tgHD rats exhibited a poor efficiency in the RGT task with difficulties to choose advantageous options, a steep DD curve as delays increased in the DD task and a high rate of premature and bursts responses in the DRL task. tgHD rats also demonstrated a concomitant and correlated presence of both action and cognitive/choice impulsivity in contrast to wild type (WT) animals. Moreover, a reduced volume associated with an increased basal cellular activity of the central nucleus of amygdala indicated a dysfunctional amygdala in tgHD rats, which could underlie inhibitory dyscontrol. In conclusion, tgHD rats are a good model for impulsivity disorder that could be used more widely to identify potential pharmacotherapies to treat these invasive symptoms in HD.
EVALuna2:32793

IMU-838, a Developmental DHODH Inhibitor in Phase II for Autoimmune Disease, Shows Anti-SARS-CoV-2 and Broad-Spectrum Antiviral Efficacy In Vitro - Hahn, Friedrich; Wangen, Christina; Häge, Sigrun; Peter, Antonia Sophia; Dobler, Gerhard; Hurst, Brett; Julander, Justin; Fuchs, Jonas; Ruzsics, Zsolt; Überla, Klaus; Jäck, Hans-Martin; Ptak, Roger; et al. (Viruses, 2020)
The ongoing pandemic spread of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) demands skillful strategies for novel drug development, drug repurposing and cotreatments, in particular focusing on existing candidates of host-directed antivirals (HDAs). The developmental drug IMU-838, currently being investigated in a phase 2b trial in patients suffering from autoimmune diseases, represents an inhibitor of human dihydroorotate dehydrogenase (DHODH) with a recently proven antiviral activity in vitro and in vivo. Here, we established an analysis system for assessing the antiviral potency of IMU-838 and DHODH-directed back-up drugs in cultured cell-based infection models. By the use of SARS-CoV-2-specific immunofluorescence, Western blot, in-cell ELISA, viral yield reduction and RT-qPCR methods, we demonstrated the following: (i) IMU-838 and back-ups show anti-SARS-CoV-2 activity at several levels of viral replication, i.e., protein production, double-strand RNA synthesis, and release of infectious virus; (ii) antiviral efficacy in Vero cells was demonstrated in a micromolar range (IMU-838 half-maximal effective concentration, EC50, of 7.6 ± 5.8 µM); (iii) anti-SARS-CoV-2 activity was distinct from cytotoxic effects (half-cytotoxic concentration, CC50, >100 µM); (iv) the drug in vitro potency was confirmed using several Vero lineages and human cells; (v) combination with remdesivir showed enhanced anti-SARS-CoV-2 activity; (vi) vidofludimus, the active determinant of IMU-838, exerted a broad-spectrum activity against a selection of major human pathogenic viruses. These findings strongly suggest that developmental DHODH inhibitors represent promising candidates for use as anti-SARS-CoV-2 therapeutics.
CRIS-Team Scopus Importer:2020-12-25
Keywords: antiviral therapy; dihydroorotate dehydrogenase (DHODH) inhibitors; host-directed antivirals (HDAs); IMU-838; SARS-CoV-2; vidofludimus

IMU-838, a small molecule DHODH inhibitor in phase II clinical trial for multiple sclerosis, shows potent Anti-EBV activity in cell-culture-based systems: Potential additional benefits in multiple sclerosis treatment - Marschall, Manfred; Peelen, E.; Müller, Regina; Wangen, C.; Wagner, Sören; Muehler, A.; Groeppel, M.; Vitt, D.; Kohlhof, H.; Hahn, Friedrich (MULTIPLE SCLEROSIS JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-03

Increased malignancy of oral squamous cell carcinomas (oscc) is associated with macrophage polarization in regional lymph nodes - an immunohistochemical study - Wehrhan, Falk; Buettner-Herold, Maike; Hyckel, Peter; Moebius, Patrick; Preidl, Raimund; Distel, Luitpold; Ries, Jutta; Amann, Kerstin Ute; Schmitt, Christian; Neukam, Friedrich Wilhelm; Weber, Manuel (BMC Cancer, 2014)
It is largely accepted that specific immunological parameters in solid malignancies are associated with patient's prognosis. Recently a correlation of macrophage polarization with histomorphological parameters could also be shown in oral squamous cell carcinoma (oscc). The observed tumor derived peripheral immune tolerance could be associated with the macrophage polarization in regional tumor draining lymph nodes.So far there are no studies analyzing the macrophage polarization in cervical lymph nodes of oscc patients. In the present study we aimed to correlate macrophage polarization in different anatomical lymph node compartments of patients diagnosed with oscc with histopathologic parameters of the primary tumor (T-, N-, L-, V-, Pn-status, grading).Tumor free (n = 37) and metastatic (n = 17) lymph nodes of T1 and T2 oscc patients were processed for immunohistochemistry to detect CD68, CD11c, CD163 and MRC1 positive cells. Samples were digitized using whole slide imaging and the number of cells expressing the aforementioned markers in the region of interest quantitatively analyzed.The malignancy of the primary tumor (defined by T-, L-, Pn-status, grading) correlated with the lymph node macrophage polarization. L1 and Pn1 tumor cases displayed a significantly (p < 0.05) decreased M1 and increased M2 polarization in the sinus of the lymph nodes. G3 cases presented a significantly (p < 0.05) increased M2 polarization in the sinus compared to G2 cases. T2 tumors had significantly (p < 0.05) increased M2 polarization in the interfollicular zone of regional lymph nodes compared to T1 tumors. Metastatic and non-metastatic lymph nodes did not differ regarding their macrophage polarization.The current study revealed for the first time an influence of oscc on the macrophage polarization in regional lymph nodes. Markers of malignant behavior in the primary tumor were associated with a shift of macrophage polarization in lymph nodes from the anti-tumoral M1 type to the tumor-promoting M2 type. As tumor free and metastatic lymph nodes did not differ in terms of their macrophage polarization pattern, there must be other factors influencing the location for lymph node metastasis formation.
EVALuna2:18175

In-depth analysis of T cell immunity and antibody responses in heterologous prime-boost-boost vaccine regimens against SARS-CoV-2 and Omicron variant - Heinen, Natalie; Marheinecke, Corinna Sophie; Bessen, Clara; Blazquez-Navarro, Arturo; Roch, Toralf; Stervbo, Ulrik; Anft, Moritz; Plaza-Sirvent, Carlos; Busse, Sandra; Kloehn, Mara; Schrader, Jil; Blanco, Elena Vidal; et al. (Frontiers in Immunology, 2022)
With the emergence of novel Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) Variants of Concern (VOCs), vaccination studies that elucidate the efficiency and effectiveness of a vaccination campaign are critical to assess the durability and the protective immunity provided by vaccines. SARS-CoV-2 vaccines have been found to induce robust humoral and cell-mediated immunity in individuals vaccinated with homologous vaccination regimens. Recent studies also suggest improved immune response against SARS-CoV-2 when heterologous vaccination strategies are employed. Yet, few data exist on the extent to which heterologous prime-boost-boost vaccinations with two different vaccine platforms have an impact on the T cell-mediated immune responses with a special emphasis on the currently dominantly circulating Omicron strain. In this study, we collected serum and peripheral blood mononuclear cells (PBMCs) from 57 study participants of median 35-year old's working in the health care field, who have received different vaccination regimens. Neutralization assays revealed robust but decreased neutralization of Omicron VOC, including BA.1 and BA.4/5, compared to WT SARS-CoV-2 in all vaccine groups and increased WT SARS-CoV-2 binding and neutralizing antibodies titers in homologous mRNA prime-boost-boost study participants. By investigating cytokine production, we found that homologous and heterologous prime-boost-boost-vaccination induces a robust cytokine response of CD4(+) and CD8(+) T cells. Collectively, our results indicate robust humoral and T cell mediated immunity against Omicron in homologous and heterologous prime-boost-boost vaccinated study participants, which might serve as a guide for policy decisions.
CRIS-Team WoS Importer:2023-01-27

Induction of Labour: Change of Method and its Effects - Kehl, Sven; Weiss, C.; Dammer, U.; Raabe, E.; Burghaus, Stefanie; Heimrich, J.; Hackl, J.; Winkler, Michael; Beckmann, Matthias; Faschingbauer, Florian (Geburtshilfe und Frauenheilkunde, 2015)
Aim: The combination of mechanical and drug procedures for the induction of labour seems to be beneficial. Accordingly, the normal procedure in clinical routine has been changed and induction of labour by means of a balloon catheter has been implemented. The aim of this study was to find out if this procedural change has resulted in a more effective induction of labour. Materials and Method: In this historical cohort study 230 inductions of labour at term in the year 2012 were compared with 291 inductions of labour in the year 2013, all at the University of Erlangen Perinatal Centre. Exclusion criteria were, among others, a multiple pregnancy, a premature rupture of membranes and a prior Caesarean section. In 2012 births were induced solely by use of the drugs dinoprostone and misoprostol, in 2013 not only with misoprostol but also mainly by use of a balloon catheter. The primary target parameter was the rate of failed labour inductions, defined as "no birth within 72 hours". Results: Altogether 521 inductions of labour were analysed. The rate of failed inductions of labour could be reduced by the changes in induction method (first-time mothers: 23 vs. 9 %, p = 0.0059; multiparous women: 10 vs. 1 %, p = 0.0204). Furthermore, the rate of primary Caesarean sections due to failed induction of labour (5.7 vs. 1.4 %, p = 0.0064), that of the observation of green amniotic fluid (first-time mothers: 23 vs. 9 %, p = 0.0059; multiparous women: 10 vs. 1 %, p = 0.0204) and of infantile infections (first-time mothers: 23 vs. 9 %, p = 0.0059; multiparous women: 10 vs. 1 %, p = 0.0204) were all reduced as well. Conclusion: The routine use of a balloon catheter for induction of labour has markedly improved the procedure. There were fewer failed labour inductions and fewer Caesarean sections due to failed induction of labour.
EVALuna2:17598

Induction of the NF-kb signal transduction pathway in response to Corynebacterium diphtheriae infection - Ott, Lisa; Scholz, Brigitte; Höller, Martina; Hasselt, Kristin; Enßer, Armin; Burkovski, Andreas (Microbiology, 2013)

Infection as a cause of childhood leukemia: virus detection employing whole genome sequencing - Bartenhagen, Christoph; Fischer, Ute; Korn, Klaus; Pfister, Stefan M.; Gombert, Michael; Chen, Cai; Okpanyi, Vera; Hauer, Julia; Rinaldi, Anna; Bourquin, Jean-Pierre; Eckert, Cornelia; Hu, Jianda; et al. (Haematologica, 2017)
EVALuna2:33763

Influence of Human Cytomegalovirus Glycoprotein O Polymorphism on the Inhibitory Effect of Soluble Forms of Trimer- and Pentamer-Specific Entry Receptors - Brait, Nadja; Stoegerer, Tanja; Kalser, Julia; Adler, Barbara; Kunz, Ines; Benesch, Max; Kropff, Barbara; Mach, Michael; Puchhammer-Stoeckl, Elisabeth; Goerzer, Irene (Journal of Virology, 2020)
Human cytomegalovirus (HCMV) envelope glycoprotein complexes, gH/gL/gO trimer and gH/gL/UL128-131 pentamer, are important for cell-free HCMV entry. While soluble NRP2-Fc (sNRP2-Fc) interferes with epithelial/endothelial cell entry through UL128, soluble platelet-derived growth factor receptor alpha-Fc (sPDGFR alpha-Fc) interacts with gO, thereby inhibiting infection of all cell types. Since gO is the most variable subunit, we investigated the influence of gO polymorphism on the inhibitory capacities of sPDGFR alpha-Fc and sNRP2-Fc. Accordingly, gO genotype 1c (GT1c) sequence was fully or partially replaced by gO GT2b, GT3, and GT5 sequences in the bacterial artificial chromosome (BAC) TB40-BAC4-luc background (where luc is luciferase). All mutants were tested for fibroblast and epithelial cell infectivity, for virion content of gB, gH, and gO, and for infection inhibition by sPDGFR alpha-Fc and sNRP2-Fc. Full-length and partial gO GT swapping may increase epithelial-to-fibroblast ratios due to subtle alterations in fibroblast and/or epithelial infectivity but without substantial changes in gB and gH levels in mutant virions. All gO GT mutants except recombinant gO GT1c/3 displayed a nearly complete inhibition at 1.25 mu g/ml sPDGFR alpha-Fc on epithelial cells (98% versus 91%), and all experienced complete inhibition on fibroblasts (>= 99%). While gO GT replacement did not influence sNRP2-Fc inhibition at 1.25 mu g/ml on epithelial cells (97% to 99%), it rendered recombinant mutant GT1c/3 moderately accessible to fibroblast inhibition (40%). In contrast to the steep sPDGFR alpha-Fc inhibition curves (slope of >1.0), sNRP2-Fc dose-response curves on epithelial cells displayed slopes of similar to 1.0, suggesting functional differences between these entry inhibitors. Our findings demonstrate that artificially generated gO recombinants rather than the major gO genotypic forms may affect the inhibitory capacities of sPDGFR alpha and sNRP2 in a cell type-dependent manner.
CRIS-Team WoS Importer:2020-08-07

Influenza A virus drift variants reduced the detection sensitivity of a commercial multiplex nucleic acid amplification assay in the season 2014/15 - Huzly, Daniela; Korn, Klaus; Bierbaum, Sibylle; Eberle, Bjoern; Falcone, Valeria; Knöll, Antje; Steininger, Philipp; Panning, Marcus (Archives of Virology, 2016)
The influenza season 2014/15 was dominated by drift variants of influenza A(H3N2), which resulted in a reduced vaccine effectiveness. It was not clear if the performance of commercial nucleic-acid-based amplification (NAT) assays for the detection of influenza was affected. The purpose of this study was to perform a real-life evaluation of two commercial NAT assays. During January-April 2015, we tested a total of 665 samples from patients with influenza-like illness using the Fast Track Diagnostics Respiratory pathogens 21, a commercial multiplex kit, (cohorts 1 and 2, n = 563 patients) and the Xpert Flu/RSV XC assay (cohort 3, n = 102 patients), a single-use cartridge system. An in-house influenza real-time RT-PCR (cohort 1) and the RealStar Influenza RT-PCR 1.0 Kit (cohort 2 and 3) served as reference tests. Compared to the reference assay, an overall agreement of 95.9 % (cohort 1), 95 % (cohort 2), and 98 % (cohort 3) was achieved. A total of 24 false-negative results were observed using the Fast Track Diagnostics Respiratory pathogens 21 kit. No false-negative results occurred using the Xpert Flu/RSV XC assay. The Fast Track Diagnostics Respiratory pathogens 21 kit and the Xpert Flu/RSV XC assay had sensitivities of 90.7 % and 100 % and specificities of 100 % and 94.1 %, respectively, compared to the RealStar 1.0 kit. Upon modification of the Fast Track Diagnostics Respiratory pathogens 21 kit, the sensitivity increased to 97.3 %. Influenza virus strains circulating during the 2014/15 season reduced the detection sensitivity of a commercial NAT assay, and continuous monitoring of test performance is therefore necessary.
EVALuna2:8334

Inherited human IFN-γ deficiency underlies mycobacterial disease - Kerner, Gaspard; Rosain, Jérémie; Guérin, Antoine; Al-Khabaz, Ahmad; Oleaga-Quintas, Carmen; Rapaport, Franck; Massaad, Michel J.; Ding, Jing Ya; Khan, Taushif; Ali, Fatima Al; Rahman, Mahbuba; Deswarte, Caroline; et al. (Journal of Clinical Investigation, 2020)
Mendelian susceptibility to mycobacterial disease (MSMD) is characterized by a selective predisposition to clinical disease caused by the Bacille Calmette-Guérin (BCG) vaccine and environmental mycobacteria. The known genetic etiologies of MSMD are inborn errors of IFN-γ immunity due to mutations of 15 genes controlling the production of or response to IFN-γ. Since the first MSMD-causing mutations were reported in 1996, biallelic mutations in the genes encoding IFN-γ receptor 1 (IFN-γR1) and IFN-γR2 have been reported in many patients of diverse ancestries. Surprisingly, mutations of the gene encoding the IFN-γ cytokine itself have not been reported, raising the remote possibility that there might be other agonists of the IFN-γ receptor. We describe 2 Lebanese cousins with MSMD, living in Kuwait, who are both homozygous for a small deletion within the IFNG gene (c.354-357del), causing a frameshift that generates a premature stop codon (p.T119Ifs4∗). The mutant allele is loss of expression and loss of function. We also show that the patients' herpesvirus Saimiri-immortalized T lymphocytes did not produce IFN-γ, a phenotype that can be rescued by retrotransduction with WT IFNG cDNA. The blood T and NK lymphocytes from these patients also failed to produce and secrete detectable amounts of IFN-γ. Finally, we show that human IFNG has evolved under stronger negative selection than IFNGR1 or IFNGR2, suggesting that it is less tolerant to heterozygous deleterious mutations than IFNGR1 or IFNGR2. This may account for the rarity of patients with autosomal-recessive, complete IFN-γ deficiency relative to patients with complete IFN-γR1 and IFN-γR2 deficiencies.
CRIS-Team Scopus Importer:2020-06-16

Inhibition of cGAS DNA Sensing by a Herpesvirus Virion Protein - Wu, Jian-Jun; Li, Wenwei; Shao, Yaming; Avey, Denis; Fu, Bishi; Gillen, Joseph; Hand, Travis; Ma, Siming; Liu, Xia; Miley, Wendell; Konrad, Andreas; Neipel, Frank; et al. (Cell Host & Microbe, 2015)
Invading viral DNA can be recognized by the host cytosolic DNA sensor, cyclic GMP-AMP (cGAMP) synthase (cGAS), resulting in production of the second messenger cGAMP, which directs the adaptor protein STING to stimulate production of type I interferons (IFNs). Although several DNA viruses are sensed by cGAS, viral strategies targeting cGAS are virtually unknown. We report here that Kaposi's sarcoma-associated herpesvirus (KSHV) ORF52, an abundant gammaherpesvirus-specific tegument protein, subverts cytosolic DNA sensing by directly inhibiting cGAS enzymatic activity through a mechanism involving both cGAS binding and DNA binding. Moreover, ORF52 homologs in other gammaherpesviruses also inhibit cGAS activity and similarly bind cGAS and DNA, suggesting conserved inhibitory mechanisms. Furthermore, KSHV infection evokes cGAS-dependent responses that can limit the infection, and an ORF52 null mutant exhibits increased cGAS signaling. Our findings reveal a mechanism through which gammaherpesviruses antagonize host cGAS DNA sensing.
EVALuna2:8258

Inhibition of HIV-1 infection by human pegivirus type 1-derived peptides is affected by human pegivirus type 1 genotype and HIV-1 coreceptor tropism - Ruegamer, Tamara; Hoffmann, Rebecca; Rohrhofer, Anette; Audebert, Franz; Salzberger, Bernd; Korn, Klaus; Schuster, Philipp; Eichler, Jutta; Schmidt, Barbara (Aids, 2018)
Objective(s): Up to 40% of HIV-1 infected individuals are coinfected with human pegivirus type 1 (HPgV-1). The majority of studies, but not all, have reported a beneficial effect of HPgV-1 coinfection on HIV-1 disease progression. So far, the impact of different HPgV-1 genotypes on different HIV-1 subtypes remains unclear. Methods: Peptides derived from HPgV-1 envelope protein E2, and representing different viral genotypes, were synthesized using Fmoc/t-Bu-based solid phase peptide synthesis. The inhibitory effect of these peptides on the infection of reporter cell lines was tested using an HIV-1 subtype panel representing clades A (n = 2), AG (n = 2), B (n = 6), C (n = 2), D (n = 2), F (n = 2), G (n = 1), G/H (n = 1), and group O (n = 2). Results: HIV-1 infection was blocked more efficiently by peptides derived from HPgV-1 GT2 than GT1 (P = 0.05). The HIV-1 subtype did not affect the degree of inhibition by a peptide derived from HPgV-1 GT2. All CXCR4-/dual-tropic isolates (n = 12), but only half (four out of eight) CCR5-tropic viruses were inhibited by this peptide (P = 0.014). Conclusion: Our data indicate that the inhibitory effect of peptides derived from HPgV-1 E2 protein is dependent on the genotype, suggesting that coinfection with HPgV-1 GT1 is less likely to confer a beneficial effect on HIV-1 disease progression than GT2. The preferential suppression of more pathogenic CXCR4-tropic HIV-1 by peptides derived from HPgV-1 GT2 may explain the favorable effect in patients harboring these HIV-1 isolates. Consequently, HPgV-1 genotype and HIV-1 coreceptor tropism are likely determinants for the beneficial effect of HPgV-1 co-infection in HIV-1-infected individuals. Copyright (C) 2018 Wolters Kluwer Health, Inc. All rights reserved.
EVALuna2:35265

Inhibitors of Deubiquitinating Enzymes Block HIV-1 Replication and Augment the Presentation of Gag-Derived MHC-I Epitopes - Setz, Christian; Friedrich, Melanie; Rauch, Pia; Fraedrich, Kirsten; Matthaei, Alina; Traxdorf, Maximilian; Schubert, Ulrich (Viruses, 2017)
In recent years it has been well established that two major constituent parts of the ubiquitin proteasome system (UPS)-the proteasome holoenzymes and a number of ubiquitin ligases-play a crucial role, not only in virus replication but also in the regulation of the immunogenicity of human immunodeficiency virus type 1 (HIV-1). However, the role in HIV-1 replication of the third major component, the deubiquitinating enzymes (DUBs), has remained largely unknown. In this study, we show that the DUB-inhibitors (DIs) P22077 and PR-619, specific for the DUBs USP7 and USP47, impair Gag processing and thereby reduce the infectivity of released virions without affecting viral protease activity. Furthermore, the replication capacity of X4- and R5-tropic HIV-1NL4-3in human lymphatic tissue is decreased upon treatment with these inhibitors without affecting cell viability. Most strikingly, combinatory treatment with DIs and proteasome inhibitors synergistically blocks virus replication at concentrations where mono-treatment was ineffective, indicating that DIs can boost the therapeutic effect of proteasome inhibitors. In addition, P22077 and PR-619 increase the polyubiquitination of Gag and thus its entry into the UPS and the major histocompatibility complex (MHC)-I pathway. In summary, our data point towards a model in which specific inhibitors of DUBs not only interfere with virus spread but also increase the immune recognition of HIV-1 expressing cells.
EVALuna2:33758

Inhibitors of Deubiquitinating Enzymes Interfere with the SARS-CoV-2 Papain-like Protease and Block Virus Replication In Vitro - Große, Maximilian; Setz, Christian; Rauch, Pia; Auth, Janina; Morokutti-Kurz, Martina; Temchura, Vladimir; Schubert, Ulrich (Viruses, 2022)
The ubiquitin proteasome system (UPS), particularly its deubiquitinating enzymes (DUBs), play a key role in the replication cycle of coronaviruses. The SARS-CoV-2 papain-like protease (Plpro) is known to process the viral polyproteins to form the replicase transcriptase complex and to counteract the host viral response. Recently, it was shown that this viral protease can also act as a deubiquitinating enzyme. In this study, we demonstrate that certain DUB-Inhibitors (DIs) interfere with SARS-CoV-2 replication. The DIs PR-619 and HBX41108 restrict SARS-CoV-2 in both Vero B4 and human Calu-3 lung cells where cells were infected with a Multiplicity of Infection (MOI) of 0.02. An in vitro protease assay using recombinant Plpro and Amido-4-methylcoumarin (AMC)-conjugated substrate revealed that PR-619 and HBX41108 are able to block the protease at concentrations where the interventions restricted virus replication. In contrast, DIs that do not inhibit Plpro had no influence on virus replication, which indicated that the protease might be at least one major target. Future vertical studies that would gain more insights into the mechanisms of how DUBs effect the replication of SARS-CoV-2 will further validate them as a potential therapeutic target.
CRIS-Team Scopus Importer:2022-07-15
Keywords: coronavirus; COVID-19; deubiquitinating enzymes; inhibitors of deubiquitinating enzymes; papain-like protease; SARS-CoV-2; ubiquitin proteasome system; USP7

Inhibitors of dual-specificity tyrosine phosphorylation-regulated kinases (DYRK) exert a strong anti-herpesviral activity - Hutterer, Corina; Milbradt, Jens; Hamilton, Stuart; Zaja, Mirko; Leban, Johann; Henry, Christophe; Vitt, Daniel; Steingruber, Mirjam; Sonntag, Eric; Zeitträger, Isabel; Bahsi, Hanife; Stamminger, Thomas; et al. (Antiviral Research, 2017)
Infection with human cytomegalovirus (HCMV) is a serious medical problem, particularly in immunocompromised individuals and neonates. The success of (val)ganciclovir therapy is hampered by low drug compatibility and induction of viral resistance. A novel strategy of antiviral treatment is based on the exploitation of cell-directed signaling, e. g. pathways with a known relevance for carcinogenesis and tumor drug development. Here we describe a principle for putative antiviral drugs based on targeting dual-specificity tyrosine phosphorylation-regulated kinases (DYRKs). DYRKs constitute an evolutionarily conserved family of protein kinases with key roles in the control of cell proliferation and differentiation. Members of the DYRK family are capable of phosphorylating a number of substrate proteins, including regulators of the cell cycle, e.g. DYRK1B can induce cell cycle arrest, a critical step for the regulation of HCMV replication. Here we provide first evidence for a critical role of DYRKs during viral replication and the high antiviral potential of DYRK inhibitors (SC84227, SC97202 and SC97208, Harmine and AZ-191). Using established replication assays for laboratory and clinically relevant strains of HCMV, concentration-dependent profiles of inhibition were obtained. Mean inhibitory concentrations (EC50) of 0.98 ± 0.08 μM/SC84227, 0.60 ± 0.02 μM/SC97202, 6.26 ± 1.64 μM/SC97208, 0.71 ± 0.019 μM/Harmine and 0.63 ± 0.23 μM/AZ-191 were determined with HCMV strain AD169-GFP for the infection of primary human fibroblasts. A first analysis of the mode of antiviral action suggested a block of viral replication at the early-late stage of HCMV gene expression. Moreover, rhesus macaque cytomegalovirus (RhCMV), varicella-zoster virus (VZV) and herpes simplex virus (HSV-1) showed a similarly high sensitivity to these compounds. Thus, we conclude that DYRK signaling represents a promising target pathway for the development of novel anti-herpesviral strategies.
EVALuna2:33759

Innate extracellular vesicles from melanoma patients suppress beta-catenin in tumor cells by miRNA-34a - Lee, Jung-Hyun; Dindorf, Jochen; Eberhardt, Martin; Lai, Xin; Ostalecki, Christian; Koliha, Nina; Gross, Stefani; Blume, Katja; Bruns, Heiko; Wild, Stefan; Schuler, Gerold; Vera, Julio; et al. (Life Science Alliance, 2019)
Upon tumor development, new extracellular vesicles appear in circulation. Our knowledge of their relative abundance, function, and overall impact on cancer development is still preliminary. Here, we demonstrate that plasma extracellular vesicles (pEVs) of non-tumor origin are persistently increased in untreated and post-excision melanoma patients, exhibiting strong suppressive effects on the proliferation of tumor cells. Plasma vesicle numbers, miRNAs, and protein levels were elevated two-to tenfold and detected many years after tumor resection. The vesicles revealed individual and clinical stage-specific miRNA profiles as well as active ADAM10. However, whereas pEV from patients preventing tumor relapse down-regulated beta-catenin and blocked tumor cell proliferation in an miR-34a-dependent manner, pEV from metastatic patients lost this ability and stimulated beta-catenin-mediated transcription. Cancer-induced pEV may constitute an innate immune mechanismsuppressing tumor cell activity including that of residual cancer cells present after primary surgery.
CRIS-Team WoS Importer:2019-05-17

Innate nuclear sensor IFI16 translocates into the cytoplasm during the early stage of in vitro human cytomegalovirus infection and is entrapped in the egressing virions during the late stage - Dell'Oste, Valentina; Gatti, Deborah; Gugliesi, Francesca; De Andrea, Marco; Bawadekar, Mandar; Lo Cigno, Irene; Biolatti, Matteo; Vallino, Marta; Marschall, Manfred; Gariglio, Marisa; Landolfo, Santo (Journal of Virology, 2014)
Intrinsic immune mechanisms mediated by constitutively expressed proteins termed "restriction factors" provide frontline antiviral defense. We recently demonstrated that the DNA sensor IFI16 restricts human cytomegalovirus (HCMV) replication by downregulating viral early and late but not immediate-early mRNAs and their protein expression. We show here that at an early time point during the in vitro infection of low-passage-number human embryonic lung fibroblasts, IFI16 binds to HCMV DNA. However, during a later phase following infection, IFI16 is mislocalized to the cytoplasmic virus assembly complex (AC), where it colocalizes with viral structural proteins. Indeed, upon its binding to pUL97, IFI16 undergoes phosphorylation and relocalizes to the cytoplasm of HCMV-infected cells. ESCRT (endosomal sorting complex required for transport) machinery regulates the translocation of IFI16 into the virus AC by sorting and trafficking IFI16 into multivesicular bodies (MVB), as demonstrated by the interaction of IFI16 with two MVB markers: Vps4 and TGN46. Finally, IFI16 becomes incorporated into the newly assembled virions as demonstrated by Western blotting of purified virions and electron microscopy. Together, these results suggest that HCMV has evolved mechanisms to mislocalize and hijack IFI16, trapping it within mature virions. However, the significance of this IFI16 trapping following nuclear mislocalization remains to be established.Intracellular viral DNA sensors and restriction factors are critical components of host defense, which alarm and sensitize immune system against intruding pathogens. We have recently demonstrated that the DNA sensor IFI16 restricts human cytomegalovirus (HCMV) replication by downregulating viral early and late but not immediate-early mRNAs and their protein expression. However, viruses are known to evolve numerous strategies to cope and counteract such restriction factors and neutralize the first line of host defense mechanisms. Our findings describe that during early stages of infection, IFI16 successfully recognizes HCMV DNA. However, in late stages HCMV mislocalizes IFI16 into the cytoplasmic viral assembly complex and finally entraps the protein into mature virions. We clarify here the mechanisms HCMV relies to overcome intracellular viral restriction, which provides new insights about the relevance of DNA sensors during HCMV infection.
EVALuna2:8250

Innate signalling molecules as genetic adjuvants do not alter the efficacy of a DNA-based influenza A vaccine - Lapuente, Dennis; Stab, Viktoria; Storcksdieck, Michael; Maaske, Andre; Köster, Mario; Xiao, Han; Ehrhardt, Christina; Tenbusch, Matthias (PLoS ONE, 2020)
In respect to the heterogeneity among influenza A virus strains and the shortcomings of current vaccination programs, there is a huge interest in the development of alternative vaccines that provide a broader and more long-lasting protection. Gene-based approaches are considered as promising candidates for such flu vaccines. In our study, innate signalling molecules from the RIG-I and the NALP3 pathways were evaluated as genetic adjuvants in intramuscular DNA immunizations. Plasmids encoding a constitutive active form of RIG-I (cRIG-I), IPS-1, IL-1β, or IL-18 were co-administered with plasmids encoding the hemagglutinin and nucleoprotein derived from H1N1/Puerto Rico/8/1934 via electroporation in BALB/c mice. Immunogenicity was analysed in detail and efficacy was demonstrated in homologous and heterologous influenza challenge experiments. Although the biological activities of the adjuvants have been confirmed by in vitro reporter assays, their single or combined inclusion in the vaccine did not result in superior vaccine efficacy. With the exception of significantly increased levels of antigen-specific IgG1 after the co-administration of IL-1β, there were only minor alterations concerning the immunogenicity. Since DNA electroporation alone induced substantial inflammation at the injection site, as demonstrated in this study using Mx2-Luc reporter mice, it might override the adjuvants' contribution to the inflammatory microenvironment and thereby minimizes the influence on the immunogenicity. Taken together, the DNA immunization was protective against subsequent challenge infections but could not be further improved by the genetic adjuvants analysed in this study.
CRIS-Team Scopus Importer:2020-04-17

In situ enzymatic activity of transglutaminase isoforms on brain tissue sections of rodents: A new approach to monitor differences in post-translational protein modifications during neurodegeneration - Schulze-Krebs, Anja; Canneva, Fabio; Schnepf, Rebecca; Dobner, Julia; Dieterich, Walburga; von Hörsten, Stephan (Brain Research, 2016)
Mammalian transglutaminases (TGs) catalyze the irreversible post-translational modifications of proteins, the most prominent of which is the calcium-dependent formation of covalent acyl transfers between the ?-carboxamide group of glutamine and the ?-amino-group of lysine (GGEL-linkage). In the central nervous system, at least four TG isoforms are present and some of them are differentially expressed under pathological conditions in human patients. However, the precise TG-isoform-dependent enzymatic activities in the brain as well as their anatomical distribution are unknown. Specificity of the used biotinylated peptides was analyzed using an in vitro assay. Isoform-specific TG activity was evaluated in in vitro and in situ studies, using brain extracts and native brain tissue obtained from rodents. Our method allowed us to reveal in vitro and in situ TG-isoform-dependent enzymatic activity in brain extracts and tissue of rats and mice, with a specific focus on TG6. In situ activity of this isoform varied between BACHD mice in comparison to their wt controls. TG isozyme-specific activity can be detected by isoform-specific biotinylated peptides in brain tissue sections of rodents to reveal differences in the anatomical and/or subcellular distribution of TG activity. Our findings yield the basis for a broader application of this method for the screening of pathological expression and activity of TGs in a variety of animal models of human diseases, as in the case of neurodegenerative conditions such as Huntington?s, Parkinson?s and Alzheimer?s, where protein modification is involved as a key mechanism of disease progression.
EVALuna2:2088

Interactions of LSECtin and DC-SIGN/DC-SIGNR with viral ligands: Differential pH dependence, internalization and virion binding - Gramberg, Thomas; Soilleux, Elizabeth; Fisch, Tanja; Lalor, Patricia F.; Hofmann, Heike; Wheeldon, Sophie; Cotterill, Andrew; Wegele, Anja; Winkler, Thomas; Adams, David H.; Poehlmann, Stefan (Virology, 2008)
The calcium-dependent lectins DC-SIGN and DC-SIGNR (collectively termed DC-SIGN/R) bind to high-mannose carbohydrates on a variety of viruses. In contrast, the related lectin LSECtin does not recognize mannose-rich glycans and interacts with a more restricted spectrum of viruses. Here, we analyzed whether these lectins differ in their mode of ligand engagement. LSECtin and DC-SIGNR, which we found to be co-expressed by liver, lymph node and bone marrow sinusoidal endothelial cells, bound to soluble Ebola virus glycoprotein (EBOV-GP) with comparable affinities. Similarly, LSECtin, DC-SIGN and the Langerhans cell-specific lectin Langerin readily bound to soluble human immunodeficiency virus type-1 (HIV-1) GP. However, only DC-SIGN captured HIV-1 particles, indicating that binding to soluble GP is not necessarily predictive of binding to virion-associatedGP. Capture of EBOV-GP by LSECtin triggered ligand internalization, suggesting that LSECtin like DC-SIGN might function as an antigen uptake receptor. However, the intracellular fate of lectin-ligand complexes might differ. Thus, exposure to low-pH medium, which mimics the acidic luminal environment in endosomes/lysosomes, released ligand bound to DC-SIGN/R but had no effect on LSECtin interactions with ligand. Our results reveal important differences between pathogen capture by DC-SIGN/R and LSECtin and hint towards different biological functions of these lectins. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: LSECtin; DC-SIGN; HIV; attachment; lectin; Ebola

Interference of retroviral envelope with vaccine-induced CD8+T cell responses is relieved by co-administration of cytokine-encoding vectors - Bongard, Nadine; Lapuente, Dennis; Windmann, Sonja; Dittmer, Ulf; Tenbusch, Matthias; Bayer, Wibke (Retrovirology, 2017)
BACKGROUND: Retroviral envelope (Env) proteins are known to exhibit immunosuppressive properties, which become apparent not only in retroviral infections, but also in gene-based immunizations using retroviral immunogens, where envelope interferes with the induction of CD8+T cell responses towards another, simultaneously or subsequently delivered, immunogen. RESULTS: In the Friend retrovirus mouse model, immunization with a plasmid encoding the Friend murine leukemia virus (F-MuLV) Leader-Gag protein resulted in induction of a strong GagL85-93-specific CD8+T cell response, while the response was completely abrogated by co-immunization with an F-MuLV Env-encoding plasmid. In order to overcome this interference of retroviral envelope, we employed plasmids encoding the cytokines interleukin (IL) 1β, IL2, IL12, IL15, IL21, IL28A or granulocyte-macrophage colony-stimulating factor (GM-CSF) as genetic adjuvants. Co-application of plasmids encoding IL2, IL12, IL21, IL28A and especially GM-CSF rescued the induction of GagL85-93-specific CD8+T cells in mice vaccinated with FV Leader-Gag and Env. Mice that were immunized with plasmids encoding Leader-Gag and Env and the cytokines IL1β, IL12, IL15, IL28A or GM-CSF, but not Leader-Gag and Env without any cytokine, showed significantly reduced viral loads upon a high-dose Friend virus challenge infection. CONCLUSIONS: Our data demonstrate the potency of cytokine-encoding vectors as adjuvants and immune modulators in composite vaccines for anti-retroviral immunization.
EVALuna2:33766

Interleukin-1 beta activates essential checkpoints in the formation of lung-resident memory T cell - Lapuente, D.; Fuchs, J.; Maier, Carolin; Bonsmann, M. Storcksdieck Genannt; Maaske, A.; Stab, V.; Heinecke, V.; Liedtke, K.; Hess, R.; Westendorf, A.; Bayer, W.; Ehrhardt, C.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Interleukin-3 is a predictive marker for severity and outcome during SARS-CoV-2 infections - Bénard, Alan; Jacobsen, Anne; Brunner, Maximilian; Krautz, Christian; Klösch, Bettina; Swierzy, Izabela; Naschberger, Elisabeth; Podolska, Malgorzata; Kouhestani, Dina; David, Paul; Birkholz, Torsten; Castellanos, Ixchel; et al. (Nature Communications, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide health threat. In a prospective multicentric study, we identify IL-3 as an independent prognostic marker for the outcome during SARS-CoV-2 infections. Specifically, low plasma IL-3 levels is associated with increased severity, viral load, and mortality during SARS-CoV-2 infections. Patients with severe COVID-19 exhibit also reduced circulating plasmacytoid dendritic cells (pDCs) and low plasma IFNα and IFNλ levels when compared to non-severe COVID-19 patients. In a mouse model of pulmonary HSV-1 infection, treatment with recombinant IL-3 reduces viral load and mortality. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating pDCs into the airways by stimulating CXCL12 secretion from pulmonary CD123+ epithelial cells, both, in mice and in COVID-19 negative patients exhibiting pulmonary diseases. This study identifies IL-3 as a predictive disease marker for SARS-CoV-2 infections and as a potential therapeutic target for pulmunory viral infections.
CRIS-Team Scopus Importer:2021-03-05

Intracellular African swine fever virus DNA remains unmethylated in infected Vero cells - Weber, Stefanie; Hakobyan, Astghik; Zakaryan, Hovakim; Doerfler, Walter (Epigenomics, 2018)
Aim: Sequence-specific CpG methylation of eukaryotic promoters is an important epigenetic signal for long-term gene silencing. We have now studied the methylation status of African swine fever virus (ASFV) DNA at various times after infection of Vero cells in culture. Methods & results: ASFV DNA was detectable throughout the infection cycle and was found unmethylated in productively infected Vero cells as documented by bisulfite sequencing of 13 viral DNA segments. Conclusion: ASFV DNA does not become de novo methylated in the course of infection in selected segments spread across the entire genome. Thus DNA methylation does not interfere with ASFV genome transcription. Lack of de novo methylation has previously been observed for free intracellular viral DNA in cells permissively infected with human adenoviruses, with human papillomaviruses and others.
EVALuna2:35287

Intracellular localization map of human herpesvirus 8 proteins. - Sander, Gaby; Konrad, Andreas; Thurau, Mathias; Wies, Effi; Leubert, Rene; Kremmer, Elisabeth; Dinkel, Holger; Schulz, Thomas; Neipel, Frank; Stürzl, Michael (Journal of Virology, 2008)
Human herpesvirus 8 (HHV-8) is the etiological agent of Kaposi's sarcoma. We present a localization map of 85 HHV-8-encoded proteins in mammalian cells. Viral open reading frames were cloned with a Myc tag in expression plasmids, confirmed by full-length sequencing, and expressed in HeLa cells. Protein localizations were analyzed by immunofluorescence microscopy. Fifty-one percent of all proteins were localized in the cytoplasm, 22% were in the nucleus, and 27% were found in both compartments. Surprisingly, we detected viral FLIP (v-FLIP) in the nucleus and in the cytoplasm, whereas cellular FLIPs are generally localized exclusively in the cytoplasm. This suggested that v-FLIP may exert additional or alternative functions compared to cellular FLIPs. In addition, it has been shown recently that the K10 protein can bind to at least 15 different HHV-8 proteins. We noticed that K10 and only five of its 15 putative binding factors were localized in the nucleus when the proteins were expressed in HeLa cells individually. Interestingly, in coexpression experiments K10 colocalized with 87% (13 of 15) of its putative binding partners. Colocalization was induced by translocation of either K10 alone or both proteins. These results indicate active intracellular translocation processes in virus-infected cells. Specifically in this framework, the localization map may provide a useful reference to further elucidate the function of HHV-8-encoded genes in human diseases.

Intracellular trafficking of the human cytomegalovirus-encoded 7-trans-membrane protein homologs pUS27 and pUL78 during viral infection: a comparative analysis - Niemann, Ina; Reichel, Anna; Stamminger, Thomas (Viruses, 2014)
Human cytomegalovirus (HCMV) encodes four G protein-coupled receptor (GPCR) homologs, termed pUS27, pUS28, pUL33, and pUL78. In contrast to the extensively characterized vGPCRs pUS28 and pUL33, knowledge concerning pUS27 and pUL78 is limited. Previous studies already demonstrated constitutive internalization of pUS27 and pUL78, as well as an association with the endosomal machinery, however, these results were mainly obtained using transiently transfected cells. To explore the subcellular localization of both receptors during viral infection, we constructed recombinant HCMVs expressing tagged vGPCRs. Colocalization analyses revealed a predominant association of pUS27 or pUL78 with the trans-Golgi network or the endoplasmic reticulum, respectively. Intriguingly, our data emphasize that protein sorting is highly regulated by viral functions as we detected dramatic changes in the colocalization of pUS27 and pUL78 with endosomal markers during progression of HCMV replication. Furthermore, we observed cell type-dependent differences in trafficking of both vGPCRs between fibroblasts and epithelial cells. Most importantly, infection experiments with a recombinant HCMV carrying tagged versions of pUS27 and pUL78 simultaneously, revealed that these two proteins do not colocalize during viral infection. This contrasts to results of transient expression experiments. In conclusion, our results highlight the importance to investigate vGPCR trafficking in a viral context.
EVALuna2:8228

Intrastructural help: harnessing heterologous T helper cells induced by licensed vaccines to improve the quality of HIV-1 Env antibody responses after immunization with Virus-like particles incorporating T helper cell epitopes of the heterologous antigen - Elsayed, H.; Temchura, Vladimir; Nabi, G.; Tenbusch, Matthias; Überla, Klaus (2017)
EVALuna2:33746

Intrastructural Help: Harnessing T Helper Cells Induced by Licensed Vaccines for Improvement of HIV Env Antibody Responses to Virus-Like Particle Vaccines - Elsayed, Hassan; Nabi, Ghulam; Mckinstry, William J.; Khoo, Keith K.; Mak, Johnson; Salazar, Andres M.; Tenbusch, Matthias; Temchura, Vladimir; Überla, Klaus (Journal of Virology, 2018)
Induction of persistent antibody responses by vaccination is generally thought to depend on efficient help by T follicular helper cells. Since the T helper cell response to HIV Env may not be optimal, we explored the possibility of improving the HIV Env antibody response to virus-like particle (VLP) vaccines by recruiting T helper cells induced by commonly used licensed vaccines to provide help for Env-specific B cells. B cells specific for the surface protein of a VLP can internalize the entire VLP and thus present peptides derived from the surface and core proteins on their major histocompatibility complex class II (MHC-II) molecules. This allows T helper cells specific for the core protein to provide intrastructural help for B cells recognizing the surface protein. Consistently, priming mice with an adjuvanted Gag protein vaccine enhanced the HIV Env antibody response to subsequent booster immunizations with HIV VLPs. To harness T helper cells induced by the licensed Tetanolpur vaccines, HIV VLPs that contained T helper cell epitopes of tetanus toxoid were generated. Tetanol-immunized mice raised stronger antibody responses to immunizations with VLPs containing tetanus toxoid T helper cell epitopes but not to VLPs lacking these epitopes. Depending on the priming immunization, the IgG subtype response to HIV Env after the VLP immunization could also be modified. Thus, harnessing T helper cells induced by other vaccines appears to be a promising approach to improve the HIV Env antibody response to VLP vaccines. IMPORTANCE Induction of HIV Env antibodies at sufficient levels with optimal Fc effector functions for durable protection remains a challenge. Efficient T cell help may be essential to induce such a desirable antibody response. Here, we provide proof of concept that T helper cells induced by a licensed vaccine can be harnessed to provide help for HIV Env-specific B cells and to modulate the Env-specific IgG subtype response.
EVALuna2:35272

Intrastructural help: improving the HIV-1 envelope antibody response induced by virus-like particle vaccines - Temchura, Vladimir; Überla, Klaus (Current Opinion in HIV and AIDS, 2017)
PURPOSE OF REVIEW: The importance of IgG Fc-effector functions for the efficacy of HIV vaccines is increasingly recognized. Although different types of vaccines were shown to induce antibodies with different Fc-activities, there is no clear strategy how to raise antibody responses with a desired pattern of Fc-effector functions. Given the central role of T-helper cells in regulating the germinal center reaction and the differentiation of B cells in an antigen-specific manner, the review will discuss whether T-helper cells directed against non-HIV envelope (Env) antigens could be harnessed to improve the HIV-Env antibody response. RECENT FINDINGS: Comparing CD4 T-cell responses in HIV-infected individuals with and without neutralizing antibody breadth suggests that robust Gag-specific CD4 T cells may provide important T-cell help to Env-specific B cells. In a murine model, GagPol-specific T-helper cells were shown to provide intrastructural help for HIV-Env-specific antibody responses after immunization with a virus-like particle vaccine. GagPol-specific T-helper cells imprinted the IgG subtype ratio observed for Gag onto the HIV-Env antibody response and modulated the glycosylation pattern of the HIV Env-specific antibodies. SUMMARY: Intrastructural help is a promising strategy to improve overall levels and Fc-effector functions of the HIV-Env antibody response.
EVALuna2:33765

Introduction of Inhaled Nitrous Oxide and Oxygen for Pain Management during Labour - Evaluation of Patients' and Midwives' Satisfaction - Dammer, U.; Weiss, C.; Raabe, E.; Heimrich, J.; Koch, Matthias; Winkler, Michael; Faschingbauer, F.; Beckmann, Matthias; Kehl, Sven (Geburtshilfe und Frauenheilkunde, 2014)
Aim: Effective pain management during labour is important because pain affects the birth experience. Epidural analgesia is effective but often it may not be possible; however, inhaled analgesia offers another option. Use of inhaled nitrous oxide and oxygen for pain management in labour is well established in obstetrics but is still not used much in Germany. This study aimed to investigate the acceptance of the inhaled analgesia of inhaled nitrous oxide and oxygen by midwives and pregnant women during labour. Material and Methods: In this observational study carried out between April and September 2013, a total of 66 pregnant women received inhaled nitrous oxide and oxygen during labour on request and after prior assessment of suitability. After the birth, all of the women and the responsible midwives were interviewed about their experience and satisfaction with the inhaled analgesia. Results: A statistically significant reduction of pain was achieved with nitrous oxide and oxygen. The inhaled analgesia was mostly used by women who refused epidural analgesia. The likelihood of using inhaled nitrous oxide and oxygen again was reported as higher for patients who tolerated it well (p = 0.0129) and used it in the second stage of labour (p = 0.0003) and when bearing down (p = 0.0008). Conclusion: Inhaled nitrous oxide and oxygen is an effective method for pain management during labour and is accepted well by women in labour and by midwives.
EVALuna2:17457

In Utero Administration of Drugs Targeting Microglia Improves the Neurodevelopmental Outcome Following Cytomegalovirus Infection of the Rat Fetal Brain - Cloarec, Robin; Bauer, Sylvian; Teissier, Natacha; Schaller, Fabienne; Luche, Herve; Courtens, Sandra; Salmi, Manal; Pauly, Vanessa; Bois, Emilie; Pallesi-Pocachard, Emilie; Buhler, Emmanuelle; Michel, Francois J.; et al. (Frontiers in Cellular Neuroscience, 2018)
Congenital cytomegalovirus (CMV) infections represent one leading cause of neurodevelopmental disorders. Recently, we reported on a rat model of CMV infection of the developing brain in utero, characterized by early and prominent infection and alteration of microglia-the brain-resident mononuclear phagocytes. Besides their canonical function against pathogens, microglia are also pivotal to brain development. Here we show that CMV infection of the rat fetal brain recapitulated key postnatal phenotypes of human congenital CMV including increased mortality, sensorimotor impairment reminiscent of cerebral palsy, hearing defects, and epileptic seizures. The possible influence of early microglia alteration on those phenotypes was then questioned by pharmacological targeting of microglia during pregnancy. One single administration of clodronate liposomes in the embryonic brains at the time of CMV injection to deplete microglia, and maternal feeding with doxycyxline throughout pregnancy to modify microglia in the litters' brains, were both associated with dramatic improvements of survival, body weight gain, sensorimotor development and with decreased risk of epileptic seizures. Improvement of microglia activation status did not persist postnatally after doxycycline discontinuation; also, active brain infection remained unchanged by doxycycline. Altogether our data indicate that early microglia alteration, rather than brain CMV load per se, is instrumental in influencing survival and the neurological outcomes of CMV-infected rats, and suggest that microglia might participate in the neurological outcome of congenital CMV in humans. Furthermore this study represents a first proof-of-principle for the design of microglia-targeted preventive strategies in the context of congenital CMV infection of the brain.
EVALuna2:35285

Investigational Antiviral Therapy Models for the Prevention and Treatment of Congenital Cytomegalovirus Infection during Pregnancy - Hamilton, Stuart T.; Marschall, Manfred; Rawlinson, William D. (Antimicrobial Agents and Chemotherapy, 2021)
Congenital cytomegalovirus (HCMV) infection may cause significant fetal malformation, lifelong disease, and, in severe cases, fetal or neonatal death. Placental infection with HCMV is the major mechanism of mother-to-child transmission (MTCT) and fetal injury. Thus, any pharmaceutical antiviral interference to reduce viral load may reduce placental damage, MTCT, and fetal disease. However, there is currently no licensed HCMV antiviral for use during pregnancy. In this study, aciclovir and the HCMV-specific antivirals letermovir, maribavir, and cidofovir were compared with ganciclovir for antiviral effects in model systems of pregnancy, including first-trimester TEV-1 trophoblast cell cultures and third-trimester ex vivo placental explant histocultures. HCMV-infected trophoblasts at 7 days postinfection (dpi) showed an EC50 of 21 mu M for aciclovir, 0.0007 mu M for letermovir, 0.11 mu M for maribavir, and 0.29 mu M for cidofovir, relative to 0.42 mu M for ganciclovir. Antivirals added at 10 mu M showed no cytotoxic effects and did not affect trophoblast cell proliferation (P > 0.9999). Multiple-round HCMV replication measured at 7 dpi showed letermovir, maribavir, and cidofovir treatment inhibited immediate early, early, and true late viral protein expression as assayed on Western blots. Antiviral treatment of HCMV-infected placental explants showed significant inhibition (P < 0.05) of viral replication with letermovir (83.3%), maribavir (83.6%), cidofovir (89.3%), and ganciclovir (82.4%), but not aciclovir (P > 0.9999). In ex vivo model systems, recently trialed HCMV antivirals letermovir and maribavir were effective at inhibiting HCMV replication. They partly fulfil requirements for use as safe and effective therapeutics during pregnancy to control congenital HCMV. Clinical trials of these newer agents would assist assessment of their utility in pregnancy.
CRIS-Team WoS Importer:2021-01-15

In vivo proof-of-concept for two experimental antiviral drugs, both directed to cellular targets, using a murine cytomegalovirus model - Sonntag, Eric; Hahn, Friedrich; Bertzbach, Luca D.; Seyler, Lisa; Wangen, Christina; Müller, Regina; Tannig, Pierre; Grau, Benedikt; Baumann, Matthias; Zent, Eldar; Zischinsky, Gunther; Eickhoff, Jan; et al. (Antiviral Research, 2019)
Infections with the human cytomegalovirus (HCMV) cause serious medical problems including organ rejection and congenital infection. Treatment of HCMV infections with currently available medication targeting viral enzymes is often accompanied with severe side effects and the occurrence of drug-resistant viruses. This demands novel therapeutical approaches like targeting genetically stable host cell proteins that are crucial for virus replication. Although numerous experimental drugs with promising in vitro efficacy have been identified, the lack of available data in animal models limits their potential for further clinical development. Recently, we described the very strong in vitro antiherpesviral activity of the NF-κB inhibitor TF27 and the CDK7 inhibitor LDC4297 at low nanomolar concentrations. In the present study, we present first data for the in vivo efficacy of both experimental drugs using an established cytomegalovirus animal model (murine CMV replication in immunodefective Rag −/− mice). The main findings of this study are (i) a strong inhibitory potency against beta- and gamma-herpesviruses of both compounds in vitro, (ii) even more important, a pronounced anticytomegaloviral activity also exerted in vivo, that resulted from (iii) a restriction of viral replication to the site of infection, thus preventing organ dissemination, (iv) in the absence of major compound-associated adverse events. Thus, we provide evidence for a strong antiviral potency in vivo and proof-of-concept for both drugs, which may encourage their further drug development, possibly including pharmacologically optimized derivatives, for a potential use in future antiherpesviral treatment.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Antiviral drug development; Antiviral experimental drugs; Artemisinin and pyrazolotriazine compounds; Herpesviral in vitro/vivo models; Human and murine cytomegaloviruses; Proof-of-concept

Ion Channel Activity of Vpu Proteins Is Conserved throughout Evolution of HIV-1 and SIV - Greiner, Timo; Bolduan, Sebastian; Hertel, Brigitte; Gro, Christine; Hamacher, Kay; Schubert, Ulrich; Moroni, Anna; Thiel, Gerhard (Viruses, 2016)
The human immunodeficiency virus type 1 (HIV-1) protein Vpu is encoded exclusively by HIV-1 and related simian immunodeficiency viruses (SIVs). The transmembrane domain of the protein has dual functions: it counteracts the human restriction factor tetherin and forms a cation channel. Since these two functions are causally unrelated it remains unclear whether the channel activity has any relevance for viral release and replication. Here we examine structure and function correlates of different Vpu homologs from HIV-1 and SIV to understand if ion channel activity is an evolutionary conserved property of Vpu proteins. An electrophysiological testing of Vpus from different HIV-1 groups (N and P) and SIVs from chimpanzees (SIVcpz), and greater spot-nosed monkeys (SIVgsn) showed that they all generate channel activity in HEK293T cells. This implies a robust and evolutionary conserved channel activity and suggests that cation conductance may also have a conserved functional significance.
EVALuna2:32858

Iota-carrageenan inhibits replication of sars-cov-2 and the respective variants of concern alpha, beta, gamma and delta - Fröba, Maria; Große, Maximilian; Setz, Christian; Rauch, Pia; Auth, Janina; Spanaus, Lucas; Münch, Jan; Ruetalo, Natalia; Schindler, Michael; Morokutti-Kurz, Martina; Graf, Philipp; Prieschl-Grassauer, Eva; et al. (International Journal of Molecular Sciences, 2021)
The COVID-19 pandemic continues to spread around the world and remains a major public health threat. Vaccine inefficiency, vaccination breakthroughs and lack of supply, especially in developing countries, as well as the fact that a non-negligible part of the population either refuse vaccination or cannot be vaccinated due to age, pre-existing illness or non-response to existing vaccines intensify this issue. This might also contribute to the emergence of new variants, being more efficiently transmitted, more virulent and more capable of escaping naturally acquired and vaccine-induced immunity. Hence, the need of effective and viable prevention options to reduce viral transmission is of outmost importance. In this study, we investigated the antiviral effect of iota-, lambda-and kappa-carrageenan, sulfated polysaccharides extracted from red seaweed, on SARS-CoV-2 Wuhan type and the spreading variants of concern (VOCs) Alpha, Beta, Gamma and Delta. Carrageenans as part of broadly used nasal and mouth sprays as well as lozenges have the potential of first line defense to inhibit the infection and transmission of SARS-CoV-2. Here, we demonstrate by using a SARS-CoV-2 spike pseudotyped lentivirus particles (SSPL) system and patient-isolated SARS-CoV-2 VOCs to infect transgenic A549ACE2/TMPRSS2 and Calu-3 human lung cells that all three carrageenan types exert antiviral activity. Iota-carrageenan exhibits antiviral activity with comparable IC50 values against the SARS-CoV-2 Wuhan type and the VOCs. Altogether, these results indicate that iota-carrageenan might be effective for prophylaxis and treatment of SARS-CoV-2 infections independent of the present and potentially future variants.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Carrageenan types; Coronavirus; COVID-19; Iota-carrageenan; Kappa-carrageenan; Lambda-carrageenan; Pseudotyping; SARS-CoV-2; Sulfated polymer; Variants of concern; Virus variants

Iota-carrageenan neutralizes SARS-CoV-2 and inhibits viral replication in vitro - Morokutti-Kurz, Martina; Fröba, Maria; Graf, Philipp; Große, Maximilian; Grassauer, Andreas; Auth, Jürgen; Schubert, Ulrich; Prieschl-Grassauer, Eva (PLoS ONE, 2021)
In the absence of a vaccine and other effective prophylactic or therapeutic countermeasures the severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) remains a significant public health threat. Attachment and entry of coronaviruses including SARS-CoV-2 is mainly mediated by the spike glycoprotein. Here, we show that iota-carrageenan can inhibit the cell entry of the SARS-CoV-2 spike pseudotyped lentivirus in a dose dependent manner. SARS-CoV-2 spike pseudotyped lentivirus particles were efficiently neutralized with an IC50 value of 2.6 μg/ml iota-carrageenan. Experiments with patient isolated wild type SARS-CoV-2 virus showed an inhibition of replication in a similar range. In vitro data on iota-carrageenan against various Rhino- and endemic Coronaviruses showed similar IC50 values and translated readily into clinical effectiveness when a nasal spray containing iota-carrageenan demonstrated a reduction of severity and duration of symptoms of common cold caused by various respiratory viruses. Accordingly, our in vitro data on SARS-CoV-2 spike pseudotyped lentivirus and replication competent SARS-CoV-2 suggest that administration of iota-carrageenan may be an effective and safe prophylaxis or treatment for SARS-CoV-2 infections.
CRIS-Team Scopus Importer:2021-03-05

IsoQC (QPCTL) knock-out mice suggest differential substrate conversion by glutaminyl cyclase isoenzymes - Becker, Andreas; Eichentopf, Rico; Sedlmeier, Reinhard; Waniek, Alexander; Cynis, Holger; Koch, Birgit; Stephan, Anett; Baeuscher, Christoph; Kohlmann, Stephanie; Hoffmann, Torsten; Kehlen, Astrid; Berg, Sabine; et al. (Biological Chemistry, 2016)
Secretory peptides and proteins are frequently modified by pyroglutamic acid (pE, pGlu) at their N-terminus. This modification is catalyzed by the glutaminyl cyclases QC and isoQC. Here, we decipher the roles of the isoenzymes by characterization of IsoQC-/- mice. These mice show a significant reduction of glutaminyl cyclase activity in brain and peripheral tissue, suggesting ubiquitous expression of the isoQC enzyme. An assay of substrate conversion in vivo reveals impaired generation of the pGlu-modified C-C chemokine ligand 2 (CCL2, MCP-1) in isoQC-/- mice. The pGlu-formation was also impaired in primary neurons, which express significant levels of QC. Interestingly, however, the formation of the neuropeptide hormone thyrotropin-releasing hormone (TRH), assessed by immunohistochemistry and hormonal analysis of hypothalamic-pituitary-thyroid axis, was not affected in isoQC-/-, which contrasts to QC-/-. Thus, the results reveal differential functions of isoQC and QC in the formation of the pGlu-peptides CCL2 and TRH. Substrates requiring extensive prohormone processing in secretory granules, such as TRH, are primarily converted by QC. In contrast, protein substrates such as CCL2 appear to be primarily converted by isoQC. The results provide a new example, how subtle differences in subcellular localization of enzymes and substrate precursor maturation might influence pGlu-product formation.
EVALuna2:24978

(Iso)Quinoline–Artemisinin Hybrids Prepared through Click Chemistry: Highly Potent Agents against Viruses - Capci Karagöz, Aysun; Lorion, Mélanie M.; Mai, Christina; Hahn, Friedrich; Hodek, Jan; Wangen, Christina; Weber, Jan; Marschall, Manfred; Ackermann, Lutz; Tsogoeva, Svetlana (Chemistry - A European Journal, 2020)
Viral infections cause life-threatening diseases in millions of people worldwide every year and there is an urgent need for new, effective antiviral drugs. Hybridization of two chemically diverse compounds into a new bioactive effector product is a successful concept to improve the properties of a hybrid drug relative to the parent compounds. In this study, (iso)quinoline–artemisinin hybrids, obtained through copper-catalyzed azide–alkyne cycloaddition or metal-free click reactions (in organic solvents or in the presence of water), were analyzed in vitro, for the first time, for their inhibitory activity against human cytomegalovirus (HCMV), relative to their parent compounds and the reference drug ganciclovir. EC50 (HCMV) values were obtained in a range 0.22–1.20 μm, which indicated highly potent antiviral properties in the absence of cytotoxic effects on normal cells (CC50>100 μm). The most active hybrid, 1 (EC50=0.22 μm), is 25 times more potent than its parent compound artesunic acid (EC50=5.41 μm) and 12 times more efficient than the standard drug ganciclovir (EC50=2.6 μm). Interestingly, hybrid 1 also shows inhibitory activity against hepatitis B virus in vitro (EC50 (HBeAg)=2.57 μm).
CRIS-Team Scopus Importer:2020-08-28
Keywords: antiviral agents; artemisinins; click chemistry; cycloaddition; quinolines

Is the BNT162b2 COVID-19 vaccine effective in elderly populations? Results from population data from Bavaria, Germany - Gomes, Delphina; Beyerlein, Andreas; Katz, Katharina; Hoelscher, Gabriele; Nennstiel, Uta; Liebl, Bernhard; Überla, Klaus; Von Kries, Ruediger (PLoS ONE, 2021)
Background
CRIS-Team WoS Importer:2022-02-25

Just One Position-Independent Lysine Residue Can Direct MelanA into Proteasomal Degradation following N-Terminal Fusion of Ubiquitin - Setz, Christian; Friedrich, Melanie; Hahn, Sabine; Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Schubert, Ulrich (PLoS ONE, 2013)
N-terminal stable in frame fusion of ubiquitin (Ub) has been shown to target the fusion protein for proteasomal degradation. This pathway, called the Ub fusion degradation (UFD), might also elevate MHC class I (MHC-I) antigen presentation of specific antigens. The UFD, mainly studied on cytosolic proteins, has been described to be mediated by polyubiquitination of specific lysine residues within the fused Ub moiety. Using the well characterized melanoma-specific antigen MelanA as a model protein, we analyzed the requirements of the UFD for ubiquitination and proteasomal degradation of a transmembrane protein. Here we show that fusion of the non-cleavable UbG76V variant to the N-terminus of MelanA results in rapid proteasomal degradation via the endoplasmic reticulum-associated degradation (ERAD) pathway and, consequently, leads to an increased MHC-I antigen presentation. While lysine residues within Ub are dispensable for these effects, the presence of one single lysine residue, irrespectively of its location along the fusion protein, is sufficient to induce degradation of MelanA. These results show that the ubiquitination, ER to cytosol relocation and proteasomal degradation of a transmembrane protein can be increased by N-terminal fusion of Ub at the presence of at least one, position independent lysine residue. These findings are in contrast to the conventional wisdom concerning the UFD and indicate a new concept to target a protein into the ubiquitin-proteasome system (UPS) and thus for enhanced MHC-I antigen presentation, and might open up new possibilities in the development of tumor vaccines. © 2013 Setz et al.
CRIS-Team Scopus Importer:2021-10-01

Kaposi's sarcoma-associated herpesvirus gH/gL: glycoprotein export and interaction with cellular receptors. - Hahn, Alexander; Birkmann, Alexander; Wies, Effi; Dorer, Dominik; Mahr, Kerstin; Stürzl, Michael; Titgemeyer, Fritz; Neipel, Frank (Journal of Virology, 2009)
The attachment, entry, and fusion of Kaposi's sarcoma-associated herpesvirus (KSHV) with target cells are mediated by complex machinery containing, among others, viral glycoprotein H (gH) and its alleged chaperone, gL. We observed that KSHV gH, in contrast to its homologues in several other herpesviruses, is transported to the cytoplasm membrane independently from gL, but not vice versa. Mutational analysis revealed that the N terminus of gH is sufficient for gL interaction. However, the entire extracellular part of gH is required for efficient gL secretion. The soluble ectodomain of gH was sufficient to interact with the surfaces of potential target cells in a heparin-dependent manner, and binding was further enhanced by coexpression of gL. Surface plasmon resonance revealed a remarkably high affinity of gH for glycosaminoglycans. Heparan sulfate (HS) proteoglycans of the syndecan family act as cellular receptors for the gH/gL complex. They promoted KSHV infection, and expression of gH/gL on target cells inhibited subsequent KSHV infection. Whereas gH alone was able to bind to HS, we observed that only the gH/gL complex adhered to heparan sulfate-negative cells at lamellipodium-like structures.

Kaposi’s sarcoma-associated herpesvirus glycoprotein K8.1 is critical for infection in a cell-specific manner and functions at the attachment step on keratinocytes - Liu, Shanchuan; Großkopf, Anna K.; Yang, Xiaoliang; Mannheim, Maximilian E.; Backovic, Marija; Scribano, Stefano; Schlagowski, Sarah; Enßer, Armin; Hahn, Alexander S. (Journal of Virology, 2023)
Kaposi’s sarcoma-associated herpesvirus (KSHV) is associated with Kaposi’s sarcoma and B cell malignancies. K8.1, the major antigenic component of the KSHV virion, has been reported to play a critical role in the infection of B cells, but otherwise its function remains enigmatic. We created a K8.1 knockout virus (KSHVΔK8.1) in the BAC16 genetic background and analyzed its infectivity on a range of adherent cells. We observed a strong defect on several epithelial cells, such as the HaCaT keratinocyte cell line, human embryonic kidney (HEK) 293T, and A549 lung epithelial cells. However, we did not observe such a defect in other cells, including lymphatic and blood endothelial cells. Mechanistically, we found that reduced infectivity of the K8.1 knockout virus correlated with reduced attachment to HaCaT cells. The defect in infectivity of KSHVΔK8.1 could be rescued by complementation through expression of K8.1 in KSHVΔK8.1 producing cells by means of a lentiviral vector. In a coculture infection model with iSLK producer cells, KSHVΔK8.1 was highly efficient at infecting the BJAB B cell line but was significantly impaired at infecting the MC116 B cell line, in line with a previous report. In fusion assays together with the gH/gL glycoprotein complex and gB, the components of the conserved herpesviral core fusion machinery, we did not observe activation of membrane fusion by K8.1 or its R8.1 homolog of the rhesus monkey rhadinovirus. In summary, we found K8.1 to function in a highly cell-specific manner during KSHV entry at the attachment step, playing an important role in the infection of epithelial cells. IMPORTANCE Kaposi’s sarcoma-associated herpesvirus (KSHV) is the causative agent of several B cell malignancies and Kaposi’s sarcoma. We analyzed the function of K8.1, the major antigenic component of the KSHV virion in the infection of different cells. To do this, we deleted K8.1 from the viral genome. It was found that K8.1 is critical for the infection of certain epithelial cells, e.g., a skin model cell line but not for infection of many other cells. K8.1 was found to mediate attachment of the virus to cells where it plays a role in infection. In contrast, we did not find K8.1 or a related protein from a closely related monkey virus to activate fusion of the viral and cellular membranes, at least not under the conditions tested. These findings suggest that K8.1 functions in a highly cell-specific manner during KSHV entry, playing a crucial role in the attachment of KSHV to, e.g., skin epithelial cells.
CRIS-Team Scopus Importer:2023-11-17
Keywords: attachment; entry; glycoproteins; Kaposi's sarcoma; Kaposi's sarcoma-associated herpesvirus; KSHV; virus

Kaposi's sarcoma-associated herpesvirus serology in Europe and Uganda: multicentre study with multiple and novel assays. - Schatz, Octavian; Monini, Paolo; Bugarini, Roberto; Neipel, Frank; Schulz, Thomas F.; Andreoni, Massimo; Erb, Peter; Eggers, Maren; Haas, Jürgen; Buttò, Stefano; Lukwiya, Matthew; Bogner, Johannes R.; et al. (Journal of Medical Virology, 2001)
A multicentre study was undertaken to define novel assays with increased inter-assay concordance, sensitivity, specificity and predictive value for serological diagnosis of human herpesvirus type 8 (HHV-8) infection. A total of 562 sera from European and Ugandan human immunodeficiency virus (HIV)-infected or uninfected individuals with or without Kaposi's sarcoma (KS) and blood donors were examined under code by 18 different assays in seven European laboratories. Sera from KS patients and all non-KS sera found positive by at least 70%, 80%, or 90% of the assays were considered "true positive." The validity of the assays was then evaluated by univariate logistic regression analysis. Two immunofluorescence assays (IFA) for detection of antibodies against HHV-8 lytic (Rlyt) or latent (LLANA) antigens and two enzyme-linked-immunosorbent assays (ELISA) (M2, EK8.1) for detection of antibodies against HHV-8 structural proteins were found to be highly concordant, specific, and sensitive, with odds ratios that indicated a high predictive value. When used together, the two IFA (Rlyt-LLANA) showed the best combination of sensitivity (89.1%) and specificity (94.9%). The performance of these assays indicate that they may be used for the clinical management of individuals at risk of developing HHV-8 associated tumours such as allograft recipients.

Kaposi's sarcoma associated herpesvirus tegument protein ORF75 is essential for viral lytic replication and plays a critical role in the antagonization of ND10-instituted intrinsic immunity - Full, Florian; Jungnickl, Doris; Reuter, Nina; Bogner, Elke; Brulois, Kevin; Scholz, Brigitte; Stürzl, Michael; Myoung, Jinjong; Jung, Jae U.; Stamminger, Thomas; Enßer, Armin (PLoS Pathogens, 2014)
Nuclear domain 10 (ND10) components are restriction factors that inhibit herpesviral replication. Effector proteins of different herpesviruses can antagonize this restriction by a variety of strategies, including degradation or relocalization of ND10 proteins. We investigated the interplay of Kaposi's Sarcoma-Associated Herpesvirus (KSHV) infection and cellular defense by nuclear domain 10 (ND10) components. Knock-down experiments in primary human cells show that KSHV-infection is restricted by the ND10 components PML and Sp100, but not by ATRX. After KSHV infection, ATRX is efficiently depleted and Daxx is dispersed from ND10, indicating that these two ND10 components can be antagonized by KSHV. We then identified the ORF75 tegument protein of KSHV as the viral factor that induces the disappearance of ATRX and relocalization of Daxx. ORF75 belongs to a viral protein family (viral FGARATs) that has homologous proteins in all gamma-herpesviruses. Isolated expression of ORF75 in primary cells induces a relocalization of PML and dispersal of Sp100, indicating that this viral effector protein is able to influence multiple ND10 components. Moreover, by constructing a KSHV mutant harboring a stop codon at the beginning of ORF75, we could demonstrate that ORF75 is absolutely essential for viral replication and the initiation of viral immediate-early gene expression. Using recombinant viruses either carrying Flag- or YFP-tagged variants of ORF75, we could further corroborate the role of ORF75 in the antagonization of ND10-mediated intrinsic immunity, and show that it is independent of the PML antagonist vIRF3. Members of the viral FGARAT family target different ND10 components, suggesting that the ND10 targets of viral FGARAT proteins have diversified during evolution. We assume that overcoming ND10 intrinsic defense constitutes a critical event in the replication of all herpesviruses; on the other hand, restriction of herpesviral replication by ND10 components may also promote latency as the default outcome of infection.
EVALuna2:8222

Killer cell proteases can target viral immediate-early proteins to control human cytomegalovirus infection in a noncytotoxic manner - Shan, Liling; Li, Shuang; Meeldijk, Jan; Blijenberg, Bernadet; Hendriks, Astrid; van Boxtel, Karlijn J.W.M.; van den Berg, Sara P.H.; Groves, Ian J.; Potts, Martin; Svrlanska, Adriana; Stamminger, Thomas; Wills, Mark R.; et al. (PLoS Pathogens, 2020)
Human cytomegalovirus (HCMV) is the most frequent viral cause of congenital defects and can trigger devastating disease in immune-suppressed patients. Cytotoxic lymphocytes (CD8+ T cells and NK cells) control HCMV infection by releasing interferon-γ and five granzymes (GrA, GrB, GrH, GrK, GrM), which are believed to kill infected host cells through cleavage of intracellular death substrates. However, it has recently been demonstrated that the in vivo killing capacity of cytotoxic T cells is limited and multiple T cell hits are required to kill a single virus-infected cell. This raises the question whether cytotoxic lymphocytes can use granzymes to control HCMV infection in a noncytotoxic manner. Here, we demonstrate that (primary) cytotoxic lymphocytes can block HCMV dissemination independent of host cell death, and interferon-α/β/γ. Prior to killing, cytotoxic lymphocytes induce the degradation of viral immediate-early (IE) proteins IE1 and IE2 in HCMV-infected cells. Intriguingly, both IE1 and/or IE2 are directly proteolyzed by all human granzymes, with GrB and GrM being most efficient. GrB and GrM cleave IE1 after Asp398 and Leu414, respectively, likely resulting in IE1 aberrant cellular localization, IE1 instability, and functional impairment of IE1 to interfere with the JAK-STAT signaling pathway. Furthermore, GrB and GrM cleave IE2 after Asp184 and Leu173, respectively, resulting in IE2 aberrant cellular localization and functional abolishment of IE2 to transactivate the HCMV UL112 early promoter. Taken together, our data indicate that cytotoxic lymphocytes can also employ noncytotoxic ways to control HCMV infection, which may be explained by granzyme-mediated targeting of indispensable viral proteins during lytic infection.
CRIS-Team Scopus Importer:2020-05-12

Laboratory diagnosis of congenital CMV infection in newborns: Impact of pre-analytic factors - Kohmer, N.; Nagel, Armin Michael; Berger, A.; Enders, M.; Hamprecht, K.; Korn, Klaus; Kortenbusch, M.; Überla, Klaus; Rabenau, H. F. (Journal of Clinical Virology, 2019)
Background: To identify infants with congenital cytomegalovirus (cCMV) saliva polymerase chain reaction (PCR) is an ideal screening method. However, there are only few data on the influence of pre-analytic factors on the analytical sensitivity of the CMV PCR. Objectives: This study aimed to evaluate the performance of different swabbing materials, transport time and initial virus concentration regarding to the efficacy of recovery of CMV-DNA. Study design: Two CMV suspensions containing a high or low concentration of the laboratory strain AD 169 were prepared as test samples. Sampling was simulated by immersion of different swabs in these CMV suspensions and storing the swabs dry or in specified transport media. Transport conditions were modeled by storing the samples for defined time periods prior to DNA extraction and quantitative PCR analyses. Parallel analyses in two different laboratories allowed determination of lab to lab consistency. Results: The duration of storage under the conditions analysed did not have a major effect on the recovery efficiency for the swabbing materials tested. With exception of flocked dry swabs, all tested swabbing materials demonstrated good recovery of CMV DNA. The flocked swab/eNAT system showed the best overall performance. Conclusions: All tested swabbing materials (with exception of the flocked dry swabs) seem to be well suited for recovery of CMV DNA and appropriate for use for the diagnosis of cCMV infection in symptomatic cases and in general cCMV screening programs of newborns.
CRIS-Team Scopus Importer:2019-05-02
Keywords: CMV; Congenital; Cytomegalovirus; PCR; Screening; Swabs

Latency reversing agents: Kick and kill of htlv-1? - Schnell, Annika; Kohrt, Stephan; Thoma-Kreß, Andrea (International Journal of Molecular Sciences, 2021)
Human T-cell leukemia virus type 1 (HTLV-1), the cause of adult T-cell leukemia/lym-phoma (ATLL), is a retrovirus, which integrates into the host genome and persistently infects CD4+ T-cells. Virus propagation is stimulated by (1) clonal expansion of infected cells and (2) de novo infection. Viral gene expression is induced by the transactivator protein Tax, which recruits host factors like positive transcription elongation factor b (P-TEFb) to the viral promoter. Since HTLV-1 gene expression is repressed in vivo by viral, cellular, and epigenetic mechanisms in late phases of infection, HTLV-1 avoids an efficient CD8+ cytotoxic T-cell (CTL) response directed against the im-munodominant viral Tax antigen. Hence, therapeutic strategies using latency reversing agents (LRAs) sought to transiently activate viral gene expression and antigen presentation of Tax to enhance CTL responses towards HTLV-1, and thus, to expose the latent HTLV-1 reservoir to immune destruction. Here, we review strategies that aimed at enhancing Tax expression and Tax-specific CTL responses to interfere with HTLV-1 latency. Further, we provide an overview of LRAs including (1) histone deacetylase inhibitors (HDACi) and (2) activators of P-TEFb, that have mainly been studied in context of human immunodeficiency virus (HIV), but which may also be powerful in the context of HTLV-1.
CRIS-Team Scopus Importer:2021-06-04
Keywords: ATLL; HDAC-inhibitor (HDACi); HIV; HTLV-1; Kick and kill; Latency; Latency reversing agents (LRA); P-TEFb; Shock and kill; Tax

Lectin from triticum vulgaris (WGA) inhibits infection with SARS-CoV-2 and its variants of concern alpha and beta - Auth, Janina; Fröba, Maria; Große, Maximilian; Rauch, Pia; Ruetalo, Natalia; Schindler, Michael; Morokutti-kurz, Martina; Graf, Philipp; Dolischka, Andrea; Prieschl-grassauer, Eva; Setz, Christian; Schubert, Ulrich (International Journal of Molecular Sciences, 2021)
Even in the face of global vaccination campaigns, there is still an urgent need for effective antivirals against SARS-CoV-2 and its rapidly spreading variants. Several natural compounds show potential as antiviral substances and have the advantages of broad availabilities and large therapeutic windows. Here, we report that lectin from Triticum vulgaris (Wheat Germ Agglutinin) displays antiviral activity against SARS-CoV-2 and its major Variants of Concern (VoC), Alpha and Beta. In Vero B4 cells, WGA potently inhibits SARS-CoV-2 infection with an IC50 of <10 ng/mL. WGA is effective upon preincubation with the virus or when added during infection. Pull-down assays demonstrate direct binding of WGA to SARS-CoV-2, further strengthening the hypothesis that inhibition of viral entry by neutralizing free virions might be the mode of action behind its antiviral effect. Furthermore, WGA exhibits antiviral activity against human coronavirus OC43, but not against other non-coronaviruses causing respiratory tract infections. Finally, WGA inhibits infection of the lung cell line Calu-3 with wild type and VoC viruses with comparable IC50 values. Altogether, our data indicate that topical administration of WGA might be effective for prophylaxis or treatment of SARS-CoV-2 infections.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Alpha; Antiviral; Beta; COVID-19; Lectin from Triticum vulgaris; Natural com-pounds; SARS-CoV-2; Variants of concern; WGA

Light-Driven Catalyst-Free Access to Phthalazines: Entry to Antiviral Model Drugs by Merging Domino Reactions - Guryev, Anton; Schuster, Florian; Herrmann, Lars; Hahn, Friedrich; Wangen, Christina; Hodek, Jan; Weber, Jan; Marschall, Manfred; Tsogoeva, Svetlana (European Journal of Organic Chemistry, 2022)
We report the development of a metal-free four-step one-pot synthetic strategy to access high-value functionalized phthalazines using o-methyl benzophenones as starting compounds. Combining a light-mediated enolization of o-methyl benzophenones/Diels-Alder reaction domino process with a subsequent deprotection/aromatization domino reaction in one-pot leads to sustainable and efficient organic synthesis. The tangible advantages, i. e., absence of catalysts or additives, utilization of commercially available and/or easily accessible substrates, mild reaction conditions, simplicity, and single work-up procedure, make this combined process highly appealing for the direct construction of various 1-aryl-phthalazines. Importantly, in vitro bioactivity evaluation of these newly prepared heterocyclic compounds demonstrated a strong antiviral efficacy against major human pathogens like HCMV and SARS-CoV-2.
CRIS-Team WoS Importer:2022-11-18

Linear epitope mapping of different Api m 10-isoforms with overlapping peptide arrays identifies highly conserved IgE-binding motive in most isoforms - Paulus, K. E.; Roth, M. B.; Lidholm, J.; Schmidt, Barbara; Novak, N.; Randow, S.; Vogel, L.; Holzhauser, T.; Mahler, (ALLERGY, 2019)
CRIS-Team WoS Importer:2019-08-27

Lipid Accumulation in Host Cells Promotes SARS-CoV-2 Replication - Seitz, Tatjana; Setz, Christian; Rauch, Pia; Schubert, Ulrich; Hellerbrand, Claus (Viruses, 2023)
Coronavirus disease-19 (COVID-19) is still affecting the lives of people around the globe and remains a major public health threat. Lipid levels in the host cells have been shown to promote SARS-CoV-2 replication, and since the start of COVID-19 pandemic, several studies have linked obesity and other components of the metabolic syndrome with severity of illness, as well as mortality in patients with COVID-19. The aim of this study was to obtain insights into the pathophysiological mechanisms of these associations. First, we established an in vitro model simulating high fatty acid levels and showed that this situation induced the uptake of fatty acids and triglyceride accumulation in human Calu-3 lung cells. Importantly, we found that lipid accumulation significantly enhanced the replication of SARS-CoV-2 Wuhan type or the variant of concern, Delta, in Calu-3 cells. In summary, these findings indicate that hyperlipidemia as found in patients with obesity promotes viral replication and herewith the disease course of COVID-19.
CRIS-Team WoS Importer:2023-05-26

Low-Dose Irradiation Differentially Impacts Macrophage Phenotype in Dependence of Fibroblast-Like Synoviocytes and Radiation Dose - Fuchs, Jana; Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (Journal of Immunology Research, 2019)
Rheumatoid arthritis (RA) is a multifactorial autoimmune disease whose main hallmark is inflammation and destruction of the joints. Two cell types within the synovium that play an important role in RA are fibroblast-like synoviocytes (FLS) and macrophages. The latter innate immune cells show a high plasticity in their phenotype and are central in inflammatory processes. Low-dose radiotherapy (LD-RT) with particularly a single dose of 0.5 Gy has been demonstrated to have a positive impact on pain, inflammation, and bone in inflamed joints. We now examined for the first time how LD-RT influences FLS and bone marrow-derived macrophages in co-culture systems of an experimental model of RA to reveal further mechanisms of immune modulatory effects of low and intermediate dose of ionizing radiation. For this, the bone marrow of hTNF-alpha tg mice was differentiated either with cytokines to obtain key macrophage phenotypes (M0, M1, and M2) or with supernatants (SN) of untreated or irradiated FLS. Flow cytometry analyses were used to analyse the impact of radiation (0.1, 0.5, 1.0, and 2.0 Gy) on the phenotype of macrophages in the presence or absence of SN of FLS. LD-RT had no impact on cytokine-mediated macrophage polarization in M0, M1, or M2 macrophages. However, SN of irradiated FLS particularly reduced CD206 expression on macrophages. Macrophage phenotype was stable when being in contact with SN of nonirradiated FLS, but significantly increased surface expression of CD206 and slightly decreased CD80 and CD86 expression were observed when macrophage themselves were irradiated with 0.5 Gy under these microenvironmental conditions, again highlighting discontinuous dose dependencies in the low and intermediate dose range. One can conclude that FLS-dependent microenvironmental conditions have a slight influence on the modulation of macrophage phenotype under radiation exposure conditions. Future studies are needed to reveal the impact of radiation exposure on the functions of treated macrophages under such microenvironmental conditions.
CRIS-Team WoS Importer:2019-09-13

Lung development and immune status under chronic LPS exposure in rat pups with and without CD26/DPP4 deficiency - Schmiedl, Andreas; Wagener, Inga; Jungen, Meike; von Hörsten, Stephan; Stephan, Michael (Cell and Tissue Research, 2021)
Dipeptidyl-peptidase IV (CD26), a multifactorial integral type II protein, is expressed in the lungs during development and is involved in inflammation processes. We tested whether daily LPS administration influences the CD26-dependent retardation in morphological lung development and induces alterations in the immune status. Newborn Fischer rats with and without CD26 deficiency were nebulized with 1 µg LPS/2 ml NaCl for 10 min from days postpartum (dpp) 3 to 9. We used stereological methods and fluorescence activated cell sorting (FACS) to determine morphological lung maturation and alterations in the pulmonary leukocyte content on dpp 7, 10, and 14. Daily LPS application did not change the lung volume but resulted in a significant retardation of alveolarization in both substrains proved by significantly lower values of septal surface and volume as well as higher mean free distances in airspaces. Looking at the immune status after LPS exposure compared to controls, a significantly higher percentage of B lymphocytes and decrease of CD4+CD25+ T cells were found in both subtypes, on dpp7 a significantly higher percentage of CD4 T+ cells in CD26+ pups, and a significantly higher percentage of monocytes in CD26− pups. The percentage of T cells was significantly higher in the CD26-deficient group on each dpp. Thus, daily postnatal exposition to low doses of LPS for 1 week resulted in a delay in formation of secondary septa, which remained up to dpp 14 in CD26− pups. The retardation was accompanied by moderate parenchymal inflammation and CD26-dependent changes in the pulmonary immune cell composition.
CRIS-Team Scopus Importer:2021-10-15
Keywords: CD26/DPP4; Immune cells; Lipopolysaccharide (LPS); Lung development; Rat

Macroevolution of gastric Helicobacter species unveils interspecies admixture and time of divergence (vol 12, pg 2518, 2018) - Smet, Annemieke; Yahara, Koji; Rossi, Mirko; Tay, Alfred; Backert, Steffen; Enßer, Armin; Fox, James G.; Flahou, Bram; Ducatelle, Richard; Haesebrouck, Freddy; Corander, Jukka (Isme Journal, 2019)

Macrophage and osteoclast polarization in bisphosphonate associated necrosis and osteoradionecrosis - Wehrhan, Falk; Möbius, Patrick; Amann, Kerstin Ute; Ries, Jutta; Preidl, Raimund; Neukam, Friedrich Wilhelm; Weber, Manuel (Journal of Cranio-Maxillofacial Surgery, 2017)
Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a complication of antiresorptive therapy with nitrogen-containing bisphosphonates (BP). With various suggestions as to pathogenesis, the etiology of BRONJ is not sufficiently understood. Osteoclasts and their precursors, that is, macrophages, are the main target cells of BP. BP can repolarize regeneration- and healing-associated M2 macrophages towards the tissue destructive M1-type. The current study aims to elucidate differences in macrophage and osteoclast polarization in BRONJ, osteoradionecrosis (ORN) and healthy control specimens.A total of 39 jaw bone samples (18 BRONJ, 8 ORN and 13 healthy controls) were processed for immunohistochemistry to detect CD68-, CD11c- and CD163-positive cells. Macrophages and osteoclasts were distinguished on the basis of morphological differences. Samples were digitized, and the macrophage and osteoclast cell counts were quantitatively analyzed.In jaw bone affected by BRONJ, a significantly increased macrophage infiltration and M1 polarization of macrophages can be seen. The density of CD68-expressing osteoclasts is significantly increased in BRONJ specimens compared to ORN and to healthy controls.A bisphosphonate-derived shift of macrophage polarization towards M1-polarized macrophages might impair bone tissue homeostasis and thus contribute to the pathogenesis of BRONJ. The observed increase in osteoclast density might be caused by BP-induced prolonged osteoclast survival.
EVALuna2:24431

Macrophage polarization differs between apical granulomas, radicular cysts, and dentigerous cysts - Weber, Manuel; Schlittenbauer, Tilo; Möbius, Patrick; Büttner-Herold, Maike; Ries, Jutta; Preidl, Raimund; Geppert, Carol-Immanuel; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Clinical Oral Investigations, 2017)
Apical periodontitis can appear clinically as apical granulomas or radicular cysts. There is evidence that immunologic factors are involved in the pathogenesis of both pathologies. In contrast to radicular cysts, the dentigerous cysts have a developmental origin. Macrophage polarization (M1 vs M2) is a main regulator of tissue homeostasis and differentiation. There are no studies comparing macrophage polarization in apical granulomas, radicular cysts, and dentigerous cysts.Forty-one apical granulomas, 23 radicular cysts, and 23 dentigerous cysts were analyzed in this study. A tissue microarray (TMA) of the 87 consecutive specimens was created, and CD68-, CD11c-, CD163-, and MRC1-positive macrophages were detected by immunohistochemical methods. TMAs were digitized, and the expression of macrophage markers was quantitatively assessed.Radicular cysts are characterized by M1 polarization of macrophages while apical granulomas show a significantly higher degree of M2 polarization. Dentigerous cysts have a significantly lower M1 polarization than both analyzed periapical lesions (apical granulomas and radicular cysts) and accordingly, a significantly higher M2 polarization than radicular cysts. Macrophage cell density in dentigerous cysts is significantly lower than in the periapical lesions.The development of apical periodontitis towards apical granulomas or radicular cysts might be directed by macrophage polarization. Radicular cyst formation is associated with an increased M1 polarization of infiltrating macrophages. In contrast to radicular cysts, dentigerous cysts are characterized by a low macrophage infiltration and a high degree of M2 polarization, possibly reflecting their developmental rather than inflammatory origin.As M1 polarization of macrophages is triggered by bacterial antigens, these results underline the need for sufficient bacterial clearance during endodontic treatment to prevent a possible M1 macrophage-derived stimulus for radicular cyst formation.
EVALuna2:6886

Management of Cervical Intraepithelial Neoplasia in Pregnant Women - Stübs, Frederik; Koch, Martin C.; Dietl, Anna; Schulmeyer, Carla; Behrens, Annika; Seibold, Anja; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; et al. (Anticancer Research, 2023)
BACKGROUND/AIM: The aims of the present study were to evaluate the accuracy of colposcopic findings, investigate the way in which untreated cervical intraepithelial neoplasia (CIN) 2/3 develops during pregnancy, and identify factors associated with regression, persistence, or progression rates. PATIENTS AND METHODS: In a tertiary gynecology and obstetrics department, 655 pregnant women were seen for colposcopy. The most common reason for referral was abnormal cytology findings. The follow-up findings were analyzed retrospectively on the basis of colposcopic findings and cytological and histological tests. RESULTS: The rate of accuracy for major colposcopic findings was 89.2%. Among the colposcopic findings considered "suspicious for invasion" were invasive carcinoma in 42.9% and CIN 3 in 57.1%. The persistence of CIN 3 postpartum was 80% and the rate of progression 4.1%. The rate of regression for CIN 3 was 21.9%. For CIN 2, the rate of persistence was 37.5%, with a regression rate of 31.3%. The rate of regression was higher after vaginal delivery in comparison with caesarean section. CONCLUSION: The accuracy rate of colposcopy is comparatively high, at 89.2%. This might be because pregnant women are seen by more experienced examiners in our dysplasia unit. The rate of progression is comparable with that in other studies. Vaginal delivery increases the regression rate. The newborns' birth weight or birth week did not affect the rates of regression or persistence.
CRIS-Team Scopus Importer:2023-07-07
Keywords: cervical dysplasia; High-grade squamous intraepithelial lesion (HSIL); mode of delivery; pregnancy; treatment

Manipulating the Interferon Signaling Pathway: Implications for HIV Infection - Nganou-Makamdop, Krystelle; Douek, Daniel C. (Virologica Sinica, 2019)
During human immunodeficiency virus (HIV) infection, type I interferon (IFN-I) signaling induces an antiviral state that includes the production of restriction factors that inhibit virus replication, thereby limiting the infection. As seen in other viral infections, type I IFN can also increase systemic immune activation which, in HIV disease, is one of the strongest predictors of disease progression to acquired immune deficiency syndrome (AIDS) and non-AIDS morbidity and mortality. Moreover, IFN-I is associated with CD4 T cell depletion and attenuation of antigen-specific T cell responses. Therefore, therapeutic manipulation of IFN-I signaling to improve HIV disease outcome is a source of much interest and debate in the field. Recent studies have highlighted the importance of timing (acute vs. chronic infection) and have suggested that specific targeting of type I IFNs and their subtypes may help harness the beneficial roles of the IFN-I system while avoiding its deleterious activities.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Human immunodeficiency virus (HIV); Inflammation; Simian immunodeficiency virus (SIV); Type I interferon (IFN-I)

Mass spectrometry-based characterization of the virion proteome, phosphoproteome, and associated kinase activity of human cytomegalovirus - Couté, Yohann; Kraut, Alexandra; Zimmermann, Christine; Büscher, Nicole; Hesse, Anne Marie; Bruley, Christophe; De Andrea, Marco; Wangen, Christina; Hahn, Friedrich; Marschall, Manfred; Plachter, Bodo (Microorganisms, 2020)
The assembly of human cytomegalovirus (HCMV) virions is an orchestrated process that requires, as an essential prerequisite, the complex crosstalk between viral structural proteins. Currently, however, the mechanisms governing the successive steps in the constitution of virion protein complexes remain elusive. Protein phosphorylation is a key regulator determining the sequential changes in the conformation, binding, dynamics, and stability of proteins in the course of multiprotein assembly. In this review, we present a comprehensive map of the HCMV virion proteome, including a refined view on the virion phosphoproteome, based on previous publications supplemented by new results. Thus, a novel dataset of viral and cellular proteins contained in HCMV virions is generated, providing a basis for future analyses of individual phosphorylation steps and sites involved in the orchestrated assembly of HCMV virion-specific multiprotein complexes. Finally, we present the current knowledge on the activity of pUL97, the HCMV-encoded and virion-associated kinase, in phosphorylating viral and host proteins.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Human cytomegalovirus; Mass spectrometry-based proteomics; Phosphorylation; Proteins; Virion composition; Virionassociated kinase

Maternal deprivation decelerates postnatal morphological lung development of F344 rats - Hupa, Katharina Luise; Schmiedl, Andreas; Pabst, Reinhard; von Hörsten, Stephan; Stephan, Michael (Anatomical Record-Advances in Integrative Anatomy and Evolutionary Biology, 2014)
Intensive medical care at premature born infants is often associated with separation of neonates from their mothers. Here, early artificial prolonged separation of rat pups from their dams (Maternal Deprivation, MD) was used to study potential impact on morphological lung maturation. Furthermore, we investigated the influence of an endogenous deficiency of the neuropeptide-cleaving dipeptidyl peptidase IV (DPP4), since the effects of MD are known to be partly mediated via neuropeptidergic effects, hypothesizing that MD will lead to a retardation of postnatal lung development, DPP4-dependendly. We used wild type and CD26/DPP4 deficient rats. For MD, the dam was placed each day into a separate cage for 2 h, while the pups remained in the nest on their own. Morphological lung maturation and cell proliferation at the postnatal days 7, 10, 14, and 21 were determined morphometrically. Maternally deprived wild types showed a retarded postnatal lung development compared with untreated controls in both substrains. During alveolarization, an increased thickness of alveolar septa and a decreased surface of septa about 50% were found. At the end of the morphological lung maturation, the surface of the alveolar septa was decreased at about 25% and the septal thickness remained increased about 20%. The proliferation rate was also decreased about 50% on day 14. However, the MD induced effects were less pronounced in DPP4-deficient rats, due to a significant deceleration already induced by DPP4-deficiency. Thus, MD as a model for postnatal stress experience influences remarkably postnatal development of rats, which is significantly modulated by the DPP4-system.
EVALuna2:24969

Medicine at the interface between science and ethics : Leopoldina Symposium, May 30 to June 1, 2007, Weißenburg, Bayern ; with 4 tables - Böhm, Petra; Doerfler, Walter; Ulrich, Hans G. (Wiss. Verl.-Ges., 2010)

Methodological development of a multi-readout assay for the assessment of antiviral drugs against sars-cov-2 - Hahn, Friedrich; Häge, Sigrun; Herrmann, Alexandra; Wangen, Christina; Kicuntod, Jintawee; Jungnickl, Doris; Tillmanns, Julia; Müller, Regina; Fraedrich, Kirsten; Überla, Klaus; Kohlhof, Hella; Enßer, Armin; et al. (Pathogens, 2021)
Currently, human infections with the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) are accelerating the ongoing spread of the pandemic. Several innovative types of vaccines have already been developed, whereas effective options of antiviral treatments still await a scientific implementation. The development of novel anti-SARS-CoV-2 drug candidates demands skillful strategies and analysis systems. Promising results have been achieved with first generation direct-acting antivirals targeting the viral polymerase RdRp or the protease 3CLpro . Such recently approved or investigational drugs like remdesivir and GC376 represent a basis for further development and optimization. Here, we establish a multi-readout assay (MRA) system that enables the antiviral assessment and mechanistic characterization of novel test compounds, drug repurposing and combination treatments. Our SARS-CoV-2-specific MRA combines the quantitative measurement of several parameters of virus infection, such as the intracellular production of proteins and genomes, enzymatic activities and virion release, as well as the use of reporter systems. In this regard, the antiviral efficacy of remdesivir and GC376 has been investigated in human Caco-2 cells. The readouts included the use of spike-and double-strand RNA-specific monoclonal antibodies for in-cell fluorescence imaging, a newly generated recombinant SARS-CoV-2 reporter virus d6YFP, the novel 3CLpro-based FRET CFP::YFP and the previously reported FlipGFP reporter assays, as well as viral genome-specific RT-qPCR. The data produced by our MRA confirm the high antiviral potency of these two drugs in vitro. Combined, this MRA approach may be applied for broader analyses of SARS-CoV-2-specific antivirals, including compound screenings and the characterization of selected drug candidates.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Anti-coronaviral treatment; Antiviral drug assessment; Candidate drugs; COVID-19 pandemic; Cultured human cells; Methodological development; Multi-readout assay (MRA); SARS-CoV-2 infection

Methods to study the nucleocytoplasmic transport of macromolecules with respect to their impact on the regulation of human cytomegalovirus gene expression - Thomas, Marco; Zielke, Barbara; Reuter, Nina; Stamminger, Thomas (Methods in Molecular Biology, 2014)
One defining feature of eukaryotic cells is their compartmentalization into nucleus and cytoplasm which provides sophisticated opportunities for the regulation of gene expression. Accurate subcellular localization is crucial for the effective function of most viral macromolecules, and nuclear translocation is central to the function of herpesviral proteins that are involved in processes such as transcription or DNA replication. Human cytomegalovirus (HCMV) encodes several transactivator proteins which stimulate viral gene expression either on the transcriptional or posttranscriptional level. In this chapter, we focus on nucleocytoplasmic transport mechanisms of either proteins or RNA that are utilized during HCMV infection. We describe commonly used assays to determine the subcellular localization of a protein, its nucleocytoplasmic shuttling activity, its capacity to export unspliced RNA from the nucleus, and its association with RNA in vivo.
EVALuna2:8254

Microcystic adnexal carcinoma (MAC)-like squamous cell carcinoma as a differential diagnosis to Bell´s palsy: review of guidelines for refractory facial nerve palsy - Müller, Sandra; Iro, Heinrich; Lell, M.; Seifert, F.; Bohr, Christopher; Scherl, C.; Agaimy, Abbas; Traxdorf, Maximilian (Journal of Otolaryngology-Head & Neck Surgery, 2017)
Bell´s palsy is the most common cause of facial paralysis worldwide and the most common disorder of the cranial nerves. It is a diagnosis of exclusion, accounting for 60-75% of all acquired peripheral facial nerve palsies. Our case shows the first case of a microcystic adnexal carcinoma-like squamous cell carcinoma as a cause of facial nerve palsy.The patient, a 70-year-old Caucasian male, experienced subsequent functional impairment of the trigeminal and the glossopharyngeal nerve about 1½ years after refractory facial nerve palsy. An extensive clinical work-up and tissue biopsy of the surrounding parotid gland tissue was not able to determine the cause of the paralysis. Primary infiltration of the facial nerve with subsequent spreading to the trigeminal and glossopharyngeal nerve via neuroanastomoses was suspected. After discussing options with the patient, the main stem of the facial nerve was resected to ascertain the diagnosis of MAC-like squamous cell carcinoma, and radiochemotherapy was subsequently started.This case report shows that even rare neoplastic etiologies should be considered as a cause of refractory facial nerve palsy and that it is necessary to perform an extended diagnostic work-up to ascertain the diagnosis. This includes high-resolution MRI imaging and, as perilesional parotid biopsies might be inadequate for rare cases like ours, consideration of a direct nerve biopsy to establish the right diagnosis.
EVALuna2:6836

Milk Transmission of HTLV-1 and the Need for Innovative Prevention Strategies - Millen, Sebastian; Thoma-Kreß, Andrea (Frontiers in Medicine, 2022)
Breastfeeding is recommended by the World Health Organization for at least 6 months up to 2 years of age, and breast milk protects against several diseases and infections. Intriguingly, few viruses are transmitted via breastfeeding including Human T-cell leukemia virus Type 1 (HTLV-1). HTLV-1 is a highly oncogenic yet neglected retrovirus, which primarily infects CD4+ T-cells in vivo and causes incurable diseases like HTLV-1-associated inflammatory conditions or Adult T-cell leukemia/lymphoma (ATLL) after lifelong viral persistence. Worldwide, at least 5–10 million people are HTLV-1-infected and most of them are unaware of their infection posing the risk of silent transmissions. HTLV-1 is transmitted via cell-containing body fluids such as blood products, semen, and breast milk, which constitutes the major route of mother-to-child transmission (MTCT). Risk of transmission increases with the duration of breastfeeding, however, abstinence from breastfeeding as it is recommended in some endemic countries is not an option in resource-limited settings or underrepresented areas and populations. Despite significant progress in understanding details of HTLV-1 cell-to-cell transmission, it is still not fully understood, which cells in which organs get infected via the oral route, how these cells get infected, how breast milk affects this route of infection and how to inhibit oral transmission despite breastfeeding, which is an urgent need especially in underrepresented areas of the world. Here, we review these questions and provide an outlook how future research could help to uncover prevention strategies that might ultimately allow infants to benefit from breastfeeding while reducing the risk of HTLV-1 transmission.
CRIS-Team Scopus Importer:2022-04-15
Keywords: breast milk; breastfeeding; HTLV-1; oral route; small intestine; tonsils; virus transmission

Milk Transmission of Mammalian Retroviruses - Kemeter, Laura; Birzer, Alexandra; Heym, Stefanie; Thoma-Kreß, Andrea (Microorganisms, 2023)
The transmission of viruses from one host to another typically occurs through horizontal or vertical pathways. The horizontal pathways include transmission amongst individuals, usually through bodily fluids or excretions, while vertical transmission transpires from mother to their offspring, either during pregnancy, childbirth, or breastfeeding. While there are more than 200 human pathogenic viruses to date, only a small number of them are known to be transmitted via breast milk, including cytomegalovirus (CMV), human immunodeficiency virus type 1 (HIV-1), and human T cell lymphotropic virus type 1 (HTLV-1), the latter two belonging to the family Retroviridae. Breast milk transmission is a common characteristic among mammalian retroviruses, but there is a lack of reports summarizing our knowledge regarding this route of transmission of mammalian retroviruses. Here, we provide an overview of the transmission of mammalian exogenous retroviruses with a focus on Orthoretrovirinae, and we highlight whether they have been described or suspected to be transmitted through breast milk, covering various species. We also elaborate on the production and composition of breast milk and discuss potential entry sites of exogenous mammalian retroviruses during oral transmission.
CRIS-Team Scopus Importer:2023-08-11
Keywords: breast milk; breastfeeding; human immunodeficiency virus (HIV); human T cell lymphotropic virus type 1 (HTLV-1); mammalian retrovirus; oral route; retrovirus; salivary glands; tonsils; virus transmission

miR-186, miR-3651 and miR-494: Potential biomarkers for oral squamous cell carcinoma extracted from whole blood - Ries, Jutta; Vairaktaris, Eleftherios; Agaimy, Abbas; Kintopp, Rita; Baran, Christoph; Neukam, Friedrich Wilhelm; Nkenke, Emeka (Oncology Reports, 2014)
microRNAs (miRNAs) are aberrantly expressed in the whole blood of patients suffering from different types of cancer. Collection of whole blood samples is a minimally invasive procedure. To date, little is known concerning the altered miRNA expression in patients suffering from oral squamous cell carcinoma (OSCC). The present study aimed to evaluate the difference in miRNA expression in whole blood samples in OSCC patients as compared to healthy volunteers who served as controls. In 20 blood samples from patients and healthy volunteers, the expression patterns of 1,205 human miRNAs were examined by miRNA microarray in order to identify those with the most pronounced differential expression. The results were verified by quantitative RT-PCR (RT-qPCR) for miR-186, miR-3651 and miR-494 using 57 samples of patients and 33 samples of healthy volunteers. Receiver operating characteristic (ROC) curves and the highest Youden index were calculated in order to assess cut-off points (COPs) that allowed the distinguishing of blood samples of OSCC patients from those of healthy volunteers. Significantly different expression rates were found for miR-186 (p=0.01), miR-3651 (p=0.0001) and miR-494 (p=0.004) between the OSCC patients and healthy controls. In the OSCC patients, there was a 2-fold upregulation for miR-494 and miR-3651 and a 2-fold downregulation for miR-186. Based on the determined COPs, significant correlations between miR-3651 overexpression and lymph node status (p=0.04), tumor grade (p=0.02) and clinical stage (p=0.04) were indicated. Aberrant expression levels of miR-186, miR-494 and miR-3651 in whole blood samples of OSCC patients may provide the possibility to establish a minimally invasive screening method for OSCC.
EVALuna2:6555

Modulation of immune responses to liposomal vaccines by intrastructural help - Damm, Dominik; Suleiman, Ehsan; Wagner, Jannik; Klessing, Stephan; Pfister, Felix; Elsayed, Hassan; Walkenfort, Bernd; Stobrawe, Jule; Mayer, Julia; Lehner, Elisabeth; Müller-Schmucker, Sandra; Hasenberg, Mike; et al. (European Journal of Pharmaceutics and Biopharmaceutics, 2023)
The encapsulation of HIV-unrelated T helper peptides into liposomal vaccines presenting trimers of the HIV-1 envelope glycoprotein (Env) on the surface (T helper liposomes) may recruit heterologous T cells to provide help for Env-specific B cells. This mechanism called intrastructural help can modulate the HIV-specific humoral immune response. In this study, we used cationic T helper liposomes to induce intrastructural help effects in a small animal model. The liposomes were functionalized with Env trimers by a tag-free approach designed to enable a simplified GMP production. The pre-fusion conformation of the conjugated Env trimers was verified by immunogold electron microscopy (EM) imaging and flow cytometry. The liposomes induced strong activation of Env-specific B cells in vitro. In comparison to previously established anionic liposomes, cationic T helper liposomes were superior in CD4+ T cell activation after uptake by dendritic cells. Moreover, the T helper liposomes were able to target Env-specific B cells in secondary lymphoid organs after intramuscular injection. We also observed efficient T helper cell activation and proliferation in co-cultures with Env-specific B cells in the presence of cationic T helper liposomes. Mouse immunization experiments with cationic T helper liposomes further revealed a modulation of the Env-specific IgG subtype distribution and enhancement of the longevity of antibody responses by ovalbumin- and Hepatitis B (HBV)-specific T cell help. Thus, clinical evaluation of the concept of intrastructural help seems warranted.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Env trimer; Functionalization; HIV vaccine; IgG subtype; Intrastructural help; Nanoparticle; Peptide encapsulation; T helper liposomes

Modulation of vaccine-induced HIV-1-specific immune responses by co-electroporation of PD-L1 encoding DNA - Tannig, Pierre; Peter, Antonia Sophia; Lapuente, Dennis; Klessing, Stephan; Damm, Dominik; Tenbusch, Matthias; Überla, Klaus; Temchura, Vladimir (Vaccines, 2020)
The importance of a balanced TH1/TH2 humoral immune response against the HIV-1 envelope protein (Env) for antibody-mediated HIV-1 control is increasingly recognized. However, there is no defined vaccination strategy to raise it. Since immune checkpoints are involved in the induction of adoptive immunity and their inhibitors (monoclonal antibodies) are licensed for cancer therapy, we investigated the effect of checkpoint blockade after HIV-1 genetic vaccination on enhancement and modulation of antiviral antibody responses. By intraperitoneal administration of checkpoint antibodies in mice we observed an induction of anti-drug antibodies which may interfere with immunomodulation by checkpoint inhibitors. Therefore, we blocked immune checkpoints locally by co-electroporation of DNA vaccines encoding the active soluble ectodomains of programmed cell death protein-1 (PD-1) or its ligand (PD-L1), respectively. Plasmid-encoded immune checkpoints did not elicit a detectable antibody response, suggesting no interference with their immunomodulatory effects. Co-electroporation of a HIV-1 DNA vaccine formulation with soluble PD-L1 ectodomain increased HIV-1 Env-specific TH1 CD4 T cell and IgG2a antibody responses. The overall antibody response was hereby shifted towards a more TH1/TH2 balanced subtype pattern. These findings indicate that co-electroporation of soluble checkpoint ectodomains together with DNA-based vaccines has modulatory effects on vaccine-induced immune responses that could improve vaccine efficacies.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Checkpoint blockade; Checkpoint inhibitors; HIV-1; Immunomodulation; Intramuscular electroporation; Soluble immune checkpoints

Molecular cross-talk between Y5-receptor and neuropeptide Y drives liver cancer - Dietrich, Peter; Wormser, Laura; Fritz, Valerie; Seitz, Tatjana; de Maria, Monica; Schambony, Alexandra; Kremer, Andreas; Günther, Claudia; Itzel, Timo; Thasler, Wolfgang E.; Teufel, Andreas; Trebicka, Jonel; et al. (Journal of Clinical Investigation, 2020)
Hepatocellular carcinoma (HCC) is clearly age-related and represents one of the deadliest cancer types worldwide. Due to globally increasing risk factors including metabolic disorders, the incidence rates of HCC are still rising. However, the molecular hallmarks of HCC remain poorly understood. Neuropeptide Y (NPY) and NPY-receptors represent a highly conserved, stress-activated system which is involved in diverse cancer-related hallmarks including aging and metabolic alterations, but its impact on liver cancer had been unclear. Here, we observed increased NPY5-receptor (Y5R) expression in HCC which correlated with tumor growth and survival. Furthermore, we found that its ligand NPY was secreted by peri-tumorous hepatocytes. Hepatocyte-derived NPY promoted HCC progression by Y5R-activation. Transforming growth factor beta 1 (TGFβ1) was identified as a regulator of NPY in hepatocytes and induced Y5R in invasive cancer cells. Moreover, NPY-conversion by dipeptidylpeptidase 4 (DPP4) augmented Y5R-activation and function in liver cancer. The TGFβ-NPY-Y5R-axis and DPP4 represent attractive therapeutic targets for controlling liver cancer progression.
EVALuna2:212290
Keywords: Aging; Cancer; Hepatology

Molecular Mechanisms of HTLV-1 Cell-to-Cell Transmission - Groß, Christine; Thoma-Kreß, Andrea (Viruses, 2016)
The tumorvirus human T-cell lymphotropic virus type 1 (HTLV-1), a member of the delta-retrovirus family, is transmitted via cell-containing body fluids such as blood products, semen, and breast milk. In vivo, HTLV-1 preferentially infects CD4? T-cells, and to a lesser extent, CD8? T-cells, dendritic cells, and monocytes. Efficient infection of CD4? T-cells requires cell-cell contacts while cell-free virus transmission is inefficient. Two types of cell-cell contacts have been described to be critical for HTLV-1 transmission, tight junctions and cellular conduits. Further, two non-exclusive mechanisms of virus transmission at cell-cell contacts have been proposed: (1) polarized budding of HTLV-1 into synaptic clefts; and (2) cell surface transfer of viral biofilms at virological synapses. In contrast to CD4? T-cells, dendritic cells can be infected cell-free and, to a greater extent, via viral biofilms in vitro. Cell-to-cell transmission of HTLV-1 requires a coordinated action of steps in the virus infectious cycle with events in the cell-cell adhesion process; therefore, virus propagation from cell-to-cell depends on specific interactions between cellular and viral proteins. Here, we review the molecular mechanisms of HTLV-1 transmission with a focus on the HTLV-1-encoded proteins Tax and p8, their impact on host cell factors mediating cell-cell contacts, cytoskeletal remodeling, and thus, virus propagation.
EVALuna2:8318

Mucosal expression of DEC-205 targeted allergen alleviates an asthmatic phenotype in mice - Maaske, A.; Devos, F. C.; Niezold, T.; Lapuente, D.; Tannapfel, A.; Vanoirbeek, J. A.; Überla, Klaus; Peters, Marcus; Tenbusch, Matthias (Journal of Controlled Release, 2016)
Considering the rising incidence of allergic asthma, the symptomatic treatments that are currently applied in most cases are less than ideal. Specific immunotherapy is currently the only treatment that is able to change the course of the disease, but suffers from a long treatment duration. A gene based immunization that elicits the targeting of allergens towards dendritic cells in a steady-state environment might have the potential to amend these difficulties. Here we used a replication deficient adenovirus to induce the mucosal expression of OVA coupled to a single-chain antibody against DEC-205. A single intranasal vaccination was sufficient to mitigate an OVA-dependent asthmatic phenotype in a murine model. Invasive airway measurements demonstrated improved lung function after Ad-Dec-OVA treatment, which was in line with a marked reduction of goblet cell hyperplasia and lung eosinophilia. Furthermore OVA-specific IgE titers and production of type 2 cytokines were significantly reduced. Together, the here presented data demonstrate the feasibility of mucosal expression of DEC-targeted allergens as a treatment of allergic asthma.
EVALuna2:8315

Mucosal immunization with an adenoviral vector vaccine confers superior protection against RSV compared to natural immunity - Maier, Clara; Fuchs, Jana; Irrgang, Pascal; Wissing, Michael Hermann; Beyerlein, Jasmin; Tenbusch, Matthias; Lapuente, Dennis (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) infections are the leading cause of severe respiratory illness in early infancy. Although the majority of children and adults mount immune responses against RSV, recurrent infections are frequent throughout life. Humoral and cellular responses contribute to an effective immunity but also their localization at respiratory mucosae is increasingly recognized as an important factor. In the present study, we evaluate a mucosal vaccine based on an adenoviral vector encoding for the RSV fusion protein (Ad-F), and we investigate two genetic adjuvant candidates that encode for Interleukin (IL)-1β and IFN-β promoter stimulator I (IPS-1), respectively. While vaccination with Ad-F alone was immunogenic, the inclusion of Ad-IL-1β increased F-specific mucosal immunoglobulin A (IgA) and tissue-resident memory T cells (TRM). Consequently, immunization with Ad-F led to some control of virus replication upon RSV infection, but Ad-F+Ad-IL-1β was the most effective vaccine strategy in limiting viral load and weight loss. Subsequently, we compared the Ad-F+Ad-IL-1β-induced immunity with that provoked by a primary RSV infection. Systemic F-specific antibody responses were higher in immunized than in previously infected mice. However, the primary infection provoked glycoprotein G-specific antibodies as well eventually leading to similar neutralization titers in both groups. In contrast, mucosal antibody levels were low after infection, whereas mucosal immunization raised robust F-specific responses including IgA. Similarly, vaccination generated F-specific TRM more efficiently compared to a primary RSV infection. Although the primary infection resulted in matrix protein 2 (M2)-specific T cells as well, they did not reach levels of F-specific immunity in the vaccinated group. Moreover, the infection-induced T cell response was less biased towards TRM compared to vaccine-induced immunity. Finally, our vaccine candidate provided superior protection against RSV infection compared to a primary infection as indicated by reduced weight loss, virus replication, and tissue damage. In conclusion, our mucosal vaccine candidate Ad-F+Ad-IL-1β elicits stronger mucosal immune responses and a more effective protection against RSV infection than natural immunity generated by a previous infection. Harnessing mucosal immune responses by next-generation vaccines is therefore a promising option to establish effective RSV immunity and thereby tackle a major cause of infant hospitalization.
CRIS-Team Scopus Importer:2022-09-09
Keywords: adenoviral (Ad) vector; IgA; mucosal; natural immunity; RSV (respiratory syncytial virus); tissue-resident memory T cells; TRM; vaccine

Mucosal vaccination with a viral vector vaccine induces robust lung-resident T cell responses and protects against 4T1 metastasis - Oltmanns, Friederike; Vieira Antao, Ana Isabel; Irrgang, P.; Meyn, V.; Jörg, Leticia; Tenbusch, Matthias; Lapuente, Dennis (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Multiepitope tissue analysis reveals SPPL3-mediated ADAM10 activation as a key step in the transformation of melanocytes - Ostalecki, Christian; Lee, Jung-Hyun; Dindorf, Jochen; Collenburg, Lena; Schierer, Stephan; Simon, Beate; Schliep, Stefan; Kremmer, Elisabeth; Schuler, Gerold; Baur, Andreas (Science Signaling, 2017)
The evolution of cancer is characterized by the appearance of specific mutations, but these mutations are translated into proteins that must cooperate to induce malignant transformation. Using a systemic approach with the multiepitope ligand cartography (MELC) technology, we analyzed protein expression profiles (PEPs) in nevi and BRAFV600E-positive superficial spreading melanomas (SSMs) from patient tissues to identify key transformation events. The PEPs in nevi and SSMs differed predominantly in the abundance of specific antigens, but the PEPs of nevi- and melanoma-associated keratinocytes gradually changed during the transformation process. A stepwise change in PEP with similar properties occurred in keratinocytes cocultured with melanoma cells. Analysis of the individual steps indicated that activation of the metalloproteinase ADAM10 by signal peptide peptidase-like 3 (SPPL3) triggered by mutant BRAFV600E was a critical transformation event. SPPL3-mediated ADAM10 activation involved the translocation of SPPL3 and ADAM10 into Rab4- or Rab27-positive endosomal compartments. This endosomal translocation, and hence ADAM10 activation, was inhibited by the presence of the tumor suppressor PTEN. Our findings suggest that systematic tissue antigen analysis could complement whole-genome approaches to provide more insight into cancer development.
EVALuna2:34322

Mutation of the highly conserved Ser-40 of the HIV-1 p6 gag protein to Phe causes the formation of a hydrophobic patch, enhances membrane association, and polyubiquitination of Gag - Hahn, Friedrich; Setz, Christian; Friedrich, Melanie; Rauch, Pia; Solbak, Sara Marie; Froystein, Nils Age; Henklein, Petra; Votteler, Joerg; Fossen, Torgils; Schubert, Ulrich (Viruses, 2014)
The HIV-1 p6 Gag protein contains two late assembly (l-) domains that recruit proteins of the endosomal sorting complex required for transport (ESCRT) pathway to mediate membrane fission between the nascent virion and the cell membrane. It was recently demonstrated that mutation of the highly conserved Ser-40 to Phe (S40F) disturbs CA-SP1 processing, virus morphogenesis, and infectivity. It also causes the formation of filopodia-like structures, while virus release remains unaffected. Here, we show that the mutation S40F, but not the conservative mutation to Asp (S40D) or Asn (S40N), augments membrane association, K48-linked polyubiquitination, entry into the 26S proteasome, and, consequently, enhances MHC-I antigen presentation of Gag derived epitopes. Nuclear magnetic resonance (NMR) structure analyses revealed that the newly introduced Phe-40, together with Tyr-36, causes the formation of a hydrophobic patch at the C-terminal ?-helix of p6, providing a molecular rationale for the enhanced membrane association of Gag observed in vitro and in HIV-1 expressing cells. The extended exposure of the S40F mutant to unidentified membrane-resident ubiquitin E3-ligases might trigger the polyubiquitination of Gag. The cumulative data support a previous model of a so far undefined property of p6, which, in addition to MA, acts as membrane targeting domain of Gag.
EVALuna2:8242

Myeloperoxidase Modulates Inflammation in Generalized Pustular Psoriasis and Additional Rare Pustular Skin Diseases - Haskamp, Stefan; Bruns, Heiko; Hahn, Madelaine; Hoffmann, Markus; Gregor, Anne; Löhr, Sabine; Hahn, Jonas; Ringer, Mark; Flamann, Cindy; Frey, Benjamin; Lesner, Adam; Thiel, Christian; et al. (American Journal of Human Genetics, 2020)
Generalized pustular psoriasis (GPP) is a severe multi-systemic inflammatory disease characterized by neutrophilic pustulosis and triggered by pro-inflammatory IL-36 cytokines in skin. While 19%–41% of affected individuals harbor bi-allelic mutations in IL36RN, the genetic cause is not known in most cases. To identify and characterize new pathways involved in the pathogenesis of GPP, we performed whole-exome sequencing in 31 individuals with GPP and demonstrated effects of mutations in MPO encoding the neutrophilic enzyme myeloperoxidase (MPO). We discovered eight MPO mutations resulting in MPO -deficiency in neutrophils and monocytes. MPO mutations, primarily those resulting in complete MPO deficiency, cumulatively associated with GPP (p = 1.85E−08; OR = 6.47). The number of mutant MPO alleles significantly differed between 82 affected individuals and >4,900 control subjects (p = 1.04E−09); this effect was stronger when including IL36RN mutations (1.48E−13) and correlated with a younger age of onset (p = 0.0018). The activity of four proteases, previously implicated as activating enzymes of IL-36 precursors, correlated with MPO deficiency. Phorbol-myristate-acetate-induced formation of neutrophil extracellular traps (NETs) was reduced in affected cells (p = 0.015), and phagocytosis assays in MPO-deficient mice and human cells revealed altered neutrophil function and impaired clearance of neutrophils by monocytes (efferocytosis) allowing prolonged neutrophil persistence in inflammatory skin. MPO mutations contribute significantly to GPP's pathogenesis. We implicate MPO as an inflammatory modulator in humans that regulates protease activity and NET formation and modifies efferocytosis. Our findings indicate possible implications for the application of MPO inhibitors in cardiovascular diseases. MPO and affected pathways represent attractive targets for inducing resolution of inflammation in neutrophil-mediated skin diseases.
CRIS-Team Scopus Importer:2020-09-11
Keywords: ACH; acrodermatitis continua suppurativa Hallopeau; activation of IL-36 precursors; acute generalized 4 exanthematous pustulosis; AGEP; efferocytosis; generalized pustular psoriasis; GPP; impaired NETosis; MPO deficiency; myeloperoxidase; oligogenic inheritance

Myofibrillar instability exacerbated by acute exercise in filaminopathy - Chevessier, Frederic; Schuld, Julia; Orfanos, Zacharias; Plank, Anne-Christine; Wolf, Lucie; Maerkens, Alexandra; Unger, Andreas; Schlötzer-Schrehardt, Ursula; Kley, Rudolf A.; von Hörsten, Stephan; Marcus, Katrin; Linke, Wolfgang A.; et al. (Human Molecular Genetics, 2015)
Filamin C (FLNC) mutations in humans cause myofibrillar myopathy (MFM) and cardiomyopathy, characterized by protein aggregation and myofibrillar degeneration. We generated the first patient-mimicking knock-in mouse harbouring the most common disease-causing filamin C mutation (p.W2710X). These heterozygous mice developed muscle weakness and myofibrillar instability, with formation of filamin C- and Xin-positive lesions streaming between Z-discs. These lesions, which are distinct from the classical MFM protein aggregates by their morphology and filamentous appearance, were greatly increased in number upon acute physical exercise in the mice. This pathology suggests that mutant filamin influences the mechanical stability of myofibrillar Z-discs, explaining the muscle weakness in mice and humans. Re-evaluation of biopsies from MFM-filaminopathy patients with different FLNC mutations revealed a similar, previously unreported lesion pathology, in addition to the classical protein aggregates, and suggested that structures previously interpreted as aggregates may be in part sarcomeric lesions. We postulate that these lesions define preclinical disease stages, preceding the formation of protein aggregates.
EVALuna2:7293

N471D WASH complex subunit strumpellin knock-in mice display mild motor and cardiac abnormalities and BPTF and KLHL11 dysregulation in brain tissue - Clemen, Christoph S.; Schmidt, Andreas; Winter, Lilli; Canneva, Fabio; Wittig, Ilka; Becker, Lore; Coras, Roland; Berwanger, Carolin; Hofmann, Andreas; Eggers, Britta; Marcus, Katrin; Gailus-Durner, Valerie; et al. (Neuropathology and Applied Neurobiology, 2021)
Aims We investigated N471D WASH complex subunit strumpellin (Washc5) knock-in and Washc5 knock-out mice as models for hereditary spastic paraplegia type 8 (SPG8). Methods We generated heterozygous and homozygous N471D Washc5 knock-in mice and subjected them to a comprehensive clinical, morphological and laboratory parameter screen, and gait analyses. Brain tissue was used for proteomic analysis. Furthermore, we generated heterozygous Washc5 knock-out mice. WASH complex subunit strumpellin expression was determined by qPCR and immunoblotting. Results Homozygous N471D Washc5 knock-in mice showed mild dilated cardiomyopathy, decreased acoustic startle reactivity, thinner eye lenses, increased alkaline phosphatase and potassium levels and increased white blood cell counts. Gait analyses revealed multiple aberrations indicative of locomotor instability. Similarly, the clinical chemistry, haematology and gait parameters of heterozygous mice also deviated from the values expected for healthy animals, albeit to a lesser extent. Proteomic analysis of brain tissue depicted consistent upregulation of BPTF and downregulation of KLHL11 in heterozygous and homozygous knock-in mice. WASHC5-related protein interaction partners and complexes showed no change in abundancies. Heterozygous Washc5 knock-out mice showing normal WASHC5 levels could not be bred to homozygosity. Conclusions While biallelic ablation of Washc5 was prenatally lethal, expression of N471D mutated WASHC5 led to several mild clinical and laboratory parameter abnormalities, but not to a typical SPG8 phenotype. The consistent upregulation of BPTF and downregulation of KLHL11 suggest mechanistic links between the expression of N471D mutated WASHC5 and the roles of both proteins in neurodegeneration and protein quality control, respectively.
CRIS-Team WoS Importer:2021-08-27

Nachweis einer Infektion mit Humanem Immundefizienzvirus (HIV): Serologisches Screening mit nachfolgender Bestätigungsdiagnostik durch Antikörper-basierte Testsysteme und/oder durch HIV-Nukleinsäure-Nachweis - Rabenau, Holger F.; Bannert, Norbert; Berger, Annemarie; Mantke, Oliver Donoso; Eberle, Josef; Enders, Martin; Fickenscher, Helmut; Grunert, Hans-Peter; Guertler, Lutz; Heim, Albert; Huzly, Daniela; Kaiser, Rolf; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2015)
EVALuna2:8279

Nanoparticle-based B-cell targeting vaccines: Tailoring of humoral immune responses by functionalization with different TLR-ligands - Zilker, Claudia; Kozlova, Diana; Sokolova, Viktoriya; Yan, Huimin; Epple, Matthias; Überla, Klaus; Temchura, Vladimir (Nanomedicine-Nanotechnology Biology and Medicine, 2017)
Induction of an appropriate type of humoral immune response during vaccination is essential for protection against viral and bacterial infections. We recently observed that biodegradable calcium phosphate (CaP) nanoparticles coated with proteins efficiently targeted and activated naïve antigen-specific B-cells in vitro. We now compared different administration routes for CaP-nanoparticles and demonstrated that intramuscular immunization with such CaP-nanoparticles induced stronger immune responses than immunization with monovalent antigen. Additional functionalization of the CaP-nanoparticles with TRL-ligands allowed modulating the IgG subtype response and the level of mucosal IgA antibodies. CpG-containing CaP-nanoparticles were as immunogenic as a virus-like particle vaccine. Functionalization of CaP-nanoparticles with T-helper cell epitopes or CpG also allowed overcoming lack of T-cell help. Thus, our results indicate that CaP-nanoparticle-based B-cell targeting vaccines functionalized with TLR-ligands can serve as a versatile platform for efficient induction and modulation of humoral immune responses in vivo.
EVALuna2:33772

Naturally occurring variants in the transmembrane and cytoplasmic domains of the human Coxsackie- and adenovirus receptor have no impact on virus internalisation - Herrmann, Leonie; Filip, Adrian; Lapuente, Dennis; Tenbusch, Matthias; Niehaus, Karsten; Rudolph, Volker; Farr, Martin (Biochemical and Biophysical Research Communications, 2020)
The Coxsackie- and adenovirus receptor (CAR) mediates homophilic cell-cell contacts and susceptibility to both human pathogenic viruses through its membrane-distal immunoglobulin domain. In the present study, we screened five missense variants of the human CAR gene for their influence on adenovector or Coxsackievirus entry into Chinese hamster ovary cells. The CAR variants facilitated virus internalisation to a similar extent as wild type CAR. This underlines CAR's presumed invariance and essential physiological role in embryogenesis.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Coxsackievirus and adenovirus receptor; Genetic variants; Viral infection

Neuropeptide Y (NPY) in cerebrospinal fluid from patients with Huntington's Disease: increased NPY levels and differential degradation of the NPY1-30 fragment - Wagner, Leona; Bjorkqvist, Maria; Lundh, Sofia Hult; Wolf, Raik; Boergel, Arne; Schlenzig, Dagmar; Ludwig, Hans-Henning; Rahfeld, Jens-Ulrich; Leavitt, Blair; Dernuth, Hans-Ulrich; Petersen, Asa; von Hörsten, Stephan (Journal of Neurochemistry, 2016)
Huntington's disease (HD) is an inherited and fatal polyglutamine neurodegenerative disorder caused by an expansion of the CAG triplet repeat coding region within the HD gene. Progressive dysfunction and loss of striatal GABAergic medium spiny neurons (MSNs) may account for some of the characteristic symptoms in HD patients. Interestingly, in HD, MSNs expressing neuropeptide Y (NPY) are spared and their numbers is even up-regulated in HD patients. Consistent with this, we report here on increased immuno-linked NPY (IL-NPY) levels in human cerebrospinal fluid (hCSF) from HD patients (Control n = 10; early HD n = 9; mid HD n = 11). As this antibody-based detection of NPY may provide false positive differences as a result of the antibody-based detections of only fragments of NPY, the initial finding was validated by investigating the proteolytic stability of NPY in hCSF using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) and selective inhibitors. A comparison between resulting NPY-fragments and detailed epitope analysis verified significant differences in IL-NPY1-36/3-36 and NPY1-30 levels between HD patients and control subjects with no significant differences between early vs mid HD cases. Ex vivo degradomics analysis demonstrated that NPY is initially degraded to NPY1-30 by cathepsin D in both HD patients and control subjects. Yet, NPY1-30 is then further differentially hydrolyzed by thimet oligopeptidase (TOP) in HD patients and by neprilysin (NEP) in control subjects. Furthermore, altered hCSF TOP-inhibitor Dynorphin A1-13 (Dyn-A1-13 ) and TOP-substrate Dyn-A1-8 levels indicate an impaired Dyn-A-TOP network in HD patients. Thus, we conclude that elevated IL-NPY-levels in conjunction with TOP-/NEP-activity/protein as well as Dyn-A1-13 -peptide levels may serve as a potential biomarker in human CSF of HD. Huntington's disease (HD) patients' cerebrospinal fluid (CSF) exhibits higher neuropeptide Y (NPY) levels. Further degradomics studies show that CSF-NPY is initially degraded to NPY1-30 by Cathepsin D. The NPY1-30 fragment is then differentially degraded in HD vs control involving Neprilysin (NEP), Thimet Oligopeptidase (TOP), and TOP-Dynorphin-A network. Together, these findings may help in search for HD biomarkers.
EVALuna2:24983

Neutralizing Antibodies Limit Cell-Associated Spread of Human Cytomegalovirus in Epithelial Cells and Fibroblasts - Reuter, Nina; Kropff, Barbara; Britt, William J.; Mach, Michael; Thomas, Marco (Viruses, 2022)
Human cytomegalovirus (HCMV) can cause severe clinical disease in immunocompromised individuals, such as allograft recipients and infants infected in utero. Neutralizing activity of antibodies, measured as the ability to prevent the entry of cell-free virus, has been correlated with the reduction in HCMV transmission and the severity of HCMV-associated disease. However, in vivo HCMV amplification may occur mainly via cell-to-cell spread. Thus, quantifying the inhibition of cell-to-cell transmission could be important in the evaluation of therapeutic antibodies and/or humoral responses to infection or immunization. Here, we established a quantitative plaque reduction assay, which allowed for the measurement of the capacity of antibodies to limit HCMV spread in vitro. Using an automated fluorescence spot reader, infection progression was assayed by the expansion of viral plaques during the course of infection with various GFP-expressing viruses. We found that in contrast to non-neutralizing monoclonal antibodies (mAbs), neutralizing mAbs against both glycoprotein B and H (gB and gH) could significantly inhibit viral plaque expansion of different HCMV strains and was equally efficient in fibroblasts as in epithelial cells. In contrast, an anti-pentamer mAb was active only in epithelial cells. Taken together, our data demonstrate that specific anti-HCMV mAbs can significantly limit cell-associated virus spread in vitro.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Antibodies; Cell-associated spread; Cell-to-cell spread; Glycoproteins; Herpesviruses; Human cytomegalovirus (HCMV); Neutralization; Plaque size reduction

New efficient artemisinin derived agents against human leukemia cells, human cytomegalovirus and Plasmodium falciparum: 2nd generation 1,2,4-trioxane-ferrocene hybrids. - Reiter, Christoph; Fröhlich, Tony; Zeino, Maen; Marschall, Manfred; Bahsi, Hanife; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Hampel, Frank; Efferth, Thomas; Tsogoeva, Svetlana (European journal of medicinal chemistry, 2015)
In our ongoing search for highly active hybrid molecules exceeding their parent compounds in anticancer, antimalaria as well as antiviral activity and being an alternative to the standard drugs, we present the synthesis and biological investigations of 2nd generation 1,2,4-trioxane-ferrocene hybrids. In vitro tests against the CCRF-CEM leukemia cell line revealed di-1,2,4-trioxane-ferrocene hybrid 7 as the most active compound (IC50 of 0.01 μM). Regarding the activity against the multidrug resistant subline CEM/ADR5000, 1,2,4-trioxane-ferrocene hybrid 5 showed a remarkable activity (IC50 of 0.53 μM). Contrary to the antimalaria activity of hybrids 4-8 against Plasmodium falciparum 3D7 strain with slightly higher IC50 values (between 7.2 and 30.2 nM) than that of their parent compound DHA, hybrids 5-7 possessed very promising activity (IC50 values lower than 0.5 μM) against human cytomegalovirus (HCMV). The application of 1,2,4-trioxane-ferrocene hybrids against HCMV is unprecedented and demonstrated here for the first time.
Keywords: Artemisinin; Ferrocene; Hybrid; Cancer; Malaria; Human cytomegalovirus

New insight into the phosphorylation-regulated intranuclear localization of human cytomegalovirus pUL69 mediated by cyclin-dependent kinases (CDKs) and viral CDK orthologue pUL97 - Graf, Laura; Feichtinger, Sabine; Naing, Zin; Hutterer, Corina; Milbradt, Jens; Webel, Rike; Wagner, Sabrina; Scott, Gillian M.; Hamilton, Stuart T.; Rawlinson, William D.; Stamminger, Thomas; Thomas, Marco; et al. (Journal of General Virology, 2016)
Cyclin-dependent kinases (CDKs) are multifaceted regulators involved in the replication of human cytomegalovirus. Recently, we demonstrated an interaction of CDK9-cyclin T1 as well as viral CDK orthologue pUL97 with the viral regulator pUL69, thereby leading to pUL69-activating phosphorylation. Here, we demonstrate that colocalization and direct pUL69-cyclin T1 interaction is independent of viral strains and host cell types. In vitro phosphorylation of pUL69 by CDK9 or pUL97 did not occur in a single site-specific manner, but at multiple sites. The previously described fine-speckled nuclear aggregation of pUL69 was assigned to the late phase of viral replication. CDK inhibitors, including a novel inhibitor of the CDK-activating kinase CDK7, massively intensified this fine-speckled accumulation. Interestingly, we also observed spontaneous pUL69 accumulation in the absence of inhibitors at a lower frequency. These findings provide new insight into pUL69 kinase interregulation and emphasize the importance of pUL69 phosphorylation for correct intranuclear localization.
EVALuna2:8332

No evidence for human papillomavirus infection in focal cortical dysplasia IIb - Coras, Roland; Korn, Klaus; Bien, Christian G.; Kalbhenn, Thilo; Roessler, Karl; Kobow, Katja; Giedl, Josef; Fleckenstein, Bernhard; Blümcke, Ingmar (Annals of Neurology, 2015)
The etiology of focal cortical dysplasia type IIb (FCDIIb) remains enigmatic in patients suffering from drug-resistant epilepsy, and an aberrant activation of the mammalian target of rapamycin complex 1 signaling pathway (mTORC1) was detected in this developmental brain malformation. Recently, the human papillomavirus (HPV) oncoprotein E6 has been identified as a potent activator of mTORC1, and HPV16 E6 has been described to persist in balloon cells obtained from surgical FCDIIb specimens. Although this observation was replicated by an independent second report, it contradicts current knowledge of HPV biology. HPV infects the squamous or mucocutaneous epithelium; hematogenic spread into other tissues has not been observed. In addition, brain carcinogenesis has never been reported in FCDIIb patients. Herein, we have tried to confirm 2 previous reports of HPV16 E6 infection using an independent series of 14 surgical specimens with histopathologically confirmed FCDIIb.Snap-frozen FCDIIb specimens were tested for HPV DNA using the primer set for amplification of the complete E6 reading frame of HPV16 and 3 other sets of primers (2 consensus primer sets detecting multiple HPV genotypes, and another primer set specifically used for HPV16). Furthermore, formalin-fixed and paraffin-embedded histopathological preparations were immunohistochemically analyzed using previously described antibodies directed against the HPV E6 oncoprotein.All 14 FCDIIb specimens were negative for HPV DNA with all 4 primer sets. Antibodies directed against the HPV E6 epitope showed weak labeling of cytoplasm in balloon cells, as previously described in FCDIIb, but also in other cell populations.Our data did not confirm previously reported evidence for HPV16 detection in FCDIIb. Ann Neurol 2015;77:312-319.
EVALuna2:6690

No evidence of pathogenic involvement of cathelicidins in patient cohorts and mouse models of lupus and arthritis - Kienhofer, D.; Hahn, Jonas; Schubert, I.; Reinwald, Christiane; Ipseiz, N.; Lang, Sabine; Borras, E. Bosch; Amann, Kerstin Ute; Sjowall, C.; Barron, A. E.; Hueber, Axel; Agerberth, B.; et al. (PLoS ONE, 2014)
Apart from their role in the immune defence against pathogens evidence of a role of antimicrobial peptides (AMPs) in autoimmune diseases has accumulated in the past years. The aim of this project was to examine the functional impact of the human cathelicidin LL-37 and the mouse cathelicidin-related AMP (CRAMP) on the pathogenesis of lupus and arthritis. Serum LL-37 and anti-LL-37 levels were measured by ELISA in healthy donors and patients with Systemic Lupus Erythematosus (SLE) and Rheumatoid arthritis (RA). Pristane-induced lupus was induced in female wild type (WT) and cathelicidin-deficient (CRAMP-/-) mice. Serum levels of anti-Sm/RNP, anti-dsDNA, and anti-histone were determined via ELISA, cytokines in sera and peritoneal lavages were measured via Multiplex. Expression of Interferon I stimulated genes (ISG) was determined by real-time PCR. Collagen-induced arthritis (CIA) was induced in male WT and CRAMP-/- mice and arthritis severity was visually scored and analysed histomorphometrically by OsteoMeasure software. Serum levels of anti-LL-37 were higher in SLE-patients compared to healthy donors or patients with RA. However, no correlation to markers of disease activity or organ involvement was observed. No significant differences of autoantibody or cytokine/chemokine levels, or of expression of ISGs were observed between WT and CRAMP-/- mice after pristane-injection. Furthermore, lung and kidney pathology did not differ in the absence of CRAMP. Incidence and severity of CIA and histological parameters (inflammation, cartilage degradation, and bone erosion) were not different in WT and CRAMP-/- mice. Although cathelicidins are upregulated in mouse models of lupus and arthritis, cathelicidin-deficiency did not persistently affect the diseases. Also in patients with SLE, autoantibodies against cathelicidins did not correlate with disease manifestation. Reactivity against cathelicidins in lupus and arthritis could thus be an epiphenomenon caused by extensive overexpression in blood and affected tissues. In addition, other cationic AMPs could functionally compensate for the deficiency of cathelicidins.
EVALuna2:12499

Noncanonical NF-?B activation by the oncoprotein Tio occurs through a nonconserved TRAF3-binding motif - de Jong, Sarah Jill; Albrecht, Jens-Christian; Giehler, Fabian; Kieser, Arnd; Sticht, Heinrich; Biesinger, Brigitte (Science Signaling, 2013)
Members of the nuclear factor ?B (NF-?B) family of transcription factors regulate many cellular functions. Activation of NF-?B signaling is commonly classified as occurring through canonical or noncanonical pathways. Most NF-?B-inducing stimuli, including the viral oncoprotein Tio, lead to a concerted activation of both NF-?B pathways; however, extensive crosstalk at multiple levels between these signaling cascades restricts the ability to discriminate between the canonical and the noncanonical effects. We showed that noncanonical NF-?B activation by Tio depends on a distinct sequence motif that directly recruits tumor necrosis factor receptor-associated factor 3 (TRAF3). Through its TRAF3-binding motif, Tio triggered a ubiquitin-independent depletion of TRAF3 from the cytosol, which prevented TRAF3 from inhibiting signaling through the noncanonical NF-?B cascade. Furthermore, the Tio-TRAF3 interaction did not affect components of the canonical NF-?B signaling pathway or the expression of target genes; thus, Tio induced noncanonical NF-?B independently of crosstalk with the canonical pathway. Together, these data identify a distinct molecular mechanism of noncanonical NF-?B activation that should enable studies into the particular functions of this pathway.
EVALuna2:8187

Non-redundant and redundant roles of cytomegalovirus gH/gL complexes in host organ entry and intra-tissue spread - Lemmermann, Niels A. W.; Krmpotic, Astrid; Podlech, Juergen; Brizic, Ilija; Prager, Adrian; Adler, Heiko; Karbach, Astrid; Wu, Yiquan; Jonjic, Stipan; Reddehase, Matthias J.; Adler, Barbara (PLoS Pathogens, 2015)
Herpesviruses form different gH/gL virion envelope glycoprotein complexes that serve as entry complexes for mediating viral cell-type tropism in vitro; their roles in vivo, however, remained speculative and can be addressed experimentally only in animal models. For murine cytomegalovirus two alternative gH/gL complexes, gH/gL/gO and gH/gL/MCK-2, have been identified. A limitation of studies on viral tropism in vivo has been the difficulty in distinguishing between infection initiation by viral entry into first-hit target cells and subsequent cell-to-cell spread within tissues. As a new strategy to dissect these two events, we used a gO-transcomplemented ?gO mutant for providing the gH/gL/gO complex selectively for the initial entry step, while progeny virions lack gO in subsequent rounds of infection. Whereas gH/gL/gO proved to be critical for establishing infection by efficient entry into diverse cell types, including liver macrophages, endothelial cells, and hepatocytes, it was dispensable for intra-tissue spread. Notably, the salivary glands, the source of virus for host-to-host transmission, represent an exception in that entry into virus-producing cells did not strictly depend on either the gH/gL/gO or the gH/gL/MCK-2 complex. Only if both complexes were absent in gO and MCK-2 double-knockout virus, in vivo infection was abolished at all sites.
EVALuna2:8256

NORMALIZATION OF PHENOTYPE AND REDUCTION OF GLIOSIS LEVELS VIA GLUTAMINYL CYCLASES INHIBITION IN A HUNTINGTON DISEASE MOUSE MODEL - Plank, Anne-Christine; Schilling, Stephan; Hoffmann, Torsten; Lues, Inge; von Hörsten, Stephan (2018)
EVALuna2:36092

Novel cytomegalovirus-inhibitory compounds of the class pyrrolopyridines show a complex pattern of target binding that suggests an unusual mechanism of antiviral activity - Hahn, Friedrich; Hutterer, Corina; Henry, Christophe; Hamilton, Stuart T.; Strojan, Hanife; Kraut, Alexandra; Schulte, Ulrike; Schuetz, Martin; Kohrt, Stephan; Wangen, Christina; Pfizer, Jose; Coute, Yohann; et al. (Antiviral Research, 2018)
Human cytomegalovirus (HCMV) is a major human pathogen with seropositivity rates in the adult population ranging between 40% and 95%. HCMV infection is associated with severe pathology, such as life-threatening courses of infection in immunocompromised individuals and neonates. Current standard therapy with valganciclovir has the disadvantage of adverse side effects and viral drug resistance. A novel anti-HCMV drug, letermovir, has been approved recently, so that improved therapy options are available. Nevertheless, even more so far unexploited classes of compounds and molecular modes of action will be required for a next generation of antiherpesviral treatment strategies. In this study, we focused on the analysis of the antiviral potency of a novel class of compounds, i.e. pyrrolopyridine analogs, and identified both hit compounds and their target protein candidates. In essence, we provide novel evidence as follows: (i) screening hit SC88941 is highly active in inhibiting HCMV replication in primary human fibroblasts with an EC50 value of 0.20 +/- 0.01 mu M in the absence of cytotoxicity, (ii) inhibition occurs at the early-late stage of viral protein production and shows reinforcing effects upon LMV cotreatment, (iii) among the viruses analyzed, antiviral activity was most pronounced against beta-herpesviruses (HCMV, HHV-6A) and intermediate against adenovirus (HAdV-2), (iv) induction of SC88941 resistance was not detectable, thus differed from the induction of ganciclovir resistance, (v) a linker-coupled model compound was used for mass spectrometry-based target identification, thus yielding several drug-binding target proteins and (vi) a first confocal imaging approach used for addressing intracellular effects of SC88941 indicated qualitative and quantitative alteration of viral protein expression and localization. Thus, our findings suggest a multifaceted pattern of compound-target binding in connection with an unusual mode of action, opening up further opportunities of antiviral drug development.
EVALuna2:35263

Novel, orally available immune modulator MP1032 with pan-variant anti-SARS-CoV-2 and anti-inflammatory activity - Schumann, S.; Setz, C.; Schulz, P.; Kaiser, A.; Schubert, Ulrich; Brysch, W. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Novel role of NPY in neuroimmune interaction and lung growth after intrauterine growth restriction - Thangaratnarajah, Chansutha; Dinger, Katharina; Vohlen, Christina; Klaudt, Christian; Nawabi, Jawed; Garcia, Eva Lopez; Kwapiszewska, Grazyna; Dobner, Julia; Nuesken, Kai D.; Van Koningsbruggen-Rietschel, Silke; von Hörsten, Stephan; Doetsch, Joerg; et al. (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2017)
Individuals with intrauterine growth restriction (IUGR) are at risk for chronic lung disease. Using a rat model, we showed in our previous studies that altered lung structure is related to IL-6/STAT3 signaling. As neuropeptide Y (NPY), a coneurotransmitter of the sympathetic nervous system, regulates proliferation and immune response, we hypothesized that dysregulated NPY after IUGR is linked to IL-6, impaired myofibroblast function, and alveolar growth. IUGR was induced in rats by isocaloric low-protein diet; lungs were analyzed on embryonic day (E) 21, postnatal day (P) 3, P12, and P23. Finally, primary neonatal lung myofibroblasts (pnF) and murine embryonic fibroblasts (MEF) were used to assess proliferation, apoptosis, migration, and IL-6 expression. At E21, NPY and IL-6 expression was decreased, and AKT/PKC and STAT3/AMPKα signaling was reduced. Early reduction of NPY/IL-6 was associated with increased chord length in lungs after IUGR at P3, indicating reduced alveolar formation. At P23, however, IUGR rats exhibited a catch-up of body weight and alveolar growth coupled with more proliferating myofibroblasts. These structural findings after IUGR were linked to activated NPY/PKC, IL-6/AMPKα signaling. Complementary, IUGR-pnF showed increased survival, impaired migration, and reduced IL-6 compared with control-pnF (Co-pnF). In contrast, NPY induced proliferation, migration, and increased IL-6 synthesis in fibroblasts. Additionally, NPY-/-mice showed reduced IL-6 signaling and less proliferation of lung fibroblasts. Our study presents a novel role of NPY during alveolarization: NPY regulates1) IL-6 and lung STAT3/AMPKα signaling, and2) proliferation and migration of myofibroblasts. These new insights in pulmonary neuroimmune interaction offer potential strategies to enable lung growth.
EVALuna2:32789

Nsp16 shields SARS–CoV-2 from efficient MDA5 sensing and IFIT1-mediated restriction - Ruß, Alina; Wittmann, Sabine; Tsukamoto, Yuta; Herrmann, Alexandra; Deutschmann, Janina; Lagisquet, Justine; Enßer, Armin; Kato, Hiroki; Gramberg, Thomas (EMBO Reports, 2022)
Methylation of the mRNA 5′ cap by cellular methyltransferases enables efficient translation and avoids recognition by innate immune factors. Coronaviruses encode viral 2′-O-methyltransferases to shield their RNA from host factors. Here, we generate recombinant SARS–CoV-2 harboring a catalytically inactive 2′-O-methyltransferase Nsp16, Nsp16mut, and analyze viral replication in human lung epithelial cells. Although replication is only slightly attenuated, we find SARS–CoV-2 Nsp16mut to be highly immunogenic, resulting in a strongly enhanced release of type I interferon upon infection. The elevated immunogenicity of Nsp16mut is absent in cells lacking the RNA sensor MDA5. In addition, we report that Nsp16mut is highly sensitive to type I IFN treatment and demonstrate that this strong antiviral effect of type I IFN is mediated by the restriction factor IFIT1. Together, we describe a dual role for the 2′-O-methyltransferase Nsp16 during SARS–CoV-2 replication in avoiding efficient recognition by MDA5 and in shielding its RNA from interferon-induced antiviral responses, thereby identifying Nsp16 as a promising target for generating attenuated and highly immunogenic SARS–CoV-2 strains and as a potential candidate for therapeutic intervention.
CRIS-Team Scopus Importer:2022-11-04
Keywords: 2′-O-methyltransferase; IFIT1; MDA5; Nsp16; SARS–CoV-2

Nuclear Egress Complexes of HCMV and Other Herpesviruses: Solving the Puzzle of Sequence Coevolution, Conserved Structures and Subfamily-Spanning Binding Properties - Marschall, Manfred; Häge, Sigrun; Conrad, Marcus; Alkhashrom, Sewar; Kicuntod, Jintawee; Schweininger, Johannes; Kriegel, Mark; Loesing, Josephine; Tillmanns, Julia; Neipel, Frank; Eichler, Jutta; Muller, Yves; et al. (Viruses, 2020)
Herpesviruses uniquely express two essential nuclear egress-regulating proteins forming a heterodimeric nuclear egress complex (core NEC). These core NECs serve as hexameric lattice-structured platforms for capsid docking and recruit viral and cellular NEC-associated factors that jointly exert nuclear lamina as well as membrane-rearranging functions (multicomponent NEC). The regulation of nuclear egress has been profoundly analyzed for murine and human cytomegaloviruses (CMVs) on a mechanistic basis, followed by the description of core NEC crystal structures, first for HCMV, then HSV-1, PRV and EBV. Interestingly, the highly conserved structural domains of these proteins stand in contrast to a very limited sequence conservation of the key amino acids within core NEC-binding interfaces. Even more surprising, although a high functional consistency was found when regarding the basic role of NECs in nuclear egress, a clear specification was identified regarding the limited, subfamily-spanning binding properties of core NEC pairs and NEC multicomponent proteins. This review summarizes the evolving picture of the relationship between sequence coevolution, structural conservation and properties of NEC interaction, comparing HCMV to alpha-, beta- and gamma-herpesviruses. Since NECs represent substantially important elements of herpesviral replication that are considered as drug-accessible targets, their putative translational use for antiviral strategies is discussed.
CRIS-Team WoS Importer:2020-08-07

Nuclear import of isoforms of the cytomegalovirus kinase pUL97 is mediated by differential activity of NLS1 and NLS2 both acting through classical importin-? binding - Webel, Rike; Solbak, Sara M. O.; Held, Christian; Milbradt, Jens; Groß, Andrea; Eichler, Jutta; Wittenberg, Thomas; Jardin, Christophe; Sticht, Heinrich; Fossen, Torgils; Marschall, Manfred (Journal of General Virology, 2012)
The multifunctional protein kinase pUL97 of human cytomegalovirus (HCMV) strongly determines the efficiency of virus replication. Previously, the existence of two pUL97 isoforms that arise from alternative translational initiation and show a predominant nuclear localization was described. Two bipartite nuclear localization sequences, NLS1 and NLS2, were identified in the N terminus of the large isoform, whilst the small isoform exclusively contained NLS2. The current study found the following: (i) pUL97 nuclear localization in HCMV-infected primary fibroblasts showed accumulations in virus replication centres and other nuclear sections; (ii) in a quantitative evaluation system for NLS activity, the large isoform showed higher efficiency of nuclear translocation than the small isoform; (iii) NLS1 was mapped to aa 6-35 and NLS2 to aa 190-213; (iv) using surface plasmon resonance spectroscopy, the binding of both NLS1 and NLS2 to human importin-? was demonstrated, stressing the importance of individual arginine residues in the bipartite consensus motifs; (v) nuclear magnetic resonance spectroscopy of pUL97 peptides confirmed an earlier statement about the functional requirement of NLS1 embedding into an intact ?-helical structure; and (vi) a bioinformatics investigation of the solvent-accessible surface suggested a high accessibility of NLS1 and an isoform-specific, variable accessibility of NLS2 for interaction with importin-?. Thus, the nucleocytoplasmic transport mechanism of the isoforms appeared to be differentially regulated, and this may have consequences for isoform-dependent functions of pUL97 during virus replication.
EVALuna2:8160

Nuclear PYHIN proteins target the host transcription factor Sp1 thereby restricting HIV-1 in human macrophages and CD4+ T cells - Bosso, Matteo; Prelli Bozzo, Caterina; Hotter, Dominik; Volcic, Meta; Stürzel, Christina M.; Rammelt, Annika; Ni, Yi; Urban, Stephan; Becker, Miriam; Schelhaas, Mario; Wittmann, Sabine; Christensen, Maria H.; et al. (PLoS Pathogens, 2020)
Members of the family of pyrin and HIN domain containing (PYHIN) proteins play an emerging role in innate immunity. While absent in melanoma 2 (AIM2) acts a cytosolic sensor of non-self DNA and plays a key role in inflammasome assembly, the γ-interferon-inducible protein 16 (IFI16) restricts retroviral gene expression by sequestering the transcription factor Sp1. Here, we show that the remaining two human PYHIN proteins, i.e. myeloid cell nuclear differentiation antigen (MNDA) and pyrin and HIN domain family member 1 (PYHIN1 or IFIX) share this antiretroviral function of IFI16. On average, knock-down of each of these three nuclear PYHIN proteins increased infectious HIV-1 yield from human macrophages by more than an order of magnitude. Similarly, knock-down of IFI16 strongly increased virus transcription and production in primary CD4+ T cells. The N-terminal pyrin domain (PYD) plus linker region containing a nuclear localization signal (NLS) were generally required and sufficient for Sp1 sequestration and anti-HIV-1 activity of IFI16, MNDA and PYHIN1. Replacement of the linker region of AIM2 by the NLS-containing linker of IFI16 resulted in a predominantly nuclear localization and conferred direct antiviral activity to AIM2 while attenuating its ability to form inflammasomes. The reverse change caused nuclear-to-cytoplasmic relocalization of IFI16 and impaired its antiretroviral activity but did not result in inflammasome assembly. We further show that the Zn-finger domain of Sp1 is critical for the interaction with IFI16 supporting that pyrin domains compete with DNA for Sp1 binding. Finally, we found that human PYHIN proteins also inhibit Hepatitis B virus and simian vacuolating virus 40 as well as the LINE-1 retrotransposon. Altogether, our data show that IFI16, PYHIN1 and MNDA restrict HIV-1 and other viral pathogens by interfering with Sp1-dependent gene expression and support an important role of nuclear PYHIN proteins in innate antiviral immunity.
CRIS-Team Scopus Importer:2020-08-28

O-linked N-acetylglucosaminylation of Sp1 inhibits the human immunodeficiency virus type 1 promoter - Jochmann, Ramona; Thurau, Mathias; Jung, Susan; Hofmann, Christian; Naschberger, Elisabeth; Kremmer, Elisabeth; Harrer, Thomas; Miller, Matthew; Schaft, Niels; Stürzl, Michael (Journal of Virology, 2009)
Human immunodeficiency virus type 1 (HIV-1) gene expression and replication are regulated by the promoter/enhancer located in the U3 region of the proviral 5′ long terminal repeat (LTR). The binding of cellular transcription factors to specific regulatory sites in the 5′ LTR is a key event in the replication cycle of HIV-1. Since transcriptional activity is regulated by the posttranslational modification of transcription factors with the monosaccharide O-linked N-acetyl-D-glucosamine (O-GlcNAc), we evaluated whether increased O-GlcNAcylation affects HIV-1 transcription. In the present study we demonstrate that treatment of HIV-1-infected lymphocytes with the O-GlcNAcylation-enhancing agent glucosamine (GlcN) repressed viral transcription in a dose-dependent manner. Overexpression of O-GlcNAc transferase (OGT), the sole known enzyme catalyzing the addition of O-GlcNAc to proteins, specifically inhibited the activity of the HIV-1 LTR promoter in different T-cell lines and in primary CD4+ T lymphocytes. Inhibition of HIV-1 LTR activity in infected T cells was most efficient (>95%) when OGT was recombinantly overexpressed prior to infection. O-GlcNAcylation of the transcription factor Sp1 and the presence of Sp1-binding sites in the LTR were found to be crucial for this inhibitory effect. From this study, we conclude that O-GlcNAcylation of Sp1 inhibits the activity of the HIV-1 LTR promoter. Modulation of Sp1 O-GlcNAcylation may play a role in the regulation of HIV-1 latency and activation and links viral replication to the glucose metabolism of the host cell. Hence, the establishment of a metabolic treatment might supplement the repertoire of antiretroviral therapies against AIDS. Copyright © 2009, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

Oncogenesis in HIV-infection. - Albini, Adriana; Aluigi, M; Benelli, Roberto; Biberfeld, Peter; Blasig, C; Calabro, M; Calvo, F; Chieco-Bianchi, L; Corbellino, M; Del Mistro, A; Ekman, M; Favero, A; et al. (International Journal of Oncology, 1996)
The presence of human Kaposi's sarcoma associated herpesvirus-like sequences (KSHV) was examined in different epidemiological variants of Kaposi's sarcoma (KS) and in KS-derived cell cultures by polymerase chain reaction (PCR). KSHV DNA was present in all tumor biopsies of AIDS-associated KS (59 biopsies), endemic KS (26 biopsies; 21 African endemic KS, 5 Greek endemic KS), sporadic/classical KS (28 biopsies) and post-transplant/iatrogenic KS (6 of 7 biopsies). On the contrary, these sequences were only detected rarely in non-involved skin of KS patients (3 positive specimens of 12), in the peripheral blood mononuclear cells of HIV-infected patients (3 positive specimens of 54) and in lymphoma-biopsies (3 positive specimens of 47). Cell cultures derived from KS skin lesions were positive for KSHV DNA only in the first two passages. However, two longer-term positive cultures from a biopsy of a patient affected with sporadic KS and a biopsy of a patient affected with epidemic KS was identified. A strong association of KSHV with KS tissue was observed in all the different epidemiological variants of KS. Long-term positive KS-derived cell cultures will be an important tool to study the herpesvirus-like agent and to investigate its functional role in the initiation and progression of KS.

One year survival of brain tumor patients is closely linked to symptomatic CMV-encephalopathy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, Florian; et al. (2017)
EVALuna2:32882

On the way of assessing autonomous role of p6 in HIV-1 spread - Cantu, Laura; Del Favero, Elena; Moroni, Anna; Schubert, Ulrich; Ricci, Caterina (EUROPEAN BIOPHYSICS JOURNAL WITH BIOPHYSICS LETTERS, 2021)
CRIS-Team WoS Importer:2021-08-13

ORF3c is expressed in SARS-CoV-2-infected cells and inhibits innate sensing by targeting MAVS - Müller, Martin; Herrmann, Alexandra; Fujita, Shigeru; Uriu, Keiya; Kruth, Carolin; Strange, Adam; Kolberg, Jan E.; Schneider, Markus; Ito, Jumpei; Müller, Marcel A.; Drosten, Christian; Enßer, Armin; et al. (EMBO Reports, 2023)
Most SARS-CoV-2 proteins are translated from subgenomic RNAs (sgRNAs). While the majority of these sgRNAs are monocistronic, some viral mRNAs encode more than one protein. One example is the ORF3a sgRNA that also encodes ORF3c, an enigmatic 41-amino-acid peptide. Here, we show that ORF3c is expressed in SARS-CoV-2-infected cells and suppresses RIG-I- and MDA5-mediated IFN-β induction. ORF3c interacts with the signaling adaptor MAVS, induces its C-terminal cleavage, and inhibits the interaction of RIG-I with MAVS. The immunosuppressive activity of ORF3c is conserved among members of the subgenus sarbecovirus, including SARS-CoV and coronaviruses isolated from bats. Notably, however, the SARS-CoV-2 delta and kappa variants harbor premature stop codons in ORF3c, demonstrating that this reading frame is not essential for efficient viral replication in vivo and is likely compensated by other viral proteins. In agreement with this, disruption of ORF3c does not significantly affect SARS-CoV-2 replication in CaCo-2, CaLu-3, or Rhinolophus alcyone cells. In summary, we here identify ORF3c as an immune evasion factor of SARS-CoV-2 that suppresses innate sensing in infected cells.
CRIS-Team Scopus Importer:2023-11-03
Keywords: cryptic open reading frames; IFN antagonist; immune evasion; ORF3c; SARS-CoV-2

Oriented display of HIV-1 Env trimers by a novel coupling strategy enhances B cell activation and phagocytosis - Di Vincenzo, Riccardo; Beutel, Jannis; Arnold, Philipp; Wang, Yu; Damm, Dominik; Tannig, Pierre; Lux, Anja; Temchura, Vladimir; Eichler, Jutta; Überla, Klaus (Frontiers in Immunology, 2024)
Introduction: Conformationally stabilized Env trimers have been developed as antigens for the induction of neutralizing antibodies against HIV-1. However, the non-glycosylated immunodominant base of these soluble antigens may compete with the neutralizing antibody response. This has prompted attempts to couple Env trimers to organic or inorganic nanoparticles with the base facing towards the carrier. Such a site-directed coupling could not only occlude the base of the trimer, but also enhance B cell activation by repetitive display. Methods: To explore the effect of an ordered display of HIV-1 Env on microspheres on the activation of Env-specific B cells we used Bind&Bite, a novel covalent coupling approach for conformationally sensitive antigens based on heterodimeric coiled-coil peptides. By engineering a trimeric HIV-1 Env protein with a basic 21-aa peptide (Peptide K) extension at the C-terminus, we were able to covalently biotinylate the antigen in a site-directed fashion using an acidic complementary peptide (Peptide E) bearing a reactive site and a biotin molecule. This allowed us to load our antigen onto streptavidin beads in an oriented manner. Results: Microspheres coated with HIV-1 Env through our Bind&Bite system showed i) enhanced binding by conformational anti-HIV Env broadly neutralizing antibodies (bNAbs), ii) reduced binding activity by antibodies directed towards the base of Env, iii) higher Env-specific B cell activation, and iv) were taken-up more efficiently after opsonization compared to beads presenting HIV-1 Env in an undirected orientation. Discussion: In comparison to site-directed biotinylation via the Avi-tag, Bind&Bite, offers greater flexibility with regard to alternative covalent protein modifications, allowing selective modification of multiple proteins via orthogonal coiled-coil peptide pairs. Thus, the Bind&Bite coupling approach via peptide K and peptide E described in this study offers a valuable tool for nanoparticle vaccine design where surface conjugation of correctly folded antigens is required.
CRIS-Team Scopus Importer:2024-03-01
Keywords: antigen display; B cell activation; HIV-1; neutralizing antibodies; peptides; phagocytosis

Osteoclastic expression of higher-level regulators NFATc1 and BCL6 in medication-related osteonecrosis of the jaw secondary to bisphosphonate therapy: a comparison with osteoradionecrosis and osteomyelitis - Wehrhan, Falk; Gross, Christian; Creutzburg, Kay; Amann, Kerstin Ute; Ries, Jutta; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Weber, Manuel (Journal of Translational Medicine, 2019)
BackgroundWith an increasing indication spectrum of antiresorptive drugs, the medication-related osteonecrosis of the jaw secondary to bisphosphonate therapy [MRONJ (BP)] is continuously gaining clinical relevance. Impaired osteoclast function, accompanied by altered cell morphology and expression of osteoclastic effector proteins, contributes to the pathogenesis of MRONJ (BP). However, the underlying regulatory mechanisms at a transcriptional level are unaddressed so far. These mechanisms are crucial to the development of disease-characteristic osteoclastic anomalies, that contribute to the pathogenesis of MRONJ (BP). NFATc1 is considered a master upstream osteoclastic activator, whereas BCL6 acts as osteoclastic suppressor. The present study aimed to elucidate the NFATc1 and BCL6 mediated osteoclastic regulation and activity in MRONJ (BP) compared to osteoradionecrosis (ORN) and osteomyelitis (OM) and normal jaw bone.MethodsFormalin-fixed jaw bone specimens from 70 patients [MRONJ (BP) n=30; OM: n=15, ORN: n=15, control: n=10] were analyzed retrospectively for osteoclast expression of NFATc1 and BCL6. The specimens were processed for H&E staining and immunohistochemistry. The histological sections were digitalized and analyzed by virtual microscopy.ResultsOsteoclastic expression of NFATc1 and BCL6 was significantly higher in MRONJ (BP) specimens compared to OM and control specimens. NFATc1 and BCL6 labeling indices revealed no significant differences between MRONJ (BP) and ORN. The ratio of nuclear BCL6+ osteoclasts to cytoplasmic BCL6+ osteoclasts revealed significantly higher values for MRONJ (BP) specimens compared to OM and controls.ConclusionThis study displays that osteoclasts in MRONJ (BP) tissues feature increased expression of the higher-level regulators, paradoxically of both NFATc1 and BCL6. These observations can help to explain the genesis of morphologically altered and resorptive inactive osteoclasts in MRONJ (BP) tissues by outlining the transcriptional regulation of the pathomechanically relevant osteoclastic effector proteins. Furthermore, they strengthen the etiological delineation of MRONJ (BP) from OM and extend the osteoclast profiles of MRONJ (BP), OM and ORN and thus could lead to a better histopathological differentiation that can improve treatment decision and motivate new therapeutic concepts.
CRIS-Team WoS Importer:2019-03-20

Osteosarcoma of the jaw - experience at the Medical University Vienna and comparative study with international tumor registries - Eder-Czembirek, Christina; Moser, Doris; Holawe, Simone; Brodowicz, Thomas; Ries, Jutta; Sulzbacher, Irene; Selzer, Edgar (Clinics, 2019)
OBJECTIVES: Osteosarcoma of the jaw (OSAJ) is fundamentally different in clinical practice from its peripheral counterparts. Studies are difficult to conduct due to low incidence rates. The primary aim of this study was to provide for the first time a comprehensive retrospective analysis of the treatment concepts and outcome data of OSAJ patients treated at the University Hospital Vienna and to compare these with two recently published studies on OSAJ. The clinical study was accompanied by a biomarker study investigating the prognostic relevance of melanoma-associated antigen-A (MAGE-A) in OSAJ specimens.
CRIS-Team WoS Importer:2019-05-17

Patho-Epigenetics of Infectious Diseases - Preface - Doerfler, Walter (Advances in Experimental Medicine and Biology, 2016)
EVALuna2:8311

Patient-derived cytomegaloviruses with different ganciclovir sensitivities from UL97 mutation retain their replication efficiency and some kinase activity in vitro - Wong, Diana D.; Van Zuylen, Wendy J.; Hamilton, Stuart T.; Steingruber, Mirjam; Sonntag, Eric; Marschall, Manfred; Rawlinson, William D. (Antimicrobial Agents and Chemotherapy, 2019)
Mutations in the cytomegalovirus UL97 kinase gene contribute to antiviral resistance. Mutations A594S and G598D from two clinical isolates were analyzed, and bacterial artificial chromosome (BAC)-engineered A594S recombinant cytomegalovirus exhibited a ganciclovir-resistant phenotype on plaque reduction. Viral replication was comparable to that of the wild type. Cell-based kinase activity and autophosphorylation of ectopically expressed proteins showed that mutants retained some kinase activity. This study showed that patient-derived cytomegalovirus with different ganciclovir sensitivities retained replication efficiency and exhibited some kinase activity in vitro.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Cytomegalovirus; Drug resistance; Ganciclovir; Mutation; Phosphorylation; Protein kinase; UL97

Patient-reported reactogenicity and safety of COVID-19 vaccinations vs. comparator vaccinations: a comparative observational cohort study - Werner, Felix; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Sebastião, Maria; Hueber, Susann; Warkentin, Lisette (BMC Medicine, 2023)
Background: In the course of the SARS-CoV-2 pandemic, multiple vaccines were developed. Little was known about reactogenicity and safety in comparison to established vaccines, e.g. influenza, pneumococcus, or herpes zoster. Therefore, the present study aimed to compare self-reported side effects in persons vaccinated against SARS-CoV-2 with the incidence of side effects in persons receiving one of the established vaccines. Methods: A longitudinal observational study was conducted over a total of 124 days using web-based surveys. Persons receiving either a vaccination against SARS-CoV-2 or one of the established vaccines (comparator group) were included. In the first questionnaire (short-term survey), 2 weeks after vaccination, mainly local and systemic complaints were evaluated. The long-term survey (42 days after vaccination) and follow-up survey (124 weeks after vaccination) focused on medical consultations for any reason. Multivariate analyses were conducted to determine the influence of the vaccine type (SARS-CoV-2 vs. comparator) and demographic factors. Results: In total, data from 16,636 participants were included. Self-reported reactogenicity was lowest in the comparator group (53.2%) and highest in the ChAdOx1 group (85.3%). Local reactions were reported most frequently after mRNA-1273 (73.9%) and systemic reactions mainly after vector-based vaccines (79.8%). Almost all SARS-CoV-2 vaccines showed increased odds of reporting local or systemic reactions. Approximately equal proportions of participants reported medical consultations. None in the comparator group suspected a link to vaccination, while this was true for just over one in 10 in the mRNA-1273 group. The multivariate analysis showed that people with SARS-CoV-2 vaccination were not more likely to report medical consultations; patients who had received a regimen with at least one ChAdOx1 were even less likely to report medical consultations. Younger age, female gender and higher comorbidity were mostly associated with higher odds of medical consultations. Conclusion: The rate of adverse reactions after established vaccinations was roughly comparable to previous studies. Two weeks after vaccination, participants in the SARS-CoV-2 vaccination group reported more local and systemic local reactions than participants in the comparator group. In the further course, however, there were no higher odds of medical consultations in either of the two groups. Thus, altogether, we assume comparable safety. Trial registration: DRKS-ID DRKS00025881 and DRKS-ID DRKS00025373.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Adverse drug reaction; COVID-19; Medical consultation; Observational study; Reactogenicity; SARS-CoV-2; Survey; Vaccine

Patients Receiving Cytokine Inhibitors Have Low Prevalence of SARS-CoV-2 Infection - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

PATIENTS WITH IMMUNE MEDIATED INFLAMMATORY DISEASES ARE OVERREPRESENTED IN LOW-FREQUENCY VIRAL SYMPTOM CLUSTERS - Tascilar, Koray; Simon, David; Krönke, Gerhard; Kleyer, Arnd; Ramming, Andreas; Atreya, Raja; Tenbusch, Matthias; Überla, Klaus; Berking, Carola; Sticherling, Michael; Neurath, Markus; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Patients with immune-mediated inflammatory diseases receiving cytokine inhibitors have low prevalence of SARS-CoV-2 seroconversion - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (Nature Communications, 2020)
Immune-mediated inflammatory diseases (IMIDs) of the joints, gut and skin are treated with inhibitors of inflammatory cytokines. These cytokines are involved in the pathogenesis of coronavirus disease 2019 (COVID-19). Investigating anti-SARS-CoV-2 antibody responses in IMIDs we observe a reduced incidence of SARS-CoV-2 seroconversion in IMID patients treated with cytokine inhibitors compared to patients receiving no such inhibitors and two healthy control populations, despite similar social exposure. Hence, cytokine inhibitors seem to at least partially protect from SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2020-08-07

Patterns of autologous and nonautologous interactions between core nuclear egress complex (NEC) proteins of α‐, β‐ and γ‐herpesviruses - Häge, Sigrun; Sonntag, Eric; Borst, Eva Maria; Tannig, Pierre; Seyler, Lisa; Bäuerle, Tobias; Bailer, Susanne M.; Lee, Chung Pei; Müller, Regina; Wangen, Christina; Milbradt, Jens; Marschall, Manfred (Viruses, 2020)
Nuclear egress is a regulated process shared by α‐, β‐ and γ‐herpesviruses. The core nuclear egress complex (NEC) is composed of the membrane‐anchored protein homologs of human cytomegalovirus (HCMV) pUL50, murine cytomegalovirus (MCMV) pM50, Epstein–Barr virus (EBV) BFRF1 or varicella zoster virus (VZV) Orf24, which interact with the autologous NEC partners pUL53, pM53, BFLF2 or Orf27, respectively. Their recruitment of additional proteins leads to the assembly of a multicomponent NEC, coordinately regulating viral nucleocytoplasmic capsid egress. Here, the functionality of VZV, HCMV, MCMV and EBV core NECs was investigated by coimmunoprecipitation and confocal imaging analyses. Furthermore, a recombinant MCMV, harboring a replacement of ORF M50 by UL50, was analyzed both in vitro and in vivo. In essence, core NEC interactions were strictly limited to autologous NEC pairs and only included one measurable nonautologous interaction between the homologs of HCMV and MCMV. A comparative analysis of MCMV‐WT versus MCMV‐UL50‐infected murine fibroblasts revealed almost identical phenotypes on the levels of protein and genomic replication kinetics. In infected BALB/c mice, virus spread to lung and other organs was found comparable between these viruses, thus stating functional complementarity. In conclusion, our study underlines that herpesviral core NEC proteins are functionally conserved regarding complementarity of core NEC interactions, which were found either virus‐specific or restricted within subfamilies.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Autologous vs. nonautologous interactions; Core NEC interaction properties; Core nuclear egress complexes (NECs); Degree of conservation; Functional complementarity; Multicomponent NEC recruitment of proteins; Takeover of activities in vitro and in vivo; α‐; β‐ and γ‐herpesviruses

Patterns of transmitted HIV drug resistance in europe vary by risk group - Frentz, Dineke; Van De Vijver, David; Abecasis, Ana; Albert, Jan; Hamouda, Osamah; Jorgensen, Louise; Kucherer, Claudia; Struck, Daniel; Schmit, Jean-Claude; Vercauteren, Jurgen; Asjo, Birgitta; Balotta, Claudia; et al. (PLoS ONE, 2014)
In Europe, a continuous programme (SPREAD) has been in place for ten years to study transmission of drug resistant HIV. We analysed time trends of transmitted drug resistance mutations (TDRM) in relation to the risk behaviour reported.HIV-1 patients newly diagnosed in 27 countries from 2002 through 2007 were included. Inclusion was representative for risk group and geographical distribution in the participating countries in Europe. Trends over time were calculated by logistic regression.From the 4317 patients included, the majority was men-having-sex-with-men -MSM (2084, 48%), followed by heterosexuals (1501, 35%) and injection drug users (IDU) (355, 8%). MSM were more often from Western Europe origin, infected with subtype B virus, and recently infected (<1 year) (p<0.001). The prevalence of TDRM was highest in MSM (prevalence of 11.1%), followed by heterosexuals (6.6%) and IDU (5.1%, p<0.001). TDRM was predominantly ascribed to nucleoside reverse transcriptase inhibitors (NRTI) with a prevalence of 6.6% in MSM, 3.3% in heterosexuals and 2.0% in IDU (p = 0.001). A significant increase in resistance to non- nucleoside reverse transcriptase inhibitors (NNRTIs) and a decrease in resistance to protease inhibitors was observed in MSM (p = 0.008 and p = 0.006, respectively), but not in heterosexual patients (p = 0.68 and p = 0.14, respectively).MSM showed to have significantly higher TDRM prevalence compared to heterosexuals and IDU. The increasing NNRTI resistance in MSM is likely to negatively influence the therapy response of first-line therapy, as most include NNRTI drugs.
EVALuna2:8225

PDE-5 inhibition impedes TSP-1 expression, TGF-β activation and matrix accumulation in experimental glomerulonephritis - Hohenstein, Bernd; Daniel, Christoph; Wittmann, Sabine; Hugo, Christian (Nephrology Dialysis Transplantation, 2008)
Background. Matrix expansion and mesangial proliferation are hallmarks of mesangial proliferative glomerulonephritis. Specific inhibition of PDE-5, an enzyme catalyzing the intracellular degradation of cyclic GMP, can be achieved by the inhibitor vardenafil. In this study, we investigated the effects of PDE-5 inhibition in the anti-Thy1 model in the rat in vivo. Methods. After disease induction, rats received 10 mg/kg bw vardenafil twice a day via gavage. On Days 2 and 6, renal biopsies, as well as glomerular isolates, urine and blood samples were taken to compare vardenafil- and placebo-treated groups during the course of disease. Results. Small amounts of PDE-5 were detected in healthy kidneys, but induced in a typical mesangial pattern during disease (by IHC and WB). Specific PDE-5 inhibition resulted in increased glomerular levels of cGMP. Treated animals demonstrated inhibition of MC proliferation and matrix accumulation while renal function and influx of inflammatory cells were not affected. Due to PDE-5 inhibition, the endogenous TGF-β-activating protein TSP-1 and the TGF-β-signalling protein p-smad-2/3 were decreased suggesting this as an antifibrotic mechanism of action of vardenafil in this model. Conclusion. Considering the availability and safety profile of vardenafil, the beneficial antiproliferative and antifibrotic effect in experimental glomerulonephritis may potentially be applicable to the treatment of mesangial proliferative glomerulonephritis in man. © The Author [2008]. Published by Oxford University Press on behalf of ERA-EDTA. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Anti-Thy1 model; Matrix expansion; PDE-5 inhibition; TGF-β; TSP-1

PD-L1 expression in peripheral blood samples of patients with oral squamous cell carcinomas - Ries, Jutta; Weber, Manuel; Baran, Christoph; Agaimy, Abbas; Buettner-Herold, M.; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (2018)
EVALuna2:34230

PD-L1 expression in tumor tissue and peripheral blood of patients with oral squamous cell carcinoma - Weber, Manuel; Wehrhan, Falk; Baran, Christoph; Agaimy, Abbas; Büttner-Herold, Maike; Preidl, Raimund; Neukam, Friedrich Wilhelm; Ries, Jutta (Oncotarget, 2017)
Immune checkpoints like programmed cell death-1 (PD-1) and its ligand PD-L1 are involved in immune escape mechanisms of solid tumors including oral squamous cell carcinoma (OSCC). Inhibitors of the pathway are successfully used for treating especially advanced disease. However, the physiological relevance of PD-1/PD-L1-signaling in OSCC is insufficiently understood. The aim of the study was to analyze if PD-L1 expression in tumor tissue and peripheral blood samples of OSCC patients is associated with histomorphological tumor parameters and if PD-L1 expression in patients is different from controls.OSCC tumor specimens showed a significantly higher PD-L1 expression than oral mucosa controls (p < 0.001; upregulation more than 3-fold). Cross-tabulation revealed an association of increased expression of PD-L1 mRNA in tissue specimens with malignancy (p < 0.001).OSCC cases with higher tumor grade and cases with lymph node metastases (N+) were significantly (p < 0.05) associated with increased PD-L1 expression in peripheral blood. Cross-tabulation revealed an significant association with lymph node metastases (N+) (p <= 0.002).PD-L1 mRNA expression was analyzed in tumor specimens and corresponding samples of healthy oral mucosa and peripheral blood of 45 OSCC patients and 36 healthy control persons using RT-qPCR analysis. A Mann-Whitney U-test, a cut-off point analysis and a Chi-square test were carried out.PD-L1 expression in OSCC could contribute to the immunosuppressive local tumor microenvironment. Increased malignant behavior (higher tumor grade, positive nodal status) might be associated with PD-L1 mediated systemic immune tolerance. Thus, PD-L1 expression in peripheral blood might be an indicator of the existence of metastatic disease (N+) in OSCC.
EVALuna2:25563

Pearls & Oy-sters: SARS-CoV-2 Infection of the CNS in a Patient With Meningeosis Carcinomatosa - Steininger, Philipp; Seifert, Frank; Balk, Stefanie; Kuramatsu, Joji; Kremer, Andreas; Coras, Roland; Engelhorn, Tobias; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Enßer, Armin (Neurology, 2021)
CRIS-Team Scopus Importer:2021-03-26

Performance characteristics of the VERSANT hepatitis C virus RNA 1.0 (kPCR) assay - Gruener, Nico; Viazov, S.; Korn, Klaus; Knöll, Antje; Trippler, M.; Schlaak, J. F.; Gerken, G.; Roggendorf, M.; Ross, R. Stefan (International Journal of Medical Microbiology, 2015)
HCV RNA assays are of central importance for virological diagnostics and for clinical planning and monitoring of an antiviral combination treatment of chronic HCV infections. The objective of the pre-market evaluation of the VERSANT HCV RNA 1.0 Assay (kPCR) was to collect analytical performance data for this new method of HCV RNA quantification and to compare them with the high standards that exist in this context. The assay exhibited a specificity of 100%. The mean intra- and inter-assay imprecision was 14.1% and 14.6%, respectively. The detection limit was determined to be 16IU/ml (95% confidence interval: 11.9-30.6IU/ml) and consequently corresponded to the manufacturer's claims (i.e. 15IU/ml). The test exhibited linearity for all HCV genotypes in a broad range from 15 to 10(8)IU HCV RNA/ml. Hence, the kPCR assay in general is well suitable for HCV RNA determinations in clinical practice. However, in a methodological comparison, a considerable under-quantification of the concentrations of HCV genotype 2 and 3 isolates was detected. Provided that the assay's manufacturer will quickly remedy this shortcoming, the VERSANT HCV RNA 1.0 (kPCR) can be called a completely reliable technique for HCV RNA quantification in routine virological diagnostics.
EVALuna2:8266

Peritoneal exudate cells from long-lived rats exhibit increased IL-10/IL-1? expression ratio and preserved NO/urea ratio following LPS-stimulation in vitro - Dimitrijevic, Mirjana; Aleksic, Iva; Vujic, Vesna; Stanojevic, Stanislava; Pilipovic, Ivan; von Hörsten, Stephan; Leposavic, Gordana (Age, 2014)
In humans, usual aging, differently from successful aging, is associated with deregulation of proinflammatory/anti-inflammatory cytokine balance. The corresponding data from rat studies are limited. Therefore, we examined (i) cytokine messenger RNA (mRNA) profile of fresh peritoneal cells from 6- (adult), 24- (old), and 31-month-old (long-lived) AO rats and (ii) proinflammatory (IL-1? and IL-6) and anti-inflammatory (IL-10) cytokine, NO, and urea production in their LPS-stimulated cultures. Comparing with adult rats, cells from old ones expressed lower amount of TNF-? and IL-6 mRNAs, but greater amount of IL-1? mRNA. On the other hand, cells from long-lived rats exhibited a dramatic increase in IL-10 mRNA expression followed by diminished TNF-? and IL-6 mRNA expression, and comparable expression of IL-1? mRNA relative to adult rats. Consequently, IL-10/IL-1? mRNA ratio was greater in cells from long-lived rats than in adult and old rats. In LPS-stimulated peritoneal cell cultures (contained >=95 % macrophages) from old rats, concentration of common proinflammatory cytokines was higher than in those from adult rats. Comparing with adult and old rats, in LPS-stimulated macrophage cultures from long-lived rats, TNF-? and IL-6 concentrations were lower; IL-1? concentration was comparable or greater (in respect to adult rats), whereas that of IL-10 was strikingly higher. Consistently, in macrophage cultures from long-lived rats, NO (iNOS activity marker)/urea (arginase activity marker) ratio was less and not different from that in old and adult rats, respectively. The study suggests that macrophages from long-lived rats, differently from those of old ones, have substantial ability to limit proinflammatory mediator production, which may contribute to their longevity.
EVALuna2:24973

Phenotypical Characterization of the Nuclear Egress of Recombinant Cytomegaloviruses Reveals Defective Replication upon ORF-UL50 Deletion but Not pUL50 Phosphosite Mutation - Häge, Sigrun; Sonntag, Eric; Svrlanska, Adriana; Borst, Eva Maria; Stilp, Anne Charlotte; Horsch, Deborah; Müller, Regina; Kropff, Barbara; Milbradt, Jens; Stamminger, Thomas; Schlötzer-Schrehardt, Ursula; Marschall, Manfred (Viruses, 2021)
Nuclear egress is a common herpesviral process regulating nucleocytoplasmic capsid release. For human cytomegalovirus (HCMV), the nuclear egress complex (NEC) is determined by the pUL50-pUL53 core that regulates multicomponent assembly with NEC-associated proteins and capsids. Recently, NEC crystal structures were resolved for α-, β- and γ-herpesviruses, revealing profound structural conservation, which was not mirrored, however, by primary sequence and binding properties. The NEC binding principle is based on hook-into-groove interaction through an N-terminal hook-like pUL53 protrusion that embraces an α-helical pUL50 binding groove. So far, pUL50 has been considered as the major kinase-interacting determinant and massive phosphorylation of pUL50-pUL53 was assigned to NEC formation and functionality. Here, we addressed the question of phenotypical changes of ORF-UL50-mutated HCMVs. Surprisingly, our analyses did not detect a predominant replication defect for most of these viral mutants, concerning parameters of replication kinetics (qPCR), viral protein production (Western blot/CoIP) and capsid egress (confocal imaging/EM). Specifically, only the ORF-UL50 deletion rescue virus showed a block of genome synthesis during late stages of infection, whereas all phosphosite mutants exhibited marginal differences compared to wild-type or revertants. These results (i) emphasize a rate-limiting function of pUL50 for nuclear egress, and (ii) demonstrate that mutations in all mapped pUL50 phosphosites may be largely compensated. A refined mechanistic concept points to a multifaceted nuclear egress regulation, for which the dependence on the expression and phosphorylation of pUL50 is discussed.
CRIS-Team Scopus Importer:2021-02-19
Keywords: core nuclear egress complex; differential functional relevance; human cytomegalovirus; ORF-UL50 deletion; phenotypical changes; pUL50 phosphosite mutants

Phosphorylation of murine SAMHD1 regulates its antiretroviral activity - Wittmann, Sabine; Behrendt, Rayk; Eißmann, Kristin; Volkmann, Bianca; Thomas, Dominique; Ebert, Thomas; Cribier, Alexandra; Benkirane, Monsef; Hornung, Veit; Bouzas, Nerea Ferreiros; Gramberg, Thomas (Retrovirology, 2015)
Human SAMHD1 is a triphosphohydrolase that restricts the replication of retroviruses, retroelements and DNA viruses in noncycling cells. While modes of action have been extensively described for human SAMHD1, only little is known about the regulation of SAMHD1 in the mouse. Here, we characterize the antiviral activity of murine SAMHD1 with the help of knockout mice to shed light on the regulation and the mechanism of the SAMHD1 restriction and to validate the SAMHD1 knockout mouse model for the use in future infectivity studies.We found that endogenous mouse SAMHD1 restricts not only HIV-1 but also MLV reporter virus infection at the level of reverse transcription in primary myeloid cells. Similar to the human protein, the antiviral activity of murine SAMHD1 is regulated through phosphorylation at threonine 603 and is limited to nondividing cells. Comparing the susceptibility to infection with intracellular dNTP levels and SAMHD1 phosphorylation in different cell types shows that both functions are important determinants of the antiviral activity of murine SAMHD1. In contrast, we found the proposed RNase activity of SAMHD1 to be less important and could not detect any effect of mouse or human SAMHD1 on the level of incoming viral RNA.Our findings show that SAMHD1 in the mouse blocks retroviral infection at the level of reverse transcription and is regulated through cell cycle-dependent phosphorylation. We show that the antiviral restriction mediated by murine SAMHD1 is mechanistically similar to what is known for the human protein, making the SAMHD1 knockout mouse model a valuable tool to characterize the influence of SAMHD1 on the replication of different viruses in vivo.
EVALuna2:8275

Phosphosite Analysis of the Cytomegaloviral mRNA Export Factor pUL69 Reveals Serines with Critical Importance for Recruitment of Cellular Proteins Pin1 and UAP56/URH49 - Thomas, Marco; Müller, Regina; Horn, Georg; Bogdanow, Boris; Imami, Koshi; Milbradt, Jens; Steingruber, Mirjam; Marschall, Manfred; Schilling, Eva Maria; Fossen, Torgils; Stamminger, Thomas (Journal of Virology, 2020)
Human cytomegalovirus (HCMV) encodes the viral mRNA export factor pUL69, which facilitates the cytoplasmic accumulation of mRNA via interaction with the cellular RNA helicase UAP56 or URH49. We reported previously that pUL69 is phosphorylated by cellular CDKs and the viral CDK-like kinase pUL97. Here, we set out to identify phosphorylation sites within pUL69 and to characterize their importance. Mass spectrometry-based phosphosite mapping of pUL69 identified 10 serine/threonine residues as phosphoacceptors. Surprisingly, only a few of these sites localized to the N terminus of pUL69, which could be due to the presence of additional posttranslational modifications, like arginine methylation. As an alternative approach, pUL69 mutants with substitutions of putative phosphosites were analyzed by Phos-tag SDS-PAGE. This demonstrated that serines S46 and S49 serve as targets for phosphorylation by pUL97. Furthermore, we provide evidence that phosphorylation of these serines mediates cis/trans isomerization by the prolyl isomerase Pin1, thus forming a functional Pin1 binding motif. Surprisingly, while abrogation of the Pin1 motif did not affect the replication of recombinant cytomegaloviruses, mutation of serines next to the interaction site for UAP56/URH49 strongly decreased viral replication. This was correlated with a loss of UAP56/URH49 recruitment. Intriguingly, the critical serines S13 and S15 were located within a sequence resembling the UAP56 binding motif (UBM) of cellular mRNA adaptor proteins like REF and UIF. We propose that betaherpesviral mRNA export factors have evolved an extended UAP56/URH49 recognition sequence harboring phosphorylation sites to increase their binding affinities. This may serve as a strategy to successfully compete with cellular mRNA adaptor proteins for binding to UAP56/URH49.IMPORTANCE The multifunctional regulatory protein pUL69 of human cytomegalovirus acts as a viral RNA export factor with a critical role in efficient replication. Here, we identify serine/threonine phosphorylation sites for cellular and viral kinases within pUL69. We demonstrate that the pUL97/CDK phosphosites within alpha-helix 2 of pUL69 are crucial for its cis/trans isomerization by the cellular protein Pin1. Thus, we identified pUL69 as the first HCMV-encoded protein that is phosphorylated by cellular and viral serine/threonine kinases in order to serve as a substrate for Pin1. Furthermore, our study revealed that betaherpesviral mRNA export proteins contain extended binding motifs for the cellular mRNA adaptor proteins UAP56/URH49 harboring phosphorylated serines that are critical for efficient viral replication. Knowledge of the phosphorylation sites of pUL69 and the processes regulated by these posttranslational modifications is important in order to develop antiviral strategies based on a specific interference with pUL69 phosphorylation.
CRIS-Team Scopus Importer:2020-04-14
Keywords: herpesviruses; human cytomegalovirus; ICP27; mRNA export; protein phosphorylation; pUL69

Pioneer factors in viral infection - Neugebauer, Eva; Bastidas-Quintero, Aura M.; Weidl, Daniel; Full, Florian (Frontiers in Immunology, 2023)
Pioneer factors are transcription factors sharing the fascinating ability to bind to compact chromatin and thereby alter its transcriptional fate. Most pioneer factors are known for their importance during embryonic development, for instance, in inducing zygotic genome activation or cell fate decision. Some pioneer factors are actively induced or downregulated by viral infection. With this, viruses are capable to modulate different signaling pathways resulting for example in MHC-receptor up/downregulation which contributes to viral immune evasion. In this article, we review the current state of research on how different viruses (Herpesviruses, Papillomaviruses and Hepatitis B virus) use pioneer factors for their viral replication and persistence in the host, as well as for the development of viral cancer.
CRIS-Team Scopus Importer:2023-11-03
Keywords: development; DNA-virus; DUX4; herpesvirus; pioneer factor; transcription factor; virus

Plxdc family members are novel receptors for the rhesus monkey rhadinovirus (RRV) - Grosskopf, Anna K.; Schlagowski, Sarah; Fricke, Thomas; Enßer, Armin; Desrosiers, Ronald C.; Hahn, Alexander S. (PLoS Pathogens, 2021)
The rhesus monkey rhadinovirus (RRV), a gamma 2-herpesvirus of rhesus macaques, shares many biological features with the human pathogenic Kaposi's sarcoma-associated herpesvirus (KSHV). Both viruses, as well as the more distantly related Epstein-Barr virus, engage cellular receptors from the Eph family of receptor tyrosine kinases (Ephs). However, the importance of the Eph interaction for RRV entry varies between cell types suggesting the existence of Eph-independent entry pathways. We therefore aimed to identify additional cellular receptors for RRV by affinity enrichment and mass spectrometry. We identified an additional receptor family, the Plexin domain containing proteins 1 and 2 (Plxdc1/2) that bind the RRV gH/gL glycoprotein complex. Preincubation of RRV with soluble Plxdc2 decoy receptor reduced infection by similar to 60%, while overexpression of Plxdc1 and 2 dramatically enhanced RRV susceptibility and cell-cell fusion of otherwise marginally permissive Raji cells. While the Plxdc2 interaction is conserved between two RRV strains, 26-95 and 17577, Plxdc1 specifically interacts with RRV 26-95 gH. The Plxdc interaction is mediated by a short motif at the N-terminus of RRV gH that is partially conserved between isolate 26-95 and isolate 17577, but absent in KSHV gH. Mutation of this motif abrogated the interaction with Plxdc1/2 and reduced RRV infection in a cell type-specific manner. Taken together, our findings characterize Plxdc1/2 as novel interaction partners and entry receptors for RRV and support the concept of the N-terminal domain of the gammaherpesviral gH/gL complex as a multifunctional receptor-binding domain. Further, Plxdc1/2 usage defines an important biological difference between KSHV and RRV.
CRIS-Team WoS Importer:2021-04-16

Population-based study of the durability of humoral immunity after SARS-CoV-2 infection - Peterhoff, David; Wiegrebe, Simon; Einhauser, Sebastian; Patt, Arisha J.; Beileke, Stephanie; Günther, Felix; Steininger, Philipp; Niller, Hans H.; Burkhardt, Ralph; Küchenhoff, Helmut; Gefeller, Olaf; Überla, Klaus; et al. (Frontiers in Immunology, 2023)
SARS-CoV-2 antibody quantity and quality are key markers of humoral immunity. However, there is substantial uncertainty about their durability. We investigated levels and temporal change of SARS-CoV-2 antibody quantity and quality. We analyzed sera (8 binding, 4 avidity assays for spike-(S-)protein and nucleocapsid-(N-)protein; neutralization) from 211 seropositive unvaccinated participants, from the population-based longitudinal TiKoCo study, at three time points within one year after infection with the ancestral SARS-CoV-2 virus. We found a significant decline of neutralization titers and binding antibody levels in most assays (linear mixed regression model, p<0.01). S-specific serum avidity increased markedly over time, in contrast to N-specific. Binding antibody levels were higher in older versus younger participants – a difference that disappeared for the asymptomatic-infected. We found stronger antibody decline in men versus women and lower binding and avidity levels in current versus never-smokers. Our comprehensive longitudinal analyses across 13 antibody assays suggest decreased neutralization-based protection and prolonged affinity maturation within one year after infection.
CRIS-Team Scopus Importer:2023-11-03
Keywords: antibody; avidity; COVID-19; durability; longitudinal; neutralization; population-based; SARS-CoV-2

Postnatal morphological lung development of wild type and CD26/DPP4 deficient rat pups in dependency of LPS exposure - Wagener, Inga; Jungen, Meike; von Hörsten, Stephan; Stephan, Michael; Schmiedl, Andreas (Annals of Anatomy-Anatomischer Anzeiger, 2019)
Background: Rodents are born with morphological immature lungs and an intact surfactant system. CD26/DPP4 is a multifactorial transmembrane integral type II protein, which is involved in physiological and pathophysiological processes and is already expressed during development. CD26/DPP4, called CD26 in the following, is able to enhance or dampen differently triggered inflammation. LPS exposure often used to simulate perinatal infection delays lung development. Objective: A perinatal LPS rat model was used to test the hypothesis that CD26 deficiency modulates LPS-induced retardation in morphological lung development. Methods: New born Fischer CD26 positive (CD26+) and deficient (CD26−) rats were exposed to LPS on postnatal day (day post partum, dpp) 3 and 5. Morphological parameters of lung development were determined stereologically. Lung development was analysed in 7, 10 14 and 21day old rats. Results: Compared to controls LPS application resulted (1) in a mild inflammation independent of the strain, (2) in significantly lower total surface and volume of alveolar septa combined with significantly higher total volume of airspaces and alveolar size on dpp 7 in both substrains. However, compared to controls in LPS treated CD26− rats significant lower values of total septal surface and volume combined with higher values of total parenchymal airspaces and alveolar size were found until the end of classical alveolarization (dpp14). In LPS treated CD26+ rat pups the retardation was abolished already on dpp 10. Conclusion: In absence of CD26, LPS enhances the delay of morphological lung development. Morphological recovery was slower after the end of LPS exposure in CD26 deficient lungs.
CRIS-Team Scopus Importer:2019-12-03
Keywords: CD26/DPP4; LPS; Lung development; Rat; Stereology

Precise excision of HTLV-1 provirus with a designer-recombinase - Rojo-Romanos, Teresa; Karpinski, Janet; Millen, Sebastian; Beschorner, Niklas; Simon, Florian; Paszkowski-Rogacz, Maciej; Lansing, Felix; Schneider, Paul Martin; Sonntag, Jan; Hauber, Joachim; Thoma-Kreß, Andrea; Buchholz, Frank (Molecular Therapy, 2023)
The human T cell leukemia virus type 1 (HTLV-1) is a pathogenic retrovirus that persists as a provirus in the genome of infected cells and can lead to adult T cell leukemia (ATL). Worldwide, more than 10 million people are infected and approximately 5% of these individuals will develop ATL, a highly aggressive cancer that is currently incurable. In the last years, genome editing tools have emerged as promising antiviral agents. In this proof-of-concept study, we use substrate-linked directed evolution (SLiDE) to engineer Cre-derived site-specific recombinases to excise the HTLV-1 proviral genome from infected cells. We identified a conserved loxP-like sequence (loxHTLV) present in the long terminal repeats of the majority of virus isolates. After 181 cycles of SLiDE, we isolated a designer-recombinase (designated RecHTLV), which efficiently recombines the loxHTLV sequence in bacteria and human cells with high specificity. Expression of RecHTLV in human Jurkat T cells resulted in antiviral activity when challenged with an HTLV-1 infection. Moreover, expression of RecHTLV in chronically infected SP cells led to the excision of HTLV-1 proviral DNA. Our data suggest that recombinase-mediated excision of the HTLV-1 provirus represents a promising approach to reduce proviral load in HTLV-1-infected individuals, potentially preventing the development of HTLV-1-associated diseases.
CRIS-Team Scopus Importer:2023-04-28
Keywords: adult T cell leukemia; ATL; Cre-lox; gene therapy; genome engineering; HAM/TSP; HTLV-1; HTLV-1-associated myelopathy/tropical spastic paraparesis; molecular directed evolution; retrovirus; site-specific recombinases

Prenatally traumatized mice reveal hippocampal methylation and expression changes of the stress-related genes Crhr1 and Fkbp5 - Plank, Anne-Christine; Frey, Stefan; Basedow, Lukas Andreas; Solati, Jalal; Canneva, Fabio; von Hörsten, Stephan; Kratz, Oliver; Moll, Gunther; Golub, Yulia (Translational Psychiatry, 2021)
In our previous study, we found that prenatal trauma exposure leads to an anxiety phenotype in mouse pups, characterized by increased corticosterone levels and increased anxiety-like behavior. In order to understand the mechanisms by which aversive in utero experience leads to these long-lasting behavioral and neuroendocrine changes, we investigated stress reactivity of prenatally traumatized (PT) mice, as well as the expression and methylation levels of several key regulatory genes of the stress axis in the dorsal hippocampus (dHPC) of the PT embryo and adult mice. We detected increased corticotropin-releasing hormone receptor 1 (Crhr1) and decreased FK506 binding protein 5 (Fkbp5) mRNA levels in the left dHPC of adult PT mice. These alterations were accompanied by a decreased methylation status of the Crhr1 promoter and an increased methylation status of the Fkbp5 promoter, respectively. Interestingly, the changes in Fkbp5 and Crhr1 mRNA levels were not detected in the embryonic dHPC of PT mice. Together, our findings provide evidence that prenatal trauma has a long-term impact on stress axis function and anxiety phenotype associated with altered Crhr1 and Fkbp5 transcripts and promoter methylation.
CRIS-Team Scopus Importer:2021-04-09

Prevalence and patterns of HIV drug resistance in patients with suspected virological failure in North-Western Tanzania - Henerico, Shimba; Mikasi, Sello Given; Kalluvya, Samuel Elias; Brauner, Jan M.; Abdul, Seif; Lyimo, Eric; Desderius, Bernard; Korn, Klaus; van Zyl, Gert; Jacobs, Graeme Brendon; Preiser, Wolfgang; Kasang, Christa (Journal of Antimicrobial Chemotherapy, 2022)
BACKGROUND: More than 15 million people in sub-Saharan Africa receive ART. Treatment failure is common, but the role of HIV drug resistance in treatment failure is largely unknown because drug resistance testing is not routinely done. This study determined the prevalence and patterns of HIV drug resistance in patients with suspected virological failure. MATERIALS AND METHODS: A single high viral load of >1000 viral RNA copies/mL of plasma at any point during ART was considered as suspected virological failure. HIV-1 RNA was extracted from plasma samples of these patients using the QIAamp Viral RNA kit. The protease and part of the RT regions of the HIV pol gene were characterized. RESULTS: Viral load was determined in 317 patients; 64 (20.2%) had suspected virological failure. We successfully genotyped 56 samples; 48 (85.7%) had at least one major resistance-associated mutation (RAM). Common mutations in RT were M184V (75%), T215Y (41.1%), K103N (39.3%), M41L (32.1%), D67DN (30.3%), G190A (28.6%) and A98G (26.8%). No RAMs were detected in ART regimens based on a ritonavir-boosted PI. CONCLUSIONS: The Tanzanian national guidelines define 'virological failure' as two consecutive viral load measurement results, at 3 month intervals, above the WHO threshold (1000 copies/mL). Here, we show that a single viral load above the WHO threshold is associated with high rates of RAMs. This suggests that a single high viral load measurement could be used to predict virological failure and avoid delays in switching patients from first-line to higher genetic barrier second-line regimens.
CRIS-Team Scopus Importer:2022-02-11

Prognostic significance of altered miRNA expression in whole blood of OSCC patients - Ries, Jutta; Baran, Christoph; Wehrhan, Falk; Weber, Manuel; Neukam, Friedrich Wilhelm; Krautheim-Zenk, Andrea; Nkenke, Emeka (Oncology Reports, 2017)
Currently, there is a lack of blood markers for the detection of recurrent oral squamous cell carcinoma (OSCC). The present study aimed to investigate whether the aberrant expression of single microRNAs (miRNAs) in whole blood of patients could serve as a biomarker for persistent or recurrent OSCC. Whole blood of 2 groups of formerly treated OSCC patients was investigated by RT-qPCR for their circulating miRNA profiles. The R-OC group included patients with recurrence of OSCC (n=21) and the NR-OC group included patients without recurrence (n=21). Fold-changes and significance of the differences in miRNA expression levels between the groups were determined. A cut-off point (COP) for the discrimination between the R-OC and NR-OC groups was calculated and the significance between over/under expression of the miRNAs and the recurrence of malignancy was determined. Significant differences in the miRNA expression in whole blood of the R-OC and NR-OC groups were found. The levels of miR-3651 and miR-494 were significantly increased and the level of miR-186 was significantly decreased in whole blood of the R-OC patients (pmiR-3651=0.001, pmiR-494=0.003 and pmiR-186=0.001). By the determination of the COP, increased or decreased expression of the markers was significantly correlated to the recurrence of the disease. Altered expression of miR-494, miR-3651 and miR-186 appears to be associated with the recurrence of OSCC. The present study may form the basis for establishing a blood test as a minimally invasive method for the detection of the recurrence of OSCC.
EVALuna2:24434

Prognostic significance of macrophage polarization in early stage oral squamous cell carcinomas - Weber, Manuel; Iliopoulos, Christos; Moebius, Patrick; Buettner-Herold, Maike; Amann, Kerstin Ute; Ries, Jutta; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Oral Oncology, 2016)
Polarization of tumor infiltrating macrophages is associated with the prognosis of solid malignancies and correlates with the occurrence of lymph node metastases in oral squamous cell carcinomas (oscc). Early stage (T1/T2, N0) oscc are characterized by a good prognosis and can be cured by surgery. The postoperative regime usually contains no adjuvant radio-/chemotherapy. The current pilot study was conducted to elucidate whether macrophage polarization in tumor resection specimens and diagnostic biopsies of early stage oscc is associated with tumor outcome.Patients with T1/T2, N0, and R0>5mm oscc without adjuvant therapy and 3-year follow-up after tumor resection were retrospectively selected. Tissue microarrays (TMA) containing diagnostic biopsies (n=17) and tumor resection specimens (n=17) were processed for immunohistochemistry in this pilot study to detect CD68-, CD11c-, CD163- and MRC1-positive macrophages. Samples were digitized, and the expression of macrophage markers was quantitatively analyzed.High infiltration of M2 polarized macrophages correlated with poor tumor outcome in early stage (T1/T2, N0) oscc. This correlation was observed in tumor resection specimens, but was also observed in diagnostic biopsies. M2 macrophage polarization in biopsies - but not in tumor resection samples - correlated with high scores in tumor grading.Macrophage polarization in early stage oscc is a potential prognostic marker for tumor outcome. The correlation of M2 polarized macrophages with tumor outcome can already be detected in the initial biopsies. Furthermore, M2 polarization of macrophages in biopsies is associated with an increased dedifferentiation.
EVALuna2:24408

Prognostic significance of PD-L2 expression in patients with oral squamous cell carcinoma-A comparison to the PD-L1 expression profile - Weber, Manuel; Wehrhan, Falk; Baran, Christoph; Agaimy, Abbas; Büttner-Herold, Maike; Kesting, Marco Rainer; Ries, Jutta (Cancer Medicine, 2019)
BACKGROUND: Despite the observed association of increased PD-L1 expression in peripheral blood of oral squamous cell carcinoma (OSCC) patients with histomorphologic parameters, the role of the PD1 ligands-PD-L1 and PD-L2-is insufficiently understood. Aim of the study was to investigate whether the alterations of PD-L1 and PD-L2 expression in blood are associated with survival and could serve as immune monitoring parameter. Moreover, it should be analyzed if PD-L2 is differentially expressed in tissue and blood samples of OSCC patients compared to healthy controls and if there is an association of PD-L2 expression with histomorphologic and prognostic tumor parameters. METHODS: PD-L2 mRNA expression was analyzed in tumors and healthy oral mucosa specimens and in corresponding peripheral blood samples of 48 OSCC patients and 26 healthy controls using RT-qPCR. A cutoff point (COP) was determined and a chi-square test (χ2 test) was carried out. Survival analysis of PD-L2 and previously reported PD-L1 expression data was performed using Kaplan-Meier analysis (Log-rank test). RESULTS: PD-L2 expression in tissue samples was significantly (P < 0.001) higher in OSCC patients compared to healthy controls. A significant association of PD-L2 expression above the COP (positive) with malignancy was ascertained (P < 0.001). A significant (P = 0.01) association of previously reported PD-L1 expression rates in peripheral blood with survival could be shown. CONCLUSION: Peripheral blood PD-L1 expression might be a prognostic marker for OSCC patients and a possible parameter to monitor immune dysfunction in malign diseases. In the peripheral blood, PD-L1 might be more relevant for immune tolerance than PD-L2. Local PD-L2 expression in tissue samples might be useful as a diagnostic parameter for malignancy and could contribute to the immunosuppressive local microenvironment in OSCC.
EVALuna2:35498

Propagation of SARS-CoV-2 in a Closed Cell Culture Device: Potential GMP Compatible Production Platform for Live-Attenuated Vaccine Candidates under BSL-3 Conditions? - Klessing, Stephan; Peter, Antonia Sophia; Fraedrich, Kirsten; Wagner, Jannik; Kummer, Mirko; Deutschmann, Janina; Steininger, Philipp; Steibl, Hans Dieter; Überla, Klaus (Viruses, 2023)
Live-attenuated SARS-CoV-2 vaccines present themselves as a promising approach for the induction of broad mucosal immunity. However, for initial safety assessment in clinical trials, virus production requires conditions meeting Good Manufacturing Practice (GMP) standards while maintaining biosafety level 3 (BSL-3) requirements. Since facilities providing the necessary complex ventilation systems to meet both requirements are rare, we here describe a possibility to reproducibly propagate SARS-CoV-2 in the automated, closed cell culture device CliniMACS Prodigy® in a common BSL-3 laboratory. In this proof-of-concept study, we observed an approximately 300-fold amplification of SARS-CoV-2 under serum-free conditions with high lot-to-lot consistency in the infectious titers obtained. With the possibility to increase production capacity to up to 3000 doses per run, this study outlines a potential fast-track approach for the production of live-attenuated vaccine candidates based on highly pathogenic viruses under GMP-like conditions that may contribute to pandemic preparedness.
CRIS-Team Scopus Importer:2023-03-10
Keywords: CliniMACS Prodigy®; GMP; human challenge study; live-attenuated vaccines; SARS-CoV-2; virus propagation

Properties of Oligomeric Interaction of the Cytomegalovirus Core Nuclear Egress Complex (NEC) and Its Sensitivity to an NEC Inhibitory Small Molecule - Kicuntod, Jintawee; Alkhashrom, Sewar; Häge, Sigrun; Diewald, Benedikt; Müller, Regina; Hahn, Friedrich; Lischka, Peter; Sticht, Heinrich; Eichler, Jutta; Marschall, Manfred (Viruses, 2021)
Herpesviral nuclear egress is a regulated process shared by all family members, ensuring the efficient cytoplasmic release of viral capsids. In the case of human cytomegalovirus (HCMV), the core of the nuclear egress complex (NEC) consists of the pUL50-pUL53 heterodimer that builds hexameric lattices for capsid binding and multicomponent interaction, including NEC-associated host factors. A characteristic feature of NEC interaction is the N-terminal hook structure of pUL53 that binds to an alpha-helical groove of pUL50, thus termed as hook-into-groove interaction. This central regulatory element is essential for viral replication and shows structural-functional conservation, which has been postulated as a next-generation target of antiviral strategies. However, a solid validation of this concept has been missing. In the present study, we focused on the properties of oligomeric HCMV core NEC interaction and the antiviral activity of specifically targeted prototype inhibitors. Our data suggest the following: (i) transiently expressed, variably tagged versions of HCMV NEC proteins exert hook-into-groove complexes, putatively in oligomeric assemblies that are distinguishable from heterodimers, as shown by in vitro assembly and coimmunoprecipitation approaches; (ii) this postulated oligomeric binding pattern was further supported by the use of a pUL50::pUL53 fusion construct also showing a pronounced multi-interaction potency; (iii) using confocal imaging cellular NEC-associated proteins were found partly colocalized with the tagged core NECs; (iv) a small inhibitory molecule, recently identified by an in vitro binding inhibition assay, was likewise active in blocking pUL50-pUL53 oligomeric assembly and in exerting antiviral activity in HCMV-infected fibroblasts. In summary, the findings refine the previous concept of HCMV core NEC formation and nominate this drug-accessible complex as a validated antiviral drug target.
CRIS-Team WoS Importer:2021-04-09

Protection from cytomegalovirus viremia following glycoprotein B vaccination is not dependent on neutralizing antibodies - Baraniak, Ilona; Kropff, Barbara; Ambrose, Lyn; Mcintosh, Megan; Mclean, Gary R.; Pichon, Sylvie; Atkinson, Claire; Milne, Richard S. B.; Mach, Michael; Griffiths, Paul D.; Reeves, Matthew B. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Human cytomegalovirus (HCMV) is an important pathogen in transplant patients and in congenital infection. Previously, we demonstrated that vaccination with a recombinant viral glycoprotein B (gB)/MF59 adjuvant formulation before solid organ transplant reduced viral load parameters post transplant. Reduced posttransplant viremia was directly correlated with antibody titers against gB consistent with a humoral response against gB being important. Here we show that sera from the vaccinated seronegative patients displayed little evidence of a neutralizing antibody response against cell-free HCMV in vitro. Additionally, sera from seronegative vaccine recipients had minimal effect on the replication of a strain of HCMV engineered to be cell-associated in a viral spread assay. Furthermore, although natural infection can induce antibody-dependent cellular cytotoxicity (ADCC) responses, serological analysis of seronegative vaccinees again presented no evidence of a substantial ADCC-promoting antibody response being generated de novo. Finally, analyses for responses against major antigenic domains of gB following vaccination were variable, and their pattern was distinct compared with natural infection. Taken together, these data argue that the protective effect elicited by the gB vaccine is via a mechanism of action in seronegative vaccinees that cannot be explained by neutralization or the induction of ADCC. More generally, these data, which are derived from a human challenge model that demonstrated that the gB vaccine is protective, highlight the need for more sophisticated analyses of new HCMV vaccines over and above the quantification of an ability to induce potent neutralizing antibody responses in vitro.
EVALuna2:35274

Protective capacity of neutralizing and non-neutralizing antibodies against glycoprotein B of cytomegalovirus - Bootz, Anna; Karbach, Astrid; Spindler, Johannes; Kropff, Barbara; Reuter, Nina; Sticht, Heinrich; Winkler, Thomas; Britt, William J.; Mach, Michael (PLoS Pathogens, 2017)
Human cytomegalovirus (HCMV) is an important, ubiquitous pathogen that causes severe clinical disease in immunocompromised individuals, such as organ transplant recipients and infants infected in utero. Antiviral chemotherapy remains problematic due to toxicity of the available compounds and the emergence of viruses resistant to available antiviral therapies. Antiviral antibodies could represent a valuable alternative strategy to limit the clinical consequences of viral disease in patients. The envelope glycoprotein B (gB) of HCMV is a major antigen for the induction of virus neutralizing antibodies. However, the role of anti-gB antibodies in the course of the infection in-vivo remains unknown. We have used a murine CMV (MCMV) model to generate and study a number of anti-gB monoclonal antibodies (mAbs) with differing virus-neutralizing capacities. The mAbs were found to bind to similar antigenic structures on MCMV gB that are represented in HCMV gB. When mAbs were used in immunodeficient RAG-/- hosts to limit an ongoing infection we observed a reduction in viral load both with mAbs having potent neutralizing capacity in-vitro as well as mAbs classified as non-neutralizing. In a therapeutic setting, neutralizing mAbs showed a greater capacity to reduce the viral burden compared to non-neutralizing antibodies. Efficacy was correlated with sustained concentration of virus neutralizing mAbs in-vivo rather than their in-vitro neutralizing capacity. Combinations of neutralizing mAbs further augmented the antiviral effect and were found to be as potent in protection as polyvalent serum from immune animals. Prophylactic administration of mAbs before infection was also protective and both neutralizing and non-neutralizing mAbs were equally effective in preventing lethal infection of immunodeficient mice. In summary, our data argue that therapeutic application of potently neutralizing mAbs against gB represent a strategy to modify the outcome of CMV infection in immunodeficient hosts. When present before infection, both neutralizing and non-neutralizing anti-gB exhibited protective capacity.
EVALuna2:33722

Protective mucosal immunity against SARS-CoV-2 after heterologous systemic prime-mucosal boost immunization - Lapuente, Dennis; Fuchs, Jana; Willar, Jonas; Vieira Antao, Ana Isabel; Eberlein, Valentina; Uhlig, Nadja; Issmail, Leila; Schmidt, Anna; Oltmanns, Friederike; Peter, Antonia Sophia; Müller-Schmucker, Sandra; Irrgang, Pascal; et al. (Nature Communications, 2021)
Several effective SARS-CoV-2 vaccines are currently in use, but effective boosters are needed to maintain or increase immunity due to waning responses and the emergence of novel variants. Here we report that intranasal vaccinations with adenovirus 5 and 19a vectored vaccines following a systemic plasmid DNA or mRNA priming result in systemic and mucosal immunity in mice. In contrast to two intramuscular applications of an mRNA vaccine, intranasal boosts with adenoviral vectors induce high levels of mucosal IgA and lung-resident memory T cells (TRM); mucosal neutralization of virus variants of concern is also enhanced. The mRNA prime provokes a comprehensive T cell response consisting of circulating and lung TRM after the boost, while the plasmid DNA prime induces mostly mucosal T cells. Concomitantly, the intranasal boost strategies lead to complete protection against a SARS-CoV-2 infection in mice. Our data thus suggest that mucosal booster immunizations after mRNA priming is a promising approach to establish mucosal immunity in addition to systemic responses.
CRIS-Team Scopus Importer:2021-12-10

Protective mucosal immunity against SARS-CoV-2 after heterologous systemic RNA-mucosal adenoviral vector immunization - Lapuente, Dennis; Fuchs, Julian; Willar, J.; Antao, A.; Eberlein, V.; Uhlig, N.; Issmail, L.; Schmidt, Anna; Oltmanns, Friederike; Peter, Anne; Müller-Schmucker, Sandra; Irrgang, P.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Protein biomarker discovery using human blood plasma microparticles - Taleb, Raghda Saad Zaghloul; Moez, Pacint; Younan, Doreen; Eisenacher, Martin; Tenbusch, Matthias; Sitek, Barbara; Bracht, Thilo (Proteomics for Biomarker Discovery, 2019)
Cells shed into the extracellular space a population of membranous vesicles of plasma membrane origin called microparticles (MP). Given the fact that MP are abundantly present in body fluids including plasma, rich in cell-type or disease-specific proteins and formed in conditions of stress and injury, they have been extensively investigated as biomarkers in various diseases. With the advancement in the mass spectrometry-based proteome analysis, the knowledge of the protein composition of plasma MP (PMP) has been intensively expanded, which aids the discovery of novel diagnostic target proteins. However, the lack of standardized and accurate protocols for PMP isolation limits the implementation of PMP as biomarkers in clinical settings. Here, we describe in detail a robust protocol for PMP isolation from human blood plasma via ultracentrifugation followed by label-free quantitative proteome analysis of PMP.
CRIS-Team Scopus Importer:2019-08-09
Keywords: Blood-based biomarker; Label-free proteome quantification; Plasma microparticle proteome; Plasma microparticles; Ultracentrifugation

Protein kinases responsible for the phosphorylation of the nuclear egress core complex of human cytomegalovirus - Sonntag, Eric; Milbradt, Jens; Svrlanska, Adriana; Strojan, Hanife; Haege, Sigrun; Kraut, Alexandra; Hesse, Anne-Marie; Amin, Bushra; Sonnewald, Uwe; Coute, Yohann; Marschall, Manfred (Journal of General Virology, 2017)
Nuclear egress of herpesvirus capsids is mediated by a multi-component nuclear egress complex (NEC) assembled by a heterodimer of two essential viral core egress proteins. In the case of human cytomegalovirus (HCMV), this core NEC is defined by the interaction between the membrane-anchored pUL50 and its nuclear cofactor, pUL53. NEC protein phosphorylation is considered to be an important regulatory step, so this study focused on the respective role of viral and cellular protein kinases. Multiply phosphorylated pUL50 varieties were detected by Western blot and Phos-tag analyses as resulting from both viral and cellular kinase activities. In vitro kinase analyses demonstrated that pUL50 is a substrate of both PKC alpha and CDK1, while pUL53 can also be moderately phosphorylated by CDK1. The use of kinase inhibitors further illustrated the importance of distinct kinases for core NEC phosphorylation. Importantly, mass spectrometry-based proteomic analyses identified five major and nine minor sites of pUL50 phosphorylation. The functional relevance of core NEC phosphorylation was confirmed by various experimental settings, including kinase knock-down/knock-out and confocal imaging, in which it was found that (i) HCMV core NEC proteins are not phosphorylated solely by viral pUL97, but also by cellular kinases; (ii) both PKC and CDK1 phosphorylation are detectable for pUL50; (iii) no impact of PKC phosphorylation on NEC functionality has been identified so far; (iv) nonetheless, CDK1-specific phosphorylation appears to be required for functional core NEC interaction. In summary, our findings provide the first evidence that the HCMV core NEC is phosphorylated by cellular kinases, and that the complex pattern of NEC phosphorylation has functional relevance.
Keywords: human cytomegalovirus; nuclear egress; core NEC; protein-protein interaction; cellular protein kinases; phosphorylation

Proteolysis of mature HIV-1 p6 Gag protein by the insulin-degrading enzyme (IDE) regulates virus replication in an Env-dependent manner - Hahn, Friedrich; Schmalen, Adrian; Setz, Christian; Friedrich, Melanie; Schlößer, Stefan; Kölle, Julia; Sprenger, Robert; Rauch, Pia; Fraedrichl, Kirsten; Reif, Tatjana; Karius-Fischer, Julia; Balasubramanyam, Ashok; et al. (PLoS ONE, 2017)
There is a significantly higher risk for type II diabetes in HIV-1 carriers, albeit the molecular mechanism for this HIV-related pathology remains enigmatic. The 52 amino acid HIV-1 p6 Gag protein is synthesized as the C-terminal part of the Gag polyprotein Pr55. In this context, p6 promotes virus release by its two late (L-) domains, and facilitates the incorporation of the viral accessory protein Vpr. However, the function of p6 in its mature form, after proteolytic release from Gag, has not been investigated yet. We found that the mature p6 represents the first known viral substrate of the ubiquitously expressed cytosolic metalloendopeptidase insulin-degrading enzyme (IDE). IDE is sufficient and required for degradation of p6, and p6 is approximately 100-fold more efficiently degraded by IDE than its eponymous substrate insulin. This observation appears to be specific for HIV-1, as p6 proteins from HIV-2 and simian immunodeficiency virus, as well as the 51 amino acid p9 from equine infectious anaemia virus were insensitive to IDE degradation. The amount of virus-associated p6, as well as the efficiency of release and maturation of progeny viruses does not depend on the presence of IDE in the host cells, as it was shown by CRISPR/Cas9 edited IDE KO cells. However, HIV-1 mutants harboring IDE-insensitive p6 variants exhibit reduced virus replication capacity, a phenomenon that seems to depend on the presence of an X4-tropic Env. Furthermore, competing for IDE by exogenous insulin or inhibiting IDE by the highly specific inhibitor 6bK, also reduced virus replication. This effect could be specifically attributed to IDE since replication of HIV-1 variants coding for an IDE-insensitive p6 were inert towards IDE-inhibition. Our cumulative data support a model in which removal of p6 during viral entry is important for virus replication, at least in the case of X4 tropic HIV-1.
EVALuna2:33767

Proteolytic degradation of neuropeptide Y (NPY) from head to toe: Identification of novel NPY-cleaving peptidases and potential drug interactions in CNS and Periphery - Wagner, Leona; Wolf, Raik; Zeitschel, Ulrike; Rossner, Steffen; Petersen, Asa; Leavitt, Blair R.; Kaestner, Florian; Rothermundt, Matthias; Gaertner, Ulf-Torsten; Guendel, Daniel; Schlenzig, Dagmar; Frerker, Nadine; et al. (Journal of Neurochemistry, 2015)
The bioactivity of neuropeptide Y (NPY) is either N-terminally modulated with respect to receptor selectivity by dipeptidyl peptidase 4 (DP4)-like enzymes or proteolytic degraded by neprilysin or meprins, thereby abrogating signal transduction. However, neither the subcellular nor the compartmental differentiation of these regulatory mechanisms is fully understood. Using mass spectrometry, selective inhibitors and histochemistry, studies across various cell types, body fluids, and tissues revealed that most frequently DP4-like enzymes, aminopeptidases P, secreted meprin-A (Mep-A), and cathepsin D (CTSD) rapidly hydrolyze NPY, depending on the cell type and tissue under study. Novel degradation of NPY by cathepsins B, D, L, G, S, and tissue kallikrein could also be identified. The expression of DP4, CTSD, and Mep-A at the median eminence indicates that the bioactivity of NPY is regulated by peptidases at the interphase between the periphery and the CNS. Detailed ex vivo studies on human sera and CSF samples recognized CTSD as the major NPY-cleaving enzyme in the CSF, whereas an additional C-terminal truncation by angiotensin-converting enzyme could be detected in serum. The latter finding hints to potential drug interaction between antidiabetic DP4 inhibitors and anti-hypertensive angiotensin-converting enzyme inhibitors, while it ablates suspected hypertensive side effects of only antidiabetic DP4-inhibitors application. The bioactivity of neuropeptide Y (NPY) is either N-terminally modulated with respect to receptor selectivity by dipeptidyl peptidase 4 (DP4)-like enzymes or proteolytic degraded by neprilysin or meprins, thereby abrogating signal transduction. However, neither the subcellular nor the compartmental differentiation of these regulatory mechanisms is fully understood. Using mass spectrometry, selective inhibitors and histochemistry, studies across various cell types, body fluids, and tissues revealed that most frequently DP4-like enzymes, aminopeptidases P, secreted meprin-A (Mep-A), and cathepsin D (CTSD) rapidly hydrolyze NPY, depending on the cell type and tissue under study. Novel degradation of NPY by cathepsins B, D, L, G, S, and tissue kallikrein could also be identified. The expression of DP4, CTSD, and Mep-A at the median eminence indicates that the bioactivity of NPY is regulated by peptidases at the interphase between the periphery and the CNS. Detailed ex vivo studies on human sera and CSF samples recognized CTSD as the major NPY-cleaving enzyme in the CSF, whereas an additional C-terminal truncation by angiotensin-converting enzyme could be detected in serum. The latter finding hints to potential drug interaction between antidiabetic DP4 inhibitors and anti-hypertensive angiotensin-converting enzyme inhibitors, while it ablates suspected hypertensive side effects of only antidiabetic DP4-inhibitors application.
EVALuna2:24982

Proteolytic α‐synuclein cleavage in health and disease - Bluhm, Alexandra; Schrempel, Sarah; von Hörsten, Stephan; Schulze, Anja; Roßner, Steffen (International Journal of Molecular Sciences, 2021)
In Parkinson’s disease, aggregates of α‐synuclein within Lewy bodies and Lewy neurites represent neuropathological hallmarks. However, the cellular and molecular mechanisms triggering oligomeric and fibrillary α‐synuclein aggregation are not fully understood. Recent evidence indicates that oxidative stress induced by metal ions and post‐translational modifications such as phosphorylation, ubiquitination, nitration, glycation, and SUMOylation affect α‐synuclein conformation along with its aggregation propensity and neurotoxic profiles. In addition, proteolytic cleavage of α‐synuclein by specific proteases results in the formation of a broad spectrum of fragments with consecutively altered and not fully understood physiological and/or pathological properties. In the present review, we summarize the current knowledge on proteolytical α‐ synuclein cleavage by neurosin, calpain‐1, cathepsin D, and matrix metalloproteinase‐3 in health and disease. We also shed light on the contribution of the same enzymes to proteolytical processing of pathogenic proteins in Alzheimer’s disease and report potential cross‐disease mechanisms of pathogenic protein aggregation.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Animal models; Dementia with Lewy bodies; Parkinson’s disease; Post‐translational modification; Proteolysis; Substantia nigra; α‐synuclein

Proteomic analysis of the multimeric nuclear egress complex of human cytomegalovirus - Milbradt, Jens; Kraut, Alexandra; Hutterer, Corina; Sonntag, Ellen; Schmeiser, Cathrin; Ferro, Myriam; Wagner, Sabrina; Lenac, Tihana; Claus, Claudia; Pinkert, Sandra; Hamilton, Stuart T.; Rawlinson, William D.; et al. (Molecular & Cellular Proteomics, 2014)
Herpesviral capsids are assembled in the host cell nucleus before being translocated into the cytoplasm for further maturation. The crossing of the nuclear envelope represents a major event that requires the formation of the nuclear egress complex (NEC). Previous studies demonstrated that human cytomegalovirus (HCMV) proteins pUL50 and pUL53, as well as their homologs in all members of Herpesviridae, interact with each other at the nuclear envelope and form the heterodimeric core of the NEC. In order to characterize further the viral and cellular protein content of the multimeric NEC, the native complex was isolated from HCMV-infected human primary fibroblasts at various time points and analyzed using quantitative proteomics. Previously postulated components of the HCMV-specific NEC, as well as novel potential NEC-associated proteins such as emerin, were identified. In this regard, interaction and colocalization between emerin and pUL50 were confirmed by coimmunoprecipitation and confocal microscopy analyses, respectively. A functional validation of viral and cellular NEC constituents was achieved through siRNA-mediated knockdown experiments. The important role of emerin in NEC functionality was demonstrated by a reduction of viral replication when emerin expression was down-regulated. Moreover, under such conditions, reduced production of viral proteins and deregulation of viral late cytoplasmic maturation were observed. Combined, these data prove the functional importance of emerin as an NEC component, associated with pUL50, pUL53, pUL97, p32/gC1qR, and further regulatory proteins. Summarized, our findings provide the first proteomics-based characterization and functional validation of the HCMV-specific multimeric NEC.
EVALuna2:8226

Proteomic interaction patterns between human cyclins, the cyclin-dependent kinase ortholog pUL97 and additional cytomegalovirus proteins - Steingruber, Mirjam; Kraut, Alexandra; Socher, Eileen; Sticht, Heinrich; Reichel, Anna; Stamminger, Thomas; Amin, Bushra; Coute, Yohann; Hutterer, Corina; Marschall, Manfred (Viruses, 2016)
The human cytomegalovirus (HCMV)-encoded cyclin-dependent kinase (CDK) ortholog pUL97 associates with human cyclin B1 and other types of cyclins. Here, the question was addressed whether cyclin interaction of pUL97 and additional viral proteins is detectable by mass spectrometry-based approaches. Proteomic data were validated by coimmunoprecipitation (CoIP), Western blot, in vitro kinase and bioinformatic analyses. Our findings suggest that: (i) pUL97 shows differential affinities to human cyclins; (ii) pUL97 inhibitor maribavir (MBV) disrupts the interaction with cyclin B1, but not with other cyclin types; (iii) cyclin H is identified as a new high-affinity interactor of pUL97 in HCMV-infected cells; (iv) even more viral phosphoproteins, including all known substrates of pUL97, are detectable in the cyclin-associated complexes; and (v) a first functional validation of pUL97-cyclin B1 interaction, analyzed by in vitro kinase assay, points to a cyclin-mediated modulation of pUL97 substrate preference. In addition, our bioinformatic analyses suggest individual, cyclin-specific binding interfaces for pUL97-cyclin interaction, which could explain the different strengths of interactions and the selective inhibitory effect of MBV on pUL97-cyclin B1 interaction. Combined, the detection of cyclin-associated proteins in HCMV-infected cells suggests a complex pattern of substrate phosphorylation and a role of cyclins in the fine-modulation of pUL97 activities.
Keywords: CDK ortholog pUL97; Cyclin-associated protein complexes; Human cyclins; Human cytomegalovirus; Molecular modeling; Proteomic analysis

pUL69 of Human Cytomegalovirus Recruits the Cellular Protein Arginine Methyltransferase 6 via a Domain That Is Crucial for mRNA Export and Efficient Viral Replication - Thomas, Marco; Sonntag, Ellen; Müller, Regina; Schmidt, Stefanie; Zielke, Barbara; Fossen, Torgils; Stamminger, Thomas (Journal of Virology, 2015)
The regulatory protein pUL69 of human cytomegalovirus acts as a viral mRNA export factor, facilitating the cytoplasmic accumulation of unspliced RNA via interaction with the cellular mRNA export factor UAP56. Here we provide evidence for a posttranslational modification of pUL69 via arginine methylation within the functionally important N terminus. First, we demonstrated a specific immunoprecipitation of full-length pUL69 as well as pUL69aa1-146 by a mono/dimethylarginine-specific antibody. Second, we observed a specific electrophoretic mobility shift upon overexpression of the catalytically active protein arginine methyltransferase 6 (PRMT6). Third, a direct interaction of pUL69 and PRMT6 was confirmed by yeast two-hybrid and coimmunoprecipitation analyses. We mapped the PRMT6 interaction motif to the pUL69 N terminus and identified critical amino acids within the arginine-rich R1 box of pUL69 that were crucial for PRMT6 and/or UAP56 recruitment. In order to test the impact of putative methylation substrates on the functions of pUL69, we constructed various pUL69 derivatives harboring arginine-to-alanine substitutions and tested them for RNA export activity. Thus, we were able to discriminate between arginines within the R1 box of pUL69 that were crucial for UAP56/PRMT6-interaction and/or mRNA export activity. Remarkably, nuclear magnetic resonance (NMR) analyses revealed the same ?-helical structures for pUL69 sequences encoding either the wild type R1/R2 boxes or a UAP56/PRMT6 binding-deficient derivative, thereby excluding the possibility that R/A amino acid substitutions within R1 affected the secondary structure of pUL69. We therefore conclude that the pUL69 N terminus is methylated by PRMT6 and that this critically affects the functions of pUL69 for efficient mRNA export and replication of human cytomegalovirus.The UL69 protein of human cytomegalovirus is a multifunctional regulatory protein that acts as a viral RNA export factor with a critical role for efficient replication. Here, we demonstrate that pUL69 is posttranslationally modified via arginine methylation and that the protein methyltransferase PRMT6 mediates this modification. Furthermore, arginine residues with a crucial function for RNA export and for binding of the cellular RNA export factor UAP56 as well as PRMT6 were mapped within the arginine-rich R1 motif of pUL69. Importantly, we demonstrated that mutation of those arginines did not alter the secondary structure of R1, suggesting that they may serve as critical methylation substrates. In summary, our study reveals a novel posttranslational modification of pUL69 which has a significant impact on the function of this important viral regulatory protein. Since PRMTs appear to be amenable to selective inhibition by small molecules, this may constitute a novel target for antiviral therapy.
EVALuna2:8296

Quantitating the Transfer of the HTLV-1 p8 Protein Between T-Cells by Flow Cytometry - Donhauser, Norbert; Heym, Stefanie; Thoma-Kreß, Andrea (Frontiers in Microbiology, 2018)
The Human T-cell leukemia virus type 1 (HTLV-1)-encoded accessory protein p8 is cleaved from the precursor protein p12 encoded by the HTLV-1 open reading frame I. Both p12 and p8 are thought to contribute to efficient viral persistence. Mechanistically, p8 induces T-cell conjugates and cellular conduits. The latter are considered to facilitate transfer of p8 to target cells and virus transmission. Transfer of p8 between p8-expressing T-cells and recipient cells has been analyzed by immunofluorescence and live imaging. However, automatic quantitation of p8-transfer between cells has not been studied yet. Here we developed a novel method allowing time saving quantitation of p8 transfer between cells by flow cytometry. After establishing a protocol for the detection of intracellular p8 by flow cytometry and validation of p8 protein expression by western blot and immunofluorescence, we set up a co-culture assay between p8-expressing donor Jurkat T-cells and recipient Jurkat T-cells that had been prestained with a well-retained live cell dye. Upon quantitating the amount of p8 positive recipient cells with regard to the percentage of p8 expressing donor cells, time course experiments confirmed that p8 is rapidly transferred between Jurkat T-cells. We found that p8 enters approximately 5% of recipient T-cells immediately upon co-culture for 5 min. Prolonged co-culture for up to 24 h revealed an increase of relative p8 transfer to approximately 23% of the recipient cells. Immunofluorescence analysis of co-culture experiments and manual quantitation of p8 expression in fluorescence images confirmed the validity of the flow cytometry based assay. Application of the new assay revealed that manipulation of actin polymerization significantly decreased p8 transfer between Jurkat T-cells suggesting an important role of actin dynamics contributing to p8 transfer. Further, transfer of p8 to co-cultured T-cells varies between different donor cell types since p8 transfer could hardly been detected in co-cultures of 293T donor cells with Jurkat acceptor cells. In summary, our novel assay allows automatic and rapid quantitation of p8 transfer to target cells and might thus contribute to a better understanding of cellular processes and dynamics regulating p8 transfer and HTLV-1 transmission.
EVALuna2:35284

Quantitative and qualitative comparison of 4D-DSA with 3D-DSA using computational fluid dynamics simulations in cerebral aneurysms - Lang, Sabine; Birkhold, A. I.; Schmidt, Manuel; Endres, J.; Strother, C.; Dörfler, Arnd; Lücking, Hannes; Hölter, Philip (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: 4D-DSA allows time-resolved 3D imaging of the cerebral vasculature. The aim of our study was to evaluate this method in comparison with the current criterion standard 3D-DSA by qualitative and quantitative means using computational fluid dynamics. MATERIALS AND METHODS: 3D- and 4D-DSA datasets were acquired in patients with cerebral aneurysms. Computational fluid dynamics analysis was performed for all datasets. Using computational fluid dynamics, we compared 4D-DSA with 3D-DSA in terms of both aneurysmal geometry (quantitative: Maximum diameter, ostium size [OZ1/2], volume) and hemodynamic parameters (qualitative: Flow stability, flow complexity, inflow concentration; quantitative: Average/maximum wall shear stress, impingement zone, low-stress zone, intra-aneurysmal pressure, and flow velocity). Qualitative parameters were descriptively analyzed. Correlation coefficients (r, P value) were calculated for quantitative parameters. RESULTS: 3D- and 4D-DSA datasets of 10 cerebral aneurysms in 10 patients were postprocessed. Evaluation of aneurysmal geometry with 4D-DSA (rmaximum diameter = 0.98, Pmaximum diameter <.001; rOZ1/OZ2 = 0.98/0.86, POZ1/OZ2 =.001/.002; rvolume = 0.98, Pvolume <.001) correlated highly with 3D-DSA. Evaluation of qualitative hemodynamic parameters (flow stability, flow complexity, inflow concentration) did show complete accordance, and evaluation of quantitative hemodynamic parameters (raverage/maximum wall shear stress diastole=0.92/0.88, Paverage/maximum wall shear stress diastole <.001/.001; raverage/maximum wall shear stress systole = 0.94/0.93, Paverage/maximum wall shear stress systole < .001/.001; rimpingement zone=0.96, Pimpingement zone <.001; rlow-stress zone=1.00, Plow-stress zone <.01; rpressure diastole=0.84,Ppressure diastole< .002; rpressure systole=0.9, Ppressure systole <.001; rflow velocity diastole=0.95, Pflow velocity diastole <.001; rflow velocity systole=0.93,Pflow velocity systole <.001) did show nearly complete accordance between 4D- and 3D-DSA. CONCLUSIONS: Despite a different injection protocol, 4D-DSA is a reliable basis for computational fluid dynamics analysis of the intracranial vasculature and provides equivalent visualization of aneurysm geometry compared with 3D-DSA.
CRIS-Team Scopus Importer:2019-09-17

Quantitative proteome analysis of plasma microparticles for the characterization of HCV-induced hepatic cirrhosis and hepatocellular carcinoma - Taleb, Raghda Saad Zaghloul; Moez, Pacint; Younan, Doreen; Eisenacher, Martin; Tenbusch, Matthias; Sitek, Barbara; Bracht, Thilo (Proteomics Clinical Applications, 2017)
PURPOSE: Hepatocellular carcinoma (HCC) is the most common primary malignant liver tumor and a leading cause of cancer-related deaths worldwide. Cirrhosis induced by hepatitis-C virus (HCV) infection is the most critical risk factor for HCC. However, the mechanism of HCV-induced carcinogenesis is not fully understood. Plasma microparticles (PMP) contribute to numerous physiological and pathological processes and contain proteins whose composition correlates to the respective pathophysiological conditions. EXPERIMENTAL DESIGN: We analyzed PMP from 22 HCV-induced cirrhosis patients, 16 HCV-positive HCC patients with underlying cirrhosis and 18 healthy controls. PMP were isolated using ultracentrifugation and analyzed via label-free LC-MS/MS. RESULTS: We identified 840 protein groups and quantified 507 proteins. 159 proteins were found differentially abundant between the three experimental groups. PMP in both disease entities displayed remarkable differences in the proteome composition compared to healthy controls. Conversely, the proteome difference between both diseases was minimal. GO analysis revealed that PMP isolated from both diseases were significantly enriched in proteins involved in complement activation, while endopeptidase activity was downregulated exclusively in HCC patients. CONCLUSION: This study reports for the first time a quantitative proteome analysis for PMP from patients with HCV-induced cirrhosis and HCC. Data are available via ProteomeXchange with identifier PXD005777.
EVALuna2:33747

Quinine Inhibits Infection of Human Cell Lines with SARS-CoV-2 - Große, Maximilian; Ruetalo, Natalia; Layer, Mirjam; Hu, Dan; Businger, Ramona; Rheber, Sascha; Setz, Christian; Rauch, Pia; Auth, Janina; Froeba, Maria; Brysch, Ekkehard; Schindler, Michael; et al. (Viruses, 2021)
While vaccination campaigns are ongoing worldwide, there is still a tremendous medical need for efficient antivirals against SARS-CoV-2 infection. Among several drug candidates, chloroquine (CQN) and hydroxychloroquine (H-CQN) were tested intensively, and any contentious therapeutic effect of both has been discussed controversially in the light of severe side effects and missing efficacy. Originally, H-CQN descended from the natural substance quinine, a medicinal product used since the Middle Ages, which actually is regulatory approved for various indications. We hypothesized that quinine also exerts anti-SARS-CoV-2 activity. In Vero cells, quinine inhibited SARS-CoV-2 infection more effectively than CQN, and H-CQN and was less toxic. In human Caco-2 colon epithelial cells as well as the lung cell line A549 stably expressing ACE2 and TMPRSS2, quinine also showed antiviral activity. In consistence with Vero cells, quinine was less toxic in A549 as compared to CQN and H-CQN. Finally, we confirmed our findings in Calu-3 lung cells, expressing ACE2 and TMPRSS2 endogenously. In Calu-3, infections with high titers of SARS-CoV-2 were completely blocked by quinine, CQN, and H-CQN in concentrations above 50 mu M. The estimated IC(50)s were similar to 25 mu M in Calu-3, while overall, the inhibitors exhibit IC50 values between similar to 3.7 to similar to 50 mu M, dependent on the cell line and multiplicity of infection (MOI). Conclusively, our data indicate that quinine could have the potential of a treatment option for SARS-CoV-2, as the toxicological and pharmacological profile seems more favorable when compared to its progeny drugs H-CQN or CQN.
CRIS-Team WoS Importer:2021-05-28

Radiation dose in cerebral angiography and flat detector CT applications in neuroradiology - Struffert, Tobias; Lang, Sabine; Scholz, R.; Hauer, M.; Dörfler, Arnd (Radiologe, 2015)
Flat detectors (FD) have completely replaced image intensifiers in angiography. Due to this development not only the image quality of 2D digital subtraction angiography series (2-D-DSA) could be improved but also the acquisition of computed tomography (CT)-like cross-sectional images (FD-CT) within the angio suite became feasible. These techniques are now being used in daily clinical routine. Only little information about effective doses of these applications to patients has been published in the literature. We describe the effective patient dose of current applications in the field of angiography and demonstrate strategies to minimize the dose to the patient. In addition, we compare FD-CT applications to standard multislice CT applications.
EVALuna2:22998

Rapid response flow cytometric assay for the detection of antibody responses to SARS-CoV-2 - Lapuente, Dennis; Maier, Clara; Irrgang, Pascal; Hübner, Julian; Peter, Antonia Sophia; Hoffmann, Markus; Enßer, Armin; Ziegler, Katharina; Winkler, Thomas; Birkholz, Torsten; Kremer, Andreas; Steininger, Philipp; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
SARS-CoV-2 has emerged as a previously unknown zoonotic coronavirus that spread worldwide causing a serious pandemic. While reliable nucleic acid–based diagnostic assays were rapidly available, only a limited number of validated serological assays were available in the early phase of the pandemic. Here, we evaluated a novel flow cytometric approach to assess spike-specific antibody responses.HEK 293T cells expressing SARS-CoV-2 spike protein in its natural confirmation on the surface were used to detect specific IgG and IgM antibody responses in patient sera by flow cytometry. A soluble angiotensin-converting-enzyme 2 (ACE-2) variant was developed as external standard to quantify spike-specific antibody responses on different assay platforms. Analyses of 201 pre-COVID-19 sera proved a high assay specificity in comparison to commercially available CLIA and ELISA systems, while also revealing the highest sensitivity in specimens from PCR-confirmed SARS-CoV-2-infected patients. The external standard allowed robust quantification of antibody responses among different assay platforms. In conclusion, our newly established flow cytometric assay allows sensitive and quantitative detection of SARS-CoV-2-specific antibodies, which can be easily adopted in different laboratories and does not rely on external supply of assay kits. The flow cytometric assay also provides a blueprint for rapid development of serological tests to other emerging viral infections
CRIS-Team Scopus Importer:2020-10-30
Keywords: Antibodies; Coronavirus; Flow cytometry; SARS-CoV-2; Serology

Reactivation of HCMV during RT of the brain results in critical illness and early mortality - Frey, Benjamin; Goerig, Nicole; Becker, Ina; Donaubauer, Anna-Jasmina; Korn, Klaus; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Putz, Florian; Semrau, Sabine; et al. (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Reactogenicity after heterologous and homologous COVID-19 prime-boost vaccination regimens: descriptive interim results of a comparative observational cohort study - Warkentin, Lisette; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Gall, Christine; Sebastiao, Maria; Hueber, Susann (BMC Infectious Diseases, 2022)
Background Due to safety signals after vaccination with COVID-19 vector vaccines, several states recommended to complete the primary immunization series in individuals having received one dose of ChAdOx1 (AstraZeneca) with an mRNA vaccine. However, data on safety and reactogenicity of this heterologous regimen are still scarce. The aim of this study was therefore to compare the reactogenicity and the frequency of medical consultations after boost vaccination in a heterologous regimen with ChAdOx1 and mRNA-vaccines (BNT162b2, BioNTech/Pfizer or mRNA-1273, Moderna) to homologous regimens with ChAdOx1 or mRNA-vaccines, respectively. Methods In an observational cohort study reactogenicity and safety were assessed 14-19 days (short-term) and 40 to 56 days (long-term) after the boost vaccination using web-based surveys. In the short-term survey solicited and unsolicited reactions were assessed, while the long-term survey focussed on health problems leading to medical consultation after the vaccination, including those that were not suspected to be vaccine-related. Results In total, 9146 participants completed at least one of the surveys (ChAdOx1/ChAdOx1: n = 552, ChAdOx1/mRNA: n = 2382, mRNA/mRNA: n = 6212). In the short-term survey, 86% with ChAdOx1/mRNA regimen reported at least one reaction, in the ChAdOx1/ChAdOx1 and mRNA/mRNA cohorts 58% and 76%, respectively (age and sex adjusted p < 0.0001). In the long-term survey, comparable proportions of individuals reported medical consultation (ChAdOx1/ChAdOx1 vs. ChAdOx1/mRNA vs. mRNA/mRNA: 15% vs. 18% vs. 16%, age and sex adjusted p = 0.398). Female gender was associated with a higher reactogenicity and more medical consultations. Younger age was associated with a higher reactogenicity, whereas elderly people reported more medical consultations. Conclusion Although the short-term reactogenicity was higher with the heterologous regimen than with the homologous regimens, other factors such as higher efficacy and limited resources during the pandemic may prevail in recommending specific regimens.
CRIS-Team WoS Importer:2022-06-17

Reactogenicity and safety of COVID-19 primary immunisation and booster vaccination regimens: a comparative observational cohort study - Warkentin, Lisette; Werner, Felix; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Sebastiao, Maria; Hueber, Susann (BMC Medicine, 2023)
Background: Since the beginning of the COVID-19 vaccination campaigns, recommendations regarding the vaccination have been very dynamic. Although the safety and efficacy of different vaccines have been analysed, data were scarce for vaccine regimens combining different vaccines. We therefore aimed to evaluate and compare the perceived reactogenicity and need for medical consultation after the most frequently applied homologous and heterologous COVID-19 vaccination regimens. Methods: In an observational cohort study, reactogenicity and safety were assessed within a maximum follow-up time of 124 days using web-based surveys. Reactogenicity was assessed for different vaccination regimens 2 weeks after a vaccination (short-term survey). The following surveys, long-term and follow-up surveys, focused on the utilisation of medical services, including those that were not suspected to be vaccine-related. Results: Data of 17,269 participants were analysed. The least local reactions were seen after a ChAdOx1 − ChAdOx1 regimen (32.6%, 95% CI [28.2, 37.2]) and the most after the first dose with mRNA-1273 (73.9%, 95% CI [70.5, 77.2]). Systemic reactions were least frequent in participants with a BNT162b2 booster after a homologous primary immunisation with ChAdOx1 (42.9%, 95% CI [32.1, 54.1]) and most frequent after a ChAdOx1 − mRNA-1273 (85.5%, 95% CI [82.9, 87.8]) and mRNA-1273/mRNA-1273 regimen (85.1%, 95% CI [83.2, 87.0]). In the short-term survey, the most common consequences were medication intake and sick leave (after local reactions 0% to 9.9%; after systemic reactions 4.5% to 37.9%). In the long-term and follow-up surveys, between 8.2 and 30.9% of participants reported consulting a doctor and between 0% and 5.4% seeking hospital care. The regression analyses 124 days after the first and after the third dose showed that the odds for reporting medical consultation were comparable between the vaccination regimens. Conclusions: Our analysis revealed differences in reactogenicity between the COVID-19 vaccines and vaccination regimens in Germany. The lowest reactogenicity as reported by participants was seen with BNT162b2, especially in homologous vaccination regimens. However, in all vaccination regimens reactogenicity rarely led to medical consultations. Small differences in seeking any medical consultation after 6 weeks diminished during the follow-up period. In the end, none of the vaccination regimens was associated with a higher risk for medical consultation. Trial registration: DRKS DRKS00025881 (https://drks.de/search/de/trial/DRKS00025373 ). Registered on 14 October 2021. DRKS DRKS00025373 (https://drks.de/search/de/trial/DRKS00025881 ). Registered on 21 May 2021. Registered retrospectively.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Adverse drug reaction; COVID-19; Medical consultation; Observational study; Reactogenicity; Survey; Vaccines

Reactogenicity correlates only weakly with humoral immunogenicity after COVID-19 vaccination with BNT162b2 mRNA (Comirnaty®) - Held, Jürgen; Esse, Jan; Tascilar, Koray; Steininger, Philipp; Schober, Kilian; Irrgang, Pascal; Alsalameh, Rayya; Tenbusch, Matthias; Seggewies, Christof; Bogdan, Christian (Vaccines, 2021)
mRNA vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), such as BNT162b2 (Comirnaty®), have proven to be highly immunogenic and efficient but also show marked reactogenicity, leading to adverse effects (AEs). Here, we analyzed whether the severity of AEs predicts the antibody response against the SARS-CoV-2 spike protein. Healthcare workers without prior SARS-CoV-2 infection, who received a prime-boost vaccination with BNT162b2, completed a standardized electronic questionnaire on the duration and severity of AEs. Serum specimens were collected two to four weeks after the boost vaccination and tested with the COVID-19 ELISA IgG (Vircell-IgG), the LIAISON® SARS-CoV-2 S1/S2 IgG CLIA (DiaSorin-IgG) and the iFlash-2019-nCoV NAb surrogate neutralization assay (Yhlo-NAb). A penalized linear regression model fitted by machine learning was used to correlate AEs with antibody levels. Eighty subjects were enrolled in the study. Systemic, but not local, AEs occurred more frequently after the boost vaccination. Elevated SARS-CoV-2 IgG antibody levels were measured in 92.5% of subjects with Vircell-IgG and in all subjects with DiaSorin-IgG and Yhlo-NAb. Gender, age and BMI showed no association with the antibody levels or with the AEs. The linear regression model identified headache, malaise and nausea as AEs with the greatest variable importance for higher antibody levels (Vircell-IgG and DiaSorin-IgG). However, the model performance for predicting antibody levels from AEs was very low for Vircell-IgG (squared correlation coefficient r2 = 0.04) and DiaSorin-IgG (r2 = 0.06). AEs did not predict the surrogate neutralization (Yhlo-NAb) results. In conclusion, AEs correlate only weakly with the SARS-CoV-2 spike protein antibody levels after COVID-19 vaccination with BNT162b2 mRNA.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Adverse effects; Adverse reactions; Antibody; BioNTech; Machine learning; MRNA vaccine; Pfizer; SARS-CoV-2; Side effects

Re-Analysis of the Widely Used Recombinant Murine Cytomegalovirus MCMV-m157luc Derived from the Bacmid pSM3fr Confirms Its Hybrid Nature - Cordsmeier, Arne; Bednar, Christopher; Kübel, Sabrina; Bauer, Larissa; Enßer, Armin (International Journal of Molecular Sciences, 2023)
Murine cytomegalovirus (MCMV), and, in particular, recombinant virus derived from MCMV-bacmid pSM3fr, is widely used as the small animal infection model for human cytomegalovirus (HCMV). We sequenced the complete genomes of MCMV strains and recombinants for quality control. However, we noticed deviances from the deposited reference sequences of MCMV-bacmid pSM3fr. This prompted us to re-analyze pSM3fr and reannotate the reference sequence, as well as that for the commonly used MCMV-m157luc reporter virus. A correct reference sequence for this frequently used pSM3fr, containing a repaired version of m129 (MCK-2) and the luciferase gene instead of ORF m157, was constructed. The new reference also contains the original bacmid sequence, and it has a hybrid origin from MCMV strains Smith and K181.
CRIS-Team Scopus Importer:2023-10-06
Keywords: MCMV; MCMV bacmid reference; MCMV-m157lucMCK-2 repair; pSM3fr

Recognize Yourself-Innate Sensing of Non-LTR Retrotransposons - Lagisquet, Justine; Zuber, Kilian; Gramberg, Thomas (Viruses, 2021)
Although mobile genetic elements, or transposons, have played an important role in genome evolution, excess activity of mobile elements can have detrimental consequences. Already, the enhanced expression of transposons-derived nucleic acids can trigger autoimmune reactions that may result in severe autoinflammatory disorders. Thus, cells contain several layers of protective measures to restrict transposons and to sense the enhanced activity of these "intragenomic pathogens". This review focuses on our current understanding of immunogenic patterns derived from the most active elements in humans, the retrotransposons long interspersed element (LINE)-1 and Alu. We describe the role of known pattern recognition receptors in nucleic acid sensing of LINE-1 and Alu and the possible consequences for autoimmune diseases.
CRIS-Team WoS Importer:2021-02-12

Recombinant Human Cytomegalovirus Expressing an Analog-Sensitive Kinase pUL97 as Novel Tool for Functional Analyses - Krämer, Nadine; Schütz, Martin; Mato, Uxía Gestal; Herhaus, Lina; Marschall, Manfred; Zimmermann, Christine (Viruses, 2022)
The human cytomegalovirus (HCMV) is a member of the beta-herpesvirus family and inflicts life-long latent infections in its hosts. HCMV has been shown to manipulate and dysregulate many cellular processes. One major interactor with the cellular host is the viral kinase pUL97. The UL97 gene is essential for viral replication, and kinase-deficient mutants of pUL97 display a severe replication defect. Recently, another group established an analog-sensitive version of the pUL97 protein. This mutant kinase can be treated with a non-hydrolysable ATP analog, thereby inhibiting its kinase function. This process is reversible by removing the ATP analog by media change. We introduced this mutant version of the pUL97 protein into the laboratory strain Ad169 of HCMV, BADwt, creating a BAD-UL97-as1 viral mutant. This mutant virus replicated normally in infected cells in the absence of the ATP analog and maintained its ability to phosphorylate its cellular substrates. However, when treated with the ATP analog, BAD-UL97-as1 displayed a defect in the production of intra- and extracellular viral DNA and in the production of viral progeny. Furthermore, in the presence of 3MB-PP1, a well-established substrate of pUL97 was no longer hyperphosphorylated. This effect was detectable as early as 4 h post treatment, which allows for studies on pUL97 without the complication of low viral titers. Nevertheless, we observed off-target effects of 3MB-PP1 on several cellular processes, which should be considered with this approach.
CRIS-Team Scopus Importer:2022-11-04
Keywords: analog-sensitive pUL97 variant; BACmid-derived recombinant HCMV; functional analyses; human cytomegalovirus (HCMV); protein kinase pUL97; pUL97-specific inhibitors; viral kinase activity

Redirecting T cells to ewing's sarcoma family of tumors by a chimeric NKG2D receptor expressed by lentiviral transduction or mRNA transfection - Lehner, Manfred; Goetz, Gabriel; Proff, Julia; Schaft, Niels; Dörrie, Jan; Full, Florian; Enßer, Armin; Muller, Yves; Cerwenka, Adelheid; Abken, Hinrich; Parolini, Ornella; Ambros, Peter F.; et al. (PLoS ONE, 2012)
We explored the possibility to target Ewing's sarcoma family of tumors (ESFT) by redirecting T cells. To this aim, we considered NKG2D-ligands (NKG2D-Ls) as possible target antigens. Detailed analysis of the expression of MICA, MICB, ULBP-1, -2, and -3 in fourteen ESFT cell lines revealed consistent expression of at least one NKG2D-L. Thus, for redirecting T cells, we fused a CD3ζ/CD28-derived signaling domain to the ectodomain of NKG2D, however, opposite transmembrane orientation of this signaling domain and NKG2D required inverse orientation fusion of either of them. We hypothesized that the particularly located C-terminus of the NKG2D ectodomain should allow reengineering of the membrane anchoring from a native N-terminal to an artificial C-terminal linkage. Indeed, the resulting chimeric NKG2D receptor (chNKG2D) was functional and efficiently mediated ESFT cell death triggered by activated T cells. Notably, ESFT cells with even low NKG2D-L expression were killed by CD8 pos and also CD4 pos cells. Both, mRNA transfection and lentiviral transduction resulted in high level surface expression of chNKG2D. However, upon target-cell recognition receptor surface levels were maintained by tranfected RNA only during the first couple of hours after transfection. Later, target-cell contact resulted in strong and irreversible receptor down-modulation, whereas lentivirally mediated expression of chNKG2D remained constant under these conditions. Together, our study defines NKG2D-Ls as targets for a CAR-mediated T cell based immunotherapy of ESFT. A comparison of two different methods of gene transfer reveals strong differences in the susceptibility to ligand-induced receptor down-modulation with possible implications for the applicability of RNA transfection. © 2012 Lehner et al.
CRIS-Team Scopus Importer:2021-10-01

Reduction in subventricular zone-derived olfactory bulb neurogenesis in a rat model of Huntington's disease is accompanied by striatal invasion of neuroblasts - Kandasamy, Mahesh; Rosskopf, Michael; Wagner, Katrin; Klein, Barbara; Couillard-Despres, Sebastien; Reitsamer, Herbert A.; Stephan, Michael; Nguyen, Huu Phuc; Riess, Olaf; Bogdahn, Ulrich; Winkler, Jürgen; von Hörsten, Stephan; et al. (PLoS ONE, 2015)
Huntington's disease (HD) is an inherited progressive neurodegenerative disorder caused by an expanded CAG repeat in exon 1 of the huntingtin gene (HTT). The primary neuropathology of HD has been attributed to the preferential degeneration of medium spiny neurons (MSN) in the striatum. Reports on striatal neurogenesis have been a subject of debate; nevertheless, it should be considered as an endogenous attempt to repair the brain. The subventricular zone (SVZ) might offer a close-by region to supply the degenerated striatum with new cells. Previously, we have demonstrated that R6/2 mice, a widely used preclinical model representing an early onset HD, showed reduced olfactory bulb (OB) neurogenesis but induced striatal migration of neuroblasts without affecting the proliferation of neural progenitor cell (NPCs) in the SVZ. The present study revisits these findings, using a clinically more relevant transgenic rat model of late onset HD (tgHD rats) carrying the human HTT gene with 51 CAG repeats and mimicking many of the neuropathological features of HD seen in patients. We demonstrate that cell proliferation is reduced in the SVZ and OB of tgHD rats compared to WT rats. In the OB of tgHD rats, although cell survival was reduced, the frequency of neuronal differentiation was not altered in the granule cell layer (GCL) compared to the WT rats. However, an increased frequency of dopamenergic neuronal differentiation was noticed in the glomerular layer (GLOM) of tgHD rats. Besides this, we observed a selective proliferation of neuroblasts in the adjacent striatum of tgHD rats. There was no evidence for neuronal maturation and survival of these striatal neuroblasts. Therefore, the functional role of these invading neuroblasts still needs to be determined, but they might offer an endogenous alternative for stem or neuronal cell transplantation strategies.
EVALuna2:24974

Regulation of the tumor marker Fascin by the viral oncoprotein Tax of human T-cell leukemia virus type 1 (HTLV-1) depends on promoter activation and on a promoter-independent mechanism - Mohr, Caroline F.; Groß, Christine; Bros, Matthias; Reske-Kunz, Angelika B.; Biesinger, Brigitte; Thoma-Kreß, Andrea (Virology, 2015)
Adult T-cell leukemia/lymphoma is a highly infiltrative neoplasia of CD4(+) T-lymphocytes that occurs in about 5% of carriers infected with the deltaretrovirus human T-cell leukemia virus type 1 (HTLV-1). The viral oncoprotein Tax perturbs cellular signaling pathways leading to upregulation of host cell factors, amongst them the actin-bundling protein Fascin, an invasion marker of several types of cancer. However, transcriptional regulation of Fascin by Tax is poorly understood. In this study, we identified a triple mode of transcriptional induction of Fascin by Tax, which requires (1) NF-?B-dependent promoter activation, (2) a Tax-responsive region in the Fascin promoter, and (3) a promoter-independent mechanism sensitive to the Src family kinase inhibitor PP2. Thus, Tax regulates Fascin by a multitude of signals. Beyond, using Tax-expressing and virus-transformed lymphocytes as a model system, our study is the first to identify the invasion marker Fascin as a novel target of PP2, an inhibitor of metastasis.
EVALuna2:8284

Regulatory Interaction between the Cellular Restriction Factor IFI16 and Viral pp65 (pUL83) Modulates Viral Gene Expression and IFI16 Protein Stability - Biolatti, Matteo; Dell'Oste, Valentina; Pautasso, Sara; Von Einem, Jens; Marschall, Manfred; Plachter, Bodo; Gariglio, Marisa; De Andrea, Marco; Landolfo, Santo (Journal of Virology, 2016)
A key player in the intrinsic resistance against human cytomegalovirus (HCMV) is the interferon-?-inducible protein 16 (IFI16), which behaves as a viral DNA sensor in the first hours postinfection and as a repressor of viral gene transcription in the later stages. Previous studies on HCMV replication demonstrated that IFI16 binds to the viral protein kinase pUL97, undergoes phosphorylation, and relocalizes to the cytoplasm of infected cells. In this study, we demonstrate that the tegument protein pp65 (pUL83) recruits IFI16 to the promoter of the UL54 gene and downregulates viral replication, as shown by use of the HCMV mutant v65Stop, which lacks pp65 expression. Interestingly, at late time points of HCMV infection, IFI16 is stabilized by its interaction with pp65, which stood in contrast to IFI16 degradation, observed in herpes simplex virus 1 (HSV-1)-infected cells. Moreover, we found that its translocation to the cytoplasm, in addition to pUL97, strictly depends on pp65, as demonstrated with the HCMV mutant RV-VM1, which expresses a form of pp65 unable to translocate into the cytoplasm. Thus, these data reveal a dual role for pp65: during early infection, it modulates IFI16 activity at the promoter of immediate-early and early genes; subsequently, it delocalizes IFI16 from the nucleus into the cytoplasm, thereby stabilizing and protecting it from degradation. Overall, these data identify a novel activity of the pp65/IFI16 interactome involved in the regulation of UL54 gene expression and IFI16 stability during early and late phases of HCMV replication.The DNA sensor IFI16, a member of the PYHIN proteins, restricts HCMV replication by impairing viral DNA synthesis. Using a mutant virus lacking the tegument protein pp65 (v65Stop), we demonstrate that pp65 recruits IFI16 to the early UL54 gene promoter. As a putative counteraction to its restriction activity, pp65 supports the nucleocytoplasmic export of IFI16, which was demonstrated with the viral mutant RV-VM1 expressing a nuclearly retained pp65. These data reveal a dual role of pp65 in IFI16 regulation: in the early phase of HCMV infection, it contributes to viral evasion from IFI16 restriction activity, while at later time points, it promotes the nuclear delocalization of IFI16, thereby stabilizing and protecting it from degradation. In the present work, we further clarify the mechanisms HCMV relies on to overcome intracellular innate immune restriction and provide new insights into the relevance of DNA-sensing restriction factor IFI16 during HCMV infection.
EVALuna2:8328

Replication of Influenza A Virus in Secondary Lymphatic Tissue Contributes to Innate Immune Activation - Friedrich, Sarah-Kim; Schmitz, Rosa; Bergerhausen, Michael; Lang, Judith; Duhan, Vikas; Hardt, Cornelia; Tenbusch, Matthias; Prinz, Marco; Asano, Kenichi; Bhat, Hilal; Hamdan, Thamer A.; Lang, Philipp Alexander; et al. (Pathogens, 2021)
The replication of viruses in secondary lymphoid organs guarantees sufficient amounts of pattern-recognition receptor ligands and antigens to activate the innate and adaptive immune system. Viruses with broad cell tropism usually replicate in lymphoid organs; however, whether a virus with a narrow tropism relies on replication in the secondary lymphoid organs to activate the immune system remains not well studied. In this study, we used the artificial intravenous route of infection to determine whether Influenza A virus (IAV) replication can occur in secondary lymphatic organs (SLO) and whether such replication correlates with innate immune activation. Indeed, we found that IAV replicates in secondary lymphatic tissue. IAV replication was dependent on the expression of Sialic acid residues in antigen-presenting cells and on the expression of the interferon-inhibitor UBP43 (Usp18). The replication of IAV correlated with innate immune activation, resulting in IAV eradication. The genetic deletion of Usp18 curbed IAV replication and limited innate immune activation. In conclusion, we found that IAV replicates in SLO, a mechanism which allows innate immune activation.
CRIS-Team WoS Importer:2021-06-04

Reporter Systems to Study HTLV-1 Transmission - Groß, Christine; Thoma-Kreß, Andrea (Methods in Molecular Biology, 2017)
The retrovirus Human T-lymphotropic virus type 1 (HTLV-1) preferentially infects CD4+ T-cells via cell-to-cell transmission, while cell-free infection of T-cells is inefficient. Substantial insights into the different routes of transmission have largely been obtained by imaging techniques or by flow cytometry. Recently, strategies to quantify infection events with HTLV-1 improved. In this chapter, we present two different methods to quantitate virus transmission. Both methods are based on measuring gene activity of luciferase with a cost-saving in-house luciferase assay. First, we established a reporter Jurkat T-cell line carrying a luciferase gene under the control of the HTLV-1 core promoter U3R. Upon co-culture with chronically HTLV-1-infected T-cell lines, reporter cells are infected, and upon expression of the viral transactivator Tax, the viral promoter is activated resulting in enhanced luciferase activity. However, this assay as presented here does not exclude cell fusion as the mechanism allowing intracellular Tax-dependent activation of luciferase gene expression. Therefore, we describe a second method, the single-cycle replication-dependent reporter system developed by Mazurov et al. (PLoS Pathog 6:e1000788, 2010) that allows quantitation of HTLV-1 infection in co-cultured cells. Taken together, both methods facilitate quantitation of HTLV-1 transmission and will help to unravel pathways required for cell-to-cell transmission on a quantitative basis.
EVALuna2:35816

Respiratory syncytial-virus induced cytokine production from leukocytes is impaired in severe asthma - Jameel, Kaschin Jamal; Yanik, Sarah; Buelthoff, Eike; Rohde, Simon; Weidinger, Daniel; Yusuf, Faisal; Kronsbein, Juliane; Tenbusch, Matthias; Knobloch, Juergen (EUROPEAN RESPIRATORY JOURNAL, 2021)
CRIS-Team WoS Importer:2022-02-25

Results of Tick-Borne Encephalitis Virus (TBEV) Diagnostics in an Endemic Area in Southern Germany, 2007 to 2022. - Steininger, Philipp; Enßer, Armin; Knöll, Antje; Korn, Klaus (Viruses, 2023)
Tick-borne encephalitis virus (TBEV) is the most important tick-transmitted neurotropic flavivirus in Europe and Asia. Our analysis aimed to investigate the contribution of TBEV-specific antibody detection by serological assays and TBEV RNA detection by real-time PCR to the diagnosis of tick-borne encephalitis (TBE). We analyzed data from 3713 patients from 16 years of laboratory TBEV diagnostics in an endemic area in Southern Germany. During this period, 126 cases of TBE were diagnosed. TBEV-specific IgM ELISA tests showed a high clinical sensitivity (96.8%) and a very high clinical specificity (99.7%). In immunocompetent patients, TBE was reliably diagnosed by detection of TBEV IgM antibodies in serum. Intrathecal TBEV IgG antibody synthesis was detected in 46 of 84 (55%) cases by analysis of paired serum and cerebrospinal fluid (CSF) samples. None of the 87 immunocompetent TBE patients tested had detectable TBEV RNA in serum or CSF. In contrast, in two TBE patients without TBEV-specific antibodies, diagnosis could only be made by the detection of TBEV RNA in CSF. Both patients had previously been treated with the B cell-depleting antibody rituximab. Therefore, in patients with CNS infection and humoral immunodeficiency, it is necessary to include TBEV PCR in the diagnostic approach.
EVALuna2:545508

Review - EPIGENETICS, 2018 Inheritable Epigenetic Response towards Foreign DNA Entry by Mammalian Host Cells: A Guardian of Genomic Stability - Doerfler, Walter; Weber, Stefanie; Naumann, Anja (Epigenetics, 2018)
Apart from its well-documented role in long-term promoter silencing, the genome-wide distribution patterns of 28 million methylated or unmethylated CpG dinucleotides, e. g. in the human genome, is in search of genetic functions. We have set out to study changes in the cellular CpG methylation profile upon introducing foreign DNA into mammalian cells. As stress factors served the genomic integration of foreign (viral or bacterial plasmid) DNA, virus infections or the immortalization of cells with Epstein Barr Virus (EBV). In all instances investigated, alterations in cellular CpG methylation and transcription profiles were observed to different degrees. In the case of adenovirus DNA integration in adenovirus type 12 (Ad12)-transformed hamster cells, the extensive changes in cellular CpG methylation persisted even after the complete loss of all transgenomic Ad12 DNA. Hence, stress-induced alterations in CpG methylation can be inherited independent of the continued presence of the transgenome. Upon virus infections, changes in cellular CpG methylation appear early after infection. In EBV immortalized as compared to control cells, CpG hypermethylation in the far-upstream region of the human FMR1 promoter decreased four-fold. We conclude that in the wake of cellular stress due to foreign DNA entry, preexisting CpG methylation patterns were altered, possibly at specific CpG dinucleotides. Frequently, transcription patterns were also affected. As a working concept, we view CpG methylation profiles in mammalian genomes as a guarding sensor for genomic stability under epigenetic control. As a caveat towards manipulations of cells with foreign DNA, such cells can no longer be considered identical to their un-manipulated counterparts.
EVALuna2:35356

Rhesus monkey rhadinovirus isolated from hemangioma tissue - Enßer, Armin; Yasuda, Koji; Lauer, William; Desrosiers, Ronald C.; Hahn, Alexander S. (Microbiology Resource Announcements, 2020)
We isolated a rhesus monkey rhadinovirus, isolate RRVmmu 209-07, from hemangioma tissue. The virion DNA was sequenced by Illumina-based sequencing. Isolate RRVmmu 209-07 is highly similar overall to RRV 26-95, but considerable differences exist in the 3= region of the genome.
CRIS-Team Scopus Importer:2020-04-07

Rodent’s Stride Length Depends on Body Size: Implications for CatWalk Assay - Timotius, Ivanna; Moceri, Sandra; Plank, Anne-Christine; Habermeyer, Johanna; Canneva, Fabio; Casadei, Nicolas; Riess, Olaf; Winkler, Jürgen; Klucken, Jochen; Eskofier, Björn; von Hörsten, Stephan (Measuring Behavior 2018, 2018)
The analysis of gait is an essential part of rodent phenotyping. Regarding the complex nature of walking, preclinical gait analysis is normally based on several gait parameters (which have been progressively developed [1,2] in recent years) including the animal’s stride length, body speed, support, etc. The stride length is altered in several diseases [3–5] and this parameter can be easily translated from rodent models to human patients. However, we hypothesized that the stride length is affected by the body size [6,7], which becomes a challenge in analyzing gait. Using the gait parameters assessed by CatWalk system [8–10], we examined the correlation between body-length/body-weight with stride length using CatWalk-video-derived body silhouette length. To examine the effect of growth and aging in rodents, we studied wild-type Sprague-Dawley male rats and C57BL/6N mice. Moreover, we examined the body size difference between genotypes in BACSCNA transgenic rats [11,12] and BACHD transgenic mice [13]. The CatWalk data were collected as the rodents walked freely on top of a glass-floored corridor. The rat gait was monitored at 4 different age points (10, 26, 55 and 62 weeks old), whereas the mice were monitored at 3 different age points (20, 32, and 47 weeks old). The rodent numbers included in the experiments were: (a) wild-type male rats (n=16-27/time point), (b) BACSCNA rats (n=19-32/time point), (c) wild-type mice (n=12-13/time point), and (d) BACHD mice (n=9-11/time point). The rodents were maintained under specific-pathogen-free condition. All research and animal care procedures were performed in compliance with international animal welfare standards and approved by the district governments of Lower Franconia, Würzburg, Bavaria, Germany (RegUFr#55.2-2532-2-218). The correlations between front stride length (averaged from the left and right side) and the body-silhouette-length/body-weight are shown in Figure 1. Significant correlations are shown with both body silhouette lengths and body weight. The correlation between hind stride length and body size showed the similar relationship as the front stride length (data not shown). Besides body size differences due to growth, pathological body size differences were also observed as shown in Figure 2. Thus, we demonstrated that stride length is highly correlated with body silhouette length (based on the CatWalk video) and body weight. In the near future, we need to subject gait parameters to a scaling process using body weight or silhouette length, raising the possibility of normalization for differences in size as a potential confounding of gait measure
Keywords: Stride Length; Body Size; Rodent; CatWalk

Role of CMV chemokine receptor M33 in airway graft rejection in a mouse transplant model - Hanka, Isabella; Stamminger, Thomas; Ramsperger-Gleixner, Martina; Kuckhahn, Annika V.; Müller, Regina; Weyand, Michael; Heim, Christian (Transplant Immunology, 2021)
Background: Cytomegalovirus (CMV) infection is a risk factor for bronchiolitis obliterans (BO), one form of chronic lung allograft dysfunction (CLAD). The viral chemokine receptor M33 is essential for successful spread of murine CMV to host salivary glands. In the present study we investigated the impact of M33 on chronic airway rejection. Methods: MHC I-mismatched tracheas of C·B10-H2b/LilMcdJ mice were transplanted into BALB/c (H2d) recipients and infected at different dates with wild type (WT) or M33-deleted (delM33) MCMV representing clinical settings of viral recipient (R)-donor (D)-serostatus: (D−/R+) or (D+/R-). Grafts were recovered for gene expression and histological / immunofluorescence analysis, respectively. Results: Evaluations showed significantly increased signs of chronic rejection in WT-infected mice compared to uninfected allografts seen in lower epithelium/lamina propria-ratio (ELR) (ELR 0.46 ± 0.07 [WT post] vs. ELR 0.66 ± 0.10 [non-inf.]; p < 0.05). The rejection in delM33-infected groups was significantly reduced vs. WT-infected groups (0.67 ± 0.04 [delM33 post]; vs. WT post p < 0.05). Furthermore, decreased rejection was observed in WT pre-infected compared to post-infected groups (0.56 ± 0.08 [WT pre]; vs. WT post p < 0.05). CD8+ T cell infiltration was significantly higher in WT-post compared to the delM33 infected or non-infected allografts. Conclusions: These data support the role of the CMV in accelerating CLAD. The deletion of chemokine receptor M33 leads to attenuated rejection.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Bronchiolitis obliterans; Chemokine receptor M33; Chronic rejection; Murine cytomegalovirus; Tracheal transplantation

Role of hypothalamus-pituitary-adrenal axis modulation in the stress-resilient phenotype of DPP4-deficient rats - Golub, Yulia; Schildbach, Eva-Maria; Touma, Chadi; Kratz, Oliver; Moll, Gunther; von Hörsten, Stephan; Canneva, Fabio (Behavioural Brain Research, 2019)
BACKGROUND: Dipeptidyl peptidase 4 (DPP4, CD26) is a moonlighting enzyme responsible for the proteolytic inactivation of neuropeptide Y (NPY), a peptide known for its anxiolytic effect in the central nervous system. Our previous work revealed a stress-resilient phenotype and a potentiation of short-term fear extinction in a congenic rat model deficient for DPP4 activity (DPP4mut). Here, we investigated neuroendocrine mechanisms underlying the phenotype of the DPP4mut animals. We studied the function of the hypothalamus-pituitary-adrenal (HPA) axis including the expression levels of its key genes and explored the possibility of structural NPY system changes. METHODS AND RESULTS: We find decreased expression of Nr3c1 (glucocorticoid receptor - GR) and Fkbp5 (FK506 binding protein 5) in the amygdala and the hypothalamus of the DPP4mut rats, as well as the lower stress-induced peripheral corticosterone (CORT) levels. We detect no significant alterations in basal and DEX-induced CORT levels in the DPP4mut animals. The abundance of NPY-ergic neurons in the basolateral amygdala, dentate gyrus and hippocampus did not differ between the DPP4mut and their wild type littermates. CONCLUSION: DPP4mut rats show blunted CORT response in line with their lower behavioral stress-response profile. These results are consistent with the hypothesis that increased central NPY levels elevate the threshold of stress response. We suggest that changes in the expression levels of key HPA axis genes (Nr3c1 and Fkbp5) are a consequence of the altered stress-perception of DPP4mut animals, thus further contributing to the stress-resilient phenotype.
EVALuna2:36365

Rubella vaccine–induced granulomas are a novel phenotype with incomplete penetrance of genetic defects in cytotoxicity - Groß, Miriam; Speckmann, Carsten; May, Annette; Gajardo-Carrasco, Tania; Wustrau, Katharina; Maier, Sarah Lena; Panning, Marcus; Huzly, Daniela; Agaimy, Abbas; Bryceson, Yenan T.; Choo, Sharon; Chow, C. W.; et al. (Journal of Allergy and Clinical Immunology, 2021)
Background: Rubella virus–induced granulomas have been described in patients with various inborn errors of immunity. Most defects impair T-cell immunity, suggesting a critical role of T cells in rubella elimination. However, the molecular mechanism of virus control remains elusive. Objective: This study sought to understand the defective effector mechanism allowing rubella vaccine virus persistence in granulomas. Methods: Starting from an index case with Griscelli syndrome type 2 and rubella skin granulomas, this study combined an international survey with a literature search to identify patients with cytotoxicity defects and granuloma. The investigators performed rubella virus immunohistochemistry and PCR and T-cell migration assays. Results: This study identified 21 patients with various genetically confirmed cytotoxicity defects, who presented with skin and visceral granulomas. Rubella virus was demonstrated in all 12 accessible biopsies. Granuloma onset was typically before 2 years of age and lesions persisted from months to years. Granulomas were particularly frequent in MUNC13-4 and RAB27A deficiency, where 50% of patients at risk were affected. Although these proteins have also been implicated in lymphocyte migration, 3-dimensional migration assays revealed no evidence of impaired migration of patient T cells. Notably, patients showed no evidence of reduced control of concomitantly given measles, mumps, or varicella live-attenuated vaccine or severe infections with other viruses. Conclusions: This study identified lymphocyte cytotoxicity as a key effector mechanism for control of rubella vaccine virus, without evidence for its need in control of live measles, mumps, or varicella vaccines. Rubella vaccine–induced granulomas are a novel phenotype with incomplete penetrance of genetic disorders of cytotoxicity.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Cytotoxicity; granuloma; Griscelli syndrome type 2; hemophagocytic lymphohistiocytosis; live vaccine; primary immunodeficiency; rubella virus

Salivary duct carcinoma of the sinonasal cavity: A case report and review of the literature - Müller, Sandra; Mantsopoulos, Konstantinos; Iro, Heinrich; Agaimy, Abbas (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2016)
Salivary duct carcinoma is a rare, aggressive tumor entity first described by Kleinsasser et al in 1968, as a group of malignant salivary gland tumors characterized by duct formation and central necrosis. A case with an unusual localization in the nasal cavity and maxillary sinus is being described in our report.A 60-year-old patient presented with difficulty of nasal breathing and recurrent episodes of epistaxis from the left nasal cavity over the previous 3 months. On endoscopy, a vulnerable lesion in the left inferior nasal meatus could be seen. Biopsy showed salivary duct carcinoma. Treatment consisted of tumor resection by means of a combined endoscopic-osteoplastic surgical approach to the maxillary sinus, bilateral neck dissection, partial parotidectomy, and adjuvant radiochemotherapy.The patient is 6 months after completion of treatment and is free of disease.As salivary duct carcinoma of the sinonasal tract is extremely rare, no therapeutic standards have been developed and treatment essentially is based upon experience with ductal adenocarcinoma of the salivary glands. Surgery therapy should be radical, aiming at eradicating locoregional disease with the role of adjuvant radiotherapy lying in the management of cases with negative prognostic factors. © 2016 Wiley Periodicals, Inc. Head Neck 38:E2464-E2466, 2016.
EVALuna2:6924

SAMHD1 … and Viral Ways around It. - Deutschmann, Janina; Gramberg, Thomas (Viruses, 2021)
The SAM and HD domain-containing protein 1 (SAMHD1) is a dNTP triphosphohydrolase that plays a crucial role for a variety of different cellular functions. Besides balancing intracellular dNTP concentrations, facilitating DNA damage repair, and dampening excessive immune responses, SAMHD1 has been shown to act as a major restriction factor against various virus species. In addition to its well-described activity against retroviruses such as HIV-1, SAMHD1 has been identified to reduce the infectivity of different DNA viruses such as the herpesviruses CMV and EBV, the poxvirus VACV, or the hepadnavirus HBV. While some viruses are efficiently restricted by SAMHD1, others have developed evasion mechanisms that antagonize the antiviral activity of SAMHD1. Within this review, we summarize the different cellular functions of SAMHD1 and highlight the countermeasures viruses have evolved to neutralize the restriction factor SAMHD1.
CRIS-Team WoS Importer:2021-04-09

SAMHD1 in Retroviral Restriction and Innate Immune Sensing–Should We Leash the Hound? - Herrmann, Alexandra; Happel, Anna-Ursula; Gramberg, Thomas (Current HIV Research, 2016)
The antiviral restriction factor SAM domain and HD domain-containing protein 1 (SAMHD1) is a dNTP triphosphohydrolase and thereby contributes to the regulation of intracellular dNTP levels. SAMHD1 blocks retroviral infection at the level of reverse transcription in myeloid cells and resting CD4+ T cells and is counteracted by the accessory protein Vpx, which is encoded by human immunodeficiency virus 2 (HIV-2) and several simian immunodeficiency virus (SIV) strains. Recently, it has been shown that the antiviral activity of SAMHD1 in myeloid dendritic cells (DC) hampers the induction of an efficient immune response directed against HIV-1.Within this review, we will summarize recent advances on the biology of SAMHD1 and its function as an antiviral restriction factor. In addition, we will discuss its role in autoimmunity and the antiviral immune response directed against HIV-1 and will evaluate the possibility of modulating SAMHD1 activity to generate an enhanced antiretroviral immune response.
EVALuna2:8304

SARS-CoV-2 and SARS-CoV Spike-Mediated Cell-Cell Fusion Differ in Their Requirements for Receptor Expression and Proteolytic Activation - Hörnich, Bojan F.; Grosskopf, Anna K.; Schlagowski, Sarah; Tenbusch, Matthias; Kleine-Weber, Hannah; Neipel, Frank; Stahl-Hennig, Christiane; Hahn, Alexander S. (Journal of Virology, 2021)
Severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) infects cells through interaction of its spike protein (SARS2-S) with angiotensin-converting enzyme 2 (ACE2) and activation by proteases, in particular transmembrane protease serine 2 (TMPRSS2). Viruses can also spread through fusion of infected with uninfected cells. We compared the requirements of ACE2 expression, proteolytic activation, and sensitivity to inhibitors for SARS2-S-mediated and SARS-CoV-S (SARS1-S)-mediated cell-cell fusion. SARS2-S-driven fusion was moderately increased by TMPRSS2 and strongly by ACE2, while SARS1-S-driven fusion was strongly increased by TMPRSS2 and less so by ACE2 expression. In contrast to that of SARS1-S, SARS2-S-mediated cell-cell fusion was efficiently activated by batimastat-sensitive metalloproteases. Mutation of the S1/S2 proteolytic cleavage site reduced effector cell-target cell fusion when ACE2 or TMPRSS2 was limiting and rendered SARS2-S-driven cell-cell fusion more dependent on TMPRSS2. When both ACE2 and TMPRSS2 were abundant, initial target cell-effector cell fusion was unaltered compared to that of wild-type (wt) SARS2-S, but syncytia remained smaller. Mutation of the S2 cleavage (S2') site specifically abrogated activation by TMPRSS2 for both cell-cell fusion and SARS2-S-driven pseudoparticle entry but still allowed for activation by metalloproteases for cell-cell fusion and by cathepsins for particle entry. Finally, we found that the TMPRSS2 inhibitor bromhexine, unlike the inhibitor camostat, was unable to reduce TMPRSS2-activated cell-cell fusion by SARS1-S and SARS2-S. Paradoxically, bromhexine enhanced cell-cell fusion in the presence of TMPRSS2, while its metabolite ambroxol exhibited inhibitory activity under some conditions. On Calu-3 lung cells, ambroxol weakly inhibited SARS2-S-driven lentiviral pseudoparticle entry, and both substances exhibited a dose-dependent trend toward weak inhibition of authentic SARS-CoV-2.IMPORTANCE Cell-cell fusion allows viruses to infect neighboring cells without the need to produce free virus and contributes to tissue damage by creating virus-infected syncytia. Our results demonstrate that the S2' cleavage site is essential for activation by TMPRSS2 and unravel important differences between SARS-CoV and SARS-CoV-2, among those, greater dependence of SARS-CoV-2 on ACE2 expression and activation by metalloproteases for cell-cell fusion. Bromhexine, reportedly an inhibitor of TMPRSS2, is currently being tested in clinical trials against coronavirus disease 2019. Our results indicate that bromhexine enhances fusion under some conditions. We therefore caution against the use of bromhexine in high dosages until its effects on SARS-CoV-2 spike activation are better understood. The related compound ambroxol, which similarly to bromhexine is clinically used as an expectorant, did not exhibit activating effects on cell-cell fusion. Both compounds exhibited weak inhibitory activity against SARS-CoV-2 infection at high concentrations, which might be clinically attainable for ambroxol.
CRIS-Team Scopus Importer:2021-04-30
Keywords: cell-cell fusion; COVID-19; SARS-CoV-2; spike; TMPRSS2; virus entry

SARS-CoV-2 N gene dropout and N gene Ct value shift as indicator for the presence of B.1.1.7 lineage in a commercial multiplex PCR assay - Wollschläger, Paul; Todt, Daniel; Gerlitz, Nadja; Pfaender, Stephanie; Bollinger, Thomas; Sing, Andreas; Dangel, Alexandra; Ackermann, Nickolaus; Korn, Klaus; Enßer, Armin; Steinmann, Eike; Buhl, Michael; et al. (Clinical Microbiology and Infection, 2021)
Objectives: Detection and surveillance of SARS-CoV-2 is of eminent importance, particularly due to the rapid emergence of variants of concern (VOCs). In this study we evaluated if a commercially available quantitative real-time PCR (qRT-PCR) assay can identify SARS-CoV-2 B.1.1.7 lineage samples by a specific N gene dropout or Ct value shift compared with the S or RdRp gene. Methods: VOC B.1.1.7 and non-B.1.1.7 SARS-CoV-2-positive patient samples were identified via whole-genome sequencing and variant-specific PCR. Confirmed B.1.1.7 (n = 48) and non-B.1.1.7 samples (n = 58) were analysed using the Allplex™ SARS-CoV-2/FluA/FluB/RSV™ PCR assay for presence of SARS-CoV-2 S, RdRp and N genes. The N gene coding sequence of SARS-CoV-2 with and without the D3L mutation (specific for B.1.1.7) was cloned into pCR™II-TOPO™ vectors to validate polymorphism-dependent N gene dropout with the Allplex™ SARS-CoV-2/FluA/FluB/RSV™ PCR assay. Results: All studied B.1.1.7-positive patient samples showed significantly higher Ct values in qRT-PCR (Δ6–10, N gene dropout on Ct values > 29) of N gene than the corresponding values of S (p ≤ 0.0001) and RdRp (p ≤ 0.0001) genes. The assay reliably discriminated B.1.1.7 and non-B.1.1.7 positive samples (area under the curve = 1) in a receiver operating characteristic curve analysis. Identical Ct value shifts (Δ7–10) were detected in reverse genetic experiments, using isolated plasmids containing N gene coding sequences corresponding to D3 or 3L variants. Discussion: An N gene dropout or Ct value shift is shown for B.1.1.7-positive samples in the Allplex™ SARS-CoV-2/FluA/FluB/RSV™ PCR assay. This approach can be used as a rapid tool for B.1.1.7 detection in single assay high throughput diagnostics.
CRIS-Team Scopus Importer:2021-07-02
Keywords: B.1.1.7; Diagnostic quantitative RT-PCR; Mutation; SARS-CoV-2; VOC

SARS-CoV-2 samples may escape detection because of a single point mutation in the N gene - Ziegler, Katharina; Steininger, Philipp; Ziegler, Renate; Steinmann, Jörg; Korn, Klaus; Enßer, Armin (Eurosurveillance, 2020)
We found that a single nucleotide polymorphism (SNP) in the nucleoprotein gene of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from a patient interfered with detection in a widely used commercial assay. Some 0.2% of the isolates in the EpiCoV database contain this SNP. Although SARS-CoV-2 was still detected by the other probe in the assay, this underlines the necessity of targeting two independent essential regions of a pathogen for reliable detection.
CRIS-Team Scopus Importer:2020-10-23

SARS-CoV-2-seronegative HIV-1-infected subjects target CTL epitopes in the SARS-CoV-2 nucleoprotein cross-reactive to common cold coronaviruses - Schmidt, Katja; Nganou-Makamdop, Krystelle; Tenbusch, Matthias; El Kenz, Boutaina; Maier, Clara; Lapuente, Dennis; Überla, Klaus; Spriewald, Bernd; Bergmann, Silke; Harrer, Ellen; Harrer, Thomas (INFECTION, 2021)
CRIS-Team WoS Importer:2021-04-09

SARS-CoV-2-seronegative subjects target CTL epitopes in the SARS-CoV-2 nucleoprotein cross-reactive to common cold coronaviruses - Schmidt, Kristin; Nganou-Makamdop, K.; Tenbusch, Matthias; El Kenz, B.; Maier, Clara; Lapuente, Dennis; Überla, Klaus; Spriewald, Bernd; Bergmann, Sabrina; Harrer, Ellen; Harrer, Thomas (JOURNAL OF THE INTERNATIONAL AIDS SOCIETY, 2021)
CRIS-Team WoS Importer:2021-11-26

SARS-CoV-2-Seronegative Subjects Target CTL Epitopes in the SARS-CoV-2 Nucleoprotein Cross-Reactive to Common Cold Coronaviruses - Schmidt, Katja; Nganou-Makamdop, Krystelle; Tenbusch, Matthias; El Kenz, Boutaina; Maier, Clara; Lapuente, Dennis; Überla, Klaus; Spriewald, Bernd; Bergmann, Silke; Harrer, Ellen; Harrer, Thomas (Frontiers in Immunology, 2021)
The beta-coronavirus SARS-CoV-2 induces severe disease (COVID-19) mainly in elderly persons with risk factors, whereas the majority of patients experience a mild course of infection. As the circulating common cold coronaviruses OC43 and HKU1 share some homologous sequences with SARS-CoV-2, beta-coronavirus cross-reactive T-cell responses could influence the susceptibility to SARS-CoV-2 infection and the course of COVID-19. To investigate the role of beta-coronavirus cross-reactive T-cells, we analyzed the T-cell response against a 15 amino acid long peptide (SCoV-DP15: DLSPRWYFYYLGTGP) from the SARS-CoV-2 nucleoprotein sequence with a high homology to the corresponding sequence (QLLPRWYFYYLGTGP) in OC43 and HKU1. SCoV-DP15-specific T-cells were detected in 4 out of 23 (17.4%) SARS-CoV-2-seronegative healthy donors. As HIV-1 infection is a potential risk factor for COVID-19, we also studied a cohort of HIV-1-infected patients on antiretroviral therapy. 44 out of these 116 HIV-1-infected patients (37.9%) showed a specific recognition of the SCoV-DP15 peptide or of shorter peptides within SCoV-DP15 by CD4+ T-cells and/or by CD8+ T-cells. We could define several new cross-reactive HLA-I-restricted epitopes in the SARS-CoV-2 nucleoprotein such as SPRWYFYYL (HLA-B*07, HLA-B*35), DLSPRWYFYY (HLA-A*02), LSPRWYFYY (HLA-A*29), WYFYYLGTGP and WYFYYLGT. Epitope specific CD8+ T-cell lines recognized corresponding epitopes within OC43 and HKU1 to a similar degree or even at lower peptide concentrations suggesting that they were induced by infection with OC43 or HKU1. Our results confirm that SARS-CoV-2-seronegative subjects can target SARS-CoV-2 not only by beta-coronavirus cross-reactive CD4+ T-cells but also by cross-reactive CD8+ cytotoxic T-cells (CTL). The delineation of cross-reactive T-cell epitopes contributes to an efficient epitope-specific immunomonitoring of SARS-CoV-2-specific T-cells. Further prospective studies are needed to prove a protective role of cross-reactive T-cells and their restricting HLA alleles for control of SARS-CoV-2 infection. The frequent observation of SARS-CoV-2-reactive T-cells in HIV-1-infected subjects could be a reason that treated HIV-1 infection does not seem to be a strong risk factor for the development of severe COVID-19.
CRIS-Team Scopus Importer:2021-05-28
Keywords: CD8; CTL; CTL epitope; HIV-1; HKU1; OC43; SARS-CoV-2 (2019-nCoV)

SARS-CoV-2 Spike Protein Is Capable of Inducing Cell–Cell Fusions Independent from Its Receptor ACE2 and This Activity Can Be Impaired by Furin Inhibitors or a Subset of Monoclonal Antibodies - Reuter, Nina; CHEN, XIAOHAN; Kropff, Barbara; Peter, Antonia Sophia; Britt, William J.; Mach, Michael; Überla, Klaus; Thomas, Marco (Viruses, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which was responsible for the COVID-19 pandemic, efficiently spreads cell-to-cell through mechanisms facilitated by its membrane glycoprotein spike. We established a dual split protein (DSP) assay based on the complementation of GFP and luciferase to quantify the fusogenic activity of the SARS-CoV-2 spike protein. We provide several lines of evidence that the spike protein of SARS-CoV-2, but not SARS-CoV-1, induced cell–cell fusion even in the absence of its receptor, angiotensin-converting enzyme 2 (ACE2). This poorly described ACE2-independent cell fusion activity of the spike protein was strictly dependent on the proteasomal cleavage of the spike by furin while TMPRSS2 was dispensable. Previous and current variants of concern (VOCs) differed significantly in their fusogenicity. The Delta spike was extremely potent compared to Alpha, Beta, Gamma and Kappa, while the Omicron spike was almost devoid of receptor-independent fusion activity. Nonetheless, for all analyzed variants, cell fusion was dependent on furin cleavage and could be pharmacologically inhibited with CMK. Mapping studies revealed that amino acids 652-1273 conferred the ACE2-independent fusion activity of the spike. Unexpectedly, residues proximal to the furin cleavage site were not of major relevance, whereas residue 655 critically regulated fusion. Finally, we found that the spike’s fusion activity in the absence of ACE2 could be inhibited by antibodies directed against its N-terminal domain (NTD) but not by antibodies targeting its receptor-binding domain (RBD). In conclusion, our BSL-1-compatible DSP assay allowed us to screen for inhibitors or antibodies that interfere with the spike’s fusogenic activity and may therefore contribute to both rational vaccine design and development of novel treatment options against SARS-CoV-2.
CRIS-Team Scopus Importer:2023-08-11
Keywords: ACE2; antibodies; cell–cell fusion; furin; glycoprotein; inhibitors; neutralization; receptor-independent; screening; severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); spike; therapy; variants of concern (VOCs)

Sars-Cov-2 Vaccine-Induced Cellular and Humoral Immunity in Patients after CD19.CAR-T Cell Therapy - Reimann, Hannah; Kremer, Anita; Blumenberg, Viktoria; Schmidt, Katja; Aigner, Michael; Kremer, Andreas; Tenbusch, Matthias; Bruns, Heiko; Harrer, Thomas; Schett, Georg; Müller, Fabian; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

SARS-CoV-2 variants with NSP12 P323L/G671S mutations display enhanced virus replication in ferret upper airways and higher transmissibility - Kim, Se Mi; Kim, Eun Ha; Casel, Mark Anthony B.; Kim, Young Il; Sun, Rong; Kwak, Mi Jeong; Yoo, Ji Seung; Yu, Mina; Yu, Kwang Min; Jang, Seung Gyu; Rollon, Rare; Choi, Jeong Ho; et al. (Cell Reports, 2023)
With the emergence of multiple predominant SARS-CoV-2 variants, it becomes important to have a comprehensive assessment of their viral fitness and transmissibility. Here, we demonstrate that natural temperature differences between the upper (33°C) and lower (37°C) respiratory tract have profound effects on SARS-CoV-2 replication and transmissibility. Specifically, SARS-CoV-2 variants containing the NSP12 mutations P323L or P323L/G671S exhibit enhanced RNA-dependent RNA polymerase (RdRp) activity at 33°C compared with 37°C and high transmissibility. Molecular dynamics simulations and microscale thermophoresis demonstrate that the NSP12 P323L and P323L/G671S mutations stabilize the NSP12-NSP7-NSP8 complex through hydrophobic effects, leading to increased viral RdRp activity. Furthermore, competitive transmissibility assay reveals that reverse genetic (RG)-P323L or RG-P323L/G671S NSP12 outcompetes RG-WT (wild-type) NSP12 for replication in the upper respiratory tract, allowing markedly rapid transmissibility. This suggests that NSP12 P323L or P323L/G671S mutation of SARS-CoV-2 is associated with increased RdRp complex stability and enzymatic activity, promoting efficient transmissibility.
CRIS-Team Scopus Importer:2023-09-15
Keywords: CP: Immunology; ferret; NSP12 mutation; RNA-dependent RNA polymerase; SARS-CoV-2; transmissibility

SARS-CoV-2 worldwide replication drives rapid rise and selection of mutations across the viral genome: a time-course study – potential challenge for vaccines and therapies - Weber, Stefanie; Ramirez, Christina M.; Weiser, Barbara; Burger, Harold; Doerfler, Walter (Embo Molecular Medicine, 2021)
Scientists and the public were alarmed at the first large viral variant of SARS-CoV-2 reported in December 2020. We have followed the time course of emerging viral mutants and variants during the SARS-CoV-2 pandemic in ten countries on four continents. We examined > 383,500 complete SARS-CoV-2 nucleotide sequences in GISAID (Global Initiative of Sharing All Influenza Data) with sampling dates extending until April 05, 2021. These sequences originated from ten different countries: United Kingdom, South Africa, Brazil, United States, India, Russia, France, Spain, Germany, and China. Among the 77 to 100 novel mutations, some previously reported mutations waned and some of them increased in prevalence over time. VUI2012/01 (B.1.1.7) and 501Y.V2 (B.1.351), the so-called UK and South Africa variants, respectively, and two variants from Brazil, 484K.V2, now called P.1 and P.2, increased in prevalence. Despite lockdowns, worldwide active replication in genetically and socio-economically diverse populations facilitated selection of new mutations. The data on mutant and variant SARS-CoV-2 strains provided here comprise a global resource for easy access to the myriad mutations and variants detected to date globally. Rapidly evolving new variant and mutant strains might give rise to escape variants, capable of limiting the efficacy of vaccines, therapies, and diagnostic tests.
CRIS-Team Scopus Importer:2021-06-11
Keywords: high incidence of C to T transitions; numerous new mutations; South African and Brazil variants; time course of SARS-CoV-2 mutant emergence; UK variant B.1.1.7

Schizophrenia dimension-specific antipsychotic drug action and failure in amphetamine-sensitized psychotic-like rats - Uzuneser, Taygun; Schindehuette, Magnus; Dere, Ekrem; von Hörsten, Stephan; Kornhuber, Johannes; Groemer, Teja W.; Müller, Christian P. (European Neuropsychopharmacology, 2018)
Schizophrenic patients suffer from various disruptions in their psyche, mood and cognition, most of which cannot be effectively treated with the available antipsychotic drugs. Some dimensions of the schizophrenia syndrome in man can be mimicked in animals by the amphetamine (AMPH)-sensitization-induced psychosis model. Using such a sensitization procedure, we induced a psychosis-like syndrome in rats, measured as a deficit in sensory information processing and memory deficits. We then investigated the possible restorative effects of continuous treatment with haloperidol (HAL), a typical antipsychotic drug, on distinct dimensions of the syndrome. We found that, continuous infusion of a clinically relevant dose of HAL (0.5 mg/kg/day) effectively ameliorated AMPH-sensitization-induced sensorimotor gating disruptions after seven days of treatment. However, the sensory information processing deficit reappeared after prolonged HAL treatment, suggesting a treatment failure in this dimension of the syndrome. HAL had at this dose little beneficial effects on the cognitive deficits. In contrast, a continuously administered low dose of HAL (0.05 mg/kg/day) successfully attenuated cognitive deficits, but aggravated the sensorimotor gating deficit under both short- or long-term treatment conditions. Post mortem neurochemical analysis revealed that the psychotic-like behavior induced by our manipulations might be explained by altered monoamine levels in distinct brain regions. These findings provide evidence for dissociating and dose-dependent HAL treatment action and failure at different dimensions of schizophrenia.
EVALuna2:36090

Sequence-function analysis of three T cell receptors targeting the HIV-1 p17 - Mummert, Christiane; Hofmann, Christian; Hueckelhoven, Angela G.; Bergmann, Silke; Müller-Schmucker, Sandra; Harrer, Ellen G.; Dörrie, Jan; Schaft, Niels; Harrer, Thomas (2016)
EVALuna2:19635

Sequence-specific activation of the DNA sensor cGAS by Y-form DNA structures as found in primary HIV-1 cDNA - Herzner, Anna-Maria; Hagmann, Cristina Amparo; Goldeck, Marion; Wolter, Steven; Kuebler, Kirsten; Wittmann, Sabine; Gramberg, Thomas; Andreeva, Liudmila; Hopfner, Karl-Peter; Mertens, Christina; Zillinger, Thomas; Jin, Tengchuan; et al. (Nature Immunology, 2015)
Cytosolic DNA that emerges during infection with a retrovirus or DNA virus triggers antiviral type I interferon responses. So far, only double-stranded DNA (dsDNA) over 40 base pairs (bp) in length has been considered immunostimulatory. Here we found that unpaired DNA nucleotides flanking short base-paired DNA stretches, as in stem-loop structures of single-stranded DNA (ssDNA) derived from human immunodeficiency virus type 1 (HIV-1), activated the type I interferon-inducing DNA sensor cGAS in a sequence-dependent manner. DNA structures containing unpaired guanosines flanking short (12- to 20-bp) dsDNA (Y-form DNA) were highly stimulatory and specifically enhanced the enzymatic activity of cGAS. Furthermore, we found that primary HIV-1 reverse transcripts represented the predominant viral cytosolic DNA species during early infection of macrophages and that these ssDNAs were highly immunostimulatory. Collectively, our study identifies unpaired guanosines in Y-form DNA as a highly active, minimal cGAS recognition motif that enables detection of HIV-1 ssDNA.
EVALuna2:8285

Serological evidence of increased susceptibility to varicella-zoster virus reactivation or reinfection in natalizumab-treated patients with multiple sclerosis - Kohlmann, Rebekka; Salmen, Anke; Chan, Andrew; Knabbe, Cornelius; Diekmann, Juergen; Brockmeyer, Norbert; Skaletz-Rorowski, Adriane; Michalik, Claudia; Gold, Ralf; Überla, Klaus (Multiple sclerosis journal, 2015)
Serious adverse drug reactions of disease-modifying drugs in multiple sclerosis (MS) therapy may include enhanced susceptibility to reactivation of neurotropic herpes viruses like varicella-zoster virus (VZV) and the John Cunningham (JC) polyomavirus.Because symptomatic reactivation of these viruses are rare events, we determined the incidence of rises in anti-VZV IgG antibody levels as a potential marker for enhanced susceptibility to subclinical and symptomatic reactivation of neurotropic viruses.Anti-VZV IgG levels were measured in paired serum samples taken 6-8 months apart from natalizumab-treated MS patients, healthy blood donors and human immunodeficiency virus (HIV) infected patients.The incidence of significant rises in anti-VZV IgG levels in natalizumab-treated MS patients was 4.26 per 100 person-years, which was significantly higher than in healthy blood donors. Retrospective evaluation of the available medical records of patients with rises of anti-VZV IgG levels did not reveal herpes zoster (i.e. shingles) manifestations.The increased incidence of significant rises of anti-VZV IgG levels in natalizumab-treated MS patients might indicate an association of natalizumab treatment of MS with an elevated risk of a subclinical VZV reactivation and/or reinfection events. Whether this is predictive of an increased risk of herpes zoster or even symptomatic reactivation of other neurotropic viruses remains to be determined in larger prospective studies.
EVALuna2:8294

Severe bornavirus-encephalitis presenting as Guillain–Barré-syndrome - Coras, Roland; Korn, Klaus; Kürten, Stefanie; Huttner, Hagen; Enßer, Armin (Acta Neuropathologica, 2019)
CRIS-Team Scopus Importer:2019-06-04

'Shared-Hook' and 'Changed-Hook' Binding Activities of Herpesviral Core Nuclear Egress Complexes Identified by Random Mutagenesis - Lösing, Josephine; Haege, Sigrun; Schütz, Martin; Wagner, Sabrina; Wardin, Julia; Sticht, Heinrich; Marschall, Manfred (Cells, 2022)
Herpesviruses replicate their genomes and assemble their capsids in the host cell nucleus. To progress towards morphogenesis in the cytoplasm, herpesviruses evolved the strategy of nuclear egress as a highly regulated process of nucleo-cytoplasmic capsid transition. The process is conserved among alpha-, beta- and gamma-herpesviruses and involves the formation of a core and multicomponent nuclear egress complex (NEC). Core NEC is assembled by the interaction between the nucleoplasmic hook protein, i.e., pUL53 (human cytomegalovirus, HCMV), and the integral membrane-associated groove protein, i.e., pUL50. Our study aimed at the question of whether a panherpesviral NEC scaffold may enable hook-into-groove interaction across herpesviral subfamilies. For this purpose, NEC constructs were generated for members of all three subfamilies and analyzed for multi-ligand interaction using a yeast two-hybrid (Y2H) approach with randomized pUL53 mutagenesis libraries. The screening identified ten library clones displaying cross-viral shared hook-into-groove interaction. Interestingly, a slightly modified Y2H screening strategy provided thirteen further changed-hook pUL53 clones having lost parental pUL50 interaction but gained homolog interaction. In addition, we designed a sequence-predicted hybrid construct based on HCMV and Epstein-Barr virus (EBV) core NEC proteins and identified a cross-viral interaction phenotype. Confirmation was provided by applying protein-protein interaction analyses in human cells, such as coimmunoprecipitation settings, confocal nuclear rim colocalization assays, and HCMV Delta UL53 infection experiments with pUL53-complementing cells. Combined, the study provided the first examples of cross-viral NEC interaction patterns and revealed a higher yield of human cell-confirmed binding clones using a library exchange rate of 3.4 than 2.7. Thus, the study provides improved insights into herpesviral NEC protein binding specificities of core NEC formation. This novel information might be exploited to gain a potential target scaffold for the development of broadly acting NEC-directed inhibitory small molecules.
CRIS-Team WoS Importer:2023-01-27

Sialic acids on B cells are crucial for their survival and provide protection against apoptosis - Linder, Alexandra; Schmidt, Michael; Hitschfel, Julia; Abeln, Markus; Schneider, Pascal; Gerardy-Schahn, Rita; Münster-Kühnel, Anja K.; Nitschke, Lars (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Sialic acids (Sias) on the B cell membrane are involved in cell migration, in the control of the complement system and, as sialic acid–binding immunoglobulin-like lectin (Siglec) ligands, in the regulation of cellular signaling. We studied the role of sialoglycans on B cells in a mouse model with B cell–specific deletion of cytidine monophosphate sialic acid synthase (CMAS), the enzyme essential for the synthesis of sialoglycans. Surprisingly, these mice showed a severe B cell deficiency in secondary lymphoid organs. Additional depletion of the complement factor C3 rescued the phenotype only marginally, demonstrating a complement-independent mechanism. The B cell survival receptor BAFF receptor was not up-regulated, and levels of activated caspase 3 and processed caspase 8 were high in B cells of Cmas-deficient mice, indicating ongoing apoptosis. Overexpressed Bcl-2 could not rescue this phenotype, pointing to extrinsic apoptosis. These results show that sialoglycans on the B cell surface are crucial for B cell survival by counteracting several death-inducing pathways.
CRIS-Team Scopus Importer:2022-07-22
Keywords: B cell development; extrinsic apoptosis; sialic acids; Siglec

Signal hotspot mutations in SARS-CoV-2 genomes evolve as the virus spreads and actively replicates in different parts of the world - Weber, Stefanie; Ramirez, Christina; Doerfler, Walter (Virus Research, 2020)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) was first identified in Wuhan, China late in 2019. Nine months later (Sept. 23, 2020), the virus has infected > 31.6 million people around the world and caused > 971.000 (3.07 %) fatalities in 220 countries and territories. Research on the genetics of the SARS-CoV-2 genome, its mutants and their penetrance can aid future defense strategies. By analyzing sequence data deposited between December 2019 and end of May 2020, we have compared nucleotide sequences of 570 SARS-CoV-2 genomes from China, Europe, the US, and India to the sequence of the Wuhan isolate. During worldwide spreading among human populations, at least 10 distinct hotspot mutations had been selected and found in up to > 80 % of viral genomes. Many of these mutations led to amino acid exchanges in replication-relevant viral proteins. Mutations in the SARS-CoV-2 genome would also impinge upon the secondary structure of the viral RNA molecule and its repertoire of interactions with essential cellular and viral proteins. The increasing frequency of SARS-CoV-2 mutation hotspots might select for dangerous viral pathogens. Alternatively, in a 29.900 nucleotide-genome, there might be a limit to the number of mutable and selectable sites which, when exhausted, could prove disadvantageous to viral survival. The speed, at which novel SARS-CoV-2 mutants are selected and dispersed around the world, could pose problems for the development of vaccines and therapeutics.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Consequences for secondary and tertiary structures of viral RNA; Impact on replication-relevant viral proteins; Questions about immunogenesis and vaccine development; Selection of viral hotspot mutations; Sequence comparisons between 570 viral genomes to Wuhan isolate; Severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2)

Significance of altered PD-L1 expression in tumor tissue of oral squamous cell carcinomas - Weber, Manuel; Wehrhan, Falk; Baran, Christoph; Agaimy, Abbas; Buettner-Herold, M.; Preidl, Raimund; Neukam, Friedrich Wilhelm; Ries, Jutta (2018)
EVALuna2:34231

Silhouette-Length-Scaled Gait Parameters for Motor Functional Analysis in Mice and Rats - Timotius, Ivanna; Moceri, Sandra; Plank, Anne-Christine; Habermeyer, Johanna; Canneva, Fabio; Winkler, Jürgen; Klucken, Jochen; Casadei, Nicolas; Riess, Olaf; Eskofier, Björn; von Hörsten, Stephan (eNeuro, 2019)
Gait analysis of transgenic mice and rats modeling human diseases often suffers from the condition that those models exhibit genotype-driven differences in body size, weight, and length. Thus, we hypothesized that scaling by the silhouette length improves the reliability of gait analysis allowing normalization for individual body size differences. Here, we computed video-derived silhouette length and area parameters from a standard markerless gait analysis system using image-processing techniques. By using length- and area-derived data along with body weight and age, we systematically scaled individual gait parameters. We compared these different scaling approaches and report here that normalization for silhouette length improves the validity and reliability of gait analysis in general. The application of this silhouette length scaling to transgenic Huntington disease mice and Parkinson´s disease rats identifies the remaining differences reflecting more reliable, body length-independent motor functional differences. Overall, this emphasizes the need for silhouette-length-based intra-assay scaling as an improved standard approach in rodent gait analysis.<br
Keywords: CatWalk; gait; Huntington; normalization; Parkinson; scaling

Siponimod (BAF-312) Attenuates Perihemorrhagic Edema And Improves Survival in Experimental Intracerebral Hemorrhage - Bobinger, Tobias; Manaenko, Anatol; Burkardt, Petra; Beuscher, Vanessa; Sprügel, Maximilian; Röder, Sebastian; Bäuerle, Tobias; Seyler, Lisa; Nagel, Armin Michael; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; et al. (Stroke, 2019)
Background and Purpose- Perihemorrhagic edema (PHE) is associated with poor outcome after intracerebral hemorrhage (ICH). Infiltration of immune cells is considered a major contributor of PHE. Recent studies suggest that immunomodulation via S1PR (sphingosine-1-phosphate receptor) modulators improve outcome in ICH. Siponimod, a selective modulator of sphingosine 1-phosphate receptors type 1 and type 5, demonstrated an excellent safety profile in a large study of patients with multiple sclerosis. Here, we investigated the impact of siponimod treatment on perihemorrhagic edema, neurological deficits, and survival in a mouse model of ICH. Methods- ICH was induced by intracranial injection of 0.075 U of bacterial collagenase in 123 mice. Mice were randomly assigned to different treatment groups: vehicle, siponimod given as a single dosage 30 minutes after the operation or given 3× for 3 consecutive days starting 30 minutes after operation. The primary outcome of our study was evolution of PHE measured by magnetic resonance-imaging on T2-maps 72 hours after ICH, secondary outcomes included evolution of PHE 24 hours after ICH, survival and neurological deficits, as well as effects on circulating blood cells and body weight. Results- Siponimod significantly reduced PHE measured by magnetic resonance imaging (P=0.021) as well as wet-dry method (P=0.04) 72 hours after ICH. Evaluation of PHE 24 hours after ICH showed a tendency toward attenuated brain edema in the low-dosage group (P=0.08). Multiple treatments with siponimod significantly improved neurological deficits measured by Garcia Score (P=0.03). Survival at day 10 was improved in mice treated with multiple dosages of siponimod (P=0.037). Mice treated with siponimod showed a reduced weight loss after ICH (P=0.036). Conclusions- Siponimod (BAF-312) attenuated PHE after ICH, increased survival, and reduced ICH-induced sensorimotor deficits in our experimental ICH-model. Findings encourage further investigation of inflammatory modulators as well as the translation of BAF-312 to a human study of ICH patients.
EVALuna2:204480

Smaller, Stronger, More Stable: Peptide Variants of a SARS-CoV-2 Neutralizing Miniprotein - Weißenborn, Lucas; Richel, Elie; Hueseman, Helena; Welzer, Julia; Beck, Silvan; Schäfer, Simon; Sticht, Heinrich; Überla, Klaus; Eichler, Jutta (International Journal of Molecular Sciences, 2022)
Based on the structure of a de novo designed miniprotein (LCB1) in complex with the receptor binding domain (RBD) of the SARS-CoV-2 spike protein, we have generated and characterized truncated peptide variants of LCB1, which present only two of the three LCB1 helices, and which fully retained the virus neutralizing potency against different SARS-CoV-2 variants of concern (VOC). This antiviral activity was even 10-fold stronger for a cyclic variant of the two-helix peptides, as compared to the full-length peptide. Furthermore, the proteolytic stability of the cyclic peptide was substantially improved, rendering it a better potential candidate for SARS-CoV-2 therapy. In a more mechanistic approach, the peptides also served as tools to dissect the role of individual mutations in the RBD for the susceptibility of the resulting virus variants to neutralization by the peptides. As the peptides reported here were generated through chemical synthesis, rather than recombinant protein expression, they are amenable to further chemical modification, including the incorporation of a wide range of non-proteinogenic amino acids, with the aim to further stabilize the peptides against proteolytic degradation, as well as to improve the strength, as well the breadth, of their virus neutralizing capacity.
CRIS-Team WoS Importer:2022-06-24
Keywords: SARS-CoV-2; virus; peptides; structure-based design; synthetic peptides; peptide mimics

Small oral squamous cell carcinomas with nodal lymphogenic metastasis show increased infiltration of M2 polarized macrophages - An immunohistochemical analysis - Weber, Manuel; Büttner, Maike; Hyckel, Peter; Moebius, Patrick; Distel, Luitpold; Ries, Jutta; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Journal of Cranio-Maxillofacial Surgery, 2014)
In solid malignancies the influence of immunological parameters - especially of macrophages - on invasiveness, metastatic potential and prognosis has been shown. There are no studies quantitatively analysing the macrophage polarization in oral squamous cell carcinoma (oscc). The aim of this study was to correlate macrophage polarization in the epithelial and stromal compartment of oscc with histopathologic parameters.T1 and T2 oscc samples (n = 34) were used. Automated immunohistochemical staining detected CD68, CD11c, CD163 and MRC1 positive cells. All samples were completely digitalized using whole slide imaging and the number of stained cells per area was assessed quantitatively.Primary tumours with lymphogenic metastasis (N+) showed a significantly (p < 0.05) increased count of CD68, CD11c, CD163 and MRC1 positive cells in the epithelial fraction compared to N0 tumours. The ratio of CD163 positive cells (M2 macrophages) to CD68 positive cells (M1 and M2 macrophages) was significantly (p < 0.05) increased in N+ tumours.An increased macrophage infiltration and an increased M2 polarization in primary oral squamous cell carcinomas with lymphogenic metastasis was shown. Macrophages that migrated into the epithelial tumour fraction seem to be of special biological importance. The results indicate a central role of macrophages in the progression of oscc.
EVALuna2:18151

Small ubiquitin-related modifier (SUMO) pathway-mediated enhancement of human cytomegalovirus replication correlates with a recruitment of SUMO-1/3 proteins to viral replication compartments - Scherer, Myriam; Reuter, Nina; Wagenknecht, Nadine; Otto, Victoria; Sticht, Heinrich; Stamminger, Thomas (Journal of General Virology, 2013)
Recent studies have suggested that the small ubiquitin-related modifier (SUMO) conjugation pathway may play an important role in intrinsic antiviral resistance and thus for repression of herpesviral infections. In particular, it was shown that the herpes simplex virus type-1 regulatory protein ICP0 acts as a SUMO-targeted ubiquitin ligase (STUbL), inducing the widespread degradation of SUMO-conjugated proteins during infection. As the IE1 protein of human cytomegalovirus (HCMV) is known to mediate a de-SUMOylation of PML, we investigated whether HCMV uses a similar mechanism to counteract intrinsic antiviral resistance. We generated primary human fibroblasts stably expressing FLAG-SUMO-1 or FLAG-SUMO-3 and analysed the SUMOylation pattern after HCMV infection or isolated IE1 expression. However, Western blot experiments did not reveal a global loss of SUMO conjugates, either in HCMV-infected or in IE1-expressing cells, arguing against a function of IE1 as an STUbL. Interestingly, we observed that FLAG-SUMO-1 and FLAG-SUMO-3, subsequent to IE1-mediated promyelocytic leukemia protein (PML) de-SUMOylation and the consequent disruption of PML nuclear bodies, were recruited into viral replication compartments. This raised the question of whether FLAG-SUMO-1/3 might promote HCMV replication. Intriguingly, overexpression of FLAG-SUMO-1/3 enhanced accumulation of viral DNA, which correlated with an increase in viral replication and in virus particle release. Together, these data indicate that HCMV, in contrast to other herpesviruses, has evolved subtle mechanisms enabling it to utilize the SUMO conjugation pathway for its own benefit, resulting in an overall positive effect of SUMO conjugation for HCMV replication.
EVALuna2:8191

SMARCB1(INI1)-deficient sinonasal basaloid carcinoma: a novel member of the expanding family of SMARCB1-deficient neoplasms - Agaimy, Abbas; Koch, Michael; Lell, Michael; Semrau, Sabine; Dudek, Wojciech; Wachter, David; Knöll, Antje; Iro, Heinrich; Haller, Florian; Hartmann, Arndt (American Journal of Surgical Pathology, 2014)
Poorly differentiated sinonasal carcinomas are a heterogenous group of aggressive neoplasms that encompasses squamous cell carcinoma including basaloid variant, lymphoepithelial carcinoma, sinonasal undifferentiated carcinoma, and neuroendocrine-type small cell carcinoma. We herein describe 3 cases of a hitherto unreported variant combining features of basaloid carcinoma with variable intermingled rhabdoid cells. Patients were 2 women (aged 28 and 35) and a man (52 y) who presented with sinonasal masses. All had advanced local disease with bone involvement (pT4). None had a history of irradiation or a family history of rhabdoid tumors. Treatment was surgery and adjuvant chemoradiation. One patient developed liver, lung, pleural, and pericardial metastases (63 mo) and is currently (70 mo) alive under palliative treatment. Another developed recurrent cervical lymph node metastases and died of disease 8.5 years later. The youngest patient was disease-free at last follow-up 7 years later. Histologic features were very similar in all 3 cases and showed intimate admixture of compact basaloid cell nests with peripheral palisading, perivascular pseudorosettes, and a few scattered rhabdoid cells. Rhabdoid cells were more extensive in the metastasis in 1 case but formed a minor inconspicuous component in the primary tumors in all cases. Striking features common to all cases were (1) basaloid "blue" appearance at low power, (2) papilloma-like exophytic component, (3) extensive pagetoid surface growth with prominent denuding features, and (4) replacement of underlying mucous glands mimicking an inverted papilloma. Clear-cut origin from benign papilloma and overt squamous differentiation were lacking. Diffuse (2) or partial (1) p16 expression was noted, but all cases lacked human papillomavirus DNA by molecular tests. In situ hybridization was negative for Epstein-Barr virus. Immunohistochemistry showed diffuse expression of pancytokeratin. CK5 and vimentin showed intermingling of CK5/vimentin basaloid and CK5/vimentin rhabdoid cells. Complete loss of nuclear SMARCB1 expression was seen in all cases including also the denuding carcinoma in situ-like surface lesions. To our knowledge, this variant of sinonasal carcinoma has not been reported before. The identical features in all 3 cases suggest a specific disease rather than a nonspecific dedifferentiated phenotype. Awareness of this rare variant and thus reporting of additional cases is necessary for defining its full morphologic and biological spectrum.
EVALuna2:6600

SMYD2 Inhibition Downregulates TMPRSS2 and Decreases SARS-CoV-2 Infection in Human Intestinal and Airway Epithelial Cells - Yu, Yidong; Herrmann, Alexandra; Thonn, Veronika; Cordsmeier, Arne; Neurath, Markus; Enßer, Armin; Becker, Christoph (Cells, 2022)
The COVID-19 pandemic caused by SARS-CoV-2 has lasted for more than two years. Despite the presence of very effective vaccines, the number of virus variants that escape neutralizing antibodies is growing. Thus, there is still a need for effective antiviral treatments that target virus replication independently of the circulating variant. Here, we show for the first time that deficiency or pharmacological inhibition of the cellular lysine-methyltransferase SMYD2 decreases TMPRSS2 expression on both mRNA and protein levels. SARS-CoV-2 uses TMPRSS2 for priming its spike protein to infect target cells. Treatment of cultured cells with the SMYD2 inhibitors AZ505 or BAY598 significantly inhibited viral replication. In contrast, treatment of Vero E6 cells, which do not express detectable amounts of TMPRSS2, had no effect on SARS-CoV-2 infection. Moreover, by generating a recombinant reporter virus that expresses the spike protein of the Delta variant of SARS-CoV-2, we demonstrate that BAY598 exhibits similar antiviral activity against this variant of concern. In summary, SMYD2 inhibition downregulates TMPRSS2 and blocks viral replication. Targeting cellular SMYD2 represents a promising tool to curtail SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2022-04-29
Keywords: antiviral treatment; AZ505; BAY598; COVID-19; SARS-CoV-2; SMYD2; TMPRSS2

Soluble CD83 modulates human-monocyte-derived macrophages toward alternative phenotype, function, and metabolism. - Peckert-Maier, Katrin; Wild, Andreas; Sprißler, Laura; Fuchs, Maximilian; Beck, Philipp; Auger, Jean-Philippe; Sinner, Pia; Strack, Astrid; Mühl-Zürbes, Petra; Ramadan, Ntilek; Kunz, Meik; Krönke, Gerhard; et al. (Frontiers in Immunology, 2023)
Alterations in macrophage (Mφ) polarization, function, and metabolic signature can foster development of chronic diseases, such as autoimmunity or fibrotic tissue remodeling. Thus, identification of novel therapeutic agents that modulate human Mφ biology is crucial for treatment of such conditions. Herein, we demonstrate that the soluble CD83 (sCD83) protein induces pro-resolving features in human monocyte-derived Mφ biology. We show that sCD83 strikingly increases the expression of inhibitory molecules including ILT-2 (immunoglobulin-like transcript 2), ILT-4, ILT-5, and CD163, whereas activation markers, such as MHC-II and MSR-1, were significantly downregulated. This goes along with a decreased capacity to stimulate alloreactive T cells in mixed lymphocyte reaction (MLR) assays. Bulk RNA sequencing and pathway analyses revealed that sCD83 downregulates pathways associated with pro-inflammatory, classically activated Mφ (CAM) differentiation including HIF-1A, IL-6, and cytokine storm, whereas pathways related to alternative Mφ activation and liver X receptor were significantly induced. By using the LXR pathway antagonist GSK2033, we show that transcription of specific genes (e.g., PPARG, ABCA1, ABCG1, CD36) induced by sCD83 is dependent on LXR activation. In summary, we herein reveal for the first time mechanistic insights into the modulation of human Mφ biology by sCD83, which is a further crucial preclinical study for the establishment of sCD83 as a new therapeutical agent to treat inflammatory conditions.
EVALuna2:549687

Soluble DPP4 originates in part from bone marrow cells and not from the kidney - Wang, Zhendi; Grigo, Christina; Steinbeck, Julia; von Hörsten, Stephan; Amann, Kerstin Ute; Daniel, Christoph (Peptides, 2014)
Dipeptidyl peptidase 4 (DPP4) is known to inactivate incretins as well as important chemokines and neuropeptides. DPP4 is expressed as a transmembrane protein but also occurs as a soluble enzyme circulating in the blood. However, the origin of the soluble DPP4 (sDPP4) is still unknown. In this study, DPP4 activity was quantified in plasma and extracted from different rat organs. Then, in order to see if the kidney or the bone marrow was the source of sDPP4, kidney or bone marrow transplantation was performed between wildtype (wt) Dark Agouti (DA) and DPP4 deficient congenic rats (n=6-9). Kidney was verified to have the highest DPP4 activity, followed by spleen and lung. In the following three weeks after successful kidney transplantation only transient trace plasma DPP4 activity was detected in DPP4 deficient rats receiving wt kidneys. In addition, DPP4 activity was not diminished in DA wt rats receiving DPP4 deficient kidneys. Both findings indicated that sDPP4 did not originate from the kidney. In contrast, 43±14% (compared to wt) sDPP4 activity was detected in the plasma of DPP4 deficient DA rats that were reconstituted with wt bone marrow cells. Not only leukocyte but also macrophage subpopulations express DPP4 in bone marrow as well as in blood as assessed by flow cytometry. Thus, bone marrow derived cells but not the kidney represent at least one source of sDPP4. And leukocyte or macrophage subpopulations could be potential candidates.
EVALuna2:3742

Sox10 is an active nucleocytoplasmic shuttle protein, and shuttling is crucial for Sox10-mediated transactivation - Wegner, Michael; Stamminger, Thomas; Glaser, Gabriele; et al. (Molecular and Cellular Biology, 2002)
Sox10 belongs to a family of transcription regulators characterized by a DNA-binding domain known as the HMG box. It plays fundamental roles in neural crest development, peripheral gliogenesis, and terminal differentiation of oligodendrocytes. In accord with its function as transcription factor, Sox10 contains two nuclear localization signals and is most frequently detected in the nucleus. In this study, we report that Sox10 is an active nucleocytoplasmic shuttle protein, competent of both entering and exiting the nucleus. We identified a functional Rev-type nuclear export signal within the DNA-binding domain of Sox10. Mutational inactivation of this nuclear export signal or treatment of cells with the CRM1-specific export inhibitor leptomycin B inhibited nuclear export and consequently nucleocytoplasmic shuttling of Sox10. Importantly, the inhibition of the nuclear export of Sox10 led to decreased transactivation of transfected reporters and endogenous target genes, arguing that continuous nucleocytoplasmic shuttling is essential for the function of Sox10. To our knowledge this is the first time that nuclear export has been reported and shown to be functionally relevant for any Sox protein.
UnivIS-Import:2015-03-09:Pub.2002.med.IB.LPCIPDBI.sox10i

Specific antibody deficiency and autoinflammatory disease extend the clinical and immunological spectrum of heterozygous NFKB1 loss-of-function mutations in humans - Schipp, Cyrill; Nabhani, Schafiq; Bienemann, Kirsten; Simanovsky, Natalia; Kfir-Erenfeld, Shlomit; Assayag-Asherie, Nathalie; Oommen, Prasad T.; Revel-Vilk, Shoshana; Hoenscheid, Andrea; Gombert, Michael; Ginzel, Sebastian; Schaefer, Daniel; et al. (Haematologica, 2016)
EVALuna2:32859

Specific residues of a conserved domain in the N terminus of the human cytomegalovirus pUL50 protein determine its intranuclear interaction with pUL53 - Milbradt, Jens; Auerochs, Sabrina; Sevvana, Madhumati; Muller, Yves; Sticht, Heinrich; Marschall, Manfred (Journal of Biological Chemistry, 2012)
Herpesviral capsids are assembled in the host cell nucleus and are subsequently translocated to the cytoplasm. During this process it has been demonstrated that the human cytomegalovirus proteins pUL50 and pUL53 interact and form, together with other viral and cellular proteins, the nuclear egress complex at the nuclear envelope. In this study we provide evidence that specific residues of a conserved N-terminal region of pUL50 determine its intranuclear interaction with pUL53. In silico evaluation and biophysical analyses suggested that the conserved region forms a regular secondary structure adopting a globular fold. Importantly, site-directed replacement of individual amino acids by alanine indicated a strong functional influence of specific residues inside this globular domain. In particular, mutation of the widely conserved residues Glu-56 or Tyr-57 led to a loss of interaction with pUL53. Consistent with the loss of binding properties, mutants E56A and Y57A showed a defective function in the recruitment of pUL53 to the nuclear envelope in expression plasmid-transfected and human cytomegalovirus-infected cells. In addition, in silico analysis suggested that residues 3-20 form an amphipathic ?-helix that appears to be conserved among Herpesviridae. Point mutants revealed a structural role of this N-terminal ?-helix for pUL50 stability rather than a direct role in the binding of pUL53. In contrast, the central part of the globular domain including Glu-56 and Tyr-57 is directly responsible for the functional interaction with pUL53 and thus determines formation of the basic nuclear egress complex.
EVALuna2:8148

Spectrum bias and individual strengths of SARS-CoV-2 serological tests–A population-based evaluation - Einhauser, Sebastian; Peterhoff, David; Niller, Hans Helmut; Beileke, Stephanie; Günther, Felix; Steininger, Philipp; Burkhardt, Ralph; Heid, Iris M.; Pfahlberg, Annette Bettina; Überla, Klaus; Gefeller, Olaf; Wagner, Ralf (Diagnostics, 2021)
Antibody testing for determining the SARS-CoV-2 serostatus was rapidly introduced in early 2020 and since then has been gaining special emphasis regarding correlates of protection. With limited access to representative samples with known SARS-CoV-2 infection status during the initial period of test development and validation, spectrum bias has to be considered when moving from a “test establishment setting” to population-based settings, in which antibody testing is currently implemented. To provide insights into the presence and magnitude of spectrum bias and to estimate performance measures of antibody testing in a population-based environment, we compared SARS-CoV-2 neutralization to a battery of serological tests and latent class analyses (LCA) in a subgroup (n = 856) of the larger population based TiKoCo-19 cohort (n = 4185). Regarding spectrum bias, we could proof notable differences in test sensitivities and specificities when moving to a population-based setting, with larger effects visible in earlier registered tests. While in the population-based setting the two Roche ELECSYS anti-SARS-CoV-2 tests outperformed every other test and even LCA regarding sensitivity and specificity in dichotomous testing, they didn’t provide satisfying quantitative correlation with neutralization capacity. In contrast, our in-house anti SARS-CoV-2-Spike receptor binding domain (RBD) IgG-ELISA (enzyme-linked-immunosorbant assay) though inferior in dichotomous testing, provided satisfactory quantitative correlation and may thus represent a better correlate of protection. In summary, all tests, led by the two Roche tests, provided sufficient accuracy for dichotomous identification of neutralizing sera, with increasing spectrum bias visible in earlier registered tests, while the majority of tests, except the RBD-ELISA, didn’t provide satisfactory quantitative correlations.
CRIS-Team Scopus Importer:2021-10-29
Keywords: ECLIA; ELISA; Neutralization; SARS-CoV-2; Sensitivity; Serology; Specificity; Spectrum bias; Test accuracy

Spike and nsp6 are key determinants of SARS-CoV-2 Omicron BA.1 attenuation - Chen, Da Yuan; Chin, Chue Vin; Kenney, Devin; Tavares, Alexander H.; Khan, Nazimuddin; Conway, Hasahn L.; Liu, Guan Qun; Choudhary, Manish C.; Gertje, Hans P.; O’Connell, Aoife K.; Adams, Scott; Kotton, Darrell N.; et al. (Nature, 2023)
The SARS-CoV-2 Omicron variant is more immune evasive and less virulent than other major viral variants that have so far been recognized1–12. The Omicron spike (S) protein, which has an unusually large number of mutations, is considered to be the main driver of these phenotypes. Here we generated chimeric recombinant SARS-CoV-2 encoding the S gene of Omicron (BA.1 lineage) in the backbone of an ancestral SARS-CoV-2 isolate, and compared this virus with the naturally circulating Omicron variant. The Omicron S-bearing virus robustly escaped vaccine-induced humoral immunity, mainly owing to mutations in the receptor-binding motif; however, unlike naturally occurring Omicron, it efficiently replicated in cell lines and primary-like distal lung cells. Similarly, in K18-hACE2 mice, although virus bearing Omicron S caused less severe disease than the ancestral virus, its virulence was not attenuated to the level of Omicron. Further investigation showed that mutating non-structural protein 6 (nsp6) in addition to the S protein was sufficient to recapitulate the attenuated phenotype of Omicron. This indicates that although the vaccine escape of Omicron is driven by mutations in S, the pathogenicity of Omicron is determined by mutations both in and outside of the S protein.
CRIS-Team Scopus Importer:2023-02-24

Spike residue 403 affects binding of coronavirus spikes to human ACE2 - Zech, Fabian; Schniertshauer, Daniel; Jung, Christoph; Herrmann, Alexandra; Cordsmeier, Arne; Xie, Qinya; Nchioua, Rayhane; Bozzo, Caterina Prelli; Volcic, Meta; Koepke, Lennart; Mueller, Janis A.; Krueger, Jana; et al. (Nature Communications, 2021)
The bat sarbecovirus RaTG13 is a close relative of SARS-CoV-2, the cause of the COVID-19 pandemic. However, this bat virus was most likely unable to directly infect humans since its Spike (S) protein does not interact efficiently with the human ACE2 receptor. Here, we show that a single T403R mutation increases binding of RaTG13 S to human ACE2 and allows VSV pseudoparticle infection of human lung cells and intestinal organoids. Conversely, mutation of R403T in the SARS-CoV-2 S reduces pseudoparticle infection and viral replication. The T403R RaTG13 S is neutralized by sera from individuals vaccinated against COVID-19 indicating that vaccination might protect against future zoonoses. Our data suggest that a positively charged amino acid at position 403 in the S protein is critical for efficient utilization of human ACE2 by S proteins of bat coronaviruses. This finding could help to better predict the zoonotic potential of animal coronaviruses.
CRIS-Team Scopus Importer:2021-12-10

Stable DNA methylation boundaries and expanded trinucleotide repeats: role of DNA insertions - Naumann, Anja; Kraus, Cornelia; Hoogeveen, Andre; Ramirez, Christina M.; Doerfler, Walter (Journal of Molecular Biology, 2014)
The human genome segment upstream of the FMR1 (fragile X mental retardation 1) gene (Xq27.3) contains several genetic signals, among them is a DNA methylation boundary that is located 65-70 CpGs upstream of the CGG repeat. In fragile X syndrome (FXS), the boundary is lost, and the promoter is inactivated by methylation spreading. Here we document boundary stability in spite of critical expansions of the CGG trinucleotide repeat in male or female premutation carriers and in high functioning males (HFMs). HFMs carry a full CGG repeat expansion but exhibit an unmethylated promoter and lack the FXS phenotype. The boundary is also stable in Turner (45, X) females. A CTCF-binding site is located slightly upstream of the methylation boundary and carries a unique G-to-A polymorphism (single nucleotide polymorphism), which occurs 3.6 times more frequently in genomes with CGG expansions. The increased frequency of this single nucleotide polymorphism might have functional significance. In CGG expansions, the CTCF region does not harbor additional mutations. In FXS individuals and often in cells transgenomic for EBV (Epstein Barr Virus) DNA or for the telomerase gene, the large number of normally methylated CpGs in the far-upstream region of the boundary is decreased about 4-fold. A methylation boundary is also present in the human genome segment upstream of the HTT (huntingtin) promoter (4p16.3) and is stable both in normal and Huntington disease chromosomes. Hence, the vicinity of an expanded repeat does not per se compromise methylation boundaries. Methylation boundaries exert an important function as promoter safeguards.
EVALuna2:8223

STAT6-induced production of mucus and resistin-like molecules in lung Club cells does not protect against helminth or influenza A virus infection - Ruhl, Andreas; Vieira Antao, Ana Isabel; Dietschmann, Axel; Radtke, Daniel; Tenbusch, Matthias; Vöhringer, David (European Journal of Immunology, 2023)
Airway epithelial cells contribute to a variety of lung diseases including allergic asthma, where IL-4 and IL-13 promote activation of the transcription factor STAT6. This leads to goblet cell hyperplasia and the secretion of effector molecules by epithelial cells. However, the specific effect of activated STAT6 in lung epithelial cells is only partially understood. Here, we created a mouse strain to selectively investigate the role of constitutively active STAT6 in Club cells, a subpopulation of airway epithelial cells. CCSP-Cre_STAT6vt mice and bronchiolar organoids derived from these show an enhanced expression of the chitinase-like protein Chil4 (Ym2) and resistin-like molecules (Relm-α, -β, -γ). In addition, goblet cells of these mice spontaneously secrete mucus into the bronchi. However, the activated epithelium resulted neither in impaired lung function nor conferred a protective effect against the migrating helminth Nippostrongylus brasiliensis. Moreover, CCSP-Cre_STAT6vt mice showed similar allergic airway inflammation induced by live conidia of the fungus Aspergillus fumigatus and similar recovery after influenza A virus infection compared to control mice. Together these results highlight that STAT6 signaling in Club cells induces the secretion of Relm proteins and mucus without impairing lung function, but this is not sufficient to confer protection against helminth or viral infections.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Aspergillus fumigatus; Club cell; Influenza a virus; Mucus; Nippostrongylus brasilienis; Relm-α; STAT6

Stellenwert der Vakzine gegen humane Papillomaviren in der Prävention von Krebserkrankungen - Schulmeyer, Carla; Knöll, Antje; Iro, Heinrich; Müller, Susanna; Beckmann, Matthias (Onkologe, 2021)
Background: Human papillomaviruses (HPV) are the most common causes of genital viral infections. HPV infections usually heal, but can also persist and thus cause lesions of different grades. Infections with high-risk HPV types (hrHPV) 16, 18, 31, 33, 45, 52, and 58 are responsible for causing 90% of cervical cancer cases in Europe. Head and neck cancer, vaginal and vulvar cancer and their precursors, as well as penile or anal cancer may also be associated with hrHPV. Objectives: The aim of this work is to demonstrate the importance of HPV vaccines in the prevention of genital as well as head and neck cancers. Materials and methods: This work is based on a selective literature search in the PubMed database on the correlation between HPV vaccines and HPV-associated cancer. Results: HPV vaccination ensures a high level of protection against precancerous lesions and cancer of the cervix, vagina, vulva, anus, and genital warts. Conclusions: Results of HPV vaccination and its positive effects on head and neck tumors is expected within the next few decades.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Condylomata acuminata; HPV; Oropharyngeal neoplasms; Sexually transmitted diseases; Uterine cervical neoplasms

Stimulatory effects of human cytomegalovirus tegument protein pp71 lead to increased expression of CCL2 (monocyte chemotactic protein-1) during infection - Naing, Zin; Webel, Rike; Hamilton, Stuart; Schmeiser, Cathrin; Scott, Gillian; Marschall, Manfred; Rawlinson, William (Journal of General Virology, 2015)
Human cytomegalovirus (CMV) is the most common infectious cause of congenital birth defects in developed countries. Studies of infected amniotic fluid and placentae show CMV infection leads to a pro-inflammatory shift in cytokine profiles with implications for pathogenesis of foetal disease. ELISA, immunofluorescence and real-time-PCR assays were used to investigate CCL2 (monocyte chemotactic protein-1) and TNF-? changes following CMV infection of human fibroblasts, as well as following transient expression of CMV gene products in HeLa cells. Infection of human fibroblasts with CMV AD169 resulted in increased cytoplasmic and extracellular expression of CCL2 during early stages of infection, followed by marked downregulation of the chemokine at late times. Induction of CCL2 was not observed with CMV clinical strain Merlin, consistent with the postulated immune-evasion potential of this genetically intact WT strain. Comparison between live and UV-irradiated virus infections showed that changes in CCL2 levels were a direct response to active CMV replication. There were no significant changes in TNF-? expression during a parallel time-course of CMV infection. In transient transfection assays, overexpression of CMV tegument protein pp71 resulted in intracellular and extracellular upregulation of CCL2 protein. mRNA analysis showed that pp71-induced elevation in CCL2 was mediated through transcriptional upregulation. The data showed that CMV-induced upregulation of CCL2 during early stages of infection was mediated, at least in part, by stimulation of viral pp71, which may contribute to viral pathogenesis through enhanced virus dissemination.
EVALuna2:8267

Strong induction of 4-1BB, a growth and survival promoting costimulatory receptor, in HTLV-1-infected cultured and patients' T cells by the viral Tax oncoprotein - Pichler, Klemens; Kattan, Tarek; Gentzsch, Juliane; Kreß, Andrea; Taylor, Graham P.; Bangham, Charles R. M.; Grassmann, Ralph (Blood, 2008)
Human T-cell leukemia virus type 1 (HTLV1), the cause of adult T-cell leukemia, stimulates the growth of infected T cells in cultures and in nonleukemic patients. In the latter, HTLV-1 is found in long-term persisting T-cell clones. The persistence of normal T cells is controlled by the growth-stimulating and antiapoptotic functions of costimulatory receptors, while the growth-stimulating HTLV-1 functions are mediated by the viral oncoprotein Tax. Here we analyzed the impact of Tax on costimulatory receptors in T cells with repressible Tax and found that among these receptors 4-1BB (TNFRSF9/CD137/ILA) was induced most strongly. Upregulated 4-1BB expression was a consistent feature of all HTLV-1-infected cell lines, whether patient-derived or in vitro transformed. Tax was sufficient to induce the expression of the endogenous 4-1BB gene in uninfected T cells, and it strongly activated (45-fold) the 4-1BB promoter via a single NF-κB site. The ligand of 4-1BB was also found on transformed T-cell lines, opening up the possibility of autostimulation. Moreover, 4-1BB expression in patients' lymphocytes ex vivo correlated with Tax expression, strongly suggesting Tax-mediated 4-1BB activation in vivo. Thus, 4-1BB up-regulation by Tax could contribute to growth, survival, and clonal expansion of the infected cells during persistence and disease. © 2008 by The American Society of Hematology.
Created from Fastlane, Scopus look-up

Structural proteins of Kaposi's sarcoma-associated herpesvirus antagonize p53-mediated apoptosis - Chudasama, Priya; Konrad, A.; Jochmann, R.; Lausen, Berthold; Holz, Patrick; Naschberger, Elisabeth; Neipel, Frank; Britzen-Laurent, Nathalie; Stürzl, Michael (Oncogene, 2015)
The tumor suppressor p53 is a central regulatory molecule of apoptosis and is commonly mutated in tumors. Kaposi's sarcoma-associated herpesvirus (KSHV)-related malignancies express wild-type p53. Accordingly, KSHV encodes proteins that counteract the cell death-inducing effects of p53. Here, the effects of all KSHV genes on the p53 signaling pathway were systematically analyzed using the reversely transfected cell microarray technology. With this approach we detected eight KSHV-encoded genes with potent p53 inhibiting activity in addition to the previously described inhibitory effects of KSHV genes ORF50, K10 and K10.5. Interestingly, the three most potent newly identified inhibitors were KSHV structural proteins, namely ORF22 (glycoprotein H), ORF25 (major capsid protein) and ORF64 (tegument protein). Validation of these results with a classical transfection approach showed that these proteins inhibited p53 signaling in a dose-dependent manner and that this effect could be reversed by small interfering RNA-mediated knockdown of the respective viral gene. All three genes inhibited p53-mediated apoptosis in response to Nutlin-3 treatment in non-infected and KSHV-infected cells. Addressing putative mechanisms, we could show that these proteins could also inhibit the transactivation of the promoters of apoptotic mediators of p53 such as BAX and PIG3. Altogether, we demonstrate for the first time that structural proteins of KSHV can counteract p53-induced apoptosis. These proteins are expressed in the late lytic phase of the viral life cycle and are incorporated into the KSHV virion. Accordingly, these genes may inhibit cell death in the productive and in the early entrance phase of KSHV infection.
EVALuna2:8221

Study on the Impact of CMV-Encephalopathy on the Survival of Brain Cancer Patients Undergoing Radio(Chemo) therapy of the Brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, M. A.; Engelhorn, Tobias; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, F.; et al. (2017)
EVALuna2:32868

Successful treatment of COVID-19 infection with convalescent plasma in B-cell-depleted patients may promote cellular immunity - Kremer, Andreas E.; Kremer, Anita; Willam, Carsten; Völkl, Simon; Verhagen, Johan; Achenbach, Susanne; van der Meijden, Edith; Lang, Vanessa; Aigner, Michael; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; et al. (European Journal of Immunology, 2021)
Treatment with convalescent plasma has been shown to be safe in coronavirus disease in 2019 (COVID-19) infection, although efficacy reported in immunocompetent patients varies. Nevertheless, neutralizing antibodies are a key requisite in the fight against viral infections. Patients depleted of antibody-producing B cells, such as those treated with rituximab (anti-CD20) for hematological malignancies, lack a fundamental part of their adaptive immunity. Treatment with convalescent plasma appears to be of general benefit in this particularly vulnerable cohort. We analyzed clinical course and inflammation markers of three B-cell-depleted patients suffering from COVID-19 who were treated with convalescent plasma. In addition, we measured serum antibody levels as well as peripheral blood CD38/HLA-DR-positive T-cells ex vivo and CD137-positive T-cells after in vitro stimulation with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-derived peptides in these patients. We observed that therapy with convalescent plasma was effective in all three patients and analysis of CD137-positive T-cells after stimulation with SARS-CoV-2 peptides showed an increase in peptide-specific T-cells after application of convalescent plasma. In conclusion, we here demonstrate efficacy of convalescent plasma therapy in three B-cell-depleted patients and present data that suggest that while application of convalescent plasma elevates systemic antibody levels only transiently, it may also boost specific T-cell responses.
CRIS-Team Scopus Importer:2021-09-17
Keywords: B-cell deficiency; convalescent plasma; COVID-19; SARS-CoV-2; T-cell immunity

Successful treatment of COVID-19 with convalescent plasma in B-cell depleted patients may promote cellular immunity - Kremer, Andreas; Kremer, Anita; Willam, Carsten; Verhagen, Johan; Achenbach, Susanne; Van Der Meiden, E.; Lang, Vanessa; Aigner, M.; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Lutzny-Geier, Gloria; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

SUMOylation of IE2p86 is required for efficient autorepression of the human cytomegalovirus major immediate-early promoter - Reuter, Nina; Reichel, Anna; Stilp, Anne-Charlotte; Scherer, Myriam; Stamminger, Thomas (Journal of General Virology, 2018)
The human cytomegalovirus (HCMV) IE2p86 protein is pivotal for coordinated regulation of viral gene expression. Besides functioning as a promiscuous transactivator, IE2p86 is also known to negatively regulate its own transcription. This occurs via direct binding of IE2p86 to a 14-bp palindromic DNA element located between the TATA box and the transcription start site of the major immediate-early promoter (MIEP), which is referred to as the cis repression signal (CRS). However, the exact mechanism of IE2p86-based autorepression is still unclear. By testing a series of IE2p86 mutants in transient expression assays, we found that not only did a DNA binding-deficient mutant of IE2p86 fail to repress the MIEP, but SUMOylation-negative mutants also failed to repress it. This finding was further supported by infection studies with primary fibroblasts harbouring a MIEP-driven transgene as a reporter. Here, we observed that a recombinant HCMV expressing SUMOylation-negative IE2p86 was defective in transgene downregulation, in contrast to wild-type HCMV. Interestingly, however, a double-mutant virus in which both the SUMO acceptor sites and the SUMO interaction motif (SIM) of IE2p86 were inactivated regained the ability to silence the MIEP. This correlated with increased expression levels of the IE2 isoforms IE2p40 and IE2p60, suggesting that these late proteins may contribute to MIEP suppression, thus compensating for the loss of IE2p86 SUMOylation. In summary, our results show that autorepression of the MIEP is not only regulated by late isoforms of IE2, but also depends on posttranslational SUMO modification, revealing a novel mechanism to fine-tune the expression of this important viral gene region.
EVALuna2:35286

Symptoms, SARS-CoV-2 Antibodies, and Neutralization Capacity in a Cross Sectional-Population of German Children - Laub, Otto; Leipold, Georg; Toncheva, Antoaneta A.; Peterhoff, David; Einhauser, Sebastian; Neckermann, Patrick; Borchers, Natascha; Santos-Valente, Elisangela; Kheiroddin, Parastoo; Buntrock-Doepke, Heike; Laub, Sarah; Schoeberl, Patricia; et al. (Frontiers in Pediatrics, 2021)
Background: Children and youth are affected rather mildly in the acute phase of COVID-19 and thus, SARS-CoV-2 infection infection may easily be overlooked. In the light of current discussions on the vaccinations of children it seems necessary to better identify children who are immune against SARS-CoV-2 due to a previous infection and to better understand COVID-19 related immune reactions in children. Methods: In a cross-sectional design, children aged 1–17 were recruited through primary care pediatricians for the study (a) randomly, if they had an appointment for a regular health check-up or (b) if parents and children volunteered and actively wanted to participate in the study. Symptoms were recorded and two antibody tests were performed in parallel directed against S (in house test) and N (Roche Elecsys) viral proteins. In children with antibody response in either test, neutralization activity was determined. Results: We identified antibodies against SARS-CoV-2 in 162 of 2,832 eligible children (5.7%) between end of May and end of July 2020 in three, in part strongly affected regions of Bavaria in the first wave of the pandemic. Approximately 60% of antibody positive children (n = 97) showed high levels (>97th percentile) of antibodies against N-protein, and for the S-protein, similar results were found. Sufficient neutralizing activity was detected for only 135 antibody positive children (86%), irrespective of age and sex. Initial COVID-19 symptoms were unspecific in children except for the loss of smell and taste and unrelated to antibody responses or neutralization capacity. Approximately 30% of PCR positive children did not show seroconversion in our small subsample in which PCR tests were performed. Conclusions: Symptoms of SARS-CoV-2 infections are unspecific in children and antibody responses show a dichotomous structure with strong responses in many and no detectable antibodies in PCR positive children and missing neutralization activity in a relevant proportion of the young population.
CRIS-Team Scopus Importer:2021-10-29
Keywords: antibody; children; COVID-19; neutralizing; SARS-CoV-2

Synergistic Antiviral Activity of Pamapimod and Pioglitazone against SARS-CoV-2 and Its Variants of Concern - Setz, Christian; Große, Maximilian; Auth, Janina; Froba, Maria; Rauch, Pia; Bausch, Alexander; Wright, Matthew; Schubert, Ulrich (International Journal of Molecular Sciences, 2022)
The SARS-CoV-2 pandemic remains a major public health threat, especially due to newly emerging SARS-CoV-2 Variants of Concern (VoCs), which are more efficiently transmitted, more virulent, and more able to escape naturally acquired and vaccine-induced immunity. Recently, the protease inhibitor Paxlovid (R) and the polymerase inhibitor molnupiravir, both targeting mutant-prone viral components, were approved for high-risk COVID-19 patients. Nevertheless, effective therapeutics to treat COVID-19 are urgently needed, especially small molecules acting independently of VoCs and targeting genetically stable cellular pathways which are crucial for viral replication. Pamapimod is a selective inhibitor of p38 Mitogen-Activated Protein Kinase alpha (p38 MAPK alpha) that has been extensively clinically evaluated for the treatment of rheumatoid arthritis. Signaling via p38 has recently been described as a key pathway for the replication of SARS-CoV-2. Here, we reveal that the combination of pamapimod with pioglitazone, an anti-inflammatory and approved drug for the treatment of type 2 diabetes, possesses potent and synergistic activity to inhibit SARS-CoV-2 replication in vitro. Both drugs showed similar antiviral potency across several cultured cell types and similar antiviral activity against SARS-CoV-2 Wuhan type, and the VoCs Alpha, Beta, Gamma, Delta, and Omicron. These data support the combination of pamapimod and pioglitazone as a potential therapy to reduce duration and severity of disease in COVID-19 patients, an assumption currently evaluated in an ongoing phase II clinical study.
CRIS-Team WoS Importer:2022-07-08
Keywords: COVID-19; SARS-CoV-2; coronavirus; variants of concern; virus variants; pioglitazone; pamapimod; p38-inhibitor; PPRy-agonist; cellular targets

Synthesis, molecular features and biological activities of modified plant polysaccharides - Mukherjee, Shuvam; Jana, Subrata; Khawas, Sadhana; Kicuntod, Jintawee; Marschall, Manfred; Ray, Bimalendu; Ray, Sayani (Carbohydrate Polymers, 2022)
Plant polysaccharides represent a natural source material characterized by high ubiquity, abundance and biological activities that can be utilised as organic matter in numerous manufacturing processes including pharmaceutical. The goal-oriented modification of polysaccharides by chemical reactions brings about a substantial refinement in their molecular features and biological activity. An improved understanding of the intrinsic molecular features of plant polysaccharides, as well as the structure-activity relationship eventually caused by chemical alterations, may be fundamental for the development of technologies supporting their biomedical oriented exploitation. Herein, we attempt to provide a broader view on these topics and to illustrate methodologies of chemical modification. These are intended to enhance the functionality of plant polysaccharides, such as their modification-induced biological activities, finally making the products available for translational purposes.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Biological activities; Chemical modifications; Molecular features; Plant polysaccharides; Structure-activity relationship

Synthesis of Artemisinin-Derived Dimers, Trimers and Dendrimers: Investigation of Their Antimalarial and Antiviral Activities Including Putative Mechanisms of Action - Fröhlich, Tony; Hahn, Friedrich; Belmudes, Lucid; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Coute, Yohann; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2018)
Generation of dimers, trimers and dendrimers of bioactive compounds is an approach that has recently been developed for the discovery of new potent drug candidates. Herein, we present the synthesis of new artemisinin-derived dimers and dendrimers and investigate their action against malaria parasite Plasmodium falciparum 3D7 strain and human cytomegalovirus (HCMV). Dimer 7 was the most active compound (EC50 1.4 nm) in terms of antimalarial efficacy and was even more effective than the standard drugs dihydroartemisinin (EC50 2.4 nm), artesunic acid (EC50 8.9 nm) and chloroquine (EC50 9.8 nm). Trimer 4 stood out as the most active agent against HCMV in vitro replication and exerted an EC50 value of 0.026 mu m, representing an even higher activity than the two reference drugs ganciclovir (EC50 2.60 mu m) and artesunic acid (EC50 5.41 mu m). In addition, artemisinin-derived dimer 13 and trimer 15 were for the first time both immobilized on TOYOPEARL AF-Amino-650M beads and used for mass spectrometry-based target identification experiments using total lysates of HCMV-infected primary human fibroblasts. Two major groups of novel target candidates, namely cytoskeletal and mitochondrial proteins were obtained. Two putatively compound-binding viral proteins, namely major capsid protein (MCP) and envelope glycoprotein pUL132, which are both essential for HCMV replication, were identified.
EVALuna2:35275

Synthesis of Artemisinin-Estrogen Hybrids Highly Active against HCMV, P-falciparum, and Cervical and Breast Cancer - Fröhlich, Tony; Kiss, Anita; Wolfling, Janos; Mernyak, Erzsebet; Kulmany, Agnes E.; Minorics, Renata; Zupko, Istvan; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Hahn, Friedrich; Marschall, Manfred; et al. (ACS Medicinal Chemistry Letters, 2018)
Artemisinin-estrogen hybrids were for the first time both synthesized and investigated for their in vitro biological activity against malaria parasites (Plasmodium falciparum 3D7), human cytomegalovirus (HCMV), and a panel of human malignant cells of gynecological origin containing breast (MCF7, MDA-MB-231, MDA-MB-361, T47D) and cervical tumor cell lines (HeLa, SiHa, C33A). In terms of antimalarial efficacy, hybrid 8 (EC50 = 3.8 nM) was about two times more active than its parent compound artesunic acid (7) (EC50 = 8.9 nM) as well as the standard drug chloroquine (EC50 = 9.8 nM) and was, therefore, comparable to the clinically used dihydroartemisinin (6) (EC50 = 2.4 nM). Furthermore, hybrids 9-12 showed a strong antiviral effect with EC50 values in the submicromolar range (0.22-0.38 mu M) and thus possess profoundly stronger anti-HCMV activity (approximately factor 25) than the parent compound artesunic acid (7) (EC50 = 5.41 mu M). These compounds also exerted a higher in vitro anti-HCMV efficacy than ganciclovir used as the standard of current antiviral treatment. In addition, hybrids 8-12 elicited substantially more pronounced growth inhibiting action on all cancer cell lines than their parent compounds and the reference drug cisplatin. The most potent agent, hybrid 12, exhibited submicromolar EC50 values (0.15-0.93 mu M) against breast cancer and C33A cell lines.
EVALuna2:35262

Synthesis of new betulinic acid/betulin-derived dimers and hybrids with potent antimalarial and antiviral activities - Capci Karagöz, Aysun; Leidenberger, Maria; Hahn, Friedrich; Friedrich, Oliver; Hampel, Frank; Marschall, Manfred; Kappes, Bärbel; Tsogoeva, Svetlana (Bioorganic & Medicinal Chemistry, 2019)
Severe malaria and viral infections cause life-threatening diseases in millions of people worldwide every year. In search for effective bioactive hybrid molecules, which may possess improved properties compared to their parent compounds, a series of betulinic acid/betulin based dimer and hybrid compounds carrying ferrocene and/or artesunic acid moieties, was designed and, synthesized de novo. Furthermore, they were analyzed in vitro against malaria parasites (growth inhibition of 3D7-strain P. falciparum-infected erythrocytes) and human cytomegalovirus (HCMV). From this series of hybrids/dimers, the betulinic acid/betulin and artesunic acid hybrids 11 and 12 showed the most potent activities against P. falciparum and HCMV. On the strength of results, additive and/or synergistic effects between the natural or semisynthetic products, such as betulinic acid-/betulin- and artesunic acid-derived compounds, are suggested on the basis of putatively complex modes of antimicrobial action. This advantage may be taken into account in future drug development.
Keywords: Betulin; Betulinic acid; Artesunic acid; Ferrocene; Natural product hybrid; Antimalarial activity; Antiviral activity

Synthesis of Novel Hybrids of Quinazoline and Artemisinin with High Activities against Plasmodium falciparum, Human Cytomegalovirus, and Leukemia Cells - Fröhlich, Tony; Reiter, Christoph; Ibrahim, Mohammad M.; Beutel, Jannis; Hutterer, Corina; Zeitträger, Isabel; Bahsi, Hanife; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Efferth, Thomas; Marschall, Manfred; et al. (ACS Omega, 2017)
Many quinazoline derivatives have been synthesized over the last few decades with great pharmacological potential, such as antimalarial, anti-inflammatory, antimicrobial, anticancer, and antiviral. But so far, no quinazoline-artemisinin hybrids have been reported in the literature. In the present study, five novel quinazoline-artemisinin hybrids were synthesized and evaluated for their in vitro biological activity against malarial parasites (Plasmodium falciparum 3D7), leukemia cells (CCRF-CEM and CEM/ADR5000), and human cytomegalovirus. Remarkably, hybrid 9 (EC50 = 1.4 nM), the most active antimalarial compound of this study, was not only more potent than artesunic acid (EC50 = 9.7 nM) but at the same time more active than the clinically used drugs dihydroartemisinin (EC50 = 2.4 nM) and chloroquine (EC50 = 9.8 nM). Furthermore, hybrids 9 and 10 were the most potent compounds with regard to anticytomegaloviral activity (EC50 = 0.15-0.21 μM). They were able to outperform ganciclovir (EC50 = 2.6 μM), which is the relevant standard drug of antiviral therapy, by a factor of 12-17. Moreover, we identified a new highly active quinazoline derivative, compound 14, that is most effective in suppressing cytomegalovirus replication with an EC50 value in the nanomolar range (EC50 = 50 nM). In addition, hybrid 9 exhibited an antileukemia effect similar to that of artesunic acid, with EC50 values in the low micromolar range, and was 45 times more active toward the multidrug-resistant CEM/ADR5000 cells (EC50 = 0.5 μM) than the standard drug doxorubicin.
EVALuna2:35475

Synthesis of Thymoquinone-Artemisinin Hybrids: New Potent Antileukemia, Antiviral, and Antimalarial Agents - Fröhlich, Tony; Reiter, Christoph; Saeed, Mohamed E. M.; Hutterer, Corina; Hahn, Friedrich; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Marschall, Manfred; Efferth, Thomas; Tsogoeva, Svetlana (ACS Medicinal Chemistry Letters, 2018)
A series of hybrid compounds based on the natural products artemisinin and thymoquinone was synthesized and investigated for their biological activity against the malaria parasite Plasmodium falciparum 3D7 strain, human cytomegalovirus (HCMV), and two leukemia cell lines (drug sensitive CCRF-CEM and multidrug-resistant subline CEM/ADR5000). An unprecedented one-pot method of selective formation of C-10 alpha-acetate 14 starting from a 1:1 mixture of C-10 alpha- to C-10 beta-dihydroartemisinin was developed. The key step of this facile method is a mild decarboxylative activation of malonic acid mediated by DCC/DMAP. Ether-linked thymoquinone artemisinin hybrids 6a/b stood out as the most active compounds in all categories, while showing no toxic side effects toward healthy human foreskin fibroblasts and thus being selective. They exhibited EC50 values of 0.2 mu M against the doxorubicin-sensitive as well as the multidrug-resistant leukemia cells and therefore can be regarded as superior to doxorubicin. Moreover, they showed to be five times more active than the standard drug ganciclovir and nearly eight times more active than artesunic acid against HCMV. In addition, hybrids 6a/b possessed excellent antimalarial activity (EC50 = 5.9/3.7 nM), which was better than that of artesunic acid (EC50 = 8.2 nM) and chloroquine (EC50 = 9.8 nM). Overall, most of the presented thymoquinone artemisinin-based hybrids exhibit an excellent and broad variety of biological activities (anticancer, antimalarial, and antiviral) combined with a low toxicity/high selectivity profile.
EVALuna2:35278

Systematic data analysis and data mining in CatWalk gait analysis by heat mapping exemplified in rodent models for neurodegenerative diseases - Timotius, Ivanna; Canneva, Fabio; Minakaki, Georgia; Moceri, Sandra; Plank, Anne-Christine; Casadei, Nicolas; Riess, Olaf; Winkler, Jürgen; Klucken, Jochen; Eskofier, Björn; von Hörsten, Stephan (Journal of Neuroscience Methods, 2019)
Background Motor impairment appears as a characteristic symptom of several diseases and injuries. Therefore, tests for analyzing motor dysfunction are widely applied across preclinical models and disease stages. Among those, gait analysis tests are commonly used, but they generate a huge number of gait parameters. Thus, complications in data analysis and reporting raise, which often leads to premature parameter selection. New methods In order to avoid arbitrary parameter selection, we present here a systematic initial data analysis by utilizing heat-maps for data reporting. We exemplified this approach within an intervention study, as well as applied it to two longitudinal studies in rodent models related to Parkinson’s disease (PD) and Huntington disease (HD). Results The systematic initial data analysis (IDA) is feasible for exploring gait parameters, both in experimental and longitudinal studies. The resulting heat maps provided a visualization of gait parameters within a single chart, highlighting important clusters of differences. Comparison with existing method Often, premature parameter selection is practiced, lacking comprehensiveness. Researchers often use multiple separated graphs on distinct gait parameters for reporting. Additionally, negative results are often not reported. Conclusions Heat mapping utilized in initial data analysis is advantageous for reporting clustered gait parameter differences in one single chart and improves data mining.
Keywords: Gait analysis; CatWalk system; Heat map; Parkinson’s disease; Huntington disease; Rodent models

Systematic Data Analysis and Data Mining in Gait Analysis by Heat Mapping - Timotius, Ivanna; Canneva, Fabio; Minakaki, Georgia; Moceri, Sandra; Casadei, Nicolas; Riess, Olaf; Winkler, Jürgen; von Hörsten, Stephan; Eskofier, Björn; Klucken, Jochen (Measuring Behavior 2018, 2018)
Motor impairment appears as a characteristic of several diseases and injuries. Therefore, tests for analyzing motor dysfunction are widely applied across preclinical models and disease stages. The standard analysis addresses an extensive number of gait parameters which raises complication and often lead to premature parameter pre-selection. The parameter selection process was typically based on the previous research or the expert presumption, which sometimes leaves a question about the importance of the unselected parameters. Instead of manual parameter selection, here we propose a data mining technique using a systematic approach of initial data analysis (IDA) using a cluster heat map for data visualization. We exemplify our approach by applying it to a classical before-intervention-after-intervention design. This IDA is useful especially for exploratory research investigating gait abnormality and has the prospect to be applied in selecting parameters for a multivariate data analysi
Keywords: systematic approach; initial data analysis; heat map; cluster; gait analysis; CatWalk assay; gait parameters

Targeting gamma-glutamyl transpeptidase: A pleiotropic enzyme involved in glutathione metabolism and in the control of redox homeostasis - Mitric, Aleksandra; Castellano, Immacolata (Free Radical Biology and Medicine, 2023)
Gamma-glutamyl transpeptidase (GGT) is an enzyme located on the outer membrane of the cells where it regulates the metabolism of glutathione (GSH), the most abundant intracellular antioxidant thiol. GGT plays a key role in the control of redox homeostasis, by hydrolyzing extracellular GSH and providing the cell with the recovery of cysteine, which is necessary for de novo intracellular GSH and protein biosynthesis. Therefore, the upregulation of GGT confers to the cell greater resistance to oxidative stress and the advantage of growing fast. Indeed, GGT is upregulated in inflammatory conditions and in the progression of various human tumors and it is involved in many physiological disorders related to oxidative stress, such as cardiovascular disease and diabetes. Currently, increased GGT expression is considered a marker of liver damage, cancer, and low-grade chronic inflammation. This review addresses the current knowledge on the structure-function relationship of GGT, focusing on human GGT, and provides information on the pleiotropic biological role and relevance of the enzyme as a target of drugs aimed at alleviating oxidative stress-related diseases. The development of new GGT inhibitors is critically discussed, as are the advantages and disadvantages of their potential use in clinics. Considering its pleiotropic activities and evolved functions, GGT is a potential "moonlighting protein".
CRIS-Team Scopus Importer:2023-10-06
Keywords: Gamma-glutamyl transpeptidase; GGT inhibitors; Glutathione; Oxidative stress; Redox homeostasis

Targeting zonulin and intestinal epithelial barrier function to prevent onset of arthritis - Tajik, Narges; Frech, Michael; Schulz, Oscar; Schälter, Fabian; Lucas, Sébastien; Azizov, Vugar; Dürholz, Kerstin; Steffen, Franziska; Omata, Yasunori; Rings, Andreas; Bertog, Marko; Rizzo, Aroldo; et al. (Nature Communications, 2020)
Gut microbial dysbiosis is associated with the development of autoimmune disease, but the mechanisms by which microbial dysbiosis affects the transition from asymptomatic autoimmunity to inflammatory disease are incompletely characterized. Here, we identify intestinal barrier integrity as an important checkpoint in translating autoimmunity to inflammation. Zonulin family peptide (zonulin), a potent regulator for intestinal tight junctions, is highly expressed in autoimmune mice and humans and can be used to predict transition from autoimmunity to inflammatory arthritis. Increased serum zonulin levels are accompanied by a leaky intestinal barrier, dysbiosis and inflammation. Restoration of the intestinal barrier in the pre-phase of arthritis using butyrate or a cannabinoid type 1 receptor agonist inhibits the development of arthritis. Moreover, treatment with the zonulin antagonist larazotide acetate, which specifically increases intestinal barrier integrity, effectively reduces arthritis onset. These data identify a preventive approach for the onset of autoimmune disease by specifically targeting impaired intestinal barrier function.
CRIS-Team Scopus Importer:2020-05-05

Target verification of artesunate-related antiviral drugs: Assessing the role of mitochondrial and regulatory proteins by click chemistry and fluorescence labeling - Hahn, Friedrich; Niesar, Aischa; Wangen, Christina; Wild, Markus; Grau, Benedikt; Herrmann, Lars; Capci, Aysun; Adrait, Annie; Couté, Yohann; Tsogoeva, Svetlana; Marschall, Manfred (Antiviral Research, 2020)
Human cytomegalovirus (HCMV) infection is associated with serious pathology such as transplant rejection or embryonic developmental defects. Antiviral treatment with currently available drugs targeting viral enzymes is often accompanied with severe side effects and the occurrence of drug-resistant viruses. For this reason, novel ways of anti-HCMV therapy focusing on so far unexploited small molecules, targets and mechanisms are intensively studied. Recently, we described the pronounced antiviral activity of the artesunate-related class of trioxane compounds, comprising NF-κB/signaling inhibitors like the trimeric derivative TF27, which proved to be highly active in a nanomolar range both in vitro and in vivo. Here, we extend this analysis by presenting further TF27/artesunate-derived antiviral compounds designed for their specific use in target verification by click chemistry applied in fluorescence labeling and tag affinity strategies. Our main findings are as follows: (i) compounds TF27, BG95, AC98 and AC173 exert strong inhibitory activity against HCMV replication in cultured primary human cells, (ii) autofluorescence activity could be quantitatively detected for BG95 and AC98, and confocal fluorescence imaging revealed accumulation in mitochondria, (iii) postulated cellular targets including mitochondrial proteins were down-regulated upon TF27 treatment, (iv) a click chemistry-based protocol of target enrichment was established, and (v) mass spectrometry-based proteomic analysis, using proteins from HCMV-infected fibroblasts covalently interacting with AC173, revealed a refined list of targets. Combined, data strongly suggest a complex mode of antiviral drug-target interaction of artesunate-related compounds, now highlighting potential roles of mitochondrial, NF-κB pathway proteins, exportins and possibly more. This strategy may further promote antiviral drug development on the basis of pharmacologically optimized trioxane derivatives.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Antiviral experimental drugs; Artemisinin compounds; Click chemistry; Human cytomegalovirus; Proteomics

T Cell Costimulation Molecules CD80/86 Inhibit Osteoclast Differentiation by Inducing the IDO/Tryptophan Pathway - Bozec, Aline; Zaiss, Mario; Kagwiria, Rosebeth; Voll, Reinhard; Rauh, Manfred; Chen, Zhu; Müller-Schmucker, Sandra; Kroczek, Richard A.; Heinzerling, Lucie; Moser, Muriel; Mellor, Andrew L.; David, Jean-Pierre; et al. (Science Translational Medicine, 2014)
Bone resorption is seminal for the physiological remodeling of bone during life. However, this process needs to be strictly controlled; excessive bone resorption results in pathologic bone loss, osteoporosis, and fracture. We describe a control mechanism of bone resorption by the adaptive immune system. CD80/86, a pair of molecules expressed by antigen-presenting cells and involved in T cell costimulation, act as negative regulator for the generation of bone-resorbing osteoclasts. CD80/86-deficient mice were osteopenic because of increased osteoclast differentiation. CD80/86-deficient osteoclasts escaped physiological inhibition by CTLA-4 or regulatory T cells. Mechanistically, engagement of CD80/86 by CTLA-4 induced activation of the enzyme indoleamine 2,3-dioxygenase (IDO) in osteoclast precursors, which degraded tryptophan and promoted apoptosis. Concordantly, IDO-deficient mice also showed an osteopenic bone phenotype with higher numbers of osteoclast precursors and osteoclasts. Also, IDO-deficient mononuclear cells escaped the anti-osteoclastogenic effect of CTLA-4. This molecular mechanism was also present in humans because targeting CD80/86 by abatacept, a CTLA-4-immunoglobulin fusion protein, reduced, whereas blockade of CTLA-4 by ipilimumab antibody enhanced, the frequency of peripheral osteoclast precursors and osteoclastogenesis. In summary, these data show an important role of the adaptive immune system, in particular T cell CD80/86 costimulation molecules, in the physiological regulation of bone resorption and preservation of bone mass, as well as affect the understanding of the function of current and future drugs fostering or blocking the effects of CTLA-4 in humans.
EVALuna2:12912

T Cell Immunity against Influenza: The Long Way from Animal Models Towards a Real-Life Universal Flu Vaccine - Schmidt, Anna; Lapuente, Dennis (Viruses, 2021)
Current flu vaccines rely on the induction of strain-specific neutralizing antibodies, which leaves the population vulnerable to drifted seasonal or newly emerged pandemic strains. Therefore, universal flu vaccine approaches that induce broad immunity against conserved parts of influenza have top priority in research. Cross-reactive T cell responses, especially tissue-resident memory T cells in the respiratory tract, provide efficient heterologous immunity, and must therefore be a key component of universal flu vaccines. Here, we review recent findings about T cell-based flu immunity, with an emphasis on tissue-resident memory T cells in the respiratory tract of humans and different animal models. Furthermore, we provide an update on preclinical and clinical studies evaluating T cell-evoking flu vaccines, and discuss the implementation of T cell immunity in real-life vaccine policies.
CRIS-Team Scopus Importer:2021-03-05
Keywords: influenza; influenza vaccine; T cells; tissue-resident memory T cells; TRM; universal flu vaccine; vaccine

The antidepressant fluoxetine mobilizes vesicles to the recycling pool of rat hippocampal synapses during high activity - Jung, Jasmin; Loy, Kristina; Schilling, Eva-Maria; Röther, Mareike; Brauner, Jan M.; Huth, Tobias; Schlötzer-Schrehardt, Ursula; Alzheimer, Christian; Kornhuber, Johannes; Welzel, Oliver; Groemer, Teja W. (Molecular Neurobiology, 2014)
Effects of the antidepressant fluoxetine in therapeutic concentration on stimulation-dependent synaptic vesicle recycling were examined in cultured rat hippocampal neurons using fluorescence microscopy. Short-term administration of fluoxetine neither inhibited exocytosis nor endocytosis of RRP vesicular membranes. On the contrary, acute application of the drug markedly increased the size of the recycling pool of hippocampal synapses. This increase in recycling pool size was corroborated using the styryl dye FM 1-43, antibody staining with ?Syt1-CypHer(TM)5E and overexpression of synapto-pHluorin, and was accompanied by an increase in the frequency of miniature postsynaptic currents. Analysis of axonal transport and fluorescence recovery after photobleaching excluded vesicles originating from the synapse-spanning superpool as a source, indicating that these new release-competent vesicles derived from the resting pool. Super resolution microscopy and ultrastructural analysis by electron microscopy revealed that short-term incubation with fluoxetine had no influence on the number of active synapses and synaptic morphology compared to controls. These observations support the idea that therapeutic concentrations of fluoxetine enhance the recycling vesicle pool size and thus the recovery of neurotransmission from exhausting stimuli. The change in the recycling pool size is consistent with the plasticity hypothesis of the pathogenesis of major depressive disorder as stabilization of the vesicle recycling might be responsible for neural outgrowth and plasticity.
EVALuna2:2369

The Artemisinin-Derived Autofluorescent Compound BG95 Exerts Strong Anticytomegaloviral Activity Based on a Mitochondrial Targeting Mechanism - Wild, Markus; Hahn, Friedrich; Grau, Benedikt; Herrmann, Lars; Niesar, Aischa; Schütz, Martin; Lorion, Melanie M.; Ackermann, Lutz; Tsogoeva, Svetlana; Marschall, Manfred (International Journal of Molecular Sciences, 2020)
Human cytomegalovirus (HCMV) is a major human pathogen associated with severe pathology. Current options of antiviral therapy only partly satisfy the needs of a well-tolerated long-term treatment/prophylaxis free from drug-induced viral resistance. Recently, we reported the strong antiviral properties in vitro and in vivo of the broad-spectrum anti-infective drug artesunate and its optimized derivatives. NF-κB signaling was described as a targeting mechanism and additional target proteins have recently been identified. Here, we analyzed the autofluorescent hybrid compound BG95, which could be utilized for intracellular visualization by confocal imaging and a tracking analysis in virus-infected primary human fibroblasts. As an important finding, BG95 accumulated in mitochondria visualized by anti-prohibitin and MitoTracker staining, and induced statistically significant changes of mitochondrial morphology, distinct from those induced by HCMV infection. Notably, mitochondrial membrane potential was found substantially reduced by BG95, an effect apparently counteracting efficient HCMV replication, which requires active mitochondria and upregulated energy levels. This finding was consistent with binding properties of artesunate-like compounds to mitochondrial proteins and thereby suggested a new mechanistic aspect. Combined, the present study underlines an important role of mitochondria in the multifaceted, host-directed antiviral mechanism of this drug class, postulating a new mitochondria-specific mode of protein targeting.
CRIS-Team Scopus Importer:2020-08-14
Keywords: antiviral drugs; artemisinin derivative; autofluorescence; human cytomegalovirus; intracellular tracking; mitochondrial architecture; mitochondrial impairment; mitochondrial targeting

The Autophagy-Initiating Protein Kinase ULK1 Phosphorylates Human Cytomegalovirus Tegument Protein pp28 and Regulates Efficient Virus Release - König, Patrick; Svrlanska, Adriana; Read, Clarissa; Feichtinger, Sabine; Stamminger, Thomas (Journal of Virology, 2021)
Autophagy is a catabolic process contributing to intrinsic cellular defense by degrading viral particles or proteins; however, several viruses hijack this pathway for their own benefit. The role of autophagy during human cytomegalovirus (HCMV) replication has not been definitely clarified yet. Utilizing small interfering RNA (siRNA)-based screening, we observed that depletion of many autophagy-related proteins resulted in reduced virus release, suggesting a requirement of autophagy-related factors for efficient HCMV replication. Additionally, we could show that the autophagy-initiating serine/threonine protein kinase ULK1 as well as other constituents of the ULK1 complex were upregulated at early times of infection and stayed upregulated throughout the replication cycle. We demonstrate that indirect interference with ULK1 through inhibition of the upstream regulator AMP-activated protein kinase (AMPK) impaired virus release. Furthermore, this result was verified by direct abrogation of ULK1 kinase activity utilizing the ULK1-specific kinase inhibitors SBI-0206965 and ULK-101. Analysis of viral protein expression in the presence of ULK-101 revealed a connection between the cellular kinase ULK1 and the viral tegument protein pp28 (pUL99), and we identified pp28 as a novel viral substrate of ULK1 by in vitro kinase assays. In the absence of ULK1 kinase activity, large pp28- and pp65-positive structures could be detected in the cytoplasm at late time points of infection. Transmission electron microscopy demonstrated that these structures represent large perinuclear protein accumulations presumably representing aggresomes. Our results indicate that HCMV manipulates ULK1 and further components of the autophagic machinery to ensure the efficient release of viral particles.IMPORTANCE The catabolic program of autophagy represents a powerful immune defense against viruses that is, however, counteracted by antagonizing viral factors. Understanding the exact interplay between autophagy and HCMV infection is of major importance since autophagy-related proteins emerged as promising targets for pharmacologic intervention. Our study provides evidence for a proviral role of several autophagy-related proteins suggesting that HCMV has developed strategies to usurp components of the autophagic machinery for its own benefit. In particular, we observed strong upregulation of the autophagy-initiating protein kinase ULK1 and further components of the ULK1 complex during HCMV replication. In addition, both siRNA-mediated depletion of ULK1 and interference with ULK1 protein kinase activity by two chemically different inhibitors resulted in impaired viral particle release. Thus, we propose that ULK1 kinase activity is required for efficient HCMV replication and thus represents a promising novel target for future antiviral drug development.
CRIS-Team Scopus Importer:2021-03-19
Keywords: autophagy; human cytomegalovirus; tegument protein; ULK1

The broad-spectrum antiinfective drug artesunate interferes with the canonical nuclear factor kappa B (NF-κB) pathway by targeting RelA/p65 - Hutterer, Corina; Niemann, Ina; Milbradt, Jens; Fröhlich, Tony; Reiter, Christoph; Kadioglu, Onat; Bahsi, Hanife; Zeitträger, Isabel; Wagner, Sabrina; Einsiedel, Jürgen; Gmeiner, Peter; Vogel, Nicolas; et al. (Antiviral Research, 2015)
Infection with human cytomegalovirus (HCMV) is a serious medical problem, particularly in immunocompromised individuals and neonates. The success of standard antiviral therapy is hampered by low drug compatibility and induction of viral resistance. A novel strategy is based on the exploitation of cell-directed signaling inhibitors. The broad antiinfective drug artesunate (ART) offers additional therapeutic options such as oral bioavailability and low levels of toxic side-effects. Here, novel ART-derived compounds including dimers and trimers were synthesized showing further improvements over the parental drug. Antiviral activity and mechanistic aspects were determined leading to the following statements: (i) ART exerts antiviral activity towards human and animal herpesviruses, (ii) no induction of ART-resistant HCMV mutants occurred in vitro, (iii) chemically modified derivatives of ART showed strongly enhanced anti-HCMV efficacy, (iv) NF-κB reporter constructs, upregulated during HCMV replication, could be partially blocked by ART treatment, (v) ART activity analyzed in stable reporter cell clones indicated an inhibition of stimulated NF-κB but not CREB pathway, (vi) solid-phase immobilized ART was able to bind to NF-κB RelA/p65, and (vii) peptides within NF-κB RelA/p65 represent candidates of ART binding as analyzed by in silico docking and mass spectrometry. These novel findings open new prospects for the future medical use of ART and ART-related drug candidates.
Keywords: Artesunate and chemical derivatives; Binding of artesunate to NF-κB RelA/p65; Broad antiviral activity; Human cytomegalovirus; Increase of antiviral efficacy; Interference with NF-κB signaling pathways

The chemical class of quinazoline compounds provides a core structure for the design of anticytomegaloviral kinase inhibitors - Hutterer, Corina; Hamilton, S.; Steingruber, Mirjam; Zeitträger, Isabel; Bahsi, Hanife; Thuma, Natalie; Naing, Z.; Oerfi, Z.; Oerfi, L.; Socher, Eileen; Sticht, Heinrich; Rawlinson, W.; et al. (Antiviral Research, 2016)
HCMV is a member of the family Herpesviridae and represents a worldwide distributed pathogen with seropositivity rates in the adult population ranging between 40% and 90%. Notably, HCMV infection is a serious, sometimes life-threatening medical problem for newborns and immunosuppressed individuals, including transplant recipients and patients under antitumoral chemotherapy. Current standard therapy with valganciclovir has the disadvantage of inducing drug-resistant virus mutants and toxicity-related side effects. Our analysis stresses the earlier finding that kinase inhibitors of the quinazoline class exert an antiviral response by targeting the viral protein kinase pUL97 without inducing resistance. Therefore, quinazolines have been used as a core structure to gain insight in the mode of inhibitor-kinase interaction. Here, we demonstrate that (i) the novel quinazolines Vi7392 and Vi7453 are highly active against HCMV laboratory and clinically relevant strains including maribavir- and ganciclovir-resistant variants, (ii) antiviral activity is not cell-type specific and was also detected in a placental explant tissue model using a genetically intact HCMV strain (iii) the viral kinase pUL97 represents a target of the anticytomegaloviral activity of these compounds, (iv) induction of pUL97-conferring drug resistance was not detectable under single-step selection, thus differed from the induction of ganciclovir resistance, and (v) pUL97 drug docking simulations enabled detailed insights into specific drug-target binding properties providing a promising basis for the design of optimized kinase inhibitors. These novel findings may open new prospects for the future medical use of quinazoline drug candidates and the use of drug-target dynamic simulations for rational design of antivirals.
Keywords: Antiviral drug target; Homology model of pUL97; Human cytomegalovirus; pUL97 drug docking simulation; Quinazoline compounds; Viral kinase pUL97

The complex regulatory role of cytomegalovirus nuclear egress protein pul50 in the production of infectious virus - Häge, Sigrun; Büscher, Nicole; Pakulska, Victoria; Hahn, Friedrich; Adrait, Annie; Krauter, Steffi; Borst, Eva Maria; Schlötzer-Schrehardt, Ursula; Couté, Yohann; Plachter, Bodo; Marschall, Manfred (Cells, 2021)
The regulation of the nucleocytoplasmic release of herpesviral capsids is defined by the process of nuclear egress. Due to their large size, nuclear capsids are unable to traverse via nuclear pores, so that herpesviruses evolved to develop a vesicular transport pathway mediating their transition through both leaflets of the nuclear membrane. This process involves regulatory proteins, which support the local distortion of the nuclear envelope. For human cytomegalovirus (HCMV), the nuclear egress complex (NEC) is determined by the pUL50-pUL53 core that initiates multicomponent assembly with NEC-associated proteins and capsids. Hereby, pUL50 serves as a multi-interacting determinant that recruits several viral and cellular factors by direct and indirect con-tacts. Recently, we generated an ORF-UL50-deleted recombinant HCMV in pUL50-complementing cells and obtained first indications of putative additional functions of pUL50. In this study, we produced purified ∆UL50 particles under both complementing (∆UL50C) and non-complementing (∆UL50N) conditions and performed a phenotypical characterization. Findings were as follows: (i) ∆UL50N particle preparations exhibited a clear replicative defect in qPCR-based infection kinetics compared to ∆UL50C particles; (ii) immuno-EM analysis of ∆UL50C did not reveal major changes in nuclear distribution of pUL53 and lamin A/C; (iii) mass spectrometry-based quantitative proteomics showed a large concordance of protein contents in the NIEP fractions of ∆UL50C and ∆UL50N particles, but virion fraction was close to the detection limit for ∆UL50N; (iv) confocal imaging of viral marker proteins of immediate early (IE) and later phases of ∆UL50N infection indicated a very low number of cells showing an onset of viral lytic protein expression; and, finally (v) quantitative measurements of encapsidated genomes provided evidence for a substantial reduction in the DNA contents in ∆UL50N compared to ∆UL50C particles. In summary, the results point to a complex and important regulatory role of the HCMV nuclear egress protein pUL50 in the maturation of infectious virus.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Conditional expression; Efficiency of infectious virus production; Functional properties; Human cytomegalovirus; NEC protein pUL50; Nuclear egress complex (NEC); Regulation of viral replication

The contribution of systems biology and reverse genetics to the understanding of Kaposi's sarcoma-associated herpesvirus pathogenesis in endothelial cells. - Stürzl, Michael; Konrad, Andreas; Alkharsah, Khaled R.; Jochmann, Ramona; Thurau, Mathias; Marquardt, Gaby; Schulz, Thomas F. (Thrombosis and Haemostasis, 2009)
Kaposi's sarcoma-associated herpesvirus (KSHV)/human herpesvirus-8 is the causative agent of the endothelial cell-derived tumour Kaposi's sarcoma. Herpesviruses possess large complex genomes which provide many options to regulate cellular physiology during the viral life cycle and in the course of tumourigenicity. Novel techniques of systems biology and reverse genetics are increasingly applied to dissect the complex interaction of KSHV with endothelial cells. This review will outline novel results and pitfalls of these technologies in the elucidation of KSHV pathogenicity.

The crystal structure of the varicella-zoster Orf24-Orf27 nuclear egress complex spotlights multiple determinants of herpesvirus subfamily specificity - Schweininger, Johannes; Kriegel, Mark; Häge, Sigrun; Conrad, Marcus; Alkhashrom, Sewar; Lösing, Josephine; Weiler, Sigrid; Tillmanns, Julia; Egerer-Sieber, Claudia; Decker, Andrea; Rovis, Tihana Lenac; Eichler, Jutta; et al. (Journal of Biological Chemistry, 2022)
Varicella-zoster virus (VZV) is a human pathogen from the α-subfamily of herpesviruses. The VZV Orf24-Orf27 complex represents the essential viral core nuclear egress complex (NEC) that orchestrates the egress of the preassembled virus capsids from the nucleus. While previous studies have primarily emphasized that the architecture of core NEC complexes is highly conserved among herpesviruses, the present report focuses on subfamily-specific structural and functional features that help explain the differences in the autologous versus nonautologous interaction patterns observed for NEC formation across herpesviruses. Here, we describe the crystal structure of the Orf24-Orf27 complex at 2.1 Å resolution. Coimmunoprecipitation and confocal imaging data show that Orf24-Orf27 complex formation displays some promiscuity in a herpesvirus subfamily-restricted manner. At the same time, analysis of thermodynamic parameters of NEC formation of three prototypical α-, β-, and γ herpesviruses, i.e., VZV, human cytomegalovirus (HCMV), and Epstein-Barr virus (EBV), revealed highly similar binding affinities for the autologous interaction with specific differences in enthalpy and entropy. Computational alanine scanning, structural comparisons, and mutational data highlight intermolecular interactions shared among α-herpesviruses that are clearly distinct from those seen in β- and γ-herpesviruses, including a salt bridge formed between Orf24-Arg167 and Orf27-Asp126. This interaction is located outside of the hook-into-groove interface and contributes significantly to the free energy of complex formation. Combined, these data explain distinct properties of specificity and permissivity so far observed in herpesviral NEC interactions. These findings will prove valuable in attempting to target multiple herpesvirus core NECs with selective or broadacting drug candidates.
CRIS-Team Scopus Importer:2022-03-04

The cyclin-dependent kinase ortholog pUL97 of human cytomegalovirus interacts with cyclins - Graf, Laura; Webel, Rike; Wagner, Sabrina; Hamilton, Stuart T.; Rawlinson, William D.; Sticht, Heinrich; Marschall, Manfred (Viruses, 2013)
The human cytomegalovirus (HCMV)-encoded protein kinase, pUL97, is considered a cyclin-dependent kinase (CDK) ortholog, due to shared structural and functional characteristics. The primary mechanism of CDK activation is binding to corresponding cyclins, including cyclin T1, which is the usual regulatory cofactor of CDK9. This study provides evidence of direct interaction between pUL97 and cyclin T1 using yeast two-hybrid and co-immunoprecipitation analyses. Confocal immunofluorescence revealed partial colocalization of pUL97 with cyclin T1 in subnuclear compartments, most pronounced in viral replication centres. The distribution patterns of pUL97 and cyclin T1 were independent of HCMV strain and host cell type. The sequence domain of pUL97 responsible for the interaction with cyclin T1 was between amino acids 231-280. Additional co-immunoprecipitation analyses showed cyclin B1 and cyclin A as further pUL97 interaction partners. Investigation of the pUL97-cyclin T1 interaction in an ATP consumption assay strongly suggested phosphorylation of pUL97 by the CDK9/cyclin T1 complex in a substrate concentration-dependent manner. This is the first demonstration of interaction between a herpesviral CDK ortholog and cellular cyclins.
EVALuna2:8102

The cytokine response of circulating immune cells to rhinovirus is reduced in severe asthma - Jamal, Jameel K.; Yanik, S.; Buelthoff, E.; Yusuf, F.; Struck, B.; Rohde, S.; Pfeifer, K.; Kronsbein, J.; Koch, A.; Tenbusch, Matthias; Knobloch, J. (PNEUMOLOGIE, 2020)
CRIS-Team WoS Importer:2020-11-27

The cytomegalovirus egress proteins pUL50 and pUL53 are translocated to the nuclear envelope through two distinct modes of nuclear import - Schmeiser, Cathrin; Borst, Eva; Sticht, Heinrich; Marschall, Manfred; Milbradt, Jens (Journal of General Virology, 2013)
The nucleocytoplasmic export of cytomegaloviral capsids is regulated by formation of a multi-component nuclear egress complex (NEC), essentially based on viral proteins pUL50 and pUL53. In this study, the generation of recombinant human cytomegaloviruses, expressing tagged versions of pUL50 and pUL53, enabled the investigation of NEC formation in infected primary fibroblasts. For these recombinant viruses, a wild-type-like mode of pUL50-pUL53 interaction and recruitment of both proteins to the nuclear envelope could be demonstrated. Importantly, pUL50 was translocated from an initial cytoplasmic distribution to the nuclear rim, whereas pUL53 accumulated in the nucleus before attaining overall rim colocalization with pUL50. Specified experimental settings illustrated that pUL50 and pUL53 were subject to different pathways of intracellular trafficking. Importantly, a novel nuclear localization signal (NLS) could be identified and functionally verified for pUL53 (amino acids 18-27), whereas no NLS was present in pUL50. Analysis of amino acid replacement mutants further illustrated the differential modes of nuclear import of the two essential viral egress proteins. Taken together, our findings suggest a combination of classical nuclear import (pUL53) and interaction-mediated recruitment (pUL50) as the driving forces for core NEC formation and viral nuclear egress.
EVALuna2:8188

The cytomegalovirus protein kinase pUL97: Host interactions, regulatory mechanisms and antiviral drug targeting - Steingruber, Mirjam; Marschall, Manfred (Microorganisms, 2020)
Human cytomegalovirus (HCMV) expresses a variety of viral regulatory proteins that undergo close interaction with host factors including viral-cellular multiprotein complexes. The HCMV protein kinase pUL97 represents a viral cyclin-dependent kinase ortholog (vCDK) that determines the efficiency of HCMV replication via phosphorylation of viral and cellular substrates. A hierarchy of functional importance of individual pUL97-mediated phosphorylation events has been discussed; however, the most pronounced pUL97-dependent phenotype could be assigned to viral nuclear egress, as illustrated by deletion of the UL97 gene or pharmacological pUL97 inhibition. Despite earlier data pointing to a cyclin-independent functionality, experimental evidence increasingly emphasized the role of pUL97-cyclin complexes. Consequently, the knowledge about pUL97 involvement in host interaction, viral nuclear egress and additional replicative steps led to the postulation of pUL97 as an antiviral target. Indeed, validation experiments in vitro and in vivo confirmed the sustainability of this approach. Consequently, current investigations of pUL97 in antiviral treatment go beyond the known pUL97-mediated ganciclovir prodrug activation and henceforward include pUL97-specific kinase inhibitors. Among a number of interesting small molecules analyzed in experimental and preclinical stages, maribavir is presently investigated in clinical studies and, in the near future, might represent a first kinase inhibitor applied in the field of antiviral therapy.
CRIS-Team Scopus Importer:2020-04-24
Keywords: Antiviral drugs; Cyclin/cyclin-dependent kinase complexes; Human cytomegalovirus (HCMV); Kinase-host interactions; Protein kinase pUL97; Regulatory mechanisms

The Ebola virus glycoprotein and HIV-1 Vpu employ different strategies to counteract the antiviral factor tetherin. - Kühl, Annika; Banning, Carina; Marzi, Andrea; Votteler, Jörg; Steffen, Imke; Bertram, Stephanie; Glowacka, Ilona; Konrad, Andreas; Stürzl, Michael; Guo, Ju-Tao; Schubert, Ulrich; Feldmann, Heinz; et al. (Journal of Infectious Diseases, 2011)
The antiviral protein tetherin/BST2/CD317/HM1.24 restricts cellular egress of human immunodeficiency virus (HIV) and of particles mimicking the Ebola virus (EBOV), a hemorrhagic fever virus. The HIV-1 viral protein U (Vpu) and the EBOV-glycoprotein (EBOV-GP) both inhibit tetherin. Here, we compared tetherin counteraction by EBOV-GP and Vpu. We found that EBOV-GP but not Vpu counteracted tetherin from different primate species, indicating that EBOV-GP and Vpu target tetherin differentially. Tetherin interacted with the GP2 subunit of EBOV-GP, which might encode the determinants for tetherin counteraction. Vpu reduced cell surface expression of tetherin while EBOV-GP did not, suggesting that both proteins employ different mechanisms to counteract tetherin. Finally, Marburg virus (MARV)-GP also inhibited tetherin and downregulated tetherin in a cell type-dependent fashion, indicating that tetherin antagonism depends on the cellular source of tetherin. Collectively, our results indicate that EBOV-GP counteracts tetherin by a novel mechanism and that tetherin inhibition is conserved between EBOV-GP and MARV-GP.

The ephrin receptor tyrosine kinase A2 is a cellular receptor for Kaposi's sarcoma-associated herpesvirus - Hahn, Alexander; Kaufmann, Johanna K.; Wies, Effi; Naschberger, Elisabeth; Panteleev-Ivlev, Julia; Schmidt, Katharina; Holzer, Angela; Schmidt, Martin; Chen, Jin; Koenig, Simone; Enßer, Armin; Myoung, Jinjong; et al. (Nature Medicine, 2012)
Kaposi's sarcoma-associated herpesvirus (KSHV) is the causative agent of Kaposi's sarcoma, a highly vascularized tumor originating from lymphatic endothelial cells, and of at least two different B cell malignancies. A dimeric complex formed by the envelope glycoproteins H and L (gH-gL) is required for entry of herpesviruses into host cells. We show that the ephrin receptor tyrosine kinase A2 (EphA2) is a cellular receptor for KSHV gH-gL. EphA2 co-precipitated with both gH-gL and KSHV virions. Infection of human epithelial cells with a GFP-expressing recombinant KSHV strain, as measured by FACS analysis, was increased upon overexpression of EphA2. Antibodies against EphA2 and siRNAs directed against EphA2 inhibited infection of endothelial cells. Pretreatment of KSHV with soluble EphA2 resulted in inhibition of KSHV infection by up to 90%. This marked reduction of KSHV infection was seen with all the different epithelial and endothelial cells used in this study. Similarly, pretreating epithelial or endothelial cells with the soluble EphA2 ligand ephrinA4 impaired KSHV infection. Deletion of the gene encoding EphA2 essentially abolished KSHV infection of mouse endothelial cells. Binding of gH-gL to EphA2 triggered EphA2 phosphorylation and endocytosis, a major pathway of KSHV entry. Quantitative RT-PCR and in situ histochemistry revealed a close correlation between KSHV infection and EphA2 expression both in cultured cells derived from human Kaposi's sarcoma lesions or unaffected human lymphatic endothelium, and in situ in Kaposi's sarcoma specimens, respectively. Taken together, our results identify EphA2, a tyrosine kinase with known functions in neovascularization and oncogenesis, as an entry receptor for KSHV. © 2012 Nature America, Inc. All rights reserved.
Created from Fastlane, Scopus look-up

The global spread of HIV-1 subtype B epidemic - Magiorkinis, Gkikas; Angelis, Konstantinos; Mamais, Ioannis; Katzourakis, Aris; Hatzakis, Angelos; Albert, Jan; Lawyer, Glenn; Hamouda, Osamah; Struck, Daniel; Vercauteren, Jurgen; Wensing, Annemarie; Alexiev, Ivailo; et al. (Infection Genetics and Evolution, 2016)
Human immunodeficiency virus type 1 (HIV-1) was discovered in the early 1980s when the virus had already established a pandemic. For at least three decades the epidemic in the Western World has been dominated by subtype B infections, as part of a sub-epidemic that traveled from Africa through Haiti to United States. However, the pattern of the subsequent spread still remains poorly understood. Here we analyze a large dataset of globally representative HIV-1 subtype B strains to map their spread around the world over the last 50years and describe significant spread patterns. We show that subtype B travelled from North America to Western Europe in different occasions, while Central/Eastern Europe remained isolated for the most part of the early epidemic. Looking with more detail in European countries we see that the United Kingdom, France and Switzerland exchanged viral isolates with non-European countries than with European ones. The observed pattern is likely to mirror geopolitical landmarks in the post-World War II era, namely the rise and the fall of the Iron Curtain and the European colonialism. In conclusion, HIV-1 spread through specific migration routes which are consistent with geopolitical factors that affected human activities during the last 50years, such as migration, tourism and trade. Our findings support the argument that epidemic control policies should be global and incorporate political and socioeconomic factors.
EVALuna2:8331

The HIV 5' Gag Region Displays a Specific Nucleotide Bias Regulating Viral Splicing and Infectivity - Grewe, Bastian; Vogt, Carolin; Horstkötter, Theresa; Tippler, Bettina; Xiao, Han; Müller, Bianca; Überla, Klaus; Wagner, Ralf; Asbach, Benedikt; Bohne, Jens (Viruses, 2021)
Alternative splicing and the expression of intron-containing mRNAs is one hallmark of HIV gene expression. To facilitate the otherwise hampered nuclear export of non-fully processed mRNAs, HIV encodes the Rev protein, which recognizes its intronic response element and fuels the HIV RNAs into the CRM-1-dependent nuclear protein export pathway. Both alternative splicing and Rev-dependency are regulated by the primary HIV RNA sequence. Here, we show that these processes are extremely sensitive to sequence alterations in the 5'coding region of the HIV genomic RNA. Increasing the GC content by insertion of either GFP or silent mutations activates a cryptic splice donor site in gag, entirely deregulates the viral splicing pattern, and lowers infectivity. Interestingly, an adaptation of the inserted GFP sequence toward an HIV-like nucleotide bias reversed these phenotypes completely. Of note, the adaptation yielded completely different primary sequences although encoding the same amino acids. Thus, the phenotypes solely depend on the nucleotide composition of the two GFP versions. This is a strong indication of an HIV-specific mRNP code in the 5' gag region wherein the primary RNA sequence bias creates motifs for RNA-binding proteins and controls the fate of the HIV-RNA in terms of viral gene expression and infectivity.
CRIS-Team Scopus Importer:2021-06-18
Keywords: alternative splicing; HIV gene expression; mRNP code; U1 snRNP

The human CIB1-EVER1-EVER2 complex governs keratinocyte-intrinsic immunity to beta-papillomaviruses - De Jong, Sarah Jill; Crequer, Amandine; Matos, Irina; Hum, David; Gunasekharan, Vignesh; Lorenzo, Lazaro; Jabot-Hanin, Fabienne; Imahorn, Elias; Arias, Andres A.; Vahidnezhad, Hassan; Youssefian, Leila; Markle, Janet G.; et al. (Journal of Experimental Medicine, 2018)
Patients with epidermodysplasia verruciformis (EV) and biallelic null mutations of TMC6 (encoding EVER1) or TMC8 (EVER2) are selectively prone to disseminated skin lesions due to keratinocyte-tropic human beta-papillomaviruses (beta-HPVs), which lack E5 and E8. We describe EV patients homozygous for null mutations of the CIB1 gene encoding calcium-and integrin-binding protein-1 (CIB1). CIB1 is strongly expressed in the skin and cultured keratinocytes of controls but not in those of patients. CIB1 forms a complex with EVER1 and EVER2, and CIB1 proteins are not expressed in EVER1- or EVER2-deficient cells. The known functions of EVER1 and EVER2 in human keratinocytes are not dependent on CIB1, and CIB1 deficiency does not impair keratinocyte adhesion or migration. In keratinocytes, the CIB1 protein interacts with the HPV E5 and E8 proteins encoded by alpha-HPV16 and gamma-HPV4, respectively, suggesting that this protein acts as a restriction factor against HPVs. Collectively, these findings suggest that the disruption of CIB1-EVER1-EVER2-dependent keratinocyte-intrinsic immunity underlies the selective susceptibility to beta-HPVs of EV patients.
EVALuna2:35267

The Human CMV IE1 Protein: An Offender of PML Nuclear Bodies - Scherer, Myriam; Schilling, Eva-Maria; Stamminger, Thomas (Advances in Anatomy Embryology and Cell Biology, 2017)
PML nuclear bodies (PML-NBs) are SUMOylation-dependent, highly complex protein assemblies that accumulate in the interchromosomal territories of the cell nucleus. Research of the last two decades revealed that many viruses have evolved effector proteins that modify PML-NBs. This correlates with antagonization of individual PML-NB components which act as host cell restriction factors. The multifunctional immediate-early protein IE1 of human cytomegalovirus directly interacts with the PML protein resulting in a disruption of the dot-like structure of PML-NBs. This review summarizes recent advances on the functional consequences of PML-NB modification by IE1. In particular, we describe that PML exerts a novel co-regulatory role during the interferon response which is abrogated by IE1. Via binding to PML, IE1 is able to compromise both intrinsic antiviral defense mechanisms and classical innate immune responses. These interactions of IE1 with innate host defenses are crucial for the onset of lytic replication and, consequently, may represent promising targets for antiviral strategies.
EVALuna2:35297

The human cytomegalovirus IE1 protein antagonizes PML nuclear body-mediated intrinsic immunity via the inhibition of PML de novo SUMOylation - Schilling, Eva-Maria; Scherer, Myriam; Reuter, Nina; Schweininger, Johannes; Muller, Yves; Stamminger, Thomas (Journal of Virology, 2017)
PML nuclear bodies (NBs) are accumulations of cellular proteins embedded in a scaffold-like structure built by SUMO-modified PML/TRIM19. PML and other NB proteins act as cellular restriction factors against human cytomegalovirus (HCMV); however, this intrinsic defense is counteracted by the immediate early protein 1 (IE1) of HCMV. IE1 directly interacts with the PML coiled-coil domain via its globular core region and disrupts NB foci by inducing a loss of PML SUMOylation. Here, we demonstrate that IE1 acts via abrogating the de novo SUMOylation of PML. In order to overcome reversible SUMOylation dynamics, we made use of a cell-based assay that combines inducible IE1 expression with a SUMO mutant resistant to SUMO proteases. Interestingly, we observed that IE1 expression did not affect preSUMOylated PML; however, it clearly prevented de novo SUMO conjugation. Consistent results were obtained by in vitro SUMOylation assays, demonstrating that IE1 alone is sufficient for this effect. Furthermore, IE1 acts in a selective manner, since K160 was identified as the main target lysine. This is strengthened by the fact that IE1 also prevents AsO-mediated hyperSUMOylation of K160, thereby blocking PML degradation. Since IE1 did not interfere with coiled-coil-mediated PML dimerization, we propose that IE1 affects PML autoSUMOylation either by directly abrogating PML E3 ligase function or by preventing access to SUMO sites. Thus, our data suggest a novel mechanism for how a viral protein counteracts a cellular restriction factor by selectively preventing the de novo SUMOylation at specific lysine residues without affecting global protein SUMOylation.
EVALuna2:33771
Keywords: Human cytomegalovirus; Immediate early 1; Intrinsic immunity; Nuclear domain 10; PML nuclear bodies; Sumoylation

The human cytomegalovirus nuclear egress complex unites multiple functions: Recruitment of effectors, nuclear envelope rearrangement, and docking to nuclear capsids - Marschall, Manfred; Muller, Yves; Diewald, Benedikt; Sticht, Heinrich; Milbradt, Jens (Reviews in Medical Virology, 2017)
Keywords: antiviral drugs; capsid-NEC docking; herpesviruses; human cytomegalovirus; nuclear egress complex

The improved antibody response against HIV-1 after a vaccination based on intrastructural help is complemented by functional CD8+ T cell responses - Bonsmann, Michael Storcksdieck Genannt; Niezold, Thomas; Hannaman, Drew; Überla, Klaus; Tenbusch, Matthias (Vaccine, 2016)
Despite more than three decades of intense research, a prophylactic HIV-1 vaccine remains elusive. Four vaccine modalities have been evaluated in clinical efficacy studies, but only one demonstrated at least modest efficacy, which correlated with polyfunctional antibody responses to the HIV surface protein Env. To be most effective, a HIV-1 vaccine probably has to induce both, functional antibody and CD8(+) T cell responses. We therefore analyzed DNA/DNA and DNA/virus-like particle (VLP) regimens for their ability to induce humoral and cellular immune responses. Here, DNA vaccination of mice induced strong CD8(+) responses against Env and Gag. However, the humoral response to Env was dominated by IgG1, a subclass known for its low functionality. In contrast, priming only with the Gag-encoding plasmid followed by a boost with VLPs consisting of Gag and Env improved the quality of the anti-Env antibody response via intrastructural help (ISH) provided by Gag-specific T cells to Env-specific B cells. Furthermore, the Gag-specific CD8(+) T cells induced by the DNA prime immunization could still protect from a lethal infection with recombinant vaccinia virus encoding HIV Gag. Therefore, this immunization regimen represents a promising approach to combine functional antibody responses toward HIV Env with strong CD8(+) responses controlling early viral replication.
EVALuna2:8340

The interaction between cyclin B1 and cytomegalovirus protein kinase pUL97 is determined by an active kinase domain - Steingruber, Mirjam; Socher, Eileen; Hutterer, Corina; Webel, Rike; Bergbrede, Tim; Lenac, Tihana; Sticht, Heinrich; Marschall, Manfred (Viruses, 2015)
Replication of human cytomegalovirus (HCMV) is characterized by a tight virus-host cell interaction. Cyclin-dependent protein kinases (CDKs) are functionally integrated into viral gene expression and protein modification. The HCMV-encoded protein kinase pUL97 acts as a CDK ortholog showing structural and functional similarities. Recently, we reported an interaction between pUL97 kinase with a subset of host cyclins, in particular with cyclin T1. Here, we describe an interaction of pUL97 at an even higher affinity with cyclin B1. As a striking feature, the interaction between pUL97 and cyclin B1 proved to be strictly dependent on pUL97 activity, as interaction could be abrogated by treatment with pUL97 inhibitors or by inserting mutations into the conserved kinase domain or the nonconserved C-terminus of pUL97, both producing loss of activity. Thus, we postulate that the mechanism of pUL97-cyclin B1 interaction is determined by an active pUL97 kinase domain.
Keywords: Active conformation; CDK ortholog; Cyclin B; Human cytomegalovirus; Kinase activity; Mode of kinase-cyclin interaction; Protein kinase pUL97; Protein-protein interaction

The Interactive Complex between Cytomegalovirus Kinase vCDK/pUL97 and Host Factors CDK7-Cyclin H Determines Individual Patterns of Transcription in Infected Cells. - Schütz, Martin; Cordsmeier, Arne; Wangen, Christina; Horn, Anselm; Wyler, Emanuel; Enßer, Armin; Sticht, Heinrich; Marschall, Manfred (International Journal of Molecular Sciences, 2023)
The infection of human cytomegalovirus (HCMV) is strongly determined by the host-cell interaction in a way that the efficiency of HCMV lytic replication is dependent on the regulatory interplay between viral and cellular proteins. In particular, the activities of protein kinases, such as cyclin-dependent kinases (CDKs) and the viral CDK ortholog (vCDK/pUL97), play an important role in both viral reproduction and virus-host interaction. Very recently, we reported on the complexes formed between vCDK/pUL97, human cyclin H, and CDK7. Major hallmarks of this interplay are the interaction between cyclin H and vCDK/pUL97, which is consistently detectable across various conditions and host cell types of infection, the decrease or increase in pUL97 kinase activity resulting from cyclin H knock-down or elevated levels, respectively, and significant trans-stimulation of human CDK7 activity by pUL97 in vitro. Due to the fact that even a ternary complex of vCDK/pUL97-cyclin H-CDK7 can be detected by coimmunoprecipitation and visualized by bioinformatic structural modeling, we postulated a putative impact of the respective kinase activities on the patterns of transcription in HCMV-infected cells. Here, we undertook a first vCDK/pUL97-specific transcriptomic analysis, which combined conditions of fully lytic HCMV replication with those under specific vCDK/pUL97 or CDK7 drug-mediated inhibition or transient cyclin H knockout. The novel results were further strengthened using bioinformatic modeling of the involved multi-protein complexes. Our data underline the importance of these kinase activities for the C-terminal domain (CTD) phosphorylation-driven activation of host RNA polymerase in HCMV-infected cells. The impact of the individual experimental conditions on differentially expressed gene profiles is described in detail and discussed.
EVALuna2:545510

The Kaposi's sarcoma-associated herpesvirus-encoded vIRF-3 inhibits cellular IRF-5 - Wies, Effi; Hahn, Alexander; Schmidt, Katharina; Viebahn, Cornelia; Rohland, Nadine; Lux, Anja; Schellhorn, Tim; Holzer, Angela; Jung, Jae U.; Neipel, Frank (Journal of Biological Chemistry, 2009)
Kaposi's sarcoma-associated herpesvirus encodes four genes with homology to the family of interferon regulatory factors (IRFs). At least one of these viral IRFs, vIRF-3, is expressed in latently Kaposi's sarcoma-associated herpesvirus-infected primary effusion lymphoma (PEL) cells and is essential for the survival of PEL cells. We now report that vIRF-3 interacts with cellular IRF-5, thereby inhibiting binding of IRF-5 to interferon-responsive promoter elements. Consequently, vIRF-3 blocked IRF-5-mediated promoter activation. A central double helix motif present in vIRF-3 was sufficient to abrogate both DNA binding and transcriptional transactivation by IRF-5. Upon DNA damage or activation of the interferon or Toll-like receptor pathways, cytoplasmic IRF-5 has been reported to be translocated to the nucleus, which results in induction of both p53-independent apoptosis and p21-mediated cell cycle arrest. We report here that IRF-5 is present in the nuclei of PEL cells without interferon stimulation. Silencing of vIRF-3 expression in PEL cells was accompanied by increased sensitivity to interferon- mediated apoptosis and up-regulation of IRF-5 target genes. In addition, vIRF-3 antagonized IRF-5-mediated activation of the p21 promoter. The data presented here indicate that vIRF-3 contributes to immune evasion and sustained proliferation of PEL cells by releasing IRF-5 from transcription complexes. © 2009 by The American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2022-09-23

The Major Immediate-Early Protein IE2 of Human Cytomegalovirus Is Sufficient to Induce Proteasomal Degradation of CD83 on Mature Dendritic Cells - Heilingloh, Christiane; Grosche, Linda; Kummer, Mirko; Mühl-Zürbes, Petra; Kamm, Lisa; Scherer, Myriam; Latzko, Melanie; Stamminger, Thomas; Steinkasserer, Alexander (Frontiers in Microbiology, 2017)
Human cytomegalovirus (HCMV) is the prototypic beta-herpesvirus and widespread throughout the human population. While infection is asymptomatic in healthy individuals, it can lead to high morbidity and mortality in immunocompromised persons. Importantly, HCMV evolved multiple strategies to interfere with immune cell function in order to establish latency in infected individuals. As mature DCs (mDCs) are antigen-presenting cells able to activate naïve T cells they play a crucial role during induction of effective antiviral immune responses. Interestingly, earlier studies demonstrated that the functionally important mDC surface molecule CD83 is down-regulated upon HCMV infection resulting in a reduced T cell stimulatory capacity of the infected cells. However, the viral effector protein and the precise mechanism of HCMV-mediated CD83 reduction remain to be discovered. Using flow cytometric analyses, we observed significant down-modulation of CD83 surface expression becoming significant already 12 h after HCMV infection. Moreover, Western bot analyses revealed that, in sharp contrast to previous studies, loss of CD83 is not restricted to the membrane-bound molecule, but also occurs intracellularly. Furthermore, inhibition of the proteasome almost completely restored CD83 surface expression during HCMV infection. Results of infection kinetics and cycloheximide-actinomycin D-chase experiments, strongly suggested that an HCMV immediate early gene product is responsible for the induction of CD83 down-modulation. Consequently, we were able to identify the major immediate early protein IE2 as the viral effector protein that induces proteasomal CD83 degradation.
EVALuna2:26039

The ND10 Component Promyelocytic Leukemia Protein Acts as an E3 Ligase for SUMOylation of the Major Immediate Early Protein IE1 of Human Cytomegalovirus - Reuter, Nina; Schilling, Eva-Maria; Scherer, Myriam; Müller, Regina; Stamminger, Thomas (Journal of Virology, 2017)
Previous studies identified the nuclear domain 10 (ND10) components promyelocytic leukemia protein (PML), hDaxx, and Sp100 as factors of an intrinsic immune response against human cytomegalovirus (HCMV). This antiviral function of ND10, however, is antagonized by viral effector proteins like IE1p72, which induces dispersal of ND10. Furthermore, we have shown that both major immediate early proteins of HCMV, IE1p72 and IE2p86, transiently colocalize with ND10 subnuclear structures and undergo modification by the covalent attachment of SUMO. Since recent reports indicate that PML acts as a SUMO E3 ligase, we asked whether the SUMOylation of IE1p72 and IE2p86 is regulated by PML. To address this, PML-depleted fibroblasts, as well as cells overexpressing individual PML isoforms, were infected with HCMV. Western blot experiments revealed a clear correlation between the degree of IE1p72 SUMO conjugation and the abundance of PML. On the other hand, the SUMOylation of IE2p86 was not affected by PML. By performingin vitroSUMOylation assays, we were able to provide direct evidence that IE1p72 is a substrate for PML-mediated SUMOylation. Interestingly, disruption of the RING finger domain of PML, which is proposed to confer SUMO E3 ligase activity, abolished PML-induced SUMOylation of IE1p72. In contrast, IE1p72 was still efficiently SUMO modified by a SUMOylation-defective PML mutant, indicating that intact ND10 bodies are not necessary for this effect. Thus, this is the first report that the E3 ligase PML is capable of stimulating the SUMOylation of a viral protein which is supposed to serve as a cellular mechanism to compromise specific functions of IE1p72.IMPORTANCEThe major immediate early proteins of human cytomegalovirus, termed IE1p72 and IE2p86, have previously been shown to undergo posttranslational modification by covalent coupling to SUMO moieties at specific lysine residues. However, the enzymatic activities that are responsible for this modification have not been identified. Here, we demonstrate that the PML protein, which mediates an intrinsic immune response against HCMV, specifically serves as an E3 ligase for SUMO modification of IE1p72. Since SUMO modification of IE1p72 has previously been shown to interfere with STAT factor binding, thus compromising the interferon-antagonistic function of this viral effector protein, our finding highlights an additional mechanism through which PML is able to restrict viral infections.
EVALuna2:33764

The N-Terminus of the HIV-1 p6 Gag Protein Regulates Susceptibility to Degradation by IDE - Schmalen, Adrian; Karius-Fischer, Julia; Rauch, Pia; Setz, Christian; Korn, Klaus; Henklein, Petra; Fossen, Torgils; Schubert, Ulrich (Viruses, 2018)
As part of the Pr55(Gag) polyprotein, p6 fulfills an essential role in the late steps of the replication cycle. However, almost nothing is known about the functions of the mature HIV-1 p6 protein. Recently, we showed that p6 is a bona fide substrate of the insulin-degrading enzyme (IDE), a ubiquitously expressed zinc metalloprotease. This phenomenon appears to be specific for HIV-1, since p6 homologs of HIV-2, SIV and EIAV were IDE-insensitive. Furthermore, abrogation of the IDE-mediated degradation of p6 reduces the replication capacity of HIV-1 in an Env-dependent manner. However, it remained unclear to which extent the IDE mediated degradation is phylogenetically conserved among HIV-1. Here, we describe two HIV-1 isolates with IDE resistant p6 proteins. Sequence comparison allowed deducing one single amino acid regulating IDE sensitivity of p6. Exchanging the N-terminal leucine residue of p6 derived from the IDE sensitive isolate HIV-1(NL4-3) with proline enhances its stability, while replacing Pro-1 of p6 from the IDE insensitive isolate SG3 with leucine restores susceptibility towards IDE. Phylogenetic analyses of this natural polymorphism revealed that the N-terminal leucine is characteristic for p6 derived from HIV-1 group M except for subtype A, which predominantly expresses p6 with an N-terminal proline. Consequently, p6 peptides derived from subtype A are not degraded by IDE. Thus, IDE mediated degradation of p6 is specific for HIV-1 group M isolates and not occasionally distributed among HIV-1.
EVALuna2:35256

The Oligomeric Assemblies of Cytomegalovirus Core Nuclear Egress Proteins Are Associated with Host Kinases and Show Sensitivity to Antiviral Kinase Inhibitors - Kicuntod, Jintawee; Häge, Sigrun; Hahn, Friedrich; Sticht, Heinrich; Marschall, Manfred (Viruses, 2022)
The nucleo-cytoplasmic capsid egress of herpesviruses is a unique regulated process that ensures the efficiency of viral replication and release. For human cytomegalovirus (HCMV), the core of the nuclear egress complex (NEC) consists of the pUL50–pUL53 heterodimer that is able to oligomerize and thus to build hexameric lattices. These structures determine capsid binding and multicomponent protein interaction including NEC-associated host factors. The underlying characteristic of the core NEC formation is based on the N-terminal hook structure of pUL53 that binds into an alpha-helical groove of pUL50, and is thus described as a hook-into-groove interaction. This central regulatory element has recently been validated as a target of antiviral strategies, and first NEC-targeted prototypes of inhibitory small molecules were reported by our previous study. Here, we further analyzed the oligomerization properties of the viral NEC through an approach of chemical protein cross-linking. Findings were as follows: (i) a cross-link approach demonstrated the oligomeric state of the HCMV core NEC using material from HCMV-infected or plasmid-transfected cells, (ii) a Western blot-based identification of NEC-associated kinases using the cross-linked multicomponent NECs was successful, and (iii) we demonstrated the NEC-inhibitory and antiviral activity of specific inhibitors directed to these target kinases. Combined, the results strongly underline the functional importance of the oligomerization of the HCMV-specific NEC that is both phosphorylation-dependent and sensitive to antiviral kinase inhibitors.
CRIS-Team Scopus Importer:2022-06-03
Keywords: associated protein kinases; core NEC pUL50-pUL53; cross-linking; cyclin-dependent kinases (CDKs); human cytomegalovirus; kinase inhibitors; NEC as an antiviral target; NEC-inhibitory potential; nuclear egress complex (NEC); oligomerization; viral nucleocytoplasmic egress

The peptidyl-prolyl cis/trans isomerase Pin1 interacts with three early regulatory proteins of human cytomegalovirus - Schütz, Martin; Thomas, Marco; Wangen, Christina; Wagner, Sabrina; Rauschert, Luisa; Errerd, Theresa; Kießling, Melissa; Sticht, Heinrich; Milbradt, Jens; Marschall, Manfred (Virus Research, 2020)
Human cytomegalovirus (HCMV) is a ubiquitous human pathogen of high clinical relevance. Despite intensive research of virus-host interaction, crucial details still remain unknown. In this study, the role of the cellular peptidyl-prolyl cis/trans isomerase Pin1 during HCMV infection was investigated. Pin1 is able to recognize phosphorylated serine/threonine-proline motifs and regulates the structural conformation, stability and function of its substrates. Concerning HCMV replication, our recent studies revealed that Pin1 plays an important role in viral nuclear egress by contributing to the depletion of the nuclear lamina at distinct sites through the cis/trans conversion of lamin proteins. Here, novel data illustrate the HCMV-induced upregulation of Pin1 including various cell types being permissive, semi-permissive or non-permissive for productive HCMV replication. Addressing the question of functional impact, Pin1 knock-out (KO) did not show a measurable effect on viral protein expression, at least when assessed by Western blot analysis. Applying highly sensitive methods of qPCR and plaque titration, a pharmacological inhibition of Pin1 activity, however, led to a significant decrease of viral genome equivalents and production of infectious virus, respectively. When focusing on the identification of viral proteins interacting with Pin1 by various coimmunoprecipitation (CoIP) settings, we obtained positive signals for (i) the core nuclear egress complex protein pUL50, (ii) the viral mRNA export factor pUL69 and (iii) the viral DNA polymerase processivity factor pUL44. Confocal immunofluorescence analysis focusing on partial colocalization between Pin1 and the coexpressed viral proteins pUL50, pUL69 or pUL44, respectively, was consistent with the CoIP experiments. Mapping experiments, using transient expression constructs for a series of truncated protein versions and specific replacement mutants, revealed a complex pattern of Pin1 interaction with these three early regulatory HCMV proteins. Data suggest a combination of different modes of Pin1 interactions, involving both classical phosphorylation-dependent Pin1 binding motifs and additional phosphorylation-independent binding sites. Combined, these results support the concept that Pin1 may play an important role in several stages of HCMV infection, thus determining viral replicative efficiency.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Cytomegalovirus replication; Phosphorylation-independent interaction; Pin1 inhibitor-mediated viral replication block; Pin1 interaction with pUL50; Pin1 upregulation; Prolyl cis/trans isomerase Pin1; pUL44; pUL69

The Prolyl Isomerase Pin1 Promotes the Herpesvirus-Induced Phosphorylation-Dependent Disassembly of the Nuclear Lamina Required for Nucleocytoplasmic Egress - Milbradt, Jens; Hutterer, Corina; Bahsi, Hanife; Wagner, Sabrina; Sonntag, Ellen; Horn, Anselm; Kaufer, Benedikt B.; Mori, Yasuko; Sticht, Heinrich; Fossen, Torgils; Marschall, Manfred (PLoS Pathogens, 2016)
The nuclear lamina lines the inner nuclear membrane providing a structural framework for the nucleus. Cellular processes, such as nuclear envelope breakdown during mitosis or nuclear export of large ribonucleoprotein complexes, are functionally linked to the disassembly of the nuclear lamina. In general, lamina disassembly is mediated by phosphorylation, but the precise molecular mechanism is still not completely understood. Recently, we suggested a novel mechanism for lamina disassembly during the nuclear egress of herpesviral capsids which involves the cellular isomerase Pin1. In this study, we focused on mechanistic details of herpesviral nuclear replication to demonstrate the general importance of Pin1 for lamina disassembly. In particular, Ser22-specific lamin phosphorylation consistently generates a Pin1-binding motif in cells infected with human and animal alpha-, beta-, and gammaherpesviruses. Using nuclear magnetic resonance spectroscopy, we showed that binding of Pin1 to a synthetic lamin peptide induces its cis/trans isomerization in vitro. A detailed bioinformatic evaluation strongly suggests that this structural conversion induces large-scale secondary structural changes in the lamin N-terminus. Thus, we concluded that a Pin1-induced conformational change of lamins may represent the molecular trigger responsible for lamina disassembly. Consistent with this concept, pharmacological inhibition of Pin1 activity blocked lamina disassembly in herpesvirus-infected fibroblasts and consequently impaired virus replication. In addition, a phospho-mimetic Ser22Glu lamin mutant was still able to form a regular lamina structure and overexpression of a Ser22-phosphorylating kinase did not induce lamina disassembly in Pin1 knockout cells. Intriguingly, this was observed in absence of herpesvirus infection proposing a broader importance of Pin1 for lamina constitution. Thus, our results suggest a functional model of similar events leading to disassembly of the nuclear lamina in response to herpesviral or inherent cellular stimuli. In essence, Pin1 represents a regulatory effector of lamina disassembly that promotes the nuclear pore-independent egress of herpesviral capsids.
EVALuna2:8308

The saliva of probands sucking an iota-carrageenan containing lozenge inhibits viral binding and replication of the most predominant common cold viruses and SARS-CoV-2 - Morokutti-Kurz, Martina; Unger-Manhart, Nicole; Graf, Philipp; Rauch, Pia; Kodnar, Julia; Große, Maximilian; Setz, Christian; Savli, Markus; Ehrenreich, Friedrich; Grassauer, Andreas; Prieschl-Grassauer, Eva; Schubert, Ulrich (International Journal of General Medicine, 2021)
Purpose: The aim of this study was to investigate whether sucking of an iota-carrageenan containing lozenge releases sufficient iota-carrageenan into the saliva of healthy subjects to neutralize representatives of the most common respiratory virus families causing common cold and SARS-CoV-2. Patients and Methods: In this monocentric, open label, prospective clinical trial, 31 healthy subjects were included to suck a commercially available iota-carrageenan containing lozenge. Saliva samples from 27 subjects were used for ex vivo efficacy analysis. The study’s primary objective was to assess if the mean iota-carrageenan concentration of the saliva samples exceeded 5 µg/mL, which is the concentration known to reduce replication of human rhinovirus (hRV) 1a and 8 by 90%. The iota-carrageenan concentration of the saliva samples was analyzed by UV-Vis spectroscopy. The antiviral effectiveness of the individual saliva samples was determined in vitro against a panel of respiratory viruses including hRV1a, hRV8, human coronavirus OC43, influenza virus A H1N1pdm09, coxsackievirus A10, parainfluenza virus 3 and SARS-CoV-2 using standard virological assays. Results: The mean iota-carrageenan concentration detected in the saliva exceeds the concentration needed to inhibit 90% of hRV1a and hRV8 replication by 134-fold (95% CI 116.3–160.8-fold; p < 0.001). Thus, the study met the primary endpoint. Furthermore, the iota-carrageenan saliva concentration was 60 to 30,351-fold higher than needed to reduce viral replication/binding of all tested viruses by at least 90% (p < 0.001). The effect was most pronounced in hCoV OC43; in case of SARS-CoV-2, the IC90 was exceeded by 121-fold (p < 0.001). Conclusion: Sucking an iota-carrageenan containing lozenge releases sufficient iota-carra-geenan to neutralize and inactivate the most abundant respiratory viruses as well as pandemic SARS-CoV-2. The lozenges are therefore an appropriate measure to reduce the viral load at the site of infection, hereby presumably limiting transmission within a population as well as translocation to the lower respiratory tract. Trial Registration: NCT04533906.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Antiviral; Clinical study; Corona virus; Iota-carrageenan; Lozenges; Respiratory viruses; SARS-CoV-2

The SAMHD1-mediated block of LINE-1 retroelements is regulated by phosphorylation - Herrmann, Alexandra; Wittmann, Sabine; Thomas, Dominique; Shepard, Caitlin N.; Kim, Baek; Ferreiros, Nerea; Gramberg, Thomas (Mobile DNA, 2018)
Background: The restriction factor SAMHD1 regulates intracellular nucleotide level by degrading dNTPs and blocks the replication of retroviruses and DNA viruses in non-cycling cells, like macrophages or dendritic cells. In patients, inactivating mutations in samhd1 are associated with the autoimmune disease Aicardi-Goutieres Syndrome (AGS). The accumulation of intracellular nucleic acids derived from endogenous retroelements thriving in the absence of SAMHD1 has been discussed as potential trigger of the autoimmune reaction. In vitro, SAMHD1 has been found to restrict endogenous retroelements, like LINE-1 elements (L1). The mechanism, however, by which SAMHD1 blocks endogenous retroelements, is still unclear. Results: Here, we show that SAMHD1 inhibits the replication of L1 and other endogenous retroelements in cycling cells. By applying GFP- and neomycin-based reporter assays we found that the anti-L1 activity of SAMHD1 is regulated by phosphorylation at threonine 592 (T592). Similar to the block of HIV, the cofactor binding site and the enzymatic active HD domain of SAMHD1 proofed to be essential for restriction of L1 elements. However, phosphorylation at T592 did not correlate with the dNTP hydrolase activity of SAMHD1 in cycling 293T cells suggesting an alternative mechanism of regulation. Interestingly, we found that SAMHD1 binds to ORF2 protein of L1 and that this interaction is regulated by T592 phosphorylation. Together with the finding that the block is also active in cycling cells, our results suggest that the SAMHD1-mediated inhibition of L1 is similar but not identical to HIV restriction. Conclusion: Our findings show conclusively that SAMHD1 restricts the replication of endogenous retroelements in vitro. The results suggest that SAMHD1 is important for maintaining genome integrity and support the idea of an enhanced replication of endogenous retroelements in the absence of SAMHD1 in vivo, potentially triggering autoimmune diseases like AGS. Our analysis also contributes to the better understanding of the activities of SAMHD1 in antiviral defense and nucleotide metabolism. The finding that the phosphorylation of SAMHD1 at T592 regulates its activity against retroelements but not necessarily intracellular dNTP level suggests that the dNTP hydrolase activity might not be the only function of SAMHD1 important for its antiviral activity and for controlling autoimmunity.
EVALuna2:35283

The Tax-Inducible Actin-Bundling Protein Fascin Is Crucial for Release and Cell-to-Cell Transmission of Human T-Cell Leukemia Virus Type 1 (HTLV-1) - Groß, Christine; Wiesmann, Veit; Millen, Sebastian; Kalmer, Martina; Wittenberg, Thomas; Gettemans, Jan; Thoma-Kreß, Andrea (PLoS Pathogens, 2016)
The delta-retrovirus Human T-cell leukemia virus type 1 (HTLV-1) preferentially infects CD4+ T-cells via cell-to-cell transmission. Viruses are transmitted by polarized budding and by transfer of viral biofilms at the virological synapse (VS). Formation of the VS requires the viral Tax protein and polarization of the host cytoskeleton, however, molecular mechanisms of HTLV-1 cell-to-cell transmission remain incompletely understood. Recently, we could show Tax-dependent upregulation of the actin-bundling protein Fascin (FSCN-1) in HTLV-1-infected T-cells. Here, we report that Fascin contributes to HTLV-1 transmission. Using single-cycle replication-dependent HTLV-1 reporter vectors, we found that repression of endogenous Fascin by short hairpin RNAs and by Fascin-specific nanobodies impaired gag p19 release and cell-to-cell transmission in 293T cells. In Jurkat T-cells, Tax-induced Fascin expression enhanced virus release and Fascin-dependently augmented cell-to-cell transmission to Raji/CD4+ B-cells. Repression of Fascin in HTLV-1-infected T-cells diminished virus release and gag p19 transfer to co-cultured T-cells. Spotting the mechanism, flow cytometry and automatic image analysis showed that Tax-induced T-cell conjugate formation occurred Fascin-independently. However, adhesion of HTLV-1-infected MT-2 cells in co-culture with Jurkat T-cells was reduced upon knockdown of Fascin, suggesting that Fascin contributes to dissemination of infected T-cells. Imaging of chronically infected MS-9 T-cells in co-culture with Jurkat T-cells revealed that Fascin's localization at tight cell-cell contacts is accompanied by gag polarization suggesting that Fascin directly affects the distribution of gag to budding sites, and therefore, indirectly viral transmission. In detail, we found gag clusters that are interspersed with Fascin clusters, suggesting that Fascin makes room for gag in viral biofilms. Moreover, we observed short, Fascin-containing membrane extensions surrounding gag clusters and clutching uninfected T-cells. Finally, we detected Fascin and gag in long-distance cellular protrusions. Taken together, we show for the first time that HTLV-1 usurps the host cell factor Fascin to foster virus release and cell-to-cell transmission.
EVALuna2:8339

The transcription elongation factor ELL2 is specifically upregulated in HTLV-1-infected T-cells and is dependent on the viral oncoprotein Tax - Mann, Melanie; Strobel, Sarah; Fleckenstein, Bernhard; Kreß, Andrea (Virology, 2014)
The oncoprotein Tax of human T-cell leukemia virus type 1 (HTLV-1) is a potent transactivator of viral and cellular transcription. Here, we identified ELL2 as the sole transcription elongation factor to be specifically upregulated in HTLV-1-/Tax-transformed T-cells. Tax contributes to regulation of ELL2, since transient transfection of Tax increases ELL2 mRNA, Tax transactivates the ELL2 promoter, and repression of Tax results in decrease of ELL2 in transformed T-lymphocytes. However, we also measured upregulation of ELL2 in HTLV-1-transformed cells exhibiting undetectable amounts of Tax, suggesting that ELL2 can still be maintained independent of continuous Tax expression. We further show that Tax and ELL2 synergistically activate the HTLV-1 promoter, indicating that ELL2 cooperates with Tax in viral transactivation. This is supported by our findings that Tax and ELL2 accumulate in nuclear fractions and that they co-precipitate upon co-expression in transiently-transfected cells. Thus, upregulation of ELL2 could contribute to HTLV-1 gene regulation.
EVALuna2:8235

The Trimeric Artesunate Analog TF27, a Broadly Acting Anti-Infective Model Drug, Exerts Pronounced Anti-SARS-CoV-2 Activity Spanning Variants and Host Cell Types - Hahn, Friedrich; Wangen, Christina; Häge, Sigrun; Herrmann, Lars; Herrmann, Alexandra; Tsogoeva, Svetlana; Marschall, Manfred (Pharmaceutics, 2023)
Starting in 2019, the spread of respiratory syndrome coronavirus 2 (SARS-CoV-2) and the associated pandemic of the corona virus disease (COVID-19) has led to enormous efforts in the development of medical countermeasures. Although innovative vaccines have scaled back the number of severe COVID cases, the emergence of the omicron variant (B.1.1.529) illustrates how vaccine development struggles to keep pace with viral evolution. On the other hand, while the recently approved antiviral drugs remdesivir, molnupiravir, and Paxlovid are considered as broadly acting anti-coronavirus therapeutics, only molnupiravir and Paxlovid are orally available and none of these drugs are recommended for prophylactic use. Thus, so far unexploited small molecules, targeting strategies, and antiviral mechanisms are urgently needed to address issues in the current pandemic and in putative future outbreaks of newly emerging variants of concern. Recently, we and others have described the anti-infective potential and particularly the pronounced antiviral activity of artesunate and related compounds of the trioxane/sesquiterpene class. In particular, the trimeric derivative TF27 demonstrated strong anti-cytomegalovirus activity at nanomolar concentrations in vitro as well as in vivo efficacy after oral administration in therapeutic and even prophylactic treatment settings. Here, we extended this analysis by evaluating TF27 for its anti-SARS-CoV-2 potential. Our main findings are as follows: (i) compound TF27 exerted strong anti-SARS-CoV-2 activity in vitro (EC50 = 0.46 ± 0.20 µM), (ii) antiviral activity was clearly distinct from the induction of cytotoxicity, (iii) pretreatment with TF27 prevented virus replication in cultured cells, (iv) antiviral activity has likewise been demonstrated in Calu-3 human lung and Caco-2 human colon cells infected with wild-type, delta, or omicron SARS-CoV-2, respectively, and (v) analysis of TF27 combination treatments has revealed synergistic interaction with GC376, but antagonistic interaction with EIDD-1931. Combined, the data demonstrated the pronounced anti-SARS-CoV-2 activity of TF27 and thus highlight the potential of trioxane compounds for further pharmacologic development towards improved options for COVID-specific medication.
CRIS-Team Scopus Importer:2023-02-03
Keywords: artesunate and analogs; broad-spectrum inhibitory properties; host-directed drug targeting; pronounced anti-SARS-CoV-2 activity; SARS-CoV-2 infection; trimeric analog TF27

The trimeric artesunate derivative TF27 exerts strong anti-cytomegaloviral efficacy: Focus on prophylactic efficacy and oral treatment of immunocompetent mice - Wild, Markus; Bertzbach, Luca D.; Tannig, Pierre; Wangen, Christina; Müller, Regina; Herrmann, Lars; Fröhlich, Tony; Tsogoeva, Svetlana; Kaufer, Benedikt B.; Marschall, Manfred; Hahn, Friedrich (Antiviral Research, 2020)
Human cytomegalovirus (HCMV) causes serious and even life-threatening diseases, particularly upon congenital or post-transplant infection. Treatment of HCMV infections with currently available drugs targeting viral enzymes is often limited by severe side effects and the emergence of drug-resistant viruses. To avoid this problem, novel therapeutic options directed to host proteins involved in virus replication are being investigated. Recently, we described the pronounced antiherpesviral activity of the trimeric artesunate derivative TF27 at low nanomolar concentrations in vitro and in vivo. In the present study, we report first data on the prophylactic efficacy of TF27 against human and murine CMV and the oncogenic avian alphaherpesvirus Marek's disease virus (MDV). The main findings of this study are (i) a pronounced activity of the experimental drug TF27 against alpha- and betaherpesviruses in vitro upon prophylactic treatment and (ii) a therapeutic and prophylactic efficacy upon oral treatment in an immunocompetent mouse model. Moreover, our data highlight (iii) the tolerability of orally administered TF27 free of compound-associated adverse events and further confirm (iv) the suitability of cellular factors as primary antiviral targets. Thus, we provide evidence for therapeutic and prophylactic antiherpesviral efficacy of TF27 upon oral treatment in immunocompetent hosts and thereby underline its potential for future antiviral drug development.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Artesunate derivative; Cytomegalovirus; Herpesviral infection model; Host-directed antiviral; Oral administration; Prophylactic efficacy

The tumor marker Fascin is induced by the Epstein-Barr virus-encoded oncoprotein LMP1 via NF-?B in lymphocytes and contributes to their invasive migration - Mohr, Caroline; Kalmer, Martina; Groß, Christine; Mann, Melanie; Sterz, Kai R.; Kieser, Arnd; Fleckenstein, Bernhard; Kreß, Andrea (Cell Communication and Signaling, 2014)
The actin-bundling protein Fascin (FSCN1) is a tumor marker that is highly expressed in numerous types of cancer including lymphomas and is important for migration and metastasis of tumor cells. Fascin has also been detected in B lymphocytes that are freshly-infected with Epstein-Barr virus (EBV), however, both the inducers and the mechanisms of Fascin upregulation are still unclear.Here we show that the EBV-encoded oncoprotein latent membrane protein 1 (LMP1), a potent regulator of cellular signaling and transformation, is sufficient to induce both Fascin mRNA and protein in lymphocytes. Fascin expression is mainly regulated by LMP1 via the C-terminal activation region 2 (CTAR2). Block of canonical NF-?B signaling using a chemical inhibitor of I?B kinase ? (IKK?) or cotransfection of a dominant-negative inhibitor of I?B? (NFKBIA) reduced not only expression of p100, a classical target of the canonical NF-?B-pathway, but also LMP1-induced Fascin expression. Furthermore, chemical inhibition of IKK? reduced both Fascin mRNA and protein levels in EBV-transformed lymphoblastoid cell lines, indicating that canonical NF-?B signaling is required for LMP1-mediated regulation of Fascin both in transfected and transformed lymphocytes. Beyond that, chemical inhibition of IKK? significantly reduced invasive migration of EBV-transformed lymphoblastoid cells through extracellular matrix. Transient transfection experiments revealed that Fascin contributed to LMP1-mediated enhancement of invasive migration through extracellular matrix. While LMP1 enhanced the number of invaded cells, functional knockdown of Fascin by two different small hairpin RNAs resulted in significant reduction of invaded, non-attached cells.Thus, our data show that LMP1-mediated upregulation of Fascin depends on NF-?B and both NF-?B and Fascin contribute to invasive migration of LMP1-expressing lymphocyte
EVALuna2:8232

The tumor marker Fascin is strongly induced by the Tax oncoprotein of HTLV-1 through NF-κB signals - Kreß, Andrea; Kalmer, Martina; Rowan, Aileen G.; Grassmann, Ralph; Fleckenstein, Bernhard (Blood, 2011)
Oncogenic transformation of CD4+ T cells by human T-cell lymphotropic virus type 1 (HTLV-1) is understood as the initial step to adult T-cell leukemia/lymphoma, a process that is mainly initiated by perturbation of cellular signaling by the viral Tax oncoprotein, a potent transcriptional regulator. In search of novel biomarkers with relevance to oncogenesis, we identified the tumor marker and actin-bundling protein Fascin (FSCN1) to be specifically and strongly up-regulated in both HTLV-1 - transformed and adult T-cell leukemia/lymphoma patient-derived CD4+ T cells. Fascin is important for migration and metastasis in various types of cancer. Here we report that a direct link can exist between a single viral oncoprotein and Fascin expression, as the viral oncoprotein Tax was sufficient to induce high levels of Fascin. Nuclear factor-κB signals were important for Tax-mediated transcriptional regulation of Fascin in T cells. This suggests that Fascin up-regulation by Tax contributes to the development of HTLV-1 - associated pathogenesis. © 2011 by The American Society of Hematology.
Created from Fastlane, Scopus look-up

The viral interferon-regulatory factor-3 is required for the survival of KSHV-infected primary effusion lymphoma cells. - Wies, Effi; Mori, Yasuko; Hahn, Alexander; Kremmer, Elisabeth; Stürzl, Michael; Fleckenstein, Bernhard; Neipel, Frank (Blood, 2008)
Human herpesvirus-8 (HHV-8), also known as Kaposi sarcoma-associated herpesvirus (KSHV), is etiologically linked to primary effusion lymphoma (PEL). At least 10 KSHV-encoded proteins with potential roles in KSHV-associated neoplasia have been identified. However, with few exceptions, these putative oncogenes were analyzed in heterologous systems only using overexpression of single genes. Thus, the pathogenetic relevance of most of these putative oncogenes remains essentially unclear. We used RNA interference (RNAi) to knock down the expression of several KSHV genes in cultured PEL cells carrying the KSHV genome. The viral interferon-regulatory factor-3 (vIRF-3) was found to be required for proliferation and survival of cultured PEL cells. Knock-down of vIRF-3 expression by various RNAi approaches unequivocally resulted in reduced proliferation and increased activity of caspase-3 and/or caspase-7. Thus, vIRF-3 can be seen as a bona fide oncogene of KSHV-associated lymphoma. Surprisingly, although the related Epstein-Barr virus (EBV) is usually sufficient to immortalize human B lymphocytes, silencing of vIRF-3 reduced the viability of both EBV(-) and EBV(+) PEL cells. This suggests that KSHV is the driving force in the pathogenesis of PEL.

Thirty Mouse Strain Survey of Voluntary Physical Activity and Energy Expenditure: Influence of Strain, Sex and Day–Night Variation - König, Christine; Plank, Anne-Christine; Kapp, Alexander; Timotius, Ivanna; von Hörsten, Stephan; Zimmermann, Katharina (Frontiers in Neuroscience, 2020)
We measured indirect calorimetry and activity parameters, VO2 and VCO2 to extract respiratory exchange ratio (RER) and energy expenditure in both sexes of 30 inbred mouse strains of 6 genetic families at 9–13 weeks during one photophase and the subsequent scotophase. We observed a continuous distribution of all traits. While males had higher body weights than females, we observed no sex difference for food and water intake. All strains drank and fed more during the night even if they displayed no day–night difference in activity traits. Several strains showed absent or weak day–night variation in one or more activity traits and these included FVB and 129X1, males of 129S1, SWR, NZW, and SM, and females of SJL. In general females showed higher rearing and ambulatory activity with 6 and 9 strains, respectively, showing a sex difference. Fine motor movements, like grooming, showed less sex differences. RER underlied a strong day–night difference and no sex effect. Only FVB females and males of the RIIIS and SM strain had no day–night variation. Energy expenditure underlies a large day–night variation which was absent in SWR and in FVB females and RIIIS males. In general, female bodies had a tendency to higher energy expenditure values, which became a significant difference in C3H, MAMy, SM, DBA1, and BUB. Our data illustrate the diversity of these traits in male and female inbred mice and provide a resource in the selection of strains for future studies.
CRIS-Team Scopus Importer:2020-07-31
Keywords: inbred mouse strains; indirect calorimetry assessment; phenotype screening; respiratory exchange ratio (RER); sexual dimorphism

Three exposures to the spike protein of SARS-CoV-2 by either infection or vaccination elicit superior neutralizing immunity to all variants of concern - Wratil, Paul R.; Stern, Marcel; Priller, Alina; Willmann, Annika; Almanzar, Giovanni; Vogel, Emanuel; Feuerherd, Martin; Cheng, Cho Chin; Yazici, Sarah; Christa, Catharina; Jeske, Samuel; Lupoli, Gaia; et al. (Nature Medicine, 2022)
Infection-neutralizing antibody responses after SARS-CoV-2 infection or COVID-19 vaccination are an essential component of antiviral immunity. Antibody-mediated protection is challenged by the emergence of SARS-CoV-2 variants of concern (VoCs) with immune escape properties, such as omicron (B.1.1.529) that is rapidly spreading worldwide. Here, we report neutralizing antibody dynamics in a longitudinal cohort of COVID-19 convalescent and infection-naive individuals vaccinated with mRNA BNT162b2 by quantifying anti-SARS-CoV-2-spike antibodies and determining their avidity and neutralization capacity in serum. Using live-virus neutralization assays, we show that a superior infection-neutralizing capacity against all VoCs, including omicron, developed after either two vaccinations in convalescents or after a third vaccination or breakthrough infection of twice-vaccinated, naive individuals. These three consecutive spike antigen exposures resulted in an increasing neutralization capacity per anti-spike antibody unit and were paralleled by stepwise increases in antibody avidity. We conclude that an infection-plus-vaccination-induced hybrid immunity or a triple immunization can induce high-quality antibodies with superior neutralization capacity against VoCs, including omicron.
CRIS-Team Scopus Importer:2022-02-11

Time Trend in SARS-CoV-2 Seropositivity, Surveillance Detection- and Infection Fatality Ratio until Spring 2021 in the Tirschenreuth County—Results from a Population-Based Longitudinal Study in Germany - Einhauser, Sebastian; Peterhoff, David; Beileke, Stephanie; Günther, Felix; Niller, Hans Helmut; Steininger, Philipp; Knöll, Antje; Korn, Klaus; Berr, Melanie; Schütz, Anja; Wiegrebe, Simon; Stark, Klaus J.; et al. (Viruses, 2022)
Herein, we provide results from a prospective population-based longitudinal follow-up (FU) SARS-CoV-2 serosurveillance study in Tirschenreuth, the county which was hit hardest in Germany in spring 2020 and early 2021. Of 4203 individuals aged 14 years or older enrolled at baseline (BL, June 2020), 3546 participated at FU1 (November 2020) and 3391 at FU2 (April 2021). Key metrics comprising standardized seroprevalence, surveillance detection ratio (SDR), infection fatality ratio (IFR) and success of the vaccination campaign were derived using the Roche N-and S-Elecsys anti-SARS-CoV-2 test together with a self-administered questionnaire. N-seropositivity at BL was 9.2% (1st wave). While we observed a low new seropositivity between BL and FU1 (0.9%), the combined 2nd and 3rd wave accounted for 6.1% new N-seropositives between FU1 and FU2 (ever seropositives at FU2: 15.4%). The SDR decreased from 5.4 (BL) to 1.1 (FU2) highlighting the success of massively increased testing in the population. The IFR based on a combination of serology and registration data resulted in 3.3% between November 2020 and April 2021 compared to 2.3% until June 2020. Although IFRs were consistently higher at FU2 compared to BL across age-groups, highest among individuals aged 70+ (18.3% versus 10.7%, respectively), observed differences were within statistical uncertainty bounds. While municipalities with senior care homes showed a higher IFR at BL (3.0% with senior care home vs. 0.7% w/o), this effect diminished at FU2 (3.4% vs. 2.9%). In April 2021 (FU2), vaccination rate in the elderly was high (>77.4%, age-group 80+).
CRIS-Team Scopus Importer:2022-06-17
Keywords: case fatality ratio; elderly; infection fatality ratio; longitudinal; population-based; SARS-CoV-2; senior care homes; seroprevalence; surveillance detection ratio; vaccination

Tissue sodium concentration emerged as a determinant of hypertrophic vascular remodeling in type 2 diabetes - Schmieder, Roland; Jung, Susanne; Kannenkeril, D.; Harazny, J. M.; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Angela; Uder, Michael (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Transcriptional Targeting of Dendritic Cells Using an Optimized Human Fascin1 Gene Promoter - Zeyn, Yanira; Hobernik, Dominika; Wilk, Ulrich; Pöhmerer, Jana; Hieber, Christoph; Medina-Montano, Carolina; Röhrig, Nadine; Strähle, Caroline F.; Thoma-Kreß, Andrea; Wagner, Ernst; Bros, Matthias; Berger, Simone (International Journal of Molecular Sciences, 2023)
Deeper knowledge about the role of the tumor microenvironment (TME) in cancer development and progression has resulted in new strategies such as gene-based cancer immunotherapy. Whereas some approaches focus on the expression of tumoricidal genes within the TME, DNA-based vaccines are intended to be expressed in antigen-presenting cells (e.g., dendritic cells, DCs) in secondary lymphoid organs, which in turn induce anti-tumor T cell responses. Besides effective delivery systems and the requirement of appropriate adjuvants, DNA vaccines themselves need to be optimized regarding efficacy and selectivity. In this work, the concept of DC-focused transcriptional targeting was tested by applying a plasmid encoding for the luciferase reporter gene under the control of a derivative of the human fascin1 gene promoter (pFscnLuc), comprising the proximal core promoter fused to the normally more distantly located DC enhancer region. DC-focused activity of this reporter construct was confirmed in cell culture in comparison to a standard reporter vector encoding for luciferase under the control of the strong ubiquitously active cytomegalovirus promoter and enhancer (pCMVLuc). Both plasmids were also compared upon intravenous administration in mice. The organ- and cell type-specific expression profile of pFscnLuc versus pCMVLuc demonstrated favorable activity especially in the spleen as a central immune organ and within the spleen in DCs.
CRIS-Team Scopus Importer:2023-12-22
Keywords: cytomegalovirus; dendritic cell; fascin1; gene delivery; plasmid DNA; polyethylenimine; polyplex; promotor activity; tumor cell

Transfer of htlv-1 p8 and gag to target t-cells depends on vasp, a novel interaction partner of p8 - Donhauser, Norbert; Socher, Eileen; Millen, Sebastian; Heym, Stefanie; Sticht, Heinrich; Thoma-Kreß, Andrea (PLoS Pathogens, 2020)
The Human T-cell leukemia virus type 1 (HTLV-1) orf I-encoded accessory protein p8 is cleaved from its precursor p12, and both proteins contribute to viral persistence. p8 induces cellular protrusions, which are thought to facilitate transfer of p8 to target cells and virus transmission. Host factors interacting with p8 and mediating p8 transfer are unknown. Here, we report that vasodilator-stimulated phosphoprotein (VASP), which promotes actin filament elongation, is a novel interaction partner of p8 and important for p8 and HTLV-1 Gag cell-to-cell transfer. VASP contains an Ena/VASP homology 1 (EVH1) domain that targets the protein to focal adhesions. Bioinformatics identified a short stretch in p8 (amino acids (aa) 24-45) which may mediate interactions with the EVH1 domain of VASP. Co-immunoprecipitations confirmed interactions of VASP:p8 in 293T, Jurkat and HTLV-1-infected MT-2 cells. Co-precipitation of VASP:p8 could be significantly blocked by peptides mimicking aa 26-37 of p8. Mutational studies revealed that the EVH1-domain of VASP is necessary, but not sufficient for the interaction with p8. Further, deletion of the VASP G- and F-actin binding domains significantly diminished co-precipitation of p8. Imaging identified areas of partial co-localization of VASP with p8 at the plasma membrane and in protrusive structures, which was confirmed by proximity ligation assays. Co-culture experiments revealed that p8 is transferred between Jurkat T-cells via VASP-containing conduits. Imaging and flow cytometry revealed that repression of both endogenous and overexpressed VASP by RNA interference or by CRISPR/Cas9 reduced p8 transfer to the cell surface and to target Jurkat T-cells. Stable repression of VASP by RNA interference in chronically infected MT-2 cells impaired both p8 and HTLV-1 Gag transfer to target Jurkat T-cells, while virus release was unaffected. Thus, we identified VASP as a novel interaction partner of p8, which is important for transfer of HTLV-1 p8 and Gag to target T-cells.
CRIS-Team Scopus Importer:2020-10-16

Transgenic Rat Models of Huntington's Disease - Carreira, João Casaca; Jahanshahi, Ali; Zeef, Dagmar; Kocabicak, Ersoy; Vlamings, Rinske; von Hörsten, Stephan; Temel, Yasin (Current Topics in Behavioral Neurosciences, 2015)
Several animal models for Huntington's disease (HD) have been created in order to investigate mechanisms of disease, and to evaluate the potency of novel therapies. Here, we describe the characteristics of the two transgenic rat models: transgenic rat model of HD (fragment model) and the Bacterial Artificial Chromosome HD model (full-length model). We discuss their genetic, behavioural, neuropathological and neurophysiological features.
EVALuna2:24980

Transglutaminase 6 is colocalized and interacts with mutant huntingtin in huntington disease rodent animal models - Schulze-Krebs, Anja; Canneva, Fabio; Stemick, Judith; Plank, Anne-Christine; Harrer, Julia; Bates, Gillian P.; Aeschlimann, Daniel; Steffan, Joan S.; von Hörsten, Stephan (International Journal of Molecular Sciences, 2021)
Mammalian transglutaminases (TGs) catalyze calcium-dependent irreversible posttranslational modifications of proteins and their enzymatic activities contribute to the pathogenesis of several human neurodegenerative diseases. Although different transglutaminases are found in many different tissues, the TG6 isoform is mostly expressed in the CNS. The present study was embarked on/undertaken to investigate expression, distribution and activity of transglutaminases in Huntington disease transgenic rodent models, with a focus on analyzing the involvement of TG6 in the age-and genotype-specific pathological features relating to disease progression in HD transgenic mice and a tgHD transgenic rat model using biochemical, histological and functional assays. Our results demonstrate the physical interaction between TG6 and (mutant) huntingtin by co-immunoprecipitation analysis and the contribution of its enzymatic activity for the total aggregate load in SH-SY5Y cells. In addition, we identify that TG6 expression and activity are especially abundant in the olfactory tubercle and piriform cortex, the regions displaying the highest amount of mHTT aggregates in transgenic rodent models of HD. Furthermore, mHTT aggregates were colocalized within TG6-positive cells. These findings point towards a role of TG6 in disease pathogenesis via mHTT aggregate formation.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Huntington disease; Neurodegeneration; Rodent transgenic animal models; Transglutaminase isoform 6

Transmembrane Protein pUL50 of Human Cytomegalovirus Inhibits ISGylation by Downregulating UBE1L - Lee, Myoung Kyu; Kim, Ye Ji; Kim, Young-Eui; Han, Tae-Hee; Milbradt, Jens; Marschall, Manfred; Ahn, Jin-Hyun (Journal of Virology, 2018)
Interferon-stimulated gene 15 (ISG15) encodes a ubiquitin-like protein that can be conjugated to proteins via an enzymatic cascade involving the E1, E2, and E3 enzymes. ISG15 expression and protein ISGylation modulate viral infection; however, the viral mechanisms regulating the function of ISG15 and ISGylation are not well understood. We recently showed that ISGylation suppresses the growth of human cytomegalovirus (HCMV) at multiple steps of the virus life cycle and that the virus-encoded pUL26 protein inhibits protein ISGylation. In this study, we demonstrate that the HCMV UL50-encoded transmembrane protein, a component of the nuclear egress complex, also inhibits ISGylation. pULSO interacted with UBE1L, an E1activating enzyme for ISGylation, and (to a lesser extent) with ISG15, as did pUL26. However, unlike pUL26, pUL50 caused proteasomal degradation of UBE1L. The UBE1L level induced in human fibroblast cells by interferon beta treatment or virus infection was reduced by pULSO expression. This activity of pULSO involved the transmembrane (TM) domain within its C-terminal region, although pUL50 could interact with UBE1L in a manner independent of the TM domain. Consistently, colocalization of pUL50 with UBE1L was observed in cells treated with a proteasome inhibitor. Furthermore, we found that RNF170, an endoplasmic reticulum (ER)-associated ubiquitin E3 ligase, interacted with pUL50 and promoted pUL50-mediated UBE1L degradation via ubiquitination. Our results demonstrate a novel role for the pULSO transmembrane protein of HCMV in the regulation of protein ISGylation. IMPORTANCE Proteins can be conjugated covalently by ubiquitin or ubiquitin-like proteins, such as SUMO and ISG15. ISG15 is highly induced in viral infection, and ISG15 conjugation, termed ISGylation, plays important regulatory roles in viral growth. Although ISGylation has been shown to negatively affect many viruses, including human cytomegalovirus (HCMV), viral countermeasures that might modulate ISGylation are not well understood. In the present study, we show that the transmembrane protein encoded by HCMV UL50 inhibits ISGylation by causing proteasomal degradation of UBE1L, an E1activating enzyme for ISGylation. This pUL50 activity requires membrane targeting. In support of this finding, RNF170, an ER-associated ubiquitin E3 ligase, interacts with pULSO and promotes ULSO-mediated UBE1L ubiquitination and degradation. Our results provide the first evidence, to our knowledge, that viruses can regulate ISGylation by directly targeting the ISGylation E1 enzyme.
EVALuna2:35268

Transmembrane serine protease 2 (TMPRSS2) is involved in proteolytic activation of the epithelial sodium channel (ENaC) in mouse cortical collecting duct (mCCDcl1) cells - Sure, Florian; Afonso, Sara; Bertog, Marko; Rinke, Ralf; Wittmann, Sabine; Gramberg, Thomas; Ilyaskin, Alexandr; Korbmacher, Christoph (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Transmembrane serine protease 2 (TMPRSS2) proteolytically activates the epithelial sodium channel (ENaC) by cleaving the channel's gamma-subunit - Sure, Florian; Bertog, Marko; Afonso, Sara; Diakov, A.; Rinke, Ralf; Madej, M. G.; Wittmann, Sabine; Gramberg, Thomas; Korbmacher, Christoph; Ilyaskin, Alexandr (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Transmembrane serine protease 2 (TMPRSS2) proteolytically activates the epithelial sodium channel (ENaC) by cleaving the channel's gamma-subunit - Sure, Florian; Bertog, Marko; Afonso, Sara; Diakov, Alexei; Rinke, Ralf; Madej, M. Gregor; Wittmann, Sabine; Gramberg, Thomas; Korbmacher, Christoph; Ilyaskin, Alexandr (Journal of Biological Chemistry, 2022)
The epithelial sodium channel (ENaC) is a heterotrimer consisting of alpha-, beta-, and gamma-subunits. Channel activation requires proteolytic release of inhibitory tracts from the extracellular domains of alpha-ENaC and gamma-ENaC; however, the proteases involved in the removal of the gamma-inhibitory tract remain unclear. In several epithelial tissues, ENaC is coexpressed with the transmembrane serine protease 2 (TMPRSS2). Here, we explored the effect of human TMPRSS2 on human alpha beta gamma-ENaC heterologously expressed in Xenopus laevis oocytes. We found that coexpression of TMPRSS2 stimulated ENaC-mediated whole-cell currents by approximately threefold, likely because of an increase in average channel open probability. Furthermore, TMPRSS2-dependent ENaC stimulation was not observed using a catalytically inactive TMPRSS2 mutant and was associated with fully cleaved gamma-ENaC in the intracellular and cell surface protein fractions. This stimulatory effect of TMPRSS2 on ENaC was partially preserved when inhibiting its proteolytic activity at the cell surface using aprotinin but was abolished when the gamma-inhibitory tract remained attached to its binding site following introduction of two cysteine residues (S155C-Q426C) to form a disulfide bridge. In addition, computer simulations and site-directed mutagenesis experiments indicated that TMPRSS2 can cleave gamma-ENaC at sites both proximal and distal to the gamma-inhibitory tract. This suggests a dual role of TMPRSS2 in the proteolytic release of the gamma-inhibitory tract. Finally, we demonstrated that TMPRSS2 knockdown in cultured human airway epithelial cells (H441) reduced baseline proteolytic activation of endogenously expressed ENaC. Thus, we conclude that TMPRSS2 is likely to contribute to proteolytic ENaC activation in epithelial tissues in vivo.
CRIS-Team WoS Importer:2022-06-24

Treadmill exercise intervention improves gait and postural control in alpha-synuclein mouse models without inducing cerebral autophagy - Minakaki, Georgia; Canneva, Fabio; Chevessier, Frederic; Bode, Frederik; Menges, Stefanie; Timotius, Ivanna; Kalinichenko, Liubov; Meixner, Holger; Müller, Christian P.; Eskofier, Björn; Casadei, Nicolas; Riess, Olaf; et al. (Behavioural Brain Research, 2019)
Gait and postural control dysfunction are prototypical symptoms compromising quality of life for patients with Parkinson’s disease (PD). Hallmarks of cellular pathology are dopaminergic degeneration and accumulation of the cytosolic protein alpha-synuclein, linked to impaired autophagy-lysosome pathway (ALP) clearance. Physical exercise improves gait in PD patients and motor function in rodent lesion models. Moreover, exercise is considered neuroprotective and ALP induction has been reported, e.g. in human skeletal muscle, rodent peripheral and cerebral tissues. A combined analysis of how distinct exercise paradigms affect motor and central biochemical aspects of PD could maximize benefits for patients. Here we examine the effect of 4 weeks treadmill exercise intervention in 7-8 month non-lesioned mice on a) distinct gait categories, b) ALP activity, c) dopaminergic and alpha-synuclein homeostasis. The study includes wild type, alpha-synuclein knockout, and mice exclusively expressing human alpha-synuclein. Parameters of gait regularity and stability, activity, and dynamic postural control during unforced walk, were assessed by an automated system (CatWalk XT). At baseline, alpha-synuclein mouse models exhibited irregular and less active gait, with impaired dynamic postural control, compared to wild type mice. Treadmill exercise particularly improved speed and stride length, while increasing dual diagonal versus three-paw body support in both the alpha-synuclein knockout and transgenic mice. Biochemical analyses showed higher striatal tyrosine hydroxylase immuno-reactivity and reduced higher-order alpha-synuclein species in the cerebral cortex. However, no significant cerebral ALP induction was measured. In summary, treadmill exercise improved gait activity and postural stability, and promoted dopaminergic and alpha-synuclein homeostasis, without robustly inducing cerebral ALP.<br
Keywords: alpha-synuclein; autophagy; instrumented gait analysis; mouse gait pattern; Parkinson´s disease; treadmill exercise

TRICHODYSPLASIA SPINULOSA WITH DISFIGURING FACIAL FEATURES AFTER KIDNEY TRANSPLANTATION IMPROVED BY mTOR-INHIBITION - Dieterle, A.; Korn, Klaus; Büttner, Maike; Schiffer, Mario; Kiesewetter, Franklin; Wiesener, M. S. (TRANSPLANT INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-10-29

TRIM19/PML Restricts HIV Infection in a Cell Type-Dependent Manner - Kahle, Tanja; Volkmann, Bianca; Eißmann, Kristin; Herrmann, Alexandra; Schmitt, Sven; Wittmann, Sabine; Merkel, Laura; Reuter, Nina; Stamminger, Thomas; Gramberg, Thomas (Viruses, 2016)
The promyelocytic leukemia protein (PML) is the main structural component of the nuclear matrix structures termed nuclear domain 10 (ND10) or PML nuclear bodies (PML-NBs). PML and ND10 structures have been shown to mediate an intrinsic immune response against a variety of different viruses. Their role during retroviral replication, however, is still controversially discussed. In this study, we analyzed the role of PML and the ND10 components Daxx and Sp100 during retroviral replication in different cell types. Using cell lines exhibiting a shRNA-mediated knockdown, we found that PML, but not Daxx or Sp100, inhibits HIV and other retroviruses in a cell type-dependent manner. The PML-mediated block to retroviral infection was active in primary human fibroblasts and murine embryonic fibroblasts but absent from T cells and myeloid cell lines. Quantitative PCR analysis of HIV cDNA in infected cells revealed that PML restricts infection at the level of reverse transcription. Our findings shed light on the controversial role of PML during retroviral infection and show that PML contributes to the intrinsic restriction of retroviral infections in a cell type-dependent manner.
EVALuna2:8305

Tspan8 is expressed in breast cancer and regulates E-cadherin/catenin signalling and metastasis accompanied by increased circulating extracellular vesicles - Voglstaetter, Maren; Thomsen, Andreas R.; Nouvel, Jerome; Koch, Arend; Jank, Paul; Navarro, Elena Grueso; Gainey-Schleicher, Tanja; Khanduri, Richa; Groß, Andrea; Rossner, Florian; Blaue, Carina; Franz, Clemens M.; et al. (Journal of Pathology, 2019)
Tspan8 exhibits a functional role in many cancer types including pancreatic, colorectal, oesophagus carcinoma, and melanoma. We present a first study on the expression and function of Tspan8 in breast cancer. Tspan8 protein was present in the majority of human primary breast cancer lesions and metastases in the brain, bone, lung, and liver. In a syngeneic rat breast cancer model, Tspan8+ tumours formed multiple liver and spleen metastases, while Tspan8− tumours exhibited a significantly diminished ability to metastasise, indicating a role of Tspan8 in metastases. Addressing the underlying molecular mechanisms, we discovered that Tspan8 can mediate up-regulation of E-cadherin and down-regulation of Twist, p120-catenin, and β-catenin target genes accompanied by the change of cell phenotype, resembling the mesenchymal–epithelial transition. Furthermore, Tspan8+ cells exhibited enhanced cell–cell adhesion, diminished motility, and decreased sensitivity to irradiation. As a regulator of the content and function of extracellular vesicles (EVs), Tspan8 mediated a several-fold increase in EV number in cell culture and the circulation of tumour-bearing animals. We observed increased protein levels of E-cadherin and p120-catenin in these EVs; furthermore, Tspan8 and p120-catenin were co-immunoprecipitated, indicating that they may interact with each other. Altogether, our findings show the presence of Tspan8 in breast cancer primary lesion and metastases and indicate its role as a regulator of cell behaviour and EV release in breast cancer. © 2019 The Authors. Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.
CRIS-Team Scopus Importer:2019-07-02
Keywords: beta-catenin signalling pathway; breast cancer; extracellular vesicles; mesenchymal–epithelial transition; metastases; tetraspanins; three-dimensional cell culture; Tspan8

Tuberculosis and impaired IL-23-dependent IFN-gamma immunity in humans homozygous for a common TYK2 missense variant - Boisson-Dupuis, Stephanie; Ramirez-Alejo, Noe; Li, Zhi; Patin, Etienne; Rao, Geetha; Kerner, Gaspard; Lim, Che Kang; Krementsov, Dimitry N.; Hernandez, Nicholas; Ma, Cindy S.; Zhang, Qian; Markle, Janet; et al. (Science immunology, 2018)
Inherited IL-12R beta 1 and TYK2 deficiencies impair both IL-12- and IL-23 -dependent IFN-gamma immunity and are rare monogenic causes of tuberculosis, each found in less than 1/600,000 individuals. We show that homozygosity for the common TYK2 P1104A allele, which is found in about 1/600 Europeans and between 1/1000 and 1/10,000 individuals in regions other than East Asia, is more frequent in a cohort of patients with tuberculosis from endemic areas than in ethnicity-adjusted controls (P = 8.37 x 10(-8); odds ratio, 89.31; 95% CI, 14.7 to 1725). Moreover, the frequency of P1104A in Europeans has decreased, from about 9% to 4.2%, over the past 4000 years, consistent with purging of this variant by endemic tuberculosis. Surprisingly, we also show that TYK2 P1104A impairs cellular responses to IL-23, but not to IFN-alpha, IL-10, or even IL-12, which, like IL-23, induces IFN-gamma via activation of TYK2 and JAK2. Moreover, TYK2 P1104A is properly docked on cytokine receptors and can be phosphorylated by the proximal JAK, but lacks catalytic activity. Last, we show that the catalytic activity of TYK2 is essential for IL-23, but not IL-12, responses in cells expressing wild-type JAK2. In contrast, the catalytic activity of JAK2 is redundant for both IL-12 and IL-23 responses, because the catalytically inactive P1057A JAK2, which is also docked and phosphorylated, rescues signaling in cells expressing wild-type TYK2. In conclusion, homozygosity for the catalytically inactive P1104A missense variant of TYK2 selectively disrupts the induction of IFN-gamma by IL-23 and is a common monogenic etiology of tuberculosis.
EVALuna2:35257

Turning the tables on cytomegalovirus: targeting viral Fc receptors by CARs containing mutated CH2-CH3 IgG spacer domains - Proff, Julia; Brey, Charlotte U.; Enßer, Armin; Holter, Wolfgang; Lehner, Manfred (Journal of Translational Medicine, 2018)
Background: During infection with human cytomegalovirus (HCMV) several viral proteins occur on cell surfaces in high quantity. We thus pursue an HLA-independent approach for immunotherapy of HCMV using chimeric antigen receptors (CARs) and bispecific -BiTE (R) antibody constructs. In this context, HCMV-encoded proteins that mediate viral immune evasion and bind human IgG might represent particularly attractive target antigens. Unlike in observations of similar approaches for HIV and hepatitis B and C viruses, however, HCMV-infected cells develop a striking resistance to cytotoxic effector functions at later stages of the replication cycle. In our study we therefore wanted to test two hypotheses: (1) CAR T cells can efficiently inhibit HCMV replication independently from cytotoxic effector functions, and (2) HCMV can be targeted by CH2-CH3 IgG spacer domains that contain mutations previously reported to prevent exhaustion and to rescue CAR T cell function in vivo. Methods: Replication of GFP-encoding recombinant HCMV in fibroblasts in the presence and absence of supernatants from T cell co-cultures plus/minus cytokine neutralizing antibodies was analyzed by flow cytometry. CARs with wild type and mutated CH2-CH3 domains were expressed in human T cells by mRNA electroporation, and the function of the CARs was assessed by quantifying T cell cytokine secretion. Results: We confirm and extend previous evidence of antiviral cytokine effects and demonstrate that CAR T cells strongly block HCMV replication in fibroblasts mainly by combined secretion of IFN-gamma and TNF. Furthermore, we show that fibroblasts infected with HCMV strains AD169 and Towne starting from day 3 have a high capacity for binding of human IgG1 and also strongly activate T cells expressing a CAR with CH2-CH3 domain. Importantly, we further show that mutations in the CH2-CH3 domain of IgG1 and IgG4, which were previously reported to rescue CAR T cell function by abrogating interaction with endogenous Fc receptors (FcRs), still enable recognition of FcRs encoded by HCMV. Conclusions: Our findings identify HCMV-encoded FcRs as an attractive additional target for HCMV immunotherapy by CARs and possibly bispecific antibodies. The use of specifically mutated IgG domains that bind to HCMV-FcRs without recognizing endogenous FcRs may supersede screening for novel binders directed against individual HCMV-FcRs.
EVALuna2:35288

Two Cases of Severe Tick-Borne Encephalitis in Rituximab-Treated Patients in Germany: Implications for Diagnosis and Prevention - Steininger, Philipp; Bobinger, Tobias; Dietrich, Wenke; Lee, De-Hyung; Knott, Michael; Bogdan, Christian; Korn, Klaus; Lang, Roland (Open Forum Infectious Diseases, 2017)
Rituximab (RTX) has become a standard therapy for certain B cell malignancies and autoimmune diseases. We report 2 RTX-treated patients who developed severe tick-borne encephalitis virus (TBEV) infection. The inability to generate new antibody responses renders RTX-treated patients susceptible to TBEV, impedes laboratory diagnosis, and necessitates preventive vaccination in endemic areas.
EVALuna2:22593

Tyrosine phosphorylation directs TACE into extracellular vesicles via unconventional secretion - Zhao, Zhe; Kesti, Tapio; Ugurlu, Hasan; Baur, Andreas; Fagerlund, Riku; Saksela, Kalle (Traffic, 2019)
When studying how HIV-1 Nef can promote packaging of the proinflammatory transmembrane protease TACE (tumor necrosis factor-alpha converting enzyme) into extracellular vesicles (EVs) we have revealed a novel tyrosine kinase-regulated unconventional protein secretion (UPS) pathway for TACE. When TACE was expressed without its trafficking cofactor iRhom allosteric Hck activation by Nef triggered translocation of TACE into EVs. This process was insensitive to blocking of classical secretion by inhibiting endoplasmic reticulum (ER) to Golgi transport, and involved a distinct form of TACE devoid of normal glycosylation and incompletely processed for prodomain removal. Like most other examples of UPS this process was Golgi reassembly stacking protein (GRASP)-dependent but was not associated with ER stress. These data indicate that Hck-activated UPS provides an alternative pathway for TACE secretion that can bypass iRhom-dependent ER to Golgi transfer, and suggest that tyrosine phosphorylation might have a more general role in regulating UPS.
CRIS-Team WoS Importer:2019-03-06

Ubiquitous Micro-Modular Homologies among Genomes from Viruses to Bacteria to Human Mitochondrial DNA: Platforms for Recombination during Evolution? - Weber, Stefanie; Ramirez, Christina M.; Doerfler, Walter (Viruses, 2022)
The emerging Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) and its variants have raised tantalizing questions about evolutionary mechanisms that continue to shape biology today. We have compared the nucleotide sequence of SARS-CoV-2 RNA to that of genomes of many different viruses, of endosymbiotic proteobacterial and bacterial DNAs, and of human mitochondrial DNA. The entire 4,641,652 nt DNA sequence of Escherichia coli K12 has been computer-matched to SARS-CoV-2 RNA. Numerous, very similar micro-modular clusters of 3 to 13 nucleotides lengths were detected with sequence identities of 40 to >50% in specific genome segments between SARS-CoV-2 and the investigated genomes. These clusters were part of patch-type homologies. Control sequence comparisons between 1000 randomly computer-composed sequences of 29.9 kb and with the A, C, G, T base composition of SARS-CoV-2 genome versus the reference Wuhan SARS-CoV-2 sequence showed similar patterns of sequence homologies. The universal A, C, G, T genetic coding mode might have succeeded in evolution due in part to its built-in capacity to select for a substantial reservoir of micro-modular domains and employ them as platforms for integrative recombination. Their role in SARS-CoV-2 interspecies transition and the generation of variants appears likely, but their actual involvement will require detailed investigations.
CRIS-Team Scopus Importer:2022-05-13
Keywords: Four letter genetic encoding system; Micro-modular identities in 1000 randomized SARS-CoV-2 genomes; Micro-modular sequence identities; Patch type sequence similarities; SARS-CoV-2 RNA compared to genomes of many viruses; protobacteria; Escherichia coli; Signals for evolution; annealing and integrative recombination; The 4; 641; 652 nt DNA sequence of Escherichia coli K12

Unique features of different members of the human guanylate-binding protein family - Tripal, Philipp; Bauer, Michael; Naschberger, Elisabeth; Mörtinger, Thomas; Hohenadl, Christine; Cornali, Emmanuelle; Thurau, Mathias; Stürzl, Michael (Journal of Interferon and Cytokine Research, 2007)
Guanylate-binding proteins (GBPs) are the most abundant cellular proteins expressed in response to interferon-γ (IFN-γ), with seven highly homologous members in humans, termed HuGBP-1 to HuGBP-7. To date, differential features that may indicate differential functions of these proteins have not been described. Here, we investigated the expression and subcellular localization of the different HuGBPs in endothelial cells (EC). IFN-γ, tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) induced the expression of HuGBP-1, HuGBP-2, and HuGBP-3 at similar high levels. In contrast, expression of HuGBP-4 and HuGBP-5 was robustly induced only by IFN-γ and not by TNF-α and IL-1β. Expression of HuGBP-6 and HuGBP-7 was not detected in EC under the various conditions examined. Investigating subcellular localization of the EC-expressed HuGBPs, HuGBP-1, HuGBP-3, and HuGBP-5 were exclusively detected in the cytoplasm, whereas HuGBP-2 and HuGBP-4 displayed a nucleocytoplasmic distribution. Treatment of the cells with IFN-γ and aluminum fluoride caused rapid enrichment of HuGBP-1 and HuGBP-2 in the Golgi apparatus, as demonstrated by time-lapse microscopy and fluorescence analyses of GFP-tagged HuGBPs. HuGBP-3 and HuGBP-4 were never detected in the Golgi apparatus, whereas HuGBP-5 was constitutively enriched in this cytosolic compartment, irrespective of stimulation. These results assign a characteristic pattern of expression and subcellular localization to each of the HuGBPs, indicating for the first time that these proteins may have different cellular functions. © Mary Ann Liebert, Inc.
Created from Fastlane, Scopus look-up

Unravelling the immunological roles of dipeptidyl peptidase 4 (DPP4) activity and/or structure homologue (DASH) proteins - Wagner, L.; Klemann, Christian; Stephan, M.; von Hörsten, Stephan (Clinical and Experimental Immunology, 2016)
Dipeptidyl peptidase (DPP) 4 (CD26, DPP4) is a multi-functional protein involved in T cell activation by co-stimulation via its association with adenosine deaminase (ADA), caveolin-1, CARMA-1, CD45, mannose-6-phosphate/insulin growth factor-II receptor (M6P/IGFII-R) and C-X-C motif receptor 4 (CXC-R4). The proline-specific dipeptidyl peptidase also modulates the bioactivity of several chemokines. However, a number of enzymes displaying either DPP4-like activities or representing structural homologues have been discovered in the past two decades and are referred to as DPP4 activity and/or structure homologue (DASH) proteins. Apart from DPP4, DASH proteins include fibroblast activation protein alpha (FAP), DPP8, DPP9, DPP4-like protein 1 (DPL1, DPP6, DPPX L, DPPX S), DPP4-like protein 2 (DPL2, DPP10) from the DPP4-gene family S9b and structurally unrelated enzyme DPP2, displaying DPP4-like activity. In contrast, DPP6 and DPP10 lack enzymatic DPP4-like activity. These DASH proteins play important roles in the immune system involving quiescence (DPP2), proliferation (DPP8/DPP9), antigen-presenting (DPP9), co-stimulation (DPP4), T cell activation (DPP4), signal transduction (DPP4, DPP8 and DPP9), differentiation (DPP4, DPP8) and tissue remodelling (DPP4, FAP). Thus, they are involved in many pathophysiological processes and have therefore been proposed for potential biomarkers or even drug targets in various cancers (DPP4 and FAP) and inflammatory diseases (DPP4, DPP8/DPP9). However, they also pose the challenge of drug selectivity concerning other DASH members for better efficacy and/or avoidance of unwanted side effects. Therefore, this review unravels the complex roles of DASH proteins in immunology.
EVALuna2:24979

Upregulation of CCR4 in activated CD8(+) T cells indicates enhanced lung homing in patients with severe acute SARS-CoV-2 infection - Spoerl, Silvia; Kremer, Anita; Aigner, Michael; Eisenhauer, Nina; Koch, Pauline; Meretuk, Lina; Loeffler, Patrick; Tenbusch, Matthias; Maier, Clara; Überla, Klaus; Heinzerling, Lucie; Frey, Benjamin; et al. (European Journal of Immunology, 2021)
COVID-19 is a life-threatening disease leading to bilateral pneumonia and respiratory failure. The underlying reasons why a smaller percentage of patients present with severe pulmonary symptoms whereas the majority is only mildly affected are to date not well understood.
CRIS-Team WoS Importer:2021-05-07

Using multi-channel level sets to measure the cytoplasmic localization of HCMV pUL97 in GFP-B-gal fusion constructs - Held, Christian; Webel, Rike; Palmisano, Ralf; Hutterer, Corina; Marschall, Manfred; Wittenberg, Thomas (Journal of Virological Methods, 2014)
Human cytomegalovirus UL97-encoded protein kinase (pUL97) phosphorylates cellular and viral proteins and is critical for viral replication. To quantify the efficiency of nuclear translocation and to elucidate the role of putative nuclear localization signal (NLS) elements, immunofluorescence analysis of different pUL97 expression constructs was performed. Since manual quantitation of respective expression levels lacks objectivity and reproducibility, and is time-consuming as well, a computer-based model is established. This model enables objective quantitation of the degree of cytoplasmic localization ?. To determine the degree of cytoplasmic localization of different pUL97-GFP-?-gal fusion proteins automatically, a multi-channel segmentation of the nucleus and cytoplasm of transfected HeLa cells is performed in DAPI and GFP micrographs. A watershed transform-based segmentation scheme is used for the segmentation of the cell nuclei. Subsequently, the cytoplasm is segmented using a fast marching level set method. Based on the segmentation of cell nuclei and cytoplasm, ? can be determined for each HeLa cell by quantitation of the ratio of average signal intensity outside and inside the nucleus. The degree of cytoplasmic localization of an individual construct is then determined by evaluating the average and standard deviation of ? for the corresponding HeLa cells. Evaluation demonstrates that nuclear transport of pUL97 is a multilayered mechanism resulting in different efficiencies of nuclear translocation between a small and a large isoform and objective quantitation of the cytoplasmic localization is possible with a high accuracy (96.7% and 94.3%).
EVALuna2:8237

Using multimodal information for the segmentation of fluorescent micrographs with application to Virology and microbiology - Held, Christian; Wenzel, Jens; Webel, Rike; Marschall, Manfred; Palmisano, Ralf; Wittenberg, Thomas; et al. (Proc*s 2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society,EMBC,, 2011)
In order to improve reproducibility and objectivity of fluorescence microscopy based experiments and to enable the evaluation of large datasets, flexible segmentation methods are required which are able to adapt to different stainings and cell types. This adaption is usually achieved by the manual adjustment of the segmentation methods parameters, which is time consuming and challenging for biologists with no knowledge on image processing. To avoid this, parameters of the presented methods automatically adapt to user generated ground truth to determine the best method and the optimal parameter setup. These settings can then be used for segmentation of the remaining images. As robust segmentation methods form the core of such a system, the currently used watershed transform based segmentation routine is replaced by a fast marching level set based segmentation routine which incorporates knowledge on the cell nuclei. Our evaluations reveal that incorporation of multimodal information improves segmentation quality for the presented fluorescent datasets. © 2011 IEE
UnivIS-Import:2015-04-14:Pub.2011.med.IKMI.LHMMIPDR.usingm
Keywords: Fluorescence Microscopy; Digital Pathology; image analyis

Validation of a Parvovirus B19 NAT Assay for Screening of Umbilical Cord Blood for Allogenic Hematopoietic Stem Cell Donation - Steininger, Philipp; Korn, Klaus; Hackstein, Holger; Strasser, Erwin F. (Transfusion Medicine and Hemotherapy, 2023)
Introduction: Parvovirus B19 transmitted by umbilical cord blood (UCB) products may cause severe disease in allogenic hematopoietic stem cell transplant recipients. Thus, commercially available nucleic acid test (NAT) assays for highly sensitive detection of parvovirus B19 DNA validated for the specimen cord blood plasma (CBP) are required to avoid parvovirus B19 transmission by umbilical hematopoietic stem cell preparations. Methods: The multiplex cobas DPX NAT assay was validated for detection of parvovirus B19 DNA in CBP derived from citrate anticoagulated UCB units which have been processed by the Rubinstein method. In total, 363 retained CBP samples pretested negative for parvovirus B19 DNA were prepared for analyzing sensitivity, specificity, and interference of that NAT assay. The 3rd WHO International Standard for parvovirus B19 DNA was used for determining the 95% limit of detection (LOD95) by probit analysis. Results: The validation of the parvovirus B19 NAT assay for CBP demonstrated high sensitivity, specificity, intra- and inter-assay precision. Dilution series and replicate analyses showed a high linearity of the assay with a coefficient of determination above 0.99 and revealed a LOD95 of 17 International Units (IU)/mL (95% confidence interval, 14-44 IU/mL) for parvovirus B19 DNA in CBP samples. Conclusion: The validation of a commercially available parvovirus B19 NAT assay for the specimen CBP demonstrated a high assay performance fulfilling German guidelines and international regulations.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Allogenic hematopoietic stem cell donation; Nucleic acid test screening; Parvovirus B19; Umbilical cord blood

Validation of a SARS-CoV-2 RNA RT-PCR assay for high-throughput testing in blood of COVID-19 convalescent plasma donors and patients - Strasser, Erwin; Steininger, Philipp; Korn, Klaus; Achenbach, Susanne; Tenbusch, Matthias; Cunningham, Sarah; Zimmermann, Robert; Überla, Klaus; Hackstein, Holger (Transfusion, 2020)
Background The frequency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNAemia in blood donors is uncertain. Thus, assays for SARS-CoV-2 RNA detection in blood, validated on commercially available polymerase chain reaction (PCR) systems, are required to allow a good comparability of data.
CRIS-Team WoS Importer:2020-11-27

Validation of nuclear receptor RORγ isoform 1 as a novel host-directed antiviral target based on the modulation of cholesterol levels - Wangen, Christina; Raithel, Andrea; Tillmanns, Julia; Gege, Christian; Herrmann, Alexandra; Vitt, Daniel; Kohlhof, Hella; Marschall, Manfred; Hahn, Friedrich (Antiviral Research, 2024)
Currently, the clinically approved repertoire of antiviral drugs predominantly comprises direct-acting antivirals (DAAs). However, the use of DAAs is frequently limited by adverse effects, restriction to individual virus species, or the induction of viral drug resistance. These issues will likely be resolved by the introduction of host-directed antivirals (HDAs) targeting cellular proteins crucial for viral replication. However, experiences with the development of antiviral HDAs and clinical applications are still in their infancy. With the present study, we explored the human nuclear receptor and transcription factor RORγ isoform 1 (RORγ1), a member of the retinoic acid receptor-related orphan receptor (ROR) family, as a putative target of antiviral HDAs. To this end, cell culture models were used to investigate major viral human pathogens, i.e. the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), human cytomegalovirus (HCMV), varicella zoster virus (VZV) and human immunodeficiency virus 1 (HIV-1). Our results demonstrated (i) an antiviral activity of the clinically relevant RORγ modulators cedirogant and others, (ii) that isoform RORγ1 acts as the responsible determinant and drug target in the analyzed cell culture-based models, (iii) a selectivity of the antiviral effect for RORγ1 over related receptors RORα and RORβ, (iv) a late-phase inhibition exerted by cedirogant in HCMV replication and (v) a mechanistic link to the cellular cholesterol biosynthesis. Combined, the data highlight this novel RORγ-specific antiviral targeting concept and the developmental potential of RORγ-directed small molecules.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Host-directed antiviral targeting; Major viral human pathogens; Metabolic restriction of virus replication; Novel drug targeting options; RORγ2/t modulator cedirogant; Transcriptional regulation of cholesterol biosynthesis

Variability of high risk HPV genotypes among HIV infected women in Mwanza, Tanzania- the need for evaluation of current vaccine effectiveness in developing countries - Mujuni, Fridolin; Mirambo, Mariam M.; Rambau, Peter; Korn, Klaus; Mueller, Andreas; Matovelo, Dismas; Majigo, Mtebe; Kasang, Christa; Mshana, Stephen E. (Infectious Agents and Cancer, 2016)
BACKGROUND: High risk (HR) human papilloma Virus (HPV) genotypes have been associated with cervical cancer. In Tanzania there is a limited data on the epidemiology of HPV and genotypes distribution among HIV infected women. Here we document varieties of HPV genotypes associated with cervical squamous intraepithelial lesions (SIL) among HIV- infected women at Bugando Medical Centre, Mwanza-Tanzania. METHODS: A cross sectional hospital based study involving HIV infected women was conducted between August and October, 2014. Exfoliated cells from ectocervix and endocervix were collected using cytobrush. HPV genotypes were detected using polymerase chain reaction (PCR) followed by sequencing using specific primers targeting broad range of HPV types. Cytology was done to establish squamous intraepithelial lesions. Log binomial regression analysis was done to establish risk ratios (RR) associated with HPV infection using STATA version 11. RESULTS: A total of 255 HIV infected women with mean age 39.2 ± 9.1 years were enrolled in the study. HPV DNA was detected in 138/255 (54.1 %, 95 % CI: 47-60) of HIV infected women. Twenty six genotypes were detected in various combinations; of these 17(65.3 %) were of HR genotypes. HR genotypes were detected in 124(48.6 %) of HIV infected women. Common HR genotypes detected were HPV-52(26), HPV-58(21), HPV-35(20) and HPV-16(14). The risk of being HPV positive was significantly higher among women with CD4 counts <100 (RR: 1.20, 95 % CI: 1.05-1.35, P = 0.006) and women with SIL (RR: 1.37, 95 % CI: 1.11-1.68, P = 0.005). CONCLUSION: Significant proportion of HIV infected women with low CD4 counts have various grades of cervical SIL associated with varieties of uncommon HR genotypes. There is a need to evaluate the effectiveness of the current vaccine in preventing cervical cancer in developing countries where HIV is endemic.
EVALuna2:36317

Variant morphology and random chromosomal integration of BK polyomavirus in posttransplant urothelial carcinomas - Bertz, Simone; Enßer, Armin; Stöhr, Robert; Eckstein, Markus; Apel, Hendrik; Mayr, Doris; Büttner-Herold, Maike; Gaisa, Nadine Therese; Comperat, Eva; Wullich, Bernd; Hartmann, Arndt; Knöll, Antje (Modern Pathology, 2020)
BK polyomavirus (BKPyV) causes major complications in solid organ transplant recipients but little is known about its role in the development of urothelial carcinoma (UC) during immunosuppression. Immunohistochemistry (IHC) screening for polyomavirus large T antigen (LTag) was performed in 94 micropapillary UC (MPUC), 480 unselected UC, 199 muscle invasive UC (including 83 UC with variant differentiation), 76 cases of plasmocytoid, nested and large nested UC and 15 posttransplant UC. LTag expressing UC were reevaluated regarding their histomorphological features and characterized by IHC for p53 and HER2, chromogenic in situ hybridization for HER2 and SNaPshot analysis of the TERT promoter and HRAS. Real-time PCR and next generation sequencing (NGS) were performed to search for BKPyV-DNA and for variants in the tumor and viral genomes. We detected five LTag expressing UC which were diagnosed between 2 and 18 years after kidney (n = 4) or heart (n = 1) transplantation. 89 MPUC without history of organ transplantation and overall 755 UC (including cases with variant histology) were LTag negative. Of the five LTag expressing UC, three were MPUC, one showed extensive divergent differentiation with Mullerian type clear cell carcinoma, and one displayed focal villoglandular differentiation. All five tumors had aberrant nuclear p53 expression, 2/5 were HER2-amplified, and 3/5 had TERT promoter mutations. Within the 50 most common cancer related genes altered in UC we detected very few alterations and no TP53 mutations. BKPyV-DNA was present in 5/5 UC, chromosomal integration of the BKPyV genome was detectable in 4/5 UC. Two UC with BKPyV integration showed small deletions in the BKPyV noncoding control region (NCCR). The only UC without detectable BKPyV integration had a high viral load of human herpesvirus 6 (HHV-6). Our results suggest that LTag expression of integrated BKPyV genomes and resulting p53 inactivation lead to aggressive high-grade UC with unusual, often micropapillary morphology.
CRIS-Team WoS Importer:2020-02-28

Vector order determines protection against pathogenic simian immunodeficiency virus infection in a triple component vaccine by balancing CD4+and CD8+T-cell responses - Sauermann, Ulrike; Radaelli, Antonia; Stolte-Leeb, Nicole; Raue, Katharina; Bissa, Massimiliano; Zanotto, Carlo; Krawczak, Michael; Tenbusch, Matthias; Überla, Klaus; Keele, Brandon F.; Morghen, Carlo De Giuli; Sopper, Sieghart; et al. (Journal of Virology, 2017)
An effective AIDS vaccine should elicit strong humoral and cellular immune responses while maintaining low levels of CD4+T cell activation to avoid the generation of target cells for viral infection. The present study investigated two prime-boost regimens, both starting vaccination with single cycle immunodeficiency virus, followed by two mucosal boosts either with recombinant adenovirus (rAd) or fowlpox virus (rFWPV) expressing SIVmac239 or SIVmac251gag/polandenvgenes, respectively. Finally, vectors were switched and systemically administered to the reciprocal group of animals. Only mucosal rFWPV immunizations followed by systemic rAd boost significantly protected animals against a repeated low-dose, intrarectal challenge with pathogenic SIVmac251 resulting in a vaccine efficacy (i.e. risk reduction per exposure) of 68%. Delayed viral acquisition was associated with higher levels of activated CD8+T cells and Gag-specific IFN-γ secreting CD8+cells, low virus-specific CD4+T cell responses and low Env antibody titers. In contrast, the systemic rFWPV boost induced strong virus-specific CD4+T cell activity. rAd and rFWPV also induced differential patterns of the innate immune responses, thereby possibly shaping the specific immunity. PlasmaCXCL10levels after final immunization correlated directly with virus-specific CD4+T cell responses and inversely with the number of exposures to infection. Also, the percentage of activated CD69+CD8+T cells correlated with the number of exposures to infection. Differential stimulation of the immune response likely provided the basis for the diverging levels of protection afforded by this vaccine regimen.IMPORTANCEA failed phase II AIDS vaccine trial led to the hypothesis that CD4+T cell activation can abrogate any potentially protective effects delivered by vaccination or promote acquisition of the virus because CD4+T helper cells, required for an effective immune response, also represent the target cells for viral infection. We compared two vaccination protocols that elicited similar levels of Gag-specific immune responses in rhesus macaques. Only the animal group that had a low level of virus-specific CD4+T cells in combination with high levels of activated CD8+T cells was significantly protected from infection. Notably, protection was achieved despite the lack of appreciable Env-antibody titers. Moreover, we show that both, the vector and the route of immunization affected the level of CD4+T cell responses. Thus, mucosal immunization with FWPV-based vaccines should be considered as potent prime in prime-boost vaccination protocols.
EVALuna2:33748

Viral FGARAT Homolog ORF75 of Rhesus Monkey Rhadinovirus Effects Proteasomal Degradation of the ND10 Components SP100 and PML - Hahn, Alexander S.; Grosskopf, Anna K.; Jungnickl, Doris; Scholz, Brigitte; Enßer, Armin (Journal of Virology, 2016)
Nuclear domain 10 (ND10) components restrict herpesviral infection, and herpesviruses antagonize this restriction by a variety of strategies, including degradation or relocalization of ND10 proteins. The rhesus monkey rhadinovirus (RRV) shares many key biological features with the closely related Kaposi's sarcoma-associated herpesvirus (KSHV; human herpesvirus 8) and readily infects cells of both human and rhesus monkey origin. We used the clustered regularly interspaced short palindromic repeat-Cas9 (CRISPR-Cas9) technique to generate knockout (ko) cells for each of the four ND10 components, PML, SP100, DAXX, and ATRX. These ko cells were analyzed with regard to permissiveness for RRV infection. In addition, we analyzed the fate of the individual ND10 components in infected cells by immunofluorescence and Western blotting. Knockout of the ND10 component DAXX markedly increased RRV infection, while knockout of PML or SP100 had a less pronounced effect. In line with these observations, RRV infection resulted in rapid degradation of SP100, followed by degradation of PML and the loss of ND10 structures, whereas the protein levels of ATRX and DAXX remained constant. Notably, inhibition of the proteasome but not inhibition of de novo gene expression prevented the loss of SP100 and PML in cells that did not support lytic replication, compatible with proteasomal degradation of these ND10 components through the action of a viral tegument protein. Expression of the RRV FGARAT homolog ORF75 was sufficient to effect the loss of SP100 and PML in transfected or transduced cells, implicating ORF75 as the viral effector protein.Our findings highlight the antiviral role of ND10 and its individual components and further establish the viral FGARAT homologs of the gammaherpesviruses to be important viral effectors that counteract ND10-instituted intrinsic immunity. Surprisingly, even closely related viruses like KSHV and RRV evolved to use different strategies to evade ND10-mediated restriction. RRV first targets SP100 for degradation and then targets PML with a delayed kinetic, a strategy which clearly differs from that of other gammaherpesviruses. Despite efficient degradation of these two major ND10 components, RRV is still restricted by DAXX, another abundant ND10 component, as evidenced by a marked increase in RRV infection and replication upon knockout of DAXX. Taken together, our findings substantiate PML, SP100, and DAXX as key antiviral proteins, in that the first two are targeted for degradation by RRV and the last one still potently restricts replication of RRV.
EVALuna2:8329

Viral inhibitor of apoptosis vFLIP/K13 protects endothelial cells against superoxide-induced cell death - Thurau, Mathias; Marquardt, Gaby; Britzen-Laurent, Nathalie; Weinlaender, Kristina; Naschberger, Elisabeth; Jochmann, Ramona; Alkharsah, Khaled R.; Schulz, Thomas F.; Thome, Margot; Neipel, Frank; Stürzl, Michael (Journal of Virology, 2009)
Human herpesvirus 8 (HHV-8) is the etiological agent of Kaposi's sarcoma (KS). HHV-8 encodes an antiapoptotic viral Fas-associated death domain-like interleukin-1β-converting enzyme-inhibitory protein (vFLIP/K13). The antiapoptotic activity of vFLIP/K13 has been attributed to an inhibition of caspase 8 activation and more recently to its capability to induce the expression of antiapoptotic proteins via activation of NF-κB. Our study provides the first proteome-wide analysis of the effect of vFLIP/K13 on cellular-protein expression. Using comparative proteome analysis, we identified manganese superoxide dismutase (MnSOD), a mitochondrial antioxidant and an important antiapoptotic enzyme, as the protein most strongly upregulated by vFLIP/K13 in endothelial cells. MnSOD expression was also upregulated in endothelial cells upon infection with HHV-8. Microarray analysis confirmed that MnSOD is also upregulated at the RNA level, though the differential expression at the RNA level was much lower (5.6-fold) than at the protein level (25.1-fold). The induction of MnSOD expression was dependent on vFLIP/K13-mediated activation of NF-κB, occurred in a cell-intrinsic manner, and was correlated with decreased intracellular superoxide accumulation and increased resistance of endothelial cells to superoxide-induced death. The upregulation of MnSOD expression by vFLIP/K13 may support the survival of HHV-8-infected cells in the inflammatory microenvironment in KS. Copyright © 2009, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

Viral Mimicry of Interleukin-17A by SARS-CoV-2 ORF8 - Wu, Xin; Xia, Tian; Shin, Woo-Jin; Yu, Kwang-Min; Jung, Wooram; Herrmann, Alexandra; Foo, Suan-Sin; Chen, Weiqiang; Zhang, Pengfei; Lee, Jong-Soo; Poo, Haryoung; Comhair, Suzy A. A.; et al. (Mbio, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection triggers cytokine-mediated inflammation, leading to a myriad of clinical presentations in COVID-19. The SARS-CoV-2 open reading frame 8 (ORF8) is a secreted and rapidly evolving glycoprotein. Patients infected with SARS-CoV-2 variants with ORF8 deleted are associated with mild disease outcomes, but the molecular mechanism behind this is unknown. Here, we report that SARS-CoV-2 ORF8 is a viral cytokine that is similar to but distinct from interleukin 17A (IL-17A) as it induces stronger and broader human IL-17 receptor (hIL-17R) signaling than IL-17A. ORF8 primarily targeted blood monocytes and induced the heterodimerization of hIL-17RA and hIL- 17RC, triggering a robust inflammatory response. Transcriptome analysis revealed that besides its activation of the hIL-17R pathway, ORF8 upregulated gene expression for fibrosis signaling and coagulation dysregulation. A naturally occurring ORF8 L84S variant that was highly associated with mild COVID-19 showed reduced hIL- 17RA binding and attenuated inflammatory responses. This study reveals how SARSCoV- 2 ORF8 by a viral mimicry of the IL-17 cytokine contributes to COVID-19 severe inflammation.
CRIS-Team Scopus Importer:2022-05-13
Keywords: COVID-19; inflammation; viral IL-17

Virology, pathogenesis, epidemiology and clinical management of HTLV-1 infection. Proceedings of the 30th HTLV European research network (HERN 2023) - De Mendoza, Carmen; Taylor, Graham; Gessain, Antoine; Thoma-Kreß, Andrea; Bangham, Charles; Vesterbacka, Jan; Accolla, Roberto; Bazarbachi, Ali; Van Weyenbergh, Jan; Cook, Lucy; Casseb, Jorge; Ramos, Juan Carlos; et al. (NeuroImmune Pharmacology and Therapeutics, 2024)
The 30th workshop of the HTLV European Research Network (HERN) was held in Madrid on September 15-16, 2023. Over fifty researchers from Europe and America convened for a two-day conference to update and discuss basic science, epidemiology, clinical management and therapeutics for patients with HTLV-1 infection. Scientific topics addressed included new estimates for HTLV-1 in Europe; impact of antenatal screening on mother-to-child HTLV-1 infections; new insights into the molecular epidemiology of HTLV-1; reports of elite controllers for HTLV-1 infection; role of antiretrovirals as HTLV-1 pre-exposure prophylaxis; and prospects for a HTLV-1 vaccine. The group agreed to submit a formal request to WHO for increasing the global surveillance and awareness of HTLV-1. This viral infection is a potentially life-threatening, neglected condition with neither treatment nor vaccine. At this time, expanding HTLV-1 screening is the most effective way to reduce viral dissemination.
CRIS-Team Scopus Importer:2024-01-26
Keywords: HTLV-1; leukemia; myelopathy; pregnant women; screening; sexual transmission

Virusinfektionen in der Gynäkologie - Aktuelle Entwicklungen bei humanen Papillomviren und Herpesviren - Nagel, Angela; Knöll, Antje (gynäkologische praxis, 2020)
Human papillomavirus (HPV) and herpes simplex virus (HSV) infections are the most common sexually transmitted viral diseases. Prophylactic measures such as HPV vaccination and behavioural precautions for genital herpes are the most promising strategies to prevent these viral infections. The HPV vaccine is safe, immunogenic and effective in the prevention of HPV-associated tumors, but the vaccination rate is far too low in Germany. Cervical cancer is comparatively rare in Germany today and the incidence rate of new cases has been stagnating at a low level for years. Since a persistent hrHPV infection is necessary for the development of cervical cancer, the cervical cancer screening program was modified in January 2020. For women aged 35 years and older, an HPV cervical smear test is now performed in addition to cytology and the screening interval has been extended to three years. The test algorithm for younger women has not been changed. For genital HSV infections, aciclovir-based therapy regimens are recommended, prophylactic or therapeutic vaccines will not be available in the near future. Therefore, information of the patient about the specifics of the disease (such as the often asymptomatic virus shedding) and initiation of an appropriate therapy are decisive for the reduction of the HSV transmission risk and for the treatment success.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Cervical carcinoma screening; Genital infections; Herpes simplex virus; HPV vaccine; Human papillomavirus

Visible-Light-Driven C-H Oxidation of Cyclic Tertiary Amines: Access to Synthetic Strychnos Alkaloids with Antiviral Activity - Guryev, Anton; Hahn, Friedrich; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2019)
Air and visible light have been used in facile direct C-H oxidation of cyclic tertiary amines at ambient conditions, employing organic dyes as photocatalysts and LED. Tolerance of this new environmentally compatible protocol to various side-chain derivatizations of tryptoline and tetrahydroisoquinoline substrates was demonstrated. The developed method provides a straightforward and sustainable route towards delta-lactams, which feature strong antiviral properties (EC50 down to 4.6 +/- 1.8 mu m) against human cytomegalovirus (HCMV). The clear advantages, which are easily available and inexpensive reagents, organic dyes, visible light, air/O-2 and atom efficiency, make this system highly appealing for synthesis of versatile Strychnocarpine alkaloid derivatives with antiviral activity.
CRIS-Team WoS Importer:2019-04-04

Wedelolactone inhibits human cytomegalovirus replication by targeting distinct steps of the viral replication cycle - Svrlanska, Adriana; Ruhland, Anna; Marschall, Manfred; Reuter, Nina; Stamminger, Thomas (Antiviral Research, 2019)
Wedelolactone (WDL) is a coumestan present in the plants Eclipta prostrata and Wedelia calendulacea which are used for treatment of a multitude of health problems in traditional medicine. It has previously been shown that WDL exerts antiviral activity against human immunodeficiency virus and hepatitis C virus. In this study, we investigated the effect of WDL on lytic human cytomegalovirus (HCMV) infection. We demonstrate a strong interference with HCMV replication as analyzed in multi-round replication settings. A more detailed analysis of the underlying mechanisms revealed that WDL acts at two distinct steps of the viral replication cycle. During immediate early (IE) times, we observe an inhibition of IE1/IE2 expression. Although WDL was reported to interfere with NF-κB signaling our results suggest the existence of additional mechanisms that impede viral IE expression. During later time points of infection, WDL induced a disruption of the interaction between EZH2 and EED, components of the virus-supportive polycomb repressive complex 2 (PRC2). Thereby, the stability of the PRC2 complex as well as the related complex PRC1 was disturbed leading to diminished viral DNA synthesis. Taken together, we identify WDL as a potent agent against HCMV which interferes at two distinct steps of viral replication.
EVALuna2:210593

Wedelolactone inhibits human cytomegalovirus replication by targeting distinct steps of the viral replication cycle - Svrlanska, Adriana; Ruhland, Anna; Marschall, Manfred; Reuter, Nina; Stamminger, Thomas (Antiviral Research, 2020)
Wedelolactone (WDL) is a coumestan present in the plants Eclipta prostrata and Wedelia calendulacea which are used for treatment of a multitude of health problems in traditional medicine. It has previously been shown that WDL exerts antiviral activity against human immunodeficiency virus and hepatitis C virus. In this study, we investigated the effect of WDL on lytic human cytomegalovirus (HCMV) infection. We demonstrate a strong interference with HCMV replication as analyzed in multi-round replication settings. A more detailed analysis of the underlying mechanisms revealed that WDL acts at two distinct steps of the viral replication cycle. During immediate early (IE) times, we observe an inhibition of IE1/IE2 expression. Although WDL was reported to interfere with NF-κB signaling our results suggest the existence of additional mechanisms that impede viral IE expression. During later time points of infection, WDL induced a disruption of the interaction between EZH2 and EED, components of the virus-supportive polycomb repressive complex 2 (PRC2). Thereby, the stability of the PRC2 complex as well as the related complex PRC1 was disturbed leading to diminished viral DNA synthesis. Taken together, we identify WDL as a potent agent against HCMV which interferes at two distinct steps of viral replication.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Antiviral therapy; Human cytomegalovirus; NF-κB; Polycomb repressive complexes; Wedelolactone

XCR1 expression distinguishes human conventional dendritic cell type 1 with full effector functions from their immediate precursors - Heger, Lukas; Hatscher, Lukas; Liang, Chunguang; Lehmann, Christian; Amon, Lukas; Lühr, Jennifer J.; Kaszubowski, Tomasz; Nzirorera, Rayk; Schaft, Niels; Dörrie, Jan; Irrgang, Pascal; Tenbusch, Matthias; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Dendritic cells (DCs) are major regulators of innate and adaptive immune responses. DCs can be classified into plasmacytoid DCs and conventional DCs (cDCs) type 1 and 2. Murine and human cDC1 share the mRNA expression of XCR1. Murine studies indicated a specific role of the XCR1-XCL1 axis in the induction of immune responses. Here, we describe that human cDC1 can be distinguished into XCR1- and XCR1+ cDC1 in lymphoid as well as nonlymphoid tissues. Steady-state XCR1+ cDC1 display a preactivated phenotype compared to XCR1- cDC1. Upon stimulation, XCR1+ cDC1, but not XCR1- cDC1, secreted high levels of inflammatory cytokines as well as chemokines. This was associated with enhanced activation of NK cells mediated by XCR1+ cDC1. Moreover, XCR1+ cDC1 excelled in inhibiting replication of Influenza A virus. Further, under DC differentiation conditions, XCR1- cDC1 developed into XCR1+ cDC1. After acquisition of XCR1 expression, XCR1- cDC1 secreted comparable level of inflammatory cytokines. Thus, XCR1 is a marker of terminally differentiated cDC1 that licenses the antiviral effector functions of human cDC1, while XCR1- cDC1 seem to represent a late immediate precursor of cDC1.
CRIS-Team Scopus Importer:2023-08-25
Keywords: antiviral immunity; cDC1; DC differentiation; IL-12; XCR1

Young human alpha synuclein transgenic (BAC-SNCA) mice display sex- and gene-dose-dependent phenotypic disturbances - Moceri, Sandra; Bäuerle, Natascha; Habermeyer, Johanna; Ratz-Wirsching, Veronika; Harrer, Julia; Distler, Jörg; Schulze-Krebs, Anja; Timotius, Ivanna K.; Bluhm, Alexandra; Hartlage-Rübsamen, Maike; Roßner, Steffen; Winkler, Jürgen; et al. (Behavioural Brain Research, 2024)
Parkinson's disease (PD) is a common neurodegenerative movement disorder, characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta and the accumulation of aggregated alpha synuclein (aSyn). The disease often presents with early prodromal non-motor symptoms and later motor symptoms. Diagnosing PD based purely on motor symptoms is often too late for successful intervention, as a significant neuronal loss has already occurred. Furthermore, the lower prevalence of PD in females is not well understood, highlighting the need for a better understanding of the interaction between sex and aSyn, the crucial protein for PD pathogenesis. Here, we conducted a comprehensive phenotyping study in 1- to 5-month-old mice overexpressing human aSyn gene (SNCA) in a bacterial artificial chromosome (BAC-SNCA). We demonstrate a SNCA gene-dose-dependent increase of human aSyn and phosphorylated aSyn, as well as a decrease in tyrosine hydroxylase expression in BAC-SNCA mice, with more pronounced effects in male mice. Phosphorylated aSyn was already found in the dorsal motor nucleus of the vagus nerve of 2-month-old mice. This was time-wise associated with significant gait altrations in BAC-SNCA mice as early as 1 and 3 months of age using CatWalk gait analysis. Furthermore, anxiety-related behavioral tests revealed an increase in anxiety levels in male BAC-SNCA mice. Finally, 5-month-old male BAC-SNCA mice exhibited a SNCA gene-dose-dependent elevation in energy expenditure in automated home-cage monitoring. For the first time, these findings describe early-onset, sex- and gene-dose-dependent, aSyn-mediated disturbances in BAC-SNCA mice, providing a model for sex-differences, early-onset neuropathology, and prodromal symptoms of PD.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Alpha synuclein; Behavioral phenotyping; Gait analysis; Parkinson's disease; Sex difference; SNCA gene-dose

Adult and cord blood-derived high-affinity gB-CAR-T cells effectively react against human cytomegalovirus infections - Olbrich, Henning; Theobald, Sebastian J.; Slabik, Constanze; Gerasch, Laura; Schneider, Andreas; Mach, Michael; Shum, Thomas; Mamonkin, Maksim; Stripecke, Renata (Human Gene Therapy, 2020)
Human cytomegalovirus (HCMV) reactivations are associated with lower overall survival after transplantations. Adoptive transfer of HCMV-reactive expanded or selected T cells can be applied as a compassionate use, but requires that the human leukocyte antigen-matched donor provides memory cells against HCMV. To overcome this, we developed engineered T cells expressing chimeric antigen receptors (CARs) targeted against the HCMV glycoprotein B (gB) expressed upon viral reactivation. Single-chain variable fragments (scFvs) derived from a human high-affinity gB-specific neutralizing monoclonal antibody (SM5-1) were fused to CARs with 4-1BB (BBL) or CD28 (28S) costimulatory domains and subcloned into retroviral vectors. CD4+ and CD8+ T cells obtained from HCMV-seronegative adult blood or cord blood (CB) transduced with the vectors efficiently expressed the gB-CARs. The specificity and potency of gB-CAR-T cells were demonstrated and compared in vitro using the following: 293T cells expressing gB, and with mesenchymal stem cells infected with a HCMV TB40 strain expressing Gaussia luciferase (HCMV/GLuc). BBL-gB-CAR-T cells generated with adult or CB demonstrated significantly higher in vitro activation and cytotoxicity performance than 28-gB-CAR-T cells. Nod.Rag.Gamma (NRG) mice transplanted with human CB CD34+ cells with long-term human immune reconstitution were used to model HCMV/GLuc infection in vivo by optical imaging analyses. One week after administration, response to BBL-gB-CAR-T cell therapy was observed for 5/8 mice, defined by significant reduction of the bioluminescent signal in relation to untreated controls. Response to therapy was sporadically associated with CAR detection in spleen. Thus, exploring scFv derived from the high-affinity gB-antibody SM5-1 and the 4-1BB signaling domain for CAR design enabled an in vitro high on-target effect and cytotoxicity and encouraging results in vivo. Therefore, gB-CAR-T cells can be a future clinical option for treatment of HCMV reactivations, particularly when memory T cells from the donors are not available.
CRIS-Team Scopus Importer:2020-05-02
Keywords: CAR-T cells; HCMV; humanized mice; PD-1; transplantation

Association of Kaposi's Sarcoma-Associated Herpesvirus ORF31 with ORF34 and ORF24 Is Critical for Late Gene Expression - Brulois, Kevin; Wong, Lai-Yee; Lee, Hye-Ra; Sivadas, Priyanka; Enßer, Armin; Feng, Pinghui; Gao, Shou-Jiang; Toth, Zsolt; Jung, Jae U. (Journal of Virology, 2015)
Transcription of herpesvirus late genes depends on several virus-encoded proteins whose function is not completely understood. Here, we identify a viral trimeric complex of Kaposi's sarcoma-associated herpesvirus (KSHV) open reading frame 31 (ORF31), ORF24, and ORF34 that is required for late gene expression but not viral DNA replication. We found that (i) ORF34 bridges the interaction between ORF31 and ORF24, (ii) the amino-terminal cysteine-rich and carboxyl-terminal basic domains of ORF31 mediate the ORF31-ORF34 interaction required for late gene expression, and (iii) a complex consisting of ORF24, ORF31, and ORF34 specifically binds to the K8.1 late promoter. Together, our results support the model that a subset of lytic viral proteins assembles into a transcriptional activator complex to induce expression of late genes.
EVALuna2:8281

EBV Negative Lymphoma and Autoimmune Lymphoproliferative Syndrome Like Phenotype Extend the Clinical Spectrum of Primary Immunodeficiency Caused by STK4 Deficiency - Schipp, Cyrill; Schluetermann, David; Hoenscheid, Andrea; Nabhani, Schafiq; Hoell, Jessica; Oommen, Prasad T.; Ginzel, Sebastian; Fleckenstein, Bernhard; Stork, Bjorn; Borkhardt, Arndt; Stepensky, Polina; Fischer, Ute (Frontiers in Immunology, 2018)
Serine/threonine kinase 4 (STK4) deficiency is an autosomal recessive genetic condition that leads to primary immunodeficiency (PID) typically characterized by lymphopenia, recurrent infections and Epstein Barr Virus (EBV) induced lymphoproliferation and-lymphoma. State-of-the-art treatment regimens consist of prevention or treatment of infections, immunoglobulin substitution (IVIG) and restoration of the immune system by hematopoietic stem cell transplantation. Here, we report on two patients from two consanguineous families of Turkish (patient P1) and Moroccan (patient P2) decent, with PID due to homozygous STK4 mutations. P1 harbored a previously reported frameshift (c.1103 deli, p.M368RfsX2) and P2 a novel splice donor site mutation (P2; c.525+2 T > G). Both patients presented in childhood with recurrent infections, CD4 lymphopenia and dysregulated immunoglobulin levels. Patient P1 developed a highly malignant B cell lymphoma at the age of 10 years and a second, independent Hodgkin lymphoma 5 years later. To our knowledge she is the first STK4 deficient case reported who developed lymphoma in the absence of detectable EBV or other common viruses. Lymphoma development may be due to the lacking tumor suppressive function of STK4 or the perturbed immune surveillance due to the lack of CD4+ T cells. Our data should raise physicians' awareness of (1) lymphoma proneness of STK4 deficient patients even in the absence of EBV infection and (2) possibly underlying STK4 deficiency in pediatric patients with a history of recurrent infections, CD4 lymphopenia and lymphoma and unknown genetic make-up. Patient P2 experienced recurrent otitis in childhood, but when she presented at the age of 14, she showed clinical and immunological characteristics similar to patients suffering from Autoimmune Lymphoproliferative Syndrome (ALPS): elevated DNT cell number, non-malignant lymphadenopathy and hepatosplenomegaly, hematolytic anemia, hypergammaglobulinemia. Also patient P1 presented with ALPS-like features (lymphadenopathy, elevated DNT cell number and increased Vitamin B12 levels) and both were initially clinically diagnosed as ALPS-like. Closer examination of P2, however, revealed active EBV infection and genetic testing identified a novel STK4 mutation. None of the patients harbored typically ALPS-associated mutations of the Fas receptor mediated apoptotic pathway and Fas-mediated apoptosis was not affected. The presented case reports extend the clinical spectrum of STK4 deficiency.
EVALuna2:35264

Human cytomegalovirus glycoprotein complex gH/gL/gO uses PDGFR-α as a key for entry - Wu, Yiquan; Prager, Adrian; Boos, Simone; Resch, Moritz; Brizic, Ilija; Mach, Michael; Wildner, Sabrina; Scrivano, Laura; Adler, Barbara (PLoS Pathogens, 2017)
Herpesvirus gH/gL envelope glycoprotein complexes are key players in virus entry as ligands for host cell receptors and by promoting fusion of viral envelopes with cellular membranes. Human cytomegalovirus (HCMV) has two alternative gH/gL complexes, gH/gL/gO and gH/gL/UL128,130,131A which both shape the HCMV tropism. By studying binding of HCMV particles to fibroblasts, we could for the first time show that virion gH/gL/gO binds to platelet-derived growth factor-α (PDGFR-α) on the surface of fibroblasts and that gH/gL/gO either directly or indirectly recruits gB to this complex. PDGFR-α functions as an entry receptor for HCMV expressing gH/gL/gO, but not for HCMV mutants lacking the gH/gL/gO complex. PDGFR-α-dependent entry is not dependent on activation of PDGFR-α. We could also show that the gH/gL/gO-PDGFR-α interaction starts the predominant entry pathway for infection of fibroblasts with free virus. Cell-associated virus spread is either driven by gH/gL/gO interacting with PDGFR-α or by the gH/gL/UL128,130,131A complex. PDGFR-α-positive cells may thus be preferred first target cells for infections with free virus which might have implications for the design of future HCMV vaccines or anti-HCMV drugs.
EVALuna2:33768

Limited Effector Memory B-Cell Response to Envelope Glycoprotein B During Primary Human Cytomegalovirus Infection - Dauby, Nicolas; Sartori, Delphine; Kummert, Caroline; Lecomte, Sandra; Haelterman, Edwige; Delforge, Marie-Luce; Donner, Catherine; Mach, Michael; Marchant, Arnaud (Journal of Infectious Diseases, 2016)
Following primary human cytomegalovirus (HCMV) infection, the production of antibodies against envelope glycoprotein B (gB) is delayed, compared with production of antibodies against tegument proteins, and this likely reduces the control of HCMV dissemination.The frequency and the phenotype of gB-specific and tegument protein-specific B cells were studied in a cohort of pregnant women with primary HCMV infection. Healthy adults who had chronic HCMV infection or were recently immunized with tetanus toxoid (TT) were included as controls.Primary HCMV infection was associated with high and similar frequencies of gB-specific and tegument protein-specific B cells following primary HCMV infection. During primary infection, tegument protein-specific B cells expressed an activated (CD21(low)) memory B-cell (MBC) phenotype. Activated MBCs were also induced by TT booster immunization, indicating that the expansion of this subset is part of the physiological B-cell response to protein antigens. In contrast, gB-specific B cells had a predominant classical (CD21(+)) MBC phenotype during both primary and chronic infections.The delayed production of gB-specific immunoglobulin G (IgG) during primary HCMV infection is associated with a limited induction of MBCs with effector potential. This novel mechanism by which HCMV may interfere with the production of neutralizing antibodies could represent a target for therapeutic immunization.
EVALuna2:8314

Luciferase-tagged wild-type and tropism-deficient mouse cytomegaloviruses reveal early dynamics of host colonization following peripheral challenge - Farrell, Helen; Oliveira, Martha; Macdonald, Kate; Yunis, Joseph; Mach, Michael; Bruce, Kimberley; Stevenson, Philip; Cardin, Rhonda; Davis-Poynter, Nicholas (Journal of General Virology, 2016)
Cytomegaloviruses (CMVs) establish persistent, systemic infections and cause disease by maternal-foetal transfer, suggesting that their dissemination is a key target for antiviral intervention. Late clinical presentation has meant that human CMV (HCMV) dissemination is not well understood. Murine CMV (MCMV) provides a tractable model. Whole mouse imaging of virus-expressed luciferase has proved a useful way to track systemic infections. MCMV, in which the abundant lytic gene M78 was luciferase-tagged via a self-cleaving peptide (M78-LUC), allowed serial, unbiased imaging of systemic and peripheral infection without significant virus attenuation. Ex vivo luciferase imaging showed greater sensitivity than plaque assay, and revealed both well-known infection sites (the lungs, lymph nodes, salivary glands, liver, spleen and pancreas) and less explored sites (the bone marrow and upper respiratory tract). We applied luciferase imaging to tracking MCMV lacking M33, a chemokine receptor conserved in HCMV and a proposed anti-viral drug target. M33-deficient M78-LUC colonized normally in peripheral sites and local draining lymph nodes but spread poorly to the salivary gland, suggesting a defect in vascular transport consistent with properties of a chemokine receptor.
EVALuna2:8326

Murine Cytomegalovirus Exploits Olfaction To Enter New Hosts - Farrell, Helen E.; Lawler, Clara; Tan, Cindy S. E.; Macdonald, Kate; Bruce, Kimberley; Mach, Michael; Davis-Poynter, Nick; Stevenson, Philip G. (Mbio, 2016)
Viruses transmit via the environmental and social interactions of their hosts. Herpesviruses have colonized mammals since their earliest origins, suggesting that they exploit ancient, common pathways. Cytomegaloviruses (CMVs) are assumed to enter new hosts orally, but no site has been identified. We show by live imaging that murine CMV (MCMV) infects nasally rather than orally, both after experimental virus uptake and during natural transmission. Replication-deficient virions revealed the primary target as olfactory neurons. Local, nasal replication by wild-type MCMV was not extensive, but there was rapid systemic spread, associated with macrophage infection. A long-term, transmissible infection was then maintained in the salivary glands. The viral m131/m129 chemokine homolog, which influences tropism, promoted salivary gland colonization after nasal entry but was not required for entry per se The capacity of MCMV to transmit via olfaction, together with previous demonstrations of experimental olfactory infection by murid herpesvirus 4 (MuHV-4) and herpes simplex virus 1 (HSV-1), suggest that this is a common, conserved route of mammalian herpesvirus entry.Cytomegaloviruses (CMVs) infect most mammals. Human CMV (HCMV) harms people with poor immune function and can damage the unborn fetus. It infects approximately 1% of live births. We lack a good vaccine. One problem is that how CMVs first enter new hosts remains unclear. Oral entry is often assumed, but the evidence is indirect, and no infection site is known. The difficulty of analyzing HCMV makes related animal viruses an important source of insights. Murine CMV (MCMV) infected not orally but nasally. Specifically, it targeted olfactory neurons. Viral transmission was also a nasal infection. Like HCMV, MCMV infected cells by binding to heparan, and olfactory surfaces display heparan to incoming viruses, whereas most other mucosal surfaces do not. These data establish a new understanding of CMV infections and a basis for infection control.
EVALuna2:8317

Repertoire characterization and validation of gB-specific human IgGs directly cloned from humanized mice vaccinated with dendritic cells and protected against HCMV - Theobald, Sebastian J.; Kreer, Christoph; Khailaie, Sahamoddin; Bonifacius, Agnes; Eiz-Vesper, Britta; Figueiredo, Constanca; Mach, Michael; Backovic, Marija; Ballmaier, Matthias; Koenig, Johannes; Olbrich, Henning; Schneider, Andreas; et al. (PLoS Pathogens, 2020)
Human cytomegalovirus (HCMV) causes serious complications to immune compromised hosts. Dendritic cells (iDCgB) expressing granulocyte-macrophage colony-stimulating factor, interferon-alpha and HCMV-gB were developed to promote de novo antiviral adaptive responses. Mice reconstituted with a human immune system (HIS) were immunized with iDCgB and challenged with HCMV, resulting into 93% protection. Immunization stimulated the expansion of functional effector memory CD8+ and CD4+ T cells recognizing gB. Machine learning analyses confirmed bone marrow T/CD4+, liver B/IgA+ and spleen B/IgG+ cells as predictive biomarkers of immunization (≈87% accuracy). CD8+ and CD4+ T cell responses against gB were validated. Splenic gB-binding IgM-/IgG+ B cells were sorted and analyzed at a single cell level. iDCgB immunizations elicited human-like IgG responses with a broad usage of various IgG heavy chain V gene segments harboring variable levels of somatic hypermutation. From this search, two gB-binding human monoclonal IgGs were generated that neutralized HCMV infection in vitro. Passive immunization with these antibodies provided proof-of-concept evidence of protection against HCMV infection. This HIS/HCMV in vivo model system supported the validation of novel active and passive immune therapies for future clinical translation.
CRIS-Team Scopus Importer:2020-07-31

Signatures of T and B Cell Development, Functional Responses and PD-1 Upregulation After HCMV Latent Infections and Reactivations in Nod. Rag. Gamma Mice Humanized With Cord Blood CD34(+) Cells - Theobald, Sebastian J.; Khailaie, Sahamoddin; Meyer-Hermann, Michael; Volk, Valery; Olbrich, Henning; Danisch, Simon; Gerasch, Laura; Schneider, Andreas; Sinzger, Christian; Schaudien, Dirk; Lienenklaus, Stefan; Riese, Peggy; et al. (Frontiers in Immunology, 2018)
Human cytomegalovirus (HCMV) latency is typically harmless but reactivation can be largely detrimental to immune compromised hosts. We modeled latency and reactivation using a traceable HCMV laboratory strain expressing the Gaussia luciferase reporter gene (HCMV/GLuc) in order to interrogate the viral modulatory effects on the human adaptive immunity. Humanized mice with long-term (more than 17 weeks) steady human T and B cell immune reconstitutions were infected with HCMV/GLuc and 7 weeks later were further treated with granulocyte-colony stimulating factor (G-CSF) to induce viral reactivations. Whole body bio-luminescence imaging analyses clearly differentiated mice with latent viral infections vs. reactivations. Foci of vigorous viral reactivations were detectable in liver, lymph nodes and salivary glands. The number of viral genome copies in various tissues increased upon reactivations and were detectable in sorted human CD14(+), CD169(+), and CD34(+) cells. Compared with non-infected controls, mice after infections and reactivations showed higher thymopoiesis, systemic expansion of Th, CTL, Treg, and Tfh cells and functional antiviral T cell responses. Latent infections promoted vast development of memory CD4(+) T cells while reactivations triggered a shift toward effector T cells expressing PD-1. Further, reactivations prompted a marked development of B cells, maturation of IgG(+) plasma cells, and HCMV-specific antibody responses. Multivariate statistical methods were employed using T and B cell immune phenotypic profiles obtained with cells from several tissues of individual mice. The data was used to identify combinations of markers that could predict an HCMV infection vs. reactivation status. In spleen, but not in lymph nodes, higher frequencies of effector CD4(+) T cells expressing PD-1 were among the factors most suited to distinguish HCMV reactivations from infections. These results suggest a shift from a T cell dominated immune response during latent infections toward an exhausted T cell phenotype and active humoral immune response upon reactivations. In sum, this novel in vivo humanized model combined with advanced analyses highlights a dynamic system clearly specifying the immunological spatial signatures of HCMV latency and reactivations. These signatures can be merged as predictive biomarker clusters that can be applied in the clinical translation of new therapies for the control of HCMV reactivation.
EVALuna2:35261

Transduction of Herpesvirus saimiri-Transformed T Cells with Exogenous Genes of Interest - Martínez-Barricarte, Rubén; De Jong, Sarah Jill; Markle, Janet; De Paus, Roel; Boisson-Dupuis, Stephanie; Bustamante, Jacinta; Van de Vosse, Esther; Fleckenstein, Bernhard; Casanova, Jean Laurent (Current Protocols in Immunology, 2016)
Human T cells can be transformed and expanded with herpesvirus saimiri (HVS). HVS-transformed T cells from patients have facilitated the study of a broad range of primary immunodeficiencies (PID) in which T-cell development or function is altered. However, the utility of HVS-transformed T cells for genetic studies has been limited by technical challenges in the expression of exogenous genes, including wild-type or mutant alleles. A novel, gamma retrovirus-based method for the simple and reliable transduction, purification, and study of HVS-transformed T cells is described. © 2016 by John Wiley & Sons, Inc.
EVALuna2:35292

Translocated microbiome composition determines immunological outcome in treated HIV infection - Nganou-Makamdop, Krystelle; Talla, Aarthi; Sharma, Ashish Arunkumar; Darko, Sam; Ransier, Amy; Laboune, Farida; Chipman, Jeffrey G.; Beilman, Gregory J.; Hoskuldsson, Torfi; Fourati, Slim; Schmidt, Thomas E.; Arumugam, Sahaana; et al. (Cell, 2021)
The impact of the microbiome on HIV disease is widely acknowledged although the mechanisms downstream of fluctuations in microbial composition remain speculative. We detected rapid, dynamic changes in translocated microbial constituents during two years after cART initiation. An unbiased systems biology approach revealed two distinct pathways driven by changes in the abundance ratio of Serratia to other bacterial genera. Increased CD4 T cell numbers over the first year were associated with high Serratia abundance, pro-inflammatory innate cytokines, and metabolites that drive Th17 gene expression signatures and restoration of mucosal integrity. Subsequently, decreased Serratia abundance and downregulation of innate cytokines allowed re-establishment of systemic T cell homeostasis promoting restoration of Th1 and Th2 gene expression signatures. Analyses of three other geographically distinct cohorts of treated HIV infection established a more generalized principle that changes in diversity and composition of translocated microbial species influence systemic inflammation and consequently CD4 T cell recovery.
CRIS-Team Scopus Importer:2021-07-30
Keywords: antiretroviral therapy; HIV; inflammation; microbiome; systems biology

ZNF341 controls STAT3 expression and thereby immunocompetence - Frey-Jakobs, Stefanie; Hartberger, Julia M.; Fliegauf, Manfred; Bossen, Claudia; Wehmeyer, Magdalena L.; Neubauer, Johanna C.; Bulashevska, Alla; Proietti, Michele; Froebel, Philipp; Noeltner, Christina; Yang, Linlin; Rojas-Restrepo, Jessica; et al. (Science immunology, 2018)
Signal transducer and activator of transcription 3 (STAT3) is a central regulator of immune homeostasis. STAT3 levels are strictly controlled, and STAT3 impairment contributes to several diseases including the monogenic autosomal-dominant hyper-immunoglobulin E (IgE) syndrome (AD-HIES). We investigated patients of four consanguineous families with an autosomal-recessive disorder resembling the phenotype of AD-HIES, with symptoms of immuno-deficiency, recurrent infections, skeletal abnormalities, and elevated IgE. Patients presented with reduced STAT3 expression and diminished T helper 17 cell numbers, in absence of STAT3 mutations. We identified two distinct homozygous nonsense mutations in ZNF341, which encodes a zinc finger transcription factor. Wild-type ZNF341 bound to and activated the STAT3 promoter, whereas the mutant variants showed impaired transcriptional activation, partly due to nuclear translocation failure. In summary, nonsense mutations in ZNF341 account for the STAT3-like phenotype in four autosomal-recessive kindreds. Thus, ZNF341 is a previously unrecognized regulator of immune homeostasis.
EVALuna2:35277